Bi-allelic variants in CELSR3 are implicated in central nervous system and urinary tract anomalies. - Stegmann, Jil D; Kalanithy, Jeshurun C; Dworschak, Gabriel C; Ishorst, Nina; Mingardo, Enrico; Lopes, Filipa M; Ho, Yee Mang; Grote, Phillip; Lindenberg, Tobias T; Yilmaz, Öznur; Channab, Khadija; Seltzsam, Steve; et al. (NPJ Genom Med, 2024)
CELSR3 codes for a planar cell polarity protein. We describe twelve affected individuals from eleven independent families with bi-allelic variants in CELSR3. Affected individuals presented with an overlapping phenotypic spectrum comprising central nervous system (CNS) anomalies (7/12), combined CNS anomalies and congenital anomalies of the kidneys and urinary tract (CAKUT) (3/12) and CAKUT only (2/12). Computational simulation of the 3D protein structure suggests the position of the identified variants to be implicated in penetrance and phenotype expression. CELSR3 immunolocalization in human embryonic urinary tract and transient suppression and rescue experiments of Celsr3 in fluorescent zebrafish reporter lines further support an embryonic role of CELSR3 in CNS and urinary tract formation.

Biallelic variation in the choline and ethanolamine transporter FLVCR1 underlies a pleiotropic disease spectrum from adult neurodegeneration to severe developmental disorders - Calame, Daniel G; Wong, Jovi Huixin; Panda, Puravi; Nguyen, Dat Tuan; Leong, Nancy C P; Sangermano, Riccardo; Patankar, Sohil G; Abdel-Hamid, Mohamed; Alabdi, Lama; Safwat, Sylvia; Flannery, Kyle P; Dardas, Zain; et al. (medRxiv, 2024)
FLVCR1 encodes Feline leukemia virus subgroup C receptor 1 (FLVCR1), a solute carrier (SLC) transporter within the Major Facilitator Superfamily. FLVCR1 is a widely expressed transmembrane protein with plasma membrane and mitochondrial isoforms implicated in heme, choline, and ethanolamine transport. While Flvcr1 knockout mice die in utero with skeletal malformations and defective erythropoiesis reminiscent of Diamond-Blackfan anemia, rare biallelic pathogenic FLVCR1 variants are linked to childhood or adult-onset neurodegeneration of the retina, spinal cord, and peripheral nervous system. We ascertained from research and clinical exome sequencing 27 individuals from 20 unrelated families with biallelic ultra-rare missense and predicted loss-of-function (pLoF) FLVCR1 variant alleles. We characterize an expansive FLVCR1 phenotypic spectrum ranging from adult-onset retinitis pigmentosa to severe developmental disorders with microcephaly, reduced brain volume, epilepsy, spasticity, and premature death. The most severely affected individuals, including three individuals with homozygous pLoF variants, share traits with Flvcr1 knockout mice and Diamond-Blackfan anemia including macrocytic anemia and congenital skeletal malformations. Pathogenic FLVCR1 missense variants primarily lie within transmembrane domains and reduce choline and ethanolamine transport activity compared with wild-type FLVCR1 with minimal impact on FLVCR1 stability or subcellular localization. Several variants disrupt splicing in a mini-gene assay which may contribute to genotype-phenotype correlations. Taken together, these data support an allele-specific gene dosage model in which phenotypic severity reflects residual FLVCR1 activity. This study expands our understanding of Mendelian disorders of choline and ethanolamine transport and demonstrates the importance of choline and ethanolamine in neurodevelopment and neuronal homeostasis.

Characterization and visualization of tandem repeats at genome scale. - Dolzhenko, Egor; English, Adam; Dashnow, Harriet; De Sena Brandine, Guilherme; Mokveld, Tom; Rowell, William J; Karniski, Caitlin; Kronenberg, Zev; Danzi, Matt C; Cheung, Warren A; Bi, Chengpeng; Farrow, Emily; et al. (Nat Biotechnol, 2024)
Tandem repeat (TR) variation is associated with gene expression changes and numerous rare monogenic diseases. Although long-read sequencing provides accurate full-length sequences and methylation of TRs, there is still a need for computational methods to profile TRs across the genome. Here we introduce the Tandem Repeat Genotyping Tool (TRGT) and an accompanying TR database. TRGT determines the consensus sequences and methylation levels of specified TRs from PacBio HiFi sequencing data. It also reports reads that support each repeat allele. These reads can be subsequently visualized with a companion TR visualization tool. Assessing 937,122 TRs, TRGT showed a Mendelian concordance of 98.38%, allowing a single repeat unit difference. In six samples with known repeat expansions, TRGT detected all expansions while also identifying methylation signals and mosaicism and providing finer repeat length resolution than existing methods. Additionally, we released a database with allele sequences and methylation levels for 937,122 TRs across 100 genomes.

The frequency of pathogenic variation in the All of Us cohort reveals ancestry-driven disparities. - Eric Venner; Patterson, Karynne; Kalra, Divya; Wheeler, Marsha M; Chen, Yi-Ju; Sara E Kalla; Bo Yuan; Karnes, Jason H; Kimberly Walker; Smith, Joshua D; McGee, Sean; Radhakrishnan, Aparna; et al. (Commun Biol, 2024)
Disparities in data underlying clinical genomic interpretation is an acknowledged problem, but there is a paucity of data demonstrating it. The All of Us Research Program is collecting data including whole-genome sequences, health records, and surveys for at least a million participants with diverse ancestry and access to healthcare, representing one of the largest biomedical research repositories of its kind. Here, we examine pathogenic and likely pathogenic variants that were identified in the All of Us cohort. The European ancestry subgroup showed the highest overall rate of pathogenic variation, with 2.26% of participants having a pathogenic variant. Other ancestry groups had lower rates of pathogenic variation, including 1.62% for the African ancestry group and 1.32% in the Latino/Admixed American ancestry group. Pathogenic variants were most frequently observed in genes related to Breast/Ovarian Cancer or Hypercholesterolemia. Variant frequencies in many genes were consistent with the data from the public gnomAD database, with some notable exceptions resolved using gnomAD subsets. Differences in pathogenic variant frequency observed between ancestral groups generally indicate biases of ascertainment of knowledge about those variants, but some deviations may be indicative of differences in disease prevalence. This work will allow targeted precision medicine efforts at revealed disparities.
Keywords: African People; Black People; European People; Genetic Predisposition to Disease; Genomics; Hispanic or Latino; Humans; Population Health; United States

Genetic sex validation for sample tracking in next-generation sequencing clinical testing. - Hu, Jianhong; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (BMC Res Notes, 2024)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors (49.09%), samples from transgender participants (3.64%) and stem cell or bone marrow transplant patients (7.27%) along with undetermined sample mix-ups (40%) for which sample swaps occurred prior to arrival at genome centers, however the exact cause of the events at the sampling sites resulting in the mix-ups were not able to be determined.
Keywords: Bone Marrow Transplantation; Clinical Laboratory Services; Genotype; High-Throughput Nucleotide Sequencing; Humans; Laboratories

Identification of constrained sequence elements across 239 primate genomes. - Kuderna, Lukas F K; Ulirsch, Jacob C; Rashid, Sabrina; Ameen, Mohamed; Sundaram, Laksshman; Hickey, Glenn; Cox, Anthony J; Gao, Hong; Kumar, Arvind; Aguet, Francois; Christmas, Matthew J; Clawson, Hiram; et al. (Nature, 2024)
Noncoding DNA is central to our understanding of human gene regulation and complex diseases, and measuring the evolutionary sequence constraint can establish the functional relevance of putative regulatory elements in the human genome. Identifying the genomic elements that have become constrained specifically in primates has been hampered by the faster evolution of noncoding DNA compared to protein-coding DNA, the relatively short timescales separating primate species, and the previously limited availability of whole-genome sequences. Here we construct a whole-genome alignment of 239 species, representing nearly half of all extant species in the primate order. Using this resource, we identified human regulatory elements that are under selective constraint across primates and other mammals at a 5% false discovery rate. We detected 111,318 DNase I hypersensitivity sites and 267,410 transcription factor binding sites that are constrained specifically in primates but not across other placental mammals and validate their cis-regulatory effects on gene expression. These regulatory elements are enriched for human genetic variants that affect gene expression and complex traits and diseases. Our results highlight the important role of recent evolution in regulatory sequence elements differentiating primates, including humans, from other placental mammals.
Keywords: Animals; Conserved Sequence; Deoxyribonuclease I; DNA; Evolution, Molecular; Female; Gene Expression Regulation; Genome; Humans; Mammals; Placenta; Pregnancy; Primates; Proteins; Regulatory Sequences, Nucleic Acid; Reproducibility of Results; Transcription Factors

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

Variants in ZFX are associated with an X-linked neurodevelopmental disorder with recurrent facial gestalt. - Shepherdson, James L; Hutchison, Katie; Don, Dilan Wellalage; McGillivray, George; Choi, Tae-Ik; Allan, Carolyn A; Amor, David J; Banka, Siddharth; Basel, Donald G; Buch, Laura D; Carere, Deanna Alexis; Carroll, Renée; et al. (Am J Hum Genet, 2024)
Pathogenic variants in multiple genes on the X chromosome have been implicated in syndromic and non-syndromic intellectual disability disorders. ZFX on Xp22.11 encodes a transcription factor that has been linked to diverse processes including oncogenesis and development, but germline variants have not been characterized in association with disease. Here, we present clinical and molecular characterization of 18 individuals with germline ZFX variants. Exome or genome sequencing revealed 11 variants in 18 subjects (14 males and 4 females) from 16 unrelated families. Four missense variants were identified in 11 subjects, with seven truncation variants in the remaining individuals. Clinical findings included developmental delay/intellectual disability, behavioral abnormalities, hypotonia, and congenital anomalies. Overlapping and recurrent facial features were identified in all subjects, including thickening and medial broadening of eyebrows, variations in the shape of the face, external eye abnormalities, smooth and/or long philtrum, and ear abnormalities. Hyperparathyroidism was found in four families with missense variants, and enrichment of different tumor types was observed. In molecular studies, DNA-binding domain variants elicited differential expression of a small set of target genes relative to wild-type ZFX in cultured cells, suggesting a gain or loss of transcriptional activity. Additionally, a zebrafish model of ZFX loss displayed an altered behavioral phenotype, providing additional evidence for the functional significance of ZFX. Our clinical and experimental data support that variants in ZFX are associated with an X-linked intellectual disability syndrome characterized by a recurrent facial gestalt, neurocognitive and behavioral abnormalities, and an increased risk for congenital anomalies and hyperparathyroidism.
Keywords: Animals; Female; Humans; Hyperparathyroidism; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype; Transcription Factors; Zebrafish

Variant-specific pathophysiological mechanisms of AFF3 differently influence transcriptome profiles. - Bassani, Sissy; Chrast, Jacqueline; Ambrosini, Giovanna; Voisin, Norine; Schütz, Frédéric; Brusco, Alfredo; Sirchia, Fabio; Turban, Lydia; Schubert, Susanna; Jamra, Rami Abou; Schlump, Jan-Ulrich; DeMille, Desiree; et al. (medRxiv, 2024)
BACKGROUND: We previously described the KINSSHIP syndrome, an autosomal dominant disorder associated with intellectual disability (ID), mesomelic dysplasia and horseshoe kidney,caused by variants in the degron of AFF3. Mouse knock-ins and overexpression in zebrafish provided evidence for a dominant-negative (DN) mode-of-action, wherein an increased level of AFF3 resulted in pathological effects. METHODS: Evolutionary constraints suggest that other mode-of-inheritance could be at play. We challenged this hypothesis by screening ID cohorts for individuals with predicted-to-be deleterious variants in . We used both animal and cellular models to assess the deleteriousness of the identified variants. RESULTS: We identified an individual with a KINSSHIP-like phenotype carrying a partial duplication of further strengthening the hypothesis that an increased level of AFF3 is pathological. We also detected seventeen individuals displaying a milder syndrome with either heterozygous LoF or biallelic missense variants in . Consistent with semi-dominance, we discovered three patients with homozygous LoF and one compound heterozygote for a LoF and a missense variant, who presented more severe phenotypes than their heterozygous parents. Matching zebrafish knockdowns exhibit neurological defects that could be rescued by expressing human mRNA, confirming their association with the ablation of . Conversely, some of the human mRNAs carrying missense variants identified in affected individuals did not complement. Overexpression of mutated mRNAs in zebrafish embryos produced a significant increase of abnormal larvae compared to wild-type overexpression further demonstrating deleteriousness. To further assess the effect of variation, we profiled the transcriptome of fibroblasts from affected individuals and engineered isogenic cells harboring +/+, DN/DN, LoF/+, LoF/LoF or DN/LoF genotypes. The expression of more than a third of the AFF3 bound loci is modified in either the DN/DN or the LoF/LoF lines. While the same pathways are affected, only about one-third of the differentially expressed genes are common to these homozygote datasets, indicating that LoF and DN variants largely modulate transcriptomes differently, e.g. the DNA repair pathway displayed opposite modulation. CONCLUSIONS: Our results and the high pleiotropy shown by variation at this locus suggest that minute changes in function are deleterious.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association Between Whole Blood-Derived Mitochondrial DNA Copy Number, Low-Density Lipoprotein Cholesterol, and Cardiovascular Disease Risk. - Liu, Xue; Sun, Xianbang; Zhang, Yuankai; Jiang, Wenqing; Lai, Meng; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Haessler, Jeffrey; Zheng, Yinan; et al. (J Am Heart Assoc, 2023)
Background The relationship between mitochondrial DNA copy number (mtDNA CN) and cardiovascular disease remains elusive. Methods and Results We performed cross-sectional and prospective association analyses of blood-derived mtDNA CN and cardiovascular disease outcomes in 27 316 participants in 8 cohorts of multiple racial and ethnic groups with whole-genome sequencing. We also performed Mendelian randomization to explore causal relationships of mtDNA CN with coronary heart disease (CHD) and cardiometabolic risk factors (obesity, diabetes, hypertension, and hyperlipidemia). <0.01 was used for significance. We validated most of the previously reported associations between mtDNA CN and cardiovascular disease outcomes. For example, 1-SD unit lower level of mtDNA CN was associated with 1.08 (95% CI, 1.04-1.12; <0.001) times the hazard for developing incident CHD, adjusting for covariates. Mendelian randomization analyses showed no causal effect from a lower level of mtDNA CN to a higher CHD risk (β=0.091; =0.11) or in the reverse direction (β=-0.012; =0.076). Additional bidirectional Mendelian randomization analyses revealed that low-density lipoprotein cholesterol had a causal effect on mtDNA CN (β=-0.084; <0.001), but the reverse direction was not significant (=0.059). No causal associations were observed between mtDNA CN and obesity, diabetes, and hypertension, in either direction. Multivariable Mendelian randomization analyses showed no causal effect of CHD on mtDNA CN, controlling for low-density lipoprotein cholesterol level (=0.52), whereas there was a strong direct causal effect of higher low-density lipoprotein cholesterol on lower mtDNA CN, adjusting for CHD status (β=-0.092; <0.001). Conclusions Our findings indicate that high low-density lipoprotein cholesterol may underlie the complex relationships between mtDNA CN and vascular atherosclerosis.
Keywords: Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus; DNA Copy Number Variations; DNA, Mitochondrial; Humans; Hypertension; Obesity; Risk Factors

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Eric Boerwinkle; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.
Keywords: Adult; Aged; Apolipoproteins B; Cholesterol, LDL; Coronary Disease; DNA; Female; Humans; Male; Middle Aged; Proprotein Convertase 9; Prospective Studies

Author Correction: Analyses of non-coding somatic drivers in 2,658 cancer whole genomes. - Rheinbay, Esther; Nielsen, Morten Muhlig; Abascal, Federico; Wala, Jeremiah A; Shapira, Ofer; Tiao, Grace; Hornshøj, Henrik; Hess, Julian M; Juul, Randi Istrup; Lin, Ziao; Feuerbach, Lars; Sabarinathan, Radhakrishnan; et al. (Nature, 2023)

Author Correction: Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)

Author Correction: Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2023)

Beyond the exome: What's next in diagnostic testing for Mendelian conditions. - Wojcik, Monica H; Reuter, Chloe M; Marwaha, Shruti; Mahmoud, Medhat; Duyzend, Michael H; Barseghyan, Hayk; Bo Yuan; Boone, Philip M; Groopman, Emily E; Délot, Emmanuèle C; Jain, Deepti; Sanchis-Juan, Alba; et al. (Am J Hum Genet, 2023)
Despite advances in clinical genetic testing, including the introduction of exome sequencing (ES), more than 50% of individuals with a suspected Mendelian condition lack a precise molecular diagnosis. Clinical evaluation is increasingly undertaken by specialists outside of clinical genetics, often occurring in a tiered fashion and typically ending after ES. The current diagnostic rate reflects multiple factors, including technical limitations, incomplete understanding of variant pathogenicity, missing genotype-phenotype associations, complex gene-environment interactions, and reporting differences between clinical labs. Maintaining a clear understanding of the rapidly evolving landscape of diagnostic tests beyond ES, and their limitations, presents a challenge for non-genetics professionals. Newer tests, such as short-read genome or RNA sequencing, can be challenging to order, and emerging technologies, such as optical genome mapping and long-read DNA sequencing, are not available clinically. Furthermore, there is no clear guidance on the next best steps after inconclusive evaluation. Here, we review why a clinical genetic evaluation may be negative, discuss questions to be asked in this setting, and provide a framework for further investigation, including the advantages and disadvantages of new approaches that are nascent in the clinical sphere. We present a guide for the next best steps after inconclusive molecular testing based upon phenotype and prior evaluation, including when to consider referral to research consortia focused on elucidating the underlying cause of rare unsolved genetic disorders.
Keywords: Exome; Exome Sequencing; Genetic Testing; Humans; Phenotype; Rare Diseases; Sequence Analysis, DNA

Beyond the exome: what's next in diagnostic testing for Mendelian conditions. - Wojcik, Monica H; Reuter, Chloe M; Marwaha, Shruti; Mahmoud, Medhat; Duyzend, Michael H; Barseghyan, Hayk; Bo Yuan; Boone, Philip M; Groopman, Emily E; Délot, Emmanuèle C; Jain, Deepti; Sanchis-Juan, Alba; et al. (ArXiv, 2023)
Despite advances in clinical genetic testing, including the introduction of exome sequencing (ES), more than 50% of individuals with a suspected Mendelian condition lack a precise molecular diagnosis. Clinical evaluation is increasingly undertaken by specialists outside of clinical genetics, often occurring in a tiered fashion and typically ending after ES. The current diagnostic rate reflects multiple factors, including technical limitations, incomplete understanding of variant pathogenicity, missing genotype-phenotype associations, complex gene-environment interactions, and reporting differences between clinical labs. Maintaining a clear understanding of the rapidly evolving landscape of diagnostic tests beyond ES, and their limitations, presents a challenge for non-genetics professionals. Newer tests, such as short-read genome or RNA sequencing, can be challenging to order and emerging technologies, such as optical genome mapping and long-read DNA or RNA sequencing, are not available clinically. Furthermore, there is no clear guidance on the next best steps after inconclusive evaluation. Here, we review why a clinical genetic evaluation may be negative, discuss questions to be asked in this setting, and provide a framework for further investigation, including the advantages and disadvantages of new approaches that are nascent in the clinical sphere. We present a guide for the next best steps after inconclusive molecular testing based upon phenotype and prior evaluation, including when to consider referral to a consortium such as GREGoR, which is focused on elucidating the underlying cause of rare unsolved genetic disorders.

Bi-allelic ACBD6 variants lead to a neurodevelopmental syndrome with progressive and complex movement disorders. - Kaiyrzhanov, Rauan; Rad, Aboulfazl; Lin, Sheng-Jia; Bertoli-Avella, Aida; Kallemeijn, Wouter W; Godwin, Annie; Zaki, Maha S; Huang, Kevin; Lau, Tracy; Petree, Cassidy; Efthymiou, Stephanie; Ghayoor Karimiani, Ehsan; et al. (Brain, 2023)
The acyl-CoA-binding domain-containing protein 6 (ACBD6) is ubiquitously expressed, plays a role in the acylation of lipids and proteins, and regulates the N-myristoylation of proteins via N-myristoyltransferase enzymes (NMTs). However, its precise function in cells is still unclear, as is the consequence of ACBD6 defects on human pathophysiology. Utilizing exome sequencing and extensive international data sharing efforts, we identified 45 affected individuals from 28 unrelated families (consanguinity 93%) with bi-allelic pathogenic, predominantly loss-of-function (18/20) variants in ACBD6. We generated zebrafish and Xenopus tropicalis acbd6 knockouts by CRISPR/Cas9 and characterized the role of ACBD6 on protein N-myristoylation with YnMyr chemical proteomics in the model organisms and human cells, with the latter also being subjected further to ACBD6 peroxisomal localization studies. The affected individuals (23 males and 22 females), with ages ranging from 1 to 50 years old, typically present with a complex and progressive disease involving moderate-to-severe global developmental delay/intellectual disability (100%) with significant expressive language impairment (98%), movement disorders (97%), facial dysmorphism (95%), and mild cerebellar ataxia (85%) associated with gait impairment (94%), limb spasticity/hypertonia (76%), oculomotor (71%) and behavioural abnormalities (65%), overweight (59%), microcephaly (39%) and epilepsy (33%). The most conspicuous and common movement disorder was dystonia (94%), frequently leading to early-onset progressive postural deformities (97%), limb dystonia (55%), and cervical dystonia (31%). A jerky tremor in the upper limbs (63%), a mild head tremor (59%), parkinsonism/hypokinesia developing with advancing age (32%), and simple motor and vocal tics were among other frequent movement disorders. Midline brain malformations including corpus callosum abnormalities (70%), hypoplasia/agenesis of the anterior commissure (66%), short midbrain and small inferior cerebellar vermis (38% each), as well as hypertrophy of the clava (24%) were common neuroimaging findings. acbd6-deficient zebrafish and Xenopus models effectively recapitulated many clinical phenotypes reported in patients including movement disorders, progressive neuromotor impairment, seizures, microcephaly, craniofacial dysmorphism, and midbrain defects accompanied by developmental delay with increased mortality over time. Unlike ACBD5, ACBD6 did not show a peroxisomal localisation and ACBD6-deficiency was not associated with altered peroxisomal parameters in patient fibroblasts. Significant differences in YnMyr-labelling were observed for 68 co- and 18 post-translationally N-myristoylated proteins in patient-derived fibroblasts. N-Myristoylation was similarly affected in acbd6-deficient zebrafish and Xenopus tropicalis models, including Fus, Marcks, and Chchd-related proteins implicated in neurological diseases. The present study provides evidence that bi-allelic pathogenic variants in ACBD6 lead to a distinct neurodevelopmental syndrome accompanied by complex and progressive cognitive and movement disorders.

A biallelic frameshift indel in PPP1R35 as a cause of primary microcephaly. - Dawood, Moez; Akay, Gulsen; Mitani, Tadahiro; Marafi, Dana; Fatih, Jawid M; Gezdirici, Alper; Najmabadi, Hossein; Kahrizi, Kimia; Punetha, Jaya; Grochowski, Christopher M; Du, Haowei; Jolly, Angad; et al. (Am J Med Genet A, 2023)
Protein phosphatase 1 regulatory subunit 35 (PPP1R35) encodes a centrosomal protein required for recruiting microtubule-binding elongation machinery. Several proteins in this centriole biogenesis pathway correspond to established primary microcephaly (MCPH) genes, and multiple model organism studies hypothesize PPP1R35 as a candidate MCPH gene. Here, using exome sequencing (ES) and family-based rare variant analyses, we report a homozygous, frameshifting indel deleting the canonical stop codon in the last exon of PPP1R35 [Chr7: c.753_*3delGGAAGCGTAGACCinsCG (p.Trp251Cysfs*22)]; the variant allele maps in a 3.7 Mb block of absence of heterozygosity (AOH) in a proband with severe MCPH (-4.3 SD at birth, -6.1 SD by 42 months), pachygyria, and global developmental delay from a consanguineous Turkish kindred. Droplet digital PCR (ddPCR) confirmed mutant mRNA expression in fibroblasts. In silico prediction of the translation of mutant PPP1R35 is expected to be elongated by 18 amino acids before encountering a downstream stop codon. This complex indel allele is absent in public databases (ClinVar, gnomAD, ARIC, 1000 genomes) and our in-house database of 14,000+ exomes including 1800+ Turkish exomes supporting predicted pathogenicity. Comprehensive literature searches for PPP1R35 variants yielded two probands affected with severe microcephaly (-15 SD and -12 SD) with the same homozygous indel from a single, consanguineous, Iranian family from a cohort of 404 predominantly Iranian families. The lack of heterozygous cases in two large cohorts representative of the genetic background of these two families decreased our suspicion of a founder allele and supports the contention of a recurrent mutation. We propose two potential secondary structure mutagenesis models for the origin of this variant allele mediated by hairpin formation between complementary GC rich segments flanking the stop codon via secondary structure mutagenesis.
Keywords: Codon, Terminator; Frameshift Mutation; Humans; Infant, Newborn; Iran; Microcephaly; Microtubule-Associated Proteins; Pedigree

Biallelic missense variants in COG3 cause a congenital disorder of glycosylation with impairment of retrograde vesicular trafficking. - Duan, Ruizhi; Marafi, Dana; Xia, Zhi-Jie; Ng, Bobby G; Maroofian, Reza; Sumya, Farhana Taher; Saad, Ahmed K; Du, Haowei; Fatih, Jawid M; Hunter, Jill V; Elbendary, Hasnaa M; Baig, Shahid M; et al. (J Inherit Metab Dis, 2023)
Biallelic variants in genes for seven out of eight subunits of the conserved oligomeric Golgi complex (COG) are known to cause recessive congenital disorders of glycosylation (CDG) with variable clinical manifestations. COG3 encodes a constituent subunit of the COG complex that has not been associated with disease traits in humans. Herein, we report two COG3 homozygous missense variants in four individuals from two unrelated consanguineous families that co-segregated with COG3-CDG presentations. Clinical phenotypes of affected individuals include global developmental delay, severe intellectual disability, microcephaly, epilepsy, facial dysmorphism, and variable neurological findings. Biochemical analysis of serum transferrin from one family showed the loss of a single sialic acid. Western blotting on patient-derived fibroblasts revealed reduced COG3 and COG4. Further experiments showed delayed retrograde vesicular recycling in patient cells. This report adds to the knowledge of the COG-CDG network by providing collective evidence for a COG3-CDG rare disease trait and implicating a likely pathology of the disorder as the perturbation of Golgi trafficking.
Keywords: Adaptor Proteins, Vesicular Transport; Congenital Disorders of Glycosylation; Fibroblasts; Glycosylation; Humans; Phenotype

Bi-allelic TTI1 variants cause an autosomal-recessive neurodevelopmental disorder with microcephaly. - Serey-Gaut, Margaux; Cortes, Marisol; Makrythanasis, Periklis; Suri, Mohnish; Taylor, Alexander M R; Sullivan, Jennifer A; Asleh, Ayat N; Mitra, Jaba; Dar, Mohamad A; McNamara, Amy; Shashi, Vandana; Dugan, Sarah; et al. (Am J Hum Genet, 2023)
Telomere maintenance 2 (TELO2), Tel2 interacting protein 2 (TTI2), and Tel2 interacting protein 1 (TTI1) are the three components of the conserved Triple T (TTT) complex that modulates activity of phosphatidylinositol 3-kinase-related protein kinases (PIKKs), including mTOR, ATM, and ATR, by regulating the assembly of mTOR complex 1 (mTORC1). The TTT complex is essential for the expression, maturation, and stability of ATM and ATR in response to DNA damage. TELO2- and TTI2-related bi-allelic autosomal-recessive (AR) encephalopathies have been described in individuals with moderate to severe intellectual disability (ID), short stature, postnatal microcephaly, and a movement disorder (in the case of variants within TELO2). We present clinical, genomic, and functional data from 11 individuals in 9 unrelated families with bi-allelic variants in TTI1. All present with ID, and most with microcephaly, short stature, and a movement disorder. Functional studies performed in HEK293T cell lines and fibroblasts and lymphoblastoid cells derived from 4 unrelated individuals showed impairment of the TTT complex and of mTOR pathway activity which is improved by treatment with Rapamycin. Our data delineate a TTI1-related neurodevelopmental disorder and expand the group of disorders related to the TTT complex.
Keywords: HEK293 Cells; Humans; Intracellular Signaling Peptides and Proteins; Microcephaly; Movement Disorders; Neurodevelopmental Disorders; TOR Serine-Threonine Kinases

Bi-allelic variants in the ESAM tight-junction gene cause a neurodevelopmental disorder associated with fetal intracranial hemorrhage. - Lecca, Mauro; Pehlivan, Davut; Suñer, Damià Heine; Weiss, Karin; Coste, Thibault; Zweier, Markus; Oktay, Yavuz; Danial-Farran, Nada; Rosti, Vittorio; Bonasoni, Maria Paola; Malara, Alessandro; Contrò, Gianluca; et al. (Am J Hum Genet, 2023)
The blood-brain barrier (BBB) is an essential gatekeeper for the central nervous system and incidence of neurodevelopmental disorders (NDDs) is higher in infants with a history of intracerebral hemorrhage (ICH). We discovered a rare disease trait in thirteen individuals, including four fetuses, from eight unrelated families associated with homozygous loss-of-function variant alleles of ESAM which encodes an endothelial cell adhesion molecule. The c.115del (p.Arg39Glyfs33) variant, identified in six individuals from four independent families of Southeastern Anatolia, severely impaired the in vitro tubulogenic process of endothelial colony-forming cells, recapitulating previous evidence in null mice, and caused lack of ESAM expression in the capillary endothelial cells of damaged brain. Affected individuals with bi-allelic ESAM variants showed profound global developmental delay/unspecified intellectual disability, epilepsy, absent or severely delayed speech, varying degrees of spasticity, ventriculomegaly, and ICH/cerebral calcifications, the latter being also observed in the fetuses. Phenotypic traits observed in individuals with bi-allelic ESAM variants overlap very closely with other known conditions characterized by endothelial dysfunction due to mutation of genes encoding tight junction molecules. Our findings emphasize the role of brain endothelial dysfunction in NDDs and contribute to the expansion of an emerging group of diseases that we propose to rename as "tightjunctionopathies."
Keywords: Alleles; Animals; Brain Diseases; Cell Adhesion Molecules; Endothelial Cells; Humans; Intracranial Hemorrhages; Mice; Nervous System Malformations; Neurodevelopmental Disorders; Tight Junctions

Brain monoamine vesicular transport disease caused by homozygous SLC18A2 variants: A study in 42 affected individuals. - Saida, Ken; Maroofian, Reza; Sengoku, Toru; Mitani, Tadahiro; Pagnamenta, Alistair T; Marafi, Dana; Zaki, Maha S; O'Brien, Thomas J; Karimiani, Ehsan Ghayoor; Kaiyrzhanov, Rauan; Takizawa, Marina; Ohori, Sachiko; et al. (Genet Med, 2023)
PURPOSE: Brain monoamine vesicular transport disease is an infantile-onset movement disorder that mimics cerebral palsy. In 2013, the homozygous SLC18A2 variant, p.Pro387Leu, was first reported as a cause of this rare disorder, and dopamine agonists were efficient for treating affected individuals from a single large family. To date, only 6 variants have been reported. In this study, we evaluated genotype-phenotype correlations in individuals with biallelic SLC18A2 variants. METHODS: A total of 42 affected individuals with homozygous SLC18A2 variant alleles were identified. We evaluated genotype-phenotype correlations and the missense variants in the affected individuals based on the structural modeling of rat VMAT2 encoded by Slc18a2, with cytoplasm- and lumen-facing conformations. A Caenorhabditis elegans model was created for functional studies. RESULTS: A total of 19 homozygous SLC18A2 variants, including 3 recurrent variants, were identified using exome sequencing. The affected individuals typically showed global developmental delay, hypotonia, dystonia, oculogyric crisis, and autonomic nervous system involvement (temperature dysregulation/sweating, hypersalivation, and gastrointestinal dysmotility). Among the 58 affected individuals described to date, 16 (28%) died before the age of 13 years. Of the 17 patients with p.Pro237His, 9 died, whereas all 14 patients with p.Pro387Leu survived. Although a dopamine agonist mildly improved the disease symptoms in 18 of 21 patients (86%), some affected individuals with p.Ile43Phe and p.Pro387Leu showed milder phenotypes and presented prolonged survival even without treatment. The C. elegans model showed behavioral abnormalities. CONCLUSION: These data expand the phenotypic and genotypic spectra of SLC18A2-related disorders.
Keywords: Amines; Animals; Brain; Brain Diseases; Caenorhabditis elegans; Dystonia; Humans; Movement Disorders; Rats; Vesicular Monoamine Transport Proteins

Breast Cancer Detection with an Ensemble of Deep Learning Networks Using a Consensus-Adaptive Weighting Method. - Dehghan Rouzi, Mohammad; Moshiri, Behzad; Khoshnevisan, Mohammad; Akhaee, Mohammad Ali; Jaryani, Farhang; Salehi Nasab, Samaneh; Lee, Myeounggon (J Imaging, 2023)
Breast cancer's high mortality rate is often linked to late diagnosis, with mammograms as key but sometimes limited tools in early detection. To enhance diagnostic accuracy and speed, this study introduces a novel computer-aided detection (CAD) ensemble system. This system incorporates advanced deep learning networks-EfficientNet, Xception, MobileNetV2, InceptionV3, and Resnet50-integrated via our innovative consensus-adaptive weighting (CAW) method. This method permits the dynamic adjustment of multiple deep networks, bolstering the system's detection capabilities. Our approach also addresses a major challenge in pixel-level data annotation of faster R-CNNs, highlighted in a prominent previous study. Evaluations on various datasets, including the cropped DDSM (Digital Database for Screening Mammography), DDSM, and INbreast, demonstrated the system's superior performance. In particular, our CAD system showed marked improvement on the cropped DDSM dataset, enhancing detection rates by approximately 1.59% and achieving an accuracy of 95.48%. This innovative system represents a significant advancement in early breast cancer detection, offering the potential for more precise and timely diagnosis, ultimately fostering improved patient outcomes.

Broadening the phenotypic and molecular spectrum of FINCA syndrome: Biallelic NHLRC2 variants in 15 novel individuals. - Sczakiel, Henrike L; Zhao, Max; Wollert-Wulf, Brigitte; Danyel, Magdalena; Ehmke, Nadja; Stoltenburg, Corinna; Damseh, Nadirah; Al-Ashhab, Motee; Balci, Tugce B; Osmond, Matthew; Andrade, Andrea; Schallner, Jens; et al. (Eur J Hum Genet, 2023)
FINCA syndrome [MIM: 618278] is an autosomal recessive multisystem disorder characterized by fibrosis, neurodegeneration and cerebral angiomatosis. To date, 13 patients from nine families with biallelic NHLRC2 variants have been published. In all of them, the recurrent missense variant p.(Asp148Tyr) was detected on at least one allele. Common manifestations included lung or muscle fibrosis, respiratory distress, developmental delay, neuromuscular symptoms and seizures often followed by early death due to rapid disease progression.Here, we present 15 individuals from 12 families with an overlapping phenotype associated with nine novel NHLRC2 variants identified by exome analysis. All patients described here presented with moderate to severe global developmental delay and variable disease progression. Seizures, truncal hypotonia and movement disorders were frequently observed. Notably, we also present the first eight cases in which the recurrent p.(Asp148Tyr) variant was not detected in either homozygous or compound heterozygous state.We cloned and expressed all novel and most previously published non-truncating variants in HEK293-cells. From the results of these functional studies, we propose a potential genotype-phenotype correlation, with a greater reduction in protein expression being associated with a more severe phenotype.Taken together, our findings broaden the known phenotypic and molecular spectrum and emphasize that NHLRC2-related disease should be considered in patients presenting with intellectual disability, movement disorders, neuroregression and epilepsy with or without pulmonary involvement.
Keywords: Disease Progression; Fibrosis; HEK293 Cells; Humans; Intellectual Disability; Movement Disorders; Phenotype; Seizures; Syndrome

Ceramide compensation by ceramide synthases preserves retinal function and structure in a retinal dystrophy mouse model. - Qian, Xinye; Srinivasan, Tanmay; He, Jessica; Lu, Jiaxiong; Jin, Yan; Gu, Haiwei; Rui Chen (Dis Model Mech, 2023)
Increasing evidence has supported the role of ceramide as a mediator of photoreceptor dysfunction or cell death in ceramide accumulation and deficiency contexts. TLCD3B, a non-canonical ceramide synthase, was previously identified in addition to the six canonical ceramide synthases (CerSs), and the Tlcd3b-/- mouse model exhibited both retinal dysfunction and degeneration. As previous canonical CerS-deficient mouse models failed to display retinal degeneration, the mechanisms of how TLCD3B interacts with CerSs have not been investigated. Additionally, as the ceramide profile of each CerS is distinct, it is unclear whether the overall level or the homeostasis of different ceramide species plays a critical role in photoreceptor degeneration. Interactions between TLCD3B with canonical CerSs expressed in the retina were examined by subretinally injecting recombinant adeno-associated virus 8 vectors containing the Cers2 (rAAV8-CerS2), Cers4 (rAAV8-CerS4) and Cers5 (rAAV8-CerS5) genes. Injection of all three rAAV8-CerS vectors restored retinal functions as indicated by improved electroretinogram responses, but only rAAV8-CerS5 successfully retained retinal morphology in Tlcd3b-/- mice. CerSs and TLCD3B played partially redundant roles. Additionally, rather than acting as an integral entity, different ceramide species had different impacts on retinal cells, suggesting that the maintenance of the overall ceramide profile is critical for retinal function.
Keywords: Animals; Ceramides; Mice; Oxidoreductases; Retina; Retinal Dystrophies

Clinical and functional heterogeneity associated with the disruption of retinoic acid receptor beta. - Caron, Véronique; Chassaing, Nicolas; Ragge, Nicola; Boschann, Felix; Ngu, Angelina My-Hoa; Meloche, Elisabeth; Chorfi, Sarah; Lakhani, Saquib A; Ji, Weizhen; Steiner, Laurie; Marcadier, Julien; Jansen, Philip R; et al. (Genet Med, 2023)
PURPOSE: Dominant variants in the retinoic acid receptor beta (RARB) gene underlie a syndromic form of microphthalmia, known as MCOPS12, which is associated with other birth anomalies and global developmental delay with spasticity and/or dystonia. Here, we report 25 affected individuals with 17 novel pathogenic or likely pathogenic variants in RARB. This study aims to characterize the functional impact of these variants and describe the clinical spectrum of MCOPS12. METHODS: We used in vitro transcriptional assays and in silico structural analysis to assess the functional relevance of RARB variants in affecting the normal response to retinoids. RESULTS: We found that all RARB variants tested in our assays exhibited either a gain-of-function or a loss-of-function activity. Loss-of-function variants disrupted RARB function through a dominant-negative effect, possibly by disrupting ligand binding and/or coactivators' recruitment. By reviewing clinical data from 52 affected individuals, we found that disruption of RARB is associated with a more variable phenotype than initially suspected, with the absence in some individuals of cardinal features of MCOPS12, such as developmental eye anomaly or motor impairment. CONCLUSION: Our study indicates that pathogenic variants in RARB are functionally heterogeneous and associated with extensive clinical heterogeneity.
Keywords: Humans; Microphthalmos; Receptors, Retinoic Acid; Retinoids

The clinical and genetic spectrum of autosomal-recessive TOR1A-related disorders. - Saffari, Afshin; Lau, Tracy; Tajsharghi, Homa; Karimiani, Ehsan Ghayoor; Kariminejad, Ariana; Efthymiou, Stephanie; Zifarelli, Giovanni; Sultan, Tipu; Toosi, Mehran Beiraghi; Sedighzadeh, Sahar; Siu, Victoria Mok; Ortigoza-Escobar, Juan Darío; et al. (Brain, 2023)
In the field of rare diseases, progress in molecular diagnostics led to the recognition that variants linked to autosomal-dominant neurodegenerative diseases of later onset can, in the context of biallelic inheritance, cause devastating neurodevelopmental disorders and infantile or childhood-onset neurodegeneration. TOR1A-associated arthrogryposis multiplex congenita 5 (AMC5) is a rare neurodevelopmental disorder arising from biallelic variants in TOR1A, a gene that in the heterozygous state is associated with torsion dystonia-1 (DYT1 or DYT-TOR1A), an early-onset dystonia with reduced penetrance. While 15 individuals with AMC5-TOR1A have been reported (less than 10 in detail), a systematic investigation of the full disease-associated spectrum has not been conducted. Here, we assess the clinical, radiological and molecular characteristics of 57 individuals from 40 families with biallelic variants in TOR1A. Median age at last follow-up was 3 years (0-24 years). Most individuals presented with severe congenital flexion contractures (95%) and variable developmental delay (79%). Motor symptoms were reported in 79% and included lower limb spasticity and pyramidal signs, as well as gait disturbances. Facial dysmorphism was an integral part of the phenotype, with key features being a broad/full nasal tip, narrowing of the forehead and full cheeks. Analysis of disease-associated manifestations delineated a phenotypic spectrum ranging from normal cognition and mild gait disturbance to congenital arthrogryposis, global developmental delay, intellectual disability, absent speech and inability to walk. In a subset, the presentation was consistent with foetal akinesia deformation sequence with severe intrauterine abnormalities. Survival was 71%, with higher mortality in males. Death occurred at a median age of 1.2 months (1 week-9 years), due to respiratory failure, cardiac arrest or sepsis. Analysis of brain MRI studies identified non-specific neuroimaging features, including a hypoplastic corpus callosum (72%), foci of signal abnormality in the subcortical and periventricular white matter (55%), diffuse white matter volume loss (45%), mega cisterna magna (36%) and arachnoid cysts (27%). The molecular spectrum included 22 distinct variants, defining a mutational hotspot in the C-terminal domain of the Torsin-1A protein. Genotype-phenotype analysis revealed an association of missense variants in the 3-helix bundle domain to an attenuated phenotype, while missense variants near the Walker A/B motif as well as biallelic truncating variants were linked to early death. In summary, this systematic cross-sectional analysis of a large cohort of individuals with biallelic TOR1A variants across a wide age-range delineates the clinical and genetic spectrum of TOR1A-related autosomal-recessive disease and highlights potential predictors for disease severity and survival.
Keywords: Cross-Sectional Studies; Dystonia; Dystonic Disorders; Humans; Male; Molecular Chaperones; Mutation; Nervous System Malformations; Phenotype

Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)
Chronic liver disease is a major public health burden worldwide. Although different aetiologies and mechanisms of liver injury exist, progression of chronic liver disease follows a common pathway of liver inflammation, injury and fibrosis. Here we examined the association between clonal haematopoiesis of indeterminate potential (CHIP) and chronic liver disease in 214,563 individuals from 4 independent cohorts with whole-exome sequencing data (Framingham Heart Study, Atherosclerosis Risk in Communities Study, UK Biobank and Mass General Brigham Biobank). CHIP was associated with an increased risk of prevalent and incident chronic liver disease (odds ratio = 2.01, 95% confidence interval (95% CI) [1.46, 2.79]; P < 0.001). Individuals with CHIP were more likely to demonstrate liver inflammation and fibrosis detectable by magnetic resonance imaging compared to those without CHIP (odds ratio = 1.74, 95% CI [1.16, 2.60]; P = 0.007). To assess potential causality, Mendelian randomization analyses showed that genetic predisposition to CHIP was associated with a greater risk of chronic liver disease (odds ratio = 2.37, 95% CI [1.57, 3.6]; P < 0.001). In a dietary model of non-alcoholic steatohepatitis, mice transplanted with Tet2-deficient haematopoietic cells demonstrated more severe liver inflammation and fibrosis. These effects were mediated by the NLRP3 inflammasome and increased levels of expression of downstream inflammatory cytokines in Tet2-deficient macrophages. In summary, clonal haematopoiesis is associated with an elevated risk of liver inflammation and chronic liver disease progression through an aberrant inflammatory response.
Keywords: Animals; Clonal Hematopoiesis; Disease Progression; Disease Susceptibility; Hepatitis; Inflammation; Liver Cirrhosis; Mice; Non-alcoholic Fatty Liver Disease; Odds Ratio

The complete sequence of a human Y chromosome. - Rhie, Arang; Nurk, Sergey; Cechova, Monika; Hoyt, Savannah J; Taylor, Dylan J; Altemose, Nicolas; Hook, Paul W; Koren, Sergey; Rautiainen, Mikko; Alexandrov, Ivan A; Allen, Jamie; Asri, Mobin; et al. (Nature, 2023)
The human Y chromosome has been notoriously difficult to sequence and assemble because of its complex repeat structure that includes long palindromes, tandem repeats and segmental duplications. As a result, more than half of the Y chromosome is missing from the GRCh38 reference sequence and it remains the last human chromosome to be finished. Here, the Telomere-to-Telomere (T2T) consortium presents the complete 62,460,029-base-pair sequence of a human Y chromosome from the HG002 genome (T2T-Y) that corrects multiple errors in GRCh38-Y and adds over 30 million base pairs of sequence to the reference, showing the complete ampliconic structures of gene families TSPY, DAZ and RBMY; 41 additional protein-coding genes, mostly from the TSPY family; and an alternating pattern of human satellite 1 and 3 blocks in the heterochromatic Yq12 region. We have combined T2T-Y with a previous assembly of the CHM13 genome and mapped available population variation, clinical variants and functional genomics data to produce a complete and comprehensive reference sequence for all 24 human chromosomes.
Keywords: Base Sequence; Chromosomes, Human, Y; DNA, Satellite; Genetic Variation; Genetics, Population; Genomics; Heterochromatin; Humans; Multigene Family; Reference Standards; Segmental Duplications, Genomic; Sequence Analysis, DNA; Tandem Repeat Sequences; Telomere

Complex Evolutionary History With Extensive Ancestral Gene Flow in an African Primate Radiation. - Jensen, Axel; Swift, Frances; de Vries, Dorien; Beck, Robin M D; Kuderna, Lukas F K; Knauf, Sascha; Chuma, Idrissa S; Keyyu, Julius D; Kitchener, Andrew C; Farh, Kyle; Jeffrey Rogers; Marques-Bonet, Tomas; et al. (Mol Biol Evol, 2023)
Understanding the drivers of speciation is fundamental in evolutionary biology, and recent studies highlight hybridization as an important evolutionary force. Using whole-genome sequencing data from 22 species of guenons (tribe Cercopithecini), one of the world's largest primate radiations, we show that rampant gene flow characterizes their evolutionary history and identify ancient hybridization across deeply divergent lineages that differ in ecology, morphology, and karyotypes. Some hybridization events resulted in mitochondrial introgression between distant lineages, likely facilitated by cointrogression of coadapted nuclear variants. Although the genomic landscapes of introgression were largely lineage specific, we found that genes with immune functions were overrepresented in introgressing regions, in line with adaptive introgression, whereas genes involved in pigmentation and morphology may contribute to reproductive isolation. In line with reports from other systems that hybridization might facilitate diversification, we find that some of the most species-rich guenon clades are of admixed origin. This study provides important insights into the prevalence, role, and outcomes of ancestral hybridization in a large mammalian radiation.
Keywords: Animals; Biological Evolution; Gene Flow; Genome; Genomics; Hybridization, Genetic; Mammals; Phylogeny; Primates

DATA RESOURCES AND ANALYSES FAIR Header Reference genome: A TRUSTworthy standard. - Wright, Adam; Wilkinson, Mark D; Mungall, Chris; Cain, Scott; Stephen Richards; Sternberg, Paul; Provin, Ellen; Jacobs, Jonathan L; Geib, Scott; Raciti, Daniela; Yook, Karen; Stein, Lincoln; et al. (bioRxiv, 2023)
The lack of interoperable data standards among reference genome data-sharing platforms inhibits cross-platform analysis while increasing the risk of data provenance loss. Here, we describe the FAIR-bioHeaders Reference genome (FHR), a metadata standard guided by the principles of Findability, Accessibility, Interoperability, and Reuse (FAIR) in addition to the principles of Transparency, Responsibility, User focus, Sustainability, and Technology (TRUST). The objective of FHR is to provide an extensive set of data serialisation methods and minimum data field requirements while still maintaining extensibility, flexibility, and expressivity in an increasingly decentralised genomic data ecosystem. The effort needed to implement FHR is low; FHR's design philosophy ensures easy implementation while retaining the benefits gained from recording both machine and human-readable provenance.

Divergent BRAF Inhibitor Resistance Mechanisms Revealed through Epigenetic Mapping. - Kang, Yuanyuan; Ji, Zhenyu; Li, He; Tsao, Hensin (J Invest Dermatol, 2023)
Although tremendous progress has been made in targeted and immune-based treatments for advanced melanoma, there remains a substantial therapeutic failure rate. For patients with BRAF(V600)-mutant melanomas, resistance to BRAF inhibitors remains a significant survival hurdle. Although multiple compensatory mechanisms to bypass BRAF blockade have been discovered, the epigenetic patterns are still poorly characterized. In this report, we generated eight matched pairs of vemurafenib-sensitive/-resistant melanoma lines and subjected these to concurrent RNA-sequencing and H3K27ac chromatin immunoprecipitation sequencing analysis. Globally, we identified two classes of epigenetic profiles that correlate with resistance. Class 1 resistance involves fewer RNA expression alterations accompanied by fewer enhancer mark changes with H3K27ac. Class 2 resistance shows widespread alterations in transcription and enhancer profiles, which converge on epithelial‒mesenchymal transition and hypoxia-related pathways. We also observed significant and dynamic changes in superenhancers that underpin these transcriptomic patterns. We subsequently verified the two-class structure in pre-BRAF inhibitors and postrelapse human melanoma specimens. Our findings reveal a broad and underappreciated spectrum of epigenetic plasticity during acquired BRAF inhibitor resistance.
Keywords: Cell Line, Tumor; Drug Resistance, Neoplasm; Epigenesis, Genetic; Humans; Indoles; Melanoma; Mutation; Protein Kinase Inhibitors; Proto-Oncogene Proteins B-raf; RNA; Sulfonamides

The EN-TEx resource of multi-tissue personal epigenomes & variant-impact models. - Rozowsky, Joel; Gao, Jiahao; Borsari, Beatrice; Yang, Yucheng T; Galeev, Timur; Gürsoy, Gamze; Epstein, Charles B; Xiong, Kun; Xu, Jinrui; Li, Tianxiao; Liu, Jason; Yu, Keyang; et al. (Cell, 2023)
Understanding how genetic variants impact molecular phenotypes is a key goal of functional genomics, currently hindered by reliance on a single haploid reference genome. Here, we present the EN-TEx resource of 1,635 open-access datasets from four donors (∼30 tissues × ∼15 assays). The datasets are mapped to matched, diploid genomes with long-read phasing and structural variants, instantiating a catalog of >1 million allele-specific loci. These loci exhibit coordinated activity along haplotypes and are less conserved than corresponding, non-allele-specific ones. Surprisingly, a deep-learning transformer model can predict the allele-specific activity based only on local nucleotide-sequence context, highlighting the importance of transcription-factor-binding motifs particularly sensitive to variants. Furthermore, combining EN-TEx with existing genome annotations reveals strong associations between allele-specific and GWAS loci. It also enables models for transferring known eQTLs to difficult-to-profile tissues (e.g., from skin to heart). Overall, EN-TEx provides rich data and generalizable models for more accurate personal functional genomics.
Keywords: Epigenome; Genome-Wide Association Study; Genomics; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2023)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at ∼450 000 cytosine-phosphate-guanine (CpG) sites in 9732 middle-aged to older adults from 14 community-based studies. Single CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5) and co-localized with FOLH1 expression in brain (posterior probability = 0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis and multi-omics co-localization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug-repositioning analysis indicated antihyperlipidaemic agents, more specifically peroxisome proliferator-activated receptor-alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood-brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidaemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood-brain barrier disruption.
Keywords: Aged; Brain; DNA Methylation; Epigenesis, Genetic; Genome-Wide Association Study; Humans; Magnetic Resonance Imaging; Middle Aged; Protein-Arginine N-Methyltransferases; Repressor Proteins; White Matter

Exome-wide assessment of isolated biliary atresia: A report from the National Birth Defects Prevention Study using child-parent trios and a case-control design to identify novel rare variants. - Sok, Pagna; Aniko Sabo; Almli, Lynn M; Jenkins, Mary M; Nembhard, Wendy N; Agopian, A J; Bamshad, Michael J; Blue, Elizabeth E; Brody, Lawrence C; Brown, Austin L; Browne, Marilyn L; Canfield, Mark A; et al. (Am J Med Genet A, 2023)
The etiology of biliary atresia (BA) is unknown, but recent studies suggest a role for rare protein-altering variants (PAVs). Exome sequencing data from the National Birth Defects Prevention Study on 54 child-parent trios, one child-mother duo, and 1513 parents of children with other birth defects were analyzed. Most (91%) cases were isolated BA. We performed (1) a trio-based analysis to identify rare de novo, homozygous, and compound heterozygous PAVs and (2) a case-control analysis using a sequence kernel-based association test to identify genes enriched with rare PAVs. While we replicated previous findings on PKD1L1, our results do not suggest that recurrent de novo PAVs play important roles in BA susceptibility. In fact, our finding in NOTCH2, a disease gene associated with Alagille syndrome, highlights the difficulty in BA diagnosis. Notably, IFRD2 has been implicated in other gastrointestinal conditions and warrants additional study. Overall, our findings strengthen the hypothesis that the etiology of BA is complex.
Keywords: Biliary Atresia; Case-Control Studies; Exome; Homozygote; Humans; Membrane Proteins; Parents

Familial Hypercholesterolemia in the Electronic Medical Records and Genomics Network: Prevalence, Penetrance, Cardiovascular Risk, and Outcomes After Return of Results. - Dikilitas, Ozan; Sherafati, Alborz; Saadatagah, Seyedmohammad; Satterfield, Benjamin A; Kochan, David C; Anderson, Katherine C; Chung, Wendy K; Hebbring, Scott J; Salvati, Zachary M; Sharp, Richard R; Sturm, Amy C; Richard A Gibbs; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: The implications of secondary findings detected in large-scale sequencing projects remain uncertain. We assessed prevalence and penetrance of pathogenic familial hypercholesterolemia (FH) variants, their association with coronary heart disease (CHD), and 1-year outcomes following return of results in phase III of the electronic medical records and genomics network. METHODS: Adult participants (n=18 544) at 7 sites were enrolled in a prospective cohort study to assess the clinical impact of returning results from targeted sequencing of 68 actionable genes, including , , and . FH variant prevalence and penetrance (defined as low-density lipoprotein cholesterol >155 mg/dL) were estimated after excluding participants enrolled on the basis of hypercholesterolemia. Multivariable logistic regression was used to estimate the odds of CHD compared to age- and sex-matched controls without FH-associated variants. Process (eg, referral to a specialist or ordering new tests), intermediate (eg, new diagnosis of FH), and clinical (eg, treatment modification) outcomes within 1 year after return of results were ascertained by electronic health record review. RESULTS: The prevalence of FH-associated pathogenic variants was 1 in 188 (69 of 13,019 unselected participants). Penetrance was 87.5%. The presence of an FH variant was associated with CHD (odds ratio, 3.02 [2.00-4.53]) and premature CHD (odds ratio, 3.68 [2.34-5.78]). At least 1 outcome occurred in 92% of participants; 44% received a new diagnosis of FH and 26% had treatment modified following return of results. CONCLUSIONS: In a multisite cohort of electronic health record-linked biobanks, monogenic FH was prevalent, penetrant, and associated with presence of CHD. Nearly half of participants with an FH-associated variant received a new diagnosis of FH and a quarter had treatment modified after return of results. These results highlight the potential utility of sequencing electronic health record-linked biobanks to detect FH.
Keywords: Adult; Cardiovascular Diseases; Coronary Artery Disease; Electronic Health Records; Genomics; Heart Disease Risk Factors; Humans; Hyperlipoproteinemia Type II; Penetrance; Prevalence; Proprotein Convertase 9; Prospective Studies; Risk Factors

FOXI3 pathogenic variants cause one form of craniofacial microsomia. - Mao, Ke; Borel, Christelle; Ansar, Muhammad; Jolly, Angad; Makrythanasis, Periklis; Froehlich, Christine; Iwaszkiewicz, Justyna; Wang, Bingqing; Xu, Xiaopeng; Li, Qiang; Blanc, Xavier; Zhu, Hao; et al. (Nat Commun, 2023)
Craniofacial microsomia (CFM; also known as Goldenhar syndrome), is a craniofacial developmental disorder of variable expressivity and severity with a recognizable set of abnormalities. These birth defects are associated with structures derived from the first and second pharyngeal arches, can occur unilaterally and include ear dysplasia, microtia, preauricular tags and pits, facial asymmetry and other malformations. The inheritance pattern is controversial, and the molecular etiology of this syndrome is largely unknown. A total of 670 patients belonging to unrelated pedigrees with European and Chinese ancestry with CFM, are investigated. We identify 18 likely pathogenic variants in 21 probands (3.1%) in FOXI3. Biochemical experiments on transcriptional activity and subcellular localization of the likely pathogenic FOXI3 variants, and knock-in mouse studies strongly support the involvement of FOXI3 in CFM. Our findings indicate autosomal dominant inheritance with reduced penetrance, and/or autosomal recessive inheritance. The phenotypic expression of the FOXI3 variants is variable. The penetrance of the likely pathogenic variants in the seemingly dominant form is reduced, since a considerable number of such variants in affected individuals were inherited from non-affected parents. Here we provide suggestive evidence that common variation in the FOXI3 allele in trans with the pathogenic variant could modify the phenotypic severity and accounts for the incomplete penetrance.
Keywords: Animals; Facial Asymmetry; Forkhead Transcription Factors; Goldenhar Syndrome; Mice; Pedigree

Functional characterization of age-dependent p16 epimutation reveals biological drivers and therapeutic targets for colorectal cancer. - Yang, Li; Chen, Xiaomin; Lee, Christy; Shi, Jiejun; Lawrence, Emily B; Zhang, Lanjing; Yumei Li; Gao, Nan; Jung, Sung Yun; Creighton, Chad J; Li, Jingyi Jessica; Cui, Ya; et al. (J Exp Clin Cancer Res, 2023)
BACKGROUND: Methylation of the p16 promoter resulting in epigenetic gene silencing-known as p16 epimutation-is frequently found in human colorectal cancer and is also common in normal-appearing colonic mucosa of aging individuals. Thus, to improve clinical care of colorectal cancer (CRC) patients, we explored the role of age-related p16 epimutation in intestinal tumorigenesis. METHODS: We established a mouse model that replicates two common genetic and epigenetic events observed in human CRCs: Apc mutation and p16 epimutation. We conducted long-term survival and histological analysis of tumor development and progression. Colonic epithelial cells and tumors were collected from mice and analyzed by RNA sequencing (RNA-seq), quantitative PCR, and flow cytometry. We performed single-cell RNA sequencing (scRNA-seq) to characterize tumor-infiltrating immune cells throughout tumor progression. We tested whether anti-PD-L1 immunotherapy affects overall survival of tumor-bearing mice and whether inhibition of both epigenetic regulation and immune checkpoint is more efficacious. RESULTS: Mice carrying combined Apc mutation and p16 epimutation had significantly shortened survival and increased tumor growth compared to those with Apc mutation only. Intriguingly, colon tumors with p16 epimutation exhibited an activated interferon pathway, increased expression of programmed death-ligand 1 (Pdl1), and enhanced infiltration of immune cells. scRNA-seq further revealed the presence of Foxp3 Tregs and γδT17 cells, which contribute to an immunosuppressive tumor microenvironment (TME). Furthermore, we showed that a combined therapy using an inhibitor of DNA methylation and a PD-L1 immune checkpoint inhibitor is more effective for improving survival in tumor-bearing mice than blockade of either pathway alone. CONCLUSIONS: Our study demonstrated that age-dependent p16 epimutation creates a permissive microenvironment for malignant transformation of polyps to colon cancer. Our findings provide a mechanistic rationale for future targeted therapy in patients with p16 epimutation.
Keywords: Animals; B7-H1 Antigen; Carcinogenesis; Cell Transformation, Neoplastic; Colonic Neoplasms; Colorectal Neoplasms; DNA Methylation; Epigenesis, Genetic; Humans; Mice; Tumor Microenvironment

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (Genetics, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-sequencing data in GTEx V8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased whole genome sequencing data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.
Keywords: Alternative Splicing; Exons; Genotype; Penetrance; RNA Splice Sites; RNA Splicing; RNA, Messenger

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Eric Boerwinkle; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Genetic Sex Validation for Sample Tracking in Clinical Testing. - Jianhong Hu; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (Res Sq, 2023)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors, samples from transgender participants and stem cell or bone marrow transplant patients along with undetermined sample mix-ups.

Genome-Wide Analysis of Structural Variants in Parkinson Disease. - Billingsley, Kimberley J; Ding, Jinhui; Jerez, Pilar Alvarez; Illarionova, Anastasia; Levine, Kristin; Grenn, Francis P; Makarious, Mary B; Moore, Anni; Vitale, Daniel; Reed, Xylena; Hernandez, Dena; Torkamani, Ali; et al. (Ann Neurol, 2023)
OBJECTIVE: Identification of genetic risk factors for Parkinson disease (PD) has to date been primarily limited to the study of single nucleotide variants, which only represent a small fraction of the genetic variation in the human genome. Consequently, causal variants for most PD risk are not known. Here we focused on structural variants (SVs), which represent a major source of genetic variation in the human genome. We aimed to discover SVs associated with PD risk by performing the first large-scale characterization of SVs in PD. METHODS: We leveraged a recently developed computational pipeline to detect and genotype SVs from 7,772 Illumina short-read whole genome sequencing samples. Using this set of SV variants, we performed a genome-wide association study using 2,585 cases and 2,779 controls and identified SVs associated with PD risk. Furthermore, to validate the presence of these variants, we generated a subset of matched whole-genome long-read sequencing data. RESULTS: We genotyped and tested 3,154 common SVs, representing over 412 million nucleotides of previously uncatalogued genetic variation. Using long-read sequencing data, we validated the presence of three novel deletion SVs that are associated with risk of PD from our initial association analysis, including a 2 kb intronic deletion within the gene LRRN4. INTERPRETATION: We identified three SVs associated with genetic risk of PD. This study represents the most comprehensive assessment of the contribution of SVs to the genetic risk of PD to date. ANN NEUROL 2023;93:1012-1022.
Keywords: Genome, Human; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Whole Genome Sequencing

Genome-wide coancestry reveals details of ancient and recent male-driven reticulation in baboons. - Sørensen, Erik F; R. Alan Harris; Zhang, Liye; Raveendran, Muthuswamy; Kuderna, Lukas F K; Walker, Jerilyn A; Storer, Jessica M; Kuhlwilm, Martin; Fontsere, Claudia; Seshadri, Lakshmi; Bergey, Christina M; Burrell, Andrew S; et al. (Science, 2023)
Baboons (genus ) are a morphologically and behaviorally diverse clade of catarrhine monkeys that have experienced hybridization between phenotypically and genetically distinct phylogenetic species. We used high-coverage whole-genome sequences from 225 wild baboons representing 19 geographic localities to investigate population genomics and interspecies gene flow. Our analyses provide an expanded picture of evolutionary reticulation among species and reveal patterns of population structure within and among species, including differential admixture among conspecific populations. We describe the first example of a baboon population with a genetic composition that is derived from three distinct lineages. The results reveal processes, both ancient and recent, that produced the observed mismatch between phylogenetic relationships based on matrilineal, patrilineal, and biparental inheritance. We also identified several candidate genes that may contribute to species-specific phenotypes.
Keywords: Animals; Biological Evolution; Gene Flow; Male; Papio; Phenotype; Phylogeny; Sex Characteristics; Species Specificity

Genomic analysis of two phlebotomine sand fly vectors of Leishmania from the New and Old World. - Labbé, Frédéric; Abdeladhim, Maha; Abrudan, Jenica; Araki, Alejandra Saori; Araujo, Ricardo N; Arensburger, Peter; Benoit, Joshua B; Brazil, Reginaldo Pecanha; Bruno, Rafaela V; Bueno da Silva Rivas, Gustavo; Carvalho de Abreu, Vinicius; Charamis, Jason; et al. (PLoS Negl Trop Dis, 2023)
Phlebotomine sand flies are of global significance as important vectors of human disease, transmitting bacterial, viral, and protozoan pathogens, including the kinetoplastid parasites of the genus Leishmania, the causative agents of devastating diseases collectively termed leishmaniasis. More than 40 pathogenic Leishmania species are transmitted to humans by approximately 35 sand fly species in 98 countries with hundreds of millions of people at risk around the world. No approved efficacious vaccine exists for leishmaniasis and available therapeutic drugs are either toxic and/or expensive, or the parasites are becoming resistant to the more recently developed drugs. Therefore, sand fly and/or reservoir control are currently the most effective strategies to break transmission. To better understand the biology of sand flies, including the mechanisms involved in their vectorial capacity, insecticide resistance, and population structures we sequenced the genomes of two geographically widespread and important sand fly vector species: Phlebotomus papatasi, a vector of Leishmania parasites that cause cutaneous leishmaniasis, (distributed in Europe, the Middle East and North Africa) and Lutzomyia longipalpis, a vector of Leishmania parasites that cause visceral leishmaniasis (distributed across Central and South America). We categorized and curated genes involved in processes important to their roles as disease vectors, including chemosensation, blood feeding, circadian rhythm, immunity, and detoxification, as well as mobile genetic elements. We also defined gene orthology and observed micro-synteny among the genomes. Finally, we present the genetic diversity and population structure of these species in their respective geographical areas. These genomes will be a foundation on which to base future efforts to prevent vector-borne transmission of Leishmania parasites.
Keywords: Animals; Genomics; Humans; Leishmania; Leishmaniasis, Cutaneous; Phlebotomus; Psychodidae

The genomic landscape of familial glioma. - Choi, Dong-Joo; Armstrong, Georgina; Lozzi, Brittney; Vijayaraghavan, Prashanth; Plon, Sharon E; Wong, Terence C; Eric Boerwinkle; Donna M Muzny; Chen, Hsiao-Chi; Richard A Gibbs; Ostrom, Quinn T; Melin, Beatrice; et al. (Sci Adv, 2023)
Glioma is a rare brain tumor with a poor prognosis. Familial glioma is a subset of glioma with a strong genetic predisposition that accounts for approximately 5% of glioma cases. We performed whole-genome sequencing on an exploratory cohort of 203 individuals from 189 families with a history of familial glioma and an additional validation cohort of 122 individuals from 115 families. We found significant enrichment of rare deleterious variants of seven genes in both cohorts, and the most significantly enriched gene was ( = 0.0006). Furthermore, we identified rare noncoding variants in both cohorts that were predicted to affect transcription factor binding sites or cause cryptic splicing. Last, we selected a subset of discovered genes for validation by CRISPR knockdown screening and found that , have profound impacts on proliferation. This study performs comprehensive surveillance of the genomic landscape of familial glioma.
Keywords: Brain Neoplasms; Calcium-Binding Proteins; DNA-Binding Proteins; Genetic Predisposition to Disease; Genomics; Glioma; Humans; Tumor Suppressor Proteins; Whole Genome Sequencing

A global catalog of whole-genome diversity from 233 primate species. - Kuderna, Lukas F K; Gao, Hong; Janiak, Mareike C; Kuhlwilm, Martin; Orkin, Joseph D; Bataillon, Thomas; Manu, Shivakumara; Valenzuela, Alejandro; Bergman, Juraj; Rousselle, Marjolaine; Silva, Felipe Ennes; Agueda, Lidia; et al. (Science, 2023)
The rich diversity of morphology and behavior displayed across primate species provides an informative context in which to study the impact of genomic diversity on fundamental biological processes. Analysis of that diversity provides insight into long-standing questions in evolutionary and conservation biology and is urgent given severe threats these species are facing. Here, we present high-coverage whole-genome data from 233 primate species representing 86% of genera and all 16 families. This dataset was used, together with fossil calibration, to create a nuclear DNA phylogeny and to reassess evolutionary divergence times among primate clades. We found within-species genetic diversity across families and geographic regions to be associated with climate and sociality, but not with extinction risk. Furthermore, mutation rates differ across species, potentially influenced by effective population sizes. Lastly, we identified extensive recurrence of missense mutations previously thought to be human specific. This study will open a wide range of research avenues for future primate genomic research.
Keywords: Animals; Biological Evolution; Genetic Variation; Genome; Humans; Mutation Rate; Phylogeny; Population Density; Primates

Hemizygous variants in protein phosphatase 1 regulatory subunit 3F (PPP1R3F) are associated with a neurodevelopmental disorder characterized by developmental delay, intellectual disability and autistic features. - Liu, Zhigang; Xin, Baozhong; Smith, Iris N; Sency, Valerie; Szekely, Julia; Alkelai, Anna; Shuldiner, Alan; Efthymiou, Stephanie; Rajabi, Farrah; Coury, Stephanie; Brownstein, Catherine A; Rudnik-Schöneborn, Sabine; et al. (Hum Mol Genet, 2023)
Protein phosphatase 1 regulatory subunit 3F (PPP1R3F) is a member of the glycogen targeting subunits (GTSs), which belong to the large group of regulatory subunits of protein phosphatase 1 (PP1), a major eukaryotic serine/threonine protein phosphatase that regulates diverse cellular processes. Here, we describe the identification of hemizygous variants in PPP1R3F associated with a novel X-linked recessive neurodevelopmental disorder in 13 unrelated individuals. This disorder is characterized by developmental delay, mild intellectual disability, neurobehavioral issues such as autism spectrum disorder, seizures and other neurological findings including tone, gait and cerebellar abnormalities. PPP1R3F variants segregated with disease in affected hemizygous males that inherited the variants from their heterozygous carrier mothers. We show that PPP1R3F is predominantly expressed in brain astrocytes and localizes to the endoplasmic reticulum in cells. Glycogen content in PPP1R3F knockout astrocytoma cells appears to be more sensitive to fluxes in extracellular glucose levels than in wild-type cells, suggesting that PPP1R3F functions in maintaining steady brain glycogen levels under changing glucose conditions. We performed functional studies on nine of the identified variants and observed defects in PP1 binding, protein stability, subcellular localization and regulation of glycogen metabolism in most of them. Collectively, the genetic and molecular data indicate that deleterious variants in PPP1R3F are associated with a new X-linked disorder of glycogen metabolism, highlighting the critical role of GTSs in neurological development. This research expands our understanding of neurodevelopmental disorders and the role of PP1 in brain development and proper function.
Keywords: Autism Spectrum Disorder; Autistic Disorder; Glucose; Glycogen; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Protein Phosphatase 1

HMZDupFinder: a robust computational approach for detecting intragenic homozygous duplications from exome sequencing data. - Du, Haowei; Dardas, Zain; Jolly, Angad; Grochowski, Christopher M; Jhangiani, Shalini N; Li, He; Donna M Muzny; Fatih, Jawid M; Yesil, Gozde; Elcioglu, Nursel H; Gezdirici, Alper; Marafi, Dana; et al. (Nucleic Acids Res, 2023)
Homozygous duplications contribute to genetic disease by altering gene dosage or disrupting gene regulation and can be more deleterious to organismal biology than heterozygous duplications. Intragenic exonic duplications can result in loss-of-function (LoF) or gain-of-function (GoF) alleles that when homozygosed, i.e. brought to homozygous state at a locus by identity by descent or state, could potentially result in autosomal recessive (AR) rare disease traits. However, the detection and functional interpretation of homozygous duplications from exome sequencing data remains a challenge. We developed a framework algorithm, HMZDupFinder, that is designed to detect exonic homozygous duplications from exome sequencing (ES) data. The HMZDupFinder algorithm can efficiently process large datasets and accurately identifies small intragenic duplications, including those associated with rare disease traits. HMZDupFinder called 965 homozygous duplications with three or less exons from 8,707 ES with a recall rate of 70.9% and a precision of 16.1%. We experimentally confirmed 8/10 rare homozygous duplications. Pathogenicity assessment of these copy number variant alleles allowed clinical genomics contextualization for three homozygous duplications alleles, including two affecting known OMIM disease genes EDAR (MIM# 224900), TNNT1(MIM# 605355), and one variant in a novel candidate disease gene: PAAF1.

Identification of allele-specific KIV-2 repeats and impact on Lp(a) measurements for cardiovascular disease risk. - Behera, S; Belyeu, J R; Chen, X; Paulin, L F; Nguyen, N Q H; Newman, E; Mahmoud, M; Menon, V K; Qi, Q; Joshi, P; Marcovina, S; Rossi, M; et al. (bioRxiv, 2023)
The abundance of Lp(a) protein holds significant implications for the risk of cardiovascular disease (CVD), which is directly impacted by the copy number (CN) of KIV-2, a 5.5 kbp sub-region. KIV-2 is highly polymorphic in the population and accurate analysis is challenging. In this study, we present the DRAGEN KIV-2 CN caller, which utilizes short reads. Data across 166 WGS show that the caller has high accuracy, compared to optical mapping and can further phase ~50% of the samples. We compared KIV-2 CN numbers to 24 previously postulated KIV-2 relevant SNVs, revealing that many are ineffective predictors of KIV-2 copy number. Population studies, including USA-based cohorts, showed distinct KIV-2 CN, distributions for European-, African-, and Hispanic-American populations and further underscored the limitations of SNV predictors. We demonstrate that the CN estimates correlate significantly with the available Lp(a) protein levels and that phasing is highly important.

Intratumoral Heterogeneity and Clonal Evolution Induced by HPV Integration. - Akagi, Keiko; Symer, David E; Mahmoud, Medhat; Jiang, Bo; Goodwin, Sara; Wangsa, Darawalee; Li, Zhengke; Xiao, Weihong; Dunn, Joe Dan; Ried, Thomas; Coombes, Kevin R; Fritz J Sedlazeck; et al. (Cancer Discov, 2023)
UNLABELLED: The human papillomavirus (HPV) genome is integrated into host DNA in most HPV-positive cancers, but the consequences for chromosomal integrity are unknown. Continuous long-read sequencing of oropharyngeal cancers and cancer cell lines identified a previously undescribed form of structural variation, "heterocateny," characterized by diverse, interrelated, and repetitive patterns of concatemerized virus and host DNA segments within a cancer. Unique breakpoints shared across structural variants facilitated stepwise reconstruction of their evolution from a common molecular ancestor. This analysis revealed that virus and virus-host concatemers are unstable and, upon insertion into and excision from chromosomes, facilitate capture, amplification, and recombination of host DNA and chromosomal rearrangements. Evidence of heterocateny was detected in extrachromosomal and intrachromosomal DNA. These findings indicate that heterocateny is driven by the dynamic, aberrant replication and recombination of an oncogenic DNA virus, thereby extending known consequences of HPV integration to include promotion of intratumoral heterogeneity and clonal evolution. SIGNIFICANCE: Long-read sequencing of HPV-positive cancers revealed "heterocateny," a previously unreported form of genomic structural variation characterized by heterogeneous, interrelated, and repetitive genomic rearrangements within a tumor. Heterocateny is driven by unstable concatemerized HPV genomes, which facilitate capture, rearrangement, and amplification of host DNA, and promotes intratumoral heterogeneity and clonal evolution. See related commentary by McBride and White, p. 814. This article is highlighted in the In This Issue feature, p. 799.
Keywords: Clonal Evolution; Gene Rearrangement; Human Papillomavirus Viruses; Humans; Oropharyngeal Neoplasms; Papillomaviridae; Papillomavirus Infections; Virus Integration

Investigating Gene-Diet Interactions Impacting the Association Between Macronutrient Intake and Glycemic Traits. - Westerman, Kenneth E; Walker, Maura E; Gaynor, Sheila M; Wessel, Jennifer; DiCorpo, Daniel; Ma, Jiantao; Alonso, Alvaro; Aslibekyan, Stella; Baldridge, Abigail S; Bertoni, Alain G; Biggs, Mary L; Brody, Jennifer A; et al. (Diabetes, 2023)
UNLABELLED: Few studies have demonstrated reproducible gene-diet interactions (GDIs) impacting metabolic disease risk factors, likely due in part to measurement error in dietary intake estimation and insufficient capture of rare genetic variation. We aimed to identify GDIs across the genetic frequency spectrum impacting the macronutrient-glycemia relationship in genetically and culturally diverse cohorts. We analyzed 33,187 participants free of diabetes from 10 National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program cohorts with whole-genome sequencing, self-reported diet, and glycemic trait data. We fit cohort-specific, multivariable-adjusted linear mixed models for the effect of diet, modeled as an isocaloric substitution of carbohydrate for fat, and its interactions with common and rare variants genome-wide. In main effect meta-analyses, participants consuming more carbohydrate had modestly lower glycemic trait values (e.g., for glycated hemoglobin [HbA1c], -0.013% HbA1c/250 kcal substitution). In GDI meta-analyses, a common African ancestry-enriched variant (rs79762542) reached study-wide significance and replicated in the UK Biobank cohort, indicating a negative carbohydrate-HbA1c association among major allele homozygotes only. Simulations revealed that >150,000 samples may be necessary to identify similar macronutrient GDIs under realistic assumptions about effect size and measurement error. These results generate hypotheses for further exploration of modifiable metabolic disease risk in additional cohorts with African ancestry. ARTICLE HIGHLIGHTS: We aimed to identify genetic modifiers of the dietary macronutrient-glycemia relationship using whole-genome sequence data from 10 Trans-Omics for Precision Medicine program cohorts. Substitution models indicated a modest reduction in glycemia associated with an increase in dietary carbohydrate at the expense of fat. Genome-wide interaction analysis identified one African ancestry-enriched variant near the FRAS1 gene that may interact with macronutrient intake to influence hemoglobin A1c. Simulation-based power calculations accounting for measurement error suggested that substantially larger sample sizes may be necessary to discover further gene-macronutrient interactions.
Keywords: Diabetes Mellitus; Diet; Eating; Genome-Wide Association Study; Glycated Hemoglobin; Guanine Nucleotide Dissociation Inhibitors; Humans

The landscape of tolerated genetic variation in humans and primates. - Gao, Hong; Hamp, Tobias; Ede, Jeffrey; Schraiber, Joshua G; McRae, Jeremy; Singer-Berk, Moriel; Yang, Yanshen; Dietrich, Anastasia S D; Fiziev, Petko P; Kuderna, Lukas F K; Sundaram, Laksshman; Wu, Yibing; et al. (Science, 2023)
Personalized genome sequencing has revealed millions of genetic differences between individuals, but our understanding of their clinical relevance remains largely incomplete. To systematically decipher the effects of human genetic variants, we obtained whole-genome sequencing data for 809 individuals from 233 primate species and identified 4.3 million common protein-altering variants with orthologs in humans. We show that these variants can be inferred to have nondeleterious effects in humans based on their presence at high allele frequencies in other primate populations. We use this resource to classify 6% of all possible human protein-altering variants as likely benign and impute the pathogenicity of the remaining 94% of variants with deep learning, achieving state-of-the-art accuracy for diagnosing pathogenic variants in patients with genetic diseases.
Keywords: Animals; Base Sequence; Gene Frequency; Genetic Variation; Humans; Primates; Whole Genome Sequencing

The landscape of tolerated genetic variation in humans and primates. - Gao, Hong; Hamp, Tobias; Ede, Jeffrey; Schraiber, Joshua G; McRae, Jeremy; Singer-Berk, Moriel; Yang, Yanshen; Dietrich, Anastasia; Fiziev, Petko; Kuderna, Lukas; Sundaram, Laksshman; Wu, Yibing; et al. (bioRxiv, 2023)
UNLABELLED: Personalized genome sequencing has revealed millions of genetic differences between individuals, but our understanding of their clinical relevance remains largely incomplete. To systematically decipher the effects of human genetic variants, we obtained whole genome sequencing data for 809 individuals from 233 primate species, and identified 4.3 million common protein-altering variants with orthologs in human. We show that these variants can be inferred to have non-deleterious effects in human based on their presence at high allele frequencies in other primate populations. We use this resource to classify 6% of all possible human protein-altering variants as likely benign and impute the pathogenicity of the remaining 94% of variants with deep learning, achieving state-of-the-art accuracy for diagnosing pathogenic variants in patients with genetic diseases. ONE SENTENCE SUMMARY: Deep learning classifier trained on 4.3 million common primate missense variants predicts variant pathogenicity in humans.

Monoallelic variation in DHX9, the gene encoding the DExH-box helicase DHX9, underlies neurodevelopment disorders and Charcot-Marie-Tooth disease. - Calame, Daniel G; Guo, Tianyu; Wang, Chen; Garrett, Lillian; Jolly, Angad; Dawood, Moez; Kurolap, Alina; Henig, Noa Zunz; Fatih, Jawid M; Herman, Isabella; Du, Haowei; Mitani, Tadahiro; et al. (Am J Hum Genet, 2023)
DExD/H-box RNA helicases (DDX/DHX) are encoded by a large paralogous gene family; in a subset of these human helicase genes, pathogenic variation causes neurodevelopmental disorder (NDD) traits and cancer. DHX9 encodes a BRCA1-interacting nuclear helicase regulating transcription, R-loops, and homologous recombination and exhibits the highest mutational constraint of all DDX/DHX paralogs but remains unassociated with disease traits in OMIM. Using exome sequencing and family-based rare-variant analyses, we identified 20 individuals with de novo, ultra-rare, heterozygous missense or loss-of-function (LoF) DHX9 variant alleles. Phenotypes ranged from NDDs to the distal symmetric polyneuropathy axonal Charcot-Marie-Tooth disease (CMT2). Quantitative Human Phenotype Ontology (HPO) analysis demonstrated genotype-phenotype correlations with LoF variants causing mild NDD phenotypes and nuclear localization signal (NLS) missense variants causing severe NDD. We investigated DHX9 variant-associated cellular phenotypes in human cell lines. Whereas wild-type DHX9 was restricted to the nucleus, NLS missense variants abnormally accumulated in the cytoplasm. Fibroblasts from an individual with an NLS variant also showed abnormal cytoplasmic DHX9 accumulation. CMT2-associated missense variants caused aberrant nucleolar DHX9 accumulation, a phenomenon previously associated with cellular stress. Two NDD-associated variants, p.Gly411Glu and p.Arg761Gln, altered DHX9 ATPase activity. The severe NDD-associated variant p.Arg141Gln did not affect DHX9 localization but instead increased R-loop levels and double-stranded DNA breaks. Dhx9 mice exhibited hypoactivity in novel environments, tremor, and sensorineural hearing loss. All together, these results establish DHX9 as a critical regulator of mammalian neurodevelopment and neuronal homeostasis.
Keywords: Animals; Cell Line; Charcot-Marie-Tooth Disease; DEAD-box RNA Helicases; Dichlorodiphenyl Dichloroethylene; DNA Helicases; Humans; Mammals; Mice; Neoplasm Proteins; Neurodevelopmental Disorders

Novel LSS variants in alopecia and intellectual disability syndrome: New case report and clinical spectrum of LSS-related rare disease traits. - Elbendary, Hasnaa M; Marafi, Dana; Saad, Ahmed K; Elhossini, Rasha; Duan, Ruizhi; Rafat, Karima; Jhangiani, Shalini N; Richard A Gibbs; Pehlivan, Davut; Calame, Daniel G; Posey, Jennifer E; James R Lupski; et al. (Clin Genet, 2023)
Pathogenic biallelic variants in LSS are associated with three Mendelian rare disease traits including congenital cataract type 44, autosomal recessive hypotrichosis type 14, and alopecia-intellectual disability syndrome type 4 (APMR4). We performed trio research exome sequencing on a family with a four-year-old male with global developmental delay, epilepsy and striking alopecia, and identified novel compound heterozygous LSS splice site (c.14+2T>C) and missense (c.1357 G>A; p.V453L) variant alleles. Rare features associated with APMR4 such as cryptorchidism, micropenis, mild cortical brain atrophy and thin corpus callosum were detected. Previously unreported APMR4 findings including cerebellar involvement in the form of unsteady ataxic gait, small vermis with prominent folia, were noted. A review of all reported variants to date in 29 families with LSS-related phenotypes showed an emerging genotype-phenotype correlation. Our report potentially expands LSS-related phenotypic spectrum and highlights the importance of performing brain imaging in LSS-related conditions.
Keywords: Alopecia; Humans; Intellectual Disability; Male; Mutation; Phenotype; Rare Diseases; Syndrome

Novel pathogenic variant in Iranian familial with inherited retinal dystrophies: genotype-phenotype correlation. - Fu, Shangyi; Fu, Jiewen; Mobasher-Jannat, Abdolkarim; Jadidi, Khosrow; Yumei Li; Rui Chen; Imani, Saber; Cheng, Jingliang (3 Biotech, 2023)
Inherited retinal dystrophies (IRDs) include a large chronic heterogeneity genetic disease. While many disease-causing pathogenic variants were involved in the progression of IRD, the Ceramide Kinase Like () gene variant in Iranian patients is not well characterized. In this study, a consanguineous Iranian family with three generations was recruited whom presented with the clinical diagnosis of autosomal recessive IRD. By targeted next-generation sequencing (TGS) and Sanger sequencing, the proband was found to have a novel, pathological homozygous deletion variant c.560_568del (p.187_190del) of the gene (NM_001030311.2) that co-segregated with the disease in all affected family members. The is highly expressed in the later four developmental retinal stages, playing a vital role in retina degeneration. Therefore, the identification of a novel, homozygous deletion variant c.560_568del (p.187_190del) in an IRD familial cohort descent provides insights into the molecular pathogenesis of IRD and facilitates genetic counseling and disease prediction.

PLS3 missense variants affecting the actin-binding domains cause X-linked congenital diaphragmatic hernia and body-wall defects. - Petit, Florence; Longoni, Mauro; Wells, Julie; Maser, Richard S; Bogenschutz, Eric L; Dysart, Matthew J; Contreras, Hannah T M; Frénois, Frederic; Pober, Barbara R; Clark, Robin D; Giampietro, Philip F; Ropers, Hilger H; et al. (Am J Hum Genet, 2023)
Congenital diaphragmatic hernia (CDH) is a relatively common and genetically heterogeneous structural birth defect associated with high mortality and morbidity. We describe eight unrelated families with an X-linked condition characterized by diaphragm defects, variable anterior body-wall anomalies, and/or facial dysmorphism. Using linkage analysis and exome or genome sequencing, we found that missense variants in plastin 3 (PLS3), a gene encoding an actin bundling protein, co-segregate with disease in all families. Loss-of-function variants in PLS3 have been previously associated with X-linked osteoporosis (MIM: 300910), so we used in silico protein modeling and a mouse model to address these seemingly disparate clinical phenotypes. The missense variants in individuals with CDH are located within the actin-binding domains of the protein but are not predicted to affect protein structure, whereas the variants in individuals with osteoporosis are predicted to result in loss of function. A mouse knockin model of a variant identified in one of the CDH-affected families, c.1497G>C (p.Trp499Cys), shows partial perinatal lethality and recapitulates the key findings of the human phenotype, including diaphragm and abdominal-wall defects. Both the mouse model and one adult human male with a CDH-associated PLS3 variant were observed to have increased rather than decreased bone mineral density. Together, these clinical and functional data in humans and mice reveal that specific missense variants affecting the actin-binding domains of PLS3 might have a gain-of-function effect and cause a Mendelian congenital disorder.
Keywords: Actins; Adult; Animals; Hernias, Diaphragmatic, Congenital; Humans; Male; Mice; Mutation, Missense; Osteoporosis

Proteomic Analysis Identifies Circulating Proteins Associated With Plasma Amyloid-β and Incident Dementia. - Tin, Adrienne; Sullivan, Kevin J; Walker, Keenan A; Bressler, Jan; Talluri, Rajesh; Yu, Bing; Simino, Jeanette; Gudmundsdottir, Valborg; Emilsson, Valur; Jennings, Lori L; Launer, Lenore; Mei, Hao; et al. (Biol Psychiatry Glob Open Sci, 2023)
BACKGROUND: Plasma amyloid-β (Aβ) (Aβ, Aβ, and Aβ/Aβ), biomarkers of the Alzheimer's form of dementia, are under consideration for clinical use. The associations of these peptides with circulating proteins may identify novel plasma biomarkers of dementia and inform peripheral factors influencing the levels of these peptides. METHODS: We analyzed the association of these 3 plasma Aβ measures with 4638 circulating proteins among a subset of the participants of the Atherosclerosis Risk in Communities (ARIC) study (midlife:  = 1955; late life:  = 2082), related the Aβ-associated proteins with incident dementia in the overall ARIC cohort (midlife:  = 11,069, late life:  = 4110) with external replication in the Age, Gene/Environment Susceptibility (AGES)-Reykjavik Study ( = 4973), estimated the proportion of Aβ variance explained, and conducted enrichment analyses to characterize the proteins associated with the plasma Aβ peptides. RESULTS: At midlife, of the 296 Aβ-associated proteins, 8 were associated with incident dementia from midlife and late life in the ARIC study, and NPPB, IBSP, and THBS2 were replicated in the AGES-Reykjavik Study. At late life, of the 34 Aβ-associated proteins, none were associated with incident dementia at midlife, and kidney function explained 10%, 12%, and 0.2% of the variance of Aβ, Aβ, and Aβ/Aβ, respectively. Aβ42-associated proteins at midlife were found to be enriched in the liver, and those at late life were found to be enriched in the spleen. CONCLUSIONS: This study identifies circulating proteins associated with plasma Aβ levels and incident dementia and informs peripheral factors associated with plasma Aβ levels.

Rare variant enrichment analysis supports as a contributory driver gene in the etiology of Mayer-Rokitansky-Küster-Hauser syndrome. - Jolly, Angad; Du, Haowei; Borel, Christelle; Chen, Na; Zhao, Sen; Grochowski, Christopher M; Duan, Ruizhi; Fatih, Jawid M; Dawood, Moez; Salvi, Sejal; Jhangiani, Shalini N; Donna M Muzny; et al. (HGG Adv, 2023)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is characterized by aplasia of the female reproductive tract; the syndrome can include renal anomalies, absence or dysgenesis, and skeletal anomalies. While functional models have elucidated several candidate genes, only (MIM: 603490) variants have been definitively associated with a subtype of MRKH with hyperandrogenism (MIM: 158330). DNA from 148 clinically diagnosed MRKH probands across 144 unrelated families and available family members from North America, Europe, and South America were exome sequenced (ES) and by family-based genomics analyzed for rare likely deleterious variants. A replication cohort consisting of 442 Han Chinese individuals with MRKH was used to further reproduce findings in diverse genetic backgrounds. Proband and OMIM phenotypes annotated using the Human Phenotype Ontology were analyzed to quantitatively delineate the phenotypic spectrum associated with variant alleles found in our MRKH cohort and those previously published. This study reports 18 novel variant alleles, 16 within a multiethnic MRKH cohort and two within a congenital scoliosis cohort. Cohort-wide analyses for a burden of rare variants within a single gene identified likely damaging variants in (MIM: 617782), a known disease gene for renal hypoplasia and uterine abnormalities (MIM: 617805), in 16 of 590 MRKH probands. variant alleles, including a CNV null allele, were found in 8 MRKH type 1 probands and 8 MRKH type II probands. This study used quantitative phenotypic analyses in a worldwide multiethnic cohort to identify and strengthen the association of to isolated uterine agenesis (MRKH type I) and syndromic MRKH type II.
Keywords: 46, XX Disorders of Sex Development; Female; Humans; Urogenital Abnormalities; Uterus

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed whole-genome sequencing study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (Am J Hum Genet, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions in lipid metabolism. Large-scale whole-genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess more associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with measurement of blood lipids and lipoproteins (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare-variant aggregate association tests using the STAAR (variant-set test for association using annotation information) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare-coding variants in nearby protein-coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500-kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variation and rare protein-coding variation at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNAs.
Keywords: Genome-Wide Association Study; Humans; Lipids; Polymorphism, Single Nucleotide; Precision Medicine; RNA, Long Noncoding; Whole Genome Sequencing

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

Scalable Nanopore sequencing of human genomes provides a comprehensive view of haplotype-resolved variation and methylation. - Kolmogorov, Mikhail; Billingsley, Kimberley J; Mastoras, Mira; Meredith, Melissa; Monlong, Jean; Lorig-Roach, Ryan; Asri, Mobin; Alvarez Jerez, Pilar; Malik, Laksh; Dewan, Ramita; Reed, Xylena; Genner, Rylee M; et al. (Nat Methods, 2023)
Long-read sequencing technologies substantially overcome the limitations of short-reads but have not been considered as a feasible replacement for population-scale projects, being a combination of too expensive, not scalable enough or too error-prone. Here we develop an efficient and scalable wet lab and computational protocol, Napu, for Oxford Nanopore Technologies long-read sequencing that seeks to address those limitations. We applied our protocol to cell lines and brain tissue samples as part of a pilot project for the National Institutes of Health Center for Alzheimer's and Related Dementias. Using a single PromethION flow cell, we can detect single nucleotide polymorphisms with F1-score comparable to Illumina short-read sequencing. Small indel calling remains difficult within homopolymers and tandem repeats, but achieves good concordance to Illumina indel calls elsewhere. Further, we can discover structural variants with F1-score on par with state-of-the-art de novo assembly methods. Our protocol phases small and structural variants at megabase scales and produces highly accurate, haplotype-specific methylation calls.
Keywords: Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Humans; Methylation; Nanopore Sequencing; Pilot Projects; Sequence Analysis, DNA

Scalable Nanopore sequencing of human genomes provides a comprehensive view of haplotype-resolved variation and methylation. - Kolmogorov, Mikhail; Billingsley, Kimberley J; Mastoras, Mira; Meredith, Melissa; Monlong, Jean; Lorig-Roach, Ryan; Asri, Mobin; Jerez, Pilar Alvarez; Malik, Laksh; Dewan, Ramita; Reed, Xylena; Genner, Rylee M; et al. (bioRxiv, 2023)
Long-read sequencing technologies substantially overcome the limitations of short-reads but to date have not been considered as feasible replacement at scale due to a combination of being too expensive, not scalable enough, or too error-prone. Here, we develop an efficient and scalable wet lab and computational protocol for Oxford Nanopore Technologies (ONT) long-read sequencing that seeks to provide a genuine alternative to short-reads for large-scale genomics projects. We applied our protocol to cell lines and brain tissue samples as part of a pilot project for the NIH Center for Alzheimer's and Related Dementias (CARD). Using a single PromethION flow cell, we can detect SNPs with F1-score better than Illumina short-read sequencing. Small indel calling remains to be difficult inside homopolymers and tandem repeats, but is comparable to Illumina calls elsewhere. Further, we can discover structural variants with F1-score comparable to state-of the-art methods involving Pacific Biosciences HiFi sequencing and trio information (but at a lower cost and greater throughput). Using ONT based phasing, we can then combine and phase small and structural variants at megabase scales. Our protocol also produces highly accurate, haplotype-specific methylation calls. Overall, this makes large-scale long-read sequencing projects feasible; the protocol is currently being used to sequence thousands of brain-based genomes as a part of the NIH CARD initiative. We provide the protocol and software as open-source integrated pipelines for generating phased variant calls and assemblies.

Single-cell somatic copy number variants in brain using different amplification methods and reference genomes. - Kalef-Ezra, Ester; Turan, Zeliha Gozde; Perez-Rodriguez, Diego; Bomann, Ida; Behera, Sairam; Morley, Caoimhe; Scholz, Sonja W; Jaunmuktane, Zane; Demeulemeester, Jonas; Fritz J Sedlazeck; Proukakis, Christos (bioRxiv, 2023)
The presence of somatic mutations, including copy number variants (CNVs), in the brain is well recognized. Comprehensive study requires single-cell whole genome amplification, with several methods available, prior to sequencing. We compared PicoPLEX with two recent adaptations of multiple displacement amplification (MDA): primary template-directed amplification (PTA) and droplet MDA, across 93 human brain cortical nuclei. We demonstrated different properties for each, with PTA providing the broadest amplification, PicoPLEX the most even, and distinct chimeric profiles. Furthermore, we performed CNV calling on two brains with multiple system atrophy and one control brain using different reference genomes. We found that 38% of brain cells have at least one Mb-scale CNV, with some supported by bulk sequencing or single-cells from other brain regions. Our study highlights the importance of selecting whole genome amplification method and reference genome for CNV calling, while supporting the existence of somatic CNVs in healthy and diseased human brain.

Single-nucleotide variant calling in single-cell sequencing data with Monopogen. - Dou, Jinzhuang; Tan, Yukun; Kock, Kian Hong; Wang, Jun; Cheng, Xuesen; Tan, Le Min; Han, Kyung Yeon; Hon, Chung-Chau; Park, Woong-Yang; Shin, Jay W; Jin, Haijing; Wang, Yujia; et al. (Nat Biotechnol, 2023)
Single-cell omics technologies enable molecular characterization of diverse cell types and states, but how the resulting transcriptional and epigenetic profiles depend on the cell's genetic background remains understudied. We describe Monopogen, a computational tool to detect single-nucleotide variants (SNVs) from single-cell sequencing data. Monopogen leverages linkage disequilibrium from external reference panels to identify germline SNVs and detects putative somatic SNVs using allele cosegregating patterns at the cell population level. It can identify 100 K to 3 M germline SNVs achieving a genotyping accuracy of 95%, together with hundreds of putative somatic SNVs. Monopogen-derived genotypes enable global and local ancestry inference and identification of admixed samples. It identifies variants associated with cardiomyocyte metabolic levels and epigenomic programs. It also improves putative somatic SNV detection that enables clonal lineage tracing in primary human clonal hematopoiesis. Monopogen brings together population genetics, cell lineage tracing and single-cell omics to uncover genetic determinants of cellular processes.

SRSF1 haploinsufficiency is responsible for a syndromic developmental disorder associated with intellectual disability. - Bogaert, Elke; Garde, Aurore; Gautier, Thierry; Rooney, Kathleen; Duffourd, Yannis; LeBlanc, Pontus; van Reempts, Emma; Tran Mau-Them, Frederic; Wentzensen, Ingrid M; Au, Kit Sing; Richardson, Kate; Northrup, Hope; et al. (Am J Hum Genet, 2023)
SRSF1 (also known as ASF/SF2) is a non-small nuclear ribonucleoprotein (non-snRNP) that belongs to the arginine/serine (R/S) domain family. It recognizes and binds to mRNA, regulating both constitutive and alternative splicing. The complete loss of this proto-oncogene in mice is embryonically lethal. Through international data sharing, we identified 17 individuals (10 females and 7 males) with a neurodevelopmental disorder (NDD) with heterozygous germline SRSF1 variants, mostly de novo, including three frameshift variants, three nonsense variants, seven missense variants, and two microdeletions within region 17q22 encompassing SRSF1. Only in one family, the de novo origin could not be established. All individuals featured a recurrent phenotype including developmental delay and intellectual disability (DD/ID), hypotonia, neurobehavioral problems, with variable skeletal (66.7%) and cardiac (46%) anomalies. To investigate the functional consequences of SRSF1 variants, we performed in silico structural modeling, developed an in vivo splicing assay in Drosophila, and carried out episignature analysis in blood-derived DNA from affected individuals. We found that all loss-of-function and 5 out of 7 missense variants were pathogenic, leading to a loss of SRSF1 splicing activity in Drosophila, correlating with a detectable and specific DNA methylation episignature. In addition, our orthogonal in silico, in vivo, and epigenetics analyses enabled the separation of clearly pathogenic missense variants from those with uncertain significance. Overall, these results indicated that haploinsufficiency of SRSF1 is responsible for a syndromic NDD with ID due to a partial loss of SRSF1-mediated splicing activity.
Keywords: Child; Developmental Disabilities; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype

StocSum: stochastic summary statistics for whole genome sequencing studies. - Wang, Nannan; Yu, Bing; Jun, Goo; Qi, Qibin; Durazo-Arvizu, Ramon A; Lindström, Sara; Morrison, Alanna C; Kaplan, Robert C; Eric Boerwinkle; Chen, Han (bioRxiv, 2023)
Genomic summary statistics, usually defined as single-variant test results from genome-wide association studies, have been widely used to advance the genetics field in a wide range of applications. Applications that involve multiple genetic variants also require their correlations or linkage disequilibrium (LD) information, often obtained from an external reference panel. In practice, it is usually difficult to find suitable external reference panels that represent the LD structure for underrepresented and admixed populations, or rare genetic variants from whole genome sequencing (WGS) studies, limiting the scope of applications for genomic summary statistics. Here we introduce StocSum, a novel reference-panel-free statistical framework for generating, managing, and analyzing stochastic summary statistics using random vectors. We develop various downstream applications using StocSum including single-variant tests, conditional association tests, gene-environment interaction tests, variant set tests, as well as meta-analysis and LD score regression tools. We demonstrate the accuracy and computational efficiency of StocSum using two cohorts from the Trans-Omics for Precision Medicine Program. StocSum will facilitate sharing and utilization of genomic summary statistics from WGS studies, especially for underrepresented and admixed populations.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Kwak, Soo Heon; Chen, Han; Li, Xihao; Di Corpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.
Keywords: Atherosclerosis; Carotid Intima-Media Thickness; Coronary Artery Disease; Diabetes Mellitus, Type 2; Genomics; Humans; Plaque, Atherosclerotic; Risk Factors

Whole Genome Analysis of Venous Thromboembolism: the Trans-Omics for Precision Medicine Program. - Seyerle, Amanda A; Laurie, Cecelia A; Coombes, Brandon J; Jain, Deepti; Conomos, Matthew P; Brody, Jennifer; Chen, Ming-Huei; Gogarten, Stephanie M; Beutel, Kathleen M; Gupta, Namrata; Heckbert, Susan R; Jackson, Rebecca D; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Risk for venous thromboembolism has a strong genetic component. Whole genome sequencing from the TOPMed program (Trans-Omics for Precision Medicine) allowed us to look for new associations, particularly rare variants missed by standard genome-wide association studies. METHODS: The 3793 cases and 7834 controls (11.6% of cases were individuals of African, Hispanic/Latino, or Asian ancestry) were analyzed using a single variant approach and an aggregate gene-based approach using our primary filter (included only loss-of-function and missense variants predicted to be deleterious) and our secondary filter (included all missense variants). RESULTS: Single variant analyses identified associations at 5 known loci. Aggregate gene-based analyses identified only (odds ratio, 6.2 for carriers of rare variants; =7.4×10) when using our primary filter. Employing our secondary variant filter led to a smaller effect size at (odds ratio, 3.8; =1.6×10), while excluding variants found only in rare isoforms led to a larger one (odds ratio, 7.5). Different filtering strategies improved the signal for 2 other known genes: became significant (minimum =1.8×10 with the secondary filter), while did not (minimum =4.4×10 with minor allele frequency <0.0005). Results were largely the same when restricting the analyses to include only unprovoked cases; however, one novel gene, , became significant (=4.4×10 using all missense variants with minor allele frequency <0.0005). CONCLUSIONS: Here, we have demonstrated the importance of using multiple variant filtering strategies, as we detected additional genes when filtering variants based on their predicted deleteriousness, frequency, and presence on the most expressed isoforms. Our primary analyses did not identify new candidate loci; thus larger follow-up studies are needed to replicate the novel locus and to identify additional rare variation associated with venous thromboembolism.
Keywords: Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Precision Medicine; Venous Thromboembolism

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Apolipoprotein E Polymorphism, Cardiac Remodeling, and Heart Failure in the ARIC Study. - Selvaraj, Senthil; Claggett, Brian; Johansen, Michelle C; Cunningham, Jonathan W; Gottesman, Rebecca F; Yu, Bing; Eric Boerwinkle; Mosley, Thomas H; Shah, Amil M; Solomon, Scott D (J Card Fail, 2022)
BACKGROUND: β-Amyloid has recently been discovered in the myocardium of patients with Alzheimer's disease (AD). Whether genetic variation in apolipoprotein E (APOE) ɛ4, a common variant associated with Alzheimer's disease, is associated with incident heart failure (HF), N-terminal pro-B-type natriuretic peptide (NT-proBNP), and cardiac structure and function is unknown. METHODS AND RESULTS: We studied 15,064 White and Black participants in the Atherosclerosis Risk in Communities, relating genotype status at visit 1 (1987-1989) to incident HF hospitalization using Cox regression. At visits 2, 4, and 5, we assessed NT-proBNP levels by genotype. At visits 3 and 5, we related Aβ peptides to incident HF. At visit 5 (2011-2013, n = 6251), we assessed the relationship of genotype with prevalent HF and echocardiographic parameters. The mean participant age was 54.7 ± 5.8 years, 45% were men, and 73% were White. At visit 5, there was no difference in prevalent HF by genotype. The APOE ε4 carriers did not have increased risk for HF hospitalization. The APOE ε4 genotype was not associated with cardiac structure and function or NT-proBNP levels. The Aβ peptides were not associated with incident HF after multivariable adjustment. CONCLUSIONS: A genetic predisposition to Alzheimer's disease through APOE ε4 is not associated with an increased prevalence of HF, HF hospitalization, myocardial remodeling, or biochemical evidence of HF.
Keywords: Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Biomarkers; Female; Heart Failure; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Ventricular Remodeling

Artificial Intelligence and Cardiovascular Genetics. - Krittanawong, Chayakrit; Johnson, Kipp W; Choi, Edward; Kaplin, Scott; Eric Venner; Mullai Murugan; Wang, Zhen; Glicksberg, Benjamin S; Amos, Christopher I; Schatz, Michael C; Tang, W H Wilson (Life (Basel), 2022)
Polygenic diseases, which are genetic disorders caused by the combined action of multiple genes, pose unique and significant challenges for the diagnosis and management of affected patients. A major goal of cardiovascular medicine has been to understand how genetic variation leads to the clinical heterogeneity seen in polygenic cardiovascular diseases (CVDs). Recent advances and emerging technologies in artificial intelligence (AI), coupled with the ever-increasing availability of next generation sequencing (NGS) technologies, now provide researchers with unprecedented possibilities for dynamic and complex biological genomic analyses. Combining these technologies may lead to a deeper understanding of heterogeneous polygenic CVDs, better prognostic guidance, and, ultimately, greater personalized medicine. Advances will likely be achieved through increasingly frequent and robust genomic characterization of patients, as well the integration of genomic data with other clinical data, such as cardiac imaging, coronary angiography, and clinical biomarkers. This review discusses the current opportunities and limitations of genomics; provides a brief overview of AI; and identifies the current applications, limitations, and future directions of AI in genomics.

Assessing Variant Causality and Severity Using Retinal Pigment Epithelial Cells Derived from Stargardt Disease Patients. - Matynia, Anna; Wang, Jun; Kim, Sangbae; Yumei Li; Dimashkie, Anupama; Jiang, Zhichun; Hu, Jane; Strom, Samuel P; Radu, Roxana A; Rui Chen; Gorin, Michael B (Transl Vis Sci Technol, 2022)
PURPOSE: Modern molecular genetics has revolutionized gene discovery, genetic diagnoses, and precision medicine yet many patients remain unable to benefit from these advances as disease-causing variants remain elusive for up to half of Mendelian genetic disorders. Patient-derived induced pluripotent stem (iPS) cells and transcriptomics were used to identify the fate of unsolved ABCA4 alleles in patients with Stargardt disease. METHODS: Multiple independent iPS lines were generated from skin biopsies of three patients with Stargardt disease harboring a single identified pathogenic ABCA4 variant. Derived retinal pigment epithelial cells (dRPE) from a normal control and patient cells were subjected to RNA-Seq on the Novaseq6000 platform, analyzed using DESeq2 with calculation of allele specific imbalance from the pathogenic or a known linked variant. Protein analysis was performed using the automated Simple Western system. RESULTS: Nine dRPE samples were generated, with transcriptome analysis on eight. Allele-specific expression indicated normal transcripts expressed from splice variants albeit at low levels, and missense transcripts expressed at near-normal levels. Corresponding protein was not easily detected. Patient phenotype correlation indicated missense variants expressed at high levels have more deleterious outcomes. Transcriptome analysis suggests mitochondrial membrane biodynamics and the unfolded protein response pathway may be relevant in Stargardt disease. CONCLUSIONS: Patient-specific iPS-derived RPE cells set the stage to assess non-expressing variants in difficult-to-detect genomic regions using easily biopsied tissue. TRANSLATIONAL RELEVANCE: This "Disease in a Dish" approach is likely to enhance the ability of patients to participate in and benefit from clinical trials while providing insights into perturbations in RPE biology.
Keywords: ATP-Binding Cassette Transporters; Epithelial Cells; Humans; Phenotype; Retinal Pigments; Stargardt Disease

Association of Pathogenic Variants in Hereditary Cancer Genes With Multiple Diseases. - Zeng, Chenjie; Bastarache, Lisa A; Tao, Ran; Eric Venner; Hebbring, Scott; Andujar, Justin D; Bland, Sarah T; Crosslin, David R; Pratap, Siddharth; Cooley, Ayorinde; Pacheco, Jennifer A; Christensen, Kurt D; et al. (JAMA Oncol, 2022)
IMPORTANCE: Knowledge about the spectrum of diseases associated with hereditary cancer syndromes may improve disease diagnosis and management for patients and help to identify high-risk individuals. OBJECTIVE: To identify phenotypes associated with hereditary cancer genes through a phenome-wide association study. DESIGN, SETTING, AND PARTICIPANTS: This phenome-wide association study used health data from participants in 3 cohorts. The Electronic Medical Records and Genomics Sequencing (eMERGEseq) data set recruited predominantly healthy individuals from 10 US medical centers from July 16, 2016, through February 18, 2018, with a mean follow-up through electronic health records (EHRs) of 12.7 (7.4) years. The UK Biobank (UKB) cohort recruited participants from March 15, 2006, through August 1, 2010, with a mean (SD) follow-up of 12.4 (1.0) years. The Hereditary Cancer Registry (HCR) recruited patients undergoing clinical genetic testing at Vanderbilt University Medical Center from May 1, 2012, through December 31, 2019, with a mean (SD) follow-up through EHRs of 8.8 (6.5) years. EXPOSURES: Germline variants in 23 hereditary cancer genes. Pathogenic and likely pathogenic variants for each gene were aggregated for association analyses. MAIN OUTCOMES AND MEASURES: Phenotypes in the eMERGEseq and HCR cohorts were derived from the linked EHRs. Phenotypes in UKB were from multiple sources of health-related data. RESULTS: A total of 214 020 participants were identified, including 23 544 in eMERGEseq cohort (mean [SD] age, 47.8 [23.7] years; 12 611 women [53.6%]), 187 234 in the UKB cohort (mean [SD] age, 56.7 [8.1] years; 104 055 [55.6%] women), and 3242 in the HCR cohort (mean [SD] age, 52.5 [15.5] years; 2851 [87.9%] women). All 38 established gene-cancer associations were replicated, and 19 new associations were identified. These included the following 7 associations with neoplasms: CHEK2 with leukemia (odds ratio [OR], 3.81 [95% CI, 2.64-5.48]) and plasma cell neoplasms (OR, 3.12 [95% CI, 1.84-5.28]), ATM with gastric cancer (OR, 4.27 [95% CI, 2.35-7.44]) and pancreatic cancer (OR, 4.44 [95% CI, 2.66-7.40]), MUTYH (biallelic) with kidney cancer (OR, 32.28 [95% CI, 6.40-162.73]), MSH6 with bladder cancer (OR, 5.63 [95% CI, 2.75-11.49]), and APC with benign liver/intrahepatic bile duct tumors (OR, 52.01 [95% CI, 14.29-189.29]). The remaining 12 associations with nonneoplastic diseases included BRCA1/2 with ovarian cysts (OR, 3.15 [95% CI, 2.22-4.46] and 3.12 [95% CI, 2.36-4.12], respectively), MEN1 with acute pancreatitis (OR, 33.45 [95% CI, 9.25-121.02]), APC with gastritis and duodenitis (OR, 4.66 [95% CI, 2.61-8.33]), and PTEN with chronic gastritis (OR, 15.68 [95% CI, 6.01-40.92]). CONCLUSIONS AND RELEVANCE: The findings of this genetic association study analyzing the EHRs of 3 large cohorts suggest that these new phenotypes associated with hereditary cancer genes may facilitate early detection and better management of cancers. This study highlights the potential benefits of using EHR data in genomic medicine.
Keywords: Acute Disease; Female; Gastritis; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Male; Neoplastic Syndromes, Hereditary; Pancreatitis

Best practices for the interpretation and reporting of clinical whole genome sequencing. - Austin-Tse, Christina A; Jobanputra, Vaidehi; Perry, Denise L; Bick, David; Taft, Ryan J; Eric Venner; Richard A Gibbs; Young, Ted; Barnett, Sarah; Belmont, John W; Boczek, Nicole; Chowdhury, Shimul; et al. (NPJ Genom Med, 2022)
Whole genome sequencing (WGS) shows promise as a first-tier diagnostic test for patients with rare genetic disorders. However, standards addressing the definition and deployment practice of a best-in-class test are lacking. To address these gaps, the Medical Genome Initiative, a consortium of leading health care and research organizations in the US and Canada, was formed to expand access to high quality clinical WGS by convening experts and publishing best practices. Here, we present best practice recommendations for the interpretation and reporting of clinical diagnostic WGS, including discussion of challenges and emerging approaches that will be critical to harness the full potential of this comprehensive test.

Biallelic variants in SLC38A3 encoding a glutamine transporter cause epileptic encephalopathy. - Marafi, Dana; Fatih, Jawid M; Kaiyrzhanov, Rauan; Ferla, Matteo P; Gijavanekar, Charul; Al-Maraghi, Aljazi; Liu, Ning; Sites, Emily; Alsaif, Hessa S; Al-Owain, Mohammad; Zakkariah, Mohamed; El-Anany, Ehab; et al. (Brain, 2022)
The solute carrier (SLC) superfamily encompasses >400 transmembrane transporters involved in the exchange of amino acids, nutrients, ions, metals, neurotransmitters and metabolites across biological membranes. SLCs are highly expressed in the mammalian brain; defects in nearly 100 unique SLC-encoding genes (OMIM: https://www.omim.org) are associated with rare Mendelian disorders including developmental and epileptic encephalopathy and severe neurodevelopmental disorders. Exome sequencing and family-based rare variant analyses on a cohort with neurodevelopmental disorders identified two siblings with developmental and epileptic encephalopathy and a shared deleterious homozygous splicing variant in SLC38A3. The gene encodes SNAT3, a sodium-coupled neutral amino acid transporter and a principal transporter of the amino acids asparagine, histidine, and glutamine, the latter being the precursor for the neurotransmitters GABA and glutamate. Additional subjects with a similar developmental and epileptic encephalopathy phenotype and biallelic predicted-damaging SLC38A3 variants were ascertained through GeneMatcher and collaborations with research and clinical molecular diagnostic laboratories. Untargeted metabolomic analysis was performed to identify novel metabolic biomarkers. Ten individuals from seven unrelated families from six different countries with deleterious biallelic variants in SLC38A3 were identified. Global developmental delay, intellectual disability, hypotonia, and absent speech were common features while microcephaly, epilepsy, and visual impairment were present in the majority. Epilepsy was drug-resistant in half. Metabolomic analysis revealed perturbations of glutamate, histidine, and nitrogen metabolism in plasma, urine, and CSF of selected subjects, potentially representing biomarkers of disease. Our data support the contention that SLC38A3 is a novel disease gene for developmental and epileptic encephalopathy and illuminate the likely pathophysiology of the disease as perturbations in glutamine homeostasis.
Keywords: Epilepsy, Generalized; Glutamine; Histidine; Humans; Metabolome; Nitrogen; Sodium-Calcium Exchanger

Biallelic Variants in the Ectonucleotidase ENTPD1 Cause a Complex Neurodevelopmental Disorder with Intellectual Disability, Distinct White Matter Abnormalities, and Spastic Paraplegia. - Calame, Daniel G; Herman, Isabella; Maroofian, Reza; Marshall, Aren E; Donis, Karina Carvalho; Fatih, Jawid M; Mitani, Tadahiro; Du, Haowei; Grochowski, Christopher M; Sousa, Sergio B; Gijavanekar, Charul; Bakhtiari, Somayeh; et al. (Ann Neurol, 2022)
OBJECTIVE: Human genomics established that pathogenic variation in diverse genes can underlie a single disorder. For example, hereditary spastic paraplegia is associated with >80 genes, with frequently only few affected individuals described for each gene. Herein, we characterize a large cohort of individuals with biallelic variation in ENTPD1, a gene previously linked to spastic paraplegia 64 (Mendelian Inheritance in Man # 615683). METHODS: Individuals with biallelic ENTPD1 variants were recruited worldwide. Deep phenotyping and molecular characterization were performed. RESULTS: A total of 27 individuals from 17 unrelated families were studied; additional phenotypic information was collected from published cases. Twelve novel pathogenic ENTPD1 variants are described (NM 001776.6): c.398_399delinsAA; p.(Gly133Glu), c.540del; p.(Thr181Leufs*18), c.640del; p.(Gly216Glufs*75), c.185 T > G; p.(Leu62*), c.1531 T > C; p.(*511Glnext*100), c.967C > T; p.(Gln323*), c.414-2_414-1del, and c.146 A > G; p.(Tyr49Cys) including 4 recurrent variants c.1109 T > A; p.(Leu370*), c.574-6_574-3del, c.770_771del; p.(Gly257Glufs*18), and c.1041del; p.(Ile348Phefs*19). Shared disease traits include childhood onset, progressive spastic paraplegia, intellectual disability (ID), dysarthria, and white matter abnormalities. In vitro assays demonstrate that ENTPD1 expression and function are impaired and that c.574-6_574-3del causes exon skipping. Global metabolomics demonstrate ENTPD1 deficiency leads to impaired nucleotide, lipid, and energy metabolism. INTERPRETATION: The ENTPD1 locus trait consists of childhood disease onset, ID, progressive spastic paraparesis, dysarthria, dysmorphisms, and white matter abnormalities, with some individuals showing neurocognitive regression. Investigation of an allelic series of ENTPD1 (1) expands previously described features of ENTPD1-related neurological disease, (2) highlights the importance of genotype-driven deep phenotyping, (3) documents the need for global collaborative efforts to characterize rare autosomal recessive disease traits, and (4) provides insights into disease trait neurobiology. ANN NEUROL 2022;92:304-321.
Keywords: Apyrase; Dysarthria; Humans; Intellectual Disability; Mutation; Paraplegia; Pedigree; Phenotype; Spastic Paraplegia, Hereditary; White Matter

Centers for Mendelian Genomics: A decade of facilitating gene discovery. - Baxter, Samantha M; Posey, Jennifer E; Lake, Nicole J; Sobreira, Nara; Chong, Jessica X; Buyske, Steven; Blue, Elizabeth E; Chadwick, Lisa H; Coban-Akdemir, Zeynep H; Doheny, Kimberly F; Davis, Colleen P; Lek, Monkol; et al. (Genet Med, 2022)
PURPOSE: Mendelian disease genomic research has undergone a massive transformation over the past decade. With increasing availability of exome and genome sequencing, the role of Mendelian research has expanded beyond data collection, sequencing, and analysis to worldwide data sharing and collaboration. METHODS: Over the past 10 years, the National Institutes of Health-supported Centers for Mendelian Genomics (CMGs) have played a major role in this research and clinical evolution. RESULTS: We highlight the cumulative gene discoveries facilitated by the program, biomedical research leveraged by the approach, and the larger impact on the research community. Beyond generating a list of gene-phenotype relationships and participating in widespread data sharing, the CMGs have created resources, tools, and training for the larger community to foster understanding of genes and genome variation. The CMGs have participated in a wide range of data sharing activities, including deposition of all eligible CMG data into the Analysis, Visualization, and Informatics Lab-space (AnVIL), sharing candidate genes through the Matchmaker Exchange and the CMG website, and sharing variants in Genotypes to Mendelian Phenotypes (Geno2MP) and VariantMatcher. CONCLUSION: The work is far from complete; strengthening communication between research and clinical realms, continued development and sharing of knowledge and tools, and improving access to richly characterized data sets are all required to diagnose the remaining molecularly undiagnosed patients.
Keywords: Exome; Exome Sequencing; Genetic Association Studies; Genomics; Humans; Phenotype

Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease. - Uddin, M D Mesbah; Nguyen, Ngoc Quynh H; Yu, Bing; Brody, Jennifer A; Pampana, Akhil; Nakao, Tetsushi; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; Weinstock, Joshua S; Honigberg, Michael C; Nachun, Daniel; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.
Keywords: Clonal Hematopoiesis; Coronary Artery Disease; DNA Methylation; Hematopoiesis; Hematopoietic Stem Cells; Humans

The complete sequence of a human genome. - Nurk, Sergey; Koren, Sergey; Rhie, Arang; Rautiainen, Mikko; Bzikadze, Andrey V; Mikheenko, Alla; Vollger, Mitchell R; Altemose, Nicolas; Uralsky, Lev; Gershman, Ariel; Aganezov, Sergey; Hoyt, Savannah J; et al. (Science, 2022)
Since its initial release in 2000, the human reference genome has covered only the euchromatic fraction of the genome, leaving important heterochromatic regions unfinished. Addressing the remaining 8% of the genome, the Telomere-to-Telomere (T2T) Consortium presents a complete 3.055 billion-base pair sequence of a human genome, T2T-CHM13, that includes gapless assemblies for all chromosomes except Y, corrects errors in the prior references, and introduces nearly 200 million base pairs of sequence containing 1956 gene predictions, 99 of which are predicted to be protein coding. The completed regions include all centromeric satellite arrays, recent segmental duplications, and the short arms of all five acrocentric chromosomes, unlocking these complex regions of the genome to variational and functional studies.
Keywords: Cell Line; Chromosomes, Artificial, Bacterial; Chromosomes, Human; Genome, Human; Human Genome Project; Humans; Reference Values; Sequence Analysis, DNA

Correction: Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2022)

Curated variation benchmarks for challenging medically relevant autosomal genes. - Wagner, Justin; Olson, Nathan D; Harris, Lindsay; McDaniel, Jennifer; Cheng, Haoyu; Fungtammasan, Arkarachai; Hwang, Yih-Chii; Gupta, Richa; Wenger, Aaron M; Rowell, William J; Khan, Ziad M; Farek, Jesse; et al. (Nat Biotechnol, 2022)
The repetitive nature and complexity of some medically relevant genes poses a challenge for their accurate analysis in a clinical setting. The Genome in a Bottle Consortium has provided variant benchmark sets, but these exclude nearly 400 medically relevant genes due to their repetitiveness or polymorphic complexity. Here, we characterize 273 of these 395 challenging autosomal genes using a haplotype-resolved whole-genome assembly. This curated benchmark reports over 17,000 single-nucleotide variations, 3,600 insertions and deletions and 200 structural variations each for human genome reference GRCh37 and GRCh38 across HG002. We show that false duplications in either GRCh37 or GRCh38 result in reference-specific, missed variants for short- and long-read technologies in medically relevant genes, including CBS, CRYAA and KCNE1. When masking these false duplications, variant recall can improve from 8% to 100%. Forming benchmarks from a haplotype-resolved whole-genome assembly may become a prototype for future benchmarks covering the whole genome.
Keywords: Genome, Human; Haplotypes; Humans; Sequence Analysis, DNA

Developmental genomics of limb malformations: Allelic series in association with gene dosage effects contribute to the clinical variability. - Duan, Ruizhi; Hijazi, Hadia; Gulec, Elif Yilmaz; Eker, Hatice Koçak; Costa, Silvia R; Sahin, Yavuz; Ocak, Zeynep; Isikay, Sedat; Ozalp, Ozge; Bozdogan, Sevcan; Aslan, Huseyin; Elcioglu, Nursel; et al. (HGG Adv, 2022)
Genetic heterogeneity, reduced penetrance, and variable expressivity, the latter including asymmetric body axis plane presentations, have all been described in families with congenital limb malformations (CLMs). Interfamilial and intrafamilial heterogeneity highlight the complexity of the underlying genetic pathogenesis of these developmental anomalies. Family-based genomics by exome sequencing (ES) and rare variant analyses combined with whole-genome array-based comparative genomic hybridization were implemented to investigate 18 families with limb birth defects. Eleven of 18 (61%) families revealed explanatory variants, including 7 single-nucleotide variant alleles and 3 copy number variants (CNVs), at previously reported "disease trait associated loci": , cluster, , , and . Breakpoint junction analyses for all three CNV alleles revealed mutational signatures consistent with microhomology-mediated break-induced replication, a mechanism facilitated by -mediated rearrangement. Homozygous duplication of was observed in one Turkish kindred and represents a novel contributory genetic mechanism to Gollop-Wolfgang Complex (MIM: 228250), where triplication of the locus has been reported in one family from Japan (i.e., 4n = 2n + 2n versus 4n = 3n + 1n allelic configurations). Genes acting on limb patterning are sensitive to a gene dosage effect and are often associated with an allelic series. We extend an allele-specific gene dosage model to potentially assist, in an adjuvant way, interpretations of interconnections among an allelic series, clinical severity, and reduced penetrance of the -related CLM spectrum.

Discovery and systematic characterization of risk variants and genes for coronary artery disease in over a million participants. - Aragam, Krishna G; Jiang, Tao; Goel, Anuj; Kanoni, Stavroula; Wolford, Brooke N; Atri, Deepak S; Weeks, Elle M; Wang, Minxian; Hindy, George; Zhou, Wei; Grace, Christopher; Roselli, Carolina; et al. (Nat Genet, 2022)
The discovery of genetic loci associated with complex diseases has outpaced the elucidation of mechanisms of disease pathogenesis. Here we conducted a genome-wide association study (GWAS) for coronary artery disease (CAD) comprising 181,522 cases among 1,165,690 participants of predominantly European ancestry. We detected 241 associations, including 30 new loci. Cross-ancestry meta-analysis with a Japanese GWAS yielded 38 additional new loci. We prioritized likely causal variants using functionally informed fine-mapping, yielding 42 associations with less than five variants in the 95% credible set. Similarity-based clustering suggested roles for early developmental processes, cell cycle signaling and vascular cell migration and proliferation in the pathogenesis of CAD. We prioritized 220 candidate causal genes, combining eight complementary approaches, including 123 supported by three or more approaches. Using CRISPR-Cas9, we experimentally validated the effect of an enhancer in MYO9B, which appears to mediate CAD risk by regulating vascular cell motility. Our analysis identifies and systematically characterizes >250 risk loci for CAD to inform experimental interrogation of putative causal mechanisms for CAD.
Keywords: Coronary Artery Disease; Genome-Wide Association Study; Humans

DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases. - Wielscher, Matthias; Mandaviya, Pooja R; Kuehnel, Brigitte; Joehanes, Roby; Mustafa, Rima; Robinson, Oliver; Zhang, Yan; Bodinier, Barbara; Walton, Esther; Mishra, Pashupati P; Schlosser, Pascal; Wilson, Rory; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.
Keywords: C-Reactive Protein; CpG Islands; DNA Methylation; Humans; Inflammation; Nucleotide Motifs

The Earth BioGenome Project 2020: Starting the clock. - Lewin, Harris A; Stephen Richards; Lieberman Aiden, Erez; Allende, Miguel L; Archibald, John M; Bálint, Miklós; Barker, Katharine B; Baumgartner, Bridget; Belov, Katherine; Bertorelle, Giorgio; Blaxter, Mark L; Cai, Jing; et al. (Proc Natl Acad Sci U S A, 2022)
Keywords: Animals; Base Sequence; Biodiversity; Eukaryota; Genomics; Humans

Elucidating the clinical spectrum and molecular basis of HYAL2 deficiency. - Fasham, James; Lin, Siying; Ghosh, Promita; Radio, Francesca Clementina; Farrow, Emily G; Thiffault, Isabelle; Kussman, Jennifer; Zhou, Dihong; Hemming, Rick; Zahka, Kenneth; Chioza, Barry A; Rawlins, Lettie E; et al. (Genet Med, 2022)
PURPOSE: We previously defined biallelic HYAL2 variants causing a novel disorder in 2 families, involving orofacial clefting, facial dysmorphism, congenital heart disease, and ocular abnormalities, with Hyal2 knockout mice displaying similar phenotypes. In this study, we better define the phenotype and pathologic disease mechanism. METHODS: Clinical and genomic investigations were undertaken alongside molecular studies, including immunoblotting and immunofluorescence analyses of variant/wild-type human HYAL2 expressed in mouse fibroblasts, and in silico modeling of putative pathogenic variants. RESULTS: Ten newly identified individuals with this condition were investigated, and they were associated with 9 novel pathogenic variants. Clinical studies defined genotype-phenotype correlations and confirmed a recognizable craniofacial phenotype in addition to myopia, cleft lip/palate, and congenital cardiac anomalies as the most consistent manifestations of the condition. In silico modeling of missense variants identified likely deleterious effects on protein folding. Consistent with this, functional studies indicated that these variants cause protein instability and a concomitant cell surface absence of HYAL2 protein. CONCLUSION: These studies confirm an association between HYAL2 alterations and syndromic cleft lip/palate, provide experimental evidence for the pathogenicity of missense alleles, enable further insights into the pathomolecular basis of the disease, and delineate the core and variable clinical outcomes of the condition.
Keywords: Alleles; Animals; Cell Adhesion Molecules; Cleft Lip; Cleft Palate; Genetic Association Studies; GPI-Linked Proteins; Humans; Hyaluronoglucosaminidase; Mice; Phenotype

Examining the Effects of Hibernation on Germline Mutation Rates in Grizzly Bears. - Wang, Richard J; Peña-Garcia, Yadira; Bibby, Madeleine G; Raveendran, Muthuswamy; R. Alan Harris; Jansen, Heiko T; Robbins, Charles T; Jeffrey Rogers; Kelley, Joanna L; Hahn, Matthew W (Genome Biol Evol, 2022)
A male mutation bias is observed across vertebrates, and, where data are available, this bias is accompanied by increased per-generation mutation rates with parental age. While continuing mitotic cell division in the male germline post puberty has been proposed as the major cellular mechanism underlying both patterns, little direct evidence for this role has been found. Understanding the evolution of the per-generation mutation rate among species requires that we identify the molecular mechanisms that change between species. Here, we study the per-generation mutation rate in an extended pedigree of the brown (grizzly) bear, Ursus arctos horribilis. Brown bears hibernate for one-third of the year, a period during which spermatogenesis slows or stops altogether. The reduction of spermatogenesis is predicted to lessen the male mutation bias and to lower the per-generation mutation rate in this species. However, using whole-genome sequencing, we find that both male bias and per-generation mutation rates are highly similar to that expected for a non-hibernating species. We also carry out a phylogenetic comparison of substitution rates along the lineage leading to brown bear and panda (a non-hibernating species) and find no slowing of the substitution rate in the hibernator. Our results contribute to accumulating evidence that suggests that male germline cell division is not the major determinant of mutation rates and mutation biases. The results also provide a quantitative basis for improved estimates of the timing of carnivore evolution.
Keywords: Animals; Germ Cells; Germ-Line Mutation; Hibernation; Male; Mutation Rate; Phylogeny; Ursidae

Expanding the phenotypic and allelic spectrum of SMG8: Clinical observations reveal overlap with SMG9-associated disease trait. - Abdel-Salam, Ghada M H; Duan, Ruizhi; Abdel-Hamid, Mohamed S; Sayed, Inas S M; Jhangiani, Shalini N; Ziad Khan; Du, Haowei; Richard A Gibbs; Posey, Jennifer E; Marafi, Dana; James R Lupski (Am J Med Genet A, 2022)
SMG8 (MIM *617315) is a regulatory subunit involved in nonsense-mediated mRNA decay (NMD), a cellular protective pathway that regulates mRNA transcription, transcript stability, and degrades transcripts containing premature stop codons. SMG8 binds SMG9 and SMG1 to form the SMG1C complex and inhibit the kinase activity of SMG1. Biallelic deleterious variants in SMG9 are known to cause a heart and brain malformation syndrome (HBMS; MIM #616920), whereas biallelic deleterious variants in SMG8 were recently described to cause a novel neurodevelopmental disorder (NDD) with dysmorphic facies and cataracts, now defined as Alzahrani-Kuwahara syndrome (ALKUS: MIM #619268). Only eight subjects from four families with ALKUS have been described to date. Through research reanalysis of a nondiagnostic clinical exome, we identified a subject from a fifth unrelated family with a homozygous deleterious variant in SMG8 and features consistent with ALKUS. Interestingly, the subject also had unilateral microphthalmia, a clinical feature that has been described in SMG9-related disorder. Our study expands the phenotypic spectrum of SMG8-related disorder, demonstrates an overlapping phenotype between SMG8- and SMG9-related rare disease traits, provides further evidence for the SMG8 and SMG9 protein interactions, and highlights the importance of revisiting nondiagnostic exome data to identify and affirm emerging novel genes for rare disease traits.
Keywords: Alleles; Homozygote; Humans; Intracellular Signaling Peptides and Proteins; Nonsense Mediated mRNA Decay; Phenotype; Phosphorylation

Functional characteristics of a broad spectrum of TBX6 variants in Mayer-Rokitansky-Küster-Hauser syndrome. - Ma, Congcong; Chen, Na; Jolly, Angad; Zhao, Sen; Coban-Akdemir, Zeynep; Tian, Weijie; Kang, Jia; Ye, Yang; Wang, Yuan; Koch, André; Zhang, Yuanqiang; Qin, Chenglu; et al. (Genet Med, 2022)
PURPOSE: Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) is characterized by congenital absence of the uterus, cervix, and the upper part of the vagina in females. Whole-gene deletion and loss-of-function variants in TBX6 have been identified in association with MRKHS. We aimed to expand the spectrum of TBX6 variants in MRKHS and explore the biological effect of the variant alleles. METHODS: Rare variants in TBX6 were called from a combined multiethnic cohort of 622 probands with MRKHS who underwent exome sequencing or genome sequencing. Multiple in vitro functional experiments were performed, including messenger RNA analysis, western blotting, transcriptional activity assay, and immunofluorescence staining. RESULTS: We identified 16 rare variants in TBX6 from the combined cohort, including 1 protein-truncating variant reported in our previous study and 15 variants with unknown effects. By comparing the prevalence of TBX6 variants in the Chinese MRKHS cohort vs 1038 female controls, we observed a significant mutational burden of TBX6 in affected individuals (P = .0004, odds ratio = 5.25), suggesting a causal role of TBX6 variants in MRKHS. Of the 15 variants with uncertain effects, 7 were shown to induce a loss-of-function effect through various mechanisms. The c.423G>A (p.Leu141=) and c.839+5G>A variants impaired the normal splicing of TBX6 messenger RNA, c.422T>C (p.Leu141Pro) and c.745G>A (p.Val249Met) led to decreased protein expression, c.10C>T (p.Pro4Ser) and c.400G>A (p.Glu134Lys) resulted in perturbed transcriptional activity, and c.356G>A (p.Arg119His) caused protein mislocalization. We observed incomplete penetrance and variable expressivity in families carrying deleterious variants, which indicates a more complex genetic mechanism than classical Mendelian inheritance. CONCLUSION: Our study expands the mutational spectrum of TBX6 in MRKHS and delineates the molecular pathogenesis of TBX6 variants, supporting the association between deleterious variants in TBX6 and MRKHS.
Keywords: 46, XX Disorders of Sex Development; Congenital Abnormalities; Female; Humans; Mullerian Ducts; RNA, Messenger; T-Box Domain Proteins; Vagina

Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways. - Young, William J; Lahrouchi, Najim; Isaacs, Aaron; Duong, ThuyVy; Foco, Luisa; Ahmed, Farah; Brody, Jennifer A; Salman, Reem; Noordam, Raymond; Benjamins, Jan-Walter; Haessler, Jeffrey; Lyytikäinen, Leo-Pekka; et al. (Nat Commun, 2022)
The QT interval is an electrocardiographic measure representing the sum of ventricular depolarization and repolarization, estimated by QRS duration and JT interval, respectively. QT interval abnormalities are associated with potentially fatal ventricular arrhythmia. Using genome-wide multi-ancestry analyses (>250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.
Keywords: Arrhythmias, Cardiac; Death, Sudden, Cardiac; Electrocardiography; Genetic Testing; Humans; Male

Genetic errors of immunity distinguish pediatric nonmalignant lymphoproliferative disorders. - Forbes, Lisa R; Eckstein, Olive S; Gulati, Nitya; Peckham-Gregory, Erin C; Ozuah, Nmazuo W; Lubega, Joseph; El-Mallawany, Nader K; Agrusa, Jennifer E; Poli, M Cecilia; Vogel, Tiphanie P; Chaimowitz, Natalia S; Rider, Nicholas L; et al. (J Allergy Clin Immunol, 2022)
BACKGROUND: Pediatric nonmalignant lymphoproliferative disorders (PLPDs) are clinically and genetically heterogeneous. Long-standing immune dysregulation and lymphoproliferation in children may be life-threatening, and a paucity of data exists to guide evaluation and treatment of children with PLPD. OBJECTIVE: The primary objective of this study was to ascertain the spectrum of genomic immunologic defects in PLPD. Secondary objectives included characterization of clinical outcomes and associations between genetic diagnoses and those outcomes. METHODS: PLPD was defined by persistent lymphadenopathy, lymph organ involvement, or lymphocytic infiltration for more than 3 months, with or without chronic or significant Epstein-Barr virus (EBV) infection. Fifty-one subjects from 47 different families with PLPD were analyzed using whole exome sequencing. RESULTS: Whole exome sequencing identified likely genetic errors of immunity in 51% to 62% of families (53% to 65% of affected children). Presence of a genetic etiology was associated with younger age and hemophagocytic lymphohistiocytosis. Ten-year survival for the cohort was 72.4%, and patients with viable genetic diagnoses had a higher survival rate (82%) compared to children without a genetic explanation (48%, P = .03). Survival outcomes for individuals with EBV-associated disease and no genetic explanation were particularly worse than outcomes for subjects with EBV-associated disease and a genetic explanation (17% vs 90%; P = .002). Ascertainment of a molecular diagnosis provided targetable treatment options for up to 18 individuals and led to active management changes for 12 patients. CONCLUSIONS: PLPD defines children at high risk for mortality, and whole exome sequencing informs clinical risks and therapeutic opportunities for this diagnosis.
Keywords: Adolescent; Autoimmunity; Child; Child, Preschool; Exome Sequencing; Female; Genetic Association Studies; Genetic Testing; Herpesvirus 4, Human; Humans; Immunity; Infant; Lymphoproliferative Disorders; Male; Young Adult

Genome Sequencing in the Parkinson Disease Clinic. - Hill, Emily J; Robak, Laurie A; Al-Ouran, Rami; Deger, Jennifer; Fong, Jamie C; Vandeventer, Paul Jerrod; Schulman, Emily; Rao, Sindhu; Saade, Hiba; Savitt, Joseph M; von Coelln, Rainer; Desai, Neeja; et al. (Neurol Genet, 2022)
BACKGROUND AND OBJECTIVES: Genetic variants affect both Parkinson disease (PD) risk and manifestations. Although genetic information is of potential interest to patients and clinicians, genetic testing is rarely performed during routine PD clinical care. The goal of this study was to examine interest in comprehensive genetic testing among patients with PD and document reactions to possible findings from genome sequencing in 2 academic movement disorder clinics. METHODS: In 203 subjects with PD (age = 63 years, 67% male), genome sequencing was performed and filtered using a custom panel, including 49 genes associated with PD, parkinsonism, or related disorders, as well as a 90-variant PD genetic risk score. Based on the results, 231 patients (age = 67 years, 63% male) were surveyed on interest in genetic testing and responses to vignettes covering (1) familial risk of PD (); (2) risk of PD dementia (); (3) PD genetic risk score; and (4) secondary, medically actionable variants (). RESULTS: Genome sequencing revealed a variant in 3% and a risk variant in 10% of our clinical sample. The genetic risk score was normally distributed, identifying 41 subjects with a high risk of PD. Medically actionable findings were discovered in 2 subjects (1%). In our survey, the majority (82%) responded that they would share a variant with relatives. Most registered unchanged or increased interest in testing when confronted with a potential risk for dementia or medically actionable findings, and most (75%) expressed interest in learning their PD genetic risk score. DISCUSSION: Our results highlight broad interest in comprehensive genetic testing among patients with PD and may facilitate integration of genome sequencing in clinical practice.

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Eric Boerwinkle; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.
Keywords: Brain; Learning; Memory, Short-Term; Multifactorial Inheritance; Verbal Learning

Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases. - Li, Yong; Cheng, Yurong; Consolato, Francesco; Schiano, Guglielmo; Chong, Michael R; Pietzner, Maik; Nguyen, Ngoc Quynh H; Scherer, Nora; Biggs, Mary L; Kleber, Marcus E; Haug, Stefan; Göçmen, Burulça; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Hypertension; Renal Insufficiency, Chronic; Uromodulin

Genomic signatures of high-altitude adaptation and chromosomal polymorphism in geladas. - Chiou, Kenneth L; Janiak, Mareike C; Schneider-Crease, India A; Sen, Sharmi; Ayele, Ferehiwot; Chuma, Idrissa S; Knauf, Sascha; Lemma, Alemayehu; Signore, Anthony V; D'Ippolito, Anthony M; Abebe, Belayneh; Haile, Abebaw Azanaw; et al. (Nat Ecol Evol, 2022)
Primates have adapted to numerous environments and lifestyles but very few species are native to high elevations. Here we investigated high-altitude adaptations in the gelada (Theropithecus gelada), a monkey endemic to the Ethiopian Plateau. We examined genome-wide variation in conjunction with measurements of haematological and morphological traits. Our new gelada reference genome is highly intact and assembled at chromosome-length levels. Unexpectedly, we identified a chromosomal polymorphism in geladas that could potentially contribute to reproductive barriers between populations. Compared with baboons at low altitude, we found that high-altitude geladas exhibit significantly expanded chest circumferences, potentially allowing for greater lung surface area for increased oxygen diffusion. We identified gelada-specific amino acid substitutions in the alpha-chain subunit of adult haemoglobin but found that gelada haemoglobin does not exhibit markedly altered oxygenation properties compared with lowland primates. We also found that geladas at high altitude do not exhibit elevated blood haemoglobin concentrations, in contrast to the normal acclimatization response to hypoxia in lowland primates. The absence of altitude-related polycythaemia suggests that geladas are able to sustain adequate tissue-oxygen delivery despite environmental hypoxia. Finally, we identified numerous genes and genomic regions exhibiting accelerated rates of evolution, as well as gene families exhibiting expansions in the gelada lineage, potentially reflecting altitude-related selection. Our findings lend insight into putative mechanisms of high-altitude adaptation while suggesting promising avenues for functional hypoxia research.
Keywords: Altitude; Animals; Chromosomes; Genomics; Hypoxia; Oxygen; Theropithecus

Harmonizing variant classification for return of results in the All of Us Research Program. - Harrison, Steven M; Austin-Tse, Christina A; Kim, Serra; Lebo, Matthew; Leon, Annette; David R Murdock; Radhakrishnan, Aparna; Shirts, Brian H; Steeves, Marcie; Eric Venner; Richard A Gibbs; Jarvik, Gail P; et al. (Hum Mutat, 2022)
The All of Us Research Program (AoURP) is a historic effort to accelerate research and improve healthcare by generating and collating data from one million people in the United States. Participants will have the option to receive results from their genome analysis, including actionable findings in 59 gene-disorder pairs for which disorder-associated variants are recommended for return by the American College of Medical Genetics and Genomics. To ensure consistent reporting across the AoURP, in a prelaunch study the four participating clinical laboratories shared all variant classifications in the 59 genes of interest from their internal databases. Of the 11,813 unique variants classified by at least two of the four laboratories, classifications were concordant with regard to reportability for 99.1% (11,711), with only 0.9% (102) having reportability differences. Through variant reassessment, data sharing, and discussion of rationale, participating laboratories resolved all 102 reportable differences. These approaches will be maintained during routine AoU reporting to ensure continuous classification harmonization and consistent reporting within AoURP.
Keywords: Genetic Testing; Genetic Variation; Genome, Human; Genomics; Humans; Population Health; United States

Human COQ4 deficiency: delineating the clinical, metabolic and neuroimaging phenotypes. - Laugwitz, Lucia; Seibt, Annette; Herebian, Diran; Peralta, Susana; Kienzle, Imke; Buchert, Rebecca; Falb, Ruth; Gauck, Darja; Müller, Amelie; Grimmel, Mona; Beck-Woedel, Stefanie; Kern, Jan; et al. (J Med Genet, 2022)
BACKGROUND: Human coenzyme Q4 (COQ4) is essential for coenzyme Q (CoQ) biosynthesis. Pathogenic variants in cause childhood-onset neurodegeneration. We aimed to delineate the clinical spectrum and the cellular consequences of COQ4 deficiency. METHODS: Clinical course and neuroradiological findings in a large cohort of paediatric patients with COQ4 deficiency were analysed. Functional studies in patient-derived cell lines were performed. RESULTS: We characterised 44 individuals from 36 families with COQ4 deficiency (16 newly described). A total of 23 different variants were identified, including four novel variants in . Correlation analyses of clinical and neuroimaging findings revealed three disease patterns: type 1: early-onset phenotype with neonatal brain anomalies and epileptic encephalopathy; type 2: intermediate phenotype with distinct stroke-like lesions; and type 3: moderate phenotype with non-specific brain pathology and a stable disease course. The functional relevance of variants was supported by in vitro studies using patient-derived fibroblast lines. Experiments revealed significantly decreased COQ4 protein levels, reduced levels of cellular CoQ and elevated levels of the metabolic intermediate 6-demethoxyubiquinone. CONCLUSION: Our study describes the heterogeneous clinical presentation of COQ4 deficiency and identifies phenotypic subtypes. Cell-based studies support the pathogenic characteristics of variants. Due to the insufficient clinical response to oral CoQ supplementation, alternative treatment strategies are warranted.
Keywords: Cell Line; Child; Humans; Infant, Newborn; Mitochondrial Proteins; Neuroimaging; Phenotype; Ubiquinone

Implementation of preemptive DNA sequence-based pharmacogenomics testing across a large academic medical center: The Mayo-Baylor RIGHT 10K Study. - Wang, Liewei; Steven E Scherer; Bielinski, Suzette J; Donna M Muzny; Jones, Leila A; Black, John Logan; Moyer, Ann M; Giri, Jyothsna; Sharp, Richard R; Matey, Eric T; Wright, Jessica A; Oyen, Lance J; et al. (Genet Med, 2022)
PURPOSE: The Mayo-Baylor RIGHT 10K Study enabled preemptive, sequence-based pharmacogenomics (PGx)-driven drug prescribing practices in routine clinical care within a large cohort. We also generated the tools and resources necessary for clinical PGx implementation and identified challenges that need to be overcome. Furthermore, we measured the frequency of both common genetic variation for which clinical guidelines already exist and rare variation that could be detected by DNA sequencing, rather than genotyping. METHODS: Targeted oligonucleotide-capture sequencing of 77 pharmacogenes was performed using DNA from 10,077 consented Mayo Clinic Biobank volunteers. The resulting predicted drug response-related phenotypes for 13 genes, including CYP2D6 and HLA, affecting 21 drug-gene pairs, were deposited preemptively in the Mayo electronic health record. RESULTS: For the 13 pharmacogenes of interest, the genomes of 79% of participants carried clinically actionable variants in 3 or more genes, and DNA sequencing identified an average of 3.3 additional conservatively predicted deleterious variants that would not have been evident using genotyping. CONCLUSION: Implementation of preemptive rather than reactive and sequence-based rather than genotype-based PGx prescribing revealed nearly universal patient applicability and required integrated institution-wide resources to fully realize individualized drug therapy and to show more efficient use of health care resources.
Keywords: Academic Medical Centers; Base Sequence; Cytochrome P-450 CYP2D6; Genotype; Humans; Pharmacogenetics

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.
Keywords: Blood Pressure; Genome-Wide Association Study; Genomics; Humans; Hypertension; Polymorphism, Single Nucleotide; Precision Medicine

Long read sequencing and expression studies of AHDC1 deletions in Xia-Gibbs syndrome reveal a novel genetic regulatory mechanism. - Chander, Varuna; Mahmoud, Medhat; Jianhong Hu; Dardas, Zain; Grochowski, Christopher M; Dawood, Moez; Khayat, Michael M; Li, He; Li, Shoudong; Jhangiani, Shalini; Korchina, Viktoriya; Shen, Hua; et al. (Hum Mutat, 2022)
Xia-Gibbs syndrome (XGS; MIM# 615829) is a rare mendelian disorder characterized by Development Delay (DD), intellectual disability (ID), and hypotonia. Individuals with XGS typically harbor de novo protein-truncating mutations in the AT-Hook DNA binding motif containing 1 (AHDC1) gene, although some missense mutations can also cause XGS. Large de novo heterozygous deletions that encompass the AHDC1 gene have also been ascribed as diagnostic for the disorder, without substantial evidence to support their pathogenicity. We analyzed 19 individuals with large contiguous deletions involving AHDC1, along with other genes. One individual bore the smallest known contiguous AHDC1 deletion (∼350 Kb), encompassing eight other genes within chr1p36.11 (Feline Gardner-Rasheed, IFI6, FAM76A, STX12, PPP1R8, THEMIS2, RPA2, SMPDL3B) and terminating within the first intron of AHDC1. The breakpoint junctions and phase of the deletion were identified using both short and long read sequencing (Oxford Nanopore). Quantification of RNA expression patterns in whole blood revealed that AHDC1 exhibited a mono-allelic expression pattern with no deficiency in overall AHDC1 expression levels, in contrast to the other deleted genes, which exhibited a 50% reduction in mRNA expression. These results suggest that AHDC1 expression in this individual is compensated by a novel regulatory mechanism and advances understanding of mutational and regulatory mechanisms in neurodevelopmental disorders.
Keywords: Abnormalities, Multiple; DNA-Binding Proteins; Endoribonucleases; Humans; Intellectual Disability; Musculoskeletal Abnormalities; Neurodevelopmental Disorders; Phosphoprotein Phosphatases; Qa-SNARE Proteins; RNA-Binding Proteins; Sphingomyelin Phosphodiesterase

The multiple de novo copy number variant (MdnCNV) phenomenon presents with peri-zygotic DNA mutational signatures and multilocus pathogenic variation. - Du, Haowei; Jolly, Angad; Grochowski, Christopher M; Bo Yuan; Dawood, Moez; Jhangiani, Shalini N; Li, He; Donna M Muzny; Fatih, Jawid M; Coban-Akdemir, Zeynep; Carlin, Mary Esther; Scheuerle, Angela E; et al. (Genome Med, 2022)
BACKGROUND: The multiple de novo copy number variant (MdnCNV) phenotype is described by having four or more constitutional de novo CNVs (dnCNVs) arising independently throughout the human genome within one generation. It is a rare peri-zygotic mutational event, previously reported to be seen once in every 12,000 individuals referred for genome-wide chromosomal microarray analysis due to congenital abnormalities. These rare families provide a unique opportunity to understand the genetic factors of peri-zygotic genome instability and the impact of dnCNV on human diseases. METHODS: Chromosomal microarray analysis (CMA), array-based comparative genomic hybridization, short- and long-read genome sequencing (GS) were performed on the newly identified MdnCNV family to identify de novo mutations including dnCNVs, de novo single-nucleotide variants (dnSNVs), and indels. Short-read GS was performed on four previously published MdnCNV families for dnSNV analysis. Trio-based rare variant analysis was performed on the newly identified individual and four previously published MdnCNV families to identify potential genetic etiologies contributing to the peri-zygotic genomic instability. Lin semantic similarity scores informed quantitative human phenotype ontology analysis on three MdnCNV families to identify gene(s) driving or contributing to the clinical phenotype. RESULTS: In the newly identified MdnCNV case, we revealed eight de novo tandem duplications, each ~ 1 Mb, with microhomology at 6/8 breakpoint junctions. Enrichment of de novo single-nucleotide variants (SNV; 6/79) and de novo indels (1/12) was found within 4 Mb of the dnCNV genomic regions. An elevated post-zygotic SNV mutation rate was observed in MdnCNV families. Maternal rare variant analyses identified three genes in distinct families that may contribute to the MdnCNV phenomenon. Phenotype analysis suggests that gene(s) within dnCNV regions contribute to the observed proband phenotype in 3/3 cases. CNVs in two cases, a contiguous gene duplication encompassing PMP22 and RAI1 and another duplication affecting NSD1 and SMARCC2, contribute to the clinically observed phenotypic manifestations. CONCLUSIONS: Characteristic features of dnCNVs reported here are consistent with a microhomology-mediated break-induced replication (MMBIR)-driven mechanism during the peri-zygotic period. Maternal genetic variants in DNA repair genes potentially contribute to peri-zygotic genomic instability. Variable phenotypic features were observed across a cohort of three MdnCNV probands, and computational quantitative phenotyping revealed that two out of three had evidence for the contribution of more than one genetic locus to the proband's phenotype supporting the hypothesis of de novo multilocus pathogenic variation (MPV) in those families.
Keywords: Comparative Genomic Hybridization; DNA; DNA Copy Number Variations; DNA-Binding Proteins; Genomic Instability; Humans; Mutation; Nucleotides; Transcription Factors

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

Novel pathogenic variants and quantitative phenotypic analyses of Robinow syndrome: WNT signaling perturbation and phenotypic variability. - Zhang, Chaofan; Jolly, Angad; Shayota, Brian J; Mazzeu, Juliana F; Du, Haowei; Dawood, Moez; Soper, Patricia Celestino; Ramalho de Lima, Ariadne; Ferreira, Barbara Merfort; Coban-Akdemir, Zeynep; White, Janson; Shears, Deborah; et al. (HGG Adv, 2022)
Robinow syndrome (RS) is a genetically heterogeneous disorder with six genes that converge on the WNT/planar cell polarity (PCP) signaling pathway implicated (, , , , , and ). RS is characterized by skeletal dysplasia and distinctive facial and physical characteristics. To further explore the genetic heterogeneity, paralog contribution, and phenotypic variability of RS, we investigated a cohort of 22 individuals clinically diagnosed with RS from 18 unrelated families. Pathogenic or likely pathogenic variants in genes associated with RS or RS phenocopies were identified in all 22 individuals, including the first variant to be reported in . We retrospectively collected medical records of 16 individuals from this cohort and extracted clinical descriptions from 52 previously published cases. We performed Human Phenotype Ontology (HPO) based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. Individuals with variants clustered into two groups with demonstrable phenotypic differences between those with missense and truncating alleles. Probands with biallelic variants clustered together with the majority of probands carrying , , and variants, demonstrating no phenotypic distinction between the -autosomal recessive and dominant forms of RS. While phenotypically similar diseases on the RS differential matched through HPO analysis, clustering using phenotype similarity score placed RS-associated phenotypes in a unique cluster containing , , and apart from non-RS-associated paralogs. Through human phenotype analyses of this RS cohort and OMIM clinical synopses of Mendelian disease, this study begins to tease apart specific biologic roles for non-canonical WNT-pathway proteins.

Novel RETREG1 (FAM134B) founder allele is linked to HSAN2B and renal disease in a Turkish family. - Taşdelen, Elifcan; Calame, Daniel G; Akay, Gulsen; Mitani, Tadahiro; Fatih, Jawid M; Herman, Isabella; Du, Haowei; Coban-Akdemir, Zeynep; Marafi, Dana; Jhangiani, Shalini N; Posey, Jennifer E; Richard A Gibbs; et al. (Am J Med Genet A, 2022)
Hereditary sensory and autonomic neuropathy type 2B (HSAN2B) is a rare autosomal recessive peripheral neuropathy caused by biallelic variants in RETREG1 (formerly FAM134B). HSAN2B is characterized by sensory impairment resulting in skin ulcerations, amputations, and osteomyelitis as well as variable weakness, spasticity, and autonomic dysfunction. Here, we report four affected individuals with recurrent osteomyelitis, ulceration, and amputation of hands and feet, sensory neuropathy, hyperhidrosis, urinary incontinence, and renal failure from a family without any known shared parental ancestry. Due to the history of chronic recurrent multifocal osteomyelitis and microcytic anemia, a diagnosis of Majeed syndrome was considered; however, sequencing of LPIN2 was negative. Family-based exome sequencing (ES) revealed a novel homozygous ultrarare RETREG1 variant NM_001034850.2:c.321G>A;p.Trp107Ter. Electrophysiological studies of the proband demonstrated axonal sensorimotor neuropathy predominantly in the lower extremities. Consistent with the lack of shared ancestry, the coefficient of inbreeding calculated from ES data was low (F = 0.002), but absence of heterozygosity (AOH) analysis demonstrated a 7.2 Mb AOH block surrounding the variant consistent with a founder allele. Two of the four affected individuals had unexplained renal failure which has not been reported in HSAN2B cases to date. Therefore, this report describes a novel RETREG1 founder allele and suggests renal failure may be an unrecognized feature of the RETREG1-disease spectrum.
Keywords: Alleles; Hereditary Sensory and Autonomic Neuropathies; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Osteomyelitis; Pedigree; Renal Insufficiency

Phenotypic and mutational spectrum of ROR2-related Robinow syndrome. - Lima, Ariadne R; Ferreira, Barbara M; Zhang, Chaofan; Jolly, Angad; Du, Haowei; White, Janson J; Dawood, Moez; Lins, Tulio C; Chiabai, Marcela A; van Beusekom, Ellen; Cordoba, Mara S; Caldas Rosa, Erica C C; et al. (Hum Mutat, 2022)
Robinow syndrome is characterized by a triad of craniofacial dysmorphisms, disproportionate-limb short stature, and genital hypoplasia. A significant degree of phenotypic variability seems to correlate with different genes/loci. Disturbances of the noncanonical WNT-pathway have been identified as the main cause of the syndrome. Biallelic variants in ROR2 cause an autosomal recessive form of the syndrome with distinctive skeletal findings. Twenty-two patients with a clinical diagnosis of autosomal recessive Robinow syndrome were screened for variants in ROR2 using multiple molecular approaches. We identified 25 putatively pathogenic ROR2 variants, 16 novel, including single nucleotide variants and exonic deletions. Detailed phenotypic analyses revealed that all subjects presented with a prominent forehead, hypertelorism, short nose, abnormality of the nasal tip, brachydactyly, mesomelic limb shortening, short stature, and genital hypoplasia in male patients. A total of 19 clinical features were present in more than 75% of the subjects, thus pointing to an overall uniformity of the phenotype. Disease-causing variants in ROR2, contribute to a clinically recognizable autosomal recessive trait phenotype with multiple skeletal defects. A comprehensive quantitative clinical evaluation of this cohort delineated the phenotypic spectrum of ROR2-related Robinow syndrome. The identification of exonic deletion variant alleles further supports the contention of a loss-of-function mechanism in the etiology of the syndrome.
Keywords: Craniofacial Abnormalities; Dwarfism; Genes, Recessive; Humans; Limb Deformities, Congenital; Male; Phenotype; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.
Keywords: Humans; Lung; National Heart, Lung, and Blood Institute (U.S.); Pulmonary Disease, Chronic Obstructive; Risk Factors; Transcriptome; United States

PrecisionFDA Truth Challenge V2: Calling variants from short and long reads in difficult-to-map regions. - Olson, Nathan D; Wagner, Justin; McDaniel, Jennifer; Stephens, Sarah H; Westreich, Samuel T; Prasanna, Anish G; Johanson, Elaine; Boja, Emily; Maier, Ezekiel J; Serang, Omar; Jáspez, David; Lorenzo-Salazar, José M; et al. (Cell Genom, 2022)
The precisionFDA Truth Challenge V2 aimed to assess the state of the art of variant calling in challenging genomic regions. Starting with FASTQs, 20 challenge participants applied their variant-calling pipelines and submitted 64 variant call sets for one or more sequencing technologies (Illumina, PacBio HiFi, and Oxford Nanopore Technologies). Submissions were evaluated following best practices for benchmarking small variants with updated Genome in a Bottle benchmark sets and genome stratifications. Challenge submissions included numerous innovative methods, with graph-based and machine learning methods scoring best for short-read and long-read datasets, respectively. With machine learning approaches, combining multiple sequencing technologies performed particularly well. Recent developments in sequencing and variant calling have enabled benchmarking variants in challenging genomic regions, paving the way for the identification of previously unknown clinically relevant variants.

Proteogenomic Markers of Chemotherapy Resistance and Response in Triple-Negative Breast Cancer. - Anurag, Meenakshi; Jaehnig, Eric J; Krug, Karsten; Lei, Jonathan T; Bergstrom, Erik J; Kim, Beom-Jun; Vashist, Tanmayi D; Huynh, Anh Minh Tran; Dou, Yongchao; Gou, Xuxu; Huang, Chen; Shi, Zhiao; et al. (Cancer Discov, 2022)
UNLABELLED: Microscaled proteogenomics was deployed to probe the molecular basis for differential response to neoadjuvant carboplatin and docetaxel combination chemotherapy for triple-negative breast cancer (TNBC). Proteomic analyses of pretreatment patient biopsies uniquely revealed metabolic pathways, including oxidative phosphorylation, adipogenesis, and fatty acid metabolism, that were associated with resistance. Both proteomics and transcriptomics revealed that sensitivity was marked by elevation of DNA repair, E2F targets, G2-M checkpoint, interferon-gamma signaling, and immune-checkpoint components. Proteogenomic analyses of somatic copy-number aberrations identified a resistance-associated 19q13.31-33 deletion where LIG1, POLD1, and XRCC1 are located. In orthogonal datasets, LIG1 (DNA ligase I) gene deletion and/or low mRNA expression levels were associated with lack of pathologic complete response, higher chromosomal instability index (CIN), and poor prognosis in TNBC, as well as carboplatin-selective resistance in TNBC preclinical models. Hemizygous loss of LIG1 was also associated with higher CIN and poor prognosis in other cancer types, demonstrating broader clinical implications. SIGNIFICANCE: Proteogenomic analysis of triple-negative breast tumors revealed a complex landscape of chemotherapy response associations, including a 19q13.31-33 somatic deletion encoding genes serving lagging-strand DNA synthesis (LIG1, POLD1, and XRCC1), that correlate with lack of pathologic response, carboplatin-selective resistance, and, in pan-cancer studies, poor prognosis and CIN. This article is highlighted in the In This Issue feature, p. 2483.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Carboplatin; Humans; Neoadjuvant Therapy; Proteogenomics; Proteomics; Triple Negative Breast Neoplasms; X-ray Repair Cross Complementing Protein 1

Quantitative dissection of multilocus pathogenic variation in an Egyptian infant with severe neurodevelopmental disorder resulting from multiple molecular diagnoses. - Herman, Isabella; Jolly, Angad; Du, Haowei; Dawood, Moez; Abdel-Salam, Ghada M H; Marafi, Dana; Mitani, Tadahiro; Calame, Daniel G; Coban-Akdemir, Zeynep; Fatih, Jawid M; Hegazy, Ibrahim; Jhangiani, Shalini N; et al. (Am J Med Genet A, 2022)
Genomic sequencing and clinical genomics have demonstrated that substantial subsets of atypical and/or severe disease presentations result from multilocus pathogenic variation (MPV) causing blended phenotypes. In an infant with a severe neurodevelopmental disorder, four distinct molecular diagnoses were found by exome sequencing (ES). The blended phenotype that includes brain malformation, dysmorphism, and hypotonia was dissected using the Human Phenotype Ontology (HPO). ES revealed variants in CAPN3 (c.259C > G:p.L87V), MUSK (c.1781C > T:p.A594V), NAV2 (c.1996G > A:p.G666R), and ZC4H2 (c.595A > C:p.N199H). CAPN3, MUSK, and ZC4H2 are established disease genes linked to limb-girdle muscular dystrophy (OMIM# 253600), congenital myasthenia (OMIM# 616325), and Wieacker-Wolff syndrome (WWS; OMIM# 314580), respectively. NAV2 is a retinoic-acid responsive novel disease gene candidate with biological roles in neurite outgrowth and cerebellar dysgenesis in mouse models. Using semantic similarity, we show that no gene identified by ES individually explains the proband phenotype, but rather the totality of the clinically observed disease is explained by the combination of disease-contributing effects of the identified genes. These data reveal that multilocus pathogenic variation can result in a blended phenotype with each gene affecting a different part of the nervous system and nervous system-muscle connection. We provide evidence from this n = 1 study that in patients with MPV and complex blended phenotypes resulting from multiple molecular diagnoses, quantitative HPO analysis can allow for dissection of phenotypic contribution of both established disease genes and novel disease gene candidates not yet proven to cause human disease.
Keywords: Animals; Calpain; Egypt; Exome Sequencing; Humans; Infant; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Neurodevelopmental Disorders; Phenotype

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

A recurrent single-exon deletion in TBCK might be under-recognized in patients with infantile hypotonia and psychomotor delay. - Dai, Hongzheng; Zhu, Wenmiao; Bo Yuan; Walley, Nicole; Schoch, Kelly; Jiang, Yong-Hui; Phillips, John A; Jones, Melissa S; Liu, Pengfei; David R Murdock; Burrage, Lindsay C; Lee, Brendan; et al. (Hum Mutat, 2022)
Advanced bioinformatics algorithms allow detection of multiple-exon copy-number variations (CNVs) from exome sequencing (ES) data, while detection of single-exon CNVs remains challenging. A retrospective review of Baylor Genetics' clinical ES patient cohort identified four individuals with homozygous single-exon deletions of TBCK (exon 23, NM_001163435.2), a gene associated with an autosomal recessive neurodevelopmental phenotype. To evaluate the prevalence of this deletion and its contribution to disease, we retrospectively analyzed single nucleotide polymorphism (SNP) array data for 8194 individuals undergoing ES, followed by PCR confirmation and RT-PCR on individuals carrying homozygous or heterozygous exon 23 TBCK deletions. A fifth individual was diagnosed with the TBCK-related disorder due to a heterozygous exon 23 deletion in trans with a c.1860+1G>A (NM_001163435.2) pathogenic variant, and three additional heterozygous carriers were identified. Affected individuals and carriers were from diverse ethnicities including European Caucasian, South Asian, Middle Eastern, Hispanic American and African American, with only one family reporting consanguinity. RT-PCR revealed two out-of-frame transcripts related to the exon 23 deletion. Our results highlight the importance of identifying single-exon deletions in clinical ES, especially for genes carrying recurrent deletions. For patients with early-onset hypotonia and psychomotor delay, this single-exon TBCK deletion might be under-recognized due to technical limitations of ES.
Keywords: DNA Copy Number Variations; Exome; Exome Sequencing; Exons; Humans; Infant; Muscle Hypotonia; Muscular Diseases; Protein Serine-Threonine Kinases; Retrospective Studies

A reverse genetics and genomics approach to gene paralog function and disease: Myokymia and the juxtaparanode. - Marafi, Dana; Kozar, Nina; Duan, Ruizhi; Bradley, Stephen; Yokochi, Kenji; Al Mutairi, Fuad; Saadi, Nebal Waill; Whalen, Sandra; Brunet, Theresa; Kotzaeridou, Urania; Choukair, Daniela; Keren, Boris; et al. (Am J Hum Genet, 2022)
The leucine-rich glioma-inactivated (LGI) family consists of four highly conserved paralogous genes, LGI1-4, that are highly expressed in mammalian central and/or peripheral nervous systems. LGI1 antibodies are detected in subjects with autoimmune limbic encephalitis and peripheral nerve hyperexcitability syndromes (PNHSs) such as Isaacs and Morvan syndromes. Pathogenic variations of LGI1 and LGI4 are associated with neurological disorders as disease traits including familial temporal lobe epilepsy and neurogenic arthrogryposis multiplex congenita 1 with myelin defects, respectively. No human disease has been reported associated with either LGI2 or LGI3. We implemented exome sequencing and family-based genomics to identify individuals with deleterious variants in LGI3 and utilized GeneMatcher to connect practitioners and researchers worldwide to investigate the clinical and electrophysiological phenotype in affected subjects. We also generated Lgi3-null mice and performed peripheral nerve dissection and immunohistochemistry to examine the juxtaparanode LGI3 microarchitecture. As a result, we identified 16 individuals from eight unrelated families with loss-of-function (LoF) bi-allelic variants in LGI3. Deep phenotypic characterization showed LGI3 LoF causes a potentially clinically recognizable PNHS trait characterized by global developmental delay, intellectual disability, distal deformities with diminished reflexes, visible facial myokymia, and distinctive electromyographic features suggestive of motor nerve instability. Lgi3-null mice showed reduced and mis-localized Kv1 channel complexes in myelinated peripheral axons. Our data demonstrate bi-allelic LoF variants in LGI3 cause a clinically distinguishable disease trait of PNHS, most likely caused by disturbed Kv1 channel distribution in the absence of LGI3.
Keywords: Animals; Autoantibodies; Axons; Genomics; Humans; Intracellular Signaling Peptides and Proteins; Mammals; Mice; Myokymia; Nerve Tissue Proteins; Phenotype; Reverse Genetics

The third international hackathon for applying insights into large-scale genomic composition to use cases in a wide range of organisms. - Kimberly Walker; Kalra, Divya; Lowdon, Rebecca; Chen, Guangyi; Molik, David; Soto, Daniela C; Dabbaghie, Fawaz; Khleifat, Ahmad Al; Mahmoud, Medhat; Paulin, Luis F; Raza, Muhammad Sohail; Pfeifer, Susanne P; et al. (F1000Res, 2022)
In October 2021, 59 scientists from 14 countries and 13 U.S. states collaborated virtually in the Third Annual Baylor College of Medicine & DNANexus Structural Variation hackathon. The goal of the hackathon was to advance research on structural variants (SVs) by prototyping and iterating on open-source software. This led to nine hackathon projects focused on diverse genomics research interests, including various SV discovery and genotyping methods, SV sequence reconstruction, and clinically relevant structural variation, including SARS-CoV-2 variants. Repositories for the projects that participated in the hackathon are available at https://github.com/collaborativebioinformatics.
Keywords: COVID-19; Genomics; Humans; SARS-CoV-2; Software

TOP-LD: A tool to explore linkage disequilibrium with TOPMed whole-genome sequence data. - Huang, Le; Rosen, Jonathan D; Sun, Quan; Chen, Jiawen; Wheeler, Marsha M; Zhou, Ying; Min, Yuan-I; Kooperberg, Charles; Conomos, Matthew P; Stilp, Adrienne M; Rich, Stephen S; Rotter, Jerome I; et al. (Am J Hum Genet, 2022)
Current publicly available tools that allow rapid exploration of linkage disequilibrium (LD) between markers (e.g., HaploReg and LDlink) are based on whole-genome sequence (WGS) data from 2,504 individuals in the 1000 Genomes Project. Here, we present TOP-LD, an online tool to explore LD inferred with high-coverage (∼30×) WGS data from 15,578 individuals in the NHLBI Trans-Omics for Precision Medicine (TOPMed) program. TOP-LD provides a significant upgrade compared to current LD tools, as the TOPMed WGS data provide a more comprehensive representation of genetic variation than the 1000 Genomes data, particularly for rare variants and in the specific populations that we analyzed. For example, TOP-LD encompasses LD information for 150.3, 62.2, and 36.7 million variants for European, African, and East Asian ancestral samples, respectively, offering 2.6- to 9.1-fold increase in variant coverage compared to HaploReg 4.0 or LDlink. In addition, TOP-LD includes tens of thousands of structural variants (SVs). We demonstrate the value of TOP-LD in fine-mapping at the GGT1 locus associated with gamma glutamyltransferase in the African ancestry participants in UK Biobank. Beyond fine-mapping, TOP-LD can facilitate a wide range of applications that are based on summary statistics and estimates of LD. TOP-LD is freely available online.
Keywords: Asian People; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Precision Medicine; Whole Genome Sequencing

Type 2 Diabetes Partitioned Polygenic Scores Associate With Disease Outcomes in 454,193 Individuals Across 13 Cohorts. - DiCorpo, Daniel; LeClair, Jessica; Cole, Joanne B; Sarnowski, Chloe; Ahmadizar, Fariba; Bielak, Lawrence F; Blokstra, Anneke; Bottinger, Erwin P; Chaker, Layal; Chen, Yii-Der I; Chen, Ye; de Vries, Paul S; et al. (Diabetes Care, 2022)
OBJECTIVE: Type 2 diabetes (T2D) has heterogeneous patient clinical characteristics and outcomes. In previous work, we investigated the genetic basis of this heterogeneity by clustering 94 T2D genetic loci using their associations with 47 diabetes-related traits and identified five clusters, termed β-cell, proinsulin, obesity, lipodystrophy, and liver/lipid. The relationship between these clusters and individual-level metabolic disease outcomes has not been assessed. RESEARCH DESIGN AND METHODS: Here we constructed individual-level partitioned polygenic scores (pPS) for these five clusters in 12 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (n = 454,193) and tested for cross-sectional association with T2D-related outcomes, including blood pressure, renal function, insulin use, age at T2D diagnosis, and coronary artery disease (CAD). RESULTS: Despite all clusters containing T2D risk-increasing alleles, they had differential associations with metabolic outcomes. Increased obesity and lipodystrophy cluster pPS, which had opposite directions of association with measures of adiposity, were both significantly associated with increased blood pressure and hypertension. The lipodystrophy and liver/lipid cluster pPS were each associated with CAD, with increasing and decreasing effects, respectively. An increased liver/lipid cluster pPS was also significantly associated with reduced renal function. The liver/lipid cluster includes known loci linked to liver lipid metabolism (e.g., GCKR, PNPLA3, and TM6SF2), and these findings suggest that cardiovascular disease risk and renal function may be impacted by these loci through their shared disease pathway. CONCLUSIONS: Our findings support that genetically driven pathways leading to T2D also predispose differentially to clinical outcomes.
Keywords: Alleles; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Genetic Loci; Humans; Obesity; Pharmaceutical Preparations

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Eric Boerwinkle; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Variant-level matching for diagnosis and discovery: Challenges and opportunities. - Rodrigues, Eliete da S; Griffith, Sean; Martin, Renan; Antonescu, Corina; Posey, Jennifer E; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Doheny, Kimberly F; James R Lupski; Valle, David; Bamshad, Michael J; Hamosh, Ada; et al. (Hum Mutat, 2022)
Here we describe MyGene2, Geno2MP, VariantMatcher, and Franklin; databases that provide variant-level information and phenotypic features to researchers, clinicians, healthcare providers and patients. Following the footsteps of the Matchmaker Exchange project that connects exome, genome, and phenotype databases at the gene level, these databases have as one goal to facilitate connection to one another using Data Connect, a standard for discovery and search of biomedical data from the Global Alliance for Genomics and Health (GA4GH).
Keywords: Databases, Genetic; Exome; Genomics; Humans; Information Dissemination; Phenotype

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldórsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

Whole-exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; de Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Eric Boerwinkle; Cushman, Mary; de Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole-exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and the National Heart, Lung and Blood Institute's Exome Sequencing Project. Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in fibrinogen gamma chain (FGG) (with fibrinogen, P = 9.1 × 10-13), coagulation factor VII (F7) (with factor VII, P = 1.3 × 10-72; seven novel variants) and VWF (with factor VIII and vWF; P = 3.2 × 10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; P = 4.2 × 10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to AAs (rs3211938) in CD36 molecule (CD36). This variant has previously been linked to dyslipidemia but not with the levels of a hemostatic factor. These efforts represent the largest integration of whole-exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.
Keywords: Exome Sequencing; Factor VII; Factor VIII; Fibrinogen; Hemostatics; Humans; Polymorphism, Single Nucleotide; von Willebrand Factor

Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Eric Boerwinkle; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Eczema; Exome; Exome Sequencing; Facies; Female; Genetic Predisposition to Disease; Genome, Human; Genomics; Growth Disorders; Histone Deacetylases; Humans; Infant; Intellectual Disability; Male; Microcephaly; Phenotype; Repressor Proteins

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Author Correction: Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2021)

Author Correction: Performance assessment of DNA sequencing platforms in the ABRF Next-Generation Sequencing Study. - Foox, Jonathan; Tighe, Scott W; Nicolet, Charles M; Zook, Justin M; Byrska-Bishop, Marta; Clarke, Wayne E; Khayat, Michael M; Mahmoud, Medhat; Laaguiby, Phoebe K; Herbert, Zachary T; Warner, Derek; Grills, George S; et al. (Nat Biotechnol, 2021)

Biallelic and monoallelic variants in PLXNA1 are implicated in a novel neurodevelopmental disorder with variable cerebral and eye anomalies. - Dworschak, Gabriel C; Punetha, Jaya; Kalanithy, Jeshurun C; Mingardo, Enrico; Erdem, Haktan B; Akdemir, Zeynep C; Karaca, Ender; Mitani, Tadahiro; Marafi, Dana; Fatih, Jawid M; Jhangiani, Shalini N; Hunter, Jill V; et al. (Genet Med, 2021)
PURPOSE: To investigate the effect of PLXNA1 variants on the phenotype of patients with autosomal dominant and recessive inheritance patterns and to functionally characterize the zebrafish homologs plxna1a and plxna1b during development. METHODS: We assembled ten patients from seven families with biallelic or de novo PLXNA1 variants. We describe genotype-phenotype correlations, investigated the variants by structural modeling, and used Morpholino knockdown experiments in zebrafish to characterize the embryonic role of plxna1a and plxna1b. RESULTS: Shared phenotypic features among patients include global developmental delay (9/10), brain anomalies (6/10), and eye anomalies (7/10). Notably, seizures were predominantly reported in patients with monoallelic variants. Structural modeling of missense variants in PLXNA1 suggests distortion in the native protein. Our zebrafish studies enforce an embryonic role of plxna1a and plxna1b in the development of the central nervous system and the eye. CONCLUSION: We propose that different biallelic and monoallelic variants in PLXNA1 result in a novel neurodevelopmental syndrome mainly comprising developmental delay, brain, and eye anomalies. We hypothesize that biallelic variants in the extracellular Plexin-A1 domains lead to impaired dimerization or lack of receptor molecules, whereas monoallelic variants in the intracellular Plexin-A1 domains might impair downstream signaling through a dominant-negative effect.
Keywords: Animals; Eye Abnormalities; Genetic Association Studies; Humans; Nerve Tissue Proteins; Neurodevelopmental Disorders; Phenotype; Receptors, Cell Surface; Zebrafish

Biallelic loss-of-function variants in the splicing regulator NSRP1 cause a severe neurodevelopmental disorder with spastic cerebral palsy and epilepsy. - Calame, Daniel G; Bakhtiari, Somayeh; Logan, Rachel; Coban-Akdemir, Zeynep; Du, Haowei; Mitani, Tadahiro; Fatih, Jawid M; Hunter, Jill V; Herman, Isabella; Pehlivan, Davut; Jhangiani, Shalini N; Person, Richard; et al. (Genet Med, 2021)
PURPOSE: Alternative splicing plays a critical role in mouse neurodevelopment, regulating neurogenesis, cortical lamination, and synaptogenesis, yet few human neurodevelopmental disorders are known to result from pathogenic variation in splicing regulator genes. Nuclear Speckle Splicing Regulator Protein 1 (NSRP1) is a ubiquitously expressed splicing regulator not known to underlie a Mendelian disorder. METHODS: Exome sequencing and rare variant family-based genomics was performed as a part of the Baylor-Hopkins Center for Mendelian Genomics Initiative. Additional families were identified via GeneMatcher. RESULTS: We identified six patients from three unrelated families with homozygous loss-of-function variants in NSRP1. Clinical features include developmental delay, epilepsy, variable microcephaly (Z-scores -0.95 to -5.60), hypotonia, and spastic cerebral palsy. Brain abnormalities included simplified gyral pattern, underopercularization, and/or vermian hypoplasia. Molecular analysis identified three pathogenic NSRP1 predicted loss-of-function variant alleles: c.1359_1362delAAAG (p.Glu455AlafsTer20), c.1272dupG (p.Lys425GlufsTer5), and c.52C>T (p.Gln18Ter). The two frameshift variants result in a premature termination codon in the last exon, and the mutant transcripts are predicted to escape nonsense mediated decay and cause loss of a C-terminal nuclear localization signal required for NSRP1 function. CONCLUSION: We establish NSRP1 as a gene for a severe autosomal recessive neurodevelopmental disease trait characterized by developmental delay, epilepsy, microcephaly, and spastic cerebral palsy.
Keywords: Cerebral Palsy; Epilepsy; Humans; Microcephaly; Neurodevelopmental Disorders; Nuclear Proteins; Pedigree; RNA Splicing

Biallelic Pathogenic Variants in Associated With Congenital Myopathy. - Calame, Daniel G; Fatih, Jawid; Herman, Isabella; Akdemir, Zeynep Coban; Du, Haowei; Jhangiani, Shalini N; Richard A Gibbs; Marafi, Dana; Pehlivan, Davut; Posey, Jennifer E; Lotze, Timothy; Mancias, Pedro; et al. (Neurol Genet, 2021)
OBJECTIVE: Pathogenic variants in , the gene encoding fast skeletal muscle troponin T, were first described in autosomal dominant distal arthrogryposis type 2B2. Recently, a homozygous splice site variant, c.681+1G>A, was identified in a patient with nemaline myopathy and distal arthrogryposis. Here, we describe the second individual with congenital myopathy associated with biallelic variants. METHODS: Clinical exome sequencing data from a patient with molecularly undiagnosed congenital myopathy underwent research reanalysis. Clinical and histopathologic data were collected and compared with the single reported patient with -related congenital myopathy. RESULTS: A homozygous variant, c.481-1G>A, was identified. This variant alters a consensus splice acceptor and is predicted to affect splicing by multiple prediction tools. Both the patient reported here and the previously published patient exhibited limb, bulbar, and respiratory muscle weakness from birth, which improved over time. Other shared features include history of polyhydramnios, hypotonia, scoliosis, and high-arched palate. Distal arthrogryposis and nemaline rods, findings reported in the first patient with -related congenital myopathy, were not observed in the patient reported here. CONCLUSIONS: This report provides further evidence for the association of biallelic variants with severe recessive congenital myopathy with or without nemaline rods and distal arthrogryposis. sequencing and copy number analysis should be incorporated into the workup of congenital myopathies.

BinomiRare: A robust test for association of a rare genetic variant with a binary outcome for mixed models and any case-control proportion. - Sofer, Tamar; Lee, Jiwon; Kurniansyah, Nuzulul; Jain, Deepti; Laurie, Cecelia A; Gogarten, Stephanie M; Conomos, Matthew P; Heavner, Ben; Hu, Yao; Kooperberg, Charles; Haessler, Jeffrey; Vasan, Ramachandran S; et al. (HGG Adv, 2021)
Whole-genome sequencing (WGS) and whole-exome sequencing studies have become increasingly available and are being used to identify rare genetic variants associated with health and disease outcomes. Investigators routinely use mixed models to account for genetic relatedness or other clustering variables (e.g., family or household) when testing genetic associations. However, no existing tests of the association of a rare variant with a binary outcome in the presence of correlated data control the type 1 error where there are (1) few individuals harboring the rare allele, (2) a small proportion of cases relative to controls, and (3) covariates to adjust for. Here, we address all three issues in developing a framework for testing rare variant association with a binary trait in individuals harboring at least one risk allele. In this framework, we estimate outcome probabilities under the null hypothesis and then use them, within the individuals with at least one risk allele, to test variant associations. We extend the BinomiRare test, which was previously proposed for independent observations, and develop the Conway-Maxwell-Poisson (CMP) test and study their properties in simulations. We show that the BinomiRare test always controls the type 1 error, while the CMP test sometimes does not. We then use the BinomiRare test to test the association of rare genetic variants in target genes with small-vessel disease (SVD) stroke, short sleep, and venous thromboembolism (VTE), in whole-genome sequence data from the Trans-Omics for Precision Medicine (TOPMed) program.

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.
Keywords: Cardiometabolic Risk Factors; Chromosomes, Human, X; Eye Proteins; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Lipids; Male; Middle Aged; Nerve Tissue Proteins; Phenomics; Polymorphism, Single Nucleotide; Subcutaneous Tissue; Whole Genome Sequencing

Clinical, neuroimaging, and molecular spectrum of TECPR2-associated hereditary sensory and autonomic neuropathy with intellectual disability. - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Brösse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al. (Hum Mutat, 2021)
Bi-allelic TECPR2 variants have been associated with a complex syndrome with features of both a neurodevelopmental and neurodegenerative disorder. Here, we provide a comprehensive clinical description and variant interpretation framework for this genetic locus. Through international collaboration, we identified 17 individuals from 15 families with bi-allelic TECPR2-variants. We systemically reviewed clinical and molecular data from this cohort and 11 cases previously reported. Phenotypes were standardized using Human Phenotype Ontology terms. A cross-sectional analysis revealed global developmental delay/intellectual disability, muscular hypotonia, ataxia, hyporeflexia, respiratory infections, and central/nocturnal hypopnea as core manifestations. A review of brain magnetic resonance imaging scans demonstrated a thin corpus callosum in 52%. We evaluated 17 distinct variants. Missense variants in TECPR2 are predominantly located in the N- and C-terminal regions containing β-propeller repeats. Despite constituting nearly half of disease-associated TECPR2 variants, classifying missense variants as (likely) pathogenic according to ACMG criteria remains challenging. We estimate a pathogenic variant carrier frequency of 1/1221 in the general and 1/155 in the Jewish Ashkenazi populations. Based on clinical, neuroimaging, and genetic data, we provide recommendations for variant reporting, clinical assessment, and surveillance/treatment of individuals with TECPR2-associated disorder. This sets the stage for future prospective natural history studies.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Cohort Studies; Cross-Sectional Studies; Family; Female; Hereditary Sensory and Autonomic Neuropathies; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Models, Molecular; Mutation, Missense; Nerve Tissue Proteins; Neuroimaging; Pedigree; Phenotype; Protein Conformation

Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2021)
Genetic discoveries of Alzheimer's disease are the drivers of our understanding, and together with polygenetic risk stratification can contribute towards planning of feasible and efficient preventive and curative clinical trials. We first perform a large genetic association study by merging all available case-control datasets and by-proxy study results (discovery n = 409,435 and validation size n = 58,190). Here, we add six variants associated with Alzheimer's disease risk (near APP, CHRNE, PRKD3/NDUFAF7, PLCG2 and two exonic variants in the SHARPIN gene). Assessment of the polygenic risk score and stratifying by APOE reveal a 4 to 5.5 years difference in median age at onset of Alzheimer's disease patients in APOE ɛ4 carriers. Because of this study, the underlying mechanisms of APP can be studied to refine the amyloid cascade and the polygenic risk score provides a tool to select individuals at high risk of Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Protein Precursor; Apolipoproteins E; Case-Control Studies; Cohort Studies; Datasets as Topic; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Male; Middle Aged; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors

COPB2 loss of function causes a coatopathy with osteoporosis and developmental delay. - Marom, Ronit; Burrage, Lindsay C; Venditti, Rossella; Clément, Aurélie; Blanco-Sánchez, Bernardo; Jain, Mahim; Scott, Daryl A; Rosenfeld, Jill A; Sutton, V Reid; Shinawi, Marwan; Mirzaa, Ghayda; DeVile, Catherine; et al. (Am J Hum Genet, 2021)
Coatomer complexes function in the sorting and trafficking of proteins between subcellular organelles. Pathogenic variants in coatomer subunits or associated factors have been reported in multi-systemic disorders, i.e., coatopathies, that can affect the skeletal and central nervous systems. We have identified loss-of-function variants in COPB2, a component of the coatomer complex I (COPI), in individuals presenting with osteoporosis, fractures, and developmental delay of variable severity. Electron microscopy of COPB2-deficient subjects' fibroblasts showed dilated endoplasmic reticulum (ER) with granular material, prominent rough ER, and vacuoles, consistent with an intracellular trafficking defect. We studied the effect of COPB2 deficiency on collagen trafficking because of the critical role of collagen secretion in bone biology. COPB2 siRNA-treated fibroblasts showed delayed collagen secretion with retention of type I collagen in the ER and Golgi and altered distribution of Golgi markers. copb2-null zebrafish embryos showed retention of type II collagen, disorganization of the ER and Golgi, and early larval lethality. Copb2 mice exhibited low bone mass, and consistent with the findings in human cells and zebrafish, studies in Copb2 mouse fibroblasts suggest ER stress and a Golgi defect. Interestingly, ascorbic acid treatment partially rescued the zebrafish developmental phenotype and the cellular phenotype in Copb2 mouse fibroblasts. This work identifies a form of coatopathy due to COPB2 haploinsufficiency, explores a potential therapeutic approach for this disorder, and highlights the role of the COPI complex as a regulator of skeletal homeostasis.
Keywords: Animals; Ascorbic Acid; Bone and Bones; Brain; Child; Child, Preschool; Coat Protein Complex I; Coatomer Protein; Collagen Type I; Developmental Disabilities; Embryo, Nonmammalian; Endoplasmic Reticulum; Female; Fibroblasts; Gene Expression Regulation, Developmental; Golgi Apparatus; Haploinsufficiency; Humans; Intellectual Disability; Male; Mice; Osteoporosis; RNA, Small Interfering; Severity of Illness Index; Zebrafish

Cross-oncopanel study reveals high sensitivity and accuracy with overall analytical performance depending on genomic regions. - Gong, Binsheng; Li, Dan; Kusko, Rebecca; Novoradovskaya, Natalia; Zhang, Yifan; Wang, Shangzi; Pabón-Peña, Carlos; Zhang, Zhihong; Lai, Kevin; Cai, Wanshi; LoCoco, Jennifer S; Lader, Eric; et al. (Genome Biol, 2021)
BACKGROUND: Targeted sequencing using oncopanels requires comprehensive assessments of accuracy and detection sensitivity to ensure analytical validity. By employing reference materials characterized by the U.S. Food and Drug Administration-led SEquence Quality Control project phase2 (SEQC2) effort, we perform a cross-platform multi-lab evaluation of eight Pan-Cancer panels to assess best practices for oncopanel sequencing. RESULTS: All panels demonstrate high sensitivity across targeted high-confidence coding regions and variant types for the variants previously verified to have variant allele frequency (VAF) in the 5-20% range. Sensitivity is reduced by utilizing VAF thresholds due to inherent variability in VAF measurements. Enforcing a VAF threshold for reporting has a positive impact on reducing false positive calls. Importantly, the false positive rate is found to be significantly higher outside the high-confidence coding regions, resulting in lower reproducibility. Thus, region restriction and VAF thresholds lead to low relative technical variability in estimating promising biomarkers and tumor mutational burden. CONCLUSION: This comprehensive study provides actionable guidelines for oncopanel sequencing and clear evidence that supports a simplified approach to assess the analytical performance of oncopanels. It will facilitate the rapid implementation, validation, and quality control of oncopanels in clinical use.
Keywords: Biomarkers, Tumor; DNA Copy Number Variations; Genetic Testing; Genomics; Humans; Molecular Diagnostic Techniques; Mutation; Neoplasms; Oncogenes; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity

Deep clinicopathological phenotyping identifies a previously unrecognized pathogenic EMD splice variant. - Calame, Daniel G; Fatih, Jawid M; Herman, Isabella; Coban-Akdemir, Zeynep; Du, Haowei; Mitani, Tadahiro; Jhangiani, Shalini N; Marafi, Dana; Richard A Gibbs; Posey, Jennifer E; Mehta, Vidya P; Mohila, Carrie A; et al. (Ann Clin Transl Neurol, 2021)
Exome sequencing (ES) has revolutionized rare disease management, yet only ~25%-30% of patients receive a molecular diagnosis. A limiting factor is the quality of available phenotypic data. Here, we describe how deep clinicopathological phenotyping yielded a molecular diagnosis for a 19-year-old proband with muscular dystrophy and negative clinical ES. Deep phenotypic analysis identified two critical data points: (1) the absence of emerin protein in muscle biopsy and (2) clinical features consistent with Emery-Dreifuss muscular dystrophy. Sequencing data analysis uncovered an ultra-rare, intronic variant in EMD, the gene encoding emerin. The variant, NM_000117.3: c.188-6A > G, is predicted to impact splicing by in silico tools. This case thus illustrates how better integration of clinicopathologic data into ES analysis can enhance diagnostic yield with implications for clinical practice.
Keywords: Adult; Exome Sequencing; Humans; Male; Membrane Proteins; Muscle, Skeletal; Muscular Dystrophy, Emery-Dreifuss; Nuclear Proteins; Young Adult

Deforming Polyarthritis in a North Indian Family-Clinical Expansion of STING-Associated Vasculopathy with Onset in Infancy (SAVI). - Anjani, Gummadi; Jindal, Ankur Kumar; Prithvi, Ashwini; Kaur, Anit; Rawat, Amit; Sharma, Madhubala; Bo Yuan; Chinn, Ivan K; Singh, Surjit (J Clin Immunol, 2021)
Keywords: Anti-Inflammatory Agents; Arthritis; Biomarkers; Child; Child, Preschool; Diagnosis, Differential; Family; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Immunosuppressive Agents; India; Joints; Male; Membrane Proteins; Phenotype; Tomography, X-Ray Computed; Treatment Outcome

Delineating the molecular and phenotypic spectrum of the SETD1B-related syndrome. - Weerts, Marjolein J A; Lanko, Kristina; Guzmán-Vega, Francisco J; Jackson, Adam; Ramakrishnan, Reshmi; Cardona-Londoño, Kelly J; Peña-Guerra, Karla A; van Bever, Yolande; van Paassen, Barbara W; Kievit, Anneke; van Slegtenhorst, Marjon; Allen, Nicholas M; et al. (Genet Med, 2021)
PURPOSE: Pathogenic variants in SETD1B have been associated with a syndromic neurodevelopmental disorder including intellectual disability, language delay, and seizures. To date, clinical features have been described for 11 patients with (likely) pathogenic SETD1B sequence variants. This study aims to further delineate the spectrum of the SETD1B-related syndrome based on characterizing an expanded patient cohort. METHODS: We perform an in-depth clinical characterization of a cohort of 36 unpublished individuals with SETD1B sequence variants, describing their molecular and phenotypic spectrum. Selected variants were functionally tested using in vitro and genome-wide methylation assays. RESULTS: Our data present evidence for a loss-of-function mechanism of SETD1B variants, resulting in a core clinical phenotype of global developmental delay, language delay including regression, intellectual disability, autism and other behavioral issues, and variable epilepsy phenotypes. Developmental delay appeared to precede seizure onset, suggesting SETD1B dysfunction impacts physiological neurodevelopment even in the absence of epileptic activity. Males are significantly overrepresented and more severely affected, and we speculate that sex-linked traits could affect susceptibility to penetrance and the clinical spectrum of SETD1B variants. CONCLUSION: Insights from this extensive cohort will facilitate the counseling regarding the molecular and phenotypic landscape of newly diagnosed patients with the SETD1B-related syndrome.
Keywords: Epilepsy; Histone-Lysine N-Methyltransferase; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Phenotype; Seizures

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.
Keywords: Adolescent; Adult; Age of Onset; Child, Preschool; China; Cohort Studies; Exome; Exome Sequencing; Female; Genetic Predisposition to Disease; Humans; Male; Retrospective Studies; Scoliosis

DNA methylation patterns identify subgroups of pancreatic neuroendocrine tumors with clinical association. - Lakis, Vanessa; Lawlor, Rita T; Newell, Felicity; Patch, Ann-Marie; Mafficini, Andrea; Sadanandam, Anguraj; Koufariotis, Lambros T; Johnston, Rebecca L; Leonard, Conrad; Wood, Scott; Rusev, Borislav; Corbo, Vincenzo; et al. (Commun Biol, 2021)
Here we report the DNA methylation profile of 84 sporadic pancreatic neuroendocrine tumors (PanNETs) with associated clinical and genomic information. We identified three subgroups of PanNETs, termed T1, T2 and T3, with distinct patterns of methylation. The T1 subgroup was enriched for functional tumors and ATRX, DAXX and MEN1 wild-type genotypes. The T2 subgroup contained tumors with mutations in ATRX, DAXX and MEN1 and recurrent patterns of chromosomal losses in half of the genome with no association between regions with recurrent loss and methylation levels. T2 tumors were larger and had lower methylation in the MGMT gene body, which showed positive correlation with gene expression. The T3 subgroup harboured mutations in MEN1 with recurrent loss of chromosome 11, was enriched for grade G1 tumors and showed histological parameters associated with better prognosis. Our results suggest a role for methylation in both driving tumorigenesis and potentially stratifying prognosis in PanNETs.
Keywords: Biomarkers, Tumor; Carcinoma, Neuroendocrine; DNA Methylation; Epigenesis, Genetic; Epigenome; Epigenomics; Genetic Predisposition to Disease; Humans; Neoplasm Grading; Pancreatic Neoplasms; Phenotype; Tumor Burden

Dominant mitochondrial membrane protein-associated neurodegeneration (MPAN) variants cluster within a specific C19orf12 isoform. - Rickman, Olivia J; Salter, Claire G; Gunning, Adam C; Fasham, James; Voutsina, Nikol; Leslie, Joseph S; McGavin, Lucy; Cross, Harold E; Posey, Jennifer E; Akdemir, Zeynep Coban; Jhangiani, Shalini N; James R Lupski; et al. (Parkinsonism Relat Disord, 2021)
Mitochondria membrane protein-associated neurodegeneration (MPAN) neurodegenerative disorder is typically associated with biallelic C19orf12 variants. Here we describe a new and review candidate previous monoallelic de novo C19orf12 variants to define loss of function mutations located in the putative non-membrane spanning C19orf12 isoform as the potential basis of monoallelic MPAN.
Keywords: Amish; Humans; Iron Metabolism Disorders; Loss of Function Mutation; Magnetic Resonance Imaging; Membrane Proteins; Mitochondrial Membranes; Mitochondrial Proteins; Neuroaxonal Dystrophies; Pedigree; Protein Isoforms

Epigenome-wide association study of mitochondrial genome copy number. - Wang, Penglong; Castellani, Christina A; Yao, Jie; Huan, Tianxiao; Bielak, Lawrence F; Zhao, Wei; Haessler, Jeffrey; Joehanes, Roby; Sun, Xianbang; Guo, Xiuqing; Longchamps, Ryan J; Manson, JoAnn E; et al. (Hum Mol Genet, 2021)
We conducted cohort- and race-specific epigenome-wide association analyses of mitochondrial deoxyribonucleic acid (mtDNA) copy number (mtDNA CN) measured in whole blood from participants of African and European origins in five cohorts (n = 6182, mean age = 57-67 years, 65% women). In the meta-analysis of all the participants, we discovered 21 mtDNA CN-associated DNA methylation sites (CpG) (P < 1 × 10-7), with a 0.7-3.0 standard deviation increase (3 CpGs) or decrease (18 CpGs) in mtDNA CN corresponding to a 1% increase in DNA methylation. Several significant CpGs have been reported to be associated with at least two risk factors (e.g. chronological age or smoking) for cardiovascular disease (CVD). Five genes [PR/SET domain 16, nuclear receptor subfamily 1 group H member 3 (NR1H3), DNA repair protein, DNA polymerase kappa and decaprenyl-diphosphate synthase subunit 2], which harbor nine significant CpGs, are known to be involved in mitochondrial biosynthesis and functions. For example, NR1H3 encodes a transcription factor that is differentially expressed during an adipose tissue transition. The methylation level of cg09548275 in NR1H3 was negatively associated with mtDNA CN (effect size = -1.71, P = 4 × 10-8) and was positively associated with the NR1H3 expression level (effect size = 0.43, P = 0.0003), which indicates that the methylation level in NR1H3 may underlie the relationship between mtDNA CN, the NR1H3 transcription factor and energy expenditure. In summary, the study results suggest that mtDNA CN variation in whole blood is associated with DNA methylation levels in genes that are involved in a wide range of mitochondrial activities. These findings will help reveal molecular mechanisms between mtDNA CN and CVD.
Keywords: Aged; DNA Copy Number Variations; DNA Methylation; DNA, Mitochondrial; Epigenome; Female; Genome, Mitochondrial; Humans; Male; Middle Aged

The Exceptional Responders Initiative: Feasibility of a National Cancer Institute Pilot Study. - Conley, Barbara A; Staudt, Lou; Takebe, Naoko; David A Wheeler; Wang, Linghua; Cardenas, Maria F; Korchina, Viktoriya; Zenklusen, Jean Claude; McShane, Lisa M; Tricoli, James V; Williams, Paul M; Lubensky, Irina; et al. (J Natl Cancer Inst, 2021)
BACKGROUND: Tumor molecular profiling from patients experiencing exceptional responses to systemic therapy may provide insights into cancer biology and improve treatment tailoring. This pilot study evaluates the feasibility of identifying exceptional responders retrospectively, obtaining pre-exceptional response treatment tumor tissues, and analyzing them with state-of-the-art molecular analysis tools to identify potential molecular explanations for responses. METHODS: Exceptional response was defined as partial (PR) or complete (CR) response to a systemic treatment with population PR or CR rate less than 10% or an unusually long response (eg, duration >3 times published median). Cases proposed by patients' clinicians were reviewed by clinical and translational experts. Tumor and normal tissue (if possible) were profiled with whole exome sequencing and, if possible, targeted deep sequencing, RNA sequencing, methylation arrays, and immunohistochemistry. Potential germline mutations were tracked for relevance to disease. RESULTS: Cases reflected a variety of tumors and standard and investigational treatments. Of 520 cases, 476 (91.5%) were accepted for further review, and 222 of 476 (46.6%) proposed cases met requirements as exceptional responders. Clinical data were obtained from 168 of 222 cases (75.7%). Tumor was provided from 130 of 168 cases (77.4%). Of 117 of the 130 (90.0%) cases with sufficient nucleic acids, 109 (93.2%) were successfully analyzed; 6 patients had potentially actionable germline mutations. CONCLUSION: Exceptional responses occur with standard and investigational treatment. Retrospective identification of exceptional responders, accessioning, and sequencing of pretreatment archived tissue is feasible. Data from molecular analyses of tumors, particularly when combining results from patients who received similar treatments, may elucidate molecular bases for exceptional responses.
Keywords: Adult; Aged; Aged, 80 and over; Exome Sequencing; Feasibility Studies; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; National Cancer Institute (U.S.); Neoplasms; Pilot Projects; Precision Medicine; Retrospective Studies; Sequence Analysis, RNA; Transcriptome; United States

Exome sequencing in children with clinically suspected maturity-onset diabetes of the young. - Tosur, Mustafa; Soler-Alfonso, Claudia; Chan, Katie M; Khayat, Michael M; Jhangiani, Shalini N; Meng, Qingchang; Refaey, Ahmad; Donna M Muzny; Richard A Gibbs; David R Murdock; Posey, Jennifer E; Balasubramanyam, Ashok; et al. (Pediatr Diabetes, 2021)
OBJECTIVE: Commercial gene panels identify pathogenic variants in as low as 27% of patients suspected to have MODY, suggesting the role of yet unidentified pathogenic variants. We sought to identify novel gene variants associated with MODY. RESEARCH DESIGN AND METHODS: We recruited 10 children with a clinical suspicion of MODY but non-diagnostic commercial MODY gene panels. We performed exome sequencing (ES) in them and their parents. RESULTS: Mean age at diabetes diagnosis was 10 (± 3.8) years. Six were females; 4 were non-Hispanic white, 5 Hispanic, and 1 Asian. Our variant prioritization analysis identified a pathogenic, de novo variant in INS (c.94G > A, p.Gly32Ser), confirmed by Sanger sequencing, in a proband who was previously diagnosed with "autoantibody-negative type 1 diabetes (T1D)" at 3 y/o. This rare variant, absent in the general population (gnomAD database), has been reported previously in neonatal diabetes. We also identified a frameshift deletion (c.2650delC, p.Gln884AsnfsTer57) in RFX6 in a child with a previous diagnosis of "autoantibody-negative T1D" at 12 y/o. The variant was inherited from the mother, who was diagnosed with "thin type 2 diabetes" at 25 y/o. Heterozygous protein-truncating variants in RFX6 gene have been recently reported in individuals with MODY. CONCLUSIONS: We diagnosed two patients with MODY using ES in children initially classified as "T1D". One has a likely pathogenic novel gene variant not previously associated with MODY. We demonstrate the clinical utility of ES in patients with clinical suspicion of MODY.
Keywords: Adolescent; Autoantibodies; Child; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Diagnosis, Differential; Exome Sequencing; Female; Frameshift Mutation; Genetic Variation; Humans; Islets of Langerhans; Male; Mutation, Missense; Pedigree

Exome sequencing reveals predominantly de novo variants in disorders with intellectual disability (ID) in the founder population of Finland. - Järvelä, Irma; Määttä, Tuomo; Acharya, Anushree; Leppälä, Juha; Jhangiani, Shalini N; Arvio, Maria; Siren, Auli; Kankuri-Tammilehto, Minna; Kokkonen, Hannaleena; Palomäki, Maarit; Varilo, Teppo; Fang, Mary; et al. (Hum Genet, 2021)
The genetics of autosomal recessive intellectual disability (ARID) has mainly been studied in consanguineous families, however, founder populations may also be of interest to study intellectual disability (ID) and the contribution of ARID. Here, we used a genotype-driven approach to study the genetic landscape of ID in the founder population of Finland. A total of 39 families with syndromic and non-syndromic ID were analyzed using exome sequencing, which revealed a variant in a known ID gene in 27 families. Notably, 75% of these variants in known ID genes were de novo or suspected de novo (64% autosomal dominant; 11% X-linked) and 25% were inherited (14% autosomal recessive; 7% X-linked; and 4% autosomal dominant). A dual molecular diagnosis was suggested in two families (5%). Via additional analysis and molecular testing, we identified three cases with an abnormal molecular karyotype, including chr21q22.12q22.2 uniparental disomy with a mosaic interstitial 2.7 Mb deletion covering DYRK1A and KCNJ6. Overall, a pathogenic or likely pathogenic variant was identified in 64% (25/39) of the families. Last, we report an alternate inheritance model for 3 known ID genes (UBA7, DDX47, DHX58) and discuss potential candidate genes for ID, including SYPL1 and ERGIC3 with homozygous founder variants and de novo variants in POLR2F and DNAH3. In summary, similar to other European populations, de novo variants were the most common variants underlying ID in the studied Finnish population, with limited contribution of ARID to ID etiology, though mainly driven by founder and potential founder variation in the latter case.
Keywords: Exome; Exome Sequencing; Family; Female; Finland; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Homozygote; Humans; Intellectual Disability; Male; Pedigree

Exome variant discrepancies due to reference-genome differences. - Li, He; Dawood, Moez; Khayat, Michael M; Farek, Jesse R; Jhangiani, Shalini N; Khan, Ziad M; Mitani, Tadahiro; Coban-Akdemir, Zeynep; James R Lupski; Eric Venner; Posey, Jennifer E; Aniko Sabo; et al. (Am J Hum Genet, 2021)
Despite release of the GRCh38 human reference genome more than seven years ago, GRCh37 remains more widely used by most research and clinical laboratories. To date, no study has quantified the impact of utilizing different reference assemblies for the identification of variants associated with rare and common diseases from large-scale exome-sequencing data. By calling variants on both the GRCh37 and GRCh38 references, we identified single-nucleotide variants (SNVs) and insertion-deletions (indels) in 1,572 exomes from participants with Mendelian diseases and their family members. We found that a total of 1.5% of SNVs and 2.0% of indels were discordant when different references were used. Notably, 76.6% of the discordant variants were clustered within discrete discordant reference patches (DISCREPs) comprising only 0.9% of loci targeted by exome sequencing. These DISCREPs were enriched for genomic elements including segmental duplications, fix patch sequences, and loci known to contain alternate haplotypes. We identified 206 genes significantly enriched for discordant variants, most of which were in DISCREPs and caused by multi-mapped reads on the reference assembly that lacked the variant call. Among these 206 genes, eight are implicated in known Mendelian diseases and 53 are associated with common phenotypes from genome-wide association studies. In addition, variant interpretations could also be influenced by the reference after lifting-over variant loci to another assembly. Overall, we identified genes and genomic loci affected by reference assembly choice, including genes associated with Mendelian disorders and complex human diseases that require careful evaluation in both research and clinical applications.
Keywords: Cohort Studies; Exome; Genetic Diseases, Inborn; Genome, Human; Humans; Polymorphism, Single Nucleotide; Reference Values

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2021)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.
Keywords: Blood Pressure; Epistasis, Genetic; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Polymorphism, Single Nucleotide

Genetic testing in ambulatory cardiology clinics reveals high rate of findings with clinical management implications. - David R Murdock; Eric Venner; Donna M Muzny; Ginger A Metcalf; Mullai Murugan; Hadley, Trevor D; Chander, Varuna; de Vries, Paul S; Jia, Xiaoming; Hussain, Aliza; Agha, Ali M; Aniko Sabo; et al. (Genet Med, 2021)
PURPOSE: Cardiovascular disease (CVD) is the leading cause of death in adults in the United States, yet the benefits of genetic testing are not universally accepted. METHODS: We developed the "HeartCare" panel of genes associated with CVD, evaluating high-penetrance Mendelian conditions, coronary artery disease (CAD) polygenic risk, LPA gene polymorphisms, and specific pharmacogenetic (PGx) variants. We enrolled 709 individuals from cardiology clinics at Baylor College of Medicine, and samples were analyzed in a CAP/CLIA-certified laboratory. Results were returned to the ordering physician and uploaded to the electronic medical record. RESULTS: Notably, 32% of patients had a genetic finding with clinical management implications, even after excluding PGx results, including 9% who were molecularly diagnosed with a Mendelian condition. Among surveyed physicians, 84% reported medical management changes based on these results, including specialist referrals, cardiac tests, and medication changes. LPA polymorphisms and high polygenic risk of CAD were found in 20% and 9% of patients, respectively, leading to diet, lifestyle, and other changes. Warfarin and simvastatin pharmacogenetic variants were present in roughly half of the cohort. CONCLUSION: Our results support the use of genetic information in routine cardiovascular health management and provide a roadmap for accompanying research.
Keywords: Adult; Cardiology; Cardiovascular Diseases; Genetic Testing; Humans; Pharmacogenetics; Pharmacogenomic Testing; United States

Genetically determined NLRP3 inflammasome activation associates with systemic inflammation and cardiovascular mortality. - Schunk, Stefan J; Kleber, Marcus E; Marz, Winfried; Pang, Shichao; Zewinger, Stephen; Triem, Sarah; Ege, Philipp; Reichert, Matthias C; Krawczyk, Marcin; Weber, Susanne N; Jaumann, Isabella; Schmit, David; et al. (Eur Heart J, 2021)
AIMS: Inflammation plays an important role in cardiovascular disease (CVD) development. The NOD-like receptor protein-3 (NLRP3) inflammasome contributes to the development of atherosclerosis in animal models. Components of the NLRP3 inflammasome pathway such as interleukin-1β can therapeutically be targeted. Associations of genetically determined inflammasome-mediated systemic inflammation with CVD and mortality in humans are unknown. METHODS AND RESULTS: We explored the association of genetic NLRP3 variants with prevalent CVD and cardiovascular mortality in 538 167 subjects on the individual participant level in an explorative gene-centric approach without performing multiple testing. Functional relevance of single-nucleotide polymorphisms on NLRP3 inflammasome activation has been evaluated in monocyte-enriched peripheral blood mononuclear cells (PBMCs). Genetic analyses identified the highly prevalent (minor allele frequency 39.9%) intronic NLRP3 variant rs10754555 to affect NLRP3 gene expression. rs10754555 carriers showed significantly higher C-reactive protein and serum amyloid A plasma levels. Carriers of the G allele showed higher NLRP3 inflammasome activation in isolated human PBMCs. In carriers of the rs10754555 variant, the prevalence of coronary artery disease was significantly higher as compared to non-carriers with a significant interaction between rs10754555 and age. Importantly, rs10754555 carriers had significantly higher risk for cardiovascular mortality during follow-up. Inflammasome inducers (e.g. urate, triglycerides, apolipoprotein C3) modulated the association between rs10754555 and mortality. CONCLUSION: The NLRP3 intronic variant rs10754555 is associated with increased systemic inflammation, inflammasome activation, prevalent coronary artery disease, and mortality. This study provides evidence for a substantial role of genetically driven systemic inflammation in CVD and highlights the NLRP3 inflammasome as a therapeutic target.
Keywords: Cardiovascular Diseases; Humans; Inflammasomes; Inflammation; Leukocytes, Mononuclear; NLR Family, Pyrin Domain-Containing 3 Protein

Genome-wide ancestry and introgression in a Zambian baboon hybrid zone. - Chiou, Kenneth L; Bergey, Christina M; Burrell, Andrew S; Disotell, Todd R; Jeffrey Rogers; Jolly, Clifford J; Phillips-Conroy, Jane E (Mol Ecol, 2021)
Hybridization in nature offers unique insights into the process of natural selection in incipient species and their hybrids. In order to evaluate the patterns and targets of selection, we examine a recently discovered baboon hybrid zone in the Kafue River Valley of Zambia, where Kinda baboons (Papio kindae) and grey-footed chacma baboons (P. ursinus griseipes) coexist with hybridization. We genotyped baboons at 14,962 variable genome-wide autosomal markers using double-digest RADseq. We compared ancestry patterns from this genome-wide data set to previously reported ancestry from mitochondrial-DNA and Y-chromosome sources. We also fit a Bayesian genomic cline model to scan for genes with extreme patterns of introgression. We show that the Kinda baboon Y chromosome has penetrated the species boundary to a greater extent than either mitochondrial DNA or the autosomal chromosomes. We also find evidence for overall restricted introgression in the JAK/STAT signalling pathway. Echoing results in other species including humans, we find evidence for enhanced and/or directional introgression of immune-related genes or pathways including the toll-like receptor pathway, the blood coagulation pathway, and the LY96 gene. Finally we show enhanced introgression and excess chacma baboon ancestry in the sperm tail gene ODF2. Together, our results elucidate the dynamics of introgressive hybridization in a primate system while identifying genes and pathways possibly under selection.
Keywords: Animals; Bayes Theorem; DNA, Mitochondrial; Hybridization, Genetic; Papio; Zambia

Genome-wide association study of circulating interleukin 6 levels identifies novel loci. - Ahluwalia, Tarunveer S; Prins, Bram P; Abdollahi, Mohammadreza; Armstrong, Nicola J; Aslibekyan, Stella; Bain, Lisa; Jefferis, Barbara; Baumert, Jens; Beekman, Marian; Ben-Shlomo, Yoav; Bis, Joshua C; Mitchell, Braxton D; et al. (Hum Mol Genet, 2021)
Interleukin 6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on chromosome (Chr) 2q14, (Pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (Pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (Pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.
Keywords: Cohort Studies; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; HLA-DRB1 Chains; Humans; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Interleukin-6; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; White People

Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women. - Jones, Garan; Trajanoska, Katerina; Santanasto, Adam J; Stringa, Najada; Kuo, Chia-Ling; Atkins, Janice L; Lewis, Joshua R; Duong, ThuyVy; Hong, Shengjun; Biggs, Mary L; Luan, Jian'an; Sarnowski, Chloe; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10), arthritis (GDF5 p = 4 × 10), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 5; HLA-DQ alpha-Chains; Humans; Male; Middle Aged; Muscle Strength; Muscle Weakness; Polymorphism, Single Nucleotide; Sarcopenia

Genomic considerations for FHIR®; eMERGE implementation lessons. - Mullai Murugan; Babb, Lawrence J; Overby Taylor, Casey; Rasmussen, Luke V; Freimuth, Robert R; Eric Venner; Yan, Fei; Yi, Victoria; Granite, Stephen J; Zouk, Hana; Aronson, Samuel J; Power, Kevin; et al. (J Biomed Inform, 2021)
Structured representation of clinical genetic results is necessary for advancing precision medicine. The Electronic Medical Records and Genomics (eMERGE) Network's Phase III program initially used a commercially developed XML message format for standardized and structured representation of genetic results for electronic health record (EHR) integration. In a desire to move towards a standard representation, the network created a new standardized format based upon Health Level Seven Fast Healthcare Interoperability Resources (HL7® FHIR®), to represent clinical genomics results. These new standards improve the utility of HL7® FHIR® as an international healthcare interoperability standard for management of genetic data from patients. This work advances the establishment of standards that are being designed for broad adoption in the current health information technology landscape.
Keywords: Electronic Health Records; Genomics; Health Level Seven; Humans; Medical Informatics; Precision Medicine

Germline mutation in : a heterogeneous, multi-systemic developmental disorder characterized by transcriptional dysregulation. - Hansen, Adam W; Arora, Payal; Khayat, Michael M; Smith, Leah J; Lewis, Andrea M; Rossetti, Linda Z; Jayaseelan, Joy; Cristian, Ingrid; Haynes, Devon; DiTroia, Stephanie; Meeks, Naomi; Delgado, Mauricio R; et al. (HGG Adv, 2021)
germline variation in was recently reported to associate with a neurodevelopmental disorder. We report twelve individuals harboring putatively pathogenic or inherited variants in , detail their phenotypes, and map all known variants to the domain structure of and crystal structure of RNA polymerase II. Affected individuals were ascertained from a local data lake, pediatric genetics clinic, and an online community of families of affected individuals. These include six affected by missense variants (including one previously reported individual), four clinical laboratory samples affected by missense variation with unknown inheritance-with yeast functional assays further supporting altered function-one affected by a in-frame deletion, and one affected by a C-terminal frameshift variant inherited from a largely asymptomatic mother. Recurrently observed phenotypes include ataxia, joint hypermobility, short stature, skin abnormalities, congenital cardiac abnormalities, immune system abnormalities, hip dysplasia, and short Achilles tendons. We report a significantly higher occurrence of epilepsy (8/12, 66.7%) than previously reported (3/15, 20%) (p value = 0.014196; chi-square test) and a lower occurrence of hypotonia (8/12, 66.7%) than previously reported (14/15, 93.3%) (p value = 0.076309). -related developmental disorders likely represent a spectrum of related, multi-systemic developmental disorders, driven by distinct mechanisms, converging at a single locus.

Haploinsufficiency of ARFGEF1 is associated with developmental delay, intellectual disability, and epilepsy with variable expressivity. - Thomas, Quentin; Gautier, Thierry; Marafi, Dana; Besnard, Thomas; Willems, Marjolaine; Moutton, Sebastien; Isidor, Bertand; Cogné, Benjamin; Conrad, Solène; Tenconi, Romano; Iascone, Maria; Sorlin, Arthur; et al. (Genet Med, 2021)
PURPOSE: ADP ribosylation factor guanine nucleotide exchange factors (ARFGEFs) are a family of proteins implicated in cellular trafficking between the Golgi apparatus and the plasma membrane through vesicle formation. Among them is ARFGEF1/BIG1, a protein involved in axon elongation, neurite development, and polarization processes. ARFGEF1 has been previously suggested as a candidate gene for different types of epilepsies, although its implication in human disease has not been well characterized. METHODS: International data sharing, in silico predictions, and in vitro assays with minigene study, western blot analyses, and RNA sequencing. RESULTS: We identified 13 individuals with heterozygous likely pathogenic variants in ARFGEF1. These individuals displayed congruent clinical features of developmental delay, behavioral problems, abnormal findings on brain magnetic resonance image (MRI), and epilepsy for almost half of them. While nearly half of the cohort carried de novo variants, at least 40% of variants were inherited from mildly affected parents who were clinically re-evaluated by reverse phenotyping. Our in silico predictions and in vitro assays support the contention that ARFGEF1-related conditions are caused by haploinsufficiency, and are transmitted in an autosomal dominant fashion with variable expressivity. CONCLUSION: We provide evidence that loss-of-function variants in ARFGEF1 are implicated in sporadic and familial cases of developmental delay with or without epilepsy.
Keywords: Epilepsy; Guanine Nucleotide Exchange Factors; Haploinsufficiency; Heterozygote; Humans; Intellectual Disability

High prevalence of multilocus pathogenic variation in neurodevelopmental disorders in the Turkish population. - Mitani, Tadahiro; Isikay, Sedat; Gezdirici, Alper; Gulec, Elif Yilmaz; Punetha, Jaya; Fatih, Jawid M; Herman, Isabella; Akay, Gulsen; Du, Haowei; Calame, Daniel G; Ayaz, Akif; Tos, Tulay; et al. (Am J Hum Genet, 2021)
Neurodevelopmental disorders (NDDs) are clinically and genetically heterogenous; many such disorders are secondary to perturbation in brain development and/or function. The prevalence of NDDs is > 3%, resulting in significant sociocultural and economic challenges to society. With recent advances in family-based genomics, rare-variant analyses, and further exploration of the Clan Genomics hypothesis, there has been a logarithmic explosion in neurogenetic "disease-associated genes" molecular etiology and biology of NDDs; however, the majority of NDDs remain molecularly undiagnosed. We applied genome-wide screening technologies, including exome sequencing (ES) and whole-genome sequencing (WGS), to identify the molecular etiology of 234 newly enrolled subjects and 20 previously unsolved Turkish NDD families. In 176 of the 234 studied families (75.2%), a plausible and genetically parsimonious molecular etiology was identified. Out of 176 solved families, deleterious variants were identified in 218 distinct genes, further documenting the enormous genetic heterogeneity and diverse perturbations in human biology underlying NDDs. We propose 86 candidate disease-trait-associated genes for an NDD phenotype. Importantly, on the basis of objective and internally established variant prioritization criteria, we identified 51 families (51/176 = 28.9%) with multilocus pathogenic variation (MPV), mostly driven by runs of homozygosity (ROHs) - reflecting genomic segments/haplotypes that are identical-by-descent. Furthermore, with the use of additional bioinformatic tools and expansion of ES to additional family members, we established a molecular diagnosis in 5 out of 20 families (25%) who remained undiagnosed in our previously studied NDD cohort emanating from Turkey.
Keywords: Adolescent; Adult; Child; Child, Preschool; Cohort Studies; Exome Sequencing; Female; Genomics; Humans; Infant; Infant, Newborn; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Prevalence; Turkey; Young Adult

A High-throughput Approach to Identify Effective Systemic Agents for the Treatment of Anaplastic Thyroid Carcinoma. - Henderson, Ying C; Mohamed, Abdallah S R; Maniakas, Anastasios; Chen, Yunyun; Powell, Reid T; Peng, Shaohua; Cardenas, Maria; Williams, Michelle D; Bell, Diana; Zafereo, Mark E; Wang, Rui Jennifer; Steven E Scherer; et al. (J Clin Endocrinol Metab, 2021)
BACKGROUND: Despite the use of aggressive multimodality treatment, most anaplastic thyroid carcinoma (ATC) patients die within a year of diagnosis. Although the combination of BRAF and MEK inhibitors has recently been approved for use in BRAF-mutated ATC, they remain effective in a minority of patients who are likely to develop drug resistance. There remains a critical clinical need for effective systemic agents for ATC with a reasonable toxicity profile to allow for rapid translational development. MATERIAL AND METHODS: Twelve human thyroid cancer cell lines with comprehensive genomic characterization were used in a high-throughput screening (HTS) of 257 compounds to select agents with maximal growth inhibition. Cell proliferation, colony formation, orthotopic thyroid models, and patient-derived xenograft (PDX) models were used to validate the selected agents. RESULTS: Seventeen compounds were effective, and docetaxel, LBH-589, and pralatrexate were selected for additional in vitro and in vivo analysis as they have been previously approved by the US Food and Drug Administration for other cancers. Significant tumor growth inhibition (TGI) was detected in all tested models treated with LBH-589; pralatrexate demonstrated significant TGI in the orthotopic papillary thyroid carcinoma model and 2 PDX models; and docetaxel demonstrated significant TGI only in the context of mutant TP53. CONCLUSIONS: HTS identified classes of systemic agents that demonstrate preferential effectiveness against aggressive thyroid cancers, particularly those with mutant TP53. Preclinical validation in both orthotopic and PDX models, which are accurate in vivo models mimicking tumor microenvironment, may support initiation of early-phase clinical trials in non-BRAF mutated or refractory to BRAF/MEK inhibition ATC.
Keywords: Animals; Antineoplastic Agents; Carcinogenicity Tests; Cell Line, Tumor; Disease Models, Animal; High-Throughput Screening Assays; Humans; Protein Kinase Inhibitors; Proto-Oncogene Proteins B-raf; Thyroid Carcinoma, Anaplastic; Thyroid Neoplasms; Tumor Microenvironment

Identification of Deep-Intronic Splice Mutations in a Large Cohort of Patients With Inherited Retinal Diseases. - Qian, Xinye; Wang, Jun; Wang, Meng; Igelman, Austin D; Jones, Kaylie D; Yumei Li; Wang, Keqing; Goetz, Kerry E; Birch, David G; Yang, Paul; Pennesi, Mark E; Rui Chen (Front Genet, 2021)
High throughput sequencing technologies have revolutionized the identification of mutations responsible for a diverse set of Mendelian disorders, including inherited retinal disorders (IRDs). However, the causal mutations remain elusive for a significant proportion of patients. This may be partially due to pathogenic mutations located in non-coding regions, which are largely missed by capture sequencing targeting the coding regions. The advent of whole-genome sequencing (WGS) allows us to systematically detect non-coding variations. However, the interpretation of these variations remains a significant bottleneck. In this study, we investigated the contribution of deep-intronic splice variants to IRDs. WGS was performed for a cohort of 571 IRD patients who lack a confident molecular diagnosis, and potential deep intronic variants that affect proper splicing were identified using SpliceAI. A total of six deleterious deep intronic variants were identified in eight patients. An minigene system was applied to further validate the effect of these variants on the splicing pattern of the associated genes. The prediction scores assigned to splice-site disruption positively correlated with the impact of mutations on splicing, as those with lower prediction scores demonstrated partial splicing. Through this study, we estimated the contribution of deep-intronic splice mutations to unassigned IRD patients and leveraged and methods to establish a framework for prioritizing deep intronic variant candidates for mechanistic and functional analyses.

IFIH1 loss-of-function variants contribute to very early-onset inflammatory bowel disease. - Cananzi, Mara; Wohler, Elizabeth; Marzollo, Antonio; Colavito, Davide; You, Jing; Jing, Huie; Bresolin, Silvia; Gaio, Paola; Martin, Renan; Mescoli, Claudia; Bade, Sangeeta; Posey, Jennifer E; et al. (Hum Genet, 2021)
Genetic defects of innate immunity impairing intestinal bacterial sensing are linked to the development of Inflammatory Bowel Disease (IBD). Although much evidence supports a role of the intestinal virome in gut homeostasis, most studies focus on intestinal viral composition rather than on host intestinal viral sensitivity. To demonstrate the association between the development of Very Early Onset IBD (VEOIBD) and variants in the IFIH1 gene which encodes MDA5, a key cytosolic sensor for viral nucleic acids. Whole exome sequencing (WES) was performed in two independent cohorts of children with VEOIBD enrolled in Italy (n = 18) and USA (n = 24). Luciferase reporter assays were employed to assess MDA5 activity. An enrichment analysis was performed on IFIH1 comparing 42 VEOIBD probands with 1527 unrelated individuals without gastrointestinal or immunological issues. We identified rare, likely loss-of-function (LoF), IFIH1 variants in eight patients with VEOIBD from a combined cohort of 42 children. One subject, carrying a homozygous truncating variant resulting in complete LoF, experienced neonatal-onset, pan-gastrointestinal, IBD-like enteropathy plus multiple infectious episodes. The remaining seven subjects, affected by VEOIBD without immunodeficiency, were carriers of one LoF variant in IFIH1. Among these, two patients also carried a second hypomorphic variant, with partial function apparent when MDA5 was weakly stimulated. Furthermore, IFIH1 variants were significantly enriched in children with VEOIBD as compared to controls (p = 0.007). Complete and partial MDA5 deficiency is associated with VEOIBD with variable penetrance and expressivity, suggesting a role for impaired intestinal viral sensing in IBD pathogenesis.
Keywords: Child, Preschool; Female; Humans; Infant; Inflammatory Bowel Diseases; Interferon-Induced Helicase, IFIH1; Italy; Loss of Function Mutation; Male; Whole Genome Sequencing

Large-scale plasma proteomic analysis identifies proteins and pathways associated with dementia risk. - Walker, Keenan A; Chen, Jingsha; Zhang, Jingning; Fornage, Myriam; Yang, Yunju; Zhou, Linda; Grams, Morgan E; Tin, Adrienne; Daya, Natalie; Hoogeveen, Ron C; Wu, Aozhou; Sullivan, Kevin J; et al. (Nat Aging, 2021)
The plasma proteomic changes that precede the onset of dementia could yield insights into disease biology and highlight new biomarkers and avenues for intervention. We quantified 4,877 plasma proteins in nondemented older adults in the Atherosclerosis Risk in Communities cohort and performed a proteome-wide association study of dementia risk over five years (n = 4,110; 428 incident cases). Thirty-eight proteins were associated with incident dementia after Bonferroni correction. Of these, 16 were also associated with late-life dementia risk when measured in plasma collected nearly 20 years earlier, during mid-life. Two-sample Mendelian randomization causally implicated two dementia-associated proteins (SVEP1 and angiostatin) in Alzheimer's disease. SVEP1, an immunologically relevant cellular adhesion protein, was found to be part of larger dementia-associated protein networks, and circulating levels were associated with atrophy in brain regions vulnerable to Alzheimer's pathology. Pathway analyses for the broader set of dementia-associated proteins implicated immune, lipid, metabolic signaling and hemostasis pathways in dementia pathogenesis.
Keywords: Aged; Alzheimer Disease; Brain; Humans; Proteome; Proteomics

MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia. - Meng, Linyan; Isohanni, Pirjo; Shao, Yunru; Graham, Brett H; Hickey, Scott E; Brooks, Stephanie; Suomalainen, Anu; Joset, Pascal; Steindl, Katharina; Rauch, Anita; Hackenberg, Annette; High, Frances A; et al. (Ann Neurol, 2021)
The Mediator multiprotein complex functions as a regulator of RNA polymerase II-catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease-causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizures and cataracts were noted in severely affected individuals. Identification of multiple patients with biallelic MED27 variants supports the critical role of MED27 in normal human neural development, particularly for the cerebellum. ANN NEUROL 2021;89:828-833.
Keywords: Adolescent; Adult; Amino Acid Sequence; Cataract; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Dystonia; Epilepsy; Exome Sequencing; Genetic Variation; Humans; Infant; Mediator Complex; Nervous System Malformations; Phenotype

missense mutations in Xia-Gibbs syndrome. - Khayat, Michael M; Jianhong Hu; Jiang, Yunyun; Li, He; Chander, Varuna; Dawood, Moez; Hansen, Adam W; Li, Shoudong; Friedman, Jennifer; Cross, Laura; Bijlsma, Emilia K; Ruivenkamp, Claudia A L; et al. (HGG Adv, 2021)
Xia-Gibbs syndrome (XGS; MIM: 615829) is a phenotypically heterogeneous neurodevelopmental disorder (NDD) caused by newly arising mutations in the AT-Hook DNA-Binding Motif-Containing 1 () gene that are predicted to lead to truncated AHDC1 protein synthesis. More than 270 individuals have been diagnosed with XGS worldwide. Despite the absence of an independent assay for AHDC1 protein function to corroborate potential functional consequences of rare variant genetic findings, there are also reports of individuals with XGS-like trait manifestations who have missense mutations and who have been provided a molecular diagnosis of the disorder. To investigate a potential contribution of missense mutations to XGS, we mapped the missense mutations from 10 such individuals to the AHDC1 conserved protein domain structure and detailed the observed phenotypes. Five newly identified individuals were ascertained from a local XGS Registry, and an additional five were taken from external reports or databases, including one publication. Where clinical data were available, individuals with missense mutations all displayed phenotypes consistent with those observed in individuals with truncating mutations, including delayed motor milestones, intellectual disability (ID), hypotonia, and speech delay. A subset of the 10 reported missense mutations cluster in two regions of the AHDC1 protein with known conserved domains, likely representing functional motifs. Variants outside the clustered regions score lower for computational prediction of their likely damaging effects. Overall, missense variants in are likely diagnostic of XGS when analysis of their position relative to conserved regions is considered together with disease trait manifestations.

Molecular Features of Cancers Exhibiting Exceptional Responses to Treatment. - David A Wheeler; Takebe, Naoko; Hinoue, Toshinori; Hoadley, Katherine A; Cardenas, Maria F; Hamilton, Alina M; Laird, Peter W; Wang, Linghua; Johnson, Adrienne; Dewal, Ninad; Miller, Vincent; Piñeyro, David; et al. (Cancer Cell, 2021)
A small fraction of cancer patients with advanced disease survive significantly longer than patients with clinically comparable tumors. Molecular mechanisms for exceptional responses to therapy have been identified by genomic analysis of tumor biopsies from individual patients. Here, we analyzed tumor biopsies from an unbiased cohort of 111 exceptional responder patients using multiple platforms to profile genetic and epigenetic aberrations as well as the tumor microenvironment. Integrative analysis uncovered plausible mechanisms for the therapeutic response in nearly a quarter of the patients. The mechanisms were assigned to four broad categories-DNA damage response, intracellular signaling, immune engagement, and genetic alterations characteristic of favorable prognosis-with many tumors falling into multiple categories. These analyses revealed synthetic lethal relationships that may be exploited therapeutically and rare genetic lesions that favor therapeutic success, while also providing a wealth of testable hypotheses regarding oncogenic mechanisms that may influence the response to cancer therapy.
Keywords: Antineoplastic Agents; Biopsy; Epigenesis, Genetic; Female; Gene Regulatory Networks; Genetic Variation; Genomics; Humans; Male; Neoplasms; Prognosis; Survival Analysis; Treatment Outcome; Tumor Microenvironment

muCNV: Genotyping Structural Variants for Population-level Sequencing. - Jun, Goo; Fritz J Sedlazeck; Zhu, Qihui; English, Adam; Ginger A Metcalf; Kang, Hyun Min; Lee, Charles; Richard A Gibbs; Eric Boerwinkle (Bioinformatics, 2021)
MOTIVATION: There are high demands for joint genotyping of structural variations with short-read sequencing, but efficient and accurate genotyping in population scale is a challenging task. RESULTS: We developed muCNV that aggregates per-sample summary pileups for joint genotyping of > 100,000 samples. Pilot results show very low Mendelian inconsistencies. Applications to large-scale projects in cloud show the computational efficiencies of muCNV genotyping pipeline. AVAILABILITY: muCNV is publicly available for download at: https://github.com/gjun/muCNV. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Neptune: an environment for the delivery of genomic medicine. - Eric Venner; Yi, Victoria; David R Murdock; Sara E Kalla; Wu, Tsung-Jung; Aniko Sabo; Li, Shoudong; Meng, Qingchang; Tian, Xia; Mullai Murugan; Cohen, Michelle; Kovar, Christie; et al. (Genet Med, 2021)
PURPOSE: Genomic medicine holds great promise for improving health care, but integrating searchable and actionable genetic data into electronic health records (EHRs) remains a challenge. Here we describe Neptune, a system for managing the interaction between a clinical laboratory and an EHR system during the clinical reporting process. METHODS: We developed Neptune and applied it to two clinical sequencing projects that required report customization, variant reanalysis, and EHR integration. RESULTS: Neptune has been applied for the generation and delivery of over 15,000 clinical genomic reports. This work spans two clinical tests based on targeted gene panels that contain 68 and 153 genes respectively. These projects demanded customizable clinical reports that contained a variety of genetic data types including single-nucleotide variants (SNVs), copy-number variants (CNVs), pharmacogenomics, and polygenic risk scores. Two variant reanalysis activities were also supported, highlighting this important workflow. CONCLUSION: Methods are needed for delivering structured genetic data to EHRs. This need extends beyond developing data formats to providing infrastructure that manages the reporting process itself. Neptune was successfully applied on two high-throughput clinical sequencing projects to build and deliver clinical reports to EHR systems. The software is open source and available at https://gitlab.com/bcm-hgsc/neptune .
Keywords: Electronic Health Records; Genomics; High-Throughput Nucleotide Sequencing; Humans; Neptune; Software

Neurodevelopmental disorder in an Egyptian family with a biallelic ALKBH8 variant. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Du, Haowei; Rafat, Karima; Fatih, Jawid M; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Richard A Gibbs; Pehlivan, Davut; Hunter, Jill V; Posey, Jennifer E; et al. (Am J Med Genet A, 2021)
Alkylated DNA repair protein AlkB homolog 8 (ALKBH8) is a member of the AlkB family of dioxygenases. ALKBH8 is a methyltransferase of the highly variable wobble nucleoside position in the anticodon loop of tRNA and thus plays a critical role in tRNA modification by preserving codon recognition and preventing errors in amino acid incorporation during translation. Moreover, its activity catalyzes uridine modifications that are proposed to be critical for accurate protein translation. Previously, two distinct homozygous truncating variants in the final exon of ALKBH8 were described in two unrelated large Saudi Arabian kindreds with intellectual developmental disorder and autosomal recessive 71 (MRT71) syndrome (MIM# 618504). Here, we report a third family-of Egyptian descent-harboring a novel homozygous frame-shift variant in the last exon of ALKBH8. Two affected siblings in this family exhibit global developmental delay and intellectual disability as shared characteristic features of MRT71 syndrome, and we further characterize their observed dysmorphic features and brain MRI findings. This description of a third family with a truncating ALKBH8 variant from a distinct population broadens the phenotypic and genotypic spectrum of MRT71 syndrome, affirms that perturbations in tRNA biogenesis can contribute to neurogenetic disease traits, and firmly establishes ALKBH8 as a novel neurodevelopmental disease gene.
Keywords: Adolescent; AlkB Homolog 8, tRNA Methyltransferase; Brain; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Infant; Magnetic Resonance Imaging; Male; Neurodevelopmental Disorders; Pedigree

Novel Anaplastic Thyroid Cancer PDXs and Cell Lines: Expanding Preclinical Models of Genetic Diversity. - Maniakas, Anastasios; Henderson, Ying C; Hei, Hu; Peng, Shaohua; Chen, Yunyun; Jiang, Yujie; Ji, Shuangxi; Cardenas, Maria; Chiu, Yulun; Bell, Diana; Williams, Michelle D; Hofmann, Marie-Claude; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: Anaplastic thyroid cancer (ATC) is a rare, aggressive, and deadly disease. Robust preclinical thyroid cancer models are needed to adequately develop and study novel therapeutic agents. Patient-derived xenograft (PDX) models may resemble patient tumors by recapitulating key genetic alterations and gene expression patterns, making them excellent preclinical models for drug response evaluation. OBJECTIVE: We developed distinct ATC PDX models concurrently with cell lines and characterized them in vitro and in vivo. METHODS: Fresh thyroid tumor from patients with a preoperative diagnosis of ATC was surgically collected and divided for concurrent cell line and PDX model development. Cell lines were created by generating single cells through enzymatic digestion. PDX models were developed following direct subcutaneous implantation of fresh tumor on the flank of immune compromised/athymic mice. RESULTS: Six ATC PDX models and 4 cell lines were developed with distinct genetic profiles. Mutational characterization showed one BRAF/TP53/CDKN2A, one BRAF/CDKN2A, one BRAF/TP53, one TP53 only, one TERT-promoter/HRAS, and one TERT-promoter/KRAS/TP53/NF2/NFE2L2 mutated phenotype. Hematoxylin-eosin staining comparing the PDX models to the original patient surgical specimens show remarkable resemblance, while immunohistochemistry stains for important biomarkers were in full concordance (cytokeratin, TTF-1, PAX8, BRAF). Short tandem repeats DNA fingerprinting analysis of all PDX models and cell lines showed strong concordance with the original tumor. PDX successful establishment rate was 32%. CONCLUSION: We have developed and characterized 6 novel ATC PDX models with 4 matching cell lines. Each PDX model harbors a distinct genetic profile, making them excellent tools for preclinical therapeutic trials.
Keywords: Aged; Animals; Apoptosis; Biomarkers, Tumor; Cell Proliferation; Disease Models, Animal; Female; Gene Expression Regulation, Neoplastic; Humans; Male; Mice; Middle Aged; Phenotype; Prognosis; Survival Rate; Thyroid Carcinoma, Anaplastic; Thyroid Neoplasms; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

A novel homozygous SLC13A5 whole-gene deletion generated by Alu/Alu-mediated rearrangement in an Iraqi family with epileptic encephalopathy. - Duan, Ruizhi; Saadi, Nebal Waill; Grochowski, Christopher M; Bhadila, Ghalia; Faridoun, Afnan; Mitani, Tadahiro; Du, Haowei; Fatih, Jawid M; Jhangiani, Shalini N; Akdemir, Zeynep C; Richard A Gibbs; Pehlivan, Davut; et al. (Am J Med Genet A, 2021)
Biallelic loss-of-function (LoF) of SLC13A5 (solute carrier family 13, member 5) induced deficiency in sodium/citrate transporter (NaCT) causes autosomal recessive developmental epileptic encephalopathy 25 with hypoplastic amelogenesis imperfecta (DEE25; MIM #615905). Many pathogenic SLC13A5 single nucleotide variants (SNVs) and small indels have been described; however, no cases with copy number variants (CNVs) have been sufficiently investigated. We describe a consanguineous Iraqi family harboring an 88.5 kb homozygous deletion including SLC13A5 in Chr17p13.1. The three affected male siblings exhibit neonatal-onset epilepsy with fever-sensitivity, recurrent status epilepticus, global developmental delay/intellectual disability (GDD/ID), and other variable neurological findings as shared phenotypical features of DEE25. Two of the three affected subjects exhibit hypoplastic amelogenesis imperfecta (AI), while the proband shows no evidence of dental abnormalities or AI at 2 years of age with apparently unaffected primary dentition. Characterization of the genomic architecture at this locus revealed evidence for genomic instability generated by an Alu/Alu-mediated rearrangement; confirmed by break-point junction Sanger sequencing. This multiplex family from a distinct population elucidates the phenotypic consequence of complete LoF of SLC13A5 and illustrates the importance of read-depth-based CNV detection in comprehensive exome sequencing analysis to solve cases that otherwise remain molecularly unsolved.
Keywords: Alu Elements; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Epilepsy, Generalized; Exome Sequencing; Female; Homozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Pedigree; Sequence Deletion; Symporters

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lindstrand, Anna; James R Lupski; Sutton, V Reid; et al. (Am J Med Genet A, 2021)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.
Keywords: Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exome Sequencing; Female; Genes, Dominant; Genes, Recessive; Genetic Heterogeneity; Genetic Predisposition to Disease; Genomic Structural Variation; Humans; Limb Deformities, Congenital; Male; Oxidoreductases; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities; Whole Genome Sequencing; Wnt Signaling Pathway

Performance assessment of DNA sequencing platforms in the ABRF Next-Generation Sequencing Study. - Foox, Jonathan; Tighe, Scott W; Nicolet, Charles M; Zook, Justin M; Byrska-Bishop, Marta; Clarke, Wayne E; Khayat, Michael M; Mahmoud, Medhat; Laaguiby, Phoebe K; Herbert, Zachary T; Warner, Derek; Grills, George S; et al. (Nat Biotechnol, 2021)
Assessing the reproducibility, accuracy and utility of massively parallel DNA sequencing platforms remains an ongoing challenge. Here the Association of Biomolecular Resource Facilities (ABRF) Next-Generation Sequencing Study benchmarks the performance of a set of sequencing instruments (HiSeq/NovaSeq/paired-end 2 × 250-bp chemistry, Ion S5/Proton, PacBio circular consensus sequencing (CCS), Oxford Nanopore Technologies PromethION/MinION, BGISEQ-500/MGISEQ-2000 and GS111) on human and bacterial reference DNA samples. Among short-read instruments, HiSeq 4000 and X10 provided the most consistent, highest genome coverage, while BGI/MGISEQ provided the lowest sequencing error rates. The long-read instrument PacBio CCS had the highest reference-based mapping rate and lowest non-mapping rate. The two long-read platforms PacBio CCS and PromethION/MinION showed the best sequence mapping in repeat-rich areas and across homopolymers. NovaSeq 6000 using 2 × 250-bp read chemistry was the most robust instrument for capturing known insertion/deletion events. This study serves as a benchmark for current genomics technologies, as well as a resource to inform experimental design and next-generation sequencing variant calling.
Keywords: Base Pair Mismatch; Benchmarking; DNA; DNA, Bacterial; Genome, Bacterial; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

PhenoDB, GeneMatcher and VariantMatcher, tools for analysis and sharing of sequence data. - Wohler, Elizabeth; Martin, Renan; Griffith, Sean; Rodrigues, Eliete da S; Antonescu, Corina; Posey, Jennifer E; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Doheny, Kimberly F; James R Lupski; Valle, David; Hamosh, Ada; et al. (Orphanet J Rare Dis, 2021)
BACKGROUND: With the advent of whole exome (ES) and genome sequencing (GS) as tools for disease gene discovery, rare variant filtering, prioritization and data sharing have become essential components of the search for disease genes and variants potentially contributing to disease phenotypes. The computational storage, data manipulation, and bioinformatic interpretation of thousands to millions of variants identified in ES and GS, respectively, is a challenging task. To aid in that endeavor, we constructed PhenoDB, GeneMatcher and VariantMatcher. RESULTS: PhenoDB is an accessible, freely available, web-based platform that allows users to store, share, analyze and interpret their patients' phenotypes and variants from ES/GS data. GeneMatcher is accessible to all stakeholders as a web-based tool developed to connect individuals (researchers, clinicians, health care providers and patients) around the globe with interest in the same gene(s), variant(s) or phenotype(s). Finally, VariantMatcher was developed to enable public sharing of variant-level data and phenotypic information from individuals sequenced as part of multiple disease gene discovery projects. Here we provide updates on PhenoDB and GeneMatcher applications and implementation and introduce VariantMatcher. CONCLUSION: Each of these tools has facilitated worldwide data sharing and data analysis and improved our ability to connect genes to phenotypic traits. Further development of these platforms will expand variant analysis, interpretation, novel disease-gene discovery and facilitate functional annotation of the human genome for clinical genomics implementation and the precision medicine initiative.
Keywords: Computational Biology; Databases, Genetic; Genomics; Humans; Phenotype; Software

Phenotypic and protein localization heterogeneity associated with AHDC1 pathogenic protein-truncating alleles in Xia-Gibbs syndrome. - Khayat, Michael M; Li, He; Chander, Varuna; Jianhong Hu; Hansen, Adam W; Li, Shoudong; Traynelis, Josh; Shen, Hua; Weissenberger, George; Stossi, Fabio; Johnson, Hannah L; James R Lupski; et al. (Hum Mutat, 2021)
Xia-Gibbs syndrome (XGS) is a rare Mendelian disease typically caused by de novo stop-gain or frameshift mutations in the AT-hook DNA binding motif containing 1 (AHDC1) gene. Patients usually present in early infancy with hypotonia and developmental delay and later exhibit intellectual disability (ID). The overall presentation is variable, however, and the emerging clinical picture is still evolving. A detailed phenotypic analysis of 34 XGS individuals revealed five core phenotypes (delayed motor milestones, speech delay, low muscle tone, ID, and hypotonia) in more than 80% of individuals and an additional 12 features that occurred more variably. Seizures and scoliosis were more frequently associated with truncations that arise before the midpoint of the protein although the occurrence of most features could not be predicted by the mutation position. Transient expression of wild type and different patient truncated AHDC1 protein forms in human cell lines revealed abnormal patterns of nuclear localization including a diffuse distribution of a short truncated form and nucleolar aggregation in mid-protein truncated forms. Overall, both the occurrence of variable phenotypes and the different distribution of the expressed protein reflect the heterogeneity of this syndrome.
Keywords: Abnormalities, Multiple; Alleles; DNA-Binding Proteins; Humans; Intellectual Disability; Mutation; Phenotype; Syndrome

Publisher Correction: Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals. - Surendran, Praveen; Feofanova, Elena V; Lahrouchi, Najim; Ntalla, Ioanna; Karthikeyan, Savita; Cook, James; Chen, Lingyan; Mifsud, Borbala; Yao, Chen; Kraja, Aldi T; Cartwright, James H; Hellwege, Jacklyn N; et al. (Nat Genet, 2021)

Risk of sudden cardiac death in EXOSC5-related disease. - Calame, Daniel G; Herman, Isabella; Fatih, Jawid M; Du, Haowei; Akay, Gulsen; Jhangiani, Shalini N; Coban-Akdemir, Zeynep; Milewicz, Dianna M; Richard A Gibbs; Posey, Jennifer E; Marafi, Dana; Hunter, Jill V; et al. (Am J Med Genet A, 2021)
The RNA exosome is a multi-subunit complex involved in the processing, degradation, and regulated turnover of RNA. Several subunits are linked to Mendelian disorders, including pontocerebellar hypoplasia (EXOSC3, MIM #614678; EXOSC8, MIM #616081: and EXOSC9, MIM #618065) and short stature, hearing loss, retinitis pigmentosa, and distinctive facies (EXOSC2, MIM #617763). More recently, EXOSC5 (MIM *606492) was found to underlie an autosomal recessive neurodevelopmental disorder characterized by developmental delay, hypotonia, cerebellar abnormalities, and dysmorphic facies. An unusual feature of EXOSC5-related disease is the occurrence of complete heart block requiring a pacemaker in a subset of affected individuals. Here, we provide a detailed clinical and molecular characterization of two siblings with microcephaly, developmental delay, cerebellar volume loss, hypomyelination, with cardiac conduction and rhythm abnormalities including sinus node dysfunction, intraventricular conduction delay, atrioventricular block, and ventricular tachycardia (VT) due to compound heterozygous variants in EXOSC5: (1) NM_020158.4:c.341C > T (p.Thr114Ile; pathogenic, previously reported) and (2) NM_020158.4:c.302C > A (p.Thr101Lys; novel variant). A review of the literature revealed an additional family with biallelic EXOSC5 variants and cardiac conduction abnormalities. These clinical and molecular data provide compelling evidence that cardiac conduction abnormalities and arrhythmias are part of the EXOSC5-related disease spectrum and argue for proactive screening due to potential risk of sudden cardiac death.
Keywords: Antigens, Neoplasm; Atrioventricular Block; Child; Death, Sudden, Cardiac; Echocardiography; Electrocardiography; Exosome Multienzyme Ribonuclease Complex; Facies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mutation; Pedigree; Phenotype; RNA-Binding Proteins; Sequence Analysis, DNA; Young Adult

SARS-CoV-2 genomic diversity and the implications for qRT-PCR diagnostics and transmission. - Sapoval, Nicolae; Mahmoud, Medhat; Jochum, Michael D; Liu, Yunxi; Elworth, R A Leo; Wang, Qi; Albin, Dreycey; Ogilvie, Huw A; Lee, Michael D; Villapol, Sonia; Hernandez, Kyle M; Maljkovic Berry, Irina; et al. (Genome Res, 2021)
The COVID-19 pandemic has sparked an urgent need to uncover the underlying biology of this devastating disease. Though RNA viruses mutate more rapidly than DNA viruses, there are a relatively small number of single nucleotide polymorphisms (SNPs) that differentiate the main SARS-CoV-2 lineages that have spread throughout the world. In this study, we investigated 129 RNA-seq data sets and 6928 consensus genomes to contrast the intra-host and inter-host diversity of SARS-CoV-2. Our analyses yielded three major observations. First, the mutational profile of SARS-CoV-2 highlights intra-host single nucleotide variant (iSNV) and SNP similarity, albeit with differences in C > U changes. Second, iSNV and SNP patterns in SARS-CoV-2 are more similar to MERS-CoV than SARS-CoV-1. Third, a significant fraction of insertions and deletions contribute to the genetic diversity of SARS-CoV-2. Altogether, our findings provide insight into SARS-CoV-2 genomic diversity, inform the design of detection tests, and highlight the potential of iSNVs for tracking the transmission of SARS-CoV-2.
Keywords: COVID-19; Genetic Variation; Genome, Viral; Host-Pathogen Interactions; Humans; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction; SARS-CoV-2

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.
Keywords: Cytochrome P-450 CYP2D6; Genetic Variation; Genome, Human; Genomics; Haplotypes; Heterozygote; Humans; INDEL Mutation; Loss of Function Mutation; Mutagenesis; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Population Density; Precision Medicine; Quality Control; Sample Size; United States; Whole Genome Sequencing

Technical note: multi-alleles at the DYS385ab locus with high frequency in a Han Chinese population from southwestern China. - Fu, Jiewen; Fu, Shangyi; Yin, Shiqiang; Cheng, Jingliang; Liu, Xiaoyan; Jin, Zeming; He, Tao; Fu, Junjiang (Int J Legal Med, 2021)
Y-chromosome short tandem repeat (Y-STR) markers have been widely used in forensic applications and usually show monoallelic or diallelic genotypic patterns at certain double-copied loci. In this study, we have found 13 samples among 703 males with multi-alleles at the DYS385ab locus, including one with five mutant alleles, nine with four, and three with three. The frequency of abnormal DYS385ab genotypes was 1.85% (13/703), which is very high in the Han Chinese population. The percentage of samples with diallelic patterns at DYS385ab was higher than that of monoallelic patterns (80.23% vs. 17.92%). Additionally, the percentage of samples with tetra-allelic patterns at DYS385ab was higher than that of tri-allelic patterns (1.28% vs. 0.43%), suggesting that there are possibly two copies with duplicated events happening frequently on the Y chromosome. Interestingly, the peak height of allele 13 was two to three-folds higher than that of other alleles. The allele 18 peak height was also two-fold higher than others, which could potentially be explained by a duplication event mechanism. We also found that tri-allelic genotypes for alleles 13, 17, and 20, tetra-allelic genotypes for alleles 13, 14, 19, and 20, and tetra-allelic genotypes for alleles 12, 13, 19 and 21 were more common than others. Furthermore, all 13 samples had multi-alleles containing allele 13, implying a founder effect in this particular Chinese-specific ethnic group. Taken together, this study provides new information for this population and will be useful for paternal lineage identification, kinship analysis, and family relationship reconstruction using Y-STR forensic DNA analysis methods.
Keywords: Alleles; Asian People; China; Chromosomes, Human, Y; Gene Frequency; Genetic Loci; Genotype; Humans; Male; Microsatellite Repeats

The trans-ancestral genomic architecture of glycemic traits. - Chen, Ji; Spracklen, Cassandra N; Marenne, Gaëlle; Varshney, Arushi; Corbin, Laura J; Luan, Jian'an; Willems, Sara M; Wu, Ying; Zhang, Xiaoshuai; Horikoshi, Momoko; Boutin, Thibaud S; Mägi, Reedik; et al. (Nat Genet, 2021)
Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.
Keywords: Alleles; Blood Glucose; Epigenesis, Genetic; Gene Expression Profiling; Genome, Human; Genome-Wide Association Study; Glycated Hemoglobin; Humans; Multifactorial Inheritance; Physical Chromosome Mapping; Quantitative Trait Loci; Quantitative Trait, Heritable; White People

Two novel bi-allelic KDELR2 missense variants cause osteogenesis imperfecta with neurodevelopmental features. - Efthymiou, Stephanie; Herman, Isabella; Rahman, Fatima; Anwar, Najwa; Maroofian, Reza; Yip, Janice; Mitani, Tadahiro; Calame, Daniel G; Hunter, Jill V; Sutton, V Reid; Yilmaz Gulec, Elif; Duan, Ruizhi; et al. (Am J Med Genet A, 2021)
Keywords: Alleles; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; Osteogenesis Imperfecta; Vesicular Transport Proteins

Variation in predicted COVID-19 risk among lemurs and lorises. - Melin, Amanda D; Orkin, Joseph D; Janiak, Mareike C; Valenzuela, Alejandro; Kuderna, Lukas; Marrone, Frank; Ramangason, Hasinala; Horvath, Julie E; Roos, Christian; Kitchener, Andrew C; Khor, Chiea Chuen; Lim, Weng Khong; et al. (Am J Primatol, 2021)
The novel coronavirus SARS-CoV-2, which in humans leads to the disease COVID-19, has caused global disruption and more than 2 million fatalities since it first emerged in late 2019. As we write, infection rates are at their highest point globally and are rising extremely rapidly in some areas due to more infectious variants. The primary target of SARS-CoV-2 is the cellular receptor angiotensin-converting enzyme-2 (ACE2). Recent sequence analyses of the ACE2 gene predict that many nonhuman primates are also likely to be highly susceptible to infection. However, the anticipated risk is not equal across the Order. Furthermore, some taxonomic groups show high ACE2 amino acid conservation, while others exhibit high variability at this locus. As an example of the latter, analyses of strepsirrhine primate ACE2 sequences to date indicate large variation among lemurs and lorises compared to other primate clades despite low sampling effort. Here, we report ACE2 gene and protein sequences for 71 individual strepsirrhines, spanning 51 species and 19 genera. Our study reinforces previous results while finding additional variability in other strepsirrhine species, and suggests several clades of lemurs have high potential susceptibility to SARS-CoV-2 infection. Troublingly, some species, including the rare and endangered aye-aye (Daubentonia madagascariensis), as well as those in the genera Avahi and Propithecus, may be at high risk. Given that lemurs are endemic to Madagascar and among the primates at highest risk of extinction globally, further understanding of the potential threat of COVID-19 to their health should be a conservation priority. All feasible actions should be taken to limit their exposure to SARS-CoV-2.
Keywords: Angiotensin-Converting Enzyme 2; Animals; COVID-19; Lemur; Lorisidae; Primate Diseases; Risk Factors

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.
Keywords: Alleles; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Glomerular Filtration Rate; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Precision Medicine; Public Health Surveillance; Quantitative Trait, Heritable; United States; Whole Genome Sequencing

Allelic Heterogeneity at the CRP Locus Identified by Whole-Genome Sequencing in Multi-ancestry Cohorts. - Raffield, Laura M; Iyengar, Apoorva K; Wang, Biqi; Gaynor, Sheila M; Spracklen, Cassandra N; Zhong, Xue; Kowalski, Madeline H; Salimi, Shabnam; Polfus, Linda M; Benjamin, Emelia J; Bis, Joshua C; Bowler, Russell; et al. (Am J Hum Genet, 2020)
Whole-genome sequencing (WGS) can improve assessment of low-frequency and rare variants, particularly in non-European populations that have been underrepresented in existing genomic studies. The genetic determinants of C-reactive protein (CRP), a biomarker of chronic inflammation, have been extensively studied, with existing genome-wide association studies (GWASs) conducted in >200,000 individuals of European ancestry. In order to discover novel loci associated with CRP levels, we examined a multi-ancestry population (n = 23,279) with WGS (∼38× coverage) from the Trans-Omics for Precision Medicine (TOPMed) program. We found evidence for eight distinct associations at the CRP locus, including two variants that have not been identified previously (rs11265259 and rs181704186), both of which are non-coding and more common in individuals of African ancestry (∼10% and ∼1% minor allele frequency, respectively, and rare or monomorphic in 1000 Genomes populations of East Asian, South Asian, and European ancestry). We show that the minor (G) allele of rs181704186 is associated with lower CRP levels and decreased transcriptional activity and protein binding in vitro, providing a plausible molecular mechanism for this African ancestry-specific signal. The individuals homozygous for rs181704186-G have a mean CRP level of 0.23 mg/L, in contrast to individuals heterozygous for rs181704186 with mean CRP of 2.97 mg/L and major allele homozygotes with mean CRP of 4.11 mg/L. This study demonstrates the utility of WGS in multi-ethnic populations to drive discovery of complex trait associations of large effect and to identify functional alleles in noncoding regulatory regions.
Keywords: Asian People; Black People; C-Reactive Protein; Cohort Studies; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; White People; Whole Genome Sequencing

Analyses of non-coding somatic drivers in 2,658 cancer whole genomes. - Rheinbay, Esther; Nielsen, Morten Muhlig; Abascal, Federico; Wala, Jeremiah A; Shapira, Ofer; Tiao, Grace; Hornshøj, Henrik; Hess, Julian M; Juul, Randi Istrup; Lin, Ziao; Feuerbach, Lars; Sabarinathan, Radhakrishnan; et al. (Nature, 2020)
The discovery of drivers of cancer has traditionally focused on protein-coding genes. Here we present analyses of driver point mutations and structural variants in non-coding regions across 2,658 genomes from the Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium of the International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA). For point mutations, we developed a statistically rigorous strategy for combining significance levels from multiple methods of driver discovery that overcomes the limitations of individual methods. For structural variants, we present two methods of driver discovery, and identify regions that are significantly affected by recurrent breakpoints and recurrent somatic juxtapositions. Our analyses confirm previously reported drivers, raise doubts about others and identify novel candidates, including point mutations in the 5' region of TP53, in the 3' untranslated regions of NFKBIZ and TOB1, focal deletions in BRD4 and rearrangements in the loci of AKR1C genes. We show that although point mutations and structural variants that drive cancer are less frequent in non-coding genes and regulatory sequences than in protein-coding genes, additional examples of these drivers will be found as more cancer genomes become available.
Keywords: Databases, Genetic; DNA Breaks; Gene Expression Regulation, Neoplastic; Genome, Human; Genome-Wide Association Study; Humans; INDEL Mutation; Mutation; Neoplasms

Author Correction: A robust benchmark for detection of germline large deletions and insertions. - Zook, Justin M; Hansen, Nancy F; Olson, Nathan D; Chapman, Lesley; Mullikin, James C; Xiao, Chunlin; Sherry, Stephen; Koren, Sergey; Phillippy, Adam M; Boutros, Paul C; Sahraeian, Sayed Mohammad E; Huang, Vincent; et al. (Nat Biotechnol, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Author Correction: NEMF mutations that impair ribosome-associated quality control are associated with neuromuscular disease. - Martin, Paige B; Kigoshi-Tansho, Yu; Sher, Roger B; Ravenscroft, Gianina; Stauffer, Jennifer E; Kumar, Rajesh; Yonashiro, Ryo; Müller, Tina; Griffith, Christopher; Allen, William; Pehlivan, Davut; Harel, Tamar; et al. (Nat Commun, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Exome Sequencing; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate

Biallelic in-frame deletion in TRAPPC4 in a family with developmental delay and cerebellar atrophy. - Saad, Ahmed K; Marafi, Dana; Mitani, Tadahiro; Jolly, Angad; Du, Haowei; Elbendary, Hasnaa M; Jhangiani, Shalini N; Akdemir, Zeynep C; Richard A Gibbs; Hunter, Jill V; Carvalho, Claudia M B C; Pehlivan, Davut; et al. (Brain, 2020)
Keywords: Atrophy; Cerebellar Diseases; Humans; Intellectual Disability; Sequence Deletion

Brown marmorated stink bug, Halyomorpha halys (Stål), genome: putative underpinnings of polyphagy, insecticide resistance potential and biology of a top worldwide pest. - Sparks, Michael E; Bansal, Raman; Benoit, Joshua B; Blackburn, Michael B; Chao, Hsu; Chen, Mengyao; Cheng, Sammy; Childers, Christopher; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Elpidina, Elena N; et al. (BMC Genomics, 2020)
BACKGROUND: Halyomorpha halys (Stål), the brown marmorated stink bug, is a highly invasive insect species due in part to its exceptionally high levels of polyphagy. This species is also a nuisance due to overwintering in human-made structures. It has caused significant agricultural losses in recent years along the Atlantic seaboard of North America and in continental Europe. Genomic resources will assist with determining the molecular basis for this species' feeding and habitat traits, defining potential targets for pest management strategies. RESULTS: Analysis of the 1.15-Gb draft genome assembly has identified a wide variety of genetic elements underpinning the biological characteristics of this formidable pest species, encompassing the roles of sensory functions, digestion, immunity, detoxification and development, all of which likely support H. halys' capacity for invasiveness. Many of the genes identified herein have potential for biomolecular pesticide applications. CONCLUSIONS: Availability of the H. halys genome sequence will be useful for the development of environmentally friendly biomolecular pesticides to be applied in concert with more traditional, synthetic chemical-based controls.
Keywords: Animals; Ecosystem; Gene Transfer, Horizontal; Genome Size; Heteroptera; Insect Proteins; Insecticide Resistance; Introduced Species; Phylogeny; Whole Genome Sequencing

A CLN6-CLN8 complex recruits lysosomal enzymes at the ER for Golgi transfer. - Bajaj, Lakshya; Sharma, Jaiprakash; di Ronza, Alberto; Zhang, Pengcheng; Eblimit, Aiden; Pal, Rituraj; Roman, Dany; Collette, John R; Booth, Clarissa; Chang, Kevin T; Sifers, Richard N; Jung, Sung Y; et al. (J Clin Invest, 2020)
Lysosomal enzymes are synthesized in the endoplasmic reticulum (ER) and transferred to the Golgi complex by interaction with the Batten disease protein CLN8 (ceroid lipofuscinosis, neuronal, 8). Here we investigated the relationship of this pathway with CLN6, an ER-associated protein of unknown function that is defective in a different Batten disease subtype. Experiments focused on protein interaction and trafficking identified CLN6 as an obligate component of a CLN6-CLN8 complex (herein referred to as EGRESS: ER-to-Golgi relaying of enzymes of the lysosomal system), which recruits lysosomal enzymes at the ER to promote their Golgi transfer. Mutagenesis experiments showed that the second luminal loop of CLN6 is required for the interaction of CLN6 with the enzymes but dispensable for interaction with CLN8. In vitro and in vivo studies showed that CLN6 deficiency results in inefficient ER export of lysosomal enzymes and diminished levels of the enzymes at the lysosome. Mice lacking both CLN6 and CLN8 did not display aggravated pathology compared with the single deficiencies, indicating that the EGRESS complex works as a functional unit. These results identify CLN6 and the EGRESS complex as key players in lysosome biogenesis and shed light on the molecular etiology of Batten disease caused by defects in CLN6.
Keywords: Animals; Endoplasmic Reticulum; Golgi Apparatus; Lysosomes; Membrane Proteins; Mice; Mice, Knockout; Multiprotein Complexes; Neuronal Ceroid-Lipofuscinoses; Protein Transport

Cohort Profile: The Right Drug, Right Dose, Right Time: Using Genomic Data to Individualize Treatment Protocol (RIGHT Protocol). - Bielinski, Suzette J; St Sauver, Jennifer L; Olson, Janet E; Larson, Nicholas B; Black, John L; Steven E Scherer; Bernard, Matthew E; Eric Boerwinkle; Borah, Bijan J; Caraballo, Pedro J; Curry, Timothy B; Harshavardhan Doddapaneni; et al. (Int J Epidemiol, 2020)
Keywords: Clinical Protocols; Cohort Studies; Female; Genomics; Humans; Male; Pharmacogenetics; Precision Medicine

Complex mosaic structural variations in human fetal brains. - Sekar, Shobana; Tomasini, Livia; Proukakis, Christos; Bae, Taejeong; Manlove, Logan; Jang, Yeongjun; Scuderi, Soraya; Zhou, Bo; Kalyva, Maria; Amiri, Anahita; Mariani, Jessica; Fritz J Sedlazeck; et al. (Genome Res, 2020)
Somatic mosaicism, manifesting as single nucleotide variants (SNVs), mobile element insertions, and structural changes in the DNA, is a common phenomenon in human brain cells, with potential functional consequences. Using a clonal approach, we previously detected 200-400 mosaic SNVs per cell in three human fetal brains (15-21 wk postconception). However, structural variation in the human fetal brain has not yet been investigated. Here, we discover and validate four mosaic structural variants (SVs) in the same brains and resolve their precise breakpoints. The SVs were of kilobase scale and complex, consisting of deletion(s) and rearranged genomic fragments, which sometimes originated from different chromosomes. Sequences at the breakpoints of these rearrangements had microhomologies, suggesting their origin from replication errors. One SV was found in two clones, and we timed its origin to ∼14 wk postconception. No large scale mosaic copy number variants (CNVs) were detectable in normal fetal human brains, suggesting that previously reported megabase-scale CNVs in neurons arise at later stages of development. By reanalysis of public single nuclei data from adult brain neurons, we detected an extrachromosomal circular DNA event. Our study reveals the existence of mosaic SVs in the developing human brain, likely arising from cell proliferation during mid-neurogenesis. Although relatively rare compared to SNVs and present in ∼10% of neurons, SVs in developing human brain affect a comparable number of bases in the genome (∼6200 vs. ∼4000 bp), implying that they may have similar functional consequences.
Keywords: Brain; Clonal Evolution; DNA, Circular; Female; Genomic Structural Variation; Genotyping Techniques; Gestational Age; Humans; Mosaicism; Neurogenesis; Pregnancy; Sequence Analysis, DNA

Congenital diaphragmatic hernia as a prominent feature of a SPECC1L-related syndrome. - Wild, K Taylor; Gordon, Tia; Bhoj, Elizabeth J; Du, Haowei; Jhangiani, Shalini N; Posey, Jennifer E; James R Lupski; Scott, Daryl A; Zackai, Elaine H (Am J Med Genet A, 2020)
Congenital diaphragmatic hernias (CDH) confer substantial morbidity and mortality. Genetic defects, including chromosomal anomalies, copy number variants, and sequence variants are identified in ~30% of patients with CDH. A genetic etiology is not yet found in 70% of patients, however there is a growing number of genetic syndromes and single gene disorders associated with CDH. While there have been two reported individuals with X-linked Opitz G/BBB syndrome with MID1 mutations who have CDH as an associated feature, CDH appears to be a much more prominent feature of a SPECC1L-related autosomal dominant Opitz G/BBB syndrome. Features unique to autosomal dominant Opitz G/BBB syndrome include branchial fistulae, omphalocele, and a bicornuate uterus. Here we present one new individual and five previously reported individuals with CDH found to have SPECC1L mutations. These cases provide strong evidence that SPECC1L is a bona fide CDH gene. We conclude that a SPECC1L-related Opitz G/BBB syndrome should be considered in any patient with CDH who has additional features of hypertelorism, a prominent forehead, a broad nasal bridge, anteverted nares, cleft lip/palate, branchial fistulae, omphalocele, and/or bicornuate uterus.
Keywords: Abnormalities, Multiple; Child, Preschool; Female; Gestational Age; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Phosphoproteins; Syndrome

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; R. Alan Harris; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Jeffrey Rogers; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Correction to: Genome-enabled insights into the biology of thrips as crop pests. - Rotenberg, Dorith; Baumann, Aaron A; Ben-Mahmoud, Sulley; Christiaens, Olivier; Dermauw, Wannes; Ioannidis, Panagiotis; Jacobs, Chris G C; Vargas Jentzsch, Iris M; Oliver, Jonathan E; Poelchau, Monica F; Rajarapu, Swapna Priya; Schneweis, Derek J; et al. (BMC Biol, 2020)
An amendment to this paper has been published and can be accessed via the original article.

Correction: Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
A correction to this paper has been published and can be accessed via a link at the top of the paper.

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.
Keywords: Cerebellar Ataxia; DNA Copy Number Variations; Exome; Exome Sequencing; Genetic Association Studies; Genetic Linkage; Genetic Predisposition to Disease; Humans; Microsatellite Repeats; Nervous System Diseases

Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals. - Surendran, Praveen; Feofanova, Elena V; Lahrouchi, Najim; Ntalla, Ioanna; Karthikeyan, Savita; Cook, James; Chen, Lingyan; Mifsud, Borbala; Yao, Chen; Kraja, Aldi T; Cartwright, James H; Hellwege, Jacklyn N; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to ~1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency ≤ 0.01) variant BP associations (P < 5 × 10), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were ~8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.
Keywords: Blood Pressure; GATA5 Transcription Factor; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Hypertension; Mutation; Phospholipase C beta; Polymorphism, Single Nucleotide

Disease-associated CTNNBL1 mutation impairs somatic hypermutation by decreasing nuclear AID. - Kuhny, Marcel; Forbes, Lisa R; Çakan, Elif; Vega-Loza, Andrea; Kostiuk, Valentyna; Dinesh, Ravi K; Glauzy, Salomé; Stray-Pedersen, Asbjorg; Pezzi, Ashley E; Hanson, I Celine; Vargas-Hernandez, Alexander; Xu, Mina LuQuing; et al. (J Clin Invest, 2020)
Patients with common variable immunodeficiency associated with autoimmune cytopenia (CVID+AIC) generate few isotype-switched B cells with severely decreased frequencies of somatic hypermutations (SHMs), but their underlying molecular defects remain poorly characterized. We identified a CVID+AIC patient who displays a rare homozygous missense M466V mutation in β-catenin-like protein 1 (CTNNBL1). Because CTNNBL1 binds activation-induced cytidine deaminase (AID) that catalyzes SHM, we tested AID interactions with the CTNNBL1 M466V variant. We found that the M466V mutation interfered with the association of CTNNBL1 with AID, resulting in decreased AID in the nuclei of patient EBV-transformed B cell lines and of CTNNBL1 466V/V Ramos B cells engineered to express only CTNNBL1 M466V using CRISPR/Cas9 technology. As a consequence, the scarce IgG+ memory B cells from the CTNNBL1 466V/V patient showed a low SHM frequency that averaged 6.7 mutations compared with about 18 mutations per clone in healthy-donor counterparts. In addition, CTNNBL1 466V/V Ramos B cells displayed a decreased incidence of SHM that was reduced by half compared with parental WT Ramos B cells, demonstrating that the CTNNBL1 M466V mutation is responsible for defective SHM induction. We conclude that CTNNBL1 plays an important role in regulating AID-dependent antibody diversification in humans.
Keywords: Amino Acid Substitution; Apoptosis Regulatory Proteins; B-Lymphocytes; Cell Line; Child, Preschool; Common Variable Immunodeficiency; Cytidine Deaminase; Female; Homozygote; Humans; Immunologic Memory; Mutation, Missense; Nuclear Proteins; Somatic Hypermutation, Immunoglobulin

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gozde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Bo Yuan; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Gene content evolution in the arthropods. - Thomas, Gregg W C; Dohmen, Elias; Hughes, Daniel S T; Murali, Shwetha C; Poelchau, Monica; Glastad, Karl; Anstead, Clare A; Ayoub, Nadia A; Batterham, Phillip; Bellair, Michelle; Binford, Greta J; Chao, Hsu; et al. (Genome Biol, 2020)
BACKGROUND: Arthropods comprise the largest and most diverse phylum on Earth and play vital roles in nearly every ecosystem. Their diversity stems in part from variations on a conserved body plan, resulting from and recorded in adaptive changes in the genome. Dissection of the genomic record of sequence change enables broad questions regarding genome evolution to be addressed, even across hyper-diverse taxa within arthropods. RESULTS: Using 76 whole genome sequences representing 21 orders spanning more than 500 million years of arthropod evolution, we document changes in gene and protein domain content and provide temporal and phylogenetic context for interpreting these innovations. We identify many novel gene families that arose early in the evolution of arthropods and during the diversification of insects into modern orders. We reveal unexpected variation in patterns of DNA methylation across arthropods and examples of gene family and protein domain evolution coincident with the appearance of notable phenotypic and physiological adaptations such as flight, metamorphosis, sociality, and chemoperception. CONCLUSIONS: These analyses demonstrate how large-scale comparative genomics can provide broad new insights into the genotype to phenotype map and generate testable hypotheses about the evolution of animal diversity.
Keywords: Animals; Arthropods; DNA Methylation; Evolution, Molecular; Genetic Speciation; Genetic Variation; Phylogeny

Genetic Burden Contributing to Extremely Low or High Bone Mineral Density in a Senior Male Population From the Osteoporotic Fractures in Men Study (MrOS). - Chen, Shan; Jain, Mahim; Jhangiani, Shalini; Akdemir, Zeynep C; Campeau, Philippe M; Klein, Robert F; Nielson, Carrie; Dai, Hongzheng; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Orwoll, Eric S; et al. (JBMR Plus, 2020)
Worldwide, one in five men aged over 50 years will experience osteoporosis or a clinical bone fracture, with a greater fracture-related mortality rate than women. However, the genetic etiology of osteoporosis in men is still poorly understood. We aimed to identify the genetic variants and candidate genes associated with extremely low or high BMD for a better understanding of the biology underlying low bone density that may point to potential therapeutic targets for increasing bone mass. Subjects from the Osteoporotic Fractures in Men Study (MrOS) cohort were evaluated by age and BMI-adjusted total hip BMD. Those with BMD values 3 SDs away from the mean were selected and the remaining individuals whose adjusted BMD ranked at the highest or lowest 100 were included. Men with the lowest adjusted BMD ( = 98) and highest adjusted BMD ( = 110) were chosen for exome sequencing. Controls ( = 82) were men of Northern and Western European descent from the US Utah population of the 1000 Genomes Project. Fisher's exact test was performed to compare low- or high-BMD subjects with controls for single-gene associations. Additionally, sets of candidate genes causative of heritable disorders of connective tissue, including osteogenesis imperfecta (OI) and Ehlers-Danlos syndrome (EDS), were grouped for multigene and mutation burden analyses. No single-gene associations with rare variants were found for either the low BMD group (33 genes) or high BMD group (18 genes). In the group of OI genes, we detected a significant threefold increased accumulation of rare variants in low-BMD subjects compared with controls ( = 0.009). Additionally, genes associated with EDS had a twofold increased frequency in low-BMD subjects compared with controls ( = 0.03). These findings reveal a rare variant burden in OI and EDS disease genes at low BMD, which suggests a potential gene-panel approach to screen for multivariant associations in larger cohorts. © 2019 The Authors. published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

Genome sequencing analysis of a family with a child displaying severe abdominal distention and recurrent hypoglycemia. - Liu, Jidong; Ding, Guolian; Zou, Kexin; Jiang, Ziru; Zhang, Junyu; Lu, Yunhua; Pignata, Antonella; Eric Venner; Liu, Pengfei; Liu, Zhandong; Wangler, Michael F; Sun, Zheng (Mol Genet Genomic Med, 2020)
BACKGROUND: Germline mutations in PTEN are associated with the PTEN hamartoma tumor syndrome (PHTS), an umbrella term used to describe a spectrum of autosomal-dominant disorders characterized by variable phenotypic manifestations associated with cell or tissue overgrowth. We report a boy who developed severe progressive abdominal distention due to a dramatic adipose mass from the age of 7 months and developed recurrent hypoinsulinemic hypoglycemia that led to seizures at the age of 4 years. METHODS: Trio-based whole-genome sequencing was performed by using blood DNA from the child and his parents. The possible pathogenic variants were verified by Sanger sequencing. Functional characterization of the identified variant was completed by western blot. RESULTS: The child inherited a single-nucleotide deletion NM_000314.6:c.849delA (p.Glu284Argfs) in the tumor suppressor gene PTEN from his father. The paternal family members have a history of cancer. It is conceivable that PTEN loss-of-function induced the adipose tumor growth and hypoglycemia, although the proband did not meet the usual diagnosis criteria of Cowden syndrome or Bannayan-Riley-Ruvalcaba syndrome that are characterized by germline mutations of PTEN. CONCLUSION: This case underlines the variability of phenotypes associated with PTEN germline mutations and provides useful information for diagnosis and genetic counseling of PTEN-related diseases for pediatric patients.
Keywords: Abdominal Neoplasms; Child, Preschool; Humans; Hypoglycemia; Loss of Function Mutation; Male; Neoplasms, Adipose Tissue; Pedigree; Phenotype; PTEN Phosphohydrolase; Seizures; Syndrome

Genome-enabled insights into the biology of thrips as crop pests. - Rotenberg, Dorith; Baumann, Aaron A; Ben-Mahmoud, Sulley; Christiaens, Olivier; Dermauw, Wannes; Ioannidis, Panagiotis; Jacobs, Chris G C; Vargas Jentzsch, Iris M; Oliver, Jonathan E; Poelchau, Monica F; Rajarapu, Swapna Priya; Schneweis, Derek J; et al. (BMC Biol, 2020)
BACKGROUND: The western flower thrips, Frankliniella occidentalis (Pergande), is a globally invasive pest and plant virus vector on a wide array of food, fiber, and ornamental crops. The underlying genetic mechanisms of the processes governing thrips pest and vector biology, feeding behaviors, ecology, and insecticide resistance are largely unknown. To address this gap, we present the F. occidentalis draft genome assembly and official gene set. RESULTS: We report on the first genome sequence for any member of the insect order Thysanoptera. Benchmarking Universal Single-Copy Ortholog (BUSCO) assessments of the genome assembly (size = 415.8 Mb, scaffold N50 = 948.9 kb) revealed a relatively complete and well-annotated assembly in comparison to other insect genomes. The genome is unusually GC-rich (50%) compared to other insect genomes to date. The official gene set (OGS v1.0) contains 16,859 genes, of which ~ 10% were manually verified and corrected by our consortium. We focused on manual annotation, phylogenetic, and expression evidence analyses for gene sets centered on primary themes in the life histories and activities of plant-colonizing insects. Highlights include the following: (1) divergent clades and large expansions in genes associated with environmental sensing (chemosensory receptors) and detoxification (CYP4, CYP6, and CCE enzymes) of substances encountered in agricultural environments; (2) a comprehensive set of salivary gland genes supported by enriched expression; (3) apparent absence of members of the IMD innate immune defense pathway; and (4) developmental- and sex-specific expression analyses of genes associated with progression from larvae to adulthood through neometaboly, a distinct form of maturation differing from either incomplete or complete metamorphosis in the Insecta. CONCLUSIONS: Analysis of the F. occidentalis genome offers insights into the polyphagous behavior of this insect pest that finds, colonizes, and survives on a widely diverse array of plants. The genomic resources presented here enable a more complete analysis of insect evolution and biology, providing a missing taxon for contemporary insect genomics-based analyses. Our study also offers a genomic benchmark for molecular and evolutionary investigations of other Thysanoptera species.
Keywords: Animals; Crops, Agricultural; Feeding Behavior; Food Chain; Genome, Insect; Immunity, Innate; Life History Traits; Perception; Phylogeny; Reproduction; Thysanoptera; Transcriptome

HEM1 deficiency disrupts mTORC2 and F-actin control in inherited immunodysregulatory disease. - Cook, Sarah A; Comrie, William A; Poli, M Cecilia; Similuk, Morgan; Oler, Andrew J; Faruqi, Aiman J; Kuhns, Douglas B; Yang, Sheng; Vargas-Hernandez, Alexander; Carisey, Alexandre F; Fournier, Benjamin; Anderson, D Eric; et al. (Science, 2020)
Immunodeficiency often coincides with hyperactive immune disorders such as autoimmunity, lymphoproliferation, or atopy, but this coincidence is rarely understood on a molecular level. We describe five patients from four families with immunodeficiency coupled with atopy, lymphoproliferation, and cytokine overproduction harboring mutations in , which encodes the hematopoietic-specific HEM1 protein. These mutations cause the loss of the HEM1 protein and the WAVE regulatory complex (WRC) or disrupt binding to the WRC regulator, Arf1, thereby impairing actin polymerization, synapse formation, and immune cell migration. Diminished cortical actin networks caused by WRC loss led to uncontrolled cytokine release and immune hyperresponsiveness. HEM1 loss also blocked mechanistic target of rapamycin complex 2 (mTORC2)-dependent AKT phosphorylation, T cell proliferation, and selected effector functions, leading to immunodeficiency. Thus, the evolutionarily conserved HEM1 protein simultaneously regulates filamentous actin (F-actin) and mTORC2 signaling to achieve equipoise in immune responses.
Keywords: Actins; ADP-Ribosylation Factor 1; CD4-Positive T-Lymphocytes; Cell Proliferation; Cytokines; Humans; Immunologic Deficiency Syndromes; Lymphoproliferative Disorders; Mechanistic Target of Rapamycin Complex 2; Membrane Proteins; Pedigree; Phosphorylation; Wiskott-Aldrich Syndrome Protein Family

Hidden genomic diversity of SARS-CoV-2: implications for qRT-PCR diagnostics and transmission. - Sapoval, Nicolae; Mahmoud, Medhat; Jochum, Michael D; Liu, Yunxi; Elworth, R A Leo; Wang, Qi; Albin, Dreycey; Ogilvie, Huw; Lee, Michael D; Villapol, Sonia; Hernandez, Kyle M; Berry, Irina Maljkovic; et al. (bioRxiv, 2020)
The COVID-19 pandemic has sparked an urgent need to uncover the underlying biology of this devastating disease. Though RNA viruses mutate more rapidly than DNA viruses, there are a relatively small number of single nucleotide polymorphisms (SNPs) that differentiate the main SARS-CoV-2 clades that have spread throughout the world. In this study, we investigated over 7,000 SARS-CoV-2 datasets to unveil both intrahost and interhost diversity. Our intrahost and interhost diversity analyses yielded three major observations. First, the mutational profile of SARS-CoV-2 highlights iSNV and SNP similarity, albeit with high variability in C>T changes. Second, iSNV and SNP patterns in SARS-CoV-2 are more similar to MERS-CoV than SARS-CoV-1. Third, a significant fraction of small indels fuel the genetic diversity of SARS-CoV-2. Altogether, our findings provide insight into SARS-CoV-2 genomic diversity, inform the design of detection tests, and highlight the potential of iSNVs for tracking the transmission of SARS-CoV-2.

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

Identification of novel fusion transcripts in meningioma. - Khan, A Basit; Gadot, Ron; Shetty, Arya; Bayley, James C; Hadley, Caroline C; Cardenas, Maria F; Jalali, Ali; Harmanci, Akdes S; Harmanci, Arif O; David A Wheeler; Klisch, Tiemo J; Patel, Akash J (J Neurooncol, 2020)
INTRODUCTION: Meningiomas are the most common primary intracranial tumor. Recent next generation sequencing analyses have elaborated the molecular drivers of this disease. We aimed to identify and characterize novel fusion genes in meningiomas. METHODS: We performed a secondary analysis of our RNA sequencing data of 145 primary meningioma from 140 patients to detect fusion genes. Semi-quantitative rt-PCR was performed to confirm transcription of the fusion genes in the original tumors. Whole exome sequencing was performed to identify copy number variations within each tumor sample. Comparative RNA seq analysis was performed to assess the clonality of the fusion constructs within the tumor. RESULTS: We detected six fusion events (NOTCH3-SETBP1, NF2-SPATA13, SLC6A3-AGBL3, PHF19-FOXP2 in two patients, and ITPK1-FBP2) in five out of 145 tumor samples. All but one event (NF2-SPATA13) led to extremely short reading frames, making these events de facto null alleles. Three of the five patients had a history of childhood radiation. Four out of six fusion events were detected in expression type C tumors, which represent the most aggressive meningioma. We validated the presence of the RNA transcripts in the tumor tissue by semi-quantitative RT PCR. All but the two PHF19-FOXP2 fusions demonstrated high degrees of clonality. CONCLUSIONS: Fusion genes occur infrequently in meningiomas and are more likely to be found in tumors with greater degree of genomic instability (expression type C) or in patients with history of cranial irradiation.
Keywords: Adult; Aged; Biomarkers, Tumor; Cohort Studies; Female; Follow-Up Studies; High-Throughput Nucleotide Sequencing; Humans; Male; Meningeal Neoplasms; Meningioma; Middle Aged; Mutation; Oncogene Proteins, Fusion; Prognosis

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; Aged; Aged, 80 and over; alpha Karyopherins; Black People; Cell Self Renewal; Clonal Hematopoiesis; Dioxygenases; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

Integrated sequencing and array comparative genomic hybridization in familial Parkinson disease. - Robak, Laurie A; Du, Renqian; Bo Yuan; Gu, Shen; Alfradique-Dunham, Isabel; Kondapalli, Vismaya; Hinojosa, Evelyn; Stillwell, Amanda; Young, Emily; Zhang, Chaofan; Song, Xiaofei; Du, Haowei; et al. (Neurol Genet, 2020)
OBJECTIVE: To determine how single nucleotide variants (SNVs) and copy number variants (CNVs) contribute to molecular diagnosis in familial Parkinson disease (PD), we integrated exome sequencing (ES) and genome-wide array-based comparative genomic hybridization (aCGH) and further probed CNV structure to reveal mutational mechanisms. METHODS: We performed ES on 110 subjects with PD and a positive family history; 99 subjects were also evaluated using genome-wide aCGH. We interrogated ES and aCGH data for pathogenic SNVs and CNVs at Mendelian PD gene loci. We confirmed SNVs via Sanger sequencing and further characterized CNVs with custom-designed high-density aCGH, droplet digital PCR, and breakpoint sequencing. RESULTS: Using ES, we discovered individuals with known pathogenic SNVs in (p.Glu365Lys, p.Thr408Met, p.Asn409Ser, and p.Leu483Pro) and (p.Arg1441Gly and p.Gly2019Ser). Two subjects were each double heterozygotes for variants in and . Based on aCGH, we additionally discovered cases with an duplication and heterozygous intragenic deletion. Five additional subjects harbored both SNVs (p.Asn52Metfs*29, p.Thr240Met, p.Pro437Leu, and p.Trp453*) and likely disrupting CNVs at the locus, consistent with compound heterozygosity. In nearly all cases, breakpoint sequencing revealed microhomology, a mutational signature consistent with CNV formation due to DNA replication errors. CONCLUSIONS: Integrated ES and aCGH yielded a genetic diagnosis in 19.3% of our familial PD cohort. Our analyses highlight potential mechanisms for and CNV formation, uncover multilocus pathogenic variation, and identify novel SNVs and CNVs for further investigation as potential PD risk alleles.

An Introduction to the Callithrix Genus and Overview of Recent Advances in Marmoset Research. - Malukiewicz, Joanna; Boere, Vanner; de Oliveira, Maria Adélia Borstelmann; D'arc, Mirela; Ferreira, Jéssica V A; French, Jeffrey; Housman, Genevieve; de Souza, Claudia Igayara; Jerusalinsky, Leandro; R de Melo, Fabiano; M Valença-Montenegro, Mônica; Moreira, Silvia Bahadian; et al. (ILAR J, 2020)
We provide here a current overview of marmoset (Callithrix) evolution, hybridization, species biology, basic/biomedical research, and conservation initiatives. Composed of 2 subgroups, the aurita group (C aurita and C flaviceps) and the jacchus group (C geoffroyi, C jacchus, C kuhlii, and C penicillata), this relatively young primate radiation is endemic to the Brazilian Cerrado, Caatinga, and Atlantic Forest biomes. Significant impacts on Callithrix within these biomes resulting from anthropogenic activity include (1) population declines, particularly for the aurita group; (2) widespread geographic displacement, biological invasions, and range expansions of C jacchus and C penicillata; (3) anthropogenic hybridization; and (4) epizootic Yellow Fever and Zika viral outbreaks. A number of Brazilian legal and conservation initiatives are now in place to protect the threatened aurita group and increase research about them. Due to their small size and rapid life history, marmosets are prized biomedical models. As a result, there are increasingly sophisticated genomic Callithrix resources available and burgeoning marmoset functional, immuno-, and epigenomic research. In both the laboratory and the wild, marmosets have given us insight into cognition, social group dynamics, human disease, and pregnancy. Callithrix jacchus and C penicillata are emerging neotropical primate models for arbovirus disease, including Dengue and Zika. Wild marmoset populations are helping us understand sylvatic transmission and human spillover of Zika and Yellow Fever viruses. All of these factors are positioning marmosets as preeminent models to facilitate understanding of facets of evolution, hybridization, conservation, human disease, and emerging infectious diseases.
Keywords: Animals; Brazil; Callithrix; Genomics; Hybridization, Genetic; Yellow Fever; Zika Virus; Zika Virus Infection

Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; Exome Sequencing; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents

Mapping the -regulatory architecture of the human retina reveals noncoding genetic variation in disease. - Cherry, Timothy J; Yang, Marty G; Harmin, David A; Tao, Peter; Timms, Andrew E; Bauwens, Miriam; Allikmets, Rando; Jones, Evan M; Rui Chen; De Baere, Elfride; Greenberg, Michael E (Proc Natl Acad Sci U S A, 2020)
The interplay of transcription factors and -regulatory elements (CREs) orchestrates the dynamic and diverse genetic programs that assemble the human central nervous system (CNS) during development and maintain its function throughout life. Genetic variation within CREs plays a central role in phenotypic variation in complex traits including the risk of developing disease. We took advantage of the retina, a well-characterized region of the CNS known to be affected by pathogenic variants in CREs, to establish a roadmap for characterizing regulatory variation in the human CNS. This comprehensive analysis of tissue-specific regulatory elements, transcription factor binding, and gene expression programs in three regions of the human visual system (retina, macula, and retinal pigment epithelium/choroid) reveals features of regulatory element evolution that shape tissue-specific gene expression programs and defines regulatory elements with the potential to contribute to Mendelian and complex disorders of human vision.
Keywords: Adult; Animals; DNA Mutational Analysis; Epigenomics; Evolution, Molecular; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Male; Mice; Middle Aged; Mutation; Regulatory Sequences, Nucleic Acid; Retina; Retinal Diseases; RNA-Seq; Species Specificity

Methylome-wide association study of central adiposity implicates genes involved in immune and endocrine systems. - Justice, Anne E; Chittoor, Geetha; Gondalia, Rahul; Melton, Phillip E; Lim, Elise; Grove, Megan L; Whitsel, Eric A; Liu, Ching-Ti; Cupples, L Adrienne; Fernandez-Rhodes, Lindsay; Guan, Weihua; Bressler, Jan; et al. (Epigenomics, 2020)
We conducted a methylome-wide association study to examine associations between DNA methylation in whole blood and central adiposity and body fat distribution, measured as waist circumference, waist-to-hip ratio and waist-to-height ratio adjusted for body mass index, in 2684 African-American adults in the Atherosclerosis Risk in Communities study. We validated significantly associated cytosine-phosphate-guanine methylation sites (CpGs) among adults using the Women's Health Initiative and Framingham Heart Study participants (combined n = 5743) and generalized associations in adolescents from The Raine Study (n = 820). We identified 11 CpGs that were robustly associated with one or more central adiposity trait in adults and two in adolescents, including CpG site associations near , ,  and that had not previously been associated with obesity-related traits.
Keywords: Adiposity; Cohort Studies; CpG Islands; Disease Susceptibility; DNA Methylation; Endocrine System; Epigenesis, Genetic; Epigenomics; Genome-Wide Association Study; Humans; Immune System; Obesity

Mutations in ASH1L confer susceptibility to Tourette syndrome. - Liu, Shiguo; Tian, Miaomiao; He, Fan; Li, Jiani; Xie, Hong; Liu, Wenmiao; Zhang, Yeting; Zhang, Ru; Yi, Mingji; Che, Fengyuan; Ma, Xu; Zheng, Yi; et al. (Mol Psychiatry, 2020)
Tourette syndrome (TS) is a childhood-onset neuropsychiatric disorder characterized by repetitive motor movements and vocal tics. The clinical manifestations of TS are complex and often overlap with other neuropsychiatric disorders. TS is highly heritable; however, the underlying genetic basis and molecular and neuronal mechanisms of TS remain largely unknown. We performed whole-exome sequencing of a hundred trios (probands and their parents) with detailed records of their clinical presentations and identified a risk gene, ASH1L, that was both de novo mutated and associated with TS based on a transmission disequilibrium test. As a replication, we performed follow-up targeted sequencing of ASH1L in additional 524 unrelated TS samples and replicated the association (P value = 0.001). The point mutations in ASH1L cause defects in its enzymatic activity. Therefore, we established a transgenic mouse line and performed an array of anatomical, behavioral, and functional assays to investigate ASH1L function. The Ash1l mice manifested tic-like behaviors and compulsive behaviors that could be rescued by the tic-relieving drug haloperidol. We also found that Ash1l disruption leads to hyper-activation and elevated dopamine-releasing events in the dorsal striatum, all of which could explain the neural mechanisms for the behavioral abnormalities in mice. Taken together, our results provide compelling evidence that ASH1L is a TS risk gene.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; China; DNA-Binding Proteins; Exome Sequencing; Family; Female; Genetic Predisposition to Disease; Histone-Lysine N-Methyltransferase; Humans; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Parents; Tic Disorders; Tourette Syndrome; Transcription Factors

Nanopore sequencing and the Shasta toolkit enable efficient de novo assembly of eleven human genomes. - Shafin, Kishwar; Pesout, Trevor; Lorig-Roach, Ryan; Haukness, Marina; Olsen, Hugh E; Bosworth, Colleen; Armstrong, Joel; Tigyi, Kristof; Maurer, Nicholas; Koren, Sergey; Fritz J Sedlazeck; Marschall, Tobias; et al. (Nat Biotechnol, 2020)
De novo assembly of a human genome using nanopore long-read sequences has been reported, but it used more than 150,000 CPU hours and weeks of wall-clock time. To enable rapid human genome assembly, we present Shasta, a de novo long-read assembler, and polishing algorithms named MarginPolish and HELEN. Using a single PromethION nanopore sequencer and our toolkit, we assembled 11 highly contiguous human genomes de novo in 9 d. We achieved roughly 63× coverage, 42-kb read N50 values and 6.5× coverage in reads >100 kb using three flow cells per sample. Shasta produced a complete haploid human genome assembly in under 6 h on a single commercial compute node. MarginPolish and HELEN polished haploid assemblies to more than 99.9% identity (Phred quality score QV = 30) with nanopore reads alone. Addition of proximity-ligation sequencing enabled near chromosome-level scaffolds for all 11 genomes. We compare our assembly performance to existing methods for diploid, haploid and trio-binned human samples and report superior accuracy and speed.
Keywords: Algorithms; Benchmarking; Chromosomes, Human; Deep Learning; Genome, Human; Genomics; Haploidy; High-Throughput Nucleotide Sequencing; HLA Antigens; Humans; Nanopore Sequencing; Sequence Analysis, DNA

NEMF mutations that impair ribosome-associated quality control are associated with neuromuscular disease. - Martin, Paige B; Kigoshi-Tansho, Yu; Sher, Roger B; Ravenscroft, Gianina; Stauffer, Jennifer E; Kumar, Rajesh; Yonashiro, Ryo; Müller, Tina; Griffith, Christopher; Allen, William; Pehlivan, Davut; Harel, Tamar; et al. (Nat Commun, 2020)
A hallmark of neurodegeneration is defective protein quality control. The E3 ligase Listerin (LTN1/Ltn1) acts in a specialized protein quality control pathway-Ribosome-associated Quality Control (RQC)-by mediating proteolytic targeting of incomplete polypeptides produced by ribosome stalling, and Ltn1 mutation leads to neurodegeneration in mice. Whether neurodegeneration results from defective RQC and whether defective RQC contributes to human disease have remained unknown. Here we show that three independently-generated mouse models with mutations in a different component of the RQC complex, NEMF/Rqc2, develop progressive motor neuron degeneration. Equivalent mutations in yeast Rqc2 selectively interfere with its ability to modify aberrant translation products with C-terminal tails which assist with RQC-mediated protein degradation, suggesting a pathomechanism. Finally, we identify NEMF mutations expected to interfere with function in patients from seven families presenting juvenile neuromuscular disease. These uncover NEMF's role in translational homeostasis in the nervous system and implicate RQC dysfunction in causing neurodegeneration.
Keywords: Amino Acid Sequence; Animals; Female; Humans; Male; Mice; Mice, Knockout; Mutation; Neuromuscular Diseases; Proteolysis; Ribosomes; RNA-Binding Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sequence Alignment

Parliament2: Accurate structural variant calling at scale. - Zarate, Samantha; Carroll, Andrew; Mahmoud, Medhat; Krasheninina, Olga; Jun, Goo; Salerno, William J; Schatz, Michael C; Eric Boerwinkle; Richard A Gibbs; Fritz J Sedlazeck (Gigascience, 2020)
BACKGROUND: Structural variants (SVs) are critical contributors to genetic diversity and genomic disease. To predict the phenotypic impact of SVs, there is a need for better estimates of both the occurrence and frequency of SVs, preferably from large, ethnically diverse cohorts. Thus, the current standard approach requires the use of short paired-end reads, which remain challenging to detect, especially at the scale of hundreds to thousands of samples. FINDINGS: We present Parliament2, a consensus SV framework that leverages multiple best-in-class methods to identify high-quality SVs from short-read DNA sequence data at scale. Parliament2 incorporates pre-installed SV callers that are optimized for efficient execution in parallel to reduce the overall runtime and costs. We demonstrate the accuracy of Parliament2 when applied to data from NovaSeq and HiSeq X platforms with the Genome in a Bottle (GIAB) SV call set across all size classes. The reported quality score per SV is calibrated across different SV types and size classes. Parliament2 has the highest F1 score (74.27%) measured across the independent gold standard from GIAB. We illustrate the compute performance by processing all 1000 Genomes samples (2,691 samples) in <1 day on GRCH38. Parliament2 improves the runtime performance of individual methods and is open source (https://github.com/slzarate/parliament2), and a Docker image, as well as a WDL implementation, is available. CONCLUSION: Parliament2 provides both a highly accurate single-sample SV call set from short-read DNA sequence data and enables cost-efficient application over cloud or cluster environments, processing thousands of samples.
Keywords: Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis; Software

Phenotypic expansion in KIF1A-related dominant disorders: A description of novel variants and review of published cases. - Montenegro-Garreaud, Ximena; Hansen, Adam W; Khayat, Michael M; Chander, Varuna; Grochowski, Christopher M; Jiang, Yunyun; Li, He; Mitani, Tadahiro; Kessler, Elena; Jayaseelan, Joy; Shen, Hua; Gezdirici, Alper; et al. (Hum Mutat, 2020)
KIF1A is a molecular motor for membrane-bound cargo important to the development and survival of sensory neurons. KIF1A dysfunction has been associated with several Mendelian disorders with a spectrum of overlapping phenotypes, ranging from spastic paraplegia to intellectual disability. We present a novel pathogenic in-frame deletion in the KIF1A molecular motor domain inherited by two affected siblings from an unaffected mother with apparent germline mosaicism. We identified eight additional cases with heterozygous, pathogenic KIF1A variants ascertained from a local data lake. Our data provide evidence for the expansion of KIF1A-associated phenotypes to include hip subluxation and dystonia as well as phenotypes observed in only a single case: gelastic cataplexy, coxa valga, and double collecting system. We review the literature and suggest that KIF1A dysfunction is better understood as a single neuromuscular disorder with variable involvement of other organ systems than a set of discrete disorders converging at a single locus.
Keywords: Child; Child, Preschool; Family; Female; Genes, Dominant; Genetic Predisposition to Disease; Humans; Kinesins; Male; Mutation; Pedigree; Peru; Phenotype

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.
Keywords: Abnormalities, Multiple; Actins; Adult; Amino Acid Substitution; Arginine; Colon; DNA Mutational Analysis; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Intestinal Pseudo-Obstruction; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Urinary Bladder; Young Adult

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

A robust benchmark for detection of germline large deletions and insertions. - Zook, Justin M; Hansen, Nancy F; Olson, Nathan D; Chapman, Lesley; Mullikin, James C; Xiao, Chunlin; Sherry, Stephen; Koren, Sergey; Phillippy, Adam M; Boutros, Paul C; Sahraeian, Sayed Mohammad E; Huang, Vincent; et al. (Nat Biotechnol, 2020)
New technologies and analysis methods are enabling genomic structural variants (SVs) to be detected with ever-increasing accuracy, resolution and comprehensiveness. To help translate these methods to routine research and clinical practice, we developed a sequence-resolved benchmark set for identification of both false-negative and false-positive germline large insertions and deletions. To create this benchmark for a broadly consented son in a Personal Genome Project trio with broadly available cells and DNA, the Genome in a Bottle Consortium integrated 19 sequence-resolved variant calling methods from diverse technologies. The final benchmark set contains 12,745 isolated, sequence-resolved insertion (7,281) and deletion (5,464) calls ≥50 base pairs (bp). The Tier 1 benchmark regions, for which any extra calls are putative false positives, cover 2.51 Gbp and 5,262 insertions and 4,095 deletions supported by ≥1 diploid assembly. We demonstrate that the benchmark set reliably identifies false negatives and false positives in high-quality SV callsets from short-, linked- and long-read sequencing and optical mapping.
Keywords: Diploidy; Genomic Structural Variation; Germ-Line Mutation; Humans; INDEL Mutation; Molecular Sequence Annotation; Sequence Analysis, DNA

Sawfly Genomes Reveal Evolutionary Acquisitions That Fostered the Mega-Radiation of Parasitoid and Eusocial Hymenoptera. - Oeyen, Jan Philip; Baa-Puyoulet, Patrice; Benoit, Joshua B; Beukeboom, Leo W; Bornberg-Bauer, Erich; Buttstedt, Anja; Calevro, Federica; Cash, Elizabeth I; Chao, Hsu; Charles, Hubert; Chen, Mei-Ju May; Childers, Christopher; et al. (Genome Biol Evol, 2020)
The tremendous diversity of Hymenoptera is commonly attributed to the evolution of parasitoidism in the last common ancestor of parasitoid sawflies (Orussidae) and wasp-waisted Hymenoptera (Apocrita). However, Apocrita and Orussidae differ dramatically in their species richness, indicating that the diversification of Apocrita was promoted by additional traits. These traits have remained elusive due to a paucity of sawfly genome sequences, in particular those of parasitoid sawflies. Here, we present comparative analyses of draft genomes of the primarily phytophagous sawfly Athalia rosae and the parasitoid sawfly Orussus abietinus. Our analyses revealed that the ancestral hymenopteran genome exhibited traits that were previously considered unique to eusocial Apocrita (e.g., low transposable element content and activity) and a wider gene repertoire than previously thought (e.g., genes for CO2 detection). Moreover, we discovered that Apocrita evolved a significantly larger array of odorant receptors than sawflies, which could be relevant to the remarkable diversification of Apocrita by enabling efficient detection and reliable identification of hosts.
Keywords: Amino Acid Sequence; Animals; Conserved Sequence; DNA Transposable Elements; Female; Gene Dosage; Genetic Speciation; Genome, Insect; Glycoproteins; Herbivory; Host-Parasite Interactions; Hymenoptera; Immunity; Insect Proteins; Male; Multigene Family; Receptors, Odorant; Social Behavior; Vision, Ocular

Spontaneous hyperactivity in Ash1l mutant mice, a new model for Tourette syndrome. - Liu, Shiguo; Tian, Miaomiao; He, Fan; Li, Jiani; Xie, Hong; Liu, Wenmiao; Zhang, Yeting; Zhang, Ru; Yi, Mingji; Che, Fengyuan; Ma, Xu; Zheng, Yi; et al. (Mol Psychiatry, 2020)

Variant Classification Concordance using the ACMG-AMP Variant Interpretation Guidelines across Nine Genomic Implementation Research Studies. - Amendola, Laura M; Muenzen, Kathleen; Biesecker, Leslie G; Bowling, Kevin M; Cooper, Greg M; Dorschner, Michael O; Driscoll, Catherine; Foreman, Ann Katherine M; Golden-Grant, Katie; Greally, John M; Hindorff, Lucia; Kanavy, Dona; et al. (Am J Hum Genet, 2020)
Harmonization of variant pathogenicity classification across laboratories is important for advancing clinical genomics. The two CLIA-accredited Electronic Medical Record and Genomics Network sequencing centers and the six CLIA-accredited laboratories and one research laboratory performing genome or exome sequencing in the Clinical Sequencing Evidence-Generating Research Consortium collaborated to explore current sources of discordance in classification. Eight laboratories each submitted 20 classified variants in the ACMG secondary finding v.2.0 genes. After removing duplicates, each of the 158 variants was annotated and independently classified by two additional laboratories using the ACMG-AMP guidelines. Overall concordance across three laboratories was assessed and discordant variants were reviewed via teleconference and email. The submitted variant set included 28 P/LP variants, 96 VUS, and 34 LB/B variants, mostly in cancer (40%) and cardiac (27%) risk genes. Eighty-six (54%) variants reached complete five-category (i.e., P, LP, VUS, LB, B) concordance, and 17 (11%) had a discordance that could affect clinical recommendations (P/LP versus VUS/LB/B). 21% and 63% of variants submitted as P and LP, respectively, were discordant with VUS. Of the 54 originally discordant variants that underwent further review, 32 reached agreement, for a post-review concordance rate of 84% (118/140 variants). This project provides an updated estimate of variant concordance, identifies considerations for LP classified variants, and highlights ongoing sources of discordance. Continued and increased sharing of variant classifications and evidence across laboratories, and the ongoing work of ClinGen to provide general as well as gene- and disease-specific guidance, will lead to continued increases in concordance.
Keywords: Cardiovascular Diseases; Computational Biology; Genetic Testing; Genetic Variation; Genetics, Medical; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Laboratories; Laboratory Proficiency Testing; Neoplasms; Sequence Analysis, DNA; Software; Terminology as Topic

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Exome Sequencing; Female; Gene Expression Regulation; Haplotypes; Humans; Immunity; Immunoglobulin G; Kruppel-Like Transcription Factors; Male; Polymorphism, Genetic; RNA, Long Noncoding; Transcription, Genetic

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Black or African American; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Wolff-Parkinson-White Syndrome; Young Adult

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

Abnormal oxidative metabolism in a quiet genomic background underlies clear cell papillary renal cell carcinoma. - Xu, Jianing; Reznik, Ed; Lee, Ho-Joon; Gundem, Gunes; Jonsson, Philip; Sarungbam, Judy; Bialik, Anna; Sánchez-Vega, Francisco; Creighton, Chad J; Hoekstra, Jake; Zhang, Li; Sajjakulnukit, Peter; et al. (Elife, 2019)
While genomic sequencing routinely identifies oncogenic alterations for the majority of cancers, many tumors harbor no discernable driver lesion. Here, we describe the exceptional molecular phenotype of a genomically quiet kidney tumor, clear cell papillary renal cell carcinoma (CCPAP). In spite of a largely wild-type nuclear genome, CCPAP tumors exhibit severe depletion of mitochondrial DNA (mtDNA) and RNA and high levels of oxidative stress, reflecting a shift away from respiratory metabolism. Moreover, CCPAP tumors exhibit a distinct metabolic phenotype uniquely characterized by accumulation of the sugar alcohol sorbitol. Immunohistochemical staining of primary CCPAP tumor specimens recapitulates both the depletion of mtDNA-encoded proteins and a lipid-depleted metabolic phenotype, suggesting that the cytoplasmic clarity in CCPAP is primarily related to the presence of glycogen. These results argue for non-genetic profiling as a tool for the study of cancers of unknown driver.
Keywords: Aerobiosis; Carcinoma, Renal Cell; Cell Respiration; Histocytochemistry; Humans; Immunohistochemistry; Kidney Neoplasms; Metabolic Networks and Pathways; Oxidation-Reduction

Ancestral Admixture Is the Main Determinant of Global Biodiversity in Fission Yeast. - Tusso, Sergio; Nieuwenhuis, Bart P S; Fritz J Sedlazeck; Davey, John W; Jeffares, Daniel C; Wolf, Jochen B W (Mol Biol Evol, 2019)
Mutation and recombination are key evolutionary processes governing phenotypic variation and reproductive isolation. We here demonstrate that biodiversity within all globally known strains of Schizosaccharomyces pombe arose through admixture between two divergent ancestral lineages. Initial hybridization was inferred to have occurred ∼20-60 sexual outcrossing generations ago consistent with recent, human-induced migration at the onset of intensified transcontinental trade. Species-wide heritable phenotypic variation was explained near-exclusively by strain-specific arrangements of alternating ancestry components with evidence for transgressive segregation. Reproductive compatibility between strains was likewise predicted by the degree of shared ancestry. To assess the genetic determinants of ancestry block distribution across the genome, we characterized the type, frequency, and position of structural genomic variation using nanopore and single-molecule real-time sequencing. Despite being associated with double-strand break initiation points, over 800 segregating structural variants exerted overall little influence on the introgression landscape or on reproductive compatibility between strains. In contrast, we found strong ancestry disequilibrium consistent with negative epistatic selection shaping genomic ancestry combinations during the course of hybridization. This study provides a detailed, experimentally tractable example that genomes of natural populations are mosaics reflecting different evolutionary histories. Exploiting genome-wide heterogeneity in the history of ancestral recombination and lineage-specific mutations sheds new light on the population history of S. pombe and highlights the importance of hybridization as a creative force in generating biodiversity.
Keywords: Epistasis, Genetic; Genetic Variation; Genomic Structural Variation; Hybridization, Genetic; Reproductive Isolation; Schizosaccharomyces; Whole Genome Sequencing

ARBoR: an identity and security solution for clinical reporting. - Eric Venner; Mullai Murugan; Hale, Walker; Jones, Jordan M; Lu, Shan; Yi, Victoria; Richard A Gibbs (J Am Med Inform Assoc, 2019)
MOTIVATION: Clinical genome sequencing laboratories return reports containing clinical testing results, signed by a board-certified clinical geneticist, to the ordering physician. This report is often a PDF, but can also be a paper copy or a structured data file. The reports are frequently modified and reissued due to changes in variant interpretation or clinical attributes. MATERIALS AND METHODS: To precisely track report authenticity, we developed ARBoR (Authenticated Resources in a Hashed Block Registry), an application for tracking the authenticity and lineage of versioned clinical reports even when they are distributed as PDF or paper copies. ARBoR tracks clinical reports as cryptographically signed hash blocks in an electronic ledger file, which is then exactly replicated to many clients. RESULTS: ARBoR was implemented for clinical reporting in the Human Genome Sequencing Center Clinical Laboratory, initially as part of the National Institute of Health's Electronic Medical Record and Genomics (eMERGE) project. CONCLUSIONS: To date, we have issued 15 205 versioned clinical reports tracked by ARBoR. This system has provided us with a simple and tamper-proof mechanism for tracking clinical reports with a complicated update history.
Keywords: Clinical Laboratory Techniques; Computer Security; Genetic Testing; Genome, Human; Genomics; Humans; Laboratories; Medical Records; Organizational Case Studies

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Jianhong Hu; Fritz J Sedlazeck; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.
Keywords: DNA Copy Number Variations; Exons; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Author Correction: Duplication of a domestication locus neutralized a cryptic variant that caused a breeding barrier in tomato. - Soyk, Sebastian; Lemmon, Zachary H; Fritz J Sedlazeck; Jiménez-Gómez, José M; Alonge, Michael; Hutton, Samuel F; Van Eck, Joyce; Schatz, Michael C; Lippman, Zachary B (Nat Plants, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Author Correction: Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Author Correction: Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2019)
Christina M. Lill, who contributed to analysis of data, was inadvertently omitted from the author list in the originally published version of this article. This has now been corrected in both the PDF and HTML versions of the article.

Biallelic CACNA2D2 variants in epileptic encephalopathy and cerebellar atrophy. - Punetha, Jaya; Karaca, Ender; Gezdirici, Alper; Lamont, Ryan E; Pehlivan, Davut; Marafi, Dana; Appendino, Juan P; Hunter, Jill V; Akdemir, Zeynep C; Fatih, Jawid M; Jhangiani, Shalini N; Richard A Gibbs; et al. (Ann Clin Transl Neurol, 2019)
OBJECTIVE: To characterize the molecular and clinical phenotypic basis of developmental and epileptic encephalopathies caused by rare biallelic variants in CACNA2D2. METHODS: Two affected individuals from a family with clinical features of early onset epileptic encephalopathy were recruited for exome sequencing at the Centers for Mendelian Genomics to identify their molecular diagnosis. GeneMatcher facilitated identification of a second family with a shared candidate disease gene identified through clinical gene panel-based testing. RESULTS: Rare biallelic CACNA2D2 variants have been previously reported in three families with developmental and epileptic encephalopathy, and one family with congenital ataxia. We identified three individuals in two unrelated families with novel homozygous rare variants in CACNA2D2 with clinical features of developmental and epileptic encephalopathy and cerebellar atrophy. Family 1 includes two affected siblings with a likely damaging homozygous rare missense variant c.1778G>C; p.(Arg593Pro) in CACNA2D2. Family 2 includes a proband with a homozygous rare nonsense variant c.485_486del; p.(Tyr162Ter) in CACNA2D2. We compared clinical and molecular findings from all nine individuals reported to date and note that cerebellar atrophy is shared among all. INTERPRETATION: Our study supports the candidacy of CACNA2D2 as a disease gene associated with a phenotypic spectrum of neurological disease that include features of developmental and epileptic encephalopathy, ataxia, and cerebellar atrophy. Age at presentation may affect apparent penetrance of neurogenetic trait manifestations and of a particular clinical neurological endophenotype, for example, seizures or ataxia.
Keywords: Adult; Atrophy; Calcium Channels; Cerebellar Ataxia; Cerebellar Diseases; Epilepsy; Female; Humans; Male; Mutation, Missense; Pedigree; Seizures; Siblings; Spasms, Infantile

Bi-allelic Pathogenic Variants in TUBGCP2 Cause Microcephaly and Lissencephaly Spectrum Disorders. - Mitani, Tadahiro; Punetha, Jaya; Akalin, Ibrahim; Pehlivan, Davut; Dawidziuk, Mateusz; Coban Akdemir, Zeynep; Yilmaz, Sarenur; Aslan, Ezgi; Hunter, Jill V; Hijazi, Hadia; Grochowski, Christopher M; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2019)
Lissencephaly comprises a spectrum of malformations of cortical development. This spectrum includes agyria, pachygyria, and subcortical band heterotopia; each represents anatomical malformations of brain cortical development caused by neuronal migration defects. The molecular etiologies of neuronal migration anomalies are highly enriched for genes encoding microtubules and microtubule-associated proteins, and this enrichment highlights the critical role for these genes in cortical growth and gyrification. Using exome sequencing and family based rare variant analyses, we identified a homozygous variant (c.997C>T [p.Arg333Cys]) in TUBGCP2, encoding gamma-tubulin complex protein 2 (GCP2), in two individuals from a consanguineous family; both individuals presented with microcephaly and developmental delay. GCP2 forms the multiprotein γ-tubulin ring complex (γ-TuRC) together with γ-tubulin and other GCPs to regulate the assembly of microtubules. By querying clinical exome sequencing cases and through GeneMatcher-facilitated collaborations, we found three additional families with bi-allelic variation and similarly affected phenotypes including a homozygous variant (c.1843G>C [p.Ala615Pro]) in two families and compound heterozygous variants consisting of one missense variant (c.889C>T [p.Arg297Cys]) and one splice variant (c.2025-2A>G) in another family. Brain imaging from all five affected individuals revealed varying degrees of cortical malformations including pachygyria and subcortical band heterotopia, presumably caused by disruption of neuronal migration. Our data demonstrate that pathogenic variants in TUBGCP2 cause an autosomal recessive neurodevelopmental trait consisting of a neuronal migration disorder, and our data implicate GCP2 as a core component of γ-TuRC in neuronal migrating cells.
Keywords: Alleles; Brain; Cell Movement; Child; Exome; Female; Genetic Variation; Homozygote; Humans; Lissencephaly; Male; Microcephaly; Microtubule-Associated Proteins; Microtubules; Nervous System Malformations; Neurons; Phenotype; Tubulin

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.
Keywords: Adolescent; Adult; Alleles; Animals; Cells, Cultured; Child; Child, Preschool; Chromosomal Instability; DNA Damage; Exome Sequencing; Female; Fibroblasts; Genetic Association Studies; Genetic Variation; Humans; Mice; Mice, Knockout; Musculoskeletal Abnormalities; NF-kappa B; Osteochondrodysplasias; Young Adult; Zebrafish

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Bo Yuan; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

The comparative genomics and complex population history of baboons. - Jeffrey Rogers; Raveendran, Muthuswamy; R. Alan Harris; Mailund, Thomas; Leppälä, Kalle; Athanasiadis, Georgios; Schierup, Mikkel Heide; Cheng, Jade; Munch, Kasper; Walker, Jerilyn A; Konkel, Miriam K; Jordan, Vallmer; et al. (Sci Adv, 2019)
Recent studies suggest that closely related species can accumulate substantial genetic and phenotypic differences despite ongoing gene flow, thus challenging traditional ideas regarding the genetics of speciation. Baboons (genus ) are Old World monkeys consisting of six readily distinguishable species. Baboon species hybridize in the wild, and prior data imply a complex history of differentiation and introgression. We produced a reference genome assembly for the olive baboon () and whole-genome sequence data for all six extant species. We document multiple episodes of admixture and introgression during the radiation of baboons, thus demonstrating their value as a model of complex evolutionary divergence, hybridization, and reticulation. These results help inform our understanding of similar cases, including modern humans, Neanderthals, Denisovans, and other ancient hominins.
Keywords: Animals; Base Sequence; Biological Evolution; Female; Gene Flow; Genomics; Haplotypes; Humans; Hybridization, Genetic; Male; Papio; Phylogeny; Polymorphism, Genetic; Whole Genome Sequencing

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

The Consortium of Metabolomics Studies (COMETS): Metabolomics in 47 Prospective Cohort Studies. - Yu, Bing; Zanetti, Krista A; Temprosa, Marinella; Albanes, Demetrius; Appel, Nathan; Barrera, Clara Barrios; Ben-Shlomo, Yoav; Eric Boerwinkle; Casas, Juan P; Clish, Clary; Dale, Caroline; Dehghan, Abbas; et al. (Am J Epidemiol, 2019)
The Consortium of Metabolomics Studies (COMETS) was established in 2014 to facilitate large-scale collaborative research on the human metabolome and its relationship with disease etiology, diagnosis, and prognosis. COMETS comprises 47 cohorts from Asia, Europe, North America, and South America that together include more than 136,000 participants with blood metabolomics data on samples collected from 1985 to 2017. Metabolomics data were provided by 17 different platforms, with the most frequently used labs being Metabolon, Inc. (14 cohorts), the Broad Institute (15 cohorts), and Nightingale Health (11 cohorts). Participants have been followed for a median of 23 years for health outcomes including death, cancer, cardiovascular disease, diabetes, and others; many of the studies are ongoing. Available exposure-related data include common clinical measurements and behavioral factors, as well as genome-wide genotype data. Two feasibility studies were conducted to evaluate the comparability of metabolomics platforms used by COMETS cohorts. The first study showed that the overlap between any 2 different laboratories ranged from 6 to 121 metabolites at 5 leading laboratories. The second study showed that the median Spearman correlation comparing 111 overlapping metabolites captured by Metabolon and the Broad Institute was 0.79 (interquartile range, 0.56-0.89).
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Biomarkers; Body Mass Index; Child; Epidemiologic Methods; Epidemiology; Female; Global Health; Health Behavior; Hematologic Tests; Humans; Longitudinal Studies; Male; Metabolomics; Middle Aged; Prospective Studies; Socioeconomic Factors; Young Adult

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Bo Yuan; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.
Keywords: Chromosome Aberrations; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Testing; Homozygote; Humans; Limit of Detection; Male; Microarray Analysis

A Diagnosis for All Rare Genetic Diseases: The Horizon and the Next Frontiers. - Boycott, Kym M; Hartley, Taila; Biesecker, Leslie G; Richard A Gibbs; Innes, A Micheil; Riess, Olaf; Belmont, John; Dunwoodie, Sally L; Jojic, Nebojsa; Lassmann, Timo; Mackay, Deborah; Temple, I Karen; et al. (Cell, 2019)
The introduction of exome sequencing in the clinic has sparked tremendous optimism for the future of rare disease diagnosis, and there is exciting opportunity to further leverage these advances. To provide diagnostic clarity to all of these patients, however, there is a critical need for the field to develop and implement strategies to understand the mechanisms underlying all rare diseases and translate these to clinical care.
Keywords: Exome; Exome Sequencing; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Rare Diseases; Sequence Analysis, DNA; Translational Research, Biomedical

Duplication of a domestication locus neutralized a cryptic variant that caused a breeding barrier in tomato. - Soyk, Sebastian; Lemmon, Zachary H; Fritz J Sedlazeck; Jiménez-Gómez, José M; Alonge, Michael; Hutton, Samuel F; Van Eck, Joyce; Schatz, Michael C; Lippman, Zachary B (Nat Plants, 2019)
Genome editing technologies are being widely adopted in plant breeding. However, a looming challenge of engineering desirable genetic variation in diverse genotypes is poor predictability of phenotypic outcomes due to unforeseen interactions with pre-existing cryptic mutations. In tomato, breeding with a classical MADS-box gene mutation that improves harvesting by eliminating fruit stem abscission frequently results in excessive inflorescence branching, flowering and reduced fertility due to interaction with a cryptic variant that causes partial mis-splicing in a homologous gene. Here, we show that a recently evolved tandem duplication carrying the second-site variant achieves a threshold of functional transcripts to suppress branching, enabling breeders to neutralize negative epistasis on yield. By dissecting the dosage mechanisms by which this structural variant restored normal flowering and fertility, we devised strategies that use CRISPR-Cas9 genome editing to predictably improve harvesting. Our findings highlight the under-appreciated impact of epistasis in targeted trait breeding and underscore the need for a deeper characterization of cryptic variation to enable the full potential of genome editing in agriculture.
Keywords: CRISPR-Associated Protein 9; CRISPR-Cas Systems; Domestication; Epistasis, Genetic; Flowers; Gene Duplication; Gene Editing; Genetic Variation; Plant Breeding; Plants, Genetically Modified; Quantitative Trait Loci; Reproduction; Solanum lycopersicum

Efficient Variant Set Mixed Model Association Tests for Continuous and Binary Traits in Large-Scale Whole-Genome Sequencing Studies. - Chen, Han; Huffman, Jennifer E; Brody, Jennifer A; Wang, Chaolong; Lee, Seunggeun; Li, Zilin; Gogarten, Stephanie M; Sofer, Tamar; Bielak, Lawrence F; Bis, Joshua C; Blangero, John; Bowler, Russell P; et al. (Am J Hum Genet, 2019)
With advances in whole-genome sequencing (WGS) technology, more advanced statistical methods for testing genetic association with rare variants are being developed. Methods in which variants are grouped for analysis are also known as variant-set, gene-based, and aggregate unit tests. The burden test and sequence kernel association test (SKAT) are two widely used variant-set tests, which were originally developed for samples of unrelated individuals and later have been extended to family data with known pedigree structures. However, computationally efficient and powerful variant-set tests are needed to make analyses tractable in large-scale WGS studies with complex study samples. In this paper, we propose the variant-set mixed model association tests (SMMAT) for continuous and binary traits using the generalized linear mixed model framework. These tests can be applied to large-scale WGS studies involving samples with population structure and relatedness, such as in the National Heart, Lung, and Blood Institute's Trans-Omics for Precision Medicine (TOPMed) program. SMMATs share the same null model for different variant sets, and a virtue of this null model, which includes covariates only, is that it needs to be fit only once for all tests in each genome-wide analysis. Simulation studies show that all the proposed SMMATs correctly control type I error rates for both continuous and binary traits in the presence of population structure and relatedness. We also illustrate our tests in a real data example of analysis of plasma fibrinogen levels in the TOPMed program (n = 23,763), using the Analysis Commons, a cloud-based computing platform.
Keywords: Chromosomes, Human, Pair 4; Cloud Computing; Female; Fibrinogen; Genetic Association Studies; Genetics, Population; Humans; Male; Models, Genetic; National Heart, Lung, and Blood Institute (U.S.); Precision Medicine; Research Design; Time Factors; United States; Whole Genome Sequencing

Evolution of DNA Methylation in Papio Baboons. - Vilgalys, Tauras P; Jeffrey Rogers; Jolly, Clifford J; Mukherjee, Sayan; Tung, Jenny (Mol Biol Evol, 2019)
Changes in gene regulation have long been thought to play an important role in primate evolution. However, although a number of studies have compared genome-wide gene expression patterns across primate species, fewer have investigated the gene regulatory mechanisms that underlie such patterns, or the relative contribution of drift versus selection. Here, we profiled genome-scale DNA methylation levels in blood samples from five of the six extant species of the baboon genus Papio (4-14 individuals per species). This radiation presents the opportunity to investigate DNA methylation divergence at both shallow and deeper timescales (0.380-1.4 My). In contrast to studies in human populations, but similar to studies in great apes, DNA methylation profiles clearly mirror genetic and geographic structure. Divergence in DNA methylation proceeds fastest in unannotated regions of the genome and slowest in regions of the genome that are likely more constrained at the sequence level (e.g., gene exons). Both heuristic approaches and Ornstein-Uhlenbeck models suggest that DNA methylation levels at a small set of sites have been affected by positive selection, and that this class is enriched in functionally relevant contexts, including promoters, enhancers, and CpG islands. Our results thus indicate that the rate and distribution of DNA methylation changes across the genome largely mirror genetic structure. However, at some CpG sites, DNA methylation levels themselves may have been a target of positive selection, pointing to loci that could be important in connecting sequence variation to fitness-related traits.
Keywords: Animals; DNA Methylation; Evolution, Molecular; Papio; Phylogeography

Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls. - Flannick, Jason; Mercader, Josep M; Fuchsberger, Christian; Udler, Miriam S; Mahajan, Anubha; Wessel, Jennifer; Teslovich, Tanya M; Caulkins, Lizz; Koesterer, Ryan; Barajas-Olmos, Francisco; Blackwell, Thomas W; Eric Boerwinkle; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 × 10) and candidate genes from knockout mice (P = 5.2 × 10). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.
Keywords: Animals; Case-Control Studies; Decision Support Techniques; Diabetes Mellitus, Type 2; Exome; Exome Sequencing; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Mice; Mice, Knockout

Exome Sequencing of a Primary Ovarian Insufficiency Cohort Reveals Common Molecular Etiologies for a Spectrum of Disease. - Jolly, Angad; Bayram, Yavuz; Turan, Serap; Aycan, Zehra; Tos, Tulay; Abali, Zehra Yavas; Hacihamdioglu, Bulent; Coban Akdemir, Zeynep Hande; Hijazi, Hadia; Bas, Serpil; Atay, Zeynep; Guran, Tulay; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Primary ovarian insufficiency (POI) encompasses a spectrum of premature menopause, including both primary and secondary amenorrhea. For 75% to 90% of individuals with hypergonadotropic hypogonadism presenting as POI, the molecular etiology is unknown. Common etiologies include chromosomal abnormalities, environmental factors, and congenital disorders affecting ovarian development and function, as well as syndromic and nonsyndromic single gene disorders suggesting POI represents a complex trait. OBJECTIVE: To characterize the contribution of known disease genes to POI and identify molecular etiologies and biological underpinnings of POI. DESIGN, SETTING, AND PARTICIPANTS: We applied exome sequencing (ES) and family-based genomics to 42 affected female individuals from 36 unrelated Turkish families, including 31 with reported parental consanguinity. RESULTS: This analysis identified likely damaging, potentially contributing variants and molecular diagnoses in 16 families (44%), including 11 families with likely damaging variants in known genes and five families with predicted deleterious variants in disease genes (IGSF10, MND1, MRPS22, and SOHLH1) not previously associated with POI. Of the 16 families, 2 (13%) had evidence for potentially pathogenic variants at more than one locus. Absence of heterozygosity consistent with identity-by-descent mediated recessive disease burden contributes to molecular diagnosis in 15 of 16 (94%) families. GeneMatcher allowed identification of additional families from diverse genetic backgrounds. CONCLUSIONS: ES analysis of a POI cohort further characterized locus heterogeneity, reaffirmed the association of genes integral to meiotic recombination, demonstrated the likely contribution of genes involved in hypothalamic development, and documented multilocus pathogenic variation suggesting the potential for oligogenic inheritance contributing to the development of POI.
Keywords: Cell Cycle Proteins; Cohort Studies; DNA Helicases; DNA-Binding Proteins; Exome Sequencing; Female; Gene Frequency; Humans; Hypogonadism; Immunoglobulins; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.
Keywords: Animals; Body Patterning; Embryonic Development; Exome Sequencing; Female; Genetic Association Studies; Genome, Human; Genomics; GTP Phosphohydrolases; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Male; Peroxidases; Zebrafish; Zebrafish Proteins

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Case-Control Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Haplotypes; Humans; Immunity; Lipid Metabolism; Lipids; Male; tau Proteins

A Genocentric Approach to Discovery of Mendelian Disorders. - Hansen, Adam W; Mullai Murugan; Li, He; Khayat, Michael M; Wang, Liwen; Rosenfeld, Jill; B. Kim Andrews; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Fritz J Sedlazeck; Ashley-Koch, Allison E; Liu, Pengfei; et al. (Am J Hum Genet, 2019)
The advent of inexpensive, clinical exome sequencing (ES) has led to the accumulation of genetic data from thousands of samples from individuals affected with a wide range of diseases, but for whom the underlying genetic and molecular etiology of their clinical phenotype remains unknown. In many cases, detailed phenotypes are unavailable or poorly recorded and there is little family history to guide study. To accelerate discovery, we integrated ES data from 18,696 individuals referred for suspected Mendelian disease, together with relatives, in an Apache Hadoop data lake (Hadoop Architecture Lake of Exomes [HARLEE]) and implemented a genocentric analysis that rapidly identified 154 genes harboring variants suspected to cause Mendelian disorders. The approach did not rely on case-specific phenotypic classifications but was driven by optimization of gene- and variant-level filter parameters utilizing historical Mendelian disease-gene association discovery data. Variants in 19 of the 154 candidate genes were subsequently reported as causative of a Mendelian trait and additional data support the association of all other candidate genes with disease endpoints.
Keywords: Databases, Genetic; Exome; Exome Sequencing; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Variation; Genomics; Humans; Pedigree; Phenotype

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.
Keywords: Brain Ischemia; Co-Repressor Proteins; Cohort Studies; Coronary Artery Disease; DNA-Binding Proteins; Factor VII; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Membrane Transport Proteins; Mendelian Randomization Analysis; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Prognosis; Stroke; Venous Thromboembolism

Genome-Wide Association Transethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2019)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46 354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated ≈35 million imputed variants with natural log-transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant ( P≤2.5×10) associations, 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. Mendelian randomization suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.
Keywords: Arterial Occlusive Diseases; Biomarkers; Blood Coagulation; Blood Coagulation Disorders, Inherited; Factor VIII; Genetic Loci; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Phenotype; Ribosomal Protein L3; Risk Factors; Venous Thrombosis; von Willebrand Factor

Genomic Profiling of Childhood Tumor Patient-Derived Xenograft Models to Enable Rational Clinical Trial Design. - Rokita, Jo Lynne; Rathi, Komal S; Cardenas, Maria F; Upton, Kristen A; Jayaseelan, Joy; Cross, Katherine L; Pfeil, Jacob; Egolf, Laura E; Way, Gregory P; Farrel, Alvin; Kendsersky, Nathan M; Patel, Khushbu; et al. (Cell Rep, 2019)
Accelerating cures for children with cancer remains an immediate challenge as a result of extensive oncogenic heterogeneity between and within histologies, distinct molecular mechanisms evolving between diagnosis and relapsed disease, and limited therapeutic options. To systematically prioritize and rationally test novel agents in preclinical murine models, researchers within the Pediatric Preclinical Testing Consortium are continuously developing patient-derived xenografts (PDXs)-many of which are refractory to current standard-of-care treatments-from high-risk childhood cancers. Here, we genomically characterize 261 PDX models from 37 unique pediatric cancers; demonstrate faithful recapitulation of histologies and subtypes; and refine our understanding of relapsed disease. In addition, we use expression signatures to classify tumors for TP53 and NF1 pathway inactivation. We anticipate that these data will serve as a resource for pediatric oncology drug development and will guide rational clinical trial design for children with cancer.
Keywords: Animals; Cell Line, Tumor; Central Nervous System Neoplasms; Child; Clinical Trials as Topic; Disease Models, Animal; Exome Sequencing; Genomics; Humans; Mice; Mutation; Neuroblastoma; Neurofibromin 1; Osteosarcoma; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Rhabdomyosarcoma; Sarcoma, Ewing; Tumor Suppressor Protein p53; Wilms Tumor; Xenograft Model Antitumor Assays

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gozde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.
Keywords: Adolescent; Adult; Arthrogryposis; Child; Child, Preschool; Cohort Studies; Connectin; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Markers; Genomics; Gestational Age; Humans; Infant; Infant, Newborn; Male; Mosaicism; Multifactorial Inheritance; Mutation; Pedigree; Ryanodine Receptor Calcium Release Channel; Vesicular Transport Proteins; Young Adult

Heterozygous CTNNB1 and TBX4 variants in a patient with abnormal lung growth, pulmonary hypertension, microcephaly, and spasticity. - Karolak, Justyna A; Szafranski, Przemyslaw; Kilner, David; Patel, Chirag; Scurry, Bonnie; Kinning, Esther; Chandler, Kate; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; James R Lupski; Popek, Edwina; Stankiewicz, Paweł (Clin Genet, 2019)
The canonical wingless (Wnt) and fibroblast growth factor (FGF) signaling pathways involving CTNNB1 and TBX4, respectively, are crucial for the regulation of human development. Perturbations of these pathways and disruptions from biological homeostasis have been associated with abnormal morphogenesis of multiple organs, including the lung. The aim of this study was to identify the underlying genetic cause of abnormal lung growth, pulmonary hypertension (PAH), severe microcephaly, and muscle spasticity in a full-term newborn, who died at 4 months of age due to progressively worsening PAH and respiratory failure. Family trio exome sequencing showed a de novo heterozygous nonsense c.1603C>T (p.Arg535*) variant in CTNNB1 and a paternally inherited heterozygous missense c.1198G>A (p.Glu400Lys) variant in TBX4, both predicted to be likely deleterious. We expand the phenotypic spectrum associated with CTNNB1 and TBX4 variants and indicate that they could act synergistically to produce a distinct more severe phenotype. Our findings further support a recently proposed complex compound inheritance model in lethal lung developmental diseases and the contention that dual molecular diagnoses can parsimoniously explain blended phenotypes.
Keywords: Alleles; beta Catenin; DNA Mutational Analysis; Exome Sequencing; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Heterozygote; Humans; Hypertension, Pulmonary; Immunohistochemistry; Microcephaly; Muscle Spasticity; Mutation; Phenotype; T-Box Domain Proteins

Homozygous Missense Variants in NTNG2, Encoding a Presynaptic Netrin-G2 Adhesion Protein, Lead to a Distinct Neurodevelopmental Disorder. - Dias, Caroline M; Punetha, Jaya; Zheng, Céline; Mazaheri, Neda; Rad, Abolfazl; Efthymiou, Stephanie; Petersen, Andrea; Dehghani, Mohammadreza; Pehlivan, Davut; Partlow, Jennifer N; Posey, Jennifer E; Salpietro, Vincenzo; et al. (Am J Hum Genet, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Exome Sequencing; Female; GPI-Linked Proteins; Homozygote; Humans; Intellectual Disability; Male; Mutation, Missense; Netrins; Neurodevelopmental Disorders; Pedigree; Young Adult

Hypertensive APOL1 risk allele carriers demonstrate greater blood pressure reduction with angiotensin receptor blockade compared to low risk carriers. - Cunningham, Patrick N; Wang, Zhiying; Grove, Megan L; Cooper-Dehoff, Rhonda M; Beitelshees, Amber L; Gong, Yan; Gums, John G; Johnson, Julie A; Turner, Stephen T; Eric Boerwinkle; Chapman, Arlene B (PLoS One, 2019)
BACKGROUND: Hypertension (HTN) disproportionately affects African Americans (AAs), who respond better to thiazide diuretics than other antihypertensives. Variants of the APOL1 gene found in AAs are associated with a higher rate of kidney disease and play a complex role in cardiovascular disease. METHODS: AA subjects from four HTN trials (n = 961) (GERA1, GERA2, PEAR1, and PEAR2) were evaluated for blood pressure (BP) response based on APOL1 genotype after 4-9 weeks of monotherapy with thiazides, beta blockers, or candesartan. APOL1 G1 and G2 variants were determined by direct sequencing or imputation. RESULTS: Baseline systolic BP (SBP) and diastolic BP (DBP) levels did not differ based on APOL1 genotype. Subjects with 1-2 APOL1 risk alleles had a greater SBP response to candesartan (-12.2 +/- 1.2 vs -7.5 +/- 1.8 mmHg, p = 0.03; GERA2), and a greater decline in albuminuria with candesartan (-8.3 +/- 3.1 vs +3.7 +/- 4.3 mg/day, p = 0.02). APOL1 genotype did not associate with BP response to thiazides or beta blockers. GWAS was performed to determine associations with BP response to candesartan depending on APOL1 genotype. While no SNPs reached genome wide significance, SNP rs10113352, intronic in CSMD1, predicted greater office SBP response to candesartan (p = 3.7 x 10-7) in those with 1-2 risk alleles, while SNP rs286856, intronic in DPP6, predicted greater office SBP response (p = 3.2 x 10-7) in those with 0 risk alleles. CONCLUSIONS: Hypertensive AAs without overt kidney disease who carry 1 or more APOL1 risk variants have a greater BP and albuminuria reduction in response to candesartan therapy. BP response to thiazides or beta blockers did not differ by APOL1 genotype. Future studies confirming this initial finding in an independent cohort are required.
Keywords: Adult; Angiotensin II Type 1 Receptor Blockers; Apolipoprotein L1; Benzimidazoles; Biphenyl Compounds; Black or African American; Female; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Tetrazoles; Treatment Outcome

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.
Keywords: Cohort Studies; Diabetes Mellitus; Female; Genetic Variation; Glycated Hemoglobin; Humans; Male; Polymorphism, Single Nucleotide; Population Groups; Precision Medicine

Improved annotation of the insect vector of citrus greening disease: biocuration by a diverse genomics community. - Saha, Surya; Hosmani, Prashant S; Villalobos-Ayala, Krystal; Miller, Sherry; Shippy, Teresa; Flores, Mirella; Rosendale, Andrew; Cordola, Chris; Bell, Tracey; Mann, Hannah; DeAvila, Gabe; DeAvila, Daniel; et al. (Database (Oxford), 2019)

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Exome Sequencing; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States

Insights into the evolution of social systems and species from baboon studies. - Fischer, Julia; Higham, James P; Alberts, Susan C; Barrett, Louise; Beehner, Jacinta C; Bergman, Thore J; Carter, Alecia J; Collins, Anthony; Elton, Sarah; Fagot, Joël; Ferreira da Silva, Maria Joana; Hammerschmidt, Kurt; et al. (Elife, 2019)
Baboons, members of the genus comprise six closely related species distributed throughout sub-Saharan Africa and southwest Arabia. The species exhibit more ecological flexibility and a wider range of social systems than many other primates. This article summarizes our current knowledge of the natural history of baboons and highlights directions for future research. We suggest that baboons can serve as a valuable model for complex evolutionary processes, such as speciation and hybridization. The evolution of baboons has been heavily shaped by climatic changes and population expansion and fragmentation in the African savanna environment, similar to the processes that acted during human evolution. With accumulating long-term data, and new data from previously understudied species, baboons are ideally suited for investigating the links between sociality, health, longevity and reproductive success. To achieve these aims, we propose a closer integration of studies at the proximate level, including functional genomics, with behavioral and ecological studies.
Keywords: Aging; Animals; Behavior, Animal; Biological Evolution; Ecology; Female; Genomics; Male; Models, Animal; Papio; Phylogeography; Social Behavior

Interchromosomal template-switching as a novel molecular mechanism for imprinting perturbations associated with Temple syndrome. - Carvalho, Claudia M B; Coban-Akdemir, Zeynep; Hijazi, Hadia; Bo Yuan; Pendleton, Matthew; Harrington, Eoghan; Beaulaurier, John; Juul, Sissel; Turner, Daniel J; Kanchi, Rupa S; Jhangiani, Shalini N; Donna M Muzny; et al. (Genome Med, 2019)
BACKGROUND: Intrachromosomal triplications (TRP) can contribute to disease etiology via gene dosage effects, gene disruption, position effects, or fusion gene formation. Recently, post-zygotic de novo triplications adjacent to copy-number neutral genomic intervals with runs of homozygosity (ROH) have been shown to result in uniparental isodisomy (UPD). The genomic structure of these complex genomic rearrangements (CGRs) shows a consistent pattern of an inverted triplication flanked by duplications (DUP-TRP/INV-DUP) formed by an iterative DNA replisome template-switching mechanism during replicative repair of a single-ended, double-stranded DNA (seDNA), the ROH results from an interhomolog or nonsister chromatid template switch. It has been postulated that these CGRs may lead to genetic abnormalities in carriers due to dosage-sensitive genes mapping within the copy-number variant regions, homozygosity for alleles at a locus causing an autosomal recessive (AR) disease trait within the ROH region, or imprinting-associated diseases. METHODS: Here, we report a family wherein the affected subject carries a de novo 2.2-Mb TRP followed by 42.2 Mb of ROH and manifests clinical features overlapping with those observed in association with chromosome 14 maternal UPD (UPD(14)mat). UPD(14)mat can cause clinical phenotypic features enabling a diagnosis of Temple syndrome. This CGR was then molecularly characterized by high-density custom aCGH, genome-wide single-nucleotide polymorphism (SNP) and methylation arrays, exome sequencing (ES), and the Oxford Nanopore long-read sequencing technology. RESULTS: We confirmed the postulated DUP-TRP/INV-DUP structure by multiple orthogonal genomic technologies in the proband. The methylation status of known differentially methylated regions (DMRs) on chromosome 14 revealed that the subject shows the typical methylation pattern of UPD(14)mat. Consistent with these molecular findings, the clinical features overlap with those observed in Temple syndrome, including speech delay. CONCLUSIONS: These data provide experimental evidence that, in humans, triplication can lead to segmental UPD and imprinting disease. Importantly, genotype/phenotype analyses further reveal how a post-zygotically generated complex structural variant, resulting from a replication-based mutational mechanism, contributes to expanding the clinical phenotype of known genetic syndromes. Mechanistically, such events can distort transmission genetics resulting in homozygosity at a locus for which only one parent is a carrier as well as cause imprinting diseases.
Keywords: Chromosome Aberrations; Chromosome Disorders; Chromosomes, Human, Pair 14; DNA Methylation; DNA Replication; Genomic Imprinting; Humans; Male; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2. - Beck, Christine R; Carvalho, Claudia M B; Akdemir, Zeynep C; Fritz J Sedlazeck; Song, Xiaofei; Meng, Qingchang; Hu, Jianhong; Harshavardhan Doddapaneni; Chong, Zechen; Chen, Edward S; Thornton, Philip C; Liu, Pengfei; et al. (Cell, 2019)
DNA rearrangements resulting in human genome structural variants (SVs) are caused by diverse mutational mechanisms. We used long- and short-read sequencing technologies to investigate end products of de novo chromosome 17p11.2 rearrangements and query the molecular mechanisms underlying both recurrent and non-recurrent events. Evidence for an increased rate of clustered single-nucleotide variant (SNV) mutation in cis with non-recurrent rearrangements was found. Indel and SNV formation are associated with both copy-number gains and losses of 17p11.2, occur up to ∼1 Mb away from the breakpoint junctions, and favor C > G transversion substitutions; results suggest that single-stranded DNA is formed during the genesis of the SV and provide compelling support for a microhomology-mediated break-induced replication (MMBIR) mechanism for SV formation. Our data show an additional mutational burden of MMBIR consisting of hypermutation confined to the locus and manifesting as SNVs and indels predominantly within genes.
Keywords: Abnormalities, Multiple; Chromosome Breakpoints; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Humans; INDEL Mutation; Models, Genetic; Mutation; Polymorphism, Single Nucleotide; Recombination, Genetic; Sequence Analysis, DNA; Smith-Magenis Syndrome

Mendelian randomization evaluation of causal effects of fibrinogen on incident coronary heart disease. - Ward-Caviness, Cavin K; de Vries, Paul S; Wiggins, Kerri L; Huffman, Jennifer E; Yanek, Lisa R; Bielak, Lawrence F; Giulianini, Franco; Guo, Xiuqing; Kleber, Marcus E; Kacprowski, Tim; Groß, Stefan; Petersman, Astrid; et al. (PLoS One, 2019)
BACKGROUND: Fibrinogen is an essential hemostatic factor and cardiovascular disease risk factor. Early attempts at evaluating the causal effect of fibrinogen on coronary heart disease (CHD) and myocardial infraction (MI) using Mendelian randomization (MR) used single variant approaches, and did not take advantage of recent genome-wide association studies (GWAS) or multi-variant, pleiotropy robust MR methodologies. METHODS AND FINDINGS: We evaluated evidence for a causal effect of fibrinogen on both CHD and MI using MR. We used both an allele score approach and pleiotropy robust MR models. The allele score was composed of 38 fibrinogen-associated variants from recent GWAS. Initial analyses using the allele score used a meta-analysis of 11 European-ancestry prospective cohorts, free of CHD and MI at baseline, to examine incidence CHD and MI. We also applied 2 sample MR methods with data from a prevalent CHD and MI GWAS. Results are given in terms of the hazard ratio (HR) or odds ratio (OR), depending on the study design, and associated 95% confidence interval (CI). In single variant analyses no causal effect of fibrinogen on CHD or MI was observed. In multi-variant analyses using incidence CHD cases and the allele score approach, the estimated causal effect (HR) of a 1 g/L higher fibrinogen concentration was 1.62 (CI = 1.12, 2.36) when using incident cases and the allele score approach. In 2 sample MR analyses that accounted for pleiotropy, the causal estimate (OR) was reduced to 1.18 (CI = 0.98, 1.42) and 1.09 (CI = 0.89, 1.33) in the 2 most precise (smallest CI) models, out of 4 models evaluated. In the 2 sample MR analyses for MI, there was only very weak evidence of a causal effect in only 1 out of 4 models. CONCLUSIONS: A small causal effect of fibrinogen on CHD is observed using multi-variant MR approaches which account for pleiotropy, but not single variant MR approaches. Taken together, results indicate that even with large sample sizes and multi-variant approaches MR analyses still cannot exclude the null when estimating the causal effect of fibrinogen on CHD, but that any potential causal effect is likely to be much smaller than observed in epidemiological studies.
Keywords: Alleles; Coronary Disease; Fibrinogen; Genetic Pleiotropy; Genetic Variation; Genome-Wide Association Study; Humans; Incidence; Mendelian Randomization Analysis; Models, Genetic; Multivariate Analysis; Myocardial Infarction; Odds Ratio

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Amino Acid Sequence; Autistic Disorder; Child; Child, Preschool; Female; Genetic Association Studies; Humans; Infant; Intellectual Disability; Male; Mutation, Missense; Nuclear Proteins; Prognosis; Sequence Homology; Syndrome; Young Adult

Molecular evolutionary trends and feeding ecology diversification in the Hemiptera, anchored by the milkweed bug genome. - Panfilio, Kristen A; Vargas Jentzsch, Iris M; Benoit, Joshua B; Erezyilmaz, Deniz; Suzuki, Yuichiro; Colella, Stefano; Robertson, Hugh M; Poelchau, Monica F; Waterhouse, Robert M; Ioannidis, Panagiotis; Weirauch, Matthew T; Hughes, Daniel S T; et al. (Genome Biol, 2019)
BACKGROUND: The Hemiptera (aphids, cicadas, and true bugs) are a key insect order, with high diversity for feeding ecology and excellent experimental tractability for molecular genetics. Building upon recent sequencing of hemipteran pests such as phloem-feeding aphids and blood-feeding bed bugs, we present the genome sequence and comparative analyses centered on the milkweed bug Oncopeltus fasciatus, a seed feeder of the family Lygaeidae. RESULTS: The 926-Mb Oncopeltus genome is well represented by the current assembly and official gene set. We use our genomic and RNA-seq data not only to characterize the protein-coding gene repertoire and perform isoform-specific RNAi, but also to elucidate patterns of molecular evolution and physiology. We find ongoing, lineage-specific expansion and diversification of repressive C2H2 zinc finger proteins. The discovery of intron gain and turnover specific to the Hemiptera also prompted the evaluation of lineage and genome size as predictors of gene structure evolution. Furthermore, we identify enzymatic gains and losses that correlate with feeding biology, particularly for reductions associated with derived, fluid nutrition feeding. CONCLUSIONS: With the milkweed bug, we now have a critical mass of sequenced species for a hemimetabolous insect order and close outgroup to the Holometabola, substantially improving the diversity of insect genomics. We thereby define commonalities among the Hemiptera and delve into how hemipteran genomes reflect distinct feeding ecologies. Given Oncopeltus's strength as an experimental model, these new sequence resources bolster the foundation for molecular research and highlight technical considerations for the analysis of medium-sized invertebrate genomes.
Keywords: Amino Acid Sequence; Animals; CYS2-HIS2 Zinc Fingers; Evolution, Molecular; Feeding Behavior; Gene Dosage; Gene Expression Profiling; Gene Transfer, Horizontal; Genes, Homeobox; Genome, Insect; Hemiptera; Pigmentation; Smell; Transcription Factors

Molecular profiling predicts meningioma recurrence and reveals loss of DREAM complex repression in aggressive tumors. - Patel, Akash J; Wan, Ying-Wooi; Al-Ouran, Rami; Revelli, Jean-Pierre; Cardenas, Maria F; Oneissi, Mazen; Xi, Liu; Jalali, Ali; Magnotti, John F; Donna M Muzny; Harshavardhan Doddapaneni; Sebastian, Sherly; et al. (Proc Natl Acad Sci U S A, 2019)
Meningiomas account for one-third of all primary brain tumors. Although typically benign, about 20% of meningiomas are aggressive, and despite the rigor of the current histopathological classification system there remains considerable uncertainty in predicting tumor behavior. Here, we analyzed 160 tumors from all 3 World Health Organization (WHO) grades (I through III) using clinical, gene expression, and sequencing data. Unsupervised clustering analysis identified 3 molecular types (A, B, and C) that reliably predicted recurrence. These groups did not directly correlate with the WHO grading system, which classifies more than half of the tumors in the most aggressive molecular type as benign. Transcriptional and biochemical analyses revealed that aggressive meningiomas involve loss of the repressor function of the DREAM complex, which results in cell-cycle activation; only tumors in this category tend to recur after full resection. These findings should improve our ability to predict recurrence and develop targeted treatments for these clinically challenging tumors.
Keywords: Adult; Aged; Aged, 80 and over; Cell Cycle; Cell Line; Disease Progression; DNA Copy Number Variations; Female; Gene Expression Profiling; Humans; Kv Channel-Interacting Proteins; Male; Meningeal Neoplasms; Meningioma; Middle Aged; Neoplasm Recurrence, Local; Prognosis; Repressor Proteins; Young Adult

Multiancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
A person's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multiancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in stage 1 (genome-wide discovery) and 66 studies in stage 2 (focused follow-up), for a total of 394,584 individuals from 5 ancestry groups. Analyses covered the period July 2014-November 2017. Genetic main effects and interaction effects were jointly assessed by means of a 2-degrees-of-freedom (df) test, and a 1-df test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in stage 1 and were evaluated in stage 2, followed by combined analyses of stage 1 and stage 2. In the combined analysis of stages 1 and 2, a total of 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2-df tests, of which 18 were novel. No genome-wide-significant associations were found testing the interaction effect alone. The novel loci included several genes (proprotein convertase subtilisin/kexin type 5 (PCSK5), vascular endothelial growth factor B (VEGFB), and apolipoprotein B mRNA editing enzyme, catalytic polypeptide 1 (APOBEC1) complementation factor (A1CF)) that have a putative role in lipid metabolism on the basis of existing evidence from cellular and experimental models.
Keywords: Adolescent; Adult; Aged; Alcohol Drinking; Cholesterol, HDL; Cholesterol, LDL; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Lipids; Male; Middle Aged; Phenotype; Racial Groups; Triglycerides; Vascular Endothelial Growth Factor B; Young Adult

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Linkage Disequilibrium; Lipids; Male; Middle Aged; Smoking; Young Adult

A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure. - Sung, Yun Ju; de Las Fuentes, Lisa; Winkler, Thomas W; Chasman, Daniel I; Bentley, Amy R; Kraja, Aldi T; Ntalla, Ioanna; Warren, Helen R; Guo, Xiuqing; Schwander, Karen; Manning, Alisa K; Brown, Michael R; et al. (Hum Mol Genet, 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 × 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Antiporters; Arterial Pressure; Blood Pressure; Caspase 9; Ethnicity; Female; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Middle Aged; Polymorphism, Genetic; Racial Groups; Receptors, Vasopressin; Smoking; Sulfate Transporters; Tumor Suppressor Proteins; Young Adult

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian People; Black People; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic or Latino; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; White People; Young Adult

Mutations in ANKLE2, a ZIKA Virus Target, Disrupt an Asymmetric Cell Division Pathway in Drosophila Neuroblasts to Cause Microcephaly. - Link, Nichole; Chung, Hyunglok; Jolly, Angad; Withers, Marjorie; Tepe, Burak; Arenkiel, Benjamin R; Shah, Priya S; Krogan, Nevan J; Aydin, Hatip; Geckinli, Bilgen B; Tos, Tulay; Isikay, Sedat; et al. (Dev Cell, 2019)
The apical Par complex, which contains atypical protein kinase C (aPKC), Bazooka (Par-3), and Par-6, is required for establishing polarity during asymmetric division of neuroblasts in Drosophila, and its activity depends on L(2)gl. We show that loss of Ankle2, a protein associated with microcephaly in humans and known to interact with Zika protein NS4A, reduces brain volume in flies and impacts the function of the Par complex. Reducing Ankle2 levels disrupts endoplasmic reticulum (ER) and nuclear envelope morphology, releasing the kinase Ballchen-VRK1 into the cytosol. These defects are associated with reduced phosphorylation of aPKC, disruption of Par-complex localization, and spindle alignment defects. Importantly, removal of one copy of ballchen or l(2)gl suppresses Ankle2 mutant phenotypes and restores viability and brain size. Human mutational studies implicate the above-mentioned genes in microcephaly and motor neuron disease. We suggest that NS4A, ANKLE2, VRK1, and LLGL1 define a pathway impinging on asymmetric determinants of neural stem cell division.
Keywords: Animals; Asymmetric Cell Division; Cell Division; Cell Polarity; Drosophila melanogaster; Humans; Membrane Proteins; Microcephaly; Mutation; Neural Stem Cells; Neurons; Nuclear Proteins; Zika Virus

A novel disorder involving dyshematopoiesis, inflammation, and HLH due to aberrant CDC42 function. - Lam, Michael T; Coppola, Simona; Krumbach, Oliver H F; Prencipe, Giusi; Insalaco, Antonella; Cifaldi, Cristina; Brigida, Immacolata; Zara, Erika; Scala, Serena; Di Cesare, Silvia; Martinelli, Simone; Di Rocco, Martina; et al. (J Exp Med, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by immune dysregulation due to inadequate restraint of overactivated immune cells and is associated with a variable clinical spectrum having overlap with more common pathophysiologies. HLH is difficult to diagnose and can be part of inflammatory syndromes. Here, we identify a novel hematological/autoinflammatory condition (NOCARH syndrome) in four unrelated patients with superimposable features, including neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and HLH. Patients shared the same de novo mutation (Chr1:22417990C>T, p.R186C) and altered hematopoietic compartment, immune dysregulation, and inflammation. mutations had been associated with syndromic neurodevelopmental disorders. In vitro and in vivo assays documented unique effects of p.R186C on CDC42 localization and function, correlating with the distinctiveness of the trait. Emapalumab was critical to the survival of one patient, who underwent successful bone marrow transplantation. Early recognition of the disorder and establishment of treatment followed by bone marrow transplant are important to survival.
Keywords: Alleles; Amino Acid Substitution; Animals; Binding Sites; cdc42 GTP-Binding Protein; Cell Line, Tumor; Child; Disease Susceptibility; Female; Genetic Association Studies; Genotype; Humans; Infant; Lymphohistiocytosis, Hemophagocytic; Male; Mice; Models, Molecular; Molecular Conformation; Mutation; Phenotype; Protein Binding

Novel Heterozygous Mutation in Is Associated With Early Onset CVID and a Functional Defect in NK Cells Complicated by Disseminated CMV Infection and Severe Nephrotic Syndrome. - Aird, Alejandra; Lagos, Macarena; Vargas-Hernandez, Alexander; Posey, Jennifer E; Coban-Akdemir, Zeynep; Jhangiani, Shalini; Mace, Emily M; Reyes, Anaid; King, Alejandra; Cavagnaro, Felipe; Forbes, Lisa R; Chinn, Ivan K; et al. (Front Pediatr, 2019)
Nuclear factor kappa-B subunit 2 (NF-κB2/p100/p52), encoded by (MIM: 164012) belongs to the NF-κB family of transcription factors that play a critical role in inflammation, immunity, cell proliferation, differentiation and survival. Heterozygous C-terminal mutations in have been associated with early-onset common variable immunodeficiency (CVID), central adrenal insufficiency and ectodermal dysplasia. Only two previously reported cases have documented decreased natural killer (NK) cell cytotoxicity, and little is known about the role of NF-κB2 in NK cell maturation and function. Here we report a 13-year-old female that presented at 6 years of age with a history of early onset recurrent sinopulmonary infections, progressive hair loss, and hypogamaglobulinemia consistent with a clinical diagnosis of CVID. At 9 years of age she had cytomegalovirus (CMV) pneumonia that responded to ganciclovir treatment. Functional NK cell testing demonstrated decreased NK cell cytotoxicity despite normal NK cell numbers, consistent with a greater susceptibility to systemic CMV infection. Research exome sequencing (ES) was performed and revealed a novel heterozygous nonsense mutation in (c.2611C>T, p.Gln871) that was not carried by either of her parents. The variant was Sanger sequenced and confirmed to be in the patient. At age 12, she presented with a reactivation of the systemic CMV infection that was associated with severe and progressive nephrotic syndrome with histologic evidence of pedicellar effacement and negative immunofluorescence. To our knowledge, this is the third NF-κB2 deficient patient in which an abnormal NK cell function has been observed, suggesting a role for non-canonical NF-κB2 signaling in NK cell cytotoxicity. NK cell function should be assessed in patients with mutations in the non-canonical NF-κB pathway to explore the risk for systemic viral infections that may lead to severe complications and impact patient survival. Similarly NF-κB2 should be considered in patients with combined immunodeficiency who have aberrant NK cell function. Further studies are needed to characterize the role of NF-κB2 in NK cell cytotoxic function.

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.
Keywords: DEAD-box RNA Helicases; Exome Sequencing; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Neoplasm Proteins; Neurodevelopmental Disorders; Pedigree; RNA Helicases

A Patient with Berardinelli-Seip Syndrome, Novel Splicesite Mutation and Concomitant Development of Non-diabetic Polyneuropathy. - Oswiecimska, Joanna; Dawidziuk, Mateusz; Gambin, Tomasz; Ziora, Katarzyna; Marek, Marta; Rzonca, Sylwia; Guilbride, D. Lys; Jhangiani, Shalini N.; Obuchowicz, Anna; Sikora, Alicja; Lupski, James R.; Wiszniewski, Wojciech; et al. (J Clin Res Pediatr Endocrinol, 2019)
Primary polyneuropathy in the context of Seip-Berardinelli type 1 seipinopathy, or congenital generalized lipodystrophy type 1 (CGL1) has not been previously reported. We report the case history of a 27 year old female CGL1 patient presenting with an unusual additional development of non-diabetic peripheral neuropathy and learning disabilities in early adolescence. Whole exome sequencing (WES) of the patient genome identified a novel variant, homozygous for a 52 bp intronic deletion in the locus, coding for 1-acylglycerol-3-phosphate O-acyltransferase 2, which is uniquely associated with CGL1 seipinopathies, with no molecular evidence for dual diagnosis. Functional studies using RNA isolated from patient peripheral blood leucocytes showed abnormal RNA splicing resulting in the loss of 25 amino acids from the patient AGPAT2 protein coding sequence. Stability and transcription levels for the misspliced mRNA in our patient nonetheless remained normal. Any AGPAT2 protein produced in our patient is therefore likely to be dysfunctional. However, formal linkage of this deletion to the neuropathy observed remains to be shown. The classical clinical presentation of a patient with -associated lipodystrophy shows normal cognition and no development of polyneuropathy. Cognitive disabilities and polyneuropathy are features associated exclusively with clinical CGL type 2 arising from seipin gene mutations. This case study suggests that in some genetic contexts, mutations can also produce phenotypes with primary polyneuropathy.
Keywords: Acyltransferases; Adult; Female; Humans; Infant; Lipodystrophy, Congenital Generalized; Male; Mutation; Pedigree; Polyneuropathies; Prognosis; RNA Splice Sites

Protein-coding variants implicate novel genes related to lipid homeostasis contributing to body-fat distribution. - Justice, Anne E; Karaderi, Tugce; Highland, Heather M; Young, Kristin L; Graff, Mariaelisa; Lu, Yingchang; Turcot, Valérie; Auer, Paul L; Fine, Rebecca S; Guo, Xiuqing; Schurmann, Claudia; Lempradl, Adelheid; et al. (Nat Genet, 2019)
Body-fat distribution is a risk factor for adverse cardiovascular health consequences. We analyzed the association of body-fat distribution, assessed by waist-to-hip ratio adjusted for body mass index, with 228,985 predicted coding and splice site variants available on exome arrays in up to 344,369 individuals from five major ancestries (discovery) and 132,177 European-ancestry individuals (validation). We identified 15 common (minor allele frequency, MAF ≥5%) and nine low-frequency or rare (MAF <5%) coding novel variants. Pathway/gene set enrichment analyses identified lipid particle, adiponectin, abnormal white adipose tissue physiology and bone development and morphology as important contributors to fat distribution, while cross-trait associations highlight cardiometabolic traits. In functional follow-up analyses, specifically in Drosophila RNAi-knockdowns, we observed a significant increase in the total body triglyceride levels for two genes (DNAH10 and PLXND1). We implicate novel genes in fat distribution, stressing the importance of interrogating low-frequency and protein-coding variants.
Keywords: Animals; Body Fat Distribution; Body Mass Index; Case-Control Studies; Drosophila; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeostasis; Humans; Lipids; Male; Proteins; Risk Factors; Waist-Hip Ratio

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Reply. - Pearce, William; Rui Chen; Jain, Nieraj (Ophthalmology, 2019)
Keywords: Humans; Macular Degeneration; Pentosan Sulfuric Polyester

Subtle changes in chromatin loop contact propensity are associated with differential gene regulation and expression. - Greenwald, William W; Li, He; Benaglio, Paola; Jakubosky, David; Matsui, Hiroko; Schmitt, Anthony; Selvaraj, Siddarth; D'Antonio, Matteo; D'Antonio-Chronowska, Agnieszka; Smith, Erin N; Frazer, Kelly A (Nat Commun, 2019)
While genetic variation at chromatin loops is relevant for human disease, the relationships between contact propensity (the probability that loci at loops physically interact), genetics, and gene regulation are unclear. We quantitatively interrogate these relationships by comparing Hi-C and molecular phenotype data across cell types and haplotypes. While chromatin loops consistently form across different cell types, they have subtle quantitative differences in contact frequency that are associated with larger changes in gene expression and H3K27ac. For the vast majority of loci with quantitative differences in contact frequency across haplotypes, the changes in magnitude are smaller than those across cell types; however, the proportional relationships between contact propensity, gene expression, and H3K27ac are consistent. These findings suggest that subtle changes in contact propensity have a biologically meaningful role in gene regulation and could be a mechanism by which regulatory genetic variants in loop anchors mediate effects on expression.
Keywords: Adolescent; Adult; Aged; Cell Line; Chromatin; DNA; Female; Gene Expression Regulation; Histones; Humans; Induced Pluripotent Stem Cells; Male; Middle Aged; Myocytes, Cardiac; Nucleic Acid Conformation; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Whole Genome Sequencing; Young Adult

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.
Keywords: Animals; Cohort Studies; Disease Models, Animal; Gene Dosage; Humans; Inheritance Patterns; Mice; Models, Genetic; Scoliosis; Spine; T-Box Domain Proteins

Use of >100,000 NHLBI Trans-Omics for Precision Medicine (TOPMed) Consortium whole genome sequences improves imputation quality and detection of rare variant associations in admixed African and Hispanic/Latino populations. - Kowalski, Madeline H; Qian, Huijun; Hou, Ziyi; Rosen, Jonathan D; Tapia, Amanda L; Shan, Yue; Jain, Deepti; Argos, Maria; Arnett, Donna K; Avery, Christy; Barnes, Kathleen C; Becker, Lewis C; et al. (PLoS Genet, 2019)
Most genome-wide association and fine-mapping studies to date have been conducted in individuals of European descent, and genetic studies of populations of Hispanic/Latino and African ancestry are limited. In addition, these populations have more complex linkage disequilibrium structure. In order to better define the genetic architecture of these understudied populations, we leveraged >100,000 phased sequences available from deep-coverage whole genome sequencing through the multi-ethnic NHLBI Trans-Omics for Precision Medicine (TOPMed) program to impute genotypes into admixed African and Hispanic/Latino samples with genome-wide genotyping array data. We demonstrated that using TOPMed sequencing data as the imputation reference panel improves genotype imputation quality in these populations, which subsequently enhanced gene-mapping power for complex traits. For rare variants with minor allele frequency (MAF) < 0.5%, we observed a 2.3- to 6.1-fold increase in the number of well-imputed variants, with 11-34% improvement in average imputation quality, compared to the state-of-the-art 1000 Genomes Project Phase 3 and Haplotype Reference Consortium reference panels. Impressively, even for extremely rare variants with minor allele count <10 (including singletons) in the imputation target samples, average information content rescued was >86%. Subsequent association analyses of TOPMed reference panel-imputed genotype data with hematological traits (hemoglobin (HGB), hematocrit (HCT), and white blood cell count (WBC)) in ~21,600 African-ancestry and ~21,700 Hispanic/Latino individuals identified associations with two rare variants in the HBB gene (rs33930165 with higher WBC [p = 8.8x10-15] in African populations, rs11549407 with lower HGB [p = 1.5x10-12] and HCT [p = 8.8x10-10] in Hispanics/Latinos). By comparison, neither variant would have been genome-wide significant if either 1000 Genomes Project Phase 3 or Haplotype Reference Consortium reference panels had been used for imputation. Our findings highlight the utility of the TOPMed imputation reference panel for identification of novel rare variant associations not previously detected in similarly sized genome-wide studies of under-represented African and Hispanic/Latino populations.
Keywords: Adult; Aged; Aged, 80 and over; beta-Globins; Black or African American; Computational Biology; Databases, Genetic; Female; Gene Frequency; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Genotyping Techniques; Hispanic or Latino; Humans; Linkage Disequilibrium; Male; Middle Aged; Precision Medicine; United States; Whole Genome Sequencing

Xia-Gibbs syndrome in adulthood: a case report with insight into the natural history of the condition. - David R Murdock; Jiang, Yunyun; Wangler, Michael; Khayat, Michael M; Aniko Sabo; Juusola, Jane; McWalter, Kirsty; Schatz, Krista Sondergaard; Gunay-Aygun, Meral; Richard A Gibbs (Cold Spring Harb Mol Case Stud, 2019)
A 55-yr-old male with severe intellectual disability, behavioral problems, kyphoscoliosis, and dysmorphic features was referred for a genetic evaluation. Chromosomal microarray, RASopathy gene panel, mitochondrial sequencing, and fragile X testing were all negative. Subsequent whole-exome sequencing revealed a heterozygous, truncating variant in the gene, consistent with a diagnosis of Xia-Gibbs syndrome (XGS). Review of his clinical history showed many classic dysmorphic and clinical features of XGS, but no major health issues in adulthood other than intellectual disability. This individual is the oldest published XGS case to date, demonstrates the wide phenotypic spectrum of the disorder, and provides information on the condition's natural history. As more adults undergo genomic studies, we will continue to learn about the adult phenotypes of genetic conditions typically diagnosed in the pediatric setting.
Keywords: Abnormalities, Multiple; Exome Sequencing; Heterozygote; Humans; Intellectual Disability; Male; Middle Aged

Additive genetic variation in the craniofacial skeleton of baboons (genus Papio) and its relationship to body and cranial size. - Joganic, Jessica L; Willmore, Katherine E; Richtsmeier, Joan T; Weiss, Kenneth M; Mahaney, Michael C; Rogers, Jeffrey; Cheverud, James M (Am J Phys Anthropol, 2018)
OBJECTIVES: Determining the genetic architecture of quantitative traits and genetic correlations among them is important for understanding morphological evolution patterns. We address two questions regarding papionin evolution: (1) what effect do body and cranial size, age, and sex have on phenotypic (V ) and additive genetic (V ) variation in baboon crania, and (2) how might additive genetic correlations between craniofacial traits and body mass affect morphological evolution? MATERIALS AND METHODS: We use a large captive pedigreed baboon sample to estimate quantitative genetic parameters for craniofacial dimensions (EIDs). Our models include nested combinations of the covariates listed above. We also simulate the correlated response of a given EID due to selection on body mass alone. RESULTS: Covariates account for 1.2-91% of craniofacial V . EID V decreases across models as more covariates are included. The median genetic correlation estimate between each EID and body mass is 0.33. Analysis of the multivariate response to selection reveals that observed patterns of craniofacial variation in extant baboons cannot be attributed solely to correlated response to selection on body mass, particularly in males. DISCUSSION: Because a relatively large proportion of EID V is shared with body mass variation, different methods of correcting for allometry by statistically controlling for size can alter residual V patterns. This may conflate direct selection effects on craniofacial variation with those resulting from a correlated response to body mass selection. This shared genetic variation may partially explain how selection for increased body mass in two different papionin lineages produced remarkably similar craniofacial phenotypes.
Keywords: Animals; Anthropology, Physical; Biological Evolution; Body Size; Cephalometry; Face; Female; Genetic Variation; Genetics, Population; Male; Papio; Skull

Author Correction: A proteomic landscape of diffuse-type gastric cancer. - Ge, Sai; Xia, Xia; Ding, Chen; Zhen, Bei; Zhou, Quan; Feng, Jinwen; Yuan, Jiajia; Chen, Rui; Li, Yumei; Ge, Zhongqi; Ji, Jiafu; Zhang, Lianhai; et al. (Nat Commun, 2018)
The original version of this Article contained an error in the email address of the corresponding author Jun Qin. The correct email is jqin1965@126.com. The error has been corrected in the HTML and PDF versions of the Article.

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Doddapaneni, Harsha; Hu, Jianhong; Muzny, Donna M; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Exome Sequencing; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Microfilament Proteins; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesins; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome

Blood pressure signature genes and blood pressure response to thiazide diuretics: results from the PEAR and PEAR-2 studies. - Sá, Ana Caroline C; Webb, Amy; Gong, Yan; McDonough, Caitrin W; Shahin, Mohamed H; Datta, Somnath; Langaee, Taimour Y; Turner, Stephen T; Beitelshees, Amber L; Chapman, Arlene B; Boerwinkle, Eric; Gums, John G; et al. (BMC Med Genomics, 2018)
BACKGROUND: Recently, 34 genes had been associated with differential expression relative to blood pressure (BP)/ hypertension (HTN). We hypothesize that some of the genes associated with BP/HTN are also associated with BP response to antihypertensive treatment with thiazide diuretics. METHODS: We assessed these 34 genes for association with differential expression to BP response to thiazide diuretics with RNA sequencing in whole blood samples from 150 hypertensive participants from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) and PEAR-2 studies. PEAR white and PEAR-2 white and black participants (n = 50 for each group) were selected based on the upper and lower quartile of BP response to hydrochlorothiazide (HCTZ) and to chlorthalidone. RESULTS: FOS, DUSP1 and PPP1R15A were differentially expressed across all cohorts (meta-analysis p-value < 2.0 × 10), and responders to HCTZ or chlorthalidone presented up-regulated transcripts. Rs11065987 in chromosome 12, a trans-eQTL for expression of FOS, PPP1R15A and other genes, is also associated with BP response to HCTZ in PEAR whites (SBP: β = - 2.1; p = 1.7 × 10; DBP: β = - 1.4; p = 2.9 × 10). CONCLUSIONS: These findings suggest FOS, DUSP1 and PPP1R15A as potential molecular determinants of antihypertensive response to thiazide diuretics. TRIAL REGISTRATION: NCT00246519 , NCT01203852 www.clinicaltrials.gov.
Keywords: Antihypertensive Agents; Blood Pressure; Female; Gene Expression Profiling; Humans; Hypertension; Male; Middle Aged; Pharmacogenomic Testing; Sodium Chloride Symporter Inhibitors

CD163+ macrophages promote angiogenesis and vascular permeability accompanied by inflammation in atherosclerosis. - Guo, Liang; Akahori, Hirokuni; Harari, Emanuel; Smith, Samantha L; Polavarapu, Rohini; Karmali, Vinit; Otsuka, Fumiyuki; Gannon, Rachel L; Braumann, Ryan E; Dickinson, Megan H; Gupta, Anuj; Jenkins, Audrey L; et al. (J Clin Invest, 2018)
Intake of hemoglobin by the hemoglobin-haptoglobin receptor CD163 leads to a distinct alternative non-foam cell antiinflammatory macrophage phenotype that was previously considered atheroprotective. Here, we reveal an unexpected but important pathogenic role for these macrophages in atherosclerosis. Using human atherosclerotic samples, cultured cells, and a mouse model of advanced atherosclerosis, we investigated the role of intraplaque hemorrhage on macrophage function with respect to angiogenesis, vascular permeability, inflammation, and plaque progression. In human atherosclerotic lesions, CD163+ macrophages were associated with plaque progression, microvascularity, and a high level of HIF1α and VEGF-A expression. We observed irregular vascular endothelial cadherin in intraplaque microvessels surrounded by CD163+ macrophages. Within these cells, activation of HIF1α via inhibition of prolyl hydroxylases promoted VEGF-mediated increases in intraplaque angiogenesis, vascular permeability, and inflammatory cell recruitment. CD163+ macrophages increased intraplaque endothelial VCAM expression and plaque inflammation. Subjects with homozygous minor alleles of the SNP rs7136716 had elevated microvessel density, increased expression of CD163 in ruptured coronary plaques, and a higher risk of myocardial infarction and coronary heart disease in population cohorts. Thus, our findings highlight a nonlipid-driven mechanism by which alternative macrophages promote plaque angiogenesis, leakiness, inflammation, and progression via the CD163/HIF1α/VEGF-A pathway.
Keywords: Adult; Animals; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Atherosclerosis; Coronary Disease; Coronary Vessels; Disease Progression; Female; Hemoglobins; Humans; Inflammation; Macrophages; Male; Mice; Mice, Inbred C57BL; Middle Aged; Myocardial Infarction; Neovascularization, Pathologic; Oxidative Stress; Permeability; Phenotype; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Signal Transduction

Challenges of Francisella classification exemplified by an atypical clinical isolate. - Matz, L M; Kamdar, K Y; Holder, M E; Metcalf, G A; Weissenberger, G M; Meng, Q; Vee, V; Han, Y; Muzny, D M; Gibbs, R A; Johnson, C L; Revell, P A; et al. (Diagn Microbiol Infect Dis, 2018)
The accumulation of sequenced Francisella strains has made it increasingly apparent that the 16S rRNA gene alone is not enough to stratify the Francisella genus into precise and clinically useful classifications. Continued whole-genome sequencing of isolates will provide a larger base of knowledge for targeted approaches with broad applicability. Additionally, examination of genomic information on a case-by-case basis will help resolve outstanding questions regarding strain stratification. We report the complete genome sequence of a clinical isolate, designated here as F. novicida-like strain TCH2015, acquired from the lymph node of a 6-year-old male. Two features were atypical for F. novicida: exhibition of functional oxidase activity and additional gene content, including proposed virulence determinants. These differences, which could potentially impact virulence and clinical diagnosis, emphasize the need for more comprehensive methods to profile Francisella isolates. This study highlights the value of whole-genome sequencing, which will lead to a more robust database of environmental and clinical genomes and inform strategies to improve detection and classification of Francisella strains.
Keywords: Child; DNA, Bacterial; Francisella; Genes, Bacterial; Genetic Variation; Genome, Bacterial; Genotype; Humans; Lymph Nodes; Male; Oxidoreductases; Sequence Analysis, DNA; Tularemia; Virulence Factors; Whole Genome Sequencing

Characterization of Wild and Captive Baboon Gut Microbiota and Their Antibiotic Resistomes. - Tsukayama, Pablo; Boolchandani, Manish; Patel, Sanket; Pehrsson, Erica C; Gibson, Molly K; Chiou, Kenneth L; Jolly, Clifford J; Jeffrey Rogers; Phillips-Conroy, Jane E; Dantas, Gautam (mSystems, 2018)
Environmental microbes have harbored the capacity for antibiotic production for millions of years, spanning the evolution of humans and other vertebrates. However, the industrial-scale use of antibiotics in clinical and agricultural practice over the past century has led to a substantial increase in exposure of these agents to human and environmental microbiota. This perturbation is predicted to alter the ecology of microbial communities and to promote the evolution and transfer of antibiotic resistance (AR) genes. We studied wild and captive baboon populations to understand the effects of exposure to humans and human activities (e.g., antibiotic therapy) on the composition of the primate fecal microbiota and the antibiotic-resistant genes that it collectively harbors (the "resistome"). Using a culture-independent metagenomic approach, we identified functional antibiotic resistance genes in the gut microbiota of wild and captive baboon groups and saw marked variation in microbiota architecture and resistomes across habitats and lifeways. Our results support the view that antibiotic resistance is an ancient feature of gut microbial communities and that sharing habitats with humans may have important effects on the structure and function of the primate microbiota. Antibiotic exposure results in acute and persistent shifts in the composition and function of microbial communities associated with vertebrate hosts. However, little is known about the state of these communities in the era before the widespread introduction of antibiotics into clinical and agricultural practice. We characterized the fecal microbiota and antibiotic resistomes of wild and captive baboon populations to understand the effect of human exposure and to understand how the primate microbiota may have been altered during the antibiotic era. We used culture-independent and bioinformatics methods to identify functional resistance genes in the guts of wild and captive baboons and show that exposure to humans is associated with changes in microbiota composition and resistome expansion compared to wild baboon groups. Our results suggest that captivity and lifestyle changes associated with human contact can lead to marked changes in the ecology of primate gut communities.

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.
Keywords: Biophysical Phenomena; Electrocardiography; Genetic Association Studies; Haplotypes; Heart Conduction System; Humans; Ion Channel Gating; Mutation, Missense; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Comparison of vitamin D metabolites in wild and captive baboons. - Ziegler, Toni E; Kapoor, Amita; Binkley, Neil C; Rice, Karen S; Jeffrey Rogers; Jolly, Clifford J; Phillips-Conroy, Jane E (Am J Primatol, 2018)
Vitamin D adequacy is essential for multiple physiologic processes. With limited exposure to sunlight for vitamin D synthesis, captive primates are supplemented with vitamin D (cholecalciferol). Vitamin D metabolite data from wild primates living indigenously could suggest optimum levels. The purpose of this study was to: 1) to explore whether baboons, a speciose genus whose members have significant exposed skin, coat color variation and wide geographical distribution, mirrors the skin pigmentation-vitamin D relationship found in humans; 2) compare vitamin D metabolite levels in wild and captive members of the same or similar baboon species; and 3) apply a recently developed method currently used in humans for measuring multiple vitamin D metabolites as a panel to explore if/how these metabolites can inform us on vitamin D sufficiency. Serum samples from males of three baboon species in the wild: Papio anubis (olive baboon, dark exposed skin), P. cynocephalus (yellow baboon, brown exposed skin), and P. hamadryas (hamadryas baboon, pink exposed skin), were compared with vitamin D supplemented captive olive baboons with sun exposure. Liquid chromatography/tandem mass spectrometry (LC/MS/MS) measured vitamin D and its main metabolites. Cholecalciferol, 25 hydroxyvitamin D (25(OH)D ), and 24,25 dihydroxyvitamin D (24,25(OH) D ), showed significant differences by species. The levels of cholecalciferol due to supplements in the captive olive baboons did not convert to higher 25(OH)D while the wild olive baboons exhibited the lowest levels for both cholecalciferol and 25(OH)D . Further metabolic conversion of 25(OH)D to 24,25(OH) D indicated that all baboons had more similar conversion ratios and these were within the same range found for humans that are depicted as having adequate vitamin D levels. This study provided evidence that exposed skin color does influence vitamin D3 levels, with lower levels in darker skinned species, but these differences are eliminated in the downstream metabolite conversion indicating strong regulatory control.
Keywords: Africa South of the Sahara; Aging; Animal Distribution; Animals; Animals, Wild; Animals, Zoo; Dietary Supplements; Male; Papio; Skin Pigmentation; Species Specificity; Vitamin D; Vitamin D Deficiency

Comprehensive Characterization of Cancer Driver Genes and Mutations. - Bailey, Matthew H; Tokheim, Collin; Porta-Pardo, Eduard; Sengupta, Sohini; Bertrand, Denis; Weerasinghe, Amila; Colaprico, Antonio; Wendl, Michael C; Kim, Jaegil; Reardon, Brendan; Ng, Patrick Kwok-Shing; Jeong, Kang Jin; et al. (Cell, 2018)
Identifying molecular cancer drivers is critical for precision oncology. Multiple advanced algorithms to identify drivers now exist, but systematic attempts to combine and optimize them on large datasets are few. We report a PanCancer and PanSoftware analysis spanning 9,423 tumor exomes (comprising all 33 of The Cancer Genome Atlas projects) and using 26 computational tools to catalog driver genes and mutations. We identify 299 driver genes with implications regarding their anatomical sites and cancer/cell types. Sequence- and structure-based analyses identified >3,400 putative missense driver mutations supported by multiple lines of evidence. Experimental validation confirmed 60%-85% of predicted mutations as likely drivers. We found that >300 MSI tumors are associated with high PD-1/PD-L1, and 57% of tumors analyzed harbor putative clinically actionable events. Our study represents the most comprehensive discovery of cancer genes and mutations to date and will serve as a blueprint for future biological and clinical endeavors.
Keywords: Algorithms; B7-H1 Antigen; Computational Biology; Databases, Genetic; Entropy; Humans; Microsatellite Instability; Mutation; Neoplasms; Principal Component Analysis; Programmed Cell Death 1 Receptor

A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.
Keywords: Adolescent; Adult; Algorithms; Child; Child, Preschool; Comparative Genomic Hybridization; Democratic Republic of the Congo; Developmental Disabilities; Disease Management; Exome Sequencing; Facies; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Homeodomain Proteins; Humans; Infant; Intellectual Disability; Male; Phenotype; Syndrome; Transcription Factors; Trinucleotide Repeat Expansion; Trinucleotide Repeats; Workflow; X Chromosome Inactivation; Young Adult

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

DNA methylation age is associated with an altered hemostatic profile in a multiethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Everett, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases; however, much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we performed European and African ancestry-specific meta-analyses which were then combined via a random effects meta-analysis. For all other measures we could not estimate ancestry-specific effects and used a single fixed effects meta-analysis. We found that 1-year higher extrinsic epigenetic age as compared with chronological age was associated with higher fibrinogen (0.004 g/L/y; 95% confidence interval, 0.001-0.007; = .01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL/y; 95% confidence interval, 0.07-0.20; = 6.6 10) concentrations, as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms, we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene () and the 3 fibrinogen subunit-encoding genes (, , and ) in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a procoagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.
Keywords: Aging; DNA Methylation; Epigenesis, Genetic; Hemostasis; Humans

Earth BioGenome Project: Sequencing life for the future of life. - Lewin, Harris A; Robinson, Gene E; Kress, W John; Baker, William J; Coddington, Jonathan; Crandall, Keith A; Durbin, Richard; Edwards, Scott V; Forest, Félix; Gilbert, M Thomas P; Goldstein, Melissa M; Grigoriev, Igor V; et al. (Proc Natl Acad Sci U S A, 2018)
Increasing our understanding of Earth's biodiversity and responsibly stewarding its resources are among the most crucial scientific and social challenges of the new millennium. These challenges require fundamental new knowledge of the organization, evolution, functions, and interactions among millions of the planet's organisms. Herein, we present a perspective on the Earth BioGenome Project (EBP), a moonshot for biology that aims to sequence, catalog, and characterize the genomes of all of Earth's eukaryotic biodiversity over a period of 10 years. The outcomes of the EBP will inform a broad range of major issues facing humanity, such as the impact of climate change on biodiversity, the conservation of endangered species and ecosystems, and the preservation and enhancement of ecosystem services. We describe hurdles that the project faces, including data-sharing policies that ensure a permanent, freely available resource for future scientific discovery while respecting access and benefit sharing guidelines of the Nagoya Protocol. We also describe scientific and organizational challenges in executing such an ambitious project, and the structure proposed to achieve the project's goals. The far-reaching potential benefits of creating an open digital repository of genomic information for life on Earth can be realized only by a coordinated international effort.
Keywords: Biodiversity; Earth, Planet; Endangered Species; Genome; High-Throughput Nucleotide Sequencing

Elucidating the molecular pathogenesis of glioma: integrated germline and somatic profiling of a familial glioma case series. - Jacobs, Daniel I; Fukumura, Kazutaka; Bainbridge, Matthew N; Armstrong, Georgina N; Tsavachidis, Spiridon; Gu, Xiangjun; Harshavardhan Doddapaneni; Jianhong Hu; Jayaseelan, Joy C; Donna M Muzny; Huse, Jason T; Bondy, Melissa L (Neuro Oncol, 2018)
BACKGROUND: The genomic characterization of sporadically arising gliomas has delineated molecularly and clinically distinct subclasses of disease. However, less is known about the molecular nature of gliomas that are familial in origin. We performed molecular subtyping of 163 tumor specimens from individuals with a family history of glioma and integrated germline and somatic genomic data to characterize the pathogenesis of 20 tumors in additional detail. METHODS: Immunohistochemical analyses were performed on formalin-fixed, paraffin-embedded tumor sections to determine molecular subtypes of glioma. For 20 cases, tumor DNA was exome sequenced on an Illumina HiSeq 2000 platform and copy number profiling was performed on the Illumina HumanOmniExpress BeadChip. Genotypes at glioma risk polymorphisms were determined from germline DNA profiled on the Illumina Infinium OncoArray and deleterious germline mutations were identified from germline sequencing data. RESULTS: All 3 molecular subtypes of sporadic glioma were represented in the overall case series, including molecular glioblastoma (n = 102), oligodendroglioma (n = 21), and astrocytoma (n = 20). Detailed profiling of 20 of these cases showed characteristic subtype-specific alterations at frequencies comparable to sporadic glioma cases. All 20 cases had alterations in genes regulating telomere length. Frequencies of common glioma risk alleles were similar to those among sporadic cases, and correlations between risk alleles and same-gene somatic mutations were not observed. CONCLUSIONS: This study illustrates that the molecular characteristics of familial tumors profiled largely recapitulate what is known about sporadic glioma and that both germline and somatic molecular features target common core pathways involved in gliomagenesis. KEY POINTS: 1. Familial and sporadic gliomas display highly comparable molecular landscapes. 2. Germline and somatic molecular events target common core pathways involved in gliomagenesis. 3. Carriage of germline glioma risk variants is not associated with somatic events in the same gene.
Keywords: Adult; Biomarkers, Tumor; Brain Neoplasms; DNA Copy Number Variations; DNA, Neoplasm; Exome; Genetic Predisposition to Disease; Genomics; Germ-Line Mutation; Glioma; Humans; Middle Aged; Prognosis

Expansions of key protein families in the German cockroach highlight the molecular basis of its remarkable success as a global indoor pest. - Harrison, Mark C; Arning, Nicolas; Kremer, Lukas P M; Ylla, Guillem; Belles, Xavier; Bornberg-Bauer, Erich; Huylmans, Ann Kathrin; Jongepier, Evelien; Piulachs, Maria-Dolors; Richards, Stephen; Schal, Coby (J Exp Zool B Mol Dev Evol, 2018)
The German cockroach, Blattella germanica, is a worldwide pest that infests buildings, including homes, restaurants, and hospitals, often living in unsanitary conditions. As a disease vector and producer of allergens, this species has major health and economic impacts on humans. Factors contributing to the success of the German cockroach include its resistance to a broad range of insecticides, immunity to many pathogens, and its ability, as an extreme generalist omnivore, to survive on most food sources. The recently published genome shows that B. germanica has an exceptionally high number of protein coding genes. In this study, we investigate the functions of the 93 significantly expanded gene families with the aim to better understand the success of B. germanica as a major pest despite such inhospitable conditions. We find major expansions in gene families with functions related to the detoxification of insecticides and allelochemicals, defense against pathogens, digestion, sensory perception, and gene regulation. These expansions might have allowed B. germanica to develop multiple resistance mechanisms to insecticides and pathogens, and enabled a broad, flexible diet, thus explaining its success in unsanitary conditions and under recurrent chemical control. The findings and resources presented here provide insights for better understanding molecular mechanisms that will facilitate more effective cockroach control.
Keywords: Animals; Blattellidae; Diet; Evolution, Molecular; Genome, Insect; Inactivation, Metabolic; Insect Proteins; Insecticide Resistance; Multigene Family; Pest Control; Receptors, Cell Surface

Functional Annotation of ESR1 Gene Fusions in Estrogen Receptor-Positive Breast Cancer. - Lei, Jonathan T; Shao, Jieya; Zhang, Jin; Iglesia, Michael; Chan, Doug W; Cao, Jin; Anurag, Meenakshi; Singh, Purba; He, Xiaping; Kosaka, Yoshimasa; Matsunuma, Ryoichi; Crowder, Robert; et al. (Cell Rep, 2018)
RNA sequencing (RNA-seq) detects estrogen receptor alpha gene (ESR1) fusion transcripts in estrogen receptor-positive (ER) breast cancer, but their role in disease pathogenesis remains unclear. We examined multiple ESR1 fusions and found that two, both identified in advanced endocrine treatment-resistant disease, encoded stable and functional fusion proteins. In both examples, ESR1-e6>YAP1 and ESR1-e6>PCDH11X, ESR1 exons 1-6 were fused in frame to C-terminal sequences from the partner gene. Functional properties include estrogen-independent growth, constitutive expression of ER target genes, and anti-estrogen resistance. Both fusions activate a metastasis-associated transcriptional program, induce cellular motility, and promote the development of lung metastasis. ESR1-e6>YAP1- and ESR1-e6>PCDH11X-induced growth remained sensitive to a CDK4/6 inhibitor, and a patient-derived xenograft (PDX) naturally expressing the ESR1-e6>YAP1 fusion was also responsive. Transcriptionally active ESR1 fusions therefore trigger both endocrine therapy resistance and metastatic progression, explaining the association with fatal disease progression, although CDK4/6 inhibitor treatment is predicted to be effective.
Keywords: Breast Neoplasms; Estrogen Receptor alpha; Female; Gene Fusion; Humans; Transfection

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.
Keywords: Adult; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cells, Cultured; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genetics, Population; Genome-Wide Association Study; Human Umbilical Vein Endothelial Cells; Humans; Hypertension; Life Style; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Genetic and mechanistic diversity in pediatric hemophagocytic lymphohistiocytosis. - Chinn, Ivan K; Eckstein, Olive S; Peckham-Gregory, Erin C; Goldberg, Baruch R; Forbes, Lisa R; Nicholas, Sarah K; Mace, Emily M; Vogel, Tiphanie P; Abhyankar, Harshal A; Diaz, Maria I; Heslop, Helen E; Krance, Robert A; et al. (Blood, 2018)
The HLH-2004 criteria are used to diagnose hemophagocytic lymphohistiocytosis (HLH), yet concern exists for their misapplication, resulting in suboptimal treatment of some patients. We sought to define the genomic spectrum and associated outcomes of a diverse cohort of children who met the HLH-2004 criteria. Genetic testing was performed clinically or through research-based whole-exome sequencing. Clinical metrics were analyzed with respect to genomic results. Of 122 subjects enrolled over the course of 17 years, 101 subjects received genetic testing. Biallelic familial HLH (fHLH) gene defects were identified in only 19 (19%) and correlated with presentation at younger than 1 year of age ( < .0001). Digenic fHLH variants were observed but lacked statistical support for disease association. In 28 (58%) of 48 subjects, research whole-exome sequencing analyses successfully identified likely molecular explanations, including underlying primary immunodeficiency diseases, dysregulated immune activation and proliferation disorders, and potentially novel genetic conditions. Two-thirds of patients identified by the HLH-2004 criteria had underlying etiologies for HLH, including genetic defects, autoimmunity, and malignancy. Overall survival was 45%, and increased mortality correlated with HLH triggered by infection or malignancy ( < .05). Differences in survival did not correlate with genetic profile or extent of therapy. HLH should be conceptualized as a phenotype of critical illness characterized by toxic activation of immune cells from different underlying mechanisms. In most patients with HLH, targeted sequencing of fHLH genes remains insufficient for identifying pathogenic mechanisms. Whole-exome sequencing, however, may identify specific therapeutic opportunities and affect hematopoietic stem cell transplantation options for these patients.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Genetic Testing; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Lymphohistiocytosis, Hemophagocytic; Male; Multifactorial Inheritance

Genetic variants in microRNA genes and targets associated with cardiovascular disease risk factors in the African-American population. - Li, Chang; Grove, Megan L; Yu, Bing; Jones, Barbara C; Morrison, Alanna; Boerwinkle, Eric; Liu, Xiaoming (Hum Genet, 2018)
The purpose of this study is to identify microRNA (miRNA) related polymorphism, including single nucleotide variants (SNVs) in mature miRNA-encoding sequences or in miRNA-target sites, and their association with cardiovascular disease (CVD) risk factors in African-American population. To achieve our objective, we examined 1900 African-Americans from the Atherosclerosis Risk in Communities study using SNVs identified from whole-genome sequencing data. A total of 971 SNVs found in 726 different mature miRNA-encoding sequences and 16,057 SNVs found in the three prime untranslated region (3'UTR) of 3647 protein-coding genes were identified and interrogated their associations with 17 CVD risk factors. Using single-variant-based approach, we found 5 SNVs in miRNA-encoding sequences to be associated with serum Lipoprotein(a) [Lp(a)], high-density lipoprotein (HDL) or triglycerides, and 2 SNVs in miRNA-target sites to be associated with Lp(a) and HDL, all with false discovery rates of 5%. Using a gene-based approach, we identified 3 pairs of associations between gene NSD1 and platelet count, gene HSPA4L and cardiac troponin T, and gene AHSA2 and magnesium. We successfully validated the association between a variant specific to African-American population, NR_039880.1:n.18A>C, in mature hsa-miR-4727-5p encoding sequence and serum HDL level in an independent sample of 2135 African-Americans. Our study provided candidate miRNAs and their targets for further investigation of their potential contribution to ethnic disparities in CVD risk factors.
Keywords: 3' Untranslated Regions; Adult; Black or African American; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; MicroRNAs; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Whole Genome Sequencing

Genetic Variants Influencing Plasma Renin Activity in Hypertensive Patients From the PEAR Study (Pharmacogenomic Evaluation of Antihypertensive Responses). - McDonough, Caitrin W; Magvanjav, Oyunbileg; Sá, Ana C C; El Rouby, Nihal M; Dave, Chintan; Deitchman, Amelia N; Kawaguchi-Suzuki, Marina; Mei, Wenbin; Shen, Yong; Singh, Ravi Shankar Prasad; Solayman, Mohamed; Bailey, Kent R; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Plasma renin is an important regulator of blood pressure (BP). Plasma renin activity (PRA) has been shown to correlate with variability in BP response to antihypertensive agents. We conducted a genome-wide association study to identify single-nucleotide polymorphisms (SNPs) associated with baseline PRA using data from the PEAR study (Pharmacogenomic Evaluation of Antihypertensive Responses). METHODS: Multiple linear regression analysis was performed in 461 whites and 297 blacks using an additive model, adjusting for age, sex, and ancestry-specific principal components. Top SNPs were prioritized by testing the expected direction of association for BP response to atenolol and hydrochlorothiazide. Top regions from the BP response prioritization were tested for functional evidence through differences in gene expression by genotype using RNA sequencing data. Regions with functional evidence were assessed for replication with baseline PRA in an independent study (PEAR-2). RESULTS: Our top SNP rs3784921 was in the gene region. The G allele of rs3784921 was associated with higher baseline PRA (β=0.47; =2.09×10) and smaller systolic BP reduction in response to hydrochlorothiazide (β=2.97; 1-sided =0.006). In addition, expression differed by rs3784921 genotype (=0.007), and rs1802409, a proxy SNP for rs3784921 (=0.98-1.00), replicated in PEAR-2 (β=0.15; 1-sided =0.038). Additional SNPs associated with baseline PRA that passed BP response prioritization were in/near the genes and CONCLUSIONS: We identified multiple regions associated with baseline PRA that were prioritized through BP response signals to 2 mechanistically different antihypertensive drugs. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT00246519.
Keywords: Adolescent; Adult; Aged; Antihypertensive Agents; Atenolol; Blood Pressure; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Male; Middle Aged; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Prospective Studies; Renin; Treatment Outcome; United States; Young Adult

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Biomarkers; Bipolar Disorder; Body Mass Index; C-Reactive Protein; Child; Female; Genetic Loci; Genome-Wide Association Study; Humans; Inflammation; Liver; Male; Mendelian Randomization Analysis; Metabolic Networks and Pathways; Middle Aged; Schizophrenia; Young Adult

The genome of the water strider Gerris buenoi reveals expansions of gene repertoires associated with adaptations to life on the water. - Armisén, David; Rajakumar, Rajendhran; Friedrich, Markus; Benoit, Joshua B; Robertson, Hugh M; Panfilio, Kristen A; Ahn, Seung-Joon; Poelchau, Monica F; Chao, Hsu; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; et al. (BMC Genomics, 2018)
BACKGROUND: Having conquered water surfaces worldwide, the semi-aquatic bugs occupy ponds, streams, lakes, mangroves, and even open oceans. The diversity of this group has inspired a range of scientific studies from ecology and evolution to developmental genetics and hydrodynamics of fluid locomotion. However, the lack of a representative water strider genome hinders our ability to more thoroughly investigate the molecular mechanisms underlying the processes of adaptation and diversification within this group. RESULTS: Here we report the sequencing and manual annotation of the Gerris buenoi (G. buenoi) genome; the first water strider genome to be sequenced thus far. The size of the G. buenoi genome is approximately 1,000 Mb, and this sequencing effort has recovered 20,949 predicted protein-coding genes. Manual annotation uncovered a number of local (tandem and proximal) gene duplications and expansions of gene families known for their importance in a variety of processes associated with morphological and physiological adaptations to a water surface lifestyle. These expansions may affect key processes associated with growth, vision, desiccation resistance, detoxification, olfaction and epigenetic regulation. Strikingly, the G. buenoi genome contains three insulin receptors, suggesting key changes in the rewiring and function of the insulin pathway. Other genomic changes affecting with opsin genes may be associated with wavelength sensitivity shifts in opsins, which is likely to be key in facilitating specific adaptations in vision for diverse water habitats. CONCLUSIONS: Our findings suggest that local gene duplications might have played an important role during the evolution of water striders. Along with these findings, the sequencing of the G. buenoi genome now provides us the opportunity to pursue exciting research opportunities to further understand the genomic underpinnings of traits associated with the extreme body plan and life history of water striders.
Keywords: Adaptation, Physiological; Animals; Evolution, Molecular; Genome; Genomics; Heteroptera; Insect Proteins; Phenotype; Phylogeny

Genomic and Molecular Landscape of DNA Damage Repair Deficiency across The Cancer Genome Atlas. - Knijnenburg, Theo A; Wang, Linghua; Zimmermann, Michael T; Chambwe, Nyasha; Gao, Galen F; Cherniack, Andrew D; Fan, Huihui; Shen, Hui; Way, Gregory P; Greene, Casey S; Liu, Yuexin; Akbani, Rehan; et al. (Cell Rep, 2018)
DNA damage repair (DDR) pathways modulate cancer risk, progression, and therapeutic response. We systematically analyzed somatic alterations to provide a comprehensive view of DDR deficiency across 33 cancer types. Mutations with accompanying loss of heterozygosity were observed in over 1/3 of DDR genes, including TP53 and BRCA1/2. Other prevalent alterations included epigenetic silencing of the direct repair genes EXO5, MGMT, and ALKBH3 in ∼20% of samples. Homologous recombination deficiency (HRD) was present at varying frequency in many cancer types, most notably ovarian cancer. However, in contrast to ovarian cancer, HRD was associated with worse outcomes in several other cancers. Protein structure-based analyses allowed us to predict functional consequences of rare, recurrent DDR mutations. A new machine-learning-based classifier developed from gene expression data allowed us to identify alterations that phenocopy deleterious TP53 mutations. These frequent DDR gene alterations in many human cancers have functional consequences that may determine cancer progression and guide therapy.
Keywords: Cell Line, Tumor; DNA Damage; Gene Silencing; Genome, Human; Humans; Loss of Heterozygosity; Machine Learning; Mutation; Neoplasms; Recombinational DNA Repair; Tumor Suppressor Proteins

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Protein-Lysine 6-Oxidase; Quantitative Trait Loci; Risk Factors

Hemimetabolous genomes reveal molecular basis of termite eusociality. - Harrison, Mark C; Jongepier, Evelien; Robertson, Hugh M; Arning, Nicolas; Bitard-Feildel, Tristan; Chao, Hsu; Childers, Christopher P; Dinh, Huyen; Doddapaneni, Harshavardhan; Dugan, Shannon; Gowin, Johannes; Greiner, Carolin; et al. (Nat Ecol Evol, 2018)
Around 150 million years ago, eusocial termites evolved from within the cockroaches, 50 million years before eusocial Hymenoptera, such as bees and ants, appeared. Here, we report the 2-Gb genome of the German cockroach, Blattella germanica, and the 1.3-Gb genome of the drywood termite Cryptotermes secundus. We show evolutionary signatures of termite eusociality by comparing the genomes and transcriptomes of three termites and the cockroach against the background of 16 other eusocial and non-eusocial insects. Dramatic adaptive changes in genes underlying the production and perception of pheromones confirm the importance of chemical communication in the termites. These are accompanied by major changes in gene regulation and the molecular evolution of caste determination. Many of these results parallel molecular mechanisms of eusocial evolution in Hymenoptera. However, the specific solutions are remarkably different, thus revealing a striking case of convergence in one of the major evolutionary transitions in biological complexity.
Keywords: Animals; Biological Evolution; Blattellidae; Evolution, Molecular; Genome; Isoptera; Phylogeny; Social Behavior

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Gibbs, Richard A; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

Identification of a pathogenic PMP2 variant in a multi-generational family with CMT type 1: Clinical gene panels versus genome-wide approaches to molecular diagnosis. - Punetha, Jaya; Mackay-Loder, Loren; Harel, Tamar; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Richard A Gibbs; Lee, Ian; Terespolsky, Deborah; Lupski, James R; Posey, Jennifer E (Mol Genet Metab, 2018)
Charcot-Marie-Tooth (CMT) disease type 1 is an inherited peripheral neuropathy characterized by demyelination and reduced nerve conduction velocities. We present a multi-generational family with peripheral neuropathy in whom clinical CMT panel testing failed to conclude a molecular diagnosis. We found a PMP2 pathogenic variant c.155T > C, p.(Ile52Thr) that segregates with disease suggesting that PMP2 variants should be considered in patients with neuropathy and that it may be prudent to include in clinical CMT gene panels.
Keywords: Charcot-Marie-Tooth Disease; Demyelinating Diseases; Humans; Mutation; Myelin P2 Protein; Neural Conduction; Pathology, Molecular; Peripheral Nervous System Diseases

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Petty, Lauren E; Donna M Muzny; Below, Jennifer E; Eric Boerwinkle; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Kalinin; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Identifying Genes Whose Mutant Transcripts Cause Dominant Disease Traits by Potential Gain-of-Function Alleles. - Coban-Akdemir, Zeynep; White, Janson J; Song, Xiaofei; Jhangiani, Shalini N; Fatih, Jawid M; Gambin, Tomasz; Bayram, Yavuz; Chinn, Ivan K; Karaca, Ender; Punetha, Jaya; Poli, Cecilia; Eric Boerwinkle; et al. (Am J Hum Genet, 2018)
Premature termination codon (PTC)-bearing transcripts are often degraded by nonsense-mediated decay (NMD) resulting in loss-of-function (LoF) alleles. However, not all PTCs result in LoF mutations, i.e., some such transcripts escape NMD and are translated to truncated peptide products that result in disease due to gain-of-function (GoF) effects. Since the location of the PTC is a major factor determining transcript fate, we hypothesized that depletion of protein-truncating variants (PTVs) within the gene region predicted to escape NMD in control databases could provide a rank for genic susceptibility for disease through GoF versus LoF. We developed an NMD escape intolerance score to rank genes based on the depletion of PTVs that would render them able to escape NMD using the Atherosclerosis Risk in Communities Study (ARIC) and the Exome Aggregation Consortium (ExAC) control databases, which was further used to screen the Baylor-Center for Mendelian Genomics disease database. This analysis revealed 1,996 genes significantly depleted for PTVs that are predicted to escape from NMD, i.e., PTVesc; further studies provided evidence that revealed a subset as candidate genes underlying Mendelian phenotypes. Importantly, these genes have characteristically low pLI scores, which can cause them to be overlooked as candidates for dominant diseases. Collectively, we demonstrate that this NMD escape intolerance score is an effective and efficient tool for gene discovery in Mendelian diseases due to production of truncated or altered proteins. More importantly, we provide a complementary analytical tool to aid identification of genes associated with dominant traits through a mechanism distinct from LoF.
Keywords: Alleles; Codon, Nonsense; Databases, Genetic; Exome; Gain of Function Mutation; Humans; Mutation; Nonsense Mediated mRNA Decay; Phenotype

Integrated Molecular Characterization of Testicular Germ Cell Tumors. - Shen, Hui; Shih, Juliann; Hollern, Daniel P; Wang, Linghua; Bowlby, Reanne; Tickoo, Satish K; Thorsson, Vesteinn; Mungall, Andrew J; Newton, Yulia; Hegde, Apurva M; Armenia, Joshua; Sánchez-Vega, Francisco; et al. (Cell Rep, 2018)
We studied 137 primary testicular germ cell tumors (TGCTs) using high-dimensional assays of genomic, epigenomic, transcriptomic, and proteomic features. These tumors exhibited high aneuploidy and a paucity of somatic mutations. Somatic mutation of only three genes achieved significance-KIT, KRAS, and NRAS-exclusively in samples with seminoma components. Integrated analyses identified distinct molecular patterns that characterized the major recognized histologic subtypes of TGCT: seminoma, embryonal carcinoma, yolk sac tumor, and teratoma. Striking differences in global DNA methylation and microRNA expression between histology subtypes highlight a likely role of epigenomic processes in determining histologic fates in TGCTs. We also identified a subset of pure seminomas defined by KIT mutations, increased immune infiltration, globally demethylated DNA, and decreased KRAS copy number. We report potential biomarkers for risk stratification, such as miRNA specifically expressed in teratoma, and others with molecular diagnostic potential, such as CpH (CpA/CpC/CpT) methylation identifying embryonal carcinomas.
Keywords: DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Humans; Male; MicroRNAs; Neoplasms, Germ Cell and Embryonal; Proto-Oncogene Proteins c-kit; ras Proteins; Seminoma; Testicular Neoplasms

Investigating the disease association of USH2A p.C759F variant by leveraging large retinitis pigmentosa cohort data. - DuPont, Mariana; Jones, Evan M; Xu, Mingchu; Chen, Rui (Ophthalmic Genet, 2018)
Retinitis pigmentosa (RP) is an inherited retinal disease with a prevalence of 1/4,000. RP is highly genetically heterogeneous and there are over 80 genes associated with RP to date. One particular variant, p.C759F, has long been reported in RP cases but its pathogenicity was questioned by a recent study. Here, by leveraging large scale next-generation sequencing data from 982 non-Asian RP probands, we used binomial tests to evaluate the enrichment of this allele in RP cohort. We observed significant enrichment of this allele both in homozygous state and in compound heterozygous state with another protein-truncating allele. The results highlighted the clinical significance of the p.C759F allele in RP cases, which is important for accurate molecular diagnosis.
Keywords: Cohort Studies; Extracellular Matrix Proteins; Gene Frequency; Genetic Variation; Humans; Mutation; Retinitis Pigmentosa; RNA, Messenger

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.
Keywords: Atrial Fibrillation; Case-Control Studies; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Quantitative Trait Loci; Transcriptome

Mutation in the intracellular chloride channel CLCC1 associated with autosomal recessive retinitis pigmentosa. - Li, Lin; Jiao, Xiaodong; D'Atri, Ilaria; Ono, Fumihito; Nelson, Ralph; Chan, Chi-Chao; Nakaya, Naoki; Ma, Zhiwei; Ma, Yan; Cai, Xiaoying; Zhang, Longhua; Lin, Siying; et al. (PLoS Genet, 2018)
We identified a homozygous missense alteration (c.75C>A, p.D25E) in CLCC1, encoding a presumptive intracellular chloride channel highly expressed in the retina, associated with autosomal recessive retinitis pigmentosa (arRP) in eight consanguineous families of Pakistani descent. The p.D25E alteration decreased CLCC1 channel function accompanied by accumulation of mutant protein in granules within the ER lumen, while siRNA knockdown of CLCC1 mRNA induced apoptosis in cultured ARPE-19 cells. TALEN KO in zebrafish was lethal 11 days post fertilization. The depressed electroretinogram (ERG) cone response and cone spectral sensitivity of 5 dpf KO zebrafish and reduced eye size, retinal thickness, and expression of rod and cone opsins could be rescued by injection of wild type CLCC1 mRNA. Clcc1+/- KO mice showed decreased ERGs and photoreceptor number. Together these results strongly suggest that intracellular chloride transport by CLCC1 is a critical process in maintaining retinal integrity, and CLCC1 is crucial for survival and function of retinal cells.
Keywords: Animals; Asian People; Cell Line; Chloride Channels; Cytoplasm; Eye Proteins; HEK293 Cells; Homozygote; Humans; Mice; Mice, Knockout; Mutation, Missense; Pakistan; Retina; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Mutations in PI3K110δ cause impaired natural killer cell function partially rescued by rapamycin treatment. - Ruiz-García, Raquel; Vargas-Hernandez, Alexander; Chinn, Ivan K; Angelo, Laura S; Cao, Tram N; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Meng, Qingchang; Forbes, Lisa R; Muzny, Donna M; Allende, Luis M; Ehlayel, Mohammed S; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Heterozygous gain-of-function mutations in PI3K110δ lead to lymphadenopathy, lymphoid hyperplasia, EBV and cytomegalovirus viremia, and sinopulmonary infections. OBJECTIVE: The known role of natural killer (NK) cell function in the control of EBV and cytomegalovirus prompted us to investigate the functional and phenotypic effects of PI3K110δ mutations on NK cell subsets and cytotoxic function. METHODS: Mutations in patients were identified by using whole-exome or targeted sequencing. We performed NK cell phenotyping and functional analysis of patients' cells using flow cytometry, standard Cr cytotoxicity assays, and quantitative confocal microscopy. RESULTS: PI3K110δ mutations led to an altered NK cell developmental phenotype and cytotoxic dysfunction. Impaired NK cell cytotoxicity was due to decreased conjugate formation with susceptible target cells and abrogated activation of cell machinery required for target cell killing. These defects were restored partially after initiation of treatment with rapamycin in 3 patients. CONCLUSION: We describe novel NK cell functional deficiency caused by PI3K110δ mutation, which is a likely contributor to the severe viremia observed in these patients. Rapamycin treatment partially restores NK cell function, providing a further rationale for its use in patients with this disease.
Keywords: Cell Differentiation; Cells, Cultured; Class I Phosphatidylinositol 3-Kinases; Cytomegalovirus; Cytomegalovirus Infections; Cytotoxicity, Immunologic; Epstein-Barr Virus Infections; Exome Sequencing; Herpesvirus 4, Human; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunological Synapses; Immunophenotyping; Killer Cells, Natural; Lymphocyte Activation; Microscopy, Confocal; Mutation; Phosphatidylinositol 3-Kinases; Sirolimus; Viremia

Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency. - Chen, Anlu; Tiosano, Dov; Guran, Tulay; Baris, Hagit N; Bayram, Yavuz; Mory, Adi; Shapiro-Kulnane, Laura; Hodges, Craig A; Akdemir, Zeynep C; Turan, Serap; Jhangiani, Shalini N; van den Akker, Focco; et al. (Hum Mol Genet, 2018)
Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of POI in adolescents. Both missense mutations identified in MRPS22 are rare, occurred in highly evolutionarily conserved residues, and are predicted to be deleterious to protein function. In contrast to prior reports of mutations in MRPS22 associated with severe mitochondrial disease, the POI phenotype is far less severe. Consistent with this genotype-phenotype correlation, mitochondrial defects in oxidative phosphorylation or rRNA levels were not detected in fibroblasts derived from the POI patients, suggesting a non-bioenergetic or tissue-specific mitochondrial defect. Furthermore, we demonstrate in a Drosophila model that mRpS22 deficiency specifically in somatic cells of the ovary had no effect on fertility, whereas flies with mRpS22 deficiency specifically in germ cells were infertile and agametic, demonstrating a cell autonomous requirement for mRpS22 in germ cell development. These findings collectively identify that MRPS22, a component of the small mitochondrial ribosome subunit, is critical for ovarian development and may therefore provide insight into the pathophysiology and treatment of ovarian dysfunction.
Keywords: Adolescent; Adult; Amenorrhea; Animals; Disease Models, Animal; Drosophila; Drosophila Proteins; Female; Fertility; Homozygote; Humans; Menopause, Premature; Mitochondrial Proteins; Mutation, Missense; Ovarian Follicle; Primary Ovarian Insufficiency; Ribosomal Proteins; Young Adult

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Racial Groups; Young Adult

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

Perspective on Oncogenic Processes at the End of the Beginning of Cancer Genomics. - Ding, Li; Bailey, Matthew H; Porta-Pardo, Eduard; Thorsson, Vesteinn; Colaprico, Antonio; Bertrand, Denis; Gibbs, David L; Weerasinghe, Amila; Huang, Kuan-Lin; Tokheim, Collin; Cortés-Ciriano, Isidro; Jayasinghe, Reyka; et al. (Cell, 2018)
The Cancer Genome Atlas (TCGA) has catalyzed systematic characterization of diverse genomic alterations underlying human cancers. At this historic junction marking the completion of genomic characterization of over 11,000 tumors from 33 cancer types, we present our current understanding of the molecular processes governing oncogenesis. We illustrate our insights into cancer through synthesis of the findings of the TCGA PanCancer Atlas project on three facets of oncogenesis: (1) somatic driver mutations, germline pathogenic variants, and their interactions in the tumor; (2) the influence of the tumor genome and epigenome on transcriptome and proteome; and (3) the relationship between tumor and the microenvironment, including implications for drugs targeting driver events and immunotherapies. These results will anchor future characterization of rare and common tumor types, primary and relapsed tumors, and cancers across ancestry groups and will guide the deployment of clinical genomic sequencing.
Keywords: Carcinogenesis; Databases, Genetic; DNA Repair; Genes, Neoplasm; Genomics; Humans; Metabolic Networks and Pathways; Microsatellite Instability; Mutation; Neoplasms; Transcriptome; Tumor Microenvironment

Phenotype expansion and development in Kosaki overgrowth syndrome. - Gawliński, P; Pelc, M; Ciara, E; Jhangiani, S; Jurkiewicz, E; Gambin, T; Różdżyńska-Świątkowska, A; Dawidziuk, M; Coban-Akdemir, Z H; Guilbride, D L; Donna M Muzny; Lupski, J R; et al. (Clin Genet, 2018)
We expand the Kosaki overgrowth syndrome (KOGS) phenotype by over 70% to include 24 unreported KOGS symptoms, in a first male patient, the third overall associated with the PDGFRB c.1751C>G p.(Pro584Arg) mutation. Eighteen of these symptoms are unique to our patient, the remaining six are shared with other patients. Of the 24 unreported features overall, 6 show marked phenotype evolution and varying time of onset. The triangular face detected at 14 months and long palpebral fissures with lateral ectropion at 4 years are present in other members of the cohort. The remaining 4 are unique to Patient 5: pronounced macrocephaly from birth, increasingly triangular anterior skull from 14 months, camptodactyly, emerging at 4 years and worsening joint contractures from 6 years. Compilation of all new symptoms reported here with published clinical data further identifies at least 18 clinical parameters common to all cases to date, encompassing both known KOGS-associated PDGFRB mutations. We therefore propose a set of 18 core KOGS symptoms, with 16 present in early childhood. These results should also impact diagnostic/prognostic scope, intervention and outcome potential for KOGS patients, particularly for developmentally progressive conditions such as scoliosis and myofibroma.
Keywords: Adolescent; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Megalencephaly; Musculoskeletal Abnormalities; Mutation; Phenotype; Receptor, Platelet-Derived Growth Factor beta

Phenotypic expansion illuminates multilocus pathogenic variation. - Karaca, Ender; Posey, Jennifer E; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini N; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gozde; et al. (Genet Med, 2018)
PURPOSE: Multilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. METHODS: Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. RESULTS: Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. CONCLUSION: Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype-phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.
Keywords: Child, Preschool; Exome; Exome Sequencing; Female; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Variation; Genotype; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Pathology, Molecular; Pedigree; Phenotype

Phenotypic expansion in - a common cause of intellectual disability in females. - Wang, Xia; Posey, Jennifer E; Rosenfeld, Jill A; Bacino, Carlos A; Scaglia, Fernando; Immken, Ladonna; Harris, Jill M; Hickey, Scott E; Mosher, Theresa M; Slavotinek, Anne; Zhang, Jing; Beuten, Joke; et al. (Ann Clin Transl Neurol, 2018)
De variants in account for 1-3% of unexplained intellectual disability (ID) cases and are amongst the most common causes of ID especially in females. Forty-seven patients (44 females, 3 males) have been described. We identified 31 additional individuals carrying 29 unique variants, including 30 postnatal individuals with complex clinical presentations of developmental delay or ID, and one fetus with abnormal ultrasound findings. Rare or novel phenotypes observed include respiratory problems, congenital heart disease, skeletal muscle mitochondrial DNA depletion, and late-onset neurologic decline. Our findings expand the spectrum of DNA variants and phenotypes associated with disorders.

The phenotypic spectrum of Xia-Gibbs syndrome. - Jiang, Yunyun; Wangler, Michael F; McGuire, Amy L; Lupski, James R; Posey, Jennifer E; Khayat, Michael M; Murdock, David R; Sanchez-Pulido, Luis; Ponting, Chris P; Xia, Fan; Hunter, Jill V; Meng, Qingchang; et al. (Am J Med Genet A, 2018)
Xia-Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT-Hook DNA Binding Motif Containing 1 gene (AHDC1). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.
Keywords: Autism Spectrum Disorder; Child; Cognition; Corpus Callosum; Developmental Disabilities; DNA-Binding Proteins; Face; Female; Humans; Male; Mutation; Pedigree; Phenotype; Registries; Seizures; Syndrome; Young Adult

Pigmentary Maculopathy Associated with Chronic Exposure to Pentosan Polysulfate Sodium. - Pearce, William A; Rui Chen; Jain, Nieraj (Ophthalmology, 2018)
PURPOSE: To describe the clinical features of a unique pigmentary maculopathy noted in the setting of chronic exposure to pentosan polysulfate sodium (PPS), a therapy for interstitial cystitis (IC). DESIGN: Retrospective case series. PARTICIPANTS: Six adult patients evaluated by a single clinician between May 1, 2015, and October 1, 2017. METHODS: Patients were identified by query of the electronic medical record system. Local records were reviewed, including results of the clinical examination, retinal imaging, and visual function assessment with static perimetry and electroretinography. Molecular testing assessed for known macular dystrophy and mitochondrial cytopathy genotypes. MAIN OUTCOME MEASURES: Mean best-corrected visual acuity (BCVA; in logarithm of the minimum angle of resolution units), median cumulative PPS exposure, subjective nature of the associated visual disturbance, qualitative examination and imaging features, and molecular testing results. RESULTS: The median age at presentation was 60 years (range, 37-62 years). All patients received PPS for a diagnosis of IC, with a median cumulative exposure of 2263 g (range, 1314-2774 g), over a median duration of exposure of 186 months (range, 144-240 months). Most patients (4 of 6) reported difficulty reading as the most bothersome symptom. Mean BCVA was 0.1±0.18 logarithm of the minimum angle of resolution. On fundus examination, nearly all eyes showed subtle paracentral hyperpigmentation at the level of the retinal pigment epithelium (RPE) with a surrounding array of vitelliform-like deposits. Four eyes of 2 patients showed paracentral RPE atrophy, and no eyes demonstrated choroidal neovascularization. Multimodal retinal imaging demonstrated abnormality of the RPE generally contained in a well-delineated area in the posterior pole. None of the 4 patients who underwent molecular testing of nuclear DNA returned a pathogenic mutation. Additionally, all 6 patients showed negative results for pathogenic variants in the mitochondrial gene MTTL1. CONCLUSIONS: We describe a novel and possibly avoidable maculopathy associated with chronic exposure to PPS. Patients reported symptoms of difficulty reading and prolonged dark adaptation despite generally intact visual acuity and subtle funduscopic findings. Multimodal imaging and functional studies are suggestive of a primary RPE injury. Additional investigation is warranted to explore causality further.
Keywords: Adult; Anticoagulants; Cystitis, Interstitial; Dyslexia; Electroretinography; Female; Fluorescein Angiography; Genetic Testing; High-Throughput Nucleotide Sequencing; Humans; Middle Aged; Multimodal Imaging; Pentosan Sulfuric Polyester; Retinal Pigment Epithelium; Retinitis Pigmentosa; Retrospective Studies; Tomography, Optical Coherence; Vision Disorders; Visual Acuity

Prioritization of Candidate Genes for Congenital Diaphragmatic Hernia in a Critical Region on Chromosome 4p16 using a Machine-Learning Algorithm. - Callaway, Danielle A; Campbell, Ian M; Stover, Samantha R; Hernandez-Garcia, Andres; Jhangiani, Shalini N; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Donna M Muzny; Lally, Kevin P; James R Lupski; Shaw, Chad A; et al. (J Pediatr Genet, 2018)
Wolf-Hirschhorn syndrome (WHS) is caused by partial deletion of the short arm of chromosome 4 and is characterized by dysmorphic facies, congenital heart defects, intellectual/developmental disability, and increased risk for congenital diaphragmatic hernia (CDH). In this report, we describe a stillborn girl with WHS and a large CDH. A literature review revealed 15 cases of WHS with CDH, which overlap a 2.3-Mb CDH critical region. We applied a machine-learning algorithm that integrates large-scale genomic knowledge to genes within the 4p16.3 CDH critical region and identified , , , , , , , and as genes whose haploinsufficiency may contribute to the development of CDH.

Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
Genome-wide association studies (GWAS) have identified >250 loci for body mass index (BMI), implicating pathways related to neuronal biology. Most GWAS loci represent clusters of common, noncoding variants from which pinpointing causal genes remains challenging. Here we combined data from 718,734 individuals to discover rare and low-frequency (minor allele frequency (MAF) < 5%) coding variants associated with BMI. We identified 14 coding variants in 13 genes, of which 8 variants were in genes (ZBTB7B, ACHE, RAPGEF3, RAB21, ZFHX3, ENTPD6, ZFR2 and ZNF169) newly implicated in human obesity, 2 variants were in genes (MC4R and KSR2) previously observed to be mutated in extreme obesity and 2 variants were in GIPR. The effect sizes of rare variants are ~10 times larger than those of common variants, with the largest effect observed in carriers of an MC4R mutation introducing a stop codon (p.Tyr35Ter, MAF = 0.01%), who weighed ~7 kg more than non-carriers. Pathway analyses based on the variants associated with BMI confirm enrichment of neuronal genes and provide new evidence for adipocyte and energy expenditure biology, widening the potential of genetically supported therapeutic targets in obesity.
Keywords: Adult; Animals; Body Mass Index; Drosophila; Energy Intake; Energy Metabolism; Female; Gene Frequency; Genetic Variation; Humans; Male; Obesity; Proteins; Syndrome

A proteomic landscape of diffuse-type gastric cancer. - Ge, Sai; Xia, Xia; Ding, Chen; Zhen, Bei; Zhou, Quan; Feng, Jinwen; Yuan, Jiajia; Chen, Rui; Li, Yumei; Ge, Zhongqi; Ji, Jiafu; Zhang, Lianhai; et al. (Nat Commun, 2018)
The diffuse-type gastric cancer (DGC) is a subtype of gastric cancer with the worst prognosis and few treatment options. Here we present a dataset from 84 DGC patients, composed of a proteome of 11,340 gene products and mutation information of 274 cancer driver genes covering paired tumor and nearby tissue. DGC can be classified into three subtypes (PX1-3) based on the altered proteome alone. PX1 and PX2 exhibit dysregulation in the cell cycle and PX2 features an additional EMT process; PX3 is enriched in immune response proteins, has the worst survival, and is insensitive to chemotherapy. Data analysis revealed four major vulnerabilities in DGC that may be targeted for treatment, and allowed the nomination of potential immunotherapy targets for DGC patients, particularly for those in PX3. This dataset provides a rich resource for information and knowledge mining toward altered signaling pathways in DGC and demonstrates the benefit of proteomic analysis in cancer molecular subtyping.
Keywords: Chemoradiotherapy, Adjuvant; Datasets as Topic; DNA Mutational Analysis; Down-Regulation; Exome; Follow-Up Studies; Gastrectomy; Genes, Neoplasm; Humans; Immunohistochemistry; Mutation; Neoadjuvant Therapy; Neoplasm Proteins; Neoplasm Staging; Oligonucleotide Array Sequence Analysis; Prognosis; Proteomics; Sequence Analysis, DNA; Signal Transduction; Stomach; Stomach Neoplasms; Survival Analysis; Tandem Mass Spectrometry; Up-Regulation

Publisher Correction: Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
In the version of this article originally published, the name of author Martin H. de Borst was coded incorrectly in the XML. The error has now been corrected in the HTML version of the paper.

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
In the version of this article originally published, one of the two authors with the name Wei Zhao was omitted from the author list and the affiliations for both authors were assigned to the single Wei Zhao in the author list. In addition, the ORCID for Wei Zhao (Department of Biostatistics and Epidemiology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA) was incorrectly assigned to author Wei Zhou. The errors have been corrected in the HTML and PDF versions of the article.

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
In the published version of this paper, the name of author Emanuele Di Angelantonio was misspelled. This error has now been corrected in the HTML and PDF versions of the article.

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.
Keywords: Alleles; Chromosome Mapping; Diabetes Mellitus, Type 2; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; White People

The Return of Actionable Variants Empirical (RAVE) Study, a Mayo Clinic Genomic Medicine Implementation Study: Design and Initial Results. - Kullo, Iftikhar J; Olson, Janet; Fan, Xiao; Jose, Merin; Safarova, Maya; Radecki Breitkopf, Carmen; Winkler, Erin; Kochan, David C; Snipes, Sara; Pacyna, Joel E; Carney, Meaghan; Chute, Christopher G; et al. (Mayo Clin Proc, 2018)
OBJECTIVES: To identify clinically actionable genetic variants from targeted sequencing of 68 disease-related genes, estimate their penetrance, and assess the impact of disclosing results to participants and providers. PATIENTS AND METHODS: The Return of Actionable Variants Empirical (RAVE) Study investigates outcomes following the return of pathogenic/likely pathogenic (P/LP) variants in 68 disease-related genes. The study was initiated in December 2016 and is ongoing. Targeted sequencing was performed in 2533 individuals with hyperlipidemia or colon polyps. The electronic health records (EHRs) of participants carrying P/LP variants in 36 cardiovascular disease (CVD) genes were manually reviewed to ascertain the presence of relevant traits. Clinical outcomes, health care utilization, family communication, and ethical and psychosocial implications of disclosure of genomic results are being assessed by surveys, telephone interviews, and EHR review. RESULTS: Of 29,208 variants in the 68 genes, 1915 were rare (frequency <1%) and putatively functional, and 102 of these (60 in 36 CVD genes) were labeled P/LP based on the American College of Medical Genetics and Genomics framework. Manual review of the EHRs of participants (n=73 with P/LP variants in CVD genes) revealed that 33 had the expected trait(s); however, only 6 of 45 participants with non-familial hypercholesterolemia (FH) P/LP variants had the expected traits. CONCLUSION: Expected traits were present in 13% of participants with P/LP variants in non-FH CVD genes, suggesting low penetrance; this estimate may change with additional testing performed as part of the clinical evaluation. Ongoing analyses of the RAVE Study will inform best practices for genomic medicine.
Keywords: Cardiovascular Diseases; Cohort Studies; Colon; Female; Genetic Predisposition to Disease; Genetic Testing; Genomics; Humans; Hyperlipidemias; Male; Middle Aged; Outcome Assessment, Health Care; Phenotype; Polymorphism, Single Nucleotide; Polyps; Surveys and Questionnaires

Rho Guanine Nucleotide Exchange Factor Is a Risk Gene for Intracranial Aneurysms. - Yang, Xinyu; Li, Jiani; Fang, Yabo; Zhang, Zhen; Jin, Daqing; Chen, Xingdong; Zhao, Yan; Li, Mengqi; Huan, Linchun; Kent, Thomas A; Dong, Jing-fei; Jiang, Rongcai; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Intracranial aneurysm (IA) is usually a late-onset disease, affecting 1% to 3% of the general population and leading to life-threatening subarachnoid hemorrhage. Genetic susceptibility has been implicated in IAs, but the causative genes remain elusive. METHODS: We performed next-generation sequencing in a discovery cohort of 20 Chinese IA patients. Bioinformatics filters were exploited to search for candidate deleterious variants with rare and low allele frequency. We further examined the candidate variants in a multiethnic sample collection of 86 whole exome sequenced unsolved familial IA cases from 3 previously published studies. RESULTS: We identified that the low-frequency variant c.4394C>A_p.Ala1465Asp (rs2298808) of was significantly associated with IA in our Chinese discovery cohort (=7.3×10; odds ratio=7.34). It was subsequently replicated in Japanese familial IA patients (=0.039; odds ratio=4.00; 95% confidence interval=0.832-14.8) and was associated with IA in the large Chinese sample collection comprising 832 sporadic IA-affected and 599 control individuals (=0.041; odds ratio=1.51; 95% confidence interval=1.02-Inf). When combining the sequencing data of all familial IA patients from 4 different ethnicities (ie, Chinese, Japanese, European American, and French-Canadian), we identified a significantly increased mutation burden for (21/106 versus 11/306; =8.1×10; odds ratio=6.6; 95% confidence interval=2.9-15.8) in cases as compared with controls. In zebrafish, was highly expressed in the brain blood vessel. knockdown caused blood extravasation in the brain region. Endothelial lesions were identified exclusively on cerebral blood vessels in the -deficient zebrafish. CONCLUSIONS: Our results provide compelling evidence that is a risk gene for IA.
Keywords: Adult; Alleles; Canada; Cohort Studies; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Intracranial Aneurysm; Male; Middle Aged; Rho Guanine Nucleotide Exchange Factors; Risk Factors; Subarachnoid Hemorrhage

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Sheep genome functional annotation reveals proximal regulatory elements contributed to the evolution of modern breeds. - Naval-Sanchez, Marina; Nguyen, Quan; McWilliam, Sean; Porto-Neto, Laercio R; Tellam, Ross; Vuocolo, Tony; Reverter, Antonio; Perez-Enciso, Miguel; Brauning, Rudiger; Clarke, Shannon; McCulloch, Alan; Zamani, Wahid; et al. (Nat Commun, 2018)
Domestication fundamentally reshaped animal morphology, physiology and behaviour, offering the opportunity to investigate the molecular processes driving evolutionary change. Here we assess sheep domestication and artificial selection by comparing genome sequence from 43 modern breeds (Ovis aries) and their Asian mouflon ancestor (O. orientalis) to identify selection sweeps. Next, we provide a comparative functional annotation of the sheep genome, validated using experimental ChIP-Seq of sheep tissue. Using these annotations, we evaluate the impact of selection and domestication on regulatory sequences and find that sweeps are significantly enriched for protein coding genes, proximal regulatory elements of genes and genome features associated with active transcription. Finally, we find individual sites displaying strong allele frequency divergence are enriched for the same regulatory features. Our data demonstrate that remodelling of gene expression is likely to have been one of the evolutionary forces that drove phenotypic diversification of this common livestock species.
Keywords: Animals; Breeding; Evolution, Molecular; Female; Gene Frequency; Genome; Male; Molecular Sequence Annotation; Phylogeny; Regulatory Elements, Transcriptional; Sheep

Sooty mangabey genome sequence provides insight into AIDS resistance in a natural SIV host. - Palesch, David; Bosinger, Steven E; Tharp, Gregory K; Vanderford, Thomas H; Paiardini, Mirko; Chahroudi, Ann; Johnson, Zachary P; Kirchhoff, Frank; Hahn, Beatrice H; Norgren, Robert B; Patel, Nirav B; Sodora, Donald L; et al. (Nature, 2018)
In contrast to infections with human immunodeficiency virus (HIV) in humans and simian immunodeficiency virus (SIV) in macaques, SIV infection of a natural host, sooty mangabeys (Cercocebus atys), is non-pathogenic despite high viraemia. Here we sequenced and assembled the genome of a captive sooty mangabey. We conducted genome-wide comparative analyses of transcript assemblies from C. atys and AIDS-susceptible species, such as humans and macaques, to identify candidates for host genetic factors that influence susceptibility. We identified several immune-related genes in the genome of C. atys that show substantial sequence divergence from macaques or humans. One of these sequence divergences, a C-terminal frameshift in the toll-like receptor-4 (TLR4) gene of C. atys, is associated with a blunted in vitro response to TLR-4 ligands. In addition, we found a major structural change in exons 3-4 of the immune-regulatory protein intercellular adhesion molecule 2 (ICAM-2); expression of this variant leads to reduced cell surface expression of ICAM-2. These data provide a resource for comparative genomic studies of HIV and/or SIV pathogenesis and may help to elucidate the mechanisms by which SIV-infected sooty mangabeys avoid AIDS.
Keywords: Acquired Immunodeficiency Syndrome; Amino Acid Sequence; Animals; Cell Adhesion Molecules; Cercocebus atys; Exons; Female; Frameshift Mutation; Genetic Predisposition to Disease; Genetic Variation; Genome; Genomics; HIV; Host Specificity; Humans; Macaca; Sequence Deletion; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Species Specificity; Toll-Like Receptor 4; Transcriptome; Whole Genome Sequencing

SPATA7 maintains a novel photoreceptor-specific zone in the distal connecting cilium. - Dharmat, Rachayata; Eblimit, Aiden; Robichaux, Michael A; Zhang, Zhixian; Nguyen, Thanh-Minh T; Jung, Sung Yun; He, Feng; Jain, Antrix; Li, Yumei; Qin, Jun; Overbeek, Paul; Roepman, Ronald; et al. (J Cell Biol, 2018)
Photoreceptor-specific ciliopathies often affect a structure that is considered functionally homologous to the ciliary transition zone (TZ) called the connecting cilium (CC). However, it is unclear how mutations in certain ciliary genes disrupt the photoreceptor CC without impacting the primary cilia systemically. By applying stochastic optical reconstruction microscopy technology in different genetic models, we show that the CC can be partitioned into two regions: the proximal CC (PCC), which is homologous to the TZ of primary cilia, and the distal CC (DCC), a photoreceptor-specific extension of the ciliary TZ. This specialized distal zone of the CC in photoreceptors is maintained by SPATA7, which interacts with other photoreceptor-specific ciliary proteins such as RPGR and RPGRIP1. The absence of results in the mislocalization of DCC proteins without affecting the PCC protein complexes. This collapse results in destabilization of the axonemal microtubules, which consequently results in photoreceptor degeneration. These data provide a novel mechanism to explain how genetic disruption of ubiquitously present ciliary proteins exerts tissue-specific ciliopathy phenotypes.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Antigens, Neoplasm; Carrier Proteins; Cell Cycle Proteins; Cytoskeletal Proteins; DNA-Binding Proteins; Eye Proteins; Mice; Mice, Inbred C57BL; Nuclear Proteins; Photoreceptor Connecting Cilium; Protein Transport

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Genetic Loci; Genetic Predisposition to Disease; Humans; Mental Disorders; Middle Aged; Multifactorial Inheritance; Neurodegenerative Diseases; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Reaction Time; Young Adult

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.
Keywords: Action Potentials; Adolescent; Animals; Calcium; Child; Child, Preschool; Electrophysiological Phenomena; Endocytosis; Female; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Movement Disorders; Mutation, Missense; Neurodevelopmental Disorders; Neurons; Rats; Synaptic Transmission; Synaptic Vesicles; Synaptotagmin I; Young Adult

Targeted sequencing identifies a missense variant in the BEST3 gene associated with antihypertensive response to hydrochlorothiazide. - Singh, Sonal; Wang, Zhiying; Shahin, Mohamed H; Langaee, Taimour Y; Gong, Yan; Turner, Stephen T; Chapman, Arlene B; Gums, John G; McDonough, Caitrin W; Bailey, Kent R; Beitelshees, Amber L; Cooper-Dehoff, Rhonda M; et al. (Pharmacogenet Genomics, 2018)
Chromosome 12q15 was identified in Genetic Epidemiology of Response Assessment (GERA) and replicated in Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) for its association with blood pressure (BP) response to hydrochlorothiazide (HCTZ). However, the functional variant is unknown and we aimed to identify the likely functional variants through targeted sequencing. The chromosome 12q15 region was sequenced in 397 best and worst responders to HCTZ in PEAR (N=199) and GERA (N=198) hypertensive study participants. Logistic regression was used for the association analysis adjusting for age, sex, race, and principal components 1 and 2. For validation, the significant single nucleotide polymorphism was tested for association with the change in systolic (ΔSBP) and diastolic BP (ΔDBP) post-treatment in the entire PEAR (N=370) and GERA (N=570) cohorts. A novel missense polymorphism (G>A, Pro383Leu) in BEST3, rs61747221, was significantly associated with better HCTZ response (P=0.0021, odds ratio=2.05). It was validated in the entire cohort of PEAR (ΔSBP: P=0.021, β=-1.60, ΔDBP: P=0.023, β=-1.08) and GERA (ΔSBP: P=0.028, β=-1.95, ΔDBP: P=0.032, β=-1.28). BEST3 encodes the calcium sensitive chloride channel in the vascular smooth muscle implicated in the regulation of BP, especially in response to vasoconstrictors like angiotensin II. These results suggest that BEST3 is involved in the chronic BP lowering mechanism of thiazides and highlight its importance as a genetic predictor of the BP response to thiazide diuretics.
Keywords: Adult; Angiotensin II; Antihypertensive Agents; Atenolol; Bestrophins; Blood Pressure; Female; Genetic Association Studies; Humans; Hypertension; Male; Middle Aged; Muscle Proteins; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors

The Toxicogenome of Hyalella azteca: A Model for Sediment Ecotoxicology and Evolutionary Toxicology. - Poynton, Helen C; Hasenbein, Simone; Benoit, Joshua B; Sepulveda, Maria S; Poelchau, Monica F; Hughes, Daniel S T; Murali, Shwetha C; Chen, Shuai; Glastad, Karl M; Goodisman, Michael A D; Werren, John H; Vineis, Joseph H; et al. (Environ Sci Technol, 2018)
Hyalella azteca is a cryptic species complex of epibenthic amphipods of interest to ecotoxicology and evolutionary biology. It is the primary crustacean used in North America for sediment toxicity testing and an emerging model for molecular ecotoxicology. To provide molecular resources for sediment quality assessments and evolutionary studies, we sequenced, assembled, and annotated the genome of the H. azteca U.S. Lab Strain. The genome quality and completeness is comparable with other ecotoxicological model species. Through targeted investigation and use of gene expression data sets of H. azteca exposed to pesticides, metals, and other emerging contaminants, we annotated and characterized the major gene families involved in sequestration, detoxification, oxidative stress, and toxicant response. Our results revealed gene loss related to light sensing, but a large expansion in chemoreceptors, likely underlying sensory shifts necessary in their low light habitats. Gene family expansions were also noted for cytochrome P450 genes, cuticle proteins, ion transporters, and include recent gene duplications in the metal sequestration protein, metallothionein. Mapping of differentially expressed transcripts to the genome significantly increased the ability to functionally annotate toxicant responsive genes. The H. azteca genome will greatly facilitate development of genomic tools for environmental assessments and promote an understanding of how evolution shapes toxicological pathways with implications for environmental and human health.
Keywords: Amphipoda; Animals; Ecotoxicology; Geologic Sediments; North America; Toxicity Tests; Water Pollutants, Chemical

The transcription factor POU3F2 regulates a gene coexpression network in brain tissue from patients with psychiatric disorders. - Chen, Chao; Meng, Qingtuan; Xia, Yan; Ding, Chaodong; Wang, Le; Dai, Rujia; Cheng, Lijun; Gunaratne, Preethi; Richard A Gibbs; Min, Shishi; Coarfa, Cristian; Reid, Jeffrey G; et al. (Sci Transl Med, 2018)
Schizophrenia and bipolar disorder are complex psychiatric diseases with risks contributed by multiple genes. Dysregulation of gene expression has been implicated in these disorders, but little is known about such dysregulation in the human brain. We analyzed three transcriptome datasets from 394 postmortem brain tissue samples from patients with schizophrenia or bipolar disorder or from healthy control individuals without a known history of psychiatric disease. We built genome-wide coexpression networks that included microRNAs (miRNAs). We identified a coexpression network module that was differentially expressed in the brain tissue from patients compared to healthy control individuals. This module contained genes that were principally involved in glial and neural cell genesis and glial cell differentiation, and included schizophrenia risk genes carrying rare variants. This module included five miRNAs and 545 mRNAs, with six transcription factors serving as hub genes in this module. We found that the most connected transcription factor gene , also identified on a genome-wide association study for bipolar disorder, could regulate the miRNA and other putative target mRNAs. These regulatory relationships were replicated using PsychENCODE/BrainGVEX datasets and validated by knockdown and overexpression experiments in SH-SY5Y cells and human neural progenitor cells in vitro. Thus, we identified a brain gene expression module that was enriched for rare coding variants in genes associated with schizophrenia and that contained the putative bipolar disorder risk gene The transcription factor may be a key regulator of gene expression in this disease-associated gene coexpression module.
Keywords: Brain; Cell Differentiation; Cell Proliferation; Databases, Genetic; Gene Expression Regulation; Gene Regulatory Networks; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Mental Disorders; Neural Stem Cells; Postmortem Changes; POU Domain Factors; Reproducibility of Results; RNA, Messenger

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

Whole-Exome Sequencing Identifies an Intronic Cryptic Splice Site in Causing Osteogenesis Imperfecta Type VI. - Jin, Zixue; Burrage, Lindsay C; Jiang, Ming-Ming; Lee, Yi-Chien; Bertin, Terry; Chen, Yuqing; Tran, Alyssa; Richard A Gibbs; Jhangiani, Shalini; Sutton, V Reid; Rauch, Frank; Lee, Brendan; et al. (JBMR Plus, 2018)
The heritable disorder osteogenesis imperfecta (OI) is characterized by bone fragility and low bone mass. OI type VI is an autosomal recessive form of the disorder with moderate to severe bone fragility. OI type VI is caused by mutations in the serpin peptidase inhibitor, clade F, member 1 (), the gene coding for pigment epithelium-derived factor (PEDF). Here, we report a patient with OI type VI caused by a novel homozygous intronic variant in identified by whole-exome sequencing (WES). The mutation was not identified using a low bone mass gene panel based on next-generation sequencing. This variant creates a novel consensus splice donor site (AGGC to AGGT) in intron 4. Analysis of cDNA generated from fibroblasts revealed retention of a 32-bp intronic fragment between exons 4 and 5 in the cDNA, a result of alternative splicing from the novel splice-donor site. As a result, the aberrant insertion of this intronic fragment generated a frameshift pathogenic variant and induced nonsense-mediated decay. Furthermore, gene expression by quantitative PCR showed expression was dramatically reduced in patient fibroblasts, and PEDF level was also significantly reduced in the patient's plasma. In conclusion, we report a novel homozygous variant that generates an alternative splice-donor in intron 4 of which gives rise to severe bone fragility. The work also demonstrates clinical utility of WES analysis, and consideration of noncoding variants, in the diagnostic setting of rare bone diseases. © 2018 The Authors. is published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Doddapaneni, H; Hu, J; Muzny, D M; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Exome Sequencing; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Wnt Proteins

Whole-exome sequencing revealed HKDC1 as a candidate gene associated with autosomal-recessive retinitis pigmentosa. - Zhang, Lin; Sun, Zixi; Zhao, Peiquan; Huang, Lulin; Xu, Mingchu; Yang, Yeming; Chen, Xue; Lu, Fang; Zhang, Xiang; Wang, Hui; Zhang, Shanshan; Liu, Wenjing; et al. (Hum Mol Genet, 2018)
Retinitis pigmentosa (RP) is an inheritable retina degenerative disease leading to blindness. Despite the identification of 70 genes associated with RP, the genetic cause of ∼40% of RP patients remains to be elucidated. Whole-exome sequencing was applied on the probands of a RP cohort of 68 unsolved cases to identify candidate genetic mutations. A homozygous missense variant (c.173C > T, p.T58 M) was found in HKDC1 in two unrelated families presenting late-onset retinal degeneration. This variant affects highly conserved amino acid residue and is very rare in several databases and absent in 4000 ethnic-matched controls. Mutant HKDC1 protein partially lost hexokinase activity. Hkdc1 is expressed in the mouse retina and localized to photoreceptor inner segments. To elucidate the in vivo roles of Hkdc1 in the retina, we generated Hkdc1 knockout (KO) mouse models using CRISPR/Cas9 technique. Two independent alleles were identified and backcrossed to C57BL/6 J for 6 generations. Absence of HKDC1 expression in the Hkdc1 KO retina was confirmed by western blot and immunostaning using HKDC1 antibody. Hkdc1 KO mice exhibited reduced scotopic electroretinogram response and thinner outer nuclear layer, similar to some of the human patient phenotypes. Loss of Hkdc1 led to mislocalization of rhodopsin to the inner segments and cell bodies of rods in some regions in the retina. Taken together, our data demonstrated that HKDC1 is associated with autosomal recessively inherited RP.
Keywords: Animals; Disease Models, Animal; Exome; Exome Sequencing; Female; Genetic Association Studies; Hexokinase; Homozygote; Humans; Male; Mice, Knockout; Mutation; Pedigree; Retina; Retinal Degeneration; Retinitis Pigmentosa

Whole-Exome Sequencing Reveals Uncaptured Variation and Distinct Ancestry in the Southern African Population of Botswana. - Retshabile, Gaone; Mlotshwa, Busisiwe C; Williams, Lesedi; Mwesigwa, Savannah; Mboowa, Gerald; Huang, Zhuoyi; Rustagi, Navin; Swaminathan, Shanker; Katagirya, Eric; Kyobe, Samuel; Wayengera, Misaki; Kisitu, Grace P; et al. (Am J Hum Genet, 2018)
Large-scale, population-based genomic studies have provided a context for modern medical genetics. Among such studies, however, African populations have remained relatively underrepresented. The breadth of genetic diversity across the African continent argues for an exploration of local genomic context to facilitate burgeoning disease mapping studies in Africa. We sought to characterize genetic variation and to assess population substructure within a cohort of HIV-positive children from Botswana-a Southern African country that is regionally underrepresented in genomic databases. Using whole-exome sequencing data from 164 Batswana and comparisons with 150 similarly sequenced HIV-positive Ugandan children, we found that 13%-25% of variation observed among Batswana was not captured by public databases. Uncaptured variants were significantly enriched (p = 2.2 × 10) for coding variants with minor allele frequencies between 1% and 5% and included predicted-damaging non-synonymous variants. Among variants found in public databases, corresponding allele frequencies varied widely, with Botswana having significantly higher allele frequencies among rare (<1%) pathogenic and damaging variants. Batswana clustered with other Southern African populations, but distinctly from 1000 Genomes African populations, and had limited evidence for admixture with extra-continental ancestries. We also observed a surprising lack of genetic substructure in Botswana, despite multiple tribal ethnicities and language groups, alongside a higher degree of relatedness than purported founder populations from the 1000 Genomes project. Our observations reveal a complex, but distinct, ancestral history and genomic architecture among Batswana and suggest that disease mapping within similar Southern African populations will require a deeper repository of genetic variation and allelic dependencies than presently exists.
Keywords: Black People; Botswana; Cohort Studies; Exome Sequencing; Gene Pool; Genetic Variation; Genetics, Population; Genome, Human; Geography; Humans; Phylogeny; Principal Component Analysis

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

Alu Insertion Polymorphisms as Evidence for Population Structure in Baboons. - Steely, Cody J; Walker, Jerilyn A; Jordan, Vallmer E; Beckstrom, Thomas O; McDaniel, Cullen L; St Romain, Corey P; Bennett, Emily C; Robichaux, Arianna; Clement, Brooke N; Raveendran, Muthuswamy; Worley, Kim C; Phillips-Conroy, Jane; et al. (Genome Biol Evol, 2017)
Male dispersal from the natal group at or near maturity is a feature of most baboon (Papio) species. It potentially has profound effects upon population structure and evolutionary processes, but dispersal, especially for unusually long distances, is not readily documented by direct field observation. In this pilot study, we investigate the possibility of retrieving baboon population structure in yellow (Papio cynocephalus) and kinda (Papio kindae) baboons from the distribution of variation in a genome-wide set of 494 Alu insertion polymorphisms, made available via the recently completed Baboon Genome Analysis Consortium. Alu insertion variation in a mixed population derived from yellow and olive (Papio anubis) baboons identified each individual's proportion of heritage from either parental species. In an unmixed yellow baboon population, our analysis showed greater similarity between neighboring than between more distantly situated groups, suggesting structuring of the population by male dispersal distance. Finally (and very provisionally), an unexpectedly sharp difference in Alu insertion frequencies between members of neighboring social groups of kinda baboons suggests that intergroup migration may be more rare than predicted in this little known species.
Keywords: Alu Elements; Animals; Evolution, Molecular; Female; Genome; Male; Papio; Phylogeny; Polymorphism, Genetic

Analyses of SLC13A5-epilepsy patients reveal perturbations of TCA cycle. - Bainbridge, Matthew N; Cooney, Erin; Miller, Marcus; Kennedy, Adam D; Wulff, Jacob E; Donti, Taraka; Jhangiani, Shalini N; Gibbs, Richard A; Elsea, Sarah H; Porter, Brenda E; Graham, Brett H (Mol Genet Metab, 2017)
OBJECTIVE: To interrogate the metabolic profile of five subjects from three families with rare, nonsense and missense mutations in SLC13A5 and Early Infantile Epileptic Encephalopathies (EIEE) characterized by severe, neonatal onset seizures, psychomotor retardation and global developmental delay. METHODS: Mass spectrometry of plasma, CSF and urine was used to identify consistently dysregulated analytes in our subjects. RESULTS: Distinctive elevations of citrate and dysregulation of citric acid cycle intermediates, supporting the hypothesis that loss of SLC13A5 function alters tricarboxylic acid cycle (TCA) metabolism and may disrupt metabolic compartmentation in the brain. SIGNIFICANCE: Our results indicate that analysis of plasma citrate and other TCA analytes in SLC13A5 deficient patients define a diagnostic metabolic signature that can aid in diagnosing children with this disease.
Keywords: Child; Citric Acid; Citric Acid Cycle; Exome Sequencing; Female; Humans; Infant, Newborn; Male; Mass Spectrometry; Metabolome; Metabolomics; Mutation; Mutation, Missense; Seizures; Spasms, Infantile; Symporters

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Gibbs, Richard A; Gogarten, Stephanie M; et al. (Nat Genet, 2017)
The exploding volume of whole-genome sequence (WGS) and multi-omics data requires new approaches for analysis. As one solution, we have created a cloud-based Analysis Commons, which brings together genotype and phenotype data from multiple studies in a setting that is accessible by multiple investigators. This framework addresses many of the challenges of multi-center WGS analyses, including data sharing mechanisms, phenotype harmonization, integrated multi-omics analyses, annotation, and computational flexibility. In this setting, the computational pipeline facilitates a sequence-to-discovery analysis workflow illustrated here by an analysis of plasma fibrinogen levels in 3996 individuals from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) WGS program. The Analysis Commons represents a novel model for transforming WGS resources from a massive quantity of phenotypic and genomic data into knowledge of the determinants of health and disease risk in diverse human populations.
Keywords: big data; Fibrinogen; Genetics, Population; Genome; Humans; Information Dissemination; Mobile Applications; Molecular Epidemiology; Regression Analysis; Software; Workflow

Association of Body Mass Index with DNA Methylation and Gene Expression in Blood Cells and Relations to Cardiometabolic Disease: A Mendelian Randomization Approach. - Mendelson, Michael M; Marioni, Riccardo E; Joehanes, Roby; Liu, Chunyu; Hedman, Åsa K; Aslibekyan, Stella; Demerath, Ellen W; Guan, Weihua; Zhi, Degui; Yao, Chen; Huan, Tianxiao; Willinger, Christine; et al. (PLoS Med, 2017)
BACKGROUND: The link between DNA methylation, obesity, and adiposity-related diseases in the general population remains uncertain. METHODS AND FINDINGS: We conducted an association study of body mass index (BMI) and differential methylation for over 400,000 CpGs assayed by microarray in whole-blood-derived DNA from 3,743 participants in the Framingham Heart Study and the Lothian Birth Cohorts, with independent replication in three external cohorts of 4,055 participants. We examined variations in whole blood gene expression and conducted Mendelian randomization analyses to investigate the functional and clinical relevance of the findings. We identified novel and previously reported BMI-related differential methylation at 83 CpGs that replicated across cohorts; BMI-related differential methylation was associated with concurrent changes in the expression of genes in lipid metabolism pathways. Genetic instrumental variable analysis of alterations in methylation at one of the 83 replicated CpGs, cg11024682 (intronic to sterol regulatory element binding transcription factor 1 [SREBF1]), demonstrated links to BMI, adiposity-related traits, and coronary artery disease. Independent genetic instruments for expression of SREBF1 supported the findings linking methylation to adiposity and cardiometabolic disease. Methylation at a substantial proportion (16 of 83) of the identified loci was found to be secondary to differences in BMI. However, the cross-sectional nature of the data limits definitive causal determination. CONCLUSIONS: We present robust associations of BMI with differential DNA methylation at numerous loci in blood cells. BMI-related DNA methylation and gene expression provide mechanistic insights into the relationship between DNA methylation, obesity, and adiposity-related diseases.
Keywords: Aged; Body Mass Index; Coronary Artery Disease; DNA Methylation; Epigenesis, Genetic; Female; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Lipid Metabolism; Male; Mendelian Randomization Analysis; Obesity; Oligonucleotide Array Sequence Analysis

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Gibbs, Richard; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

Disruption of the ATXN1-CIC complex causes a spectrum of neurobehavioral phenotypes in mice and humans. - Lu, Hsiang-Chih; Tan, Qiumin; Rousseaux, Maxime W C; Wang, Wei; Kim, Ji-Yoen; Richman, Ronald; Wan, Ying-Wooi; Yeh, Szu-Ying; Patel, Jay M; Liu, Xiuyun; Lin, Tao; Lee, Yoontae; et al. (Nat Genet, 2017)
Gain-of-function mutations in some genes underlie neurodegenerative conditions, whereas loss-of-function mutations in the same genes have distinct phenotypes. This appears to be the case with the protein ataxin 1 (ATXN1), which forms a transcriptional repressor complex with capicua (CIC). Gain of function of the complex leads to neurodegeneration, but ATXN1-CIC is also essential for survival. We set out to understand the functions of the ATXN1-CIC complex in the developing forebrain and found that losing this complex results in hyperactivity, impaired learning and memory, and abnormal maturation and maintenance of upper-layer cortical neurons. We also found that CIC activity in the hypothalamus and medial amygdala modulates social interactions. Informed by these neurobehavioral features in mouse mutants, we identified five individuals with de novo heterozygous truncating mutations in CIC who share similar clinical features, including intellectual disability, attention deficit/hyperactivity disorder (ADHD), and autism spectrum disorder. Our study demonstrates that loss of ATXN1-CIC complexes causes a spectrum of neurobehavioral phenotypes.
Keywords: Animals; Ataxin-1; Autism Spectrum Disorder; Cerebellum; Female; Humans; Intellectual Disability; Interpersonal Relations; Male; Mice; Nerve Tissue Proteins; Neurodegenerative Diseases; Nuclear Proteins; Phenotype; Repressor Proteins

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10; replication: N = 7,182, p < 1.6 × 10). The replicated methylation sites are heritable (h > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Dual molecular diagnosis contributes to atypical Prader-Willi phenotype in monozygotic twins. - Jehee, Fernanda S; de Oliveira, Valdirene T; Gurgel-Giannetti, Juliana; Pietra, Rafaella X; Rubatino, Fernando V M; Carobin, Natália V; Vianna, Gabrielle S; de Freitas, Mariana L; Fernandes, Karla S; Ribeiro, Beatriz S V; Brüggenwirth, Hennie T; Ali-Amin, Roza; et al. (Am J Med Genet A, 2017)
We describe monozygotic twin girls with genetic variation at two separate loci resulting in a blended phenotype of Prader-Willi syndrome and Pitt-Hopkins syndrome. These girls were diagnosed in early infancy with Prader-Willi syndrome, but developed an atypical phenotype, with apparent intellectual deficiency and lack of obesity. Array-comparative genomic hybridization confirmed a de novo paternal deletion of the 15q11.2q13 region and exome sequencing identified a second mutational event in both girls, which was a novel variant c.145+1G>A affecting a TCF4 canonical splicing site inherited from the mosaic mother. RNA studies showed that the variant abolished the donor splicing site, which was accompanied by activation of an alternative non-canonical splicing-site which then predicts a premature stop codon in the following exon. Clinical re-evaluation of the twins indicated that both variants are likely contributing to the more severe phenotypic presentation. Our data show that atypical clinical presentations may actually be the expression of blended clinical phenotypes arising from independent pathogenic events at two loci.
Keywords: Adolescent; Base Sequence; Child; Chromosome Deletion; Chromosomes, Human, Pair 15; Comparative Genomic Hybridization; Exome; Facies; Female; Humans; Hyperventilation; Intellectual Disability; Obesity; Pathology, Molecular; Phenotype; Prader-Willi Syndrome; Transcription Factor 4; Twins, Monozygotic

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Rett Syndrome

Erratum to: Genomic innovations, transcriptional plasticity and gene loss underlying the evolution and divergence of two highly polyphagous and invasive Helicoverpa pest species. - Pearce, S L; Clarke, D F; East, P D; Elfekih, S; Gordon, K H J; Jermiin, L S; McGaughran, A; Oakeshott, J G; Papanicolaou, A; Perera, O P; Rane, R V; Richards, S; et al. (BMC Biol, 2017)

Erratum to: The whole genome sequence of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), reveals insights into the biology and adaptive evolution of a highly invasive pest species. - Papanicolaou, Alexie; Schetelig, Marc F; Arensburger, Peter; Atkinson, Peter W; Benoit, Joshua B; Bourtzis, Kostas; Castañera, Pedro; Cavanaugh, John P; Chao, Hsu; Childers, Christopher; Curril, Ingrid; Dinh, Huyen; et al. (Genome Biol, 2017)

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Exome Sequencing; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

An Expanded Genome-Wide Association Study of Type 2 Diabetes in Europeans. - Scott, Robert A; Scott, Laura J; Mägi, Reedik; Marullo, Letizia; Gaulton, Kyle J; Kaakinen, Marika; Pervjakova, Natalia; Pers, Tune H; Johnson, Andrew D; Eicher, John D; Jackson, Anne U; Ferreira, Teresa; et al. (Diabetes, 2017)
To characterize type 2 diabetes (T2D)-associated variation across the allele frequency spectrum, we conducted a meta-analysis of genome-wide association data from 26,676 T2D case and 132,532 control subjects of European ancestry after imputation using the 1000 Genomes multiethnic reference panel. Promising association signals were followed up in additional data sets (of 14,545 or 7,397 T2D case and 38,994 or 71,604 control subjects). We identified 13 novel T2D-associated loci ( < 5 × 10), including variants near the , , and genes. Our analysis brought the total number of independent T2D associations to 128 distinct signals at 113 loci. Despite substantially increased sample size and more complete coverage of low-frequency variation, all novel associations were driven by common single nucleotide variants. Credible sets of potentially causal variants were generally larger than those based on imputation with earlier reference panels, consistent with resolution of causal signals to common risk haplotypes. Stratification of T2D-associated loci based on T2D-related quantitative trait associations revealed tissue-specific enrichment of regulatory annotations in pancreatic islet enhancers for loci influencing insulin secretion and in adipocytes, monocytes, and hepatocytes for insulin action-associated loci. These findings highlight the predominant role played by common variants of modest effect and the diversity of biological mechanisms influencing T2D pathophysiology.
Keywords: Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; White People

Extremely low-coverage whole genome sequencing in South Asians captures population genomics information. - Rustagi, Navin; Zhou, Anbo; Watkins, W Scott; Gedvilaite, Erika; Wang, Shuoguo; Ramesh, Naveen; Muzny, Donna; Gibbs, Richard A; Jorde, Lynn B; Yu, Fuli; Xing, Jinchuan (BMC Genomics, 2017)
BACKGROUND: The cost of Whole Genome Sequencing (WGS) has decreased tremendously in recent years due to advances in next-generation sequencing technologies. Nevertheless, the cost of carrying out large-scale cohort studies using WGS is still daunting. Past simulation studies with coverage at ~2x have shown promise for using low coverage WGS in studies focused on variant discovery, association study replications, and population genomics characterization. However, the performance of low coverage WGS in populations with a complex history and no reference panel remains to be determined. RESULTS: South Indian populations are known to have a complex population structure and are an example of a major population group that lacks adequate reference panels. To test the performance of extremely low-coverage WGS (EXL-WGS) in populations with a complex history and to provide a reference resource for South Indian populations, we performed EXL-WGS on 185 South Indian individuals from eight populations to ~1.6x coverage. Using two variant discovery pipelines, SNPTools and GATK, we generated a consensus call set that has ~90% sensitivity for identifying common variants (minor allele frequency ≥ 10%). Imputation further improves the sensitivity of our call set. In addition, we obtained high-coverage for the whole mitochondrial genome to infer the maternal lineage evolutionary history of the Indian samples. CONCLUSIONS: Overall, we demonstrate that EXL-WGS with imputation can be a valuable study design for variant discovery with a dramatically lower cost than standard WGS, even in populations with a complex history and without available reference data. In addition, the South Indian EXL-WGS data generated in this study will provide a valuable resource for future Indian genomic studies.
Keywords: Asian People; Genetic Variation; Genome, Mitochondrial; Humans; Metagenomics; Whole Genome Sequencing

Fifteen new risk loci for coronary artery disease highlight arterial-wall-specific mechanisms. - Howson, Joanna M M; Zhao, Wei; Barnes, Daniel R; Ho, Weang-Kee; Young, Robin; Paul, Dirk S; Waite, Lindsay L; Freitag, Daniel F; Fauman, Eric B; Salfati, Elias L; Sun, Benjamin B; Eicher, John D; et al. (Nat Genet, 2017)
Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide. Although 58 genomic regions have been associated with CAD thus far, most of the heritability is unexplained, indicating that additional susceptibility loci await identification. An efficient discovery strategy may be larger-scale evaluation of promising associations suggested by genome-wide association studies (GWAS). Hence, we genotyped 56,309 participants using a targeted gene array derived from earlier GWAS results and performed meta-analysis of results with 194,427 participants previously genotyped, totaling 88,192 CAD cases and 162,544 controls. We identified 25 new SNP-CAD associations (P < 5 × 10, in fixed-effects meta-analysis) from 15 genomic regions, including SNPs in or near genes involved in cellular adhesion, leukocyte migration and atherosclerosis (PECAM1, rs1867624), coagulation and inflammation (PROCR, rs867186 (p.Ser219Gly)) and vascular smooth muscle cell differentiation (LMOD1, rs2820315). Correlation of these regions with cell-type-specific gene expression and plasma protein levels sheds light on potential disease mechanisms.
Keywords: Arteries; Atherosclerosis; Cell Adhesion; Chemotaxis, Leukocyte; Coronary Artery Disease; Energy Metabolism; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Histone Code; Humans; Male; Muscle, Smooth, Vascular; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

First Case of Deficiency in Ecuador, Diagnosed after Whole Exome Sequencing in a Patient with Severe Cutaneous Histoplasmosis. - Pedroza, Luis Alberto; Guerrero, Nina; Stray-Pedersen, Asbjørg; Tafur, Cristina; Macias, Roque; Muñoz, Greta; Akdemir, Zeynep Coban; Jhangiani, Shalini N; Watkin, Levi B; Chinn, Ivan K; Lupski, James R; Orange, Jordan S (Front Pediatr, 2017)
Severe infections with are commonly observed in patient with secondary immunodeficiency disorders. We report a two and a half years old boy previously healthy with disseminated cutaneous histoplasmosis. Using whole exome sequencing, we found an mutation at the gene, suggesting a diagnosis of hyper-IgM (HIGM) syndrome, even in the absence of the usual features for the disease. Interestingly, the patient lives in a region endemic for histoplasmosis. The unusual infections in our case suggest that in children with severe histoplasmosis and resident in endemic areas, HIGM syndrome should be considered as a diagnosis.

Further delineation of a rare recessive encephalomyopathy linked to mutations in GFER thanks to data sharing of whole exome sequencing data. - Nambot, S; Gavrilov, D; Thevenon, J; Bruel, A L; Bainbridge, M; Rio, M; Goizet, C; Rötig, A; Jaeken, J; Niu, N; Xia, F; Vital, A; et al. (Clin Genet, 2017)
BACKGROUND: Alterations in GFER gene have been associated with progressive mitochondrial myopathy, congenital cataracts, hearing loss, developmental delay, lactic acidosis and respiratory chain deficiency in 3 siblings born to consanguineous Moroccan parents by homozygosity mapping and candidate gene approach (OMIM#613076). Next generation sequencing recently confirmed this association by the finding of compound heterozygous variants in 19-year-old girl with a strikingly similar phenotype, but this ultra-rare entity remains however unknown from most of the scientific community. MATERIALS AND METHODS: Whole exome sequencing was performed as part of a "diagnostic odyssey" for suspected mitochondrial condition in 2 patients, presenting congenital cataracts, progressive encephalomyopathy and hypotrophy and detected unreported compound heterozygous variants in GFER. RESULTS: Thanks to an international data sharing, we found 2 additional patients carrying compound heterozygous variants in GFER. Reverse phenotyping confirmed the phenotypical similarities between the 4 patients. Together with the first literature reports, the review of these 8 cases from 4 unrelated families enables us to better describe this apparently homogeneous disorder, with the clinical and biological stigmata of mitochondrial disease. CONCLUSION: This report highlights the clinical utility of whole exome sequencing and reverse phenotyping for the diagnosis of ultra-rare diseases and underlines the importance of a broad data sharing for accurate clinical delineation of previously unrecognized entities.
Keywords: Adolescent; Adult; Child; Cytochrome Reductases; Exome Sequencing; Female; Genetic Predisposition to Disease; Heterozygote; Humans; Male; Mitochondrial Encephalomyopathies; Mutation; Oxidoreductases Acting on Sulfur Group Donors; Pedigree; Young Adult

Genome Sequence of a Novel Kunsagivirus (: ) from a Wild Baboon (). - Buechler, Connor R; Bailey, Adam L; Lauck, Michael; Heffron, Anna; Johnson, Joshua C; Campos Lawson, Cristine; Rogers, Jeffrey; Kuhn, Jens H; O'Connor, David H (Genome Announc, 2017)
The picornaviral genus has a single member, kunsagivirus A, which was discovered in migratory bird feces. We report here the discovery of a novel kunsagivirus in wild yellow baboon () blood. The genomic sequence of this virus indicates the probable need for the establishment of a second kunsagivirus species.

Genomic innovations, transcriptional plasticity and gene loss underlying the evolution and divergence of two highly polyphagous and invasive Helicoverpa pest species. - Pearce, S L; Clarke, D F; East, P D; Elfekih, S; Gordon, K H J; Jermiin, L S; McGaughran, A; Oakeshott, J G; Papanicolaou, A; Perera, O P; Rane, R V; Richards, S; et al. (BMC Biol, 2017)
BACKGROUND: Helicoverpa armigera and Helicoverpa zea are major caterpillar pests of Old and New World agriculture, respectively. Both, particularly H. armigera, are extremely polyphagous, and H. armigera has developed resistance to many insecticides. Here we use comparative genomics, transcriptomics and resequencing to elucidate the genetic basis for their properties as pests. RESULTS: We find that, prior to their divergence about 1.5 Mya, the H. armigera/H. zea lineage had accumulated up to more than 100 more members of specific detoxification and digestion gene families and more than 100 extra gustatory receptor genes, compared to other lepidopterans with narrower host ranges. The two genomes remain very similar in gene content and order, but H. armigera is more polymorphic overall, and H. zea has lost several detoxification genes, as well as about 50 gustatory receptor genes. It also lacks certain genes and alleles conferring insecticide resistance found in H. armigera. Non-synonymous sites in the expanded gene families above are rapidly diverging, both between paralogues and between orthologues in the two species. Whole genome transcriptomic analyses of H. armigera larvae show widely divergent responses to different host plants, including responses among many of the duplicated detoxification and digestion genes. CONCLUSIONS: The extreme polyphagy of the two heliothines is associated with extensive amplification and neofunctionalisation of genes involved in host finding and use, coupled with versatile transcriptional responses on different hosts. H. armigera's invasion of the Americas in recent years means that hybridisation could generate populations that are both locally adapted and insecticide resistant.
Keywords: Animals; Gene Expression Profiling; Genome, Insect; Genomics; Herbivory; Introduced Species; Larva; Moths; Sequence Analysis, DNA

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Yuan, Bo; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

The house spider genome reveals an ancient whole-genome duplication during arachnid evolution. - Schwager, Evelyn E; Sharma, Prashant P; Clarke, Thomas; Leite, Daniel J; Wierschin, Torsten; Pechmann, Matthias; Akiyama-Oda, Yasuko; Esposito, Lauren; Bechsgaard, Jesper; Bilde, Trine; Buffry, Alexandra D; Chao, Hsu; et al. (BMC Biol, 2017)
BACKGROUND: The duplication of genes can occur through various mechanisms and is thought to make a major contribution to the evolutionary diversification of organisms. There is increasing evidence for a large-scale duplication of genes in some chelicerate lineages including two rounds of whole genome duplication (WGD) in horseshoe crabs. To investigate this further, we sequenced and analyzed the genome of the common house spider Parasteatoda tepidariorum. RESULTS: We found pervasive duplication of both coding and non-coding genes in this spider, including two clusters of Hox genes. Analysis of synteny conservation across the P. tepidariorum genome suggests that there has been an ancient WGD in spiders. Comparison with the genomes of other chelicerates, including that of the newly sequenced bark scorpion Centruroides sculpturatus, suggests that this event occurred in the common ancestor of spiders and scorpions, and is probably independent of the WGDs in horseshoe crabs. Furthermore, characterization of the sequence and expression of the Hox paralogs in P. tepidariorum suggests that many have been subject to neo-functionalization and/or sub-functionalization since their duplication. CONCLUSIONS: Our results reveal that spiders and scorpions are likely the descendants of a polyploid ancestor that lived more than 450 MYA. Given the extensive morphological diversity and ecological adaptations found among these animals, rivaling those of vertebrates, our study of the ancient WGD event in Arachnopulmonata provides a new comparative platform to explore common and divergent evolutionary outcomes of polyploidization events across eukaryotes.
Keywords: Animals; Evolution, Molecular; Female; Gene Duplication; Genome; Male; Spiders; Synteny

Improved annotation of the insect vector of citrus greening disease: biocuration by a diverse genomics community. - Saha, Surya; Hosmani, Prashant S; Villalobos-Ayala, Krystal; Miller, Sherry; Shippy, Teresa; Flores, Mirella; Rosendale, Andrew; Cordola, Chris; Bell, Tracey; Mann, Hannah; DeAvila, Gabe; DeAvila, Daniel; et al. (Database (Oxford), 2017)
https://citrusgreening.org/.
Keywords: Animals; Citrus; Databases, Genetic; Genome, Insect; Hemiptera; Insect Vectors; Pest Control; Plant Diseases; Rhizobiaceae

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.
Keywords: Atrial Fibrillation; Black or African American; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Quantitative Trait Loci; White People

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

Molecular Screening of 43 Brazilian Families Diagnosed with Leber Congenital Amaurosis or Early-Onset Severe Retinal Dystrophy. - Porto, Fernanda B O; Jones, Evan M; Branch, Justin; Soens, Zachry T; Maia, Igor Mendes; Sena, Isadora F G; Sampaio, Shirley A M; Simões, Renata T; Chen, Rui (Genes (Basel), 2017)
Leber congenital amaurosis (LCA) is a severe disease that leads to complete blindness in children, typically before the first year of life. Due to the clinical and genetic heterogeneity among LCA and other retinal diseases, providing patients with a molecular diagnosis is essential to assigning an accurate clinical diagnosis. Using our gene panel that targets 300 genes that are known to cause retinal disease, including 24 genes reported to cause LCA, we sequenced 43 unrelated probands with Brazilian ancestry. We identified 42 unique variants and were able to assign a molecular diagnosis to 30/43 (70%) Brazilian patients. Among these, 30 patients were initially diagnosed with LCA or a form of early-onset retinal dystrophy, 17 patients harbored mutations in LCA-associated genes, while 13 patients had mutations in genes that were reported to cause other diseases involving the retina.

Mutations in EBF3 Disturb Transcriptional Profiles and Cause Intellectual Disability, Ataxia, and Facial Dysmorphism. - Harms, Frederike Leonie; Girisha, Katta M; Hardigan, Andrew A; Kortüm, Fanny; Shukla, Anju; Alawi, Malik; Dalal, Ashwin; Brady, Lauren; Tarnopolsky, Mark; Bird, Lynne M; Ceulemans, Sophia; Bebin, Martina; et al. (Am J Hum Genet, 2017)
From a GeneMatcher-enabled international collaboration, we identified ten individuals affected by intellectual disability, speech delay, ataxia, and facial dysmorphism and carrying a deleterious EBF3 variant detected by whole-exome sequencing. One 9-bp duplication and one splice-site, five missense, and two nonsense variants in EBF3 were found; the mutations occurred de novo in eight individuals, and the missense variant c.625C>T (p.Arg209Trp) was inherited by two affected siblings from their healthy mother, who is mosaic. EBF3 belongs to the early B cell factor family (also known as Olf, COE, or O/E) and is a transcription factor involved in neuronal differentiation and maturation. Structural assessment predicted that the five amino acid substitutions have damaging effects on DNA binding of EBF3. Transient expression of EBF3 mutant proteins in HEK293T cells revealed mislocalization of all but one mutant in the cytoplasm, as well as nuclear localization. By transactivation assays, all EBF3 mutants showed significantly reduced or no ability to activate transcription of the reporter gene CDKN1A, and in situ subcellular fractionation experiments demonstrated that EBF3 mutant proteins were less tightly associated with chromatin. Finally, in RNA-seq and ChIP-seq experiments, EBF3 acted as a transcriptional regulator, and mutant EBF3 had reduced genome-wide DNA binding and gene-regulatory activity. Our findings demonstrate that variants disrupting EBF3-mediated transcriptional regulation cause intellectual disability and developmental delay and are present in ∼0.1% of individuals with unexplained neurodevelopmental disorders.
Keywords: Adolescent; Adult; Amino Acid Substitution; Ataxia; Child; Child, Preschool; Chromatin; Cyclin-Dependent Kinase Inhibitor p21; Developmental Disabilities; Exome; Face; Female; Gene Expression Regulation; Genes, Reporter; HEK293 Cells; Humans; Intellectual Disability; Language Development Disorders; Male; Models, Molecular; Mosaicism; Mutation; Neurodevelopmental Disorders; Protein Transport; Syndrome; Transcription Factors; Transcription, Genetic

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Gibbs, Richard A; Muzny, Donna; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Microfilament Proteins; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

The next generation of population-based spinal muscular atrophy carrier screening: comprehensive pan-ethnic SMN1 copy-number and sequence variant analysis by massively parallel sequencing. - Feng, Yanming; Ge, Xiaoyan; Meng, Linyan; Scull, Jennifer; Li, Jianli; Tian, Xia; Zhang, Tao; Jin, Weihong; Cheng, Hanyin; Wang, Xia; Tokita, Mari; Liu, Pengfei; et al. (Genet Med, 2017)
PURPOSE: To investigate pan-ethnic SMN1 copy-number and sequence variation by hybridization-based target enrichment coupled with massively parallel sequencing or next-generation sequencing (NGS). METHODS: NGS reads aligned to SMN1 and SMN2 exon 7 were quantified to determine the total combined copy number of SMN1 and SMN2. The ratio of SMN1 to SMN2 was calculated based on a single-nucleotide difference that distinguishes the two genes. SMN1 copy-number results were compared between the NGS and quantitative polymerase chain reaction and/or multiplex ligation-dependent probe amplification. The NGS data set was also queried for the g.27134T>G single-nucleotide polymorphism (SNP) and other SMN1 sequence pathogenic variants. RESULTS: The sensitivity of the test to detect spinal muscular atrophy (SMA) carriers with one copy of SMN1 was 100% (95% confidence interval (CI): 95.9-100%; n = 90) and specificity was 99.6% (95% CI: 99.4-99.7%; n = 6,648). Detection of the g.27134T>G SNP by NGS was 100% concordant with an restriction fragment-length polymorphism method (n = 493). Ten single-nucleotide variants in SMN1 were detectable by NGS and confirmed by gene-specific amplicon-based sequencing. This comprehensive approach yielded SMA carrier detection rates of 90.3-95.0% in five ethnic groups studied. CONCLUSION: We have developed a novel, comprehensive SMN1 copy-number and sequence variant analysis method by NGS that demonstrated improved SMA carrier detection rates across the entire population examined.Genet Med advance online publication 19 January 2017.
Keywords: Gene Dosage; Genetic Carrier Screening; High-Throughput Nucleotide Sequencing; Humans; Muscular Atrophy, Spinal; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Survival of Motor Neuron 1 Protein; Survival of Motor Neuron 2 Protein

Non-malignant respiratory epithelial cells preferentially proliferate from resected non-small cell lung cancer specimens cultured under conditionally reprogrammed conditions. - Gao, Boning; Huang, Chunxian; Kernstine, Kemp; Pelekanou, Vasiliki; Kluger, Yuval; Jiang, Tingting; Peters-Hall, Jennifer R; Coquelin, Melissa; Girard, Luc; Zhang, Wei; Huffman, Kenneth; Oliver, Dwight; et al. (Oncotarget, 2017)
The "conditionally reprogrammed cells" (CRC) method, using a Rho kinase inhibitor and irradiated mouse fibroblast cells has been described for the efficient growth of cells from malignant and non-malignant samples from primary tumor and non-malignant sites. Using the CRC method, four institutions independently cultured tumor tissues from 48 non-small cell lung cancers (NSCLC, mostly from primary resected tumors) and 22 non-malignant lungs. We found that epithelial cells could be cultured from tumor and non-malignant lung. However, epithelial cells cultured from tumors had features of non-malignant respiratory epithelial cells which include: 1) among 22 mutations found in the original tumors only two mutations were found in the CRC cultures with reduced frequency (31% to 13% and 92% to 15% from original tumor and CRC culture respectively); 2) copy number variation was analyzed in 9 tumor and their CRC cultures and only diploid patterns were found in CRC cultures; 3) mRNA expression profiles were similar to those of normal respiratory epithelial cells; and 4) co-culture of tumor and non-malignant lung epithelial cells resulted in mostly non-malignant cells. We conclude that CRC method is a highly selective and useful method for the growth of non-malignant respiratory epithelial cells from tumor specimens and only occasionally do such CRC cultures contain a small subpopulation of cancer cells marked by oncogenic mutations. While our findings are restricted to resected primary NSCLC, they indicated the necessity to fully characterize all CRC cultures and the need to develop culture technology that facilitates the growth of primary lung cancers.
Keywords: A549 Cells; Adult; Aged; Aged, 80 and over; Base Sequence; Carcinoma, Non-Small-Cell Lung; Cell Line, Tumor; Cell Proliferation; Cells, Cultured; Coculture Techniques; DNA Copy Number Variations; DNA Mutational Analysis; Epithelial Cells; Female; Gene Expression Profiling; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Male; Middle Aged; Mutation; Respiratory Mucosa; Tumor Cells, Cultured

A non-mosaic mutation in a male with severe congenital anomalies overlapping focal dermal hypoplasia. - Madan, Simran; Liu, Wei; Lu, James T; Sutton, V Reid; Toth, Bryant; Joe, Priscilla; Waterson, John R; Gibbs, Richard A; Van den Veyver, Ignatia B; Lammer, Edward J; Campeau, Philippe M; Lee, Brendan H (Mol Genet Metab Rep, 2017)
Mutations in the gene cause the X-linked dominant condition focal dermal hypoplasia (FDH). Features of FDH include striated pigmentation of the skin, ocular and skeletal malformations. FDH is generally associated with lethality in non-mosaic males and most of the currently reported male patients show mosaicism due to post-zygotic mutations in the gene. There is only one previous report of a surviving male with an inherited mutation in the gene. Here, we report two male siblings with multiple malformations including skeletal, ocular and renal defects overlapping with FDH. A novel mutation (p.Ser250Phe) was identified in a non-mosaic, hemizygous state in one of the siblings who survived to 8 years of age. The mother is a heterozygous carrier, has a random X-inactivation pattern and is asymptomatic. Findings unusual for FDH include dysplastic clavicles and bilateral Tessier IV facial clefts. This is the second case report of a non-mosaic mutation in a male individual with multiple congenital anomalies. While the pathogenicity of this mutation remains to be further investigated, the survival of a male with a non-mosaic mutation in is suggestive of a functionally mild mutation leading to an X-linked recessive mode of inheritance.

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Yuan, Bo; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

A Pan-Cancer Proteogenomic Atlas of PI3K/AKT/mTOR Pathway Alterations. - Zhang, Yiqun; Kwok-Shing Ng, Patrick; Kucherlapati, Melanie; Chen, Fengju; Liu, Yuexin; Tsang, Yiu Huen; De Velasco, Guillermo; Jeong, Kang Jin; Akbani, Rehan; Hadjipanayis, Angela; Pantazi, Angeliki; Bristow, Christopher A; et al. (Cancer Cell, 2017)
Molecular alterations involving the PI3K/AKT/mTOR pathway (including mutation, copy number, protein, or RNA) were examined across 11,219 human cancers representing 32 major types. Within specific mutated genes, frequency, mutation hotspot residues, in silico predictions, and functional assays were all informative in distinguishing the subset of genetic variants more likely to have functional relevance. Multiple oncogenic pathways including PI3K/AKT/mTOR converged on similar sets of downstream transcriptional targets. In addition to mutation, structural variations and partial copy losses involving PTEN and STK11 showed evidence for having functional relevance. A substantial fraction of cancers showed high mTOR pathway activity without an associated canonical genetic or genomic alteration, including cancers harboring IDH1 or VHL mutations, suggesting multiple mechanisms for pathway activation.
Keywords: Databases, Genetic; Gene Expression Profiling; Humans; Mutation; Neoplasms; Phosphatidylinositol 3-Kinases; Proteogenomics; Proto-Oncogene Proteins c-akt; Signal Transduction; Survival Analysis; TOR Serine-Threonine Kinases

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10, odds ratio (OR) = 0.68, minor allele frequency (MAF) = 0.0059, MAF = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10, OR = 1.43, MAF = 0.011, MAF = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10, OR = 1.67, MAF = 0.0143, MAF = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

Seroprevalence of Zika Virus in Wild African Green Monkeys and Baboons. - Buechler, Connor R; Bailey, Adam L; Weiler, Andrea M; Barry, Gabrielle L; Breitbach, Meghan E; Stewart, Laurel M; Jasinska, Anna J; Freimer, Nelson B; Apetrei, Cristian; Phillips-Conroy, Jane E; Jolly, Clifford J; Rogers, Jeffrey; et al. (mSphere, 2017)
Zika virus (ZIKV) has recently spread through the Americas and has been associated with a range of health effects, including birth defects in children born to women infected during pregnancy. Although the natural reservoir of ZIKV remains poorly defined, the virus was first identified in a captive "sentinel" macaque monkey in Africa in 1947. However, the virus has not been reported in humans or nonhuman primates (NHPs) in Africa outside Gabon in over a decade. Here, we examine ZIKV infection in 239 wild baboons and African green monkeys from South Africa, the Gambia, Tanzania, and Zambia using combinations of unbiased deep sequencing, quantitative reverse transcription-PCR (qRT-PCR), and an antibody capture assay that we optimized using serum collected from captive macaque monkeys exposed to ZIKV, dengue virus, and yellow fever virus. While we did not find evidence of active ZIKV infection in wild NHPs in Africa, we found variable ZIKV seropositivity of up to 16% in some of the NHP populations sampled. We anticipate that these results and the methodology described within will help in continued efforts to determine the prevalence, natural reservoir, and transmission dynamics of ZIKV in Africa and elsewhere. Zika virus (ZIKV) is a mosquito-borne virus originally discovered in a captive monkey living in the Zika Forest of Uganda, Africa, in 1947. Recently, an outbreak in South America has shown that ZIKV infection can cause myriad health effects, including birth defects in the children of women infected during pregnancy. Here, we sought to investigate ZIKV infection in wild African primates to better understand its emergence and spread, looking for evidence of active or prior infection. Our results suggest that up to 16% of some populations of nonhuman primate were, at some point, exposed to ZIKV. We anticipate that this study will be useful for future studies that examine the spread of infections from wild animals to humans in general and those studying ZIKV in primates in particular.

Target and Agent Prioritization for the Children's Oncology Group-National Cancer Institute Pediatric MATCH Trial. - Allen, Carl E; Laetsch, Theodore W; Mody, Rajen; Irwin, Meredith S; Lim, Megan S; Adamson, Peter C; Seibel, Nita L; Parsons, D Williams; Cho, Y Jae; Janeway, Katherine (J Natl Cancer Inst, 2017)
Over the past decades, outcomes for children with cancer have improved dramatically through serial clinical trials based in large measure on dose intensification of cytotoxic chemotherapy for children with high-risk malignancies. Progress made through such dose intensification, in general, is no longer yielding further improvements in outcome. With the revolution in sequencing technologies and rapid development of drugs that block specific proteins and pathways, there is now an opportunity to improve outcomes for pediatric cancer patients through mutation-based targeted therapeutic strategies. The Children's Oncology Group (COG), in partnership with the National Cancer Institute (NCI), is planning a trial entitled the COG-NCI Pediatric Molecular Analysis for Therapeutic Choice (Pediatric MATCH) protocol utilizing an umbrella design. This protocol will have centralized infrastructure and will consist of a biomarker profiling protocol and multiple single-arm phase II trials of targeted therapies. Pediatric patients with recurrent or refractory solid tumors, lymphomas, or histiocytoses with measurable disease will be eligible. The Pediatric MATCH Target and Agent Prioritization (TAP) committee includes membership representing COG disease committees, the Food and Drug Administration, and the NCI. The TAP Committee systematically reviewed target and agent pairs for inclusion in the Pediatric MATCH trial. Fifteen drug-target pairs were reviewed by the TAP Committee, with seven recommended for further development as initial arms of the Pediatric MATCH trial. The current evidence for availability, efficacy, and safety of targeted agents in children for each class of mutation considered for inclusion in the Pediatric MATCH trial is discussed in this review.
Keywords: Anaplastic Lymphoma Kinase; Antineoplastic Agents; Child; Cyclin-Dependent Kinase 4; Cyclin-Dependent Kinase 6; Humans; MAP Kinase Kinase Kinases; Molecular Targeted Therapy; Neoplasms; Oncogene Proteins; Phosphoinositide-3 Kinase Inhibitors; Protein Kinase Inhibitors; Receptor Protein-Tyrosine Kinases; Receptors, Fibroblast Growth Factor; Receptors, Platelet-Derived Growth Factor; Research Design; TOR Serine-Threonine Kinases

Transient structural variations have strong effects on quantitative traits and reproductive isolation in fission yeast. - Jeffares, Daniel C; Jolly, Clemency; Hoti, Mimoza; Speed, Doug; Shaw, Liam; Rallis, Charalampos; Balloux, Francois; Dessimoz, Christophe; Bähler, Jürg; Sedlazeck, Fritz J (Nat Commun, 2017)
Large structural variations (SVs) within genomes are more challenging to identify than smaller genetic variants but may substantially contribute to phenotypic diversity and evolution. We analyse the effects of SVs on gene expression, quantitative traits and intrinsic reproductive isolation in the yeast Schizosaccharomyces pombe. We establish a high-quality curated catalogue of SVs in the genomes of a worldwide library of S. pombe strains, including duplications, deletions, inversions and translocations. We show that copy number variants (CNVs) show a variety of genetic signals consistent with rapid turnover. These transient CNVs produce stoichiometric effects on gene expression both within and outside the duplicated regions. CNVs make substantial contributions to quantitative traits, most notably intracellular amino acid concentrations, growth under stress and sugar utilization in winemaking, whereas rearrangements are strongly associated with reproductive isolation. Collectively, these findings have broad implications for evolution and for our understanding of quantitative traits including complex human diseases.
Keywords: Chromosome Inversion; Chromosomes, Fungal; DNA Copy Number Variations; Evolution, Molecular; Gene Expression Regulation, Fungal; Genome, Fungal; Quantitative Trait, Heritable; Reproductive Isolation; Schizosaccharomyces; Translocation, Genetic

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Variants in SKP1, PROB1, and IL17B genes at keratoconus 5q31.1-q35.3 susceptibility locus identified by whole-exome sequencing. - Karolak, Justyna A; Gambin, Tomasz; Pitarque, Jose A; Molinari, Andrea; Jhangiani, Shalini; Stankiewicz, Pawel; Lupski, James R; Gajecka, Marzena (Eur J Hum Genet, 2017)
Keratoconus (KTCN) is a protrusion and thinning of the cornea, resulting in impairment of visual function. The extreme genetic heterogeneity makes it difficult to discover factors unambiguously influencing the KTCN phenotype. In this study, we used whole-exome sequencing (WES) and Sanger sequencing to reduce the number of candidate genes at the 5q31.1-q35.3 locus and to prioritize other potentially relevant variants in an Ecuadorian family with KTCN. We applied WES in two affected KTCN individuals from the Ecuadorian family that showed a suggestive linkage between the KTCN phenotype and the 5q31.1-q35.3 locus. Putative variants identified by WES were further evaluated in this family using Sanger sequencing. Exome capture discovered a total of 173 rare (minor allele frequency <0.001 in control population) nonsynonymous variants in both affected individuals. Among them, 16 SNVs were selected for further evaluation. Segregation analysis revealed that variants c.475T>G in SKP1, c.671G>A in PROB1, and c.527G>A in IL17B in the 5q31.1-q35.3 linkage region, and c.850G>A in HKDC1 in the 10q22 locus completely segregated with the phenotype in the studied KTCN family. We demonstrate that a combination of various techniques significantly narrowed the studied genomic region and reduced the list of the putative exonic variants. Moreover, since this locus overlapped two other chromosomal regions previously recognized in distinct KTCN studies, our findings suggest that this 5q31.1-q35.3 locus might be linked with KTCN.
Keywords: Chromosomes, Human, Pair 5; Exome; Female; Gene Frequency; Genetic Linkage; Genetic Predisposition to Disease; Genome, Human; Hexokinase; High-Throughput Nucleotide Sequencing; Humans; Interleukin-17; Keratoconus; Male; Pedigree; Phenotype; Proteins; S-Phase Kinase-Associated Proteins

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Muzny, Donna; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Exome Sequencing; Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male

Whole Transcriptome Sequencing Analyses Reveal Molecular Markers of Blood Pressure Response to Thiazide Diuretics. - Sá, Ana Caroline C; Webb, Amy; Gong, Yan; McDonough, Caitrin W; Datta, Somnath; Langaee, Taimour Y; Turner, Stephen T; Beitelshees, Amber L; Chapman, Arlene B; Boerwinkle, Eric; Gums, John G; Scherer, Steven E; et al. (Sci Rep, 2017)
Thiazide diuretics (TD) are commonly prescribed anti-hypertensives worldwide. However, <40% of patients treated with thiazide monotherapy achieve BP control. This study uses whole transcriptome sequencing to identify novel molecular markers associated with BP response to TD. We assessed global RNA expression levels in whole blood samples from 150 participants, representing patients in the upper and lower quartile of BP response to TD from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) (50 whites) and from PEAR-2 (50 whites and 50 blacks). In each study cohort, we performed poly-A RNA-sequencing in baseline samples from 25 responders and 25 non-responders to hydrochlorothiazide (HCTZ) or chlorthalidone. At FDR adjusted p-value < 0.05, 29 genes were differentially expressed in relation to HCTZ or chlorthalidone BP response in whites. For each differentially expressed gene, replication was attempted in the alternate white group and PEAR-2 blacks. CEBPD (meta-analysis p = 1.8 × 10) and TSC22D3 (p = 1.9 × 10) were differentially expressed in all 3 cohorts, and explain, in aggregate, 21.9% of response variability to TD. This is the first report of the use of transcriptome-wide sequencing data to identify molecular markers of antihypertensive drug response. These findings support CEBPD and TSC22D3 as potential biomarkers of BP response to TD.
Keywords: Alleles; Biomarkers; Blood Pressure; CCAAT-Enhancer-Binding Protein-delta; Chlorthalidone; Diuretics; Female; Gene Expression Profiling; Gene Expression Regulation; Humans; Hydrochlorothiazide; Logistic Models; Male; Middle Aged; Potassium; Reproducibility of Results; RNA, Messenger; ROC Curve; Transcription Factors; Uric Acid

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Muzny, Donna M; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-genome landscape of pancreatic neuroendocrine tumours. - Scarpa, Aldo; Chang, David K; Nones, Katia; Corbo, Vincenzo; Patch, Ann-Marie; Bailey, Peter; Lawlor, Rita T; Johns, Amber L; Miller, David K; Mafficini, Andrea; Rusev, Borislav; Scardoni, Maria; et al. (Nature, 2017)
The diagnosis of pancreatic neuroendocrine tumours (PanNETs) is increasing owing to more sensitive detection methods, and this increase is creating challenges for clinical management. We performed whole-genome sequencing of 102 primary PanNETs and defined the genomic events that characterize their pathogenesis. Here we describe the mutational signatures they harbour, including a deficiency in G:C > T:A base excision repair due to inactivation of MUTYH, which encodes a DNA glycosylase. Clinically sporadic PanNETs contain a larger-than-expected proportion of germline mutations, including previously unreported mutations in the DNA repair genes MUTYH, CHEK2 and BRCA2. Together with mutations in MEN1 and VHL, these mutations occur in 17% of patients. Somatic mutations, including point mutations and gene fusions, were commonly found in genes involved in four main pathways: chromatin remodelling, DNA damage repair, activation of mTOR signalling (including previously undescribed EWSR1 gene fusions), and telomere maintenance. In addition, our gene expression analyses identified a subgroup of tumours associated with hypoxia and HIF signalling.
Keywords: Base Sequence; Calmodulin-Binding Proteins; Carcinoma, Neuroendocrine; Chromatin Assembly and Disassembly; Chromosome Aberrations; DNA Copy Number Variations; DNA Glycosylases; DNA Mutational Analysis; DNA Repair; Female; Genome, Human; Genomics; Germ-Line Mutation; Humans; Male; Pancreatic Neoplasms; RNA-Binding Protein EWS; RNA-Binding Proteins; Telomere; TOR Serine-Threonine Kinases

Aggressive tumor growth and clinical evolution in a patient with X-linked acro-gigantism syndrome. - Naves, Luciana A; Daly, Adrian F; Dias, Luiz Augusto; Yuan, Bo; Zakir, Juliano Coelho Oliveira; Barra, Gustavo Barcellos; Palmeira, Leonor; Villa, Chiara; Trivellin, Giampaolo; Júnior, Armindo Jreige; Neto, Florêncio Figueiredo Cavalcante; Liu, Pengfei; et al. (Endocrine, 2016)
X-linked acro-gigantism (X-LAG) syndrome is a newly described disease caused by microduplications on chromosome Xq26.3 leading to copy number gain of GPR101. We describe the clinical progress of a sporadic male X-LAG syndrome patient with an Xq26.3 microduplication, highlighting the aggressive natural history of pituitary tumor growth in the absence of treatment. The patient first presented elsewhere aged 5 years 8 months with a history of excessive growth for >2 years. His height was 163 cm, his weight was 36 kg, and he had markedly elevated GH and IGF-1. MRI showed a non-invasive sellar mass measuring 32.5 × 23.9 × 29.1 mm. Treatment was declined and the family was lost to follow-up. At the age of 10 years and 7 months, he presented again with headaches, seizures, and visual disturbance. His height had increased to 197 cm. MRI showed an invasive mass measuring 56.2 × 58.1 × 45.0 mm, with compression of optic chiasma, bilateral cavernous sinus invasion, and hydrocephalus. His thyrotrope, corticotrope, and gonadotrope axes were deficient. Surgery, somatostatin analogs, and cabergoline did not control vertical growth and pegvisomant was added, although vertical growth continues (currently 207 cm at 11 years 7 months of age). X-LAG syndrome is a new genomic disorder in which early-onset pituitary tumorigenesis can lead to marked overgrowth and gigantism. This case illustrates the aggressive nature of tumor evolution and the challenging clinical management in X-LAG syndrome.
Keywords: Adenoma; Child; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Pituitary Neoplasms; Treatment Outcome

Ampullary Cancers Harbor ELF3 Tumor Suppressor Gene Mutations and Exhibit Frequent WNT Dysregulation. - Gingras, Marie-Claude; Covington, Kyle R; Chang, David K; Donehower, Lawrence A; Gill, Anthony J; Ittmann, Michael M; Creighton, Chad J; Johns, Amber L; Shinbrot, Eve; Dewal, Ninad; Fisher, William E; Pilarsky, Christian; et al. (Cell Rep, 2016)
The ampulla of Vater is a complex cellular environment from which adenocarcinomas arise to form a group of histopathologically heterogenous tumors. To evaluate the molecular features of these tumors, 98 ampullary adenocarcinomas were evaluated and compared to 44 distal bile duct and 18 duodenal adenocarcinomas. Genomic analyses revealed mutations in the WNT signaling pathway among half of the patients and in all three adenocarcinomas irrespective of their origin and histological morphology. These tumors were characterized by a high frequency of inactivating mutations of ELF3, a high rate of microsatellite instability, and common focal deletions and amplifications, suggesting common attributes in the molecular pathogenesis are at play in these tumors. The high frequency of WNT pathway activating mutation, coupled with small-molecule inhibitors of β-catenin in clinical trials, suggests future treatment decisions for these patients may be guided by genomic analysis.
Keywords: Adenocarcinoma; Ampulla of Vater; Base Sequence; DNA-Binding Proteins; Duodenal Neoplasms; Genomic Instability; Humans; Microsatellite Repeats; Molecular Sequence Data; Mutation; Pancreatic Neoplasms; Proto-Oncogene Proteins c-ets; Transcription Factors; Wnt Signaling Pathway

Are feeding preferences and insecticide resistance associated with the size of detoxifying enzyme families in insect herbivores? - Rane, Rahul V; Walsh, Tom K; Pearce, Stephen L; Jermiin, Lars S; Gordon, Karl Hj; Richards, Stephen; Oakeshott, John G (Curr Opin Insect Sci, 2016)
The size of gene families associated with xenobiotic detoxification in insects may be associated with the complexity of their diets and their propensities to develop insecticide resistance. We test these hypotheses by collating the annotations of cytochrome P450, carboxyl/cholinesterase and glutathione S-transferase genes in 65 insect species with data on their host use and history of insecticide resistance. We find 2-4 fold variation across the species in the numbers of these genes and, in some orders, especially the Hymenoptera, there is a clear relationship between the numbers of genes and feeding preferences. However in other orders, in particular the Lepidoptera, no such relationship is apparent. The size of these three gene families also tend to correlate with insecticide resistance propensity but this may not be an independent effect because species with broader host ranges are more likely to be pests that are heavily sprayed with insecticides.
Keywords: Animals; Cholinesterases; Cytochrome P-450 Enzyme System; Food Preferences; Glutathione Transferase; Herbivory; Inactivation, Metabolic; Insecta; Insecticide Resistance

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Biallelic Mutations in UNC80 Cause Persistent Hypotonia, Encephalopathy, Growth Retardation, and Severe Intellectual Disability. - Stray-Pedersen, Asbjørg; Cobben, Jan-Maarten; Prescott, Trine E; Lee, Sora; Cang, Chunlei; Aranda, Kimberly; Ahmed, Sohnee; Alders, Marielle; Gerstner, Thorsten; Aslaksen, Kathinka; Tétreault, Martine; Qin, Wen; et al. (Am J Hum Genet, 2016)
Ion channel proteins are required for both the establishment of resting membrane potentials and the generation of action potentials. Hundreds of mutations in genes encoding voltage-gated ion channels responsible for action potential generation have been found to cause severe neurological diseases. In contrast, the roles of voltage-independent "leak" channels, important for the establishment and maintenance of resting membrane potentials upon which action potentials are generated, are not well established in human disease. UNC80 is a large component of the NALCN sodium-leak channel complex that regulates the basal excitability of the nervous system. Loss-of-function mutations of NALCN cause infantile hypotonia with psychomotor retardation and characteristic facies (IHPRF). We report four individuals from three unrelated families who have homozygous missense or compound heterozygous truncating mutations in UNC80 and persistent hypotonia, encephalopathy, growth failure, and severe intellectual disability. Compared to control cells, HEK293T cells transfected with an expression plasmid containing the c.5098C>T (p.Pro1700Ser) UNC80 mutation found in one individual showed markedly decreased NALCN channel currents. Our findings demonstrate the fundamental significance of UNC80 and basal ionic conductance to human health.
Keywords: Adolescent; Alleles; Brain Diseases; Carrier Proteins; Child; Child, Preschool; Female; Growth Disorders; Humans; Intellectual Disability; Membrane Proteins; Muscle Hypotonia; Mutation; Severity of Illness Index

CAV3 mutation in a patient with transient hyperCKemia and myalgia. - Macias, Anna; Gambin, Tomasz; Szafranski, Przemyslaw; Jhangiani, Shalini N; Kolasa, Anna; Obersztyn, Ewa; Lupski, James R; Stankiewicz, Pawel; Kaminska, Anna (Neurol Neurochir Pol, 2016)
Mutations in caveolin-3 (CAV3) can lead to different clinical phenotypes affecting skeletal or cardiac muscles. Here, we describe a patient with Klinefelter syndrome, ulcerative colitis and Sjögren syndrome, who developed transient hyperCKemia, myalgia and mild muscular weakness. Using whole exome sequencing (WES), a missense mutation G169A was found in the CAV3 gene. In addition, we identified a homozygous frameshift deletion in MS4A12 that may contribute to inflammatory bowel disease, further demonstrating usefulness of WES in dual molecular diagnoses.
Keywords: Caveolin 3; Colitis, Ulcerative; Creatine Kinase; Frameshift Mutation; Humans; Klinefelter Syndrome; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Muscle, Skeletal; Muscular Diseases; Mutation, Missense; Myalgia; Phenotype; Sjogren's Syndrome; Thigh

Chromosomal-Level Assembly of the Asian Seabass Genome Using Long Sequence Reads and Multi-layered Scaffolding. - Vij, Shubha; Kuhl, Heiner; Kuznetsova, Inna S; Komissarov, Aleksey; Yurchenko, Andrey A; Van Heusden, Peter; Singh, Siddharth; Thevasagayam, Natascha M; Prakki, Sai Rama Sridatta; Purushothaman, Kathiresan; Saju, Jolly M; Jiang, Junhui; et al. (PLoS Genet, 2016)
We report here the ~670 Mb genome assembly of the Asian seabass (Lates calcarifer), a tropical marine teleost. We used long-read sequencing augmented by transcriptomics, optical and genetic mapping along with shared synteny from closely related fish species to derive a chromosome-level assembly with a contig N50 size over 1 Mb and scaffold N50 size over 25 Mb that span ~90% of the genome. The population structure of L. calcarifer species complex was analyzed by re-sequencing 61 individuals representing various regions across the species' native range. SNP analyses identified high levels of genetic diversity and confirmed earlier indications of a population stratification comprising three clades with signs of admixture apparent in the South-East Asian population. The quality of the Asian seabass genome assembly far exceeds that of any other fish species, and will serve as a new standard for fish genomics.
Keywords: Animals; Bass; Chromosome Mapping; Genome; In Situ Hybridization, Fluorescence; Phylogeny

Clinical Sequencing Exploratory Research Consortium: Accelerating Evidence-Based Practice of Genomic Medicine. - Green, Robert C; Goddard, Katrina A B; Jarvik, Gail P; Amendola, Laura M; Appelbaum, Paul S; Berg, Jonathan S; Bernhardt, Barbara A; Biesecker, Leslie G; Biswas, Sawona; Blout, Carrie L; Bowling, Kevin M; Brothers, Kyle B; et al. (Am J Hum Genet, 2016)
Despite rapid technical progress and demonstrable effectiveness for some types of diagnosis and therapy, much remains to be learned about clinical genome and exome sequencing (CGES) and its role within the practice of medicine. The Clinical Sequencing Exploratory Research (CSER) consortium includes 18 extramural research projects, one National Human Genome Research Institute (NHGRI) intramural project, and a coordinating center funded by the NHGRI and National Cancer Institute. The consortium is exploring analytic and clinical validity and utility, as well as the ethical, legal, and social implications of sequencing via multidisciplinary approaches; it has thus far recruited 5,577 participants across a spectrum of symptomatic and healthy children and adults by utilizing both germline and cancer sequencing. The CSER consortium is analyzing data and creating publically available procedures and tools related to participant preferences and consent, variant classification, disclosure and management of primary and secondary findings, health outcomes, and integration with electronic health records. Future research directions will refine measures of clinical utility of CGES in both germline and somatic testing, evaluate the use of CGES for screening in healthy individuals, explore the penetrance of pathogenic variants through extensive phenotyping, reduce discordances in public databases of genes and variants, examine social and ethnic disparities in the provision of genomics services, explore regulatory issues, and estimate the value and downstream costs of sequencing. The CSER consortium has established a shared community of research sites by using diverse approaches to pursue the evidence-based development of best practices in genomic medicine.
Keywords: Adult; Biomedical Research; Cardiovascular Diseases; Child; Clinical Trials as Topic; Evidence-Based Practice; Exome; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; National Human Genome Research Institute (U.S.); Polymorphism, Single Nucleotide; Population Groups; Software; United States

A comprehensive transcriptional map of primate brain development. - Bakken, Trygve E; Miller, Jeremy A; Ding, Song-Lin; Sunkin, Susan M; Smith, Kimberly A; Ng, Lydia; Szafer, Aaron; Dalley, Rachel A; Royall, Joshua J; Lemon, Tracy; Shapouri, Sheila; Aiona, Kaylynn; et al. (Nature, 2016)
The transcriptional underpinnings of brain development remain poorly understood, particularly in humans and closely related non-human primates. We describe a high-resolution transcriptional atlas of rhesus monkey (Macaca mulatta) brain development that combines dense temporal sampling of prenatal and postnatal periods with fine anatomical division of cortical and subcortical regions associated with human neuropsychiatric disease. Gene expression changes more rapidly before birth, both in progenitor cells and maturing neurons. Cortical layers and areas acquire adult-like molecular profiles surprisingly late in postnatal development. Disparate cell populations exhibit distinct developmental timing of gene expression, but also unexpected synchrony of processes underlying neural circuit construction including cell projection and adhesion. Candidate risk genes for neurodevelopmental disorders including primary microcephaly, autism spectrum disorder, intellectual disability, and schizophrenia show disease-specific spatiotemporal enrichment within developing neocortex. Human developmental expression trajectories are more similar to monkey than rodent, although approximately 9% of genes show human-specific regulation with evidence for prolonged maturation or neoteny compared to monkey.
Keywords: Aging; Animals; Autism Spectrum Disorder; Brain; Cell Adhesion; Conserved Sequence; Female; Humans; Intellectual Disability; Macaca mulatta; Male; Microcephaly; Neocortex; Neurodevelopmental Disorders; Neurogenesis; Risk Factors; Schizophrenia; Spatio-Temporal Analysis; Species Specificity; Transcription, Genetic; Transcriptome

Conditional knockout of retinal determination genes in differentiating cells in Drosophila. - Jin, Meng; Eblimit, Aiden; Pulikkathara, Merlyn; Corr, Stuart; Chen, Rui; Mardon, Graeme (FEBS J, 2016)
Conditional gene knockout in postmitotic cells is a valuable technique which allows the study of gene function with spatiotemporal control. Surprisingly, in contrast to its long-term and extensive use in mouse studies, this technology is lacking in Drosophila. Here, we use a novel method for generating complete loss of eyes absent (eya) or sine oculis (so) function in postmitotic cells posterior to the morphogenetic furrow (MF). Specifically, genomic rescue constructs with flippase recognition target (FRT) sequences flanking essential exons are used to generate conditional null alleles. By removing gene function in differentiating cells, we show that eya and so are dispensable for larval photoreceptor differentiation, but are required for differentiation during pupal development. Both eya and so are necessary for photoreceptor survival and the apoptosis caused by loss of eya or so function is likely a secondary consequence of inappropriate differentiation. We also confirm their requirement for cone cell development and reveal a novel role in interommatidial bristle (IOB) formation. In addition, so is required for normal eye disc morphology. This is the first report of a knockout method to study eya and so function in postmitotic cells. This technology will open the door to a large array of new functional studies in virtually any tissue and at any stage of development or in adults.
Keywords: Alleles; Animals; Cell Differentiation; Drosophila; Drosophila Proteins; Eye; Eye Proteins; Gene Knockout Techniques; Homeodomain Proteins; Larva; Photoreceptor Cells, Invertebrate; Retina

Correction: Chromosomal-Level Assembly of the Asian Seabass Genome Using Long Sequence Reads and Multi-layered Scaffolding. - Vij, Shubha; Kuhl, Heiner; Kuznetsova, Inna S; Komissarov, Aleksey; Yurchenko, Andrey A; Van Heusden, Peter; Singh, Siddharth; Thevasagayam, Natascha M; Prakki, Sai Rama Sridatta; Purushothaman, Kathiresan; Saju, Jolly M; Jiang, Junhui; et al. (PLoS Genet, 2016)
[This corrects the article DOI: 10.1371/journal.pgen.1005954.].

Cross-species identification of genomic drivers of squamous cell carcinoma development across preneoplastic intermediates. - Chitsazzadeh, Vida; Coarfa, Cristian; Drummond, Jennifer A; Nguyen, Tri; Joseph, Aaron; Chilukuri, Suneel; Charpiot, Elizabeth; Adelmann, Charles H; Ching, Grace; Nguyen, Tran N; Nicholas, Courtney; Thomas, Valencia D; et al. (Nat Commun, 2016)
Cutaneous squamous cell carcinoma (cuSCC) comprises 15-20% of all skin cancers, accounting for over 700,000 cases in USA annually. Most cuSCC arise in association with a distinct precancerous lesion, the actinic keratosis (AK). To identify potential targets for molecularly targeted chemoprevention, here we perform integrated cross-species genomic analysis of cuSCC development through the preneoplastic AK stage using matched human samples and a solar ultraviolet radiation-driven Hairless mouse model. We identify the major transcriptional drivers of this progression sequence, showing that the key genomic changes in cuSCC development occur in the normal skin to AK transition. Our data validate the use of this ultraviolet radiation-driven mouse cuSCC model for cross-species analysis and demonstrate that cuSCC bears deep molecular similarities to multiple carcinogen-driven SCCs from diverse sites, suggesting that cuSCC may serve as an effective, accessible model for multiple SCC types and that common treatment and prevention strategies may be feasible.
Keywords: Animals; Antineoplastic Agents; Carcinogenesis; Carcinoma, Squamous Cell; Disease Progression; DNA Mutational Analysis; Exome Sequencing; Female; Gene Expression Profiling; Genomics; High-Throughput Nucleotide Sequencing; Humans; Keratosis, Actinic; Mice; Mice, Hairless; Molecular Targeted Therapy; Precancerous Conditions; Sequence Analysis, RNA; Skin; Skin Neoplasms; Ultraviolet Rays

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

Diagnostic Yield of Clinical Tumor and Germline Whole-Exome Sequencing for Children With Solid Tumors. - Parsons, D Williams; Roy, Angshumoy; Yang, Yaping; Wang, Tao; Scollon, Sarah; Bergstrom, Katie; Kerstein, Robin A; Gutierrez, Stephanie; Petersen, Andrea K; Bavle, Abhishek; Lin, Frank Y; López-Terrada, Dolores H; et al. (JAMA Oncol, 2016)
IMPORTANCE: Whole-exome sequencing (WES) has the potential to reveal tumor and germline mutations of clinical relevance, but the diagnostic yield for pediatric patients with solid tumors is unknown. OBJECTIVE: To characterize the diagnostic yield of combined tumor and germline WES for children with solid tumors. DESIGN: Unselected children with newly diagnosed and previously untreated central nervous system (CNS) and non-CNS solid tumors were prospectively enrolled in the BASIC3 study at a large academic children's hospital during a 23-month period from August 2012 through June 2014. Blood and tumor samples underwent WES in a certified clinical laboratory with genetic results categorized on the basis of perceived clinical relevance and entered in the electronic health record. MAIN OUTCOMES AND MEASURES: Clinical categorization of somatic mutations; frequencies of deleterious germline mutations related to patient phenotype and incidental medically-actionable mutations. RESULTS: Of the first 150 participants (80 boys and 70 girls, mean age, 7.4 years), tumor samples adequate for WES were available from 121 patients (81%). Somatic mutations of established clinical utility (category I) were reported in 4 (3%) of 121 patients, with mutations of potential utility (category II) detected in an additional 29 (24%) of 121 patients. CTNNB1 was the gene most frequently mutated, with recurrent mutations in KIT, TSC2, and MAPK pathway genes (BRAF, KRAS, and NRAS) also identified. Mutations in consensus cancer genes (category III) were found in an additional 24 (20%) of 121 tumors. Fewer than half of somatic mutations identified were in genes known to be recurrently mutated in the tumor type tested. Diagnostic germline findings related to patient phenotype were discovered in 15 (10%) of 150 cases: 13 pathogenic or likely pathogenic dominant mutations in adult and pediatric cancer susceptibility genes (including 2 each in TP53, VHL, and BRCA1), 1 recessive liver disorder with hepatocellular carcinoma (TJP2), and 1 renal diagnosis (CLCN5). Incidental findings were reported in 8 (5%) of 150 patients. Most patients harbored germline uncertain variants in cancer genes (98%), pharmacogenetic variants (89%), and recessive carrier mutations (85%). CONCLUSIONS AND RELEVANCE: Tumor and germline WES revealed mutations in a broad spectrum of genes previously implicated in both adult and pediatric cancers. Combined reporting of tumor and germline WES identified diagnostic and/or potentially actionable findings in nearly 40% of newly diagnosed pediatric patients with solid tumors.

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.
Keywords: Alleles; Basic Helix-Loop-Helix Transcription Factors; Black or African American; Chromosomes, Human, Pair 5; DNA Methylation; Female; Gene Expression Regulation; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Failure; HEK293 Cells; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Cytokine

DNA methylation-based measures of biological age: meta-analysis predicting time to death. - Chen, Brian H; Marioni, Riccardo E; Colicino, Elena; Peters, Marjolein J; Ward-Caviness, Cavin K; Tsai, Pei-Chien; Roetker, Nicholas S; Just, Allan C; Demerath, Ellen W; Guan, Weihua; Bressler, Jan; Fornage, Myriam; et al. (Aging (Albany NY), 2016)
Estimates of biological age based on DNA methylation patterns, often referred to as "epigenetic age", "DNAm age", have been shown to be robust biomarkers of age in humans. We previously demonstrated that independent of chronological age, epigenetic age assessed in blood predicted all-cause mortality in four human cohorts. Here, we expanded our original observation to 13 different cohorts for a total sample size of 13,089 individuals, including three racial/ethnic groups. In addition, we examined whether incorporating information on blood cell composition into the epigenetic age metrics improves their predictive power for mortality. All considered measures of epigenetic age acceleration were predictive of mortality (p≤8.2x10, independent of chronological age, even after adjusting for additional risk factors (p<5.4x10, and within the racial/ethnic groups that we examined (non-Hispanic whites, Hispanics, African Americans). Epigenetic age estimates that incorporated information on blood cell composition led to the smallest p-values for time to death (p=7.5x10). Overall, this study a) strengthens the evidence that epigenetic age predicts all-cause mortality above and beyond chronological age and traditional risk factors, and b) demonstrates that epigenetic age estimates that incorporate information on blood cell counts lead to highly significant associations with all-cause mortality.
Keywords: Aging; DNA Methylation; Epigenesis, Genetic; Female; Humans; Logistic Models; Male; Mortality; Racial Groups; Risk Factors; Survival Analysis; T-Lymphocyte Subsets

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.
Keywords: Allelic Imbalance; Black or African American; Erythrocyte Indices; Erythrocytes; Erythropoiesis; Exome; Gene Frequency; Genetic Pleiotropy; Genetic Variation; Genotype; Hematocrit; Hemoglobins; Humans; Quantitative Trait Loci

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Muzny, Donna M; Doddapaneni, Harsha; Hu, Jianhong; Boerwinkle, Eric; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Genome of the Asian longhorned beetle (Anoplophora glabripennis), a globally significant invasive species, reveals key functional and evolutionary innovations at the beetle-plant interface. - McKenna, Duane D; Scully, Erin D; Pauchet, Yannick; Hoover, Kelli; Kirsch, Roy; Geib, Scott M; Mitchell, Robert F; Waterhouse, Robert M; Ahn, Seung-Joon; Arsala, Deanna; Benoit, Joshua B; Blackmon, Heath; et al. (Genome Biol, 2016)
BACKGROUND: Relatively little is known about the genomic basis and evolution of wood-feeding in beetles. We undertook genome sequencing and annotation, gene expression assays, studies of plant cell wall degrading enzymes, and other functional and comparative studies of the Asian longhorned beetle, Anoplophora glabripennis, a globally significant invasive species capable of inflicting severe feeding damage on many important tree species. Complementary studies of genes encoding enzymes involved in digestion of woody plant tissues or detoxification of plant allelochemicals were undertaken with the genomes of 14 additional insects, including the newly sequenced emerald ash borer and bull-headed dung beetle. RESULTS: The Asian longhorned beetle genome encodes a uniquely diverse arsenal of enzymes that can degrade the main polysaccharide networks in plant cell walls, detoxify plant allelochemicals, and otherwise facilitate feeding on woody plants. It has the metabolic plasticity needed to feed on diverse plant species, contributing to its highly invasive nature. Large expansions of chemosensory genes involved in the reception of pheromones and plant kairomones are consistent with the complexity of chemical cues it uses to find host plants and mates. CONCLUSIONS: Amplification and functional divergence of genes associated with specialized feeding on plants, including genes originally obtained via horizontal gene transfer from fungi and bacteria, contributed to the addition, expansion, and enhancement of the metabolic repertoire of the Asian longhorned beetle, certain other phytophagous beetles, and to a lesser degree, other phytophagous insects. Our results thus begin to establish a genomic basis for the evolutionary success of beetles on plants.
Keywords: Animals; Coleoptera; Evolution, Molecular; Gene Transfer, Horizontal; Genome, Insect; Host-Parasite Interactions; Introduced Species; Larva; Sequence Analysis, DNA; Trees

Genome Sequencing of the Phytoseiid Predatory Mite Metaseiulus occidentalis Reveals Completely Atomized Hox Genes and Superdynamic Intron Evolution. - Hoy, Marjorie A; Waterhouse, Robert M; Wu, Ke; Estep, Alden S; Ioannidis, Panagiotis; Palmer, William J; Pomerantz, Aaron F; Simão, Felipe A; Thomas, Jainy; Jiggins, Francis M; Murphy, Terence D; Pritham, Ellen J; et al. (Genome Biol Evol, 2016)
Metaseiulus occidentalis is an eyeless phytoseiid predatory mite employed for the biological control of agricultural pests including spider mites. Despite appearances, these predator and prey mites are separated by some 400 Myr of evolution and radically different lifestyles. We present a 152-Mb draft assembly of the M. occidentalis genome: Larger than that of its favored prey, Tetranychus urticae, but considerably smaller than those of many other chelicerates, enabling an extremely contiguous and complete assembly to be built-the best arachnid to date. Aided by transcriptome data, genome annotation cataloged 18,338 protein-coding genes and identified large numbers of Helitron transposable elements. Comparisons with other arthropods revealed a particularly dynamic and turbulent genomic evolutionary history. Its genes exhibit elevated molecular evolution, with strikingly high numbers of intron gains and losses, in stark contrast to the deer tick Ixodes scapularis Uniquely among examined arthropods, this predatory mite's Hox genes are completely atomized, dispersed across the genome, and it encodes five copies of the normally single-copy RNA processing Dicer-2 gene. Examining gene families linked to characteristic biological traits of this tiny predator provides initial insights into processes of sex determination, development, immune defense, and how it detects, disables, and digests its prey. As the first reference genome for the Phytoseiidae, and for any species with the rare sex determination system of parahaploidy, the genome of the western orchard predatory mite improves genomic sampling of chelicerates and provides invaluable new resources for functional genomic analyses of this family of agriculturally important mites.
Keywords: Acari; Animals; Genes, Homeobox; Genome; Genomics; High-Throughput Nucleotide Sequencing; Introns; Pest Control, Biological; Tetranychidae; Transcriptome

Genomic analyses identify molecular subtypes of pancreatic cancer. - Bailey, Peter; Chang, David K; Nones, Katia; Johns, Amber L; Patch, Ann-Marie; Marie-Claude Gingras; Miller, David K; Christ, Angelika N; Bruxner, Tim J C; Quinn, Michael C; Nourse, Craig; Murtaugh, L Charles; et al. (Nature, 2016)
Integrated genomic analysis of 456 pancreatic ductal adenocarcinomas identified 32 recurrently mutated genes that aggregate into 10 pathways: KRAS, TGF-β, WNT, NOTCH, ROBO/SLIT signalling, G1/S transition, SWI-SNF, chromatin modification, DNA repair and RNA processing. Expression analysis defined 4 subtypes: (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine (ADEX) that correlate with histopathological characteristics. Squamous tumours are enriched for TP53 and KDM6A mutations, upregulation of the TP63∆N transcriptional network, hypermethylation of pancreatic endodermal cell-fate determining genes and have a poor prognosis. Pancreatic progenitor tumours preferentially express genes involved in early pancreatic development (FOXA2/3, PDX1 and MNX1). ADEX tumours displayed upregulation of genes that regulate networks involved in KRAS activation, exocrine (NR5A2 and RBPJL), and endocrine differentiation (NEUROD1 and NKX2-2). Immunogenic tumours contained upregulated immune networks including pathways involved in acquired immune suppression. These data infer differences in the molecular evolution of pancreatic cancer subtypes and identify opportunities for therapeutic development.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Carcinoma, Pancreatic Ductal; Cell Line, Tumor; DNA Methylation; DNA-Binding Proteins; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genes, Neoplasm; Genome, Human; Genomics; Hepatocyte Nuclear Factor 3-beta; Hepatocyte Nuclear Factor 3-gamma; Histone Demethylases; Homeobox Protein Nkx-2.2; Homeodomain Proteins; Humans; Mice; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Prognosis; Receptors, Cytoplasmic and Nuclear; Survival Analysis; Trans-Activators; Transcription Factors; Transcription, Genetic; Transcriptome; Tumor Suppressor Protein p53; Tumor Suppressor Proteins; Zebrafish Proteins

A genomic approach to therapeutic target validation identifies a glucose-lowering GLP1R variant protective for coronary heart disease. - Scott, Robert A; Freitag, Daniel F; Li, Li; Chu, Audrey Y; Surendran, Praveen; Young, Robin; Grarup, Niels; Stančáková, Alena; Chen, Yuning; Varga, Tibor V; Yaghootkar, Hanieh; Luan, Jian'an; et al. (Sci Transl Med, 2016)
Regulatory authorities have indicated that new drugs to treat type 2 diabetes (T2D) should not be associated with an unacceptable increase in cardiovascular risk. Human genetics may be able to guide development of antidiabetic therapies by predicting cardiovascular and other health endpoints. We therefore investigated the association of variants in six genes that encode drug targets for obesity or T2D with a range of metabolic traits in up to 11,806 individuals by targeted exome sequencing and follow-up in 39,979 individuals by targeted genotyping, with additional in silico follow-up in consortia. We used these data to first compare associations of variants in genes encoding drug targets with the effects of pharmacological manipulation of those targets in clinical trials. We then tested the association of those variants with disease outcomes, including coronary heart disease, to predict cardiovascular safety of these agents. A low-frequency missense variant (Ala316Thr; rs10305492) in the gene encoding glucagon-like peptide-1 receptor (GLP1R), the target of GLP1R agonists, was associated with lower fasting glucose and T2D risk, consistent with GLP1R agonist therapies. The minor allele was also associated with protection against heart disease, thus providing evidence that GLP1R agonists are not likely to be associated with an unacceptable increase in cardiovascular risk. Our results provide an encouraging signal that these agents may be associated with benefit, a question currently being addressed in randomized controlled trials. Genetic variants associated with metabolic traits and multiple disease outcomes can be used to validate therapeutic targets at an early stage in the drug development process.
Keywords: Alleles; Coronary Disease; Diabetes Mellitus, Type 2; Dipeptidyl Peptidase 4; Genotype; Glucagon-Like Peptide-1 Receptor; Humans; Obesity; Receptor, Cannabinoid, CB2; Receptor, Serotonin, 5-HT2C; Receptors, Somatostatin; Sodium-Glucose Transporter 1

Germline or somatic GPR101 duplication leads to X-linked acrogigantism: a clinico-pathological and genetic study. - Iacovazzo, Donato; Caswell, Richard; Bunce, Benjamin; Jose, Sian; Yuan, Bo; Hernández-Ramírez, Laura C; Kapur, Sonal; Caimari, Francisca; Evanson, Jane; Ferraù, Francesco; Dang, Mary N; Gabrovska, Plamena; et al. (Acta Neuropathol Commun, 2016)
Non-syndromic pituitary gigantism can result from AIP mutations or the recently identified Xq26.3 microduplication causing X-linked acrogigantism (XLAG). Within Xq26.3, GPR101 is believed to be the causative gene, and the c.924G > C (p.E308D) variant in this orphan G protein-coupled receptor has been suggested to play a role in the pathogenesis of acromegaly.We studied 153 patients (58 females and 95 males) with pituitary gigantism. AIP mutation-negative cases were screened for GPR101 duplication through copy number variation droplet digital PCR and high-density aCGH. The genetic, clinical and histopathological features of XLAG patients were studied in detail. 395 peripheral blood and 193 pituitary tumor DNA samples from acromegaly patients were tested for GPR101 variants.We identified 12 patients (10 females and 2 males; 7.8 %) with XLAG. In one subject, the duplicated region only contained GPR101, but not the other three genes in found to be duplicated in the previously reported patients, defining a new smallest region of overlap of duplications. While females presented with germline mutations, the two male patients harbored the mutation in a mosaic state. Nine patients had pituitary adenomas, while three had hyperplasia. The comparison of the features of XLAG, AIP-positive and GPR101&AIP-negative patients revealed significant differences in sex distribution, age at onset, height, prolactin co-secretion and histological features. The pathological features of XLAG-related adenomas were remarkably similar. These tumors had a sinusoidal and lobular architecture. Sparsely and densely granulated somatotrophs were admixed with lactotrophs; follicle-like structures and calcifications were commonly observed. Patients with sporadic of familial acromegaly did not have an increased prevalence of the c.924G > C (p.E308D) GPR101 variant compared to public databases.In conclusion, XLAG can result from germline or somatic duplication of GPR101. Duplication of GPR101 alone is sufficient for the development of XLAG, implicating it as the causative gene within the Xq26.3 region. The pathological features of XLAG-associated pituitary adenomas are typical and, together with the clinical phenotype, should prompt genetic testing.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Female; Gene Duplication; Germ-Line Mutation; Gigantism; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Pituitary Neoplasms; Receptors, G-Protein-Coupled; Treatment Outcome; Young Adult

Hutterite-type cataract maps to chromosome 6p21.32-p21.31, cosegregates with a homozygous mutation in LEMD2, and is associated with sudden cardiac death. - Boone, Philip M; Yuan, Bo; Gu, Shen; Ma, Zhiwei; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Jain, Mahim; Murdock, Todd J; White, Janson J; Jhangiani, Shalini N; Walker, Kimberly; Wang, Qiaoyan; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Juvenile-onset cataracts are known among the Hutterites of North America. Despite being identified over 30 years ago, this autosomal recessive condition has not been mapped, and the disease gene is unknown. METHODS: We performed whole exome sequencing of three Hutterite-type cataract trios and follow-up genotyping and mapping in four extended kindreds. RESULTS: Trio exomes enabled genome-wide autozygosity mapping, which localized the disease gene to a 9.5-Mb region on chromosome 6p. This region contained two candidate variants, LEMD2 c.T38G and MUC21 c.665delC. Extended pedigrees recruited for variant genotyping revealed multiple additional relatives with juvenile-onset cataract, as well as six deceased relatives with both cataracts and sudden cardiac death. The candidate variants were genotyped in 84 family members, including 17 with cataracts; only the variant in LEMD2 cosegregated with cataracts (LOD = 9.62). SNP-based fine mapping within the 9.5 Mb linked region supported this finding by refining the cataract locus to a 0.5- to 2.9-Mb subregion (6p21.32-p21.31) containing LEMD2 but not MUC21. LEMD2 is expressed in mouse and human lenses and encodes a LEM domain-containing protein; the c.T38G missense mutation is predicted to mutate a highly conserved residue within this domain (p.Leu13Arg). CONCLUSION: We performed a genetic and genomic study of Hutterite-type cataract and found evidence for an association of this phenotype with sudden cardiac death. Using combined genetic and genomic approaches, we mapped cataracts to a small portion of chromosome 6 and propose that they result from a homozygous missense mutation in LEMD2.

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Membrane Proteins; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

Identification of novel direct targets of Drosophila Sine oculis and Eyes absent by integration of genome-wide data sets. - Jin, Meng; Aibar, Sara; Ge, Zhongqi; Chen, Rui; Aerts, Stein; Mardon, Graeme (Dev Biol, 2016)
Drosophila eye development is a complex process that involves many transcription factors (TFs) and interactions with their cofactors and targets. The TF Sine oculis (So) and its cofactor Eyes absent (Eya) are highly conserved and are both necessary and sufficient for eye development. Despite their many important roles during development, the direct targets of So are still largely unknown. Therefore the So-dependent regulatory network governing eye determination and differentiation is poorly understood. In this study, we intersected gene expression profiles of so or eya mutant eye tissue prepared from three different developmental stages and identified 1731 differentially expressed genes across the Drosophila genome. A combination of co-expression analyses and motif discovery identified a set of twelve putative direct So targets, including three known and nine novel targets. We also used our previous So ChIP-seq data to assess motif predictions for So and identified a canonical So binding motif. Finally, we performed in vivo enhancer reporter assays to test predicted enhancers from six candidate target genes and find that at least one enhancer from each gene is expressed in the developing eye disc and that their expression patterns overlap with that of So. We furthermore confirmed that the expression level of predicted direct So targets, for which antibodies are available, are reduced in so or eya post-mitotic knockout eye discs. In summary, we expand the set of putative So targets and show for the first time that the combined use of expression profiling of so with its cofactor eya is an effective method to identify novel So targets. Moreover, since So is highly conserved throughout the metazoa, our results provide the basis for future functional studies in a wide variety of organisms.
Keywords: Amino Acid Motifs; Amino Acid Sequence; Animals; Chromatin Immunoprecipitation; Compound Eye, Arthropod; Consensus Sequence; Drosophila melanogaster; Drosophila Proteins; Eye Proteins; Gene Expression Regulation, Developmental; Gene Ontology; Genetic Association Studies; Genome-Wide Association Study; Homeodomain Proteins; Imaginal Discs; Larva; Pupa; RNA, Messenger; Transcription, Genetic; Transcriptome

Integrated tumor and germline whole-exome sequencing identifies mutations in MAPK and PI3K pathway genes in an adolescent with rosette-forming glioneuronal tumor of the fourth ventricle. - Lin, Frank Y; Bergstrom, Katie; Person, Richard; Bavle, Abhishek; Ballester, Leomar Y; Scollon, Sarah; Raesz-Martinez, Robin; Jea, Andrew; Birchansky, Sherri; Wheeler, David A; Berg, Stacey L; Chintagumpala, Murali M; et al. (Cold Spring Harb Mol Case Stud, 2016)
The integration of genome-scale studies such as whole-exome sequencing (WES) into the clinical care of children with cancer has the potential to provide insight into the genetic basis of an individual's cancer with implications for clinical management. This report describes the results of clinical tumor and germline WES for a patient with a rare tumor diagnosis, rosette-forming glioneuronal tumor of the fourth ventricle (RGNT). Three pathogenic gene alterations with implications for clinical care were identified: somatic activating hotspot mutations in FGFR1 (p.N546K) and PIK3CA (p.H1047R) and a germline pathogenic variant in PTPN11 (p.N308S) diagnostic for Noonan syndrome. The molecular landscape of RGNT is not well-described, but these data are consistent with prior observations regarding the importance of the interconnected MAPK and PI3K/AKT/mTOR signaling pathways in this rare tumor. The co-occurrence of FGFR1, PIK3CA, and PTPN11 alterations provides further evidence for consideration of RGNT as a distinct molecular entity from pediatric low-grade gliomas and suggests potential therapeutic strategies for this patient in the event of tumor recurrence as novel agents targeting these pathways enter pediatric clinical trials. Although RGNT has not been definitively linked with cancer predisposition syndromes, two prior cases have been reported in patients with RASopathies (Noonan syndrome and neurofibromatosis type 1 [NF1]), providing an additional link between these tumors and the mitogen-activated protein kinase (MAPK) signaling pathway. In summary, this case provides an example of the potential for genome-scale sequencing technologies to provide insight into the biology of rare tumors and yield both tumor and germline results of potential relevance to patient care.

Integrative subcellular proteomic analysis allows accurate prediction of human disease-causing genes. - Zhao, Li; Chen, Yiyun; Bajaj, Amol Onkar; Eblimit, Aiden; Xu, Mingchu; Soens, Zachry T; Wang, Feng; Ge, Zhongqi; Jung, Sung Yun; He, Feng; Li, Yumei; Wensel, Theodore G; et al. (Genome Res, 2016)
Proteomic profiling on subcellular fractions provides invaluable information regarding both protein abundance and subcellular localization. When integrated with other data sets, it can greatly enhance our ability to predict gene function genome-wide. In this study, we performed a comprehensive proteomic analysis on the light-sensing compartment of photoreceptors called the outer segment (OS). By comparing with the protein profile obtained from the retina tissue depleted of OS, an enrichment score for each protein is calculated to quantify protein subcellular localization, and 84% accuracy is achieved compared with experimental data. By integrating the protein OS enrichment score, the protein abundance, and the retina transcriptome, the probability of a gene playing an essential function in photoreceptor cells is derived with high specificity and sensitivity. As a result, a list of genes that will likely result in human retinal disease when mutated was identified and validated by previous literature and/or animal model studies. Therefore, this new methodology demonstrates the synergy of combining subcellular fractionation proteomics with other omics data sets and is generally applicable to other tissues and diseases.
Keywords: Animals; Eye Proteins; Gene Expression Profiling; Humans; Mice; Photoreceptor Cells; Proteomics; Retinal Diseases; Transcriptome

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.
Keywords: Blood Cell Count; Exome; Genetic Loci; Genetic Pleiotropy; Genome-Wide Association Study; Humans; Immune System Diseases; Leukocytes; Quality Control

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.
Keywords: Angiopoietin-Like Protein 4; Angiopoietins; Exons; Fasting; Female; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gozde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Membrane Proteins; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Multiallelic Positions in the Human Genome: Challenges for Genetic Analyses. - Campbell, Ian M; Gambin, Tomasz; Jhangiani, Shalini; Grove, Megan L; Veeraraghavan, Narayanan; Donna M Muzny; Shaw, Chad A; Richard A Gibbs; Eric Boerwinkle; Fuli Yu; Lupski, James R (Hum Mutat, 2016)
As the amount of human genomic sequence available from personal genomes and exomes has increased, so too has the observation of genomic positions having two or more alternative alleles, so-called multiallelic sites. For portions of the haploid genome that are present in more than one copy, including segmental duplications, variation at such multisite variant positions becomes even more complex. Despite the frequency of multiallelic variants, a number of commonly used resources and tools in genomic research and diagnostics do not support these multiallelic variants all together or require special modifications. Here, we explore the frequency of multiallelic sites in large samples with whole exome sequencing and discuss potential outcomes of failing to account for multiple variant alleles. We also briefly discuss some commonly utilized resources that fully support multiallelic sites.
Keywords: Alleles; Exome; Genome, Human; Humans

Multifaceted biological insights from a draft genome sequence of the tobacco hornworm moth, Manduca sexta. - Kanost, Michael R; Arrese, Estela L; Cao, Xiaolong; Chen, Yun-Ru; Chellapilla, Sanjay; Goldsmith, Marian R; Grosse-Wilde, Ewald; Heckel, David G; Herndon, Nicolae; Jiang, Haobo; Papanicolaou, Alexie; Qu, Jiaxin; et al. (Insect Biochem Mol Biol, 2016)
Manduca sexta, known as the tobacco hornworm or Carolina sphinx moth, is a lepidopteran insect that is used extensively as a model system for research in insect biochemistry, physiology, neurobiology, development, and immunity. One important benefit of this species as an experimental model is its extremely large size, reaching more than 10 g in the larval stage. M. sexta larvae feed on solanaceous plants and thus must tolerate a substantial challenge from plant allelochemicals, including nicotine. We report the sequence and annotation of the M. sexta genome, and a survey of gene expression in various tissues and developmental stages. The Msex_1.0 genome assembly resulted in a total genome size of 419.4 Mbp. Repetitive sequences accounted for 25.8% of the assembled genome. The official gene set is comprised of 15,451 protein-coding genes, of which 2498 were manually curated. Extensive RNA-seq data from many tissues and developmental stages were used to improve gene models and for insights into gene expression patterns. Genome wide synteny analysis indicated a high level of macrosynteny in the Lepidoptera. Annotation and analyses were carried out for gene families involved in a wide spectrum of biological processes, including apoptosis, vacuole sorting, growth and development, structures of exoskeleton, egg shells, and muscle, vision, chemosensation, ion channels, signal transduction, neuropeptide signaling, neurotransmitter synthesis and transport, nicotine tolerance, lipid metabolism, and immunity. This genome sequence, annotation, and analysis provide an important new resource from a well-studied model insect species and will facilitate further biochemical and mechanistic experimental studies of many biological systems in insects.
Keywords: Animals; Gene Expression; Gene Expression Profiling; Genome, Insect; Larva; Manduca; Pupa; Sequence Analysis, DNA; Synteny

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

Novel genetic causes for cerebral visual impairment. - Bosch, Daniëlle G M; Boonstra, F Nienke; de Leeuw, Nicole; Pfundt, Rolph; Nillesen, Willy M; de Ligt, Joep; Gilissen, Christian; Jhangiani, Shalini; Lupski, James R; Cremers, Frans P M; de Vries, Bert B A (Eur J Hum Genet, 2016)
Cerebral visual impairment (CVI) is a major cause of low vision in children due to impairment in projection and/or interpretation of the visual input in the brain. Although acquired causes for CVI are well known, genetic causes underlying CVI are largely unidentified. DNAs of 25 patients with CVI and intellectual disability, but without acquired (eg, perinatal) damage, were investigated by whole-exome sequencing. The data were analyzed for de novo, autosomal-recessive, and X-linked variants, and subsequently classified into known, candidate, or unlikely to be associated with CVI. This classification was based on the Online Mendelian Inheritance in Man database, literature reports, variant characteristics, and functional relevance of the gene. After classification, variants in four genes known to be associated with CVI (AHDC1, NGLY1, NR2F1, PGAP1) in 5 patients (20%) were identified, establishing a conclusive genetic diagnosis for CVI. In addition, in 11 patients (44%) with CVI, variants in one or more candidate genes were identified (ACP6, AMOT, ARHGEF10L, ATP6V1A, DCAF6, DLG4, GABRB2, GRIN1, GRIN2B, KCNQ3, KCTD19, RERE, SLC1A1, SLC25A16, SLC35A2, SOX5, UFSP2, UHMK1, ZFP30). Our findings show that diverse genetic causes underlie CVI, some of which will provide insight into the biology underlying this disease process.
Keywords: Adolescent; Blindness, Cortical; Child; Child, Preschool; Female; Genetic Loci; Humans; Male; Polymorphism, Single Nucleotide; Young Adult

Novel mutations in LRP6 highlight the role of WNT signaling in tooth agenesis. - Ockeloen, Charlotte W; Khandelwal, Kriti D; Dreesen, Karoline; Ludwig, Kerstin U; Sullivan, Robert; van Rooij, Iris A L M; Thonissen, Michelle; Swinnen, Steven; Phan, Milien; Conte, Federica; Ishorst, Nina; Gilissen, Christian; et al. (Genet Med, 2016)
PURPOSE: We aimed to identify a novel genetic cause of tooth agenesis (TA) and/or orofacial clefting (OFC) by combining whole-exome sequencing (WES) and targeted resequencing in a large cohort of TA and OFC patients. METHODS: WES was performed in two unrelated patients: one with severe TA and OFC and another with severe TA only. After deleterious mutations were identified in a gene encoding low-density lipoprotein receptor-related protein 6 (LRP6), all its exons were resequenced with molecular inversion probes in 67 patients with TA, 1,072 patients with OFC, and 706 controls. RESULTS: We identified a frameshift (c.4594delG, p.Cys1532fs) and a canonical splice-site mutation (c.3398-2A>C, p.?) in LRP6, respectively, in the patient with TA and OFC and in the patient with severe TA only. The targeted resequencing showed significant enrichment of unique LRP6 variants in TA patients but not in nonsyndromic OFC patients. Of the five variants in patients with TA, two affected the canonical splice site and three were missense variants; all variants segregated with the dominant phenotype, and in one case the missense mutation occurred de novo. CONCLUSION: Mutations in LRP6 cause TA in humans.Genet Med 18 11, 1158-1162.
Keywords: Adolescent; Anodontia; Child; Exome; Female; Frameshift Mutation; Genetic Predisposition to Disease; Humans; Low Density Lipoprotein Receptor-Related Protein-6; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Wnt Signaling Pathway

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Muzny, Donna M; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Boerwinkle, Eric; Gibbs, Richard A; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Phenotypic Expansion of Congenital Disorder of Glycosylation Due to SRD5A3 Null Mutation. - Tuysuz, Beyhan; Pehlivan, Davut; Özkök, Ahmet; Jhangiani, Shalini; Yalcinkaya, Cengiz; Zeybek, Çiğdem Aktuğlu; Muzny, Donna Marie; Lupski, James R; Gibbs, Richard; Jaeken, Jaak (JIMD Rep, 2016)
We present a boy, admitted at 4 months, with facial dysmorphism, hypertrichosis, loose skin, bilateral inguinal hernia, severe hypotonia, psychomotor disability, seizures with hypsarrhythmia (West syndrome), hepatosplenomegaly, increased serum transaminases, iris coloboma, glaucoma, corneal clouding and bilateral dilated lateral ventricles, and extra-axial post-cerebellar space. Serum transferrin isoelectrofocusing (IEF) showed a type 1 pattern. Whole-exome genotyping showed a previously reported homozygous nonsense mutation c.320G>A; p.Trp107X in SRD5A3. Epilepsy and glaucoma have been reported only once in the 19 described SRD5A3-congenital glycosylation defect patients, and corneal clouding not at all.

Phenotypic expansion of TBX4 mutations to include acinar dysplasia of the lungs. - Szafranski, Przemyslaw; Coban-Akdemir, Zeynep H; Rupps, Rosemarie; Grazioli, Serge; Wensley, David; Jhangiani, Shalini N; Popek, Edwina; Lee, Anna F; Lupski, James R; Boerkoel, Cornelius F; Stankiewicz, Paweł (Am J Med Genet A, 2016)
Mutations in the T-box transcription factor TBX4 gene have been reported in patients with Ischiocoxopodopatellar syndrome (MIM# 147891) and childhood-onset pulmonary arterial hypertension. Whole exome sequencing of DNA from a 1 day old deceased newborn, with severe diffuse developmental lung disorder exhibiting features of acinar dysplasia, and her unaffected parents identified a de novo TBX4 missense mutation p.E86Q (c.256G>C) in the DNA-binding T-box domain. We propose phenotypic expansion of the TBX4-related clinical disease spectrum to include acinar dysplasia of the lungs. The reported mutation is the first identified genetic variant causative for acinar dysplasia. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Autopsy; Chromosomes, Human, Pair 16; DNA Copy Number Variations; DNA Mutational Analysis; Fatal Outcome; Female; Genetic Association Studies; Genotype; Heterozygote; Humans; Infant, Newborn; Karyotype; Lung; Mutation; Pedigree; Phenotype; Radiography, Thoracic; T-Box Domain Proteins

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.
Keywords: Blood Platelets; Exome; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Mean Platelet Volume; Platelet Count

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

The population genomics of rhesus macaques (Macaca mulatta) based on whole-genome sequences. - Xue, Cheng; Raveendran, Muthuswamy; Harris, R Alan; Fawcett, Gloria L; Liu, Xiaoming; White, Simon; Dahdouli, Mahmoud; Rio Deiros, David; Below, Jennifer E; Salerno, William; Cox, Laura; Fan, Guoping; et al. (Genome Res, 2016)
Rhesus macaques (Macaca mulatta) are the most widely used nonhuman primate in biomedical research, have the largest natural geographic distribution of any nonhuman primate, and have been the focus of much evolutionary and behavioral investigation. Consequently, rhesus macaques are one of the most thoroughly studied nonhuman primate species. However, little is known about genome-wide genetic variation in this species. A detailed understanding of extant genomic variation among rhesus macaques has implications for the use of this species as a model for studies of human health and disease, as well as for evolutionary population genomics. Whole-genome sequencing analysis of 133 rhesus macaques revealed more than 43.7 million single-nucleotide variants, including thousands predicted to alter protein sequences, transcript splicing, and transcription factor binding sites. Rhesus macaques exhibit 2.5-fold higher overall nucleotide diversity and slightly elevated putative functional variation compared with humans. This functional variation in macaques provides opportunities for analyses of coding and noncoding variation, and its cellular consequences. Despite modestly higher levels of nonsynonymous variation in the macaques, the estimated distribution of fitness effects and the ratio of nonsynonymous to synonymous variants suggest that purifying selection has had stronger effects in rhesus macaques than in humans. Demographic reconstructions indicate this species has experienced a consistently large but fluctuating population size. Overall, the results presented here provide new insights into the population genomics of nonhuman primates and expand genomic information directly relevant to primate models of human disease.
Keywords: Animals; Evolution, Molecular; Female; Genetic Fitness; High-Throughput Nucleotide Sequencing; Macaca mulatta; Models, Animal; Polymorphism, Single Nucleotide; Population Density; Whole Genome Sequencing

A potential founder variant in in three Norwegian families with warts, molluscum contagiosum, and T-cell dysfunction. - Sorte, Hanne S; Osnes, Liv T; Fevang, Børre; Aukrust, Pål; Erichsen, Hans C; Backe, Paul H; Abrahamsen, Tore G; Kittang, Ole B; Øverland, Torstein; Jhangiani, Shalini N; Muzny, Donna M; Vigeland, Magnus D; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Four patients from three Norwegian families presented with a common skin phenotype of warts, molluscum contagiosum, and dermatitis since early childhood, and various other immunological features. Warts are a common manifestation of (HPV), but when they are overwhelming, disseminated and/or persistent, and presenting together with other immunological features, a primary immunodeficiency disease (PIDD) may be suspected. METHODS AND RESULTS: The four patients were exome sequenced as part of a larger study for detecting genetic causes of primary immunodeficiencies. No disease-causing variants were identified in known primary immunodeficiency genes or in other disease-related OMIM genes. However, the same homozygous missense variant in (also known as ) was identified in all four patients. In each family, the variant was located within a narrow region of homozygosity, representing a potential region of autozygosity. is a protein of undetermined function. A role in T-cell activation has been suggested and the mouse protein homolog (Rltpr) is essential for costimulation of T-cell activation via CD28, and for the development of regulatory T cells. Immunophenotyping demonstrated reduced regulatory, CD4+ memory, and CD4+ follicular T cells in all four patients. In addition, they all seem to have a deficiency in IFN -synthesis in CD4+ T cells and NK cells. CONCLUSIONS: We report a novel primary immunodeficiency, and a differential molecular diagnosis to ,,,,,,, and related diseases. The specific variant may represent a Norwegian founder variant segregating on a population-specific haplotype.

Predictive Value of Antiviral Effects in the Development of Hepatocellular Carcinoma in the General Korean Population with Chronic Hepatitis B. - Shim, Jae-Jun; Oh, In Hwan; Kim, Sang Bae; Kim, Jung Wook; Lee, Chang Kyun; Jang, Jae Young; Lee, Ju-Seog; Kim, Byung-Ho (Gut Liver, 2016)
BACKGROUND/AIMS: The benefit of oral antiviral therapy in preventing hepatocellular carcinoma (HCC) in the general population is not well understood. We used a novel prediction method to estimate the risk of HCC in the Korean population based on various treatment guidelines. METHODS: The 5-year risk of HCC following antiviral therapy was calculated using an HCC risk prediction model. A virtual cohort that represented Koreans (>40 years old) with chronic hepatitis B virus (HBV) infection was established using the fifth National Health and Nutrition Examination Survey. The antiviral indications tested were the Korean National Health Insurance (NHI) and European Association for the Study of the Liver (EASL) guidelines as well as a new extended indication (serum HBV DNA >2,000 IU/mL regardless of serum aminotransferase level). RESULTS: A total of 993,872 subjects were infected with HBV in the general Korean population. Over a 5-year period, 2,725 HCC cases were predicted per 100,000 persons (0.55%/yr). When the cohort was treated based on the Korean NHI, the EASL, and the newly extended indications, HCC risks decreased to 2,531 (-7.1%), 2,089 (-23.3%), and 1,122 (-58.8%) cases per 100,000 persons, respectively (p<0.0001). CONCLUSIONS: Simulated risk prediction suggests that extending of oral antiviral indication may reduce the HCC risk in the general population.
Keywords: Adult; Antiviral Agents; Carcinoma, Hepatocellular; DNA, Viral; Female; Hepatitis B virus; Hepatitis B, Chronic; Humans; Liver Neoplasms; Male; Middle Aged; Nutrition Surveys; Predictive Value of Tests; Republic of Korea; Risk Assessment; Risk Factors; Transaminases

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apolipoproteins E; Drosophila melanogaster; Drosophila Proteins; Exome; Female; Genome-Wide Association Study; Genomics; Humans; Iceland; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Mutation; Phenotype; Receptors, Notch; Tropomyosin; White People

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic or Latino; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis; White People

Reorganization and expansion of the nidoviral family Arteriviridae. - Kuhn, Jens H; Lauck, Michael; Bailey, Adam L; Shchetinin, Alexey M; Vishnevskaya, Tatyana V; Bào, Yīmíng; Ng, Terry Fei Fan; LeBreton, Matthew; Schneider, Bradley S; Gillis, Amethyst; Tamoufe, Ubald; Diffo, Joseph Le Doux; et al. (Arch Virol, 2016)
The family Arteriviridae presently includes a single genus Arterivirus. This genus includes four species as the taxonomic homes for equine arteritis virus (EAV), lactate dehydrogenase-elevating virus (LDV), porcine respiratory and reproductive syndrome virus (PRRSV), and simian hemorrhagic fever virus (SHFV), respectively. A revision of this classification is urgently needed to accommodate the recent description of eleven highly divergent simian arteriviruses in diverse African nonhuman primates, one novel arterivirus in an African forest giant pouched rat, and a novel arterivirus in common brushtails in New Zealand. In addition, the current arterivirus nomenclature is not in accordance with the most recent version of the International Code of Virus Classification and Nomenclature. Here we outline an updated, amended, and improved arterivirus taxonomy based on current data. Taxon-specific sequence cut-offs are established relying on a newly established open reading frame 1b phylogeny and pairwise sequence comparison (PASC) of coding-complete arterivirus genomes. As a result, the current genus Arterivirus is replaced by five genera: Equartevirus (for EAV), Rodartevirus (LDV + PRRSV), Simartevirus (SHFV + simian arteriviruses), Nesartevirus (for the arterivirus from forest giant pouched rats), and Dipartevirus (common brushtail arterivirus). The current species Porcine reproductive and respiratory syndrome virus is divided into two species to accommodate the clear divergence of the European and American "types" of PRRSV, both of which now receive virus status. The current species Simian hemorrhagic fever virus is divided into nine species to accommodate the twelve known simian arteriviruses. Non-Latinized binomial species names are introduced to replace all current species names to clearly differentiate them from virus names, which remain largely unchanged.
Keywords: Arteriviridae; Cluster Analysis; Genome, Viral; Open Reading Frames; Phylogeny; RNA Virus Infections; RNA, Viral; Sequence Homology; Terminology as Topic

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

Somatic mosaicism underlies X-linked acrogigantism syndrome in sporadic male subjects. - Daly, Adrian F; Bo Yuan; Fina, Frederic; Caberg, Jean-Hubert; Trivellin, Giampaolo; Rostomyan, Liliya; de Herder, Wouter W; Naves, Luciana A; Metzger, Daniel; Cuny, Thomas; Rabl, Wolfgang; Shah, Nalini; et al. (Endocr Relat Cancer, 2016)
Somatic mosaicism has been implicated as a causative mechanism in a number of genetic and genomic disorders. X-linked acrogigantism (XLAG) syndrome is a recently characterized genomic form of pediatric gigantism due to aggressive pituitary tumors that is caused by submicroscopic chromosome Xq26.3 duplications that include GPR101 We studied XLAG syndrome patients (n= 18) to determine if somatic mosaicism contributed to the genomic pathophysiology. Eighteen subjects with XLAG syndrome caused by Xq26.3 duplications were identified using high-definition array comparative genomic hybridization (HD-aCGH). We noted that males with XLAG had a decreased log2ratio (LR) compared with expected values, suggesting potential mosaicism, whereas females showed no such decrease. Compared with familial male XLAG cases, sporadic males had more marked evidence for mosaicism, with levels of Xq26.3 duplication between 16.1 and 53.8%. These characteristics were replicated using a novel, personalized breakpoint junction-specific quantification droplet digital polymerase chain reaction (ddPCR) technique. Using a separate ddPCR technique, we studied the feasibility of identifying XLAG syndrome cases in a distinct patient population of 64 unrelated subjects with acromegaly/gigantism, and identified one female gigantism patient who had had increased copy number variation (CNV) threshold for GPR101 that was subsequently diagnosed as having XLAG syndrome on HD-aCGH. Employing a combination of HD-aCGH and novel ddPCR approaches, we have demonstrated, for the first time, that XLAG syndrome can be caused by variable degrees of somatic mosaicism for duplications at chromosome Xq26.3. Somatic mosaicism was shown to occur in sporadic males but not in females with XLAG syndrome, although the clinical characteristics of the disease were similarly severe in both sexes.
Keywords: Adult; Female; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Middle Aged; Mosaicism; Polymerase Chain Reaction; Syndrome; Young Adult

Sources of variation in hair cortisol in wild and captive non-human primates. - Fourie, Nicolaas H; Brown, Janine L; Jolly, Clifford J; Phillips-Conroy, Jane E; Jeffrey Rogers; Bernstein, Robin M (Zoology (Jena), 2016)
Hair cortisol analysis is a potentially powerful tool for evaluating adrenal function and chronic stress. However, the technique has only recently been applied widely to studies of wildlife, including primates, and there are numerous practical and technical factors that should be considered to ensure good quality data and the validity of results and conclusions. Here we report on various intrinsic and extrinsic sources of variation in hair cortisol measurements in wild and captive primates. Hair samples from both wild and captive primates revealed that age and sex can affect hair cortisol concentrations; these effects need to be controlled for when making comparisons between individual animals or populations. Hair growth rates also showed considerable inter-specific variation among a number of primate species. We describe technical limitations of hair analyses and variation in cortisol concentrations as a function of asynchronous hair growth, anatomical site of collection, and the amount and numbers of hair/s used for cortisol extraction. We discuss these sources of variation and their implications for proper study design and interpretation of results.
Keywords: Age Factors; Animals; Animals, Wild; Animals, Zoo; Chemistry Techniques, Analytical; Female; Hair; Hydrocortisone; Male; Primates; Sex Factors; Sonication

Tumour-suppressor microRNAs regulate ovarian cancer cell physical properties and invasive behaviour. - Chan, Clara K; Pan, Yinghong; Nyberg, Kendra; Marra, Marco A; Lim, Emilia L; Jones, Steven J M; Maar, Dianna; Gibb, Ewan A; Gunaratne, Preethi H; Robertson, A Gordon; Rowat, Amy C (Open Biol, 2016)
The activities of pathways that regulate malignant transformation can be influenced by microRNAs (miRs). Recently, we showed that increased expression of five tumour-suppressor miRs, miR-508-3p, miR-508-5p, miR-509-3p, miR-509-5p and miR-130b-3p, correlate with improved clinical outcomes in human ovarian cancer patients, and that miR-509-3p attenuates invasion of ovarian cancer cell lines. Here, we investigate the mechanism underlying this reduced invasive potential by assessing the impact of these five miRs on the physical properties of cells. Human ovarian cancer cells (HEYA8, OVCAR8) that are transfected with miR mimics representing these five miRs exhibit decreased invasion through collagen matrices, increased cell size and reduced deformability as measured by microfiltration and microfluidic assays. To understand the molecular basis of altered invasion and deformability induced by these miRs, we use predicted and validated mRNA targets that encode structural and signalling proteins that regulate cell mechanical properties. Combined with analysis of gene transcripts by real-time PCR and image analysis of F-actin in single cells, our results suggest that these tumour-suppressor miRs may alter cell physical properties by regulating the actin cytoskeleton. Our findings provide biophysical insights into how tumour-suppressor miRs can regulate the invasive behaviour of ovarian cancer cells, and identify potential therapeutic targets that may be implicated in ovarian cancer progression.
Keywords: Actin Cytoskeleton; Cell Line, Tumor; Cell Movement; Female; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Humans; MicroRNAs; Neoplasm Invasiveness; Ovarian Neoplasms; Signal Transduction; Up-Regulation

Two male sibs with severe micrognathia and a missense variant in MED12. - Prescott, Trine E; Kulseth, Mari Ann; Heimdal, Ketil R; Stadheim, Barbro; Hopp, Einar; Gambin, Tomasz; Coban Akdemir, Zeynep H; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Stray-Pedersen, Asbjørg (Eur J Med Genet, 2016)
Missense variants in MED12 cause three partially overlapping dysmorphic X-linked intellectual disability (XLID) syndromes: Lujan-Fryns syndrome (also known as Lujan syndrome), FG syndrome (also known as Opitz-Kaveggia syndrome) and X-linked Ohdo syndrome. We report a family with two severely micrognathic male sibs, a 10½ year old boy and a fetus, in which hemizygosity for a previously unreported missense variant in exon 13 of MED12 (NM_005120.2), c.1862G > A, p.(Arg621Gln) was detected by whole exome sequencing. The affected sibs shared no other rare variant with relevance to the phenotype. X-chromosome inactivation in blood was completely skewed (100:0) in the unaffected heterozygous mother, most likely as a result of preferential inactivation of the X-chromosome harbouring the missense variant in MED12. Neither the unaffected brother nor the unaffected maternal grandfather carried the missense variant in MED12. In the 10½ year old boy, upper airway obstruction secondary to Pierre Robin sequence necessitated a tracheostomy for the first 10 months of life. He has mild to moderate intellectual disability and some dysmorphic features seen in MED12-related syndromes. In addition, he has a horizontal gaze paresis, anomalies of the inner ear, and a cervical block vertebra. This report contributes to the expanding phenotypic range associated with MED12-mutations.
Keywords: Exons; Genes, X-Linked; Genetic Association Studies; Genotype; Humans; Infant; Male; Mediator Complex; Micrognathism; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index; Siblings; Tomography, X-Ray Computed; X Chromosome Inactivation

Unique features of a global human ectoparasite identified through sequencing of the bed bug genome. - Benoit, Joshua B; Adelman, Zach N; Reinhardt, Klaus; Dolan, Amanda; Poelchau, Monica; Jennings, Emily C; Szuter, Elise M; Hagan, Richard W; Gujar, Hemant; Shukla, Jayendra Nath; Zhu, Fang; Mohan, M; et al. (Nat Commun, 2016)
The bed bug, Cimex lectularius, has re-established itself as a ubiquitous human ectoparasite throughout much of the world during the past two decades. This global resurgence is likely linked to increased international travel and commerce in addition to widespread insecticide resistance. Analyses of the C. lectularius sequenced genome (650 Mb) and 14,220 predicted protein-coding genes provide a comprehensive representation of genes that are linked to traumatic insemination, a reduced chemosensory repertoire of genes related to obligate hematophagy, host-symbiont interactions, and several mechanisms of insecticide resistance. In addition, we document the presence of multiple putative lateral gene transfer events. Genome sequencing and annotation establish a solid foundation for future research on mechanisms of insecticide resistance, human-bed bug and symbiont-bed bug associations, and unique features of bed bug biology that contribute to the unprecedented success of C. lectularius as a human ectoparasite.
Keywords: Animals; Bedbugs; Ectoparasitic Infestations; Feeding Behavior; Gene Transfer, Horizontal; Genome; Host-Parasite Interactions; Humans; Insecticide Resistance; Insecticides; Sequence Analysis, DNA

A visual and curatorial approach to clinical variant prioritization and disease gene discovery in genome-wide diagnostics. - James, Regis A; Campbell, Ian M; Chen, Edward S; Boone, Philip M; Rao, Mitchell A; Bainbridge, Matthew N; Lupski, James R; Yang, Yaping; Eng, Christine M; Posey, Jennifer E; Shaw, Chad A (Genome Med, 2016)
BACKGROUND: Genome-wide data are increasingly important in the clinical evaluation of human disease. However, the large number of variants observed in individual patients challenges the efficiency and accuracy of diagnostic review. Recent work has shown that systematic integration of clinical phenotype data with genotype information can improve diagnostic workflows and prioritization of filtered rare variants. We have developed visually interactive, analytically transparent analysis software that leverages existing disease catalogs, such as the Online Mendelian Inheritance in Man database (OMIM) and the Human Phenotype Ontology (HPO), to integrate patient phenotype and variant data into ranked diagnostic alternatives. METHODS: Our tool, "OMIM Explorer" ( http://www.omimexplorer.com ), extends the biomedical application of semantic similarity methods beyond those reported in previous studies. The tool also provides a simple interface for translating free-text clinical notes into HPO terms, enabling clinical providers and geneticists to contribute phenotypes to the diagnostic process. The visual approach uses semantic similarity with multidimensional scaling to collapse high-dimensional phenotype and genotype data from an individual into a graphical format that contextualizes the patient within a low-dimensional disease map. The map proposes a differential diagnosis and algorithmically suggests potential alternatives for phenotype queries--in essence, generating a computationally assisted differential diagnosis informed by the individual's personal genome. Visual interactivity allows the user to filter and update variant rankings by interacting with intermediate results. The tool also implements an adaptive approach for disease gene discovery based on patient phenotypes. RESULTS: We retrospectively analyzed pilot cohort data from the Baylor Miraca Genetics Laboratory, demonstrating performance of the tool and workflow in the re-analysis of clinical exomes. Our tool assigned to clinically reported variants a median rank of 2, placing causal variants in the top 1 % of filtered candidates across the 47 cohort cases with reported molecular diagnoses of exome variants in OMIM Morbidmap genes. Our tool outperformed Phen-Gen, eXtasy, PhenIX, PHIVE, and hiPHIVE in the prioritization of these clinically reported variants. CONCLUSIONS: Our integrative paradigm can improve efficiency and, potentially, the quality of genomic medicine by more effectively utilizing available phenotype information, catalog data, and genomic knowledge.
Keywords: Computational Biology; Diagnosis, Differential; Disease; Genetic Variation; Genome-Wide Association Study; Humans; Phenotype; Pilot Projects; Retrospective Studies; Software

WGSA: an annotation pipeline for human genome sequencing studies. - Liu, Xiaoming; White, Simon; Peng, Bo; Johnson, Andrew D; Brody, Jennifer A; Li, Alexander H; Huang, Zhuoyi; Carroll, Andrew; Wei, Peng; Gibbs, Richard; Klein, Robert J; Boerwinkle, Eric (J Med Genet, 2016)
Keywords: Cloud Computing; Genome, Human; Humans; Molecular Sequence Annotation; Sequence Analysis, DNA; Software

The whole genome sequence of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), reveals insights into the biology and adaptive evolution of a highly invasive pest species. - Papanicolaou, Alexie; Schetelig, Marc F; Arensburger, Peter; Atkinson, Peter W; Benoit, Joshua B; Bourtzis, Kostas; Castañera, Pedro; Cavanaugh, John P; Chao, Hsu; Childers, Christopher; Curril, Ingrid; Dinh, Huyen; et al. (Genome Biol, 2016)
BACKGROUND: The Mediterranean fruit fly (medfly), Ceratitis capitata, is a major destructive insect pest due to its broad host range, which includes hundreds of fruits and vegetables. It exhibits a unique ability to invade and adapt to ecological niches throughout tropical and subtropical regions of the world, though medfly infestations have been prevented and controlled by the sterile insect technique (SIT) as part of integrated pest management programs (IPMs). The genetic analysis and manipulation of medfly has been subject to intensive study in an effort to improve SIT efficacy and other aspects of IPM control. RESULTS: The 479 Mb medfly genome is sequenced from adult flies from lines inbred for 20 generations. A high-quality assembly is achieved having a contig N50 of 45.7 kb and scaffold N50 of 4.06 Mb. In-depth curation of more than 1800 messenger RNAs shows specific gene expansions that can be related to invasiveness and host adaptation, including gene families for chemoreception, toxin and insecticide metabolism, cuticle proteins, opsins, and aquaporins. We identify genes relevant to IPM control, including those required to improve SIT. CONCLUSIONS: The medfly genome sequence provides critical insights into the biology of one of the most serious and widespread agricultural pests. This knowledge should significantly advance the means of controlling the size and invasive potential of medfly populations. Its close relationship to Drosophila, and other insect species important to agriculture and human health, will further comparative functional and structural studies of insect genomes that should broaden our understanding of gene family evolution.
Keywords: Animals; Animals, Genetically Modified; Biological Evolution; Ceratitis capitata; Genome, Insect; High-Throughput Nucleotide Sequencing; Humans; Introduced Species; Molecular Sequence Annotation; Pest Control, Biological

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)
Circulating blood cell counts and indices are important indicators of hematopoietic function and a number of clinical parameters, such as blood oxygen-carrying capacity, inflammation, and hemostasis. By performing whole-exome sequence association analyses of hematologic quantitative traits in 15,459 community-dwelling individuals, followed by in silico replication in up to 52,024 independent samples, we identified two previously undescribed coding variants associated with lower platelet count: a common missense variant in CPS1 (rs1047891, MAF = 0.33, discovery + replication p = 6.38 × 10(-10)) and a rare synonymous variant in GFI1B (rs150813342, MAF = 0.009, discovery + replication p = 1.79 × 10(-27)). By performing CRISPR/Cas9 genome editing in hematopoietic cell lines and follow-up targeted knockdown experiments in primary human hematopoietic stem and progenitor cells, we demonstrate an alternative splicing mechanism by which the GFI1B rs150813342 variant suppresses formation of a GFI1B isoform that preferentially promotes megakaryocyte differentiation and platelet production. These results demonstrate how unbiased studies of natural variation in blood cell traits can provide insight into the regulation of human hematopoiesis.
Keywords: Alternative Splicing; Blood Platelets; CRISPR-Cas Systems; DNA Mutational Analysis; Exome; Gene Editing; Genetic Loci; Hematopoiesis; Hematopoietic Stem Cells; Humans; Megakaryocytes; Platelet Count; Proto-Oncogene Proteins; Repressor Proteins

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Boerwinkle, Eric; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Gibbs, Richard A; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Zoonotic Potential of Simian Arteriviruses. - Bailey, Adam L; Lauck, Michael; Sibley, Samuel D; Friedrich, Thomas C; Kuhn, Jens H; Freimer, Nelson B; Jasinska, Anna J; Phillips-Conroy, Jane E; Jolly, Clifford J; Marx, Preston A; Apetrei, Cristian; Rogers, Jeffrey; et al. (J Virol, 2016)
Wild nonhuman primates are immediate sources and long-term reservoirs of human pathogens. However, ethical and technical challenges have hampered the identification of novel blood-borne pathogens in these animals. We recently examined RNA viruses in plasma from wild African monkeys and discovered several novel, highly divergent viruses belonging to the family Arteriviridae. Close relatives of these viruses, including simian hemorrhagic fever virus, have caused sporadic outbreaks of viral hemorrhagic fever in captive macaque monkeys since the 1960s. However, arterivirus infection in wild nonhuman primates had not been described prior to 2011. The arteriviruses recently identified in wild monkeys have high sequence and host species diversity, maintain high viremia, and are prevalent in affected populations. Taken together, these features suggest that the simian arteriviruses may be "preemergent" zoonotic pathogens. If not, this would imply that biological characteristics of RNA viruses thought to facilitate zoonotic transmission may not, by themselves, be sufficient for such transmission to occur.
Keywords: Animals; Arterivirus; Arterivirus Infections; Haplorhini; Humans; Primate Diseases; Zoonoses

Absence of heterozygosity due to template switching during replicative rearrangements. - Carvalho, Claudia M B; Pfundt, Rolph; King, Daniel A; Lindsay, Sarah J; Zuccherato, Luciana W; Macville, Merryn V E; Liu, Pengfei; Johnson, Diana; Stankiewicz, Pawel; Brown, Chester W; Shaw, Chad A; Hurles, Matthew E; et al. (Am J Hum Genet, 2015)
We investigated complex genomic rearrangements (CGRs) consisting of triplication copy-number variants (CNVs) that were accompanied by extended regions of copy-number-neutral absence of heterozygosity (AOH) in subjects with multiple congenital abnormalities. Molecular analyses provided observational evidence that in humans, post-zygotically generated CGRs can lead to regional uniparental disomy (UPD) due to template switches between homologs versus sister chromatids by using microhomology to prime DNA replication-a prediction of the replicative repair model, MMBIR. Our findings suggest that replication-based mechanisms might underlie the formation of diverse types of genomic alterations (CGRs and AOH) implicated in constitutional disorders.
Keywords: Base Sequence; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Humans; In Situ Hybridization, Fluorescence; Loss of Heterozygosity; Models, Genetic; Molecular Sequence Data; Netherlands; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Uniparental Disomy

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; Black or African American; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; White People

ATF6 Is Mutated in Early Onset Photoreceptor Degeneration With Macular Involvement. - Xu, Mingchu; Gelowani, Violet; Eblimit, Aiden; Wang, Feng; Young, Marielle P; Sawyer, Briana L; Zhao, Li; Jenkins, Glen; Creel, Donnell J; Wang, Keqing; Ge, Zhongqi; Wang, Hui; et al. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE: Photoreceptor degeneration (PRD) is a genetically heterogeneous retinal disorder. Although a number of genes involved in PRD have been identified, their genetic basis remains unknown in a significant number of patients. In this study, we aimed to identify novel disease-causing genes of PRD. METHODS: Comprehensive ocular examinations were performed in a 2-year-old patient diagnosed with early onset PRD. Retinal capture sequencing was performed to screen causative mutations in known retinal disease-causing loci. Whole-exome sequencing (WES) and a series of variant-filtering strategies were applied for identifying novel disease-causing genes. Retina ATF6 expression was confirmed by immunohistochemistry. RT-PCR was performed to identify ATF6 mRNA in the patient. RESULTS: The patient showed typical PRD features, with macular involvement and ellipsoid zone irregularities. Results of retinal capture sequencing were negative. WES data led to identification of biallelic loss-of-function mutations in the ATF6 gene. The first variant generates a premature stop codon (NCBI accession no. NM_007348: c.1126C>T, p.R376*) and the second variant affects a splicing donor site (NM_007348: c.1533+1G>C). Sanger sequencing confirmed the 2 alleles are from 1 parent each. Both of the variants are extremely rare in the population. The splicing variant causes either intron inclusion or exon skipping in the patient, thus severely disrupting ATF6 functional domains. ATF6 is expressed in three neuronal cell layers of mouse retina. CONCLUSIONS: Our results support ATF6 as a novel disease-causing gene for PRD and suggest that disrupted protein quality control mechanisms may be a novel pathological mechanism underlying human retinal degeneration.
Keywords: Activating Transcription Factor 6; Age Factors; Child, Preschool; Female; Humans; Macula Lutea; Mutation; Photoreceptor Cells, Vertebrate; Retinal Diseases

Autosomal-Dominant Multiple Pterygium Syndrome Is Caused by Mutations in MYH3. - Chong, Jessica X; Burrage, Lindsay C; Beck, Anita E; Marvin, Colby T; McMillin, Margaret J; Shively, Kathryn M; Harrell, Tanya M; Buckingham, Kati J; Bacino, Carlos A; Jain, Mahim; Alanay, Yasemin; Berry, Susan A; et al. (Am J Hum Genet, 2015)
Multiple pterygium syndrome (MPS) is a phenotypically and genetically heterogeneous group of rare Mendelian conditions characterized by multiple pterygia, scoliosis, and congenital contractures of the limbs. MPS typically segregates as an autosomal-recessive disorder, but rare instances of autosomal-dominant transmission have been reported. Whereas several mutations causing recessive MPS have been identified, the genetic basis of dominant MPS remains unknown. We identified four families affected by dominantly transmitted MPS characterized by pterygia, camptodactyly of the hands, vertebral fusions, and scoliosis. Exome sequencing identified predicted protein-altering mutations in embryonic myosin heavy chain (MYH3) in three families. MYH3 mutations underlie distal arthrogryposis types 1, 2A, and 2B, but all mutations reported to date occur in the head and neck domains. In contrast, two of the mutations found to cause MPS in this study occurred in the tail domain. The phenotypic overlap among persons with MPS, coupled with physical findings distinct from other conditions caused by mutations in MYH3, suggests that the developmental mechanism underlying MPS differs from that of other conditions and/or that certain functions of embryonic myosin might be perturbed by disruption of specific residues and/or domains. Moreover, the vertebral fusions in persons with MPS, coupled with evidence of MYH3 expression in bone, suggest that embryonic myosin plays a role in skeletal development.
Keywords: Arthrogryposis; Cytoskeletal Proteins; Exome; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Mutation; Myosins; Osteogenesis

Brain Tumor Epidemiology - A Hub within Multidisciplinary Neuro-oncology. Report on the 15th Brain Tumor Epidemiology Consortium (BTEC) Annual Meeting, Vienna, 2014. - Woehrer, Adelheid; Lau, Ching C; Prayer, Daniela; Bauchet, Luc; Rosenfeld, Myrna; Capper, David; Fisher, Paul G; Kool, Marcel; Müller, Martin; Kros, Johan M; Kruchko, Carol; Wiemels, Joseph; et al. (Clin Neuropathol, 2015)
The Brain Tumor Epidemiology Consortium (BTEC) is an open scientific forum, which fosters the development of multi-center, international and inter-disciplinary collaborations. BTEC aims to develop a better understanding of the etiology, outcomes, and prevention of brain tumors (http://epi.grants.cancer.gov/btec/). The 15th annual Brain Tumor Epidemiology Consortium Meeting, hosted by the Austrian Societies of Neuropathology and Neuro-oncology, was held on September 9 - 11, 2014 in Vienna, Austria. The meeting focused on the central role of brain tumor epidemiology within multidisciplinary neuro-oncology. Knowledge of disease incidence, outcomes, as well as risk factors is fundamental to all fields involved in research and treatment of patients with brain tumors; thus, epidemiology constitutes an important link between disciplines, indeed the very hub. This was reflected by the scientific program, which included various sessions linking brain tumor epidemiology with clinical neuro-oncology, tissue-based research, and cancer registration. Renowned experts from Europe and the United States contributed their personal perspectives stimulating further group discussions. Several concrete action plans evolved for the group to move forward until next year's meeting, which will be held at the Mayo Clinic at Rochester, MN, USA.
Keywords: Austria; Brain Neoplasms; Humans

The Candida albicans Histone Acetyltransferase Hat1 Regulates Stress Resistance and Virulence via Distinct Chromatin Assembly Pathways. - Tscherner, Michael; Zwolanek, Florian; Jenull, Sabrina; Fritz J Sedlazeck; Petryshyn, Andriy; Frohner, Ingrid E; Mavrianos, John; Chauhan, Neeraj; von Haeseler, Arndt; Kuchler, Karl (PLoS Pathog, 2015)
Human fungal pathogens like Candida albicans respond to host immune surveillance by rapidly adapting their transcriptional programs. Chromatin assembly factors are involved in the regulation of stress genes by modulating the histone density at these loci. Here, we report a novel role for the chromatin assembly-associated histone acetyltransferase complex NuB4 in regulating oxidative stress resistance, antifungal drug tolerance and virulence in C. albicans. Strikingly, depletion of the NuB4 catalytic subunit, the histone acetyltransferase Hat1, markedly increases resistance to oxidative stress and tolerance to azole antifungals. Hydrogen peroxide resistance in cells lacking Hat1 results from higher induction rates of oxidative stress gene expression, accompanied by reduced histone density as well as subsequent increased RNA polymerase recruitment. Furthermore, hat1Δ/Δ cells, despite showing growth defects in vitro, display reduced susceptibility to reactive oxygen-mediated killing by innate immune cells. Thus, clearance from infected mice is delayed although cells lacking Hat1 are severely compromised in killing the host. Interestingly, increased oxidative stress resistance and azole tolerance are phenocopied by the loss of histone chaperone complexes CAF-1 and HIR, respectively, suggesting a central role for NuB4 in the delivery of histones destined for chromatin assembly via distinct pathways. Remarkably, the oxidative stress phenotype of hat1Δ/Δ cells is a species-specific trait only found in C. albicans and members of the CTG clade. The reduced azole susceptibility appears to be conserved in a wider range of fungi. Thus, our work demonstrates how highly conserved chromatin assembly pathways can acquire new functions in pathogenic fungi during coevolution with the host.
Keywords: Adaptation, Physiological; Animals; Candida albicans; Candidiasis; Chromatin Assembly and Disassembly; Chromatin Immunoprecipitation; Histone Acetyltransferases; Immunoblotting; Mass Spectrometry; Mice; Mice, Inbred C57BL; Oxidative Stress; Polymerase Chain Reaction; Virulence

Cerebral visual impairment and intellectual disability caused by PGAP1 variants. - Bosch, Daniëlle G M; Boonstra, F Nienke; Kinoshita, Taroh; Jhangiani, Shalini; de Ligt, Joep; Cremers, Frans P M; Lupski, James R; Murakami, Yoshiko; de Vries, Bert B A (Eur J Hum Genet, 2015)
Homozygous variants in PGAP1 (post-GPI attachment to proteins 1) have recently been identified in two families with developmental delay, seizures and/or spasticity. PGAP1 is a member of the glycosylphosphatidylinositol anchor biosynthesis and remodeling pathway and defects in this pathway are a subclass of congenital disorders of glycosylation. Here we performed whole-exome sequencing in an individual with cerebral visual impairment (CVI), intellectual disability (ID), and factor XII deficiency and revealed compound heterozygous variants in PGAP1, c.274_276del (p.(Pro92del)) and c.921_925del (p.(Lys308Asnfs*25)). Subsequently, PGAP1-deficient Chinese hamster ovary (CHO)-cell lines were transfected with either mutant or wild-type constructs and their sensitivity to phosphatidylinositol-specific phospholipase C (PI-PLC) treatment was measured. The mutant constructs could not rescue the PGAP1-deficient CHO cell lines resistance to PI-PLC treatment. In addition, lymphoblastoid cell lines (LCLs) of the affected individual showed no sensitivity to PI-PLC treatment, whereas the LCLs of the heterozygous carrier parents were partially resistant. In conclusion, we report novel PGAP1 variants in a boy with CVI and ID and a proven functional loss of PGAP1 and show, to our knowledge, for the first time this genetic association with CVI.
Keywords: Animals; Cell Line, Tumor; Child; CHO Cells; Cricetinae; Cricetulus; Humans; Intellectual Disability; Male; Membrane Proteins; Mutation; Phosphoinositide Phospholipase C; Phosphoric Monoester Hydrolases; Syndrome; Vision Disorders; Visual Perception

Clinical, morphological, biochemical, imaging and outcome parameters in 21 individuals with mitochondrial maintenance defect related to FBXL4 mutations. - Huemer, Martina; Karall, Daniela; Schossig, Anna; Abdenur, Jose E; Al Jasmi, Fatma; Biagosch, Caroline; Distelmaier, Felix; Freisinger, Peter; Graham, Brett H; Haack, Tobias B; Hauser, Natalie; Hertecant, Jozef; et al. (J Inherit Metab Dis, 2015)
FBXL4 deficiency is a recently described disorder of mitochondrial maintenance associated with a loss of mitochondrial DNA in cells. To date, the genetic diagnosis of FBXL4 deficiency has been established in 28 individuals. This paper retrospectively reviews proxy-reported clinical and biochemical findings and evaluates brain imaging, morphological and genetic data in 21 of those patients. Neonatal/early-onset severe lactic acidosis, muscular hypotonia, feeding problems and failure to thrive is the characteristic pattern at first presentation. Facial dysmorphic features are present in 67% of cases. Seven children died (mean age 37 months); 11 children were alive (mean age at follow-up 46 months), three children were lost to follow-up. All survivors developed severe psychomotor retardation. Brain imaging was non-specific in neonates but a later-onset, rapidly progressive brain atrophy was noted. Elevated blood lactate and metabolic acidosis were observed in all individuals; creatine kinase was elevated in 45% of measurements. Diagnostic workup in patient tissues and cells revealed a severe combined respiratory chain defect with a general decrease of enzymes associated with mitochondrial energy metabolism and a relative depletion of mitochondrial DNA content. Mutations were detected throughout the FBXL4 gene albeit with no clear delineation of a genotype-phenotype correlation. Treatment with "mitochondrial medications" did not prove effective. In conclusion, a clinical pattern of early-onset encephalopathy, persistent lactic acidosis, profound muscular hypotonia and typical facial dysmorphism should prompt initiation of molecular genetic analysis of FBXL4. Establishment of the diagnosis permits genetic counselling, prevents patients undergoing unhelpful diagnostic procedures and allows for accurate prognosis.
Keywords: Acidosis, Lactic; Child; Child, Preschool; Disease Progression; F-Box Proteins; Facial Asymmetry; Family; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mitochondrial Diseases; Muscle Hypotonia; Mutation; Neuroimaging; Prognosis; Retrospective Studies; Ubiquitin-Protein Ligases

Comparison and integration of deleteriousness prediction methods for nonsynonymous SNVs in whole exome sequencing studies. - Dong, Chengliang; Wei, Peng; Jian, Xueqiu; Gibbs, Richard; Boerwinkle, Eric; Wang, Kai; Liu, Xiaoming (Hum Mol Genet, 2015)
Accurate deleteriousness prediction for nonsynonymous variants is crucial for distinguishing pathogenic mutations from background polymorphisms in whole exome sequencing (WES) studies. Although many deleteriousness prediction methods have been developed, their prediction results are sometimes inconsistent with each other and their relative merits are still unclear in practical applications. To address these issues, we comprehensively evaluated the predictive performance of 18 current deleteriousness-scoring methods, including 11 function prediction scores (PolyPhen-2, SIFT, MutationTaster, Mutation Assessor, FATHMM, LRT, PANTHER, PhD-SNP, SNAP, SNPs&GO and MutPred), 3 conservation scores (GERP++, SiPhy and PhyloP) and 4 ensemble scores (CADD, PON-P, KGGSeq and CONDEL). We found that FATHMM and KGGSeq had the highest discriminative power among independent scores and ensemble scores, respectively. Moreover, to ensure unbiased performance evaluation of these prediction scores, we manually collected three distinct testing datasets, on which no current prediction scores were tuned. In addition, we developed two new ensemble scores that integrate nine independent scores and allele frequency. Our scores achieved the highest discriminative power compared with all the deleteriousness prediction scores tested and showed low false-positive prediction rate for benign yet rare nonsynonymous variants, which demonstrated the value of combining information from multiple orthologous approaches. Finally, to facilitate variant prioritization in WES studies, we have pre-computed our ensemble scores for 87 347 044 possible variants in the whole-exome and made them publicly available through the ANNOVAR software and the dbNSFP database.
Keywords: Computational Biology; Exome; Genome, Human; Humans; Polymorphism, Single Nucleotide; Software

A comprehensive 1,000 Genomes-based genome-wide association meta-analysis of coronary artery disease. - Nikpay, Majid; Goel, Anuj; Won, Hong-Hee; Hall, Leanne M; Willenborg, Christina; Kanoni, Stavroula; Saleheen, Danish; Kyriakou, Theodosios; Nelson, Christopher P; Hopewell, Jemma C; Webb, Thomas R; Zeng, Lingyao; et al. (Nat Genet, 2015)
Existing knowledge of genetic variants affecting risk of coronary artery disease (CAD) is largely based on genome-wide association study (GWAS) analysis of common SNPs. Leveraging phased haplotypes from the 1000 Genomes Project, we report a GWAS meta-analysis of ∼185,000 CAD cases and controls, interrogating 6.7 million common (minor allele frequency (MAF) > 0.05) and 2.7 million low-frequency (0.005 < MAF < 0.05) variants. In addition to confirming most known CAD-associated loci, we identified ten new loci (eight additive and two recessive) that contain candidate causal genes newly implicating biological processes in vessel walls. We observed intralocus allelic heterogeneity but little evidence of low-frequency variants with larger effects and no evidence of synthetic association. Our analysis provides a comprehensive survey of the fine genetic architecture of CAD, showing that genetic susceptibility to this common disease is largely determined by common SNPs of small effect size.
Keywords: Coronary Artery Disease; Genome, Human; Genome-Wide Association Study; Humans; Phenotype

A comprehensive assessment of somatic mutation detection in cancer using whole-genome sequencing. - Alioto, Tyler S; Buchhalter, Ivo; Derdak, Sophia; Hutter, Barbara; Eldridge, Matthew D; Hovig, Eivind; Heisler, Lawrence E; Beck, Timothy A; Simpson, Jared T; Tonon, Laurie; Sertier, Anne-Sophie; Patch, Ann-Marie; et al. (Nat Commun, 2015)
As whole-genome sequencing for cancer genome analysis becomes a clinical tool, a full understanding of the variables affecting sequencing analysis output is required. Here using tumour-normal sample pairs from two different types of cancer, chronic lymphocytic leukaemia and medulloblastoma, we conduct a benchmarking exercise within the context of the International Cancer Genome Consortium. We compare sequencing methods, analysis pipelines and validation methods. We show that using PCR-free methods and increasing sequencing depth to ∼ 100 × shows benefits, as long as the tumour:control coverage ratio remains balanced. We observe widely varying mutation call rates and low concordance among analysis pipelines, reflecting the artefact-prone nature of the raw data and lack of standards for dealing with the artefacts. However, we show that, using the benchmark mutation set we have created, many issues are in fact easy to remedy and have an immediate positive impact on mutation detection accuracy.
Keywords: Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Leukemia, Lymphoid; Medulloblastoma; Mutation

Comprehensive molecular diagnosis of 67 Chinese Usher syndrome probands: high rate of ethnicity specific mutations in Chinese USH patients. - Jiang, Lichun; Liang, Xiaofang; Li, Yumei; Wang, Jing; Zaneveld, Jacques Eric; Wang, Hui; Xu, Shan; Wang, Keqing; Wang, Binbin; Chen, Rui; Sui, Ruifang (Orphanet J Rare Dis, 2015)
BACKGROUND: Usher syndrome (USH) is the most common disease causing combined deafness and blindness. It is predominantly an autosomal recessive genetic disorder with occasionally digenic cases. Molecular diagnosis of USH patients is important for disease management. Few studies have tried to find the genetic cause of USH in Chinese patients. This study was designed to determine the mutation spectrum of Chinese USH patients. METHODS: We applied next generation sequencing to characterize the mutation spectrum in 67 independent Chinese families with at least one member diagnosed with USH. Blood was collected at Peking Union Medical College Hospital. This cohort is one of the largest USH cohorts reported. We utilized customized panel and whole exome sequencing, variant analysis, Sanger validation and segregation tests to find disease causing mutations in these families. RESULTS: We identified biallelic disease causing mutations in known USH genes in 70 % (49) of our patients. As has been previously reported, MYO7A is the most frequently mutated gene in our USH type I patients while USH2A is the most mutated gene in our USH type II patients. In addition, we identify mutations in CLRN1, DFNB31, GPR98 and PCDH15 for the first time in Chinese USH patients. Together, mutations in CLRN1, DNFB31, GPR98 and PCDH15 account for 11.4 % of disease in our cohort. Interestingly, although the spectrum of disease genes is quite similar between our Chinese patient cohort and other patient cohorts from different (and primarily Caucasian) ethnic backgrounds, the mutations themselves are dramatically different. In particular, 76 % (52/68) of alleles found in this study have never been previously reported. Interestingly, we observed a strong enrichment for severe protein truncating mutations expected to have severe functional consequence on the protein in USH II patients compared to the reported mutation spectrum in RP patients, who often carry partial protein truncating mutations. CONCLUSIONS: Our study provides the first comprehensive genetic characterization of a large collection of Chinese USH patients. Up to 90 % of USH patients have disease caused by mutations in known USH disease genes. By combining NGS-based molecular diagnosis and patient clinical information, a more accurate diagnosis, prognosis and personalized treatment of USH patients can be achieved.
Keywords: China; Cohort Studies; Ethnicity; Female; Humans; Male; Molecular Diagnostic Techniques; Mutation; Pedigree; Phenotype; Usher Syndromes

Convergent evolution of the genomes of marine mammals. - Foote, Andrew D; Liu, Yue; Thomas, Gregg W C; Vinar, Tomas; Alföldi, Jessica; Deng, Jixin; Dugan, Shannon; van Elk, Cornelis E; Hunter, Margaret E; Joshi, Vandita; Khan, Ziad; Kovar, Christie; et al. (Nat Genet, 2015)
Marine mammals from different mammalian orders share several phenotypic traits adapted to the aquatic environment and therefore represent a classic example of convergent evolution. To investigate convergent evolution at the genomic level, we sequenced and performed de novo assembly of the genomes of three species of marine mammals (the killer whale, walrus and manatee) from three mammalian orders that share independently evolved phenotypic adaptations to a marine existence. Our comparative genomic analyses found that convergent amino acid substitutions were widespread throughout the genome and that a subset of these substitutions were in genes evolving under positive selection and putatively associated with a marine phenotype. However, we found higher levels of convergent amino acid substitutions in a control set of terrestrial sister taxa to the marine mammals. Our results suggest that, whereas convergent molecular evolution is relatively common, adaptive molecular convergence linked to phenotypic convergence is comparatively rare.
Keywords: Adaptation, Physiological; Amino Acid Substitution; Animals; Evolution, Molecular; Genome; Humans; Mammals; Phenotype; Phylogeny; Selection, Genetic

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

DVL1 frameshift mutations clustering in the penultimate exon cause autosomal-dominant Robinow syndrome. - White, Janson; Mazzeu, Juliana F; Hoischen, Alexander; Jhangiani, Shalini N; Gambin, Tomasz; Alcino, Michele Calijorne; Penney, Samantha; Saraiva, Jorge M; Hove, Hanne; Skovby, Flemming; Kayserili, Hulya; Estrella, Elicia; et al. (Am J Hum Genet, 2015)
Robinow syndrome is a genetically heterogeneous disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features and for which both autosomal-recessive and autosomal-dominant inheritance patterns have been described. Causative variants in the non-canonical signaling gene WNT5A underlie a subset of autosomal-dominant Robinow syndrome (DRS) cases, but most individuals with DRS remain without a molecular diagnosis. We performed whole-exome sequencing in four unrelated DRS-affected individuals without coding mutations in WNT5A and found heterozygous DVL1 exon 14 mutations in three of them. Targeted Sanger sequencing in additional subjects with DRS uncovered DVL1 exon 14 mutations in five individuals, including a pair of monozygotic twins. In total, six distinct frameshift mutations were found in eight subjects, and all were heterozygous truncating variants within the penultimate exon of DVL1. In five families in which samples from unaffected parents were available, the variants were demonstrated to represent de novo mutations. All variant alleles are predicted to result in a premature termination codon within the last exon, escape nonsense-mediated decay (NMD), and most likely generate a C-terminally truncated protein with a distinct -1 reading-frame terminus. Study of the transcripts extracted from affected subjects' leukocytes confirmed expression of both wild-type and variant alleles, supporting the hypothesis that mutant mRNA escapes NMD. Genomic variants identified in our study suggest that truncation of the C-terminal domain of DVL1, a protein hypothesized to have a downstream role in the Wnt-5a non-canonical pathway, is a common cause of DRS.
Keywords: Adaptor Proteins, Signal Transducing; Amino Acid Sequence; Base Sequence; Craniofacial Abnormalities; Dishevelled Proteins; DNA Primers; Dwarfism; Exome; Exons; Frameshift Mutation; Gene Components; Humans; Limb Deformities, Congenital; Molecular Sequence Data; Phosphoproteins; Sequence Analysis, DNA; Urogenital Abnormalities

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoprotein A-V; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Muzny, Donna; Uluc, Kayihan; Gibbs, Richard A; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Fine mapping the region reveals a common intronic insertion associated to HDL-C. - van Leeuwen, Elisabeth M; Huffman, Jennifer E; Bis, Joshua C; Isaacs, Aaron; Mulder, Monique; Aniko Sabo; Smith, Albert V; Demissie, Serkalem; Manichaikul, Ani; Brody, Jennifer A; Feitosa, Mary F; Duan, Qing; et al. (NPJ Aging Mech Dis, 2015)
BACKGROUND: Individuals with exceptional longevity and their offspring have significantly larger high-density lipoprotein concentrations (HDL-C) particle sizes due to the increased homozygosity for the I405V variant in the cholesteryl ester transfer protein ( gene. In this study, we investigate the association of and HDL-C further to identify novel, independent variants associated with HDL-C in humans. METHODS: We performed a meta-analysis of HDL-C within the region using 59,432 individuals imputed with 1000 Genomes data. We performed replication in an independent sample of 47,866 individuals and validation was done by Sanger sequencing. RESULTS: The meta-analysis of HDL-C within the region identified five independent variants, including an exonic variant and a common intronic insertion. We replicated these 5 variants significantly in an independent sample of 47,866 individuals. Sanger sequencing of the insertion within a single family confirmed segregation of this variant. The strongest reported association between HDL-C and variants, was rs3764261; however, after conditioning on the five novel variants we identified the support for rs3764261 was highly reduced (=3.179 mg/dl ( value=5.25×10), =0.859 mg/dl ( value=9.51×10)), and this finding suggests that these five novel variants may partly explain the association of with HDL-C. Indeed, three of the five novel variants (rs34065661, rs5817082, rs7499892) are independent of rs3764261. CONCLUSIONS: The causal variants in that account for the association with HDL-C remain unknown. We used studies imputed to the 1000 Genomes reference panel for fine mapping of the region. We identified and validated five variants within this region that may partly account for the association of the known variant (rs3764261), as well as other sources of genetic contribution to HDL-C.

FlyVar: a database for genetic variation in Drosophila melanogaster. - Wang, Fei; Jiang, Lichun; Chen, Yong; Haelterman, Nele A; Bellen, Hugo J; Chen, Rui (Database (Oxford), 2015)
FlyVar is a publicly and freely available platform that addresses the increasing need of next generation sequencing data analysis in the Drosophila research community. It is composed of three parts. First, a database that contains 5.94 million DNA polymorphisms found in Drosophila melanogaster derived from whole genome shotgun sequencing of 612 genomes of D. melanogaster. In addition, a list of 1094 dispensable genes has been identified. Second, a graphical user interface (GUI) has been implemented to allow easy and flexible queries of the database. Third, a set of interactive online tools enables filtering and annotation of genomic sequences obtained from individual D. melanogaster strains to identify candidate mutations. FlyVar permits the analysis of next generation sequencing data without the need of extensive computational training or resources. Database URL: www.iipl.fudan.edu.cn/FlyVar.
Keywords: Animals; Databases, Genetic; Drosophila melanogaster; Genes, Insect; Molecular Sequence Annotation; Polymorphism, Genetic; User-Computer Interface

FOXO1 is required for binding of PR on IRF4, novel transcriptional regulator of endometrial stromal decidualization. - Vasquez, Yasmin M; Mazur, Erik C; Li, Xilong; Kommagani, Ramakrishna; Jiang, Lichun; Chen, Rui; Lanz, Rainer B; Kovanci, Ertug; Gibbons, William E; DeMayo, Francesco J (Mol Endocrinol, 2015)
The forkhead box O1A (FOXO1) is an early-induced target of the protein kinase A pathway during the decidualization of human endometrial stromal cells (HESCs). In this study we identified the cistrome and transcriptome of FOXO1 and its role as a transcriptional regulator of the progesterone receptor (PR). Direct targets of FOXO1 were identified by integrating RNA sequencing with chromatin immunoprecipitation followed by deep sequencing. Gene ontology analysis demonstrated that FOXO1 regulates a subset of genes in decidualization such as those involved in cancer, p53 signaling, focal adhesions, and Wnt signaling. An overlap of the FOXO1 and PR chromatin immunoprecipitation followed by deep sequencing intervals revealed the co-occupancy of FOXO1 in more than 75% of PR binding intervals. Among these intervals were highly enriched motifs for the interferon regulatory factor member 4 (IRF4). IRF4 was determined to be a genomic target of both FOXO1 and PR and also to be differentially regulated in HESCs treated with small interfering RNA targeting FOXO1 or PR prior to decidualization stimulus. Ablation of FOXO1 was found to abolish binding of PR to the shared binding interval downstream of the IRF4 gene. Finally, small interfering RNA-mediated ablation of IRF4 was shown to compromise morphological transformation of decidualized HESCs and to attenuate the expression of the decidual markers IGFBP1, PRL, and WNT4. These results provide the first evidence that FOXO1 is functionally required for the binding of PR to genomic targets. Most notably, FOXO1 and PR are required for the regulation of IRF4, a novel transcriptional regulator of decidualization in HESCs.
Keywords: Base Sequence; Binding Sites; Chromatin Immunoprecipitation; Decidua; Female; Forkhead Box Protein O1; Forkhead Transcription Factors; Gene Expression Regulation; Genome, Human; Humans; Interferon Regulatory Factors; Molecular Sequence Data; Nucleotide Motifs; Protein Binding; Receptors, Progesterone; Reproducibility of Results; RNA, Small Interfering; Sequence Analysis, RNA; Software; Stromal Cells; Transcription, Genetic

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic fine mapping and genomic annotation defines causal mechanisms at type 2 diabetes susceptibility loci. - Gaulton, Kyle J; Ferreira, Teresa; Lee, Yeji; Raimondo, Anne; Mägi, Reedik; Reschen, Michael E; Mahajan, Anubha; Locke, Adam; Rayner, N William; Robertson, Neil; Scott, Robert A; Prokopenko, Inga; et al. (Nat Genet, 2015)
We performed fine mapping of 39 established type 2 diabetes (T2D) loci in 27,206 cases and 57,574 controls of European ancestry. We identified 49 distinct association signals at these loci, including five mapping in or near KCNQ1. 'Credible sets' of the variants most likely to drive each distinct signal mapped predominantly to noncoding sequence, implying that association with T2D is mediated through gene regulation. Credible set variants were enriched for overlap with FOXA2 chromatin immunoprecipitation binding sites in human islet and liver cells, including at MTNR1B, where fine mapping implicated rs10830963 as driving T2D association. We confirmed that the T2D risk allele for this SNP increases FOXA2-bound enhancer activity in islet- and liver-derived cells. We observed allele-specific differences in NEUROD1 binding in islet-derived cells, consistent with evidence that the T2D risk allele increases islet MTNR1B expression. Our study demonstrates how integration of genetic and genomic information can define molecular mechanisms through which variants underlying association signals exert their effects on disease.
Keywords: Binding Sites; Case-Control Studies; Chromatin Immunoprecipitation; Chromosome Mapping; Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Hepatocyte Nuclear Factor 3-beta; Humans; Islets of Langerhans; Liver; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Receptor, Melatonin, MT2

Genetic influences on response to novel objects and dimensions of personality in Papio baboons. - Johnson, Zachary; Brent, Linda; Alvarenga, Juan Carlos; Comuzzie, Anthony G; Shelledy, Wendy; Ramirez, Stephanie; Cox, Laura; Mahaney, Michael C; Huang, Yung-Yu; Mann, J John; Kaplan, Jay R; Rogers, Jeffrey (Behav Genet, 2015)
Behavioral variation within and between populations and species of the genus Papio has been studied extensively, but little is known about the genetic causes of individual- or population-level differences. This study investigates the influence of genetic variation on personality (sometimes referred to as temperament) in baboons and identifies a candidate gene partially responsible for the variation in that phenotype. To accomplish these goals, we examined individual variation in response to both novel objects and an apparent novel social partner (using a mirror test) among pedigreed baboons (n = 578) from the Southwest National Primate Research Center. We investigated the frequency and duration of individual behaviors in response to novel objects and used multivariate factor analysis to identify trait-like dimensions of personality. Exploratory factor analysis identified two distinct dimensions of personality within this population. Factor 1 accounts for 46.8 % of the variance within the behavioral matrix, and consists primarily of behaviors related to the "boldness" of the subject. Factor 2 accounts for 18.8 % of the variation, and contains several "anxiety" like behaviors. Several specific behaviors, and the two personality factors, were significantly heritable, with the factors showing higher heritability than most individual behaviors. Subsequent analyses show that the behavioral reactions observed in the test protocol are associated with animals' social behavior observed later in their home social groups. Finally we used linkage analysis to map quantitative trait loci for the measured phenotypes. Single nucleotide polymorphisms in a positional candidate gene (SNAP25) are associated with variation in one of the personality factors, and CSF levels of homovanillic acid and 3-methoxy-4-hydroxyphenylglycol. This study documents heritable variation in personality among baboons and suggests that sequence variation in SNAP25 may influence differences in behavior and neurochemistry in these nonhuman primates.
Keywords: Animals; Behavior, Animal; Ethylene Glycols; Female; Genetic Linkage; Genetic Variation; Homovanillic Acid; Male; Multivariate Analysis; Papio; Pedigree; Personality; Phenols; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Social Behavior; Synaptosomal-Associated Protein 25

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

The genomes of two key bumblebee species with primitive eusocial organization. - Sadd, Ben M; Barribeau, Seth M; Bloch, Guy; de Graaf, Dirk C; Dearden, Peter; Elsik, Christine G; Gadau, Jürgen; Grimmelikhuijzen, Cornelis J P; Hasselmann, Martin; Lozier, Jeffrey D; Robertson, Hugh M; Smagghe, Guy; et al. (Genome Biol, 2015)
BACKGROUND: The shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats. RESULTS: We report the high quality draft genome sequences of Bombus terrestris and Bombus impatiens, two ecologically dominant bumblebees and widely utilized study species. Comparing these new genomes to those of the highly eusocial honeybee Apis mellifera and other Hymenoptera, we identify deeply conserved similarities, as well as novelties key to the biology of these organisms. Some honeybee genome features thought to underpin advanced eusociality are also present in bumblebees, indicating an earlier evolution in the bee lineage. Xenobiotic detoxification and immune genes are similarly depauperate in bumblebees and honeybees, and multiple categories of genes linked to social organization, including development and behavior, show high conservation. Key differences identified include a bias in bumblebee chemoreception towards gustation from olfaction, and striking differences in microRNAs, potentially responsible for gene regulation underlying social and other traits. CONCLUSIONS: These two bumblebee genomes provide a foundation for post-genomic research on these key pollinators and insect societies. Overall, gene repertoires suggest that the route to advanced eusociality in bees was mediated by many small changes in many genes and processes, and not by notable expansion or depauperation.
Keywords: Animals; Bee Venoms; Bees; Behavior, Animal; Chemoreceptor Cells; Chromosome Mapping; Databases, Genetic; Evolution, Molecular; Female; Gene Expression Regulation; Gene Rearrangement; Genes, Insect; Genomics; Interspersed Repetitive Sequences; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Selenoproteins; Sequence Analysis, DNA; Social Behavior; Species Specificity; Synteny

Genomic signatures of cooperation and conflict in the social amoeba. - Ostrowski, Elizabeth A; Shen, Yufeng; Tian, Xiangjun; Sucgang, Richard; Jiang, Huaiyang; Qu, Jiaxin; Katoh-Kurasawa, Mariko; Brock, Debra A; Dinh, Christopher; Lara-Garduno, Fremiet; Lee, Sandra L; Kovar, Christie L; et al. (Curr Biol, 2015)
Cooperative systems are susceptible to invasion by selfish individuals that profit from receiving the social benefits but fail to contribute. These so-called "cheaters" can have a fitness advantage in the laboratory, but it is unclear whether cheating provides an important selective advantage in nature. We used a population genomic approach to examine the history of genes involved in cheating behaviors in the social amoeba Dictyostelium discoideum, testing whether these genes experience rapid evolutionary change as a result of conflict over spore-stalk fate. Candidate genes and surrounding regions showed elevated polymorphism, unusual patterns of linkage disequilibrium, and lower levels of population differentiation, but they did not show greater between-species divergence. The signatures were most consistent with frequency-dependent selection acting to maintain multiple alleles, suggesting that conflict may lead to stalemate rather than an escalating arms race. Our results reveal the evolutionary dynamics of cooperation and cheating and underscore how sequence-based approaches can be used to elucidate the history of conflicts that are difficult to observe directly.
Keywords: Dictyostelium; Evolution, Molecular; Genome, Protozoan; Genomics; Polymorphism, Genetic; Selection, Genetic

Germline mutations in shelterin complex genes are associated with familial glioma. - Bainbridge, Matthew N; Armstrong, Georgina N; Gramatges, M Monica; Bertuch, Alison A; Jhangiani, Shalini N; Doddapaneni, Harsha; Lewis, Lora; Tombrello, Joseph; Tsavachidis, Spyros; Liu, Yanhong; Jalali, Ali; Plon, Sharon E; et al. (J Natl Cancer Inst, 2015)
Gliomas are the most common brain tumor, with several histological subtypes of various malignancy grade. The genetic contribution to familial glioma is not well understood. Using whole exome sequencing of 90 individuals from 55 families, we identified two families with mutations in POT1 (p.G95C, p.E450X), a member of the telomere shelterin complex, shared by both affected individuals in each family and predicted to impact DNA binding and TPP1 binding, respectively. Validation in a separate cohort of 264 individuals from 246 families identified an additional mutation in POT1 (p.D617Efs), also predicted to disrupt TPP1 binding. All families with POT1 mutations had affected members with oligodendroglioma, a specific subtype of glioma more sensitive to irradiation. These findings are important for understanding the origin of glioma and could have importance for the future diagnostics and treatment of glioma.
Keywords: Adult; Aged; Brain Neoplasms; Exome; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Glioma; Humans; Male; Middle Aged; Oligodendroglioma; Pedigree; Shelterin Complex; Telomere-Binding Proteins

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Yuan, Bo; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gozde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Hemichordate genomes and deuterostome origins. - Simakov, Oleg; Kawashima, Takeshi; Marlétaz, Ferdinand; Jenkins, Jerry; Koyanagi, Ryo; Mitros, Therese; Hisata, Kanako; Bredeson, Jessen; Shoguchi, Eiichi; Gyoja, Fuki; Yue, Jia-Xing; Chen, Yi-Chih; et al. (Nature, 2015)
Acorn worms, also known as enteropneust (literally, 'gut-breathing') hemichordates, are marine invertebrates that share features with echinoderms and chordates. Together, these three phyla comprise the deuterostomes. Here we report the draft genome sequences of two acorn worms, Saccoglossus kowalevskii and Ptychodera flava. By comparing them with diverse bilaterian genomes, we identify shared traits that were probably inherited from the last common deuterostome ancestor, and then explore evolutionary trajectories leading from this ancestor to hemichordates, echinoderms and chordates. The hemichordate genomes exhibit extensive conserved synteny with amphioxus and other bilaterians, and deeply conserved non-coding sequences that are candidates for conserved gene-regulatory elements. Notably, hemichordates possess a deuterostome-specific genomic cluster of four ordered transcription factor genes, the expression of which is associated with the development of pharyngeal 'gill' slits, the foremost morphological innovation of early deuterostomes, and is probably central to their filter-feeding lifestyle. Comparative analysis reveals numerous deuterostome-specific gene novelties, including genes found in deuterostomes and marine microbes, but not other animals. The putative functions of these genes can be linked to physiological, metabolic and developmental specializations of the filter-feeding ancestor.
Keywords: Animals; Chordata, Nonvertebrate; Conserved Sequence; Echinodermata; Evolution, Molecular; Genome; Multigene Family; Phylogeny; Signal Transduction; Synteny; Transforming Growth Factor beta

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gozde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.
Keywords: Adult; Age Factors; Aging; BRCA1 Protein; Breast Neoplasms; DNA Repair; Female; Gene Regulatory Networks; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genomics; Genotype; Humans; Hypothalamus; Menopause; Middle Aged; Models, Genetic; Phenotype; Reproduction; Signal Transduction

Loss of Function Mutations in NNT Are Associated With Left Ventricular Noncompaction. - Bainbridge, Matthew N; Davis, Erica E; Choi, Wen-Yee; Dickson, Amy; Martinez, Hugo R; Wang, Min; Dinh, Huyen; Muzny, Donna M; Pignatelli, Ricardo; Katsanis, Nicholas; Boerwinkle, Eric; Gibbs, Richard A; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Left ventricular noncompaction (LVNC) is an autosomal-dominant, genetically heterogeneous cardiomyopathy with variable severity, which may co-occur with cardiac hypertrophy. METHODS AND RESULTS: Here, we generated whole exome sequence data from multiple members from 5 families with LVNC. In 4 of 5 families, the candidate causative mutation segregates with disease in known LVNC genes MYH7 and TPM1. Subsequent sequencing of MYH7 in a larger LVNC cohort identified 7 novel likely disease causing variants. In the fifth family, we identified a frameshift mutation in NNT, a nuclear-encoded mitochondrial protein, not implicated previously in human cardiomyopathies. Resequencing of NNT in additional LVNC families identified a second likely pathogenic missense allele. Suppression of nnt in zebrafish caused early ventricular malformation and contractility defects, probably driven by altered cardiomyocyte proliferation. In vivo complementation studies showed that mutant human NNT failed to rescue nnt morpholino-induced heart dysfunction, indicating a probable haploinsufficiency mechanism. CONCLUSIONS: Together, our data expand the genetic spectrum of LVNC and demonstrate how the intersection of whole exome sequence with in vivo functional studies can accelerate the identification of genes that drive human genetic disorders.
Keywords: Animals; Animals, Genetically Modified; Embryo, Nonmammalian; Exome; Family Health; Female; Frameshift Mutation; Genetic Complementation Test; Genetic Predisposition to Disease; Humans; Isolated Noncompaction of the Ventricular Myocardium; Luminescent Proteins; Male; Microscopy, Confocal; Mitochondrial Proteins; NADP Transhydrogenase, AB-Specific; Pedigree; Sequence Analysis, DNA; Zebrafish

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: Black People; Blood Glucose; Diabetes Mellitus, Type 2; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; White People

Lucilia cuprina genome unlocks parasitic fly biology to underpin future interventions. - Anstead, Clare A; Korhonen, Pasi K; Young, Neil D; Hall, Ross S; Jex, Aaron R; Murali, Shwetha C; Hughes, Daniel S T; Lee, Siu F; Perry, Trent; Stroehlein, Andreas J; Ansell, Brendan R E; Breugelmans, Bert; et al. (Nat Commun, 2015)
Lucilia cuprina is a parasitic fly of major economic importance worldwide. Larvae of this fly invade their animal host, feed on tissues and excretions and progressively cause severe skin disease (myiasis). Here we report the sequence and annotation of the 458-megabase draft genome of Lucilia cuprina. Analyses of this genome and the 14,544 predicted protein-encoding genes provide unique insights into the fly's molecular biology, interactions with the host animal and insecticide resistance. These insights have broad implications for designing new methods for the prevention and control of myiasis.
Keywords: Animals; Diptera; Female; Gene Expression Regulation; Genome, Insect; Insect Proteins; Insecticide Resistance; Insecticides; Larva; Male; Transcriptome

A massive expansion of effector genes underlies gall-formation in the wheat pest Mayetiola destructor. - Zhao, Chaoyang; Escalante, Lucio Navarro; Chen, Hang; Benatti, Thiago R; Qu, Jiaxin; Chellapilla, Sanjay; Waterhouse, Robert M; Wheeler, David; Andersson, Martin N; Bao, Riyue; Batterton, Matthew; Behura, Susanta K; et al. (Curr Biol, 2015)
Gall-forming arthropods are highly specialized herbivores that, in combination with their hosts, produce extended phenotypes with unique morphologies [1]. Many are economically important, and others have improved our understanding of ecology and adaptive radiation [2]. However, the mechanisms that these arthropods use to induce plant galls are poorly understood. We sequenced the genome of the Hessian fly (Mayetiola destructor; Diptera: Cecidomyiidae), a plant parasitic gall midge and a pest of wheat (Triticum spp.), with the aim of identifying genic modifications that contribute to its plant-parasitic lifestyle. Among several adaptive modifications, we discovered an expansive reservoir of potential effector proteins. Nearly 5% of the 20,163 predicted gene models matched putative effector gene transcripts present in the M. destructor larval salivary gland. Another 466 putative effectors were discovered among the genes that have no sequence similarities in other organisms. The largest known arthropod gene family (family SSGP-71) was also discovered within the effector reservoir. SSGP-71 proteins lack sequence homologies to other proteins, but their structures resemble both ubiquitin E3 ligases in plants and E3-ligase-mimicking effectors in plant pathogenic bacteria. SSGP-71 proteins and wheat Skp proteins interact in vivo. Mutations in different SSGP-71 genes avoid the effector-triggered immunity that is directed by the wheat resistance genes H6 and H9. Results point to effectors as the agents responsible for arthropod-induced plant gall formation.
Keywords: Adaptation, Biological; Amino Acid Sequence; Animals; Base Sequence; Chromosomes; Diptera; Larva; Models, Genetic; Molecular Sequence Data; Multigene Family; Phylogeny; Plant Tumors; Sequence Analysis, DNA; Sequence Homology; Sexual Behavior, Animal; Triticum; Two-Hybrid System Techniques; Ubiquitin-Protein Ligases

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Racial Groups; Stroke; White Matter

Mutations in COL27A1 cause Steel syndrome and suggest a founder mutation effect in the Puerto Rican population. - Gonzaga-Jauregui, Claudia; Gamble, Candace N; Yuan, Bo; Penney, Samantha; Jhangiani, Shalini; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Hecht, Jacqueline T (Eur J Hum Genet, 2015)
Osteochondrodysplasias represent a large group of developmental structural disorders that can be caused by mutations in a variety of genes responsible for chondrocyte development, differentiation, mineralization and early ossification. The application of whole-exome sequencing to disorders apparently segregating as Mendelian traits has proven to be an effective approach to disease gene identification for conditions with unknown molecular etiology. We identified a homozygous missense variant p.(Gly697Arg) in COL27A1, in a family with Steel syndrome and no consanguinity. Interestingly, the identified variant seems to have arisen as a founder mutation in the Puerto Rican population.
Keywords: Amino Acid Sequence; Child, Preschool; Comparative Genomic Hybridization; Exome; Female; Fibrillar Collagens; Follow-Up Studies; Founder Effect; Genotype; Hispanic or Latino; Humans; Infant; Male; Molecular Sequence Data; Mutation; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Prostaglandins F; Puerto Rico; Sequence Alignment

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Muzny, Donna; Yuan, Bo; Boerwinkle, Eric; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic or Latino; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

PLD3 variants in population studies. - van der Lee, Sven J; Holstege, Henne; Wong, Tsz Hang; Jakobsdottir, Johanna; Bis, Joshua C; Chouraki, Vincent; van Rooij, Jeroen G J; Grove, Megan L; Smith, Albert V; Amin, Najaf; Choi, Seung-Hoan; Beiser, Alexa S; et al. (Nature, 2015)
Keywords: Alzheimer Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Phospholipase D

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Yu, Fuli; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Muzny, Donna; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Recurrent DGCR8, DROSHA, and SIX homeodomain mutations in favorable histology Wilms tumors. - Walz, Amy L; Ooms, Ariadne; Gadd, Samantha; Gerhard, Daniela S; Smith, Malcolm A; Guidry Auvil, Jaime M; Meerzaman, Daoud; Chen, Qing-Rong; Hsu, Chih Hao; Yan, Chunhua; Nguyen, Cu; Hu, Ying; et al. (Cancer Cell, 2015)
We report the most common single-nucleotide substitution/deletion mutations in favorable histology Wilms tumors (FHWTs) to occur within SIX1/2 (7% of 534 tumors) and microRNA processing genes (miRNAPGs) DGCR8 and DROSHA (15% of 534 tumors). Comprehensive analysis of 77 FHWTs indicates that tumors with SIX1/2 and/or miRNAPG mutations show a pre-induction metanephric mesenchyme gene expression pattern and are significantly associated with both perilobar nephrogenic rests and 11p15 imprinting aberrations. Significantly decreased expression of mature Let-7a and the miR-200 family (responsible for mesenchymal-to-epithelial transition) in miRNAPG mutant tumors is associated with an undifferentiated blastemal histology. The combination of SIX and miRNAPG mutations in the same tumor is associated with evidence of RAS activation and a higher rate of relapse and death.
Keywords: Gene Expression Regulation, Neoplastic; Homeodomain Proteins; Humans; Loss of Heterozygosity; MicroRNAs; Mutation; Neoplasm Recurrence, Local; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Ribonuclease III; RNA-Binding Proteins; Wilms Tumor

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Muzny, Donna M; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Gibbs, Richard A; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

Single-Molecule Sequencing Reveals Estrogen-Regulated Clinically Relevant lncRNAs in Breast Cancer. - Jonsson, Philip; Coarfa, Cristian; Mesmar, Fahmi; Raz, Tal; Rajapakshe, Kimal; Thompson, John F; Gunaratne, Preethi H; Williams, Cecilia (Mol Endocrinol, 2015)
Estrogen receptor (ER)α-positive tumors are commonly treated with ERα antagonists or inhibitors of estrogen synthesis, but most tumors develop resistance, and we need to better understand the pathways that underlie the proliferative and tumorigenic role of this estrogen-activated transcription factor. We here present the first single-molecule sequencing of the estradiol-induced ERα transcriptome in the luminal A-type human breast cancer cell lines MCF7 and T47D. Sequencing libraries were prepared from the polyadenylated RNA fraction after 8 hours of estrogen or vehicle treatment. Single-molecule sequencing was carried out in biological and technical replicates and differentially expressed genes were defined and analyzed for enriched processes. Correlation analysis with clinical expression and survival were performed, and follow-up experiments carried out using time series, chromatin immunoprecipitation and quantitative real-time PCR. We uncovered that ERα in addition to regulating approximately 2000 protein-coding genes, also regulated up to 1000 long noncoding RNAs (lncRNAs). Most of these were up-regulated, and 178 lncRNAs were regulated in both cell lines. We demonstrate that Long Intergenic Non-protein Coding RNA 1016 (LINC01016) and LINC00160 are direct transcriptional targets of ERα, correlate with ERα expression in clinical samples, and show prognostic significance in relation to breast cancer survival. We show that silencing of LINC00160 results in reduced proliferation, demonstrating that lncRNA expression have functional consequences. Our findings suggest that ERα regulation of lncRNAs is clinically relevant and that their functions and potential use as biomarkers for endocrine response are important to explore.
Keywords: Base Sequence; Breast Neoplasms; Cell Line, Tumor; Cell Proliferation; Chromatin Immunoprecipitation; Estradiol; Estrogen Receptor alpha; Estrogens; Female; Gene Expression Regulation, Neoplastic; Gene Silencing; High-Throughput Nucleotide Sequencing; Humans; MCF-7 Cells; Real-Time Polymerase Chain Reaction; RNA, Long Noncoding; Sequence Analysis, DNA; Transcriptional Activation

Targeted sequencing in chromosome 17q linkage region identifies familial glioma candidates in the Gliogene Consortium. - Jalali, Ali; Amirian, E Susan; Bainbridge, Matthew N; Armstrong, Georgina N; Liu, Yanhong; Tsavachidis, Spyros; Jhangiani, Shalini N; Plon, Sharon E; Lau, Ching C; Claus, Elizabeth B; Barnholtz-Sloan, Jill S; Il'yasova, Dora; et al. (Sci Rep, 2015)
Glioma is a rare, but highly fatal, cancer that accounts for the majority of malignant primary brain tumors. Inherited predisposition to glioma has been consistently observed within non-syndromic families. Our previous studies, which involved non-parametric and parametric linkage analyses, both yielded significant linkage peaks on chromosome 17q. Here, we use data from next generation and Sanger sequencing to identify familial glioma candidate genes and variants on chromosome 17q for further investigation. We applied a filtering schema to narrow the original list of 4830 annotated variants down to 21 very rare (<0.1% frequency), non-synonymous variants. Our findings implicate the MYO19 and KIF18B genes and rare variants in SPAG9 and RUNDC1 as candidates worthy of further investigation. Burden testing and functional studies are planned.
Keywords: Adult; Brain Neoplasms; Chromosomes, Human, Pair 17; Family; Female; Genetic Linkage; Genetic Variation; Glioma; Humans; Male; Middle Aged; Mutation; Pedigree; Sequence Analysis, DNA; Young Adult

TET2 and CSMD1 genes affect SBP response to hydrochlorothiazide in never-treated essential hypertensives. - Chittani, Martina; Zaninello, Roberta; Lanzani, Chiara; Frau, Francesca; Ortu, Maria F; Salvi, Erika; Fresu, Giovanni; Citterio, Lorena; Braga, Daniele; Piras, Daniela A; Carpini, Simona Delli; Velayutham, Dinesh; et al. (J Hypertens, 2015)
BACKGROUND: Thiazide diuretics have been recommended as a first-line antihypertensive treatment, although the choice of 'the right drug in the individual essential hypertensive patient' remains still empirical. Essential hypertension is a complex, polygenic disease derived from the interaction of patient's genetic background with the environment. Pharmacogenomics could be a useful tool to pinpoint gene variants involved in antihypertensive drug response, thus optimizing therapeutic advantages and minimizing side effects. METHODS AND RESULTS: We looked for variants associated with blood pressure response to hydrochlorothiazide over an 8-week follow-up by means of a genome-wide association analysis in two Italian cohorts of never-treated essential hypertensive patients: 343 samples from Sardinia and 142 from Milan. TET2 and CSMD1 as plausible candidate genes to affect SBP response to hydrochlorothiazide were identified. The specificity of our findings for hydrochlorothiazide was confirmed in an independent cohort of essential hypertensive patients treated with losartan. Our best findings were also tested for replication in four independent hypertensive samples of European Ancestry, such as GENetics of drug RESponsiveness in essential hypertension, Genetic Epidemiology of Responses to Antihypertensives, NORdic DILtiazem intervention, Pharmacogenomics Evaluation of Antihypertensive Responses, and Campania Salute Network-StayOnDiur. We validated a polymorphism in CSMD1 and UGGT2. CONCLUSION: This exploratory study reports two plausible loci associated with SBP response to hydrochlorothiazide: TET2, an aldosterone-responsive mediator of αENaC gene transcription; and CSMD1, previously described as associated with hypertension in a case-control study.
Keywords: Adult; Aged; Aldosterone; Antihypertensive Agents; Blood Pressure; Case-Control Studies; Dioxygenases; DNA-Binding Proteins; Essential Hypertension; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Italy; Losartan; Male; Membrane Proteins; Middle Aged; Pharmacogenetics; Proto-Oncogene Proteins; Sodium Chloride Symporter Inhibitors; Systole; Tumor Suppressor Proteins; White People

Transethnic meta-analysis suggests genetic variation in the HEME pathway influences potassium response in patients treated with hydrochlorothiazide. - Del-Aguila, J L; Cooper-Dehoff, R M; Chapman, A B; Gums, J G; Beitelshees, A L; Bailey, K; Turner, S T; Johnson, J A; Boerwinkle, E (Pharmacogenomics J, 2015)
Hypokalemia is a recognized adverse effect of thiazide diuretic treatment. This phenomenon, which may impair insulin secretion, has been suggested to be a reason for the adverse effects on glucose metabolism associated with thiazide diuretic treatment of hypertension. However, the mechanisms underlying thiazide diuretic-induced hypokalemia are not well understood. In an effort to identify genes or genomic regions associated with potassium response to hydrochlorothiazide, without a priori knowledge of biologic effects, we performed a genome-wide association study and a multiethnic meta-analysis in 718 European- and African-American hypertensive participants from two different pharmacogenetic studies. Single-nucleotide polymorphisms rs10845697 (Bayes factor=5.560) on chromosome 12, near to the HEME binding protein 1 gene, and rs11135740 (Bayes factor=5.258) on chromosome 8, near to the Mitoferrin-1 gene, reached genome-wide association study significance (Bayes factor >5). These results, if replicated, suggest a novel mechanism involving effects of genes in the HEME pathway influencing hydrochlorothiazide-induced renal potassium loss.
Keywords: Antihypertensive Agents; Bayes Theorem; Black or African American; Carrier Proteins; Cation Transport Proteins; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 8; Female; Genome-Wide Association Study; Heme; Heme-Binding Proteins; Hemeproteins; Humans; Hydrochlorothiazide; Hypertension; Hypokalemia; Male; Middle Aged; Mitochondrial Proteins; Polymorphism, Single Nucleotide; Potassium; White People

Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. - Collison, Frederick T; Xie, Yajing Angela; Gambin, Tomasz; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Fishman, Gerald A; Allikmets, Rando (Ophthalmic Genet, 2015)
BACKGROUND: Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. MATERIALS AND METHODS: An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. RESULTS: Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. CONCLUSIONS: In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.
Keywords: Adult; Carrier Proteins; Electroretinography; Exome; Female; Genetic Testing; Heterozygote; Homocystinuria; Humans; Macular Degeneration; Mutation; Oxidoreductases; Pedigree; Scotoma; Sequence Analysis, DNA; Tomography, Optical Coherence; Visual Acuity; Visual Fields; Vitamin B 12; Vitamin B 12 Deficiency; Vitamin B Complex

Whole-exome sequencing identifies homozygous GPR161 mutation in a family with pituitary stalk interruption syndrome. - Karaca, Ender; Buyukkaya, Ramazan; Pehlivan, Davut; Charng, Wu-Lin; Yaykasli, Kursat O; Bayram, Yavuz; Gambin, Tomasz; Withers, Marjorie; Atik, Mehmed M; Arslanoglu, Ilknur; Bolu, Semih; Erdin, Serkan; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Pituitary stalk interruption syndrome (PSIS) is a rare, congenital anomaly of the pituitary gland characterized by pituitary gland insufficiency, thin or discontinuous pituitary stalk, anterior pituitary hypoplasia, and ectopic positioning of the posterior pituitary gland (neurohypophysis). The clinical presentation of patients with PSIS varies from isolated growth hormone (GH) deficiency to combined pituitary insufficiency and accompanying extrapituitary findings. Mutations in HESX1, LHX4, OTX2, SOX3, and PROKR2 have been associated with PSIS in less than 5% of cases; thus, the underlying genetic etiology for the vast majority of cases remains to be determined. OBJECTIVE: We applied whole-exome sequencing (WES) to a consanguineous family with two affected siblings who have pituitary gland insufficiency and radiographic findings of hypoplastic (thin) pituitary gland, empty sella, ectopic neurohypophysis, and interrupted pitiutary stalk-characteristic clinical diagnostic findings of PSIS. DESIGN AND PARTICIPANTS: WES was applied to two affected and one unaffected siblings. RESULTS: WES of two affected and one unaffected sibling revealed a unique homozygous missense mutation in GPR161, which encodes the orphan G protein-coupled receptor 161, a protein responsible for transducing extracellular signals across the plasma membrane into the cell. CONCLUSION: Mutations of GPR161 may be implicated as a potential novel cause of PSIS.
Keywords: Adolescent; Child, Preschool; Exome; Female; Genome-Wide Association Study; Humans; Hypopituitarism; Mutation; Pituitary Gland; Receptors, G-Protein-Coupled

Whole-exome sequencing identifies novel homozygous mutation in NPAS2 in family with nonobstructive azoospermia. - Ramasamy, Ranjith; Bakırcıoğlu, M Emre; Cengiz, Cenk; Karaca, Ender; Scovell, Jason; Jhangiani, Shalini N; Akdemir, Zeynep C; Bainbridge, Matthew; Yu, Yao; Huff, Chad; Gibbs, Richard A; Lupski, James R; et al. (Fertil Steril, 2015)
OBJECTIVE: To investigate the genetic cause of nonobstructive azoospermia (NOA) in a consanguineous Turkish family through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. DESIGN: Whole-exome sequencing (WES). SETTING: Research laboratory. PATIENT(S): Two siblings in a consanguineous family with NOA. INTERVENTION(S): Validating all variants passing filter criteria with Sanger sequencing to confirm familial segregation and absence in the control population. MAIN OUTCOME MEASURE(S): Discovery of a mutation that could potentially cause NOA. RESULT(S): A novel nonsynonymous mutation in the neuronal PAS-2 domain (NPAS2) was identified in a consanguineous family from Turkey. This mutation in exon 14 (chr2: 101592000 C>G) of NPAS2 is likely a disease-causing mutation as it is predicted to be damaging, it is a novel variant, and it segregates with the disease. Family segregation of the variants showed the presence of the homozygous mutation in the three brothers with NOA and a heterozygous mutation in the mother as well as one brother and one sister who were both fertile. The mutation is not found in the single-nucleotide polymorphism database, the 1000 Genomes Project, the Baylor College of Medicine cohort of 500 Turkish patients (not a population-specific polymorphism), or the matching 50 fertile controls. CONCLUSION(S): With the use of WES we identified a novel homozygous mutation in NPAS2 as a likely disease-causing variant in a Turkish family diagnosed with NOA. Our data reinforce the clinical role of WES in the molecular diagnosis of highly heterogeneous genetic diseases for which conventional genetic approaches have previously failed to find a molecular diagnosis.
Keywords: Adult; Azoospermia; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Exome; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree

Whole-exome sequencing points to considerable genetic heterogeneity of cerebral palsy. - McMichael, G; Bainbridge, M N; Haan, E; Corbett, M; Gardner, A; Thompson, S; van Bon, B W M; van Eyk, C L; Broadbent, J; Reynolds, C; O'Callaghan, M E; Nguyen, L S; et al. (Mol Psychiatry, 2015)
Cerebral palsy (CP) is a common, clinically heterogeneous group of disorders affecting movement and posture. Its prevalence has changed little in 50 years and the causes remain largely unknown. The genetic contribution to CP causation has been predicted to be ~2%. We performed whole-exome sequencing of 183 cases with CP including both parents (98 cases) or one parent (67 cases) and 18 singleton cases (no parental DNA). We identified and validated 61 de novo protein-altering variants in 43 out of 98 (44%) case-parent trios. Initial prioritization of variants for causality was by mutation type, whether they were known or predicted to be deleterious and whether they occurred in known disease genes whose clinical spectrum overlaps CP. Further, prioritization used two multidimensional frameworks-the Residual Variation Intolerance Score and the Combined Annotation-dependent Depletion score. Ten de novo mutations in three previously identified disease genes (TUBA1A (n=2), SCN8A (n=1) and KDM5C (n=1)) and in six novel candidate CP genes (AGAP1, JHDM1D, MAST1, NAA35, RFX2 and WIPI2) were predicted to be potentially pathogenic for CP. In addition, we identified four predicted pathogenic, hemizygous variants on chromosome X in two known disease genes, L1CAM and PAK3, and in two novel candidate CP genes, CD99L2 and TENM1. In total, 14% of CP cases, by strict criteria, had a potentially disease-causing gene variant. Half were in novel genes. The genetic heterogeneity highlights the complexity of the genetic contribution to CP. Function and pathway studies are required to establish the causative role of these putative pathogenic CP genes.
Keywords: Adult; Animals; Cerebral Palsy; Cohort Studies; Exome; Female; Gene Library; Genetic Heterogeneity; Genetic Predisposition to Disease; Gestational Age; Humans; Male; Mutation; Parents; Sequence Analysis, DNA

X-linked acrogigantism syndrome: clinical profile and therapeutic responses. - Beckers, Albert; Lodish, Maya Beth; Trivellin, Giampaolo; Rostomyan, Liliya; Lee, Misu; Faucz, Fabio R; Bo Yuan; Choong, Catherine S; Caberg, Jean-Hubert; Verrua, Elisa; Naves, Luciana Ansaneli; Cheetham, Tim D; et al. (Endocr Relat Cancer, 2015)
X-linked acrogigantism (X-LAG) is a new syndrome of pituitary gigantism, caused by microduplications on chromosome Xq26.3, encompassing the gene GPR101, which is highly upregulated in pituitary tumors. We conducted this study to explore the clinical, radiological, and hormonal phenotype and responses to therapy in patients with X-LAG syndrome. The study included 18 patients (13 sporadic) with X-LAG and microduplication of chromosome Xq26.3. All sporadic cases had unique duplications and the inheritance pattern in two families was dominant, with all Xq26.3 duplication carriers being affected. Patients began to grow rapidly as early as 2-3 months of age (median 12 months). At diagnosis (median delay 27 months), patients had a median height and weight standard deviation scores (SDS) of >+3.9 SDS. Apart from the increased overall body size, the children had acromegalic symptoms including acral enlargement and facial coarsening. More than a third of cases had increased appetite. Patients had marked hypersecretion of GH/IGF1 and usually prolactin, due to a pituitary macroadenoma or hyperplasia. Primary neurosurgical control was achieved with extensive anterior pituitary resection, but postoperative hypopituitarism was frequent. Control with somatostatin analogs was not readily achieved despite moderate to high levels of expression of somatostatin receptor subtype-2 in tumor tissue. Postoperative use of adjuvant pegvisomant resulted in control of IGF1 in all five cases where it was employed. X-LAG is a new infant-onset gigantism syndrome that has a severe clinical phenotype leading to challenging disease management.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Chromosomes, Human, X; Female; Gigantism; Humans; Infant; Male; Pituitary Neoplasms; Young Adult

ADAR2 induces reproducible changes in sequence and abundance of mature microRNAs in the mouse brain. - Vesely, Cornelia; Tauber, Stefanie; Fritz J Sedlazeck; Tajaddod, Mansoureh; von Haeseler, Arndt; Jantsch, Michael F (Nucleic Acids Res, 2014)
Adenosine deaminases that act on RNA (ADARs) deaminate adenosines to inosines in double-stranded RNAs including miRNA precursors. A to I editing is widespread and required for normal life. By comparing deep sequencing data of brain miRNAs from wild-type and ADAR2 deficient mouse strains, we detect editing sites and altered miRNA processing at high sensitivity. We detect 48 novel editing events in miRNAs. Some editing events reach frequencies of up to 80%. About half of all editing events depend on ADAR2 while some miRNAs are preferentially edited by ADAR1. Sixty-four percent of all editing events are located within the seed region of mature miRNAs. For the highly edited miR-3099, we experimentally prove retargeting of the edited miRNA to novel 3' UTRs. We show further that an abundant editing event in miR-497 promotes processing by Drosha of the corresponding pri-miRNA. We also detect reproducible changes in the abundance of specific miRNAs in ADAR2-deficient mice that occur independent of adjacent A to I editing events. This indicates that ADAR2 binding but not editing of miRNA precursors may influence their processing. Correlating with changes in miRNA abundance we find misregulation of putative targets of these miRNAs in the presence or absence of ADAR2.
Keywords: Adenosine Deaminase; Animals; Base Sequence; Brain; Cell Line; HEK293 Cells; Humans; Mice; Mice, Knockout; MicroRNAs; RNA Editing; RNA Processing, Post-Transcriptional; RNA-Binding Proteins

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; Aged; Alleles; Animals; Black People; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides; White People

Characterization of HPV and host genome interactions in primary head and neck cancers. - Parfenov, Michael; Pedamallu, Chandra Sekhar; Gehlenborg, Nils; Freeman, Samuel S; Danilova, Ludmila; Bristow, Christopher A; Lee, Semin; Hadjipanayis, Angela G; Ivanova, Elena V; Wilkerson, Matthew D; Protopopov, Alexei; Yang, Lixing; et al. (Proc Natl Acad Sci U S A, 2014)
Previous studies have established that a subset of head and neck tumors contains human papillomavirus (HPV) sequences and that HPV-driven head and neck cancers display distinct biological and clinical features. HPV is known to drive cancer by the actions of the E6 and E7 oncoproteins, but the molecular architecture of HPV infection and its interaction with the host genome in head and neck cancers have not been comprehensively described. We profiled a cohort of 279 head and neck cancers with next generation RNA and DNA sequencing and show that 35 (12.5%) tumors displayed evidence of high-risk HPV types 16, 33, or 35. Twenty-five cases had integration of the viral genome into one or more locations in the human genome with statistical enrichment for genic regions. Integrations had a marked impact on the human genome and were associated with alterations in DNA copy number, mRNA transcript abundance and splicing, and both inter- and intrachromosomal rearrangements. Many of these events involved genes with documented roles in cancer. Cancers with integrated vs. nonintegrated HPV displayed different patterns of DNA methylation and both human and viral gene expressions. Together, these data provide insight into the mechanisms by which HPV interacts with the human genome beyond expression of viral oncoproteins and suggest that specific integration events are an integral component of viral oncogenesis.
Keywords: Base Sequence; DNA Methylation; Gene Expression Regulation, Neoplastic; Genes, Neoplasm; Genome, Human; Head and Neck Neoplasms; Host-Pathogen Interactions; Humans; Molecular Sequence Data; Papillomaviridae; Virus Integration

Comparative validation of the D. melanogaster modENCODE transcriptome annotation. - Chen, Zhen-Xia; Sturgill, David; Qu, Jiaxin; Jiang, Huaiyang; Park, Soo; Boley, Nathan; Suzuki, Ana Maria; Fletcher, Anthony R; Plachetzki, David C; FitzGerald, Peter C; Artieri, Carlo G; Atallah, Joel; et al. (Genome Res, 2014)
Accurate gene model annotation of reference genomes is critical for making them useful. The modENCODE project has improved the D. melanogaster genome annotation by using deep and diverse high-throughput data. Since transcriptional activity that has been evolutionarily conserved is likely to have an advantageous function, we have performed large-scale interspecific comparisons to increase confidence in predicted annotations. To support comparative genomics, we filled in divergence gaps in the Drosophila phylogeny by generating draft genomes for eight new species. For comparative transcriptome analysis, we generated mRNA expression profiles on 81 samples from multiple tissues and developmental stages of 15 Drosophila species, and we performed cap analysis of gene expression in D. melanogaster and D. pseudoobscura. We also describe conservation of four distinct core promoter structures composed of combinations of elements at three positions. Overall, each type of genomic feature shows a characteristic divergence rate relative to neutral models, highlighting the value of multispecies alignment in annotating a target genome that should prove useful in the annotation of other high priority genomes, especially human and other mammalian genomes that are rich in noncoding sequences. We report that the vast majority of elements in the annotation are evolutionarily conserved, indicating that the annotation will be an important springboard for functional genetic testing by the Drosophila community.
Keywords: Animals; Cluster Analysis; Computational Biology; Drosophila melanogaster; Evolution, Molecular; Exons; Female; Gene Expression Profiling; Genome, Insect; Humans; Male; Molecular Sequence Annotation; Nucleotide Motifs; Phylogeny; Position-Specific Scoring Matrices; Promoter Regions, Genetic; Reproducibility of Results; RNA Editing; RNA Splice Sites; RNA Splicing; Transcription Initiation Site; Transcriptome

Design and anticipated outcomes of the eMERGE-PGx project: a multicenter pilot for preemptive pharmacogenomics in electronic health record systems. - Rasmussen-Torvik, L J; Stallings, S C; Gordon, A S; Almoguera, B; Basford, M A; Bielinski, S J; Brautbar, A; Brilliant, M H; Carrell, D S; Connolly, J J; Crosslin, D R; Doheny, K F; et al. (Clin Pharmacol Ther, 2014)
We describe here the design and initial implementation of the eMERGE-PGx project. eMERGE-PGx, a partnership of the Electronic Medical Records and Genomics Network and the Pharmacogenomics Research Network, has three objectives: (i) to deploy PGRNseq, a next-generation sequencing platform assessing sequence variation in 84 proposed pharmacogenes, in nearly 9,000 patients likely to be prescribed drugs of interest in a 1- to 3-year time frame across several clinical sites; (ii) to integrate well-established clinically validated pharmacogenetic genotypes into the electronic health record with associated clinical decision support and to assess process and clinical outcomes of implementation; and (iii) to develop a repository of pharmacogenetic variants of unknown significance linked to a repository of electronic health record-based clinical phenotype data for ongoing pharmacogenomics discovery. We describe site-specific project implementation and anticipated products, including genetic variant and phenotype data repositories, novel variant association studies, clinical decision support modules, clinical and process outcomes, approaches to managing incidental findings, and patient and clinician education methods.
Keywords: Adolescent; Aged; Child; Databases, Genetic; Drug Therapy; Electronic Health Records; Female; Genetic Association Studies; Genetic Variation; Genotype; Humans; Knowledge Bases; Male; Middle Aged; Pharmacogenetics; Phenotype; Pilot Projects; Sequence Analysis, DNA; Young Adult

Diagnosis of ALG12-CDG by exome sequencing in a case of severe skeletal dysplasia. - Murali, Chaya; Lu, James T; Jain, Mahim; Liu, David S; Lachman, Ralph; Gibbs, Richard A; Lee, Brendan H; Cohn, Daniel; Campeau, Philippe M (Mol Genet Metab Rep, 2014)
Congenital Disorder of Glycosylation type Ig (ALG12-CDG) is part of a group of autosomal recessive conditions caused by deficiency of proteins involved in the assembly of dolichol-oligosaccharides used for protein N-glycosylation. In ALG12-CDG, the enzyme affected is encoded by the gene. Affected individuals present clinically with neurodevelopmental delay, growth retardation, immune deficiency, male genital hypoplasia, and cardiomyopathy. A total of six individuals have been reported in the literature. Here, we present an infant with rhizomelic short stature, talipes equinovarus, platyspondyly, and joint dislocations. The infant had marked underossification of the pubic bones. Exome sequencing was performed and two deletions, each resulting in frameshifts, were found in . A review of the literature revealed two infants with ALG12-CDG and a severe skeletal dysplasia, including under-ossification of cervical vertebrae, pubic bones, and knees; in addition to talipes equinovarus and rhizomelic short stature. The phenotype of the individual we describe resembles pseudodiastrophic dysplasia and we discuss similarities and differences between ALG12-CDG and pseudodiastrophic dysplasia. The differential diagnosis in selected undiagnosed skeletal dysplasias should include CDGs.

Draft genome sequences and description of Lactobacillus rhamnosus strains L31, L34, and L35. - Boonma, Prapaporn; Spinler, Jennifer K; Qin, Xiang; Jittaprasatsin, Chutima; Muzny, Donna M; Doddapaneni, Harsha; Gibbs, Richard; Petrosino, Joe; Tumwasorn, Somying; Versalovic, James (Stand Genomic Sci, 2014)
Lactobacillus rhamnosus is a facultative, lactic acid bacterium in the phylum Firmicutes. Lactobacillus spp. are generally considered beneficial, and specific strains of L. rhamnosus are validated probiotics. We describe the draft genomes of three L. rhamnosus strains (L31, L34, and L35) isolated from the feces of Thai breastfed infants, which exhibit anti-inflammatory properties in vitro. The three genomes range between 2.8 - 2.9 Mb, and contain approximately 2,700 protein coding genes.

Drosophila eyes absent is required for normal cone and pigment cell development. - Karandikar, Umesh C; Jin, Meng; Jusiak, Barbara; Kwak, SuJin; Chen, Rui; Mardon, Graeme (PLoS One, 2014)
In Drosophila, development of the compound eye is orchestrated by a network of highly conserved transcriptional regulators known as the retinal determination (RD) network. The retinal determination gene eyes absent (eya) is expressed in most cells within the developing eye field, from undifferentiated retinal progenitors to photoreceptor cells whose differentiation begins at the morphogenetic furrow (MF). Loss of eya expression leads to an early block in retinal development, making it impossible to study the role of eya expression during later steps of retinal differentiation. We have identified two new regulatory regions that control eya expression during retinal development. These two enhancers are necessary to maintain eya expression anterior to the MF (eya-IAM) and in photoreceptors (eya-PSE), respectively. We find that deleting these enhancers affects developmental events anterior to the MF as well as retinal differentiation posterior to the MF. In line with previous results, we find that reducing eya expression anterior to the MF affects several early steps during early retinal differentiation, including cell cycle arrest and expression of the proneural gene ato. Consistent with previous observations that suggest a role for eya in cell proliferation during early development we find that deletion of eya-IAM leads to a marked reduction in the size of the adult retinal field. On the other hand, deletion of eya-PSE leads to defects in cone and pigment cell development. In addition we find that eya expression is necessary to activate expression of the cone cell marker Cut and to regulate levels of the Hedgehog pathway effector Ci. In summary, our study uncovers novel aspects of eya-mediated regulation of eye development. The genetic tools generated in this study will allow for a detailed study of how the RD network regulates key steps in eye formation.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Cell Cycle Checkpoints; Cell Differentiation; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Homeodomain Proteins; Larva; Nerve Tissue Proteins; Nuclear Proteins; Organogenesis; Retinal Cone Photoreceptor Cells; Retinal Pigment Epithelium; Transcription Factors

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Epigenomic profiling of young and aged HSCs reveals concerted changes during aging that reinforce self-renewal. - Sun, Deqiang; Luo, Min; Jeong, Mira; Rodriguez, Benjamin; Xia, Zheng; Hannah, Rebecca; Wang, Hui; Le, Thuc; Faull, Kym F; Chen, Rui; Gu, Hongcang; Bock, Christoph; et al. (Cell Stem Cell, 2014)
To investigate the cell-intrinsic aging mechanisms that erode the function of somatic stem cells during aging, we have conducted a comprehensive integrated genomic analysis of young and aged cells. We profiled the transcriptome, DNA methylome, and histone modifications of young and old murine hematopoietic stem cells (HSCs). Transcriptome analysis indicated reduced TGF-β signaling and perturbation of genes involved in HSC proliferation and differentiation. Aged HSCs exhibited broader H3K4me3 peaks across HSC identity and self-renewal genes and showed increased DNA methylation at transcription factor binding sites associated with differentiation-promoting genes combined with a reduction at genes associated with HSC maintenance. Altogether, these changes reinforce HSC self-renewal and diminish differentiation, paralleling phenotypic HSC aging behavior. Ribosomal biogenesis emerged as a particular target of aging with increased transcription of ribosomal protein and RNA genes and hypomethylation of rRNA genes. This data set will serve as a reference for future epigenomic analysis of stem cell aging.
Keywords: Animals; Cell Differentiation; Cells, Cultured; Cellular Senescence; Chromatin Immunoprecipitation; Epigenomics; Hematopoietic Stem Cells; Male; Mice; Transforming Growth Factor beta

Evidence for stabilizing selection on codon usage in chromosomal rearrangements of Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Zhu, Dianhui; Batterton, Matthew; Chao, Hsu; Dugan, Shannon; Javaid, Mehwish; Jayaseelan, Joy C; Lee, Sandra; Li, Mingmei; Ongeri, Fiona; Qi, Sulan; et al. (G3 (Bethesda), 2014)
There has been a renewed interest in investigating the role of stabilizing selection acting on genome-wide traits such as codon usage bias. Codon bias, when synonymous codons are used at unequal frequencies, occurs in a wide variety of taxa. Standard evolutionary models explain the maintenance of codon bias through a balance of genetic drift, mutation and weak purifying selection. The efficacy of selection is expected to be reduced in regions of suppressed recombination. Contrary to observations in Drosophila melanogaster, some recent studies have failed to detect a relationship between the recombination rate, intensity of selection acting at synonymous sites, and the magnitude of codon bias as predicted under these standard models. Here, we examined codon bias in 2798 protein coding loci on the third chromosome of D. pseudoobscura using whole-genome sequences of 47 individuals, representing five common third chromosome gene arrangements. Fine-scale recombination maps were constructed using more than 1 million segregating sites. As expected, recombination was demonstrated to be significantly suppressed between chromosome arrangements, allowing for a direct examination of the relationship between recombination, selection, and codon bias. As with other Drosophila species, we observe a strong mutational bias away from the most frequently used codons. We find the rate of synonymous and nonsynonymous polymorphism is variable between different amino acids. However, we do not observe a reduction in codon bias or the strength of selection in regions of suppressed recombination as expected. Instead, we find that the interaction between weak stabilizing selection and mutational bias likely plays a role in shaping the composition of synonymous codons across the third chromosome in D. pseudoobscura.
Keywords: Animals; Chromosomes; Codon; Drosophila; High-Throughput Nucleotide Sequencing; Polymorphism, Single Nucleotide; Recombination, Genetic; Selection, Genetic; Sequence Analysis, DNA

The first myriapod genome sequence reveals conservative arthropod gene content and genome organisation in the centipede Strigamia maritima. - Chipman, Ariel D; Ferrier, David E K; Brena, Carlo; Qu, Jiaxin; Hughes, Daniel S T; Schröder, Reinhard; Torres-Oliva, Montserrat; Znassi, Nadia; Jiang, Huaiyang; Almeida, Francisca C; Alonso, Claudio R; Apostolou, Zivkos; et al. (PLoS Biol, 2014)
Myriapods (e.g., centipedes and millipedes) display a simple homonomous body plan relative to other arthropods. All members of the class are terrestrial, but they attained terrestriality independently of insects. Myriapoda is the only arthropod class not represented by a sequenced genome. We present an analysis of the genome of the centipede Strigamia maritima. It retains a compact genome that has undergone less gene loss and shuffling than previously sequenced arthropods, and many orthologues of genes conserved from the bilaterian ancestor that have been lost in insects. Our analysis locates many genes in conserved macro-synteny contexts, and many small-scale examples of gene clustering. We describe several examples where S. maritima shows different solutions from insects to similar problems. The insect olfactory receptor gene family is absent from S. maritima, and olfaction in air is likely effected by expansion of other receptor gene families. For some genes S. maritima has evolved paralogues to generate coding sequence diversity, where insects use alternate splicing. This is most striking for the Dscam gene, which in Drosophila generates more than 100,000 alternate splice forms, but in S. maritima is encoded by over 100 paralogues. We see an intriguing linkage between the absence of any known photosensory proteins in a blind organism and the additional absence of canonical circadian clock genes. The phylogenetic position of myriapods allows us to identify where in arthropod phylogeny several particular molecular mechanisms and traits emerged. For example, we conclude that juvenile hormone signalling evolved with the emergence of the exoskeleton in the arthropods and that RR-1 containing cuticle proteins evolved in the lineage leading to Mandibulata. We also identify when various gene expansions and losses occurred. The genome of S. maritima offers us a unique glimpse into the ancestral arthropod genome, while also displaying many adaptations to its specific life history.
Keywords: Animals; Arthropods; Circadian Rhythm Signaling Peptides and Proteins; DNA Methylation; Evolution, Molecular; Female; Genome; Genome, Mitochondrial; Hormones; Male; Multigene Family; Phylogeny; Polymorphism, Genetic; Protein Kinases; Receptors, Odorant; RNA, Untranslated; Selenoproteins; Sex Chromosomes; Synteny; Transcription Factors

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analyses suggest NELL1 influences adverse metabolic response to HCTZ in African Americans. - Del-Aguila, J L; Beitelshees, A L; Cooper-Dehoff, R M; Chapman, A B; Gums, J G; Bailey, K; Gong, Y; Turner, S T; Johnson, J A; Eric Boerwinkle (Pharmacogenomics J, 2014)
Hydrochlorothiazide (HCTZ) is one of the most widely prescribed antihypertensive medications. Although it is well known that HCTZ is associated with hyperglycemia and hypertriglyceridemia, the mechanisms underlying these adverse effects are not well understood. We performed a genome-wide association study and meta-analysis of the change in fasting plasma glucose and triglycerides in response to HCTZ from two different clinical trials: the Pharmacogenomic Evaluation of Antihypertensive Responses and the Genetic Epidemiology of Responses to Antihypertensive studies. Two single-nucleotide polymorphisms (rs12279250 and rs4319515 (r(2)=0.73)), located at 11p15.1 in the NELL1 gene, achieved genome-wide significance for association with change in fasting plasma triglycerides in African Americans, whereby each variant allele was associated with a 28 mg dl(-1) increase in the change in triglycerides. NELL1 encodes a cytoplasmic protein that contains epidermal growth factor-like repeats and has been shown to represses adipogenic differentiation. These findings may represent a novel mechanism underlying HCTZ-induced adverse metabolic effects.
Keywords: Adipogenesis; Antihypertensive Agents; Black or African American; Blood Glucose; Calcium-Binding Proteins; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Lipid Metabolism; Nerve Tissue Proteins; Triglycerides

Genome-wide DNA binding pattern of the homeodomain transcription factor Sine oculis (So) in the developing eye of . - Jusiak, Barbara; Wang, Feng; Karandikar, Umesh C; Kwak, Su-Jin; Wang, Hui; Chen, Rui; Mardon, Graeme (Genom Data, 2014)
The eye of the fruit fly provides a highly tractable genetic model system for the study of animal development, and many genes that regulate eye formation have homologs implicated in human development and disease. Among these is the homeobox gene (), which encodes a homeodomain transcription factor (TF) that is both necessary for eye development and sufficient to reprogram a subset of cells outside the normal eye field toward an eye fate. We have performed a genome-wide analysis of So binding to DNA prepared from developing eye tissue in order to identify candidate direct targets of So-mediated transcriptional regulation, as described in our recent article [1]. The data are available from NCBI Gene Expression Omnibus (GEO) with the accession number GSE52943. Here we describe the methods, data analysis, and quality control of our So ChIP-seq dataset.

Genomic encyclopedia of bacteria and archaea: sequencing a myriad of type strains. - Kyrpides, Nikos C; Hugenholtz, Philip; Eisen, Jonathan A; Woyke, Tanja; Göker, Markus; Parker, Charles T; Amann, Rudolf; Beck, Brian J; Chain, Patrick S G; Chun, Jongsik; Colwell, Rita R; Danchin, Antoine; et al. (PLoS Biol, 2014)
Microbes hold the key to life. They hold the secrets to our past (as the descendants of the earliest forms of life) and the prospects for our future (as we mine their genes for solutions to some of the planet's most pressing problems, from global warming to antibiotic resistance). However, the piecemeal approach that has defined efforts to study microbial genetic diversity for over 20 years and in over 30,000 genome projects risks squandering that promise. These efforts have covered less than 20% of the diversity of the cultured archaeal and bacterial species, which represent just 15% of the overall known prokaryotic diversity. Here we call for the funding of a systematic effort to produce a comprehensive genomic catalog of all cultured Bacteria and Archaea by sequencing, where available, the type strain of each species with a validly published name (currently∼11,000). This effort will provide an unprecedented level of coverage of our planet's genetic diversity, allow for the large-scale discovery of novel genes and functions, and lead to an improved understanding of microbial evolution and function in the environment.
Keywords: Archaea; Bacteria; Databases, Genetic; Genome, Archaeal; Genome, Bacterial; Genomics; Phylogeny; Sequence Analysis, DNA

Germline rearrangements in families with strong family history of glioma and malignant melanoma, colon, and breast cancer. - Andersson, Ulrika; Wibom, Carl; Cederquist, Kristina; Aradottir, Steina; Borg, Ake; Armstrong, Georgina N; Shete, Sanjay; Lau, Ching C; Bainbridge, Matthew N; Claus, Elizabeth B; Barnholtz-Sloan, Jill; Lai, Rose; et al. (Neuro Oncol, 2014)
BACKGROUND: Although familial susceptibility to glioma is known, the genetic basis for this susceptibility remains unidentified in the majority of glioma-specific families. An alternative approach to identifying such genes is to examine cancer pedigrees, which include glioma as one of several cancer phenotypes, to determine whether common chromosomal modifications might account for the familial aggregation of glioma and other cancers. METHODS: Germline rearrangements in 146 glioma families (from the Gliogene Consortium; http://www.gliogene.org/) were examined using multiplex ligation-dependent probe amplification. These families all had at least 2 verified glioma cases and a third reported or verified glioma case in the same family or 2 glioma cases in the family with at least one family member affected with melanoma, colon, or breast cancer.The genomic areas covering TP53, CDKN2A, MLH1, and MSH2 were selected because these genes have been previously reported to be associated with cancer pedigrees known to include glioma. RESULTS: We detected a single structural rearrangement, a deletion of exons 1-6 in MSH2, in the proband of one family with 3 cases with glioma and one relative with colon cancer. CONCLUSIONS: Large deletions and duplications are rare events in familial glioma cases, even in families with a strong family history of cancers that may be involved in known cancer syndromes.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Brain Neoplasms; Breast Neoplasms; Checkpoint Kinase 2; Child, Preschool; Colonic Neoplasms; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Glioma; Humans; Male; Melanoma; Middle Aged; MutL Protein Homolog 1; MutS Homolog 2 Protein; Nuclear Proteins; Pedigree; Tumor Suppressor Protein p53; Young Adult

Gibbon genome and the fast karyotype evolution of small apes. - Carbone, Lucia; Harris, R Alan; Gnerre, Sante; Veeramah, Krishna R; Lorente-Galdos, Belen; Huddleston, John; Meyer, Thomas J; Herrero, Javier; Roos, Christian; Aken, Bronwen; Anaclerio, Fabio; Archidiacono, Nicoletta; et al. (Nature, 2014)
Gibbons are small arboreal apes that display an accelerated rate of evolutionary chromosomal rearrangement and occupy a key node in the primate phylogeny between Old World monkeys and great apes. Here we present the assembly and analysis of a northern white-cheeked gibbon (Nomascus leucogenys) genome. We describe the propensity for a gibbon-specific retrotransposon (LAVA) to insert into chromosome segregation genes and alter transcription by providing a premature termination site, suggesting a possible molecular mechanism for the genome plasticity of the gibbon lineage. We further show that the gibbon genera (Nomascus, Hylobates, Hoolock and Symphalangus) experienced a near-instantaneous radiation ∼5 million years ago, coincident with major geographical changes in southeast Asia that caused cycles of habitat compression and expansion. Finally, we identify signatures of positive selection in genes important for forelimb development (TBX5) and connective tissues (COL1A1) that may have been involved in the adaptation of gibbons to their arboreal habitat.
Keywords: Animals; Evolution, Molecular; Genome; Hominidae; Humans; Hylobates; Karyotype; Molecular Sequence Data; Phylogeny; Retroelements; Selection, Genetic; Transcription Termination, Genetic

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Bo Yuan; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled

The Glanville fritillary genome retains an ancient karyotype and reveals selective chromosomal fusions in Lepidoptera. - Ahola, Virpi; Lehtonen, Rainer; Somervuo, Panu; Salmela, Leena; Koskinen, Patrik; Rastas, Pasi; Välimäki, Niko; Paulin, Lars; Kvist, Jouni; Wahlberg, Niklas; Tanskanen, Jaakko; Hornett, Emily A; et al. (Nat Commun, 2014)
Previous studies have reported that chromosome synteny in Lepidoptera has been well conserved, yet the number of haploid chromosomes varies widely from 5 to 223. Here we report the genome (393 Mb) of the Glanville fritillary butterfly (Melitaea cinxia; Nymphalidae), a widely recognized model species in metapopulation biology and eco-evolutionary research, which has the putative ancestral karyotype of n=31. Using a phylogenetic analyses of Nymphalidae and of other Lepidoptera, combined with orthologue-level comparisons of chromosomes, we conclude that the ancestral lepidopteran karyotype has been n=31 for at least 140 My. We show that fusion chromosomes have retained the ancestral chromosome segments and very few rearrangements have occurred across the fusion sites. The same, shortest ancestral chromosomes have independently participated in fusion events in species with smaller karyotypes. The short chromosomes have higher rearrangement rate than long ones. These characteristics highlight distinctive features of the evolutionary dynamics of butterflies and moths.
Keywords: Animals; Base Sequence; Butterflies; Chromosome Aberrations; Chromosome Mapping; Evolution, Molecular; Genome; Karyotype; Likelihood Functions; Models, Genetic; Molecular Sequence Data; Phylogeny; Sequence Analysis, DNA; Synteny

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; RNA-Binding Proteins; Transcription Factors

In silico tools for splicing defect prediction: a survey from the viewpoint of end users. - Jian, Xueqiu; Boerwinkle, Eric; Liu, Xiaoming (Genet Med, 2014)
RNA splicing is the process during which introns are excised and exons are spliced. The precise recognition of splicing signals is critical to this process, and mutations affecting splicing comprise a considerable proportion of genetic disease etiology. Analysis of RNA samples from the patient is the most straightforward and reliable method to detect splicing defects. However, currently, the technical limitation prohibits its use in routine clinical practice. In silico tools that predict potential consequences of splicing mutations may be useful in daily diagnostic activities. In this review, we provide medical geneticists with some basic insights into some of the most popular in silico tools for splicing defect prediction, from the viewpoint of end users. Bioinformaticians in relevant areas who are working on huge data sets may also benefit from this review. Specifically, we focus on those tools whose primary goal is to predict the impact of mutations within the 5' and 3' splicing consensus regions: the algorithms used by different tools as well as their major advantages and disadvantages are briefly introduced; the formats of their input and output are summarized; and the interpretation, evaluation, and prospection are also discussed.
Keywords: Computational Biology; Computer Simulation; Genetic Variation; Humans; RNA Precursors; RNA Splicing; Software

Intrapopulation genome size variation in D. melanogaster reflects life history variation and plasticity. - Ellis, Lisa L; Huang, Wen; Quinn, Andrew M; Ahuja, Astha; Alfrejd, Ben; Gomez, Francisco E; Hjelmen, Carl E; Moore, Kristi L; Mackay, Trudy F C; Johnston, J Spencer; Tarone, Aaron M (PLoS Genet, 2014)
We determined female genome sizes using flow cytometry for 211 Drosophila melanogaster sequenced inbred strains from the Drosophila Genetic Reference Panel, and found significant conspecific and intrapopulation variation in genome size. We also compared several life history traits for 25 lines with large and 25 lines with small genomes in three thermal environments, and found that genome size as well as genome size by temperature interactions significantly correlated with survival to pupation and adulthood, time to pupation, female pupal mass, and female eclosion rates. Genome size accounted for up to 23% of the variation in developmental phenotypes, but the contribution of genome size to variation in life history traits was plastic and varied according to the thermal environment. Expression data implicate differences in metabolism that correspond to genome size variation. These results indicate that significant genome size variation exists within D. melanogaster and this variation may impact the evolutionary ecology of the species. Genome size variation accounts for a significant portion of life history variation in an environmentally dependent manner, suggesting that potential fitness effects associated with genome size variation also depend on environmental conditions.
Keywords: Adaptation, Physiological; Animals; Biological Evolution; Drosophila melanogaster; Environment; Female; Genetic Variation; Genome Size; Genome, Insect; Insect Hormones

LANA binds to multiple active viral and cellular promoters and associates with the H3K4methyltransferase hSET1 complex. - Hu, Jianhong; Yang, Yajie; Turner, Peter C; Jain, Vaibhav; McIntyre, Lauren M; Renne, Rolf (PLoS Pathog, 2014)
Kaposi's sarcoma-associated herpesvirus (KSHV) is a γ-herpesvirus associated with KS and two lymphoproliferative diseases. Recent studies characterized epigenetic modification of KSHV episomes during latency and determined that latency-associated genes are associated with H3K4me3 while most lytic genes are associated with the silencing mark H3K27me3. Since the latency-associated nuclear antigen (LANA) (i) is expressed very early after de novo infection, (ii) interacts with transcriptional regulators and chromatin remodelers, and (iii) regulates the LANA and RTA promoters, we hypothesized that LANA may contribute to the establishment of latency through epigenetic control. We performed a detailed ChIP-seq analysis in cells of lymphoid and endothelial origin and compared H3K4me3, H3K27me3, polII, and LANA occupancy. On viral episomes LANA binding was detected at numerous lytic and latent promoters, which were transactivated by LANA using reporter assays. LANA binding was highly enriched at H3K4me3 peaks and this co-occupancy was also detected on many host gene promoters. Bioinformatic analysis of enriched LANA binding sites in combination with biochemical binding studies revealed three distinct binding patterns. A small subset of LANA binding sites showed sequence homology to the characterized LBS1/2 sequence in the viral terminal repeat. A large number of sites contained a novel LANA binding motif (TCCAT)3 which was confirmed by gel shift analysis. Third, some viral and cellular promoters did not contain LANA binding sites and are likely enriched through protein/protein interaction. LANA was associated with H3K4me3 marks and in PEL cells 86% of all LANA bound promoters were transcriptionally active, leading to the hypothesis that LANA interacts with the machinery that methylates H3K4. Co-immunoprecipitation demonstrated LANA association with endogenous hSET1 complexes in both lymphoid and endothelial cells suggesting that LANA may contribute to the epigenetic profile of KSHV episomes.
Keywords: Antigens, Viral; Chromatin Assembly and Disassembly; Epigenesis, Genetic; HEK293 Cells; Herpesvirus 8, Human; Histone-Lysine N-Methyltransferase; Humans; Methylation; Nuclear Proteins; Plasmids; Response Elements; Sarcoma, Kaposi; Transcription, Genetic

Large conserved domains of low DNA methylation maintained by Dnmt3a. - Jeong, Mira; Sun, Deqiang; Luo, Min; Huang, Yun; Challen, Grant A; Rodriguez, Benjamin; Zhang, Xiaotian; Chavez, Lukas; Wang, Hui; Hannah, Rebecca; Kim, Sang-Bae; Yang, Liubin; et al. (Nat Genet, 2014)
Gains and losses in DNA methylation are prominent features of mammalian cell types. To gain insight into the mechanisms that promote shifts in DNA methylation and contribute to changes in cell fate, including malignant transformation, we performed genome-wide mapping of 5-methylcytosine and 5-hydroxymethylcytosine in purified mouse hematopoietic stem cells. We discovered extended regions of low methylation (canyons) that span conserved domains frequently containing transcription factors and are distinct from CpG islands and shores. About half of the genes in these methylation canyons are coated with repressive histone marks, whereas the remainder are covered by activating histone marks and are highly expressed in hematopoietic stem cells (HSCs). Canyon borders are demarked by 5-hydroxymethylcytosine and become eroded in the absence of DNA methyltransferase 3a (Dnmt3a). Genes dysregulated in human leukemias are enriched for canyon-associated genes. The new epigenetic landscape we describe may provide a mechanism for the regulation of hematopoiesis and may contribute to leukemia development.
Keywords: 5-Methylcytosine; Animals; Base Sequence; Conserved Sequence; CpG Islands; Cytosine; Databases, Genetic; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; DNA Methyltransferase 3A; Epigenesis, Genetic; Gene Expression Regulation; Hematopoietic Stem Cells; Histones; Humans; Leukemia; Male; Mice; Mice, Inbred C57BL; Mice, Mutant Strains

Large-scale identification of chemically induced mutations in Drosophila melanogaster. - Haelterman, Nele A; Jiang, Lichun; Li, Yumei; Bayat, Vafa; Sandoval, Hector; Ugur, Berrak; Tan, Kai Li; Zhang, Ke; Bei, Danqing; Xiong, Bo; Charng, Wu-Lin; Busby, Theodore; et al. (Genome Res, 2014)
Forward genetic screens using chemical mutagens have been successful in defining the function of thousands of genes in eukaryotic model organisms. The main drawback of this strategy is the time-consuming identification of the molecular lesions causative of the phenotypes of interest. With whole-genome sequencing (WGS), it is now possible to sequence hundreds of strains, but determining which mutations are causative among thousands of polymorphisms remains challenging. We have sequenced 394 mutant strains, generated in a chemical mutagenesis screen, for essential genes on the Drosophila X chromosome and describe strategies to reduce the number of candidate mutations from an average of -3500 to 35 single-nucleotide variants per chromosome. By combining WGS with a rough mapping method based on large duplications, we were able to map 274 (-70%) mutations. We show that these mutations are causative, using small 80-kb duplications that rescue lethality. Hence, our findings demonstrate that combining rough mapping with WGS dramatically expands the toolkit necessary for assigning function to genes.
Keywords: Animals; Chromosome Mapping; Drosophila melanogaster; Ethyl Methanesulfonate; Female; Genes, Essential; Genes, Insect; Male; Molecular Sequence Data; Mutagenesis; Mutagens; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; X Chromosome

Linkage analysis incorporating gene-age interactions identifies seven novel lipid loci: the Family Blood Pressure Program. - Simino, Jeannette; Kume, Rezart; Kraja, Aldi T; Turner, Stephen T; Hanis, Craig L; Sheu, Wayne; Chen, Ida; Jaquish, Cashell; Cooper, Richard S; Chakravarti, Aravinda; Quertermous, Thomas; Boerwinkle, Eric; et al. (Atherosclerosis, 2014)
OBJECTIVE: To detect novel loci with age-dependent effects on fasting (≥ 8 h) levels of total cholesterol, high-density lipoprotein, low-density lipoprotein, and triglycerides using 3600 African Americans, 1283 Asians, 3218 European Americans, and 2026 Mexican Americans from the Family Blood Pressure Program (FBPP). METHODS: Within each subgroup (defined by network, race, and sex), we employed stepwise linear regression (retention p ≤ 0.05) to adjust lipid levels for age, age-squared, age-cubed, body-mass-index, current smoking status, current drinking status, field center, estrogen therapy (females only), as well as antidiabetic, antihypertensive, and antilipidemic medication use. For each trait, we pooled the standardized male and female residuals within each network and race and fit a generalized variance components model that incorporated gene-age interactions. We conducted FBPP-wide and race-specific meta-analyses by combining the p-values of each linkage marker across subgroups using a modified Fisher's method. RESULTS: We identified seven novel loci with age-dependent effects; four total cholesterol loci from the meta-analysis of Mexican Americans (on chromosomes 2q24.1, 4q21.21, 8q22.2, and 12p11.23) and three high-density lipoprotein loci from the meta-analysis of all FBPP subgroups (on chromosomes 1p12, 14q11.2, and 21q21.1). These loci lacked significant genome-wide linkage or association evidence in the literature and had logarithm of odds (LOD) score ≥ 3 in the meta-analysis with LOD ≥ 1 in at least two network and race subgroups (exclusively of non-European descent). CONCLUSION: Incorporating gene-age interactions into the analysis of lipids using multi-ethnic cohorts can enhance gene discovery. These interaction loci can guide the selection of families for sequencing studies of lipid-associated variants.
Keywords: Adult; Age Factors; Asian; Asian People; Black or African American; Black People; Blood Pressure; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Ethnicity; Family Health; Female; Genetic Linkage; Genetic Markers; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Lipids; Male; Mexican Americans; Middle Aged; Phenotype; Quantitative Trait Loci; White People

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Mutations in NGLY1 cause an inherited disorder of the endoplasmic reticulum-associated degradation pathway. - Enns, Gregory M; Shashi, Vandana; Bainbridge, Matthew; Gambello, Michael J; Zahir, Farah R; Bast, Thomas; Crimian, Rebecca; Schoch, Kelly; Platt, Julia; Cox, Rachel; Bernstein, Jonathan A; Scavina, Mena; et al. (Genet Med, 2014)
PURPOSE: The endoplasmic reticulum-associated degradation pathway is responsible for the translocation of misfolded proteins across the endoplasmic reticulum membrane into the cytosol for subsequent degradation by the proteasome. To define the phenotype associated with a novel inherited disorder of cytosolic endoplasmic reticulum-associated degradation pathway dysfunction, we studied a series of eight patients with deficiency of N-glycanase 1. METHODS: Whole-genome, whole-exome, or standard Sanger sequencing techniques were employed. Retrospective chart reviews were performed in order to obtain clinical data. RESULTS: All patients had global developmental delay, a movement disorder, and hypotonia. Other common findings included hypolacrima or alacrima (7/8), elevated liver transaminases (6/7), microcephaly (6/8), diminished reflexes (6/8), hepatocyte cytoplasmic storage material or vacuolization (5/6), and seizures (4/8). The nonsense mutation c.1201A>T (p.R401X) was the most common deleterious allele. CONCLUSION: NGLY1 deficiency is a novel autosomal recessive disorder of the endoplasmic reticulum-associated degradation pathway associated with neurological dysfunction, abnormal tear production, and liver disease. The majority of patients detected to date carry a specific nonsense mutation that appears to be associated with severe disease. The phenotypic spectrum is likely to enlarge as cases with a broader range of mutations are detected.
Keywords: Abnormalities, Multiple; Adolescent; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Exome; Family Health; Fatal Outcome; Female; Genome-Wide Association Study; Humans; Infant; Male; Microcephaly; Movement Disorders; Muscle Hypotonia; Mutation; Pedigree; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Retrospective Studies; Seizures; Sequence Analysis, DNA; Signal Transduction; Young Adult

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Natural variation in genome architecture among 205 Drosophila melanogaster Genetic Reference Panel lines. - Huang, Wen; Massouras, Andreas; Inoue, Yutaka; Peiffer, Jason; Ràmia, Miquel; Tarone, Aaron M; Turlapati, Lavanya; Zichner, Thomas; Zhu, Dianhui; Lyman, Richard F; Magwire, Michael M; Blankenburg, Kerstin; et al. (Genome Res, 2014)
The Drosophila melanogaster Genetic Reference Panel (DGRP) is a community resource of 205 sequenced inbred lines, derived to improve our understanding of the effects of naturally occurring genetic variation on molecular and organismal phenotypes. We used an integrated genotyping strategy to identify 4,853,802 single nucleotide polymorphisms (SNPs) and 1,296,080 non-SNP variants. Our molecular population genomic analyses show higher deletion than insertion mutation rates and stronger purifying selection on deletions. Weaker selection on insertions than deletions is consistent with our observed distribution of genome size determined by flow cytometry, which is skewed toward larger genomes. Insertion/deletion and single nucleotide polymorphisms are positively correlated with each other and with local recombination, suggesting that their nonrandom distributions are due to hitchhiking and background selection. Our cytogenetic analysis identified 16 polymorphic inversions in the DGRP. Common inverted and standard karyotypes are genetically divergent and account for most of the variation in relatedness among the DGRP lines. Intriguingly, variation in genome size and many quantitative traits are significantly associated with inversions. Approximately 50% of the DGRP lines are infected with Wolbachia, and four lines have germline insertions of Wolbachia sequences, but effects of Wolbachia infection on quantitative traits are rarely significant. The DGRP complements ongoing efforts to functionally annotate the Drosophila genome. Indeed, 15% of all D. melanogaster genes segregate for potentially damaged proteins in the DGRP, and genome-wide analyses of quantitative traits identify novel candidate genes. The DGRP lines, sequence data, genotypes, quality scores, phenotypes, and analysis and visualization tools are publicly available.
Keywords: Animals; Chromatin; Drosophila melanogaster; Female; Genetic Linkage; Genetic Variation; Genome Size; Genome, Insect; Genome-Wide Association Study; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; INDEL Mutation; Linkage Disequilibrium; Male; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Reproducibility of Results

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Muzny, Donna; Boerwinkle, Eric; Gibbs, Richard; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Notch activation as a driver of osteogenic sarcoma. - Tao, Jianning; Jiang, Ming-Ming; Jiang, Lichun; Salvo, Jason S; Zeng, Huan-Chang; Dawson, Brian; Bertin, Terry K; Rao, Pulivarthi H; Chen, Rui; Donehower, Lawrence A; Gannon, Francis; Lee, Brendan H (Cancer Cell, 2014)
Osteogenic sarcoma (OS) is a deadly skeletal malignancy whose cause is unknown. We report here a mouse model of OS based on conditional expression of the intracellular domain of Notch1 (NICD). Expression of the NICD in immature osteoblasts was sufficient to drive the formation of bone tumors, including OS, with complete penetrance. These tumors display features of human OS; namely, histopathology, cytogenetic complexity, and metastatic potential. We show that Notch activation combined with loss of p53 synergistically accelerates OS development in mice, although p53-driven OS is not Rbpj dependent, which demonstrates a dual dominance of the Notch oncogene and p53 mutation in the development of OS. Using this model, we also reveal the osteoblasts as the potential sources of OS.
Keywords: Animals; Bone Neoplasms; Carcinogenesis; Cell Line, Tumor; Humans; Mice; Mice, 129 Strain; Mice, Inbred C57BL; Mice, Nude; Mice, Transgenic; Neoplasm Transplantation; Osteoblasts; Osteosarcoma; Protein Structure, Tertiary; Receptor, Notch1; Transcriptome

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Muzny, Donna M; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Onset of atonal expression in Drosophila retinal progenitors involves redundant and synergistic contributions of Ey/Pax6 and So binding sites within two distant enhancers. - Zhou, Qingxiang; Zhang, Tianyi; Jemc, Jennifer C; Chen, Yiyun; Chen, Rui; Rebay, Ilaria; Pignoni, Francesca (Dev Biol, 2014)
Proneural transcription factors drive the generation of specialized neurons during nervous system development, and their dynamic expression pattern is critical to their function. The activation of the proneural gene atonal (ato) in the Drosophila eye disc epithelium represents a critical step in the transition from retinal progenitor cell to developing photoreceptor neuron. We show here that the onset of ato transcription depends on two distant enhancers that function differently in subsets of retinal progenitor cells. A detailed analysis of the crosstalk between these enhancers identifies a critical role for three binding sites for the Retinal Determination factors Eyeless (Ey) and Sine oculis (So). We show how these sites interact to induce ato expression in distinct regions of the eye field and confirm them to be occupied by endogenous Ey and So proteins in vivo. Our study suggests that Ey and So operate differently through the same 3' cis-regulatory sites in distinct populations of retinal progenitors.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Binding Sites; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Green Fluorescent Proteins; Homeodomain Proteins; In Situ Hybridization; Nerve Tissue Proteins; Nervous System; Neurons; Paired Box Transcription Factors; PAX6 Transcription Factor; Repressor Proteins; Retina; Stem Cells; Transcription, Genetic

Parent of origin, mosaicism, and recurrence risk: probabilistic modeling explains the broken symmetry of transmission genetics. - Campbell, Ian M; Stewart, Jonathan R; James, Regis A; Lupski, James R; Stankiewicz, Paweł; Olofsson, Peter; Shaw, Chad A (Am J Hum Genet, 2014)
Most new mutations are observed to arise in fathers, and increasing paternal age positively correlates with the risk of new variants. Interestingly, new mutations in X-linked recessive disease show elevated familial recurrence rates. In male offspring, these mutations must be inherited from mothers. We previously developed a simulation model to consider parental mosaicism as a source of transmitted mutations. In this paper, we extend and formalize the model to provide analytical results and flexible formulas. The results implicate parent of origin and parental mosaicism as central variables in recurrence risk. Consistent with empirical data, our model predicts that more transmitted mutations arise in fathers and that this tendency increases as fathers age. Notably, the lack of expansion later in the male germline determines relatively lower variance in the proportion of mutants, which decreases with paternal age. Subsequently, observation of a transmitted mutation has less impact on the expected risk for future offspring. Conversely, for the female germline, which arrests after clonal expansion in early development, variance in the mutant proportion is higher, and observation of a transmitted mutation dramatically increases the expected risk of recurrence in another pregnancy. Parental somatic mosaicism considerably elevates risk for both parents. These findings have important implications for genetic counseling and for understanding patterns of recurrence in transmission genetics. We provide a convenient online tool and source code implementing our analytical results. These tools permit varying the underlying parameters that influence recurrence risk and could be useful for analyzing risk in diverse family structures.
Keywords: Adult; Aged; Aged, 80 and over; Chromosome Aberrations; DNA Copy Number Variations; Fathers; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Inheritance Patterns; Male; Middle Aged; Models, Theoretical; Mosaicism; Mothers; Pregnancy; Recurrence; Risk Factors; Young Adult

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Prospective associations of coronary heart disease loci in African Americans using the MetaboChip: the PAGE study. - Franceschini, Nora; Hu, Yijuan; Reiner, Alex P; Buyske, Steven; Nalls, Mike; Yanek, Lisa R; Li, Yun; Hindorff, Lucia A; Cole, Shelley A; Howard, Barbara V; Stafford, Jeanette M; Carty, Cara L; et al. (PLoS One, 2014)
BACKGROUND: Coronary heart disease (CHD) is a leading cause of morbidity and mortality in African Americans. However, there is a paucity of studies assessing genetic determinants of CHD in African Americans. We examined the association of published variants in CHD loci with incident CHD, attempted to fine map these loci, and characterize novel variants influencing CHD risk in African Americans. METHODS AND RESULTS: Up to 8,201 African Americans (including 546 first CHD events) were genotyped using the MetaboChip array in the Atherosclerosis Risk in Communities (ARIC) study and Women's Health Initiative (WHI). We tested associations using Cox proportional hazard models in sex- and study-stratified analyses and combined results using meta-analysis. Among 44 validated CHD loci available in the array, we replicated and fine-mapped the SORT1 locus, and showed same direction of effects as reported in studies of individuals of European ancestry for SNPs in 22 additional published loci. We also identified a SNP achieving array wide significance (MYC: rs2070583, allele frequency 0.02, P = 8.1 × 10(-8)), but the association did not replicate in an additional 8,059 African Americans (577 events) from the WHI, HealthABC and GeneSTAR studies, and in a meta-analysis of 5 cohort studies of European ancestry (24,024 individuals including 1,570 cases of MI and 2,406 cases of CHD) from the CHARGE Consortium. CONCLUSIONS: Our findings suggest that some CHD loci previously identified in individuals of European ancestry may be relevant to incident CHD in African Americans.
Keywords: Adaptor Proteins, Vesicular Transport; Black or African American; Coronary Disease; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Proto-Oncogene Proteins c-myc

Regulation of Drosophila eye development by the transcription factor Sine oculis. - Jusiak, Barbara; Karandikar, Umesh C; Kwak, Su-Jin; Wang, Feng; Wang, Hui; Chen, Rui; Mardon, Graeme (PLoS One, 2014)
Homeodomain transcription factors of the Sine oculis (SIX) family direct multiple regulatory processes throughout the metazoans. Sine oculis (So) was first characterized in the fruit fly Drosophila melanogaster, where it is both necessary and sufficient for eye development, regulating cell survival, proliferation, and differentiation. Despite its key role in development, only a few direct targets of So have been described previously. In the current study, we aim to expand our knowledge of So-mediated transcriptional regulation in the developing Drosophila eye using ChIP-seq to map So binding regions throughout the genome. We find 7,566 So enriched regions (peaks), estimated to map to 5,952 genes. Using overlap between the So ChIP-seq peak set and genes that are differentially regulated in response to loss or gain of so, we identify putative direct targets of So. We find So binding enrichment in genes not previously known to be regulated by So, including genes that encode cell junction proteins and signaling pathway components. In addition, we analyze a subset of So-bound novel genes in the eye, and find eight genes that have previously uncharacterized eye phenotypes and may be novel direct targets of So. Our study presents a greatly expanded list of candidate So targets and serves as basis for future studies of So-mediated gene regulation in the eye.
Keywords: Animals; Drosophila melanogaster; Eye; Gene Expression Regulation, Developmental; Homeodomain Proteins; Optic Disk; Organogenesis; Transcription Factors

The sheep genome illuminates biology of the rumen and lipid metabolism. - Jiang, Yu; Xie, Min; Chen, Wenbin; Talbot, Richard; Maddox, Jillian F; Faraut, Thomas; Wu, Chunhua; Muzny, Donna M; Li, Yuxiang; Zhang, Wenguang; Stanton, Jo-Ann; Brauning, Rudiger; et al. (Science, 2014)
Sheep (Ovis aries) are a major source of meat, milk, and fiber in the form of wool and represent a distinct class of animals that have a specialized digestive organ, the rumen, that carries out the initial digestion of plant material. We have developed and analyzed a high-quality reference sheep genome and transcriptomes from 40 different tissues. We identified highly expressed genes encoding keratin cross-linking proteins associated with rumen evolution. We also identified genes involved in lipid metabolism that had been amplified and/or had altered tissue expression patterns. This may be in response to changes in the barrier lipids of the skin, an interaction between lipid metabolism and wool synthesis, and an increased role of volatile fatty acids in ruminants compared with nonruminant animals.
Keywords: Amino Acid Sequence; Animals; Fatty Acids, Volatile; Gene Expression Regulation; Genome; Keratins, Hair-Specific; Lipid Metabolism; Molecular Sequence Data; Phylogeny; Rumen; Sheep, Domestic; Transcriptome; Wool

Squamous cell carcinoma of the oral tongue in young non-smokers is genomically similar to tumors in older smokers. - Pickering, Curtis R; Zhang, Jiexin; Neskey, David M; Zhao, Mei; Jasser, Samar A; Wang, Jiping; Ward, Alexandra; Tsai, C Jillian; Ortega Alves, Marcus V; Zhou, Jane H; Drummond, Jennifer; El-Naggar, Adel K; et al. (Clin Cancer Res, 2014)
PURPOSE: Epidemiologic studies have identified an increasing incidence of squamous cell carcinoma of the oral tongue (SCCOT) in younger patients. EXPERIMENTAL DESIGN: DNA isolated from tongue tumors of young (<45 years, non-smokers) and old (>45 years) patients at was subjected to whole-exome sequencing and copy-number analysis. These data were compared with data from similar patients in the TCGA (The Cancer Genome Atlas) project. RESULTS: In this study, we found that gene-specific mutation and copy-number alteration frequencies were similar between young and old patients with SCCOT in two independent cohorts. Likewise, the types of base changes observed in the young cohort were similar to those in the old cohort even though they differed in smoking history. TCGA data also demonstrate that the genomic effects of smoking are tumor site-specific, and we find that smoking has only a minor impact on the types of mutations observed in SCCOT. CONCLUSIONS: Overall, tumors from young patients with SCCOT appear genomically similar to those of older patients with SCCOT, and the cause for the increasing incidence of young SCCOT remains unknown. These data indicate that the functional impact of smoking on carcinogenesis in SCCOT is still poorly understood.
Keywords: Adult; Age Factors; Carcinoma, Squamous Cell; DNA Copy Number Variations; DNA Mutational Analysis; Female; Humans; Male; Middle Aged; Mutation; Prognosis; Smoking; Tongue Neoplasms

Two novel simian arteriviruses in captive and wild baboons (Papio spp.). - Bailey, Adam L; Lauck, Michael; Sibley, Samuel D; Pecotte, Jerilyn; Rice, Karen; Weny, Geoffrey; Tumukunde, Alex; Hyeroba, David; Greene, Justin; Correll, Michael; Gleicher, Michael; Friedrich, Thomas C; et al. (J Virol, 2014)
UNLABELLED: Since the 1960s, simian hemorrhagic fever virus (SHFV; Nidovirales, Arteriviridae) has caused highly fatal outbreaks of viral hemorrhagic fever in captive Asian macaque colonies. However, the source(s) of these outbreaks and the natural reservoir(s) of this virus remain obscure. Here we report the identification of two novel, highly divergent simian arteriviruses related to SHFV, Mikumi yellow baboon virus 1 (MYBV-1) and Southwest baboon virus 1 (SWBV-1), in wild and captive baboons, respectively, and demonstrate the recent transmission of SWBV-1 among captive baboons. These findings extend our knowledge of the genetic and geographic diversity of the simian arteriviruses, identify baboons as a natural host of these viruses, and provide further evidence that baboons may have played a role in previous outbreaks of simian hemorrhagic fever in macaques, as has long been suspected. This knowledge should aid in the prevention of disease outbreaks in captive macaques and supports the growing body of evidence that suggests that simian arterivirus infections are common in Old World monkeys of many different species throughout Africa. IMPORTANCE: Historically, the emergence of primate viruses both in humans and in other primate species has caused devastating outbreaks of disease. One strategy for preventing the emergence of novel primate pathogens is to identify microbes with the potential for cross-species transmission in their natural state within reservoir species from which they might emerge. Here, we detail the discovery and characterization of two related simian members of the Arteriviridae family that have a history of disease emergence and host switching. Our results expand the phylogenetic and geographic range of the simian arteriviruses and define baboons as a natural host for these viruses. Our findings also identify a potential threat to captive macaque colonies by showing that simian arteriviruses are actively circulating in captive baboons.
Keywords: Animals; Animals, Wild; Animals, Zoo; Arteriviridae; Female; Genetic Variation; Male; Molecular Sequence Data; Monkey Diseases; Papio; Phylogeography; RNA Virus Infections; RNA, Viral; Sequence Analysis, DNA; Topography, Medical

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Muzny, Donna; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Microfilament Proteins; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Muzny, Donna M; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Calcium Channels; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

The 1000 Genomes Project: paving the way for personalized genomic medicine. - Gibson, Ian B; Jiang, Rongcai; Yu, Fuli (Per Med, 2013)

Assemblathon 2: evaluating de novo methods of genome assembly in three vertebrate species. - Bradnam, Keith R; Fass, Joseph N; Alexandrov, Anton; Baranay, Paul; Bechner, Michael; Birol, Inanç; Boisvert, Sébastien; Chapman, Jarrod A; Chapuis, Guillaume; Chikhi, Rayan; Chitsaz, Hamidreza; Chou, Wen-Chi; et al. (Gigascience, 2013)
BACKGROUND: The process of generating raw genome sequence data continues to become cheaper, faster, and more accurate. However, assembly of such data into high-quality, finished genome sequences remains challenging. Many genome assembly tools are available, but they differ greatly in terms of their performance (speed, scalability, hardware requirements, acceptance of newer read technologies) and in their final output (composition of assembled sequence). More importantly, it remains largely unclear how to best assess the quality of assembled genome sequences. The Assemblathon competitions are intended to assess current state-of-the-art methods in genome assembly. RESULTS: In Assemblathon 2, we provided a variety of sequence data to be assembled for three vertebrate species (a bird, a fish, and snake). This resulted in a total of 43 submitted assemblies from 21 participating teams. We evaluated these assemblies using a combination of optical map data, Fosmid sequences, and several statistical methods. From over 100 different metrics, we chose ten key measures by which to assess the overall quality of the assemblies. CONCLUSIONS: Many current genome assemblers produced useful assemblies, containing a significant representation of their genes and overall genome structure. However, the high degree of variability between the entries suggests that there is still much room for improvement in the field of genome assembly and that approaches which work well in assembling the genome of one species may not necessarily work well for another.

Bacterial discrimination by dictyostelid amoebae reveals the complexity of ancient interspecies interactions. - Nasser, Waleed; Santhanam, Balaji; Miranda, Edward Roshan; Parikh, Anup; Juneja, Kavina; Rot, Gregor; Dinh, Chris; Chen, Rui; Zupan, Blaz; Shaulsky, Gad; Kuspa, Adam (Curr Biol, 2013)
BACKGROUND: Amoebae and bacteria interact within predator-prey and host-pathogen relationships, but the general response of amoeba to bacteria is not well understood. The amoeba Dictyostelium discoideum feeds on, and is colonized by, diverse bacterial species, including Gram-positive [Gram(+)] and Gram-negative [Gram(-)] bacteria, two major groups of bacteria that differ in structure and macromolecular composition. RESULTS: Transcriptional profiling of D. discoideum revealed sets of genes whose expression is enriched in amoebae interacting with different species of bacteria, including sets that appear specific to amoebae interacting with Gram(+) or with Gram(-) bacteria. In a genetic screen utilizing the growth of mutant amoebae on a variety of bacteria as a phenotypic readout, we identified amoebal genes that are only required for growth on Gram(+) bacteria, including one that encodes the cell-surface protein gp130, as well as several genes that are only required for growth on Gram(-) bacteria, including one that encodes a putative lysozyme, AlyL. These genes are required for parts of the transcriptional response of wild-type amoebae, and this allowed their classification into potential response pathways. CONCLUSIONS: We have defined genes that are critical for amoebal survival during feeding on Gram(+), or Gram(-), bacteria that we propose form part of a regulatory network that allows D. discoideum to elicit specific cellular responses to different species of bacteria in order to optimize survival.
Keywords: Dictyostelium; Gene Expression Profiling; Genes, Bacterial; Genes, Protozoan; Gram-Negative Bacteria; Gram-Positive Bacteria; Host-Pathogen Interactions; Mutation; Transcription, Genetic

Bioactivity and bioavailability of ginsenosides are dependent on the glycosidase activities of the A/J mouse intestinal microbiome defined by pyrosequencing. - Niu, Tao; Smith, Diane L; Yang, Zhen; Gao, Song; Yin, Taijun; Jiang, Zhi-Hong; You, Ming; Gibbs, Richard A; Petrosino, Joseph F; Hu, Ming (Pharm Res, 2013)
PURPOSE: To investigate the ability of bacteria in the intestinal microbiome to convert naturally occurring primary ginsenosides in red ginseng extract to active secondary ginsenosides. METHODS: Anti-proliferative ginsenoside activity was tested using mouse lung cancer LM1 cells. Permeabilities were evaluated in Caco-2 cell monolayers. Systemic exposure of secondary ginsenosides was determined in A/J mice. 16S rRNA gene pyrosequencing was used to determine membership and abundance of bacteria in intestinal microbiome. RESULTS: Secondary ginsenoside C-K exhibited higher anti-proliferative activity and permeability than primary ginsenosides. Significant amounts of secondary ginsenosides (F2 and C-K) were found in blood of A/J mice following oral administration of primary ginsenoside Rb1. Because mammalian cells did not hydrolyze ginsenoside, we determined the ability of bacteria to hydrolyze ginsenosides and found that Rb1 underwent stepwise hydrolysis to Rd, F2, and then C-K. Formation of F2 from Rd was the rate-limiting step in the biotransformation of Rb1 to C-K. CONCLUSION: Conversion to F2 is the rate-limiting step in bioactivation of primary ginsenosides by A/J mouse intestinal microbiome, whose characterization reveals the presence of certain bacterial families capable of enabling the formation of F2 and C-K in vivo.
Keywords: Animals; Antineoplastic Agents, Phytogenic; Bacteria; Biological Availability; Biotransformation; Caco-2 Cells; Cell Line, Tumor; Cell Proliferation; Drugs, Chinese Herbal; Ginsenosides; Glycoside Hydrolases; Humans; Hydrolysis; Intestinal Mucosa; Intestines; Male; Metagenome; Mice; Neoplasms; Panax; RNA, Bacterial

Combined sequence-based and genetic mapping analysis of complex traits in outbred rats. - Baud, Amelie; Hermsen, Roel; Guryev, Victor; Stridh, Pernilla; Graham, Delyth; McBride, Martin W; Foroud, Tatiana; Calderari, Sophie; Diez, Margarita; Ockinger, Johan; Beyeen, Amennai D; Gillett, Alan; et al. (Nat Genet, 2013)
Genetic mapping on fully sequenced individuals is transforming understanding of the relationship between molecular variation and variation in complex traits. Here we report a combined sequence and genetic mapping analysis in outbred rats that maps 355 quantitative trait loci for 122 phenotypes. We identify 35 causal genes involved in 31 phenotypes, implicating new genes in models of anxiety, heart disease and multiple sclerosis. The relationship between sequence and genetic variation is unexpectedly complex: at approximately 40% of quantitative trait loci, a single sequence variant cannot account for the phenotypic effect. Using comparable sequence and mapping data from mice, we show that the extent and spatial pattern of variation in inbred rats differ substantially from those of inbred mice and that the genetic variants in orthologous genes rarely contribute to the same phenotype in both species.
Keywords: Animals; Animals, Outbred Strains; Anxiety; Chromosome Mapping; Genetic Variation; Genotype; Heart Diseases; Humans; Mice; Mice, Inbred C57BL; Models, Molecular; Multiple Sclerosis; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Sequence Analysis, DNA

Comprehensive molecular diagnosis of 179 Leber congenital amaurosis and juvenile retinitis pigmentosa patients by targeted next generation sequencing. - Wang, Xia; Wang, Hui; Sun, Vincent; Tuan, Han-Fang; Keser, Vafa; Wang, Keqing; Ren, Huanan; Lopez, Irma; Zaneveld, Jacques E; Siddiqui, Sorath; Bowles, Stephanie; Khan, Ayesha; et al. (J Med Genet, 2013)
BACKGROUND: Leber congenital amaurosis (LCA) and juvenile retinitis pigmentosa (RP) are inherited retinal diseases that cause early onset severe visual impairment. An accurate molecular diagnosis can refine the clinical diagnosis and allow gene specific treatments. METHODS: We developed a capture panel that enriches the exonic DNA of 163 known retinal disease genes. Using this panel, we performed targeted next generation sequencing (NGS) for a large cohort of 179 unrelated and prescreened patients with the clinical diagnosis of LCA or juvenile RP. Systematic NGS data analysis, Sanger sequencing validation, and segregation analysis were utilised to identify the pathogenic mutations. Patients were revisited to examine the potential phenotypic ambiguity at the time of initial diagnosis. RESULTS: Pathogenic mutations for 72 patients (40%) were identified, including 45 novel mutations. Of these 72 patients, 58 carried mutations in known LCA or juvenile RP genes and exhibited corresponding phenotypes, while 14 carried mutations in retinal disease genes that were not consistent with their initial clinical diagnosis. We revisited patients in the latter case and found that homozygous mutations in PRPH2 can cause LCA/juvenile RP. Guided by the molecular diagnosis, we reclassified the clinical diagnosis in two patients. CONCLUSIONS: We have identified a novel gene and a large number of novel mutations that are associated with LCA/juvenile RP. Our results highlight the importance of molecular diagnosis as an integral part of clinical diagnosis.
Keywords: Alleles; Amino Acid Sequence; Base Sequence; Exome; Female; Genotype; High-Throughput Nucleotide Sequencing; Humans; Leber Congenital Amaurosis; Mutation; Pedigree; Polymorphism, Single Nucleotide; Reproducibility of Results; Retinitis Pigmentosa; Sensitivity and Specificity

dbNSFP v2.0: a database of human non-synonymous SNVs and their functional predictions and annotations. - Liu, Xiaoming; Jian, Xueqiu; Boerwinkle, Eric (Hum Mutat, 2013)
dbNSFP is a database developed for functional prediction and annotation of all potential non-synonymous single-nucleotide variants (nsSNVs) in the human genome. This database significantly facilitates the process of querying predictions and annotations from different databases/web-servers for large amounts of nsSNVs discovered in exome-sequencing studies. Here we report a recent major update of the database to version 2.0. We have rebuilt the SNV collection based on GENCODE 9 and currently the database includes 87,347,043 nsSNVs and 2,270,742 essential splice site SNVs (an 18% increase compared to dbNSFP v1.0). For each nsSNV dbNSFP v2.0 has added two prediction scores (MutationAssessor and FATHMM) and two conservation scores (GERP++ and SiPhy). The original five prediction and conservation scores in v1.0 (SIFT, Polyphen2, LRT, MutationTaster and PhyloP) have been updated. Rich functional annotations for SNVs and genes have also been added into the new version, including allele frequencies observed in the 1000 Genomes Project phase 1 data and the NHLBI Exome Sequencing Project, various gene IDs from different databases, functional descriptions of genes, gene expression and gene interaction information, among others. dbNSFP v2.0 is freely available for download at http://sites.google.com/site/jpopgen/dbNSFP.
Keywords: Computational Biology; Databases, Nucleic Acid; Exome; Gene Frequency; Genome, Human; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Software

De novo truncating mutations in ASXL3 are associated with a novel clinical phenotype with similarities to Bohring-Opitz syndrome. - Bainbridge, Matthew N; Hu, Hao; Muzny, Donna M; Musante, Luciana; Lupski, James R; Graham, Brett H; Chen, Wei; Gripp, Karen W; Jenny, Kim; Wienker, Thomas F; Yang, Yaping; Sutton, V Reid; et al. (Genome Med, 2013)
BACKGROUND: Molecular diagnostics can resolve locus heterogeneity underlying clinical phenotypes that may otherwise be co-assigned as a specific syndrome based on shared clinical features, and can associate phenotypically diverse diseases to a single locus through allelic affinity. Here we describe an apparently novel syndrome, likely caused by de novo truncating mutations in ASXL3, which shares characteristics with Bohring-Opitz syndrome, a disease associated with de novo truncating mutations in ASXL1. METHODS: We used whole-genome and whole-exome sequencing to interrogate the genomes of four subjects with an undiagnosed syndrome. RESULTS: Using genome-wide sequencing, we identified heterozygous, de novo truncating mutations in ASXL3, a transcriptional repressor related to ASXL1, in four unrelated probands. We found that these probands shared similar phenotypes, including severe feeding difficulties, failure to thrive, and neurologic abnormalities with significant developmental delay. Further, they showed less phenotypic overlap with patients who had de novo truncating mutations in ASXL1. CONCLUSION: We have identified truncating mutations in ASXL3 as the likely cause of a novel syndrome with phenotypic overlap with Bohring-Opitz syndrome.

Exome sequencing resolves apparent incidental findings and reveals further complexity of SH3TC2 variant alleles causing Charcot-Marie-Tooth neuropathy. - Lupski, James R; Gonzaga-Jauregui, Claudia; Yang, Yaping; Bainbridge, Matthew N; Jhangiani, Shalini; Buhay, Christian J; Kovar, Christie L; Wang, Min; Hawes, Alicia C; Reid, Jeffrey G; Eng, Christine; Muzny, Donna M; et al. (Genome Med, 2013)
BACKGROUND: The debate regarding the relative merits of whole genome sequencing (WGS) versus exome sequencing (ES) centers around comparative cost, average depth of coverage for each interrogated base, and their relative efficiency in the identification of medically actionable variants from the myriad of variants identified by each approach. Nevertheless, few genomes have been subjected to both WGS and ES, using multiple next generation sequencing platforms. In addition, no personal genome has been so extensively analyzed using DNA derived from peripheral blood as opposed to DNA from transformed cell lines that may either accumulate mutations during propagation or clonally expand mosaic variants during cell transformation and propagation. METHODS: We investigated a genome that was studied previously by SOLiD chemistry using both ES and WGS, and now perform six independent ES assays (Illumina GAII (x2), Illumina HiSeq (x2), Life Technologies' Personal Genome Machine (PGM) and Proton), and one additional WGS (Illumina HiSeq). RESULTS: We compared the variants identified by the different methods and provide insights into the differences among variants identified between ES runs in the same technology platform and among different sequencing technologies. We resolved the true genotypes of medically actionable variants identified in the proband through orthogonal experimental approaches. Furthermore, ES identified an additional SH3TC2 variant (p.M1?) that likely contributes to the phenotype in the proband. CONCLUSIONS: ES identified additional medically actionable variant calls and helped resolve ambiguous single nucleotide variants (SNV) documenting the power of increased depth of coverage of the captured targeted regions. Comparative analyses of WGS and ES reveal that pseudogenes and segmental duplications may explain some instances of apparent disease mutations in unaffected individuals.

Identification of TP53 as an acute lymphocytic leukemia susceptibility gene through exome sequencing. - Powell, Bradford C; Jiang, Lichun; Muzny, Donna M; Treviño, Lisa R; Dreyer, Zoann E; Strong, Louise C; Wheeler, David A; Gibbs, Richard A; Plon, Sharon E (Pediatr Blood Cancer, 2013)
Although acute lymphocytic leukemia (ALL) is the most common childhood cancer, genetic predisposition to ALL remains poorly understood. Whole-exome sequencing was performed in an extended kindred in which five individuals had been diagnosed with leukemia. Analysis revealed a nonsense variant of TP53 which has been previously reported in families with sarcomas and other typical Li Fraumeni syndrome-associated cancers but never in a familial leukemia kindred. This unexpected finding enabled identification of an appropriate sibling bone marrow donor and illustrates that exome sequencing will reveal atypical clinical presentations of even well-studied genes.
Keywords: Exome; Female; Genetic Predisposition to Disease; Humans; Male; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Tumor Suppressor Protein p53

Metagenomic analyses of alcohol induced pathogenic alterations in the intestinal microbiome and the effect of Lactobacillus rhamnosus GG treatment. - Bull-Otterson, Lara; Feng, Wenke; Kirpich, Irina; Wang, Yuhua; Qin, Xiang; Liu, Yanlong; Gobejishvili, Leila; Joshi-Barve, Swati; Ayvaz, Tulin; Petrosino, Joseph; Kong, Maiying; Barker, David; et al. (PLoS One, 2013)
Enteric dysbiosis plays an essential role in the pathogenesis of alcoholic liver disease (ALD). Detailed characterization of the alterations in the gut microbiome is needed for understanding their pathogenic role in ALD and developing effective therapeutic approaches using probiotic supplementation. Mice were fed liquid Lieber-DeCarli diet without or with alcohol (5% v/v) for 6 weeks. A subset of mice were administered the probiotic Lactobacillus rhamnosus GG (LGG) from 6 to 8 weeks. Indicators of intestinal permeability, hepatic steatosis, inflammation and injury were evaluated. Metagenomic analysis of the gut microbiome was performed by analyzing the fecal DNA by amplification of the V3-V5 regions of the 16S rRNA gene and large-scale parallel pyrosequencing on the 454 FLX Titanium platform. Chronic ethanol feeding caused a decline in the abundance of both Bacteriodetes and Firmicutes phyla, with a proportional increase in the gram negative Proteobacteria and gram positive Actinobacteria phyla; the bacterial genera that showed the biggest expansion were the gram negative alkaline tolerant Alcaligenes and gram positive Corynebacterium. Commensurate with the qualitative and quantitative alterations in the microbiome, ethanol caused an increase in plasma endotoxin, fecal pH, hepatic inflammation and injury. Notably, the ethanol-induced pathogenic changes in the microbiome and the liver were prevented by LGG supplementation. Overall, significant alterations in the gut microbiome over time occur in response to chronic alcohol exposure and correspond to increases in intestinal barrier dysfunction and development of ALD. Moreover, the altered bacterial communities of the gut may serve as significant therapeutic target for the prevention/treatment of chronic alcohol intake induced intestinal barrier dysfunction and liver disease.
Keywords: Animals; Anti-Infective Agents, Local; Bacteria; Biodiversity; Claudin-1; Ethanol; Feces; Gene Expression; Genetic Variation; Hydrogen-Ion Concentration; Intestinal Mucosa; Intestines; Lacticaseibacillus rhamnosus; Liver Diseases, Alcoholic; Male; Metagenome; Metagenomics; Mice; Mice, Inbred C57BL; Probiotics; Reverse Transcriptase Polymerase Chain Reaction; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Species Specificity; Zonula Occludens-1 Protein

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases

A recurrent germline PAX5 mutation confers susceptibility to pre-B cell acute lymphoblastic leukemia. - Shah, Sohela; Schrader, Kasmintan A; Waanders, Esmé; Timms, Andrew E; Vijai, Joseph; Miething, Cornelius; Wechsler, Jeremy; Yang, Jun; Hayes, James; Klein, Robert J; Zhang, Jinghui; Wei, Lei; et al. (Nat Genet, 2013)
Somatic alterations of the lymphoid transcription factor gene PAX5 (also known as BSAP) are a hallmark of B cell precursor acute lymphoblastic leukemia (B-ALL), but inherited mutations of PAX5 have not previously been described. Here we report a new heterozygous germline variant, c.547G>A (p.Gly183Ser), affecting the octapeptide domain of PAX5 that was found to segregate with disease in two unrelated kindreds with autosomal dominant B-ALL. Leukemic cells from all affected individuals in both families exhibited 9p deletion, with loss of heterozygosity and retention of the mutant PAX5 allele at 9p13. Two additional sporadic ALL cases with 9p loss harbored somatic PAX5 substitutions affecting Gly183. Functional and gene expression analysis of the PAX5 mutation demonstrated that it had significantly reduced transcriptional activity. These data extend the role of PAX5 alterations in the pathogenesis of pre-B cell ALL and implicate PAX5 in a new syndrome of susceptibility to pre-B cell neoplasia.
Keywords: Genetic Predisposition to Disease; Germ-Line Mutation; Humans; PAX5 Transcription Factor; Polymorphism, Single Nucleotide; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma

RNA interference knockdown of DNA methyl-transferase 3 affects gene alternative splicing in the honey bee. - Li-Byarlay, Hongmei; Li, Yang; Stroud, Hume; Feng, Suhua; Newman, Thomas C; Kaneda, Megan; Hou, Kirk K; Worley, Kim C; Elsik, Christine G; Wickline, Samuel A; Jacobsen, Steven E; Ma, Jian; et al. (Proc Natl Acad Sci U S A, 2013)
Studies of DNA methylation from fungi, plants, and animals indicate that gene body methylation is ancient and highly conserved in eukaryotic genomes, but its role has not been clearly defined. It has been postulated that regulation of alternative splicing of transcripts was an original function of DNA methylation, but a direct experimental test of the effect of methylation on alternative slicing at the whole genome level has never been performed. To do this, we developed a unique method to administer RNA interference (RNAi) in a high-throughput and noninvasive manner and then used it to knock down the expression of DNA methyl-transferase 3 (dnmt3), which is required for de novo DNA methylation. We chose the honey bee (Apis mellifera) for this test because it has recently emerged as an important model organism for studying the effects of DNA methylation on development and social behavior, and DNA methylation in honey bees is predominantly on gene bodies. Here we show that dnmt3 RNAi decreased global genomic methylation level as expected and in addition caused widespread and diverse changes in alternative splicing in fat tissue. Four different types of splicing events were affected by dnmt3 gene knockdown, and change in two types, exon skipping and intron retention, was directly related to decreased methylation. These results demonstrate that one function of gene body DNA methylation is to regulate alternative splicing.
Keywords: Alternative Splicing; Animals; Bees; Behavior, Animal; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; Gene Knockdown Techniques; Insect Proteins; RNA Interference; Social Behavior

TM4SF20 ancestral deletion and susceptibility to a pediatric disorder of early language delay and cerebral white matter hyperintensities. - Wiszniewski, Wojciech; Hunter, Jill V; Hanchard, Neil A; Willer, Jason R; Shaw, Chad; Tian, Qi; Illner, Anna; Wang, Xueqing; Cheung, Sau W; Patel, Ankita; Campbell, Ian M; Gelowani, Violet; et al. (Am J Hum Genet, 2013)
White matter hyperintensities (WMHs) of the brain are important markers of aging and small-vessel disease. WMHs are rare in healthy children and, when observed, often occur with comorbid neuroinflammatory or vasculitic processes. Here, we describe a complex 4 kb deletion in 2q36.3 that segregates with early childhood communication disorders and WMH in 15 unrelated families predominantly from Southeast Asia. The premature brain aging phenotype with punctate and multifocal WMHs was observed in ~70% of young carrier parents who underwent brain MRI. The complex deletion removes the penultimate exon 3 of TM4SF20, a gene encoding a transmembrane protein of unknown function. Minigene analysis showed that the resultant net loss of an exon introduces a premature stop codon, which, in turn, leads to the generation of a stable protein that fails to target to the plasma membrane and accumulates in the cytoplasm. Finally, we report this deletion to be enriched in individuals of Vietnamese Kinh descent, with an allele frequency of about 1%, embedded in an ancestral haplotype. Our data point to a constellation of early language delay and WMH phenotypes, driven by a likely toxic mechanism of TM4SF20 truncation, and highlight the importance of understanding and managing population-specific low-frequency pathogenic alleles.
Keywords: Age of Onset; Aging, Premature; Asian People; Base Sequence; Brain; Child; Child, Preschool; Chromosomes, Human, Pair 2; Exons; Female; Genetic Predisposition to Disease; Humans; Language Development Disorders; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Pedigree; Sequence Analysis, DNA; Sequence Deletion; Tetraspanins

Union makes strength: a worldwide collaborative genetic and clinical study to provide a comprehensive survey of RD3 mutations and delineate the associated phenotype. - Perrault, Isabelle; Estrada-Cuzcano, Alejandro; Lopez, Irma; Kohl, Susanne; Li, Shiqiang; Testa, Francesco; Zekveld-Vroon, Renate; Wang, Xia; Pomares, Esther; Andorf, Jean; Aboussair, Nisrine; Banfi, Sandro; et al. (PLoS One, 2013)
Leber congenital amaurosis (LCA) is the earliest and most severe retinal degeneration (RD), and the most common cause of incurable blindness diagnosed in children. It is occasionally the presenting symptom of multisystemic ciliopathies which diagnosis will require a specific care of patients. Nineteen LCA genes are currently identified and three of them account for both non-syndromic and syndromic forms of the disease. RD3 (LCA12) was implicated as a LCA gene based on the identification of homozygous truncating mutations in two LCA families despite the screening of large cohorts of patients. Here we provide a comprehensive survey of RD3 mutations and of their clinical expression through the screening of a cohort of 852 patients originating worldwide affected with LCA or early-onset and severe RD. We identified three RD3 mutations in seven unrelated consanguineous LCA families - i.e., a 2 bp deletion and two nonsense mutations - predicted to cause complete loss of function. Five families originating from the Southern Shores of the Mediterranean segregated a similar mutation (c.112C>T, p.R38*) suggesting that this change may have resulted from an ancient founder effect. Considering the low frequency of RD3 carriers, the recurrence risk for LCA in non-consanguineous unions is negligible for both heterozygote and homozygote RD3 individuals. The LCA12 phenotype in our patients is highly similar to those of patients with mutant photoreceptor-specific guanylate cyclase (GUCY2D/LCA1). This observation is consistent with the report of the role of RD3 in trafficking of GUCYs and gives further support to a common mechanism of photoreceptor degeneration in LCA12 and LCA1, i.e., inability to increase cytoplasmic cGMP concentration in outer segments and thus to recover the dark-state. Similar to LCA1, LCA12 patients have no extraocular symptoms despite complete inactivation of both RD3 alleles, supporting the view that extraocular investigations in LCA infants with RD3 mutations should be avoided.
Keywords: Adolescent; Adult; Canada; Child; Child, Preschool; China; Cohort Studies; Europe; Eye Proteins; Female; Humans; Infant; Leber Congenital Amaurosis; Linkage Disequilibrium; Male; Mutation; Pedigree; Phenotype; Polymorphism, Genetic; Retina; Retinal Degeneration; United States; Young Adult

Updating benchtop sequencing performance comparison. - Jünemann, Sebastian; Fritz J Sedlazeck; Prior, Karola; Albersmeier, Andreas; John, Uwe; Kalinowski, Jörn; Mellmann, Alexander; Goesmann, Alexander; von Haeseler, Arndt; Stoye, Jens; Harmsen, Dag (Nat Biotechnol, 2013)
Keywords: Humans; Sequence Analysis, DNA

Whole-genome sequence-based analysis of high-density lipoprotein cholesterol. - Morrison, Alanna C; Voorman, Arend; Johnson, Andrew D; Liu, Xiaoming; Yu, Jin; Li, Alexander; Muzny, Donna; Yu, Fuli; Rice, Kenneth; Zhu, Chengsong; Bis, Joshua; Heiss, Gerardo; et al. (Nat Genet, 2013)
We describe initial steps for interrogating whole-genome sequence data to characterize the genetic architecture of a complex trait, levels of high-density lipoprotein cholesterol (HDL-C). We report whole-genome sequencing and analysis of 962 individuals from the Cohorts for Heart and Aging Research in Genetic Epidemiology (CHARGE) studies. From this analysis, we estimate that common variation contributes more to heritability of HDL-C levels than rare variation, and screening for mendelian variants for dyslipidemia identified individuals with extreme HDL-C levels. Whole-genome sequencing analyses highlight the value of regulatory and non-protein-coding regions of the genome in addition to protein-coding regions.
Keywords: Cholesterol, HDL; Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genome-Wide Association Study; Genomics; Heterozygote; Humans; Open Reading Frames

Adenosine deaminases that act on RNA induce reproducible changes in abundance and sequence of embryonic miRNAs. - Vesely, Cornelia; Tauber, Stefanie; Fritz J Sedlazeck; von Haeseler, Arndt; Jantsch, Michael F (Genome Res, 2012)
Adenosine deaminases that act on RNA bind double-stranded and structured RNAs and convert adenosines to inosines by hydrolytic deamination. Inosines are recognized as guanosines, and, hence, RNA editing alters the sequence information but also structure of RNAs. Editing by ADARs is widespread and essential for normal life and development. Precursors of miRNAs are abundantly edited by ADARs, but neither the abundance nor the consequences of miRNA editing has been firmly established. Using transgenic mouse embryos that are deficient in the two enzymatically active editing enzymes ADAR and ADARB1, we compare relative frequencies but also sequence composition of miRNAs in these genetically modified backgrounds to wild-type mice by "next-generation sequencing." Deficiency of ADARB1 leads to a reproducible change in abundance of specific miRNAs and their predicted targets. Changes in miRNA abundance seem unrelated to editing events. Additional deletion of ADAR has surprisingly little impact on the mature miRNA repertoire, indicating that miRNA expression is primarily dependent on ADARB1. A-to-G transitions reflecting A-to-I editing events can be detected at few sites and at low frequency during the early embryonic stage investigated. Again, most editing events are ADARB1-dependent with only few editing sites being specifically edited by ADAR. Besides known editing events in miRNAs, a few novel, previously unknown editing events were identified. Some editing events are located to the seed region of miRNAs, opening the possibility that editing leads to their retargeting.
Keywords: Adenosine Deaminase; Animals; Base Sequence; Binding Sites; Embryo, Mammalian; Embryonic Development; Female; Gene Expression Regulation, Developmental; Gene Expression Regulation, Enzymologic; Mice; Mice, Knockout; MicroRNAs; RNA Editing; RNA, Messenger; RNA-Binding Proteins; Sequence Deletion

Atlas2 Cloud: a framework for personal genome analysis in the cloud. - Evani, Uday S; Challis, Danny; Yu, Jin; Jackson, Andrew R; Paithankar, Sameer; Bainbridge, Matthew N; Jakkamsetti, Adinarayana; Pham, Peter; Coarfa, Cristian; Milosavljevic, Aleksandar; Yu, Fuli (BMC Genomics, 2012)
BACKGROUND: Until recently, sequencing has primarily been carried out in large genome centers which have invested heavily in developing the computational infrastructure that enables genomic sequence analysis. The recent advancements in next generation sequencing (NGS) have led to a wide dissemination of sequencing technologies and data, to highly diverse research groups. It is expected that clinical sequencing will become part of diagnostic routines shortly. However, limited accessibility to computational infrastructure and high quality bioinformatic tools, and the demand for personnel skilled in data analysis and interpretation remains a serious bottleneck. To this end, the cloud computing and Software-as-a-Service (SaaS) technologies can help address these issues. RESULTS: We successfully enabled the Atlas2 Cloud pipeline for personal genome analysis on two different cloud service platforms: a community cloud via the Genboree Workbench, and a commercial cloud via the Amazon Web Services using Software-as-a-Service model. We report a case study of personal genome analysis using our Atlas2 Genboree pipeline. We also outline a detailed cost structure for running Atlas2 Amazon on whole exome capture data, providing cost projections in terms of storage, compute and I/O when running Atlas2 Amazon on a large data set. CONCLUSIONS: We find that providing a web interface and an optimized pipeline clearly facilitates usage of cloud computing for personal genome analysis, but for it to be routinely used for large scale projects there needs to be a paradigm shift in the way we develop tools, in standard operating procedures, and in funding mechanisms.
Keywords: Databases, Genetic; Genome, Human; Humans; Internet; Software; User-Computer Interface

Biological characterization and next-generation genome sequencing of the unclassified Cotia virus SPAn232 (Poxviridae). - Afonso, Priscila P; Silva, Patrícia M; Schnellrath, Laila C; Jesus, Desyreé M; Hu, Jianhong; Yang, Yajie; Renne, Rolf; Attias, Marcia; Condit, Richard C; Moussatché, Nissin; Damaso, Clarissa R (J Virol, 2012)
Cotia virus (COTV) SPAn232 was isolated in 1961 from sentinel mice at Cotia field station, São Paulo, Brazil. Attempts to classify COTV within a recognized genus of the Poxviridae have generated contradictory findings. Studies by different researchers suggested some similarity to myxoma virus and swinepox virus, whereas another investigation characterized COTV SPAn232 as a vaccinia virus strain. Because of the lack of consensus, we have conducted an independent biological and molecular characterization of COTV. Virus growth curves reached maximum yields at approximately 24 to 48 h and were accompanied by virus DNA replication and a characteristic early/late pattern of viral protein synthesis. Interestingly, COTV did not induce detectable cytopathic effects in BSC-40 cells until 4 days postinfection and generated viral plaques only after 8 days. We determined the complete genomic sequence of COTV by using a combination of the next-generation DNA sequencing technologies 454 and Illumina. A unique contiguous sequence of 185,139 bp containing 185 genes, including the 90 genes conserved in all chordopoxviruses, was obtained. COTV has an interesting panel of open reading frames (ORFs) related to the evasion of host defense, including two novel genes encoding C-C chemokine-like proteins, each present in duplicate copies. Phylogenetic analysis revealed the highest amino acid identity scores with Cervidpoxvirus, Capripoxvirus, Suipoxvirus, Leporipoxvirus, and Yatapoxvirus. However, COTV grouped as an independent branch within this clade, which clearly excluded its classification as an Orthopoxvirus. Therefore, our data suggest that COTV could represent a new poxvirus genus.
Keywords: Amino Acid Sequence; Animals; Chick Embryo; Chlorocebus aethiops; Cross Reactions; Cytopathogenic Effect, Viral; Genes, Viral; Genome, Viral; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Mice; Molecular Sequence Data; Neutralization Tests; Phylogeny; Poxviridae; Rabbits; Rats; Sequence Alignment; Swine; Viral Tropism; Virus Replication

Comparative genomics of Ceriporiopsis subvermispora and Phanerochaete chrysosporium provide insight into selective ligninolysis. - Fernandez-Fueyo, Elena; Ruiz-Duenas, Francisco J; Ferreira, Patricia; Floudas, Dimitrios; Hibbett, David S; Canessa, Paulo; Larrondo, Luis F; James, Tim Y; Seelenfreund, Daniela; Lobos, Sergio; Polanco, Rubén; Tello, Mario; et al. (Proc Natl Acad Sci U S A, 2012)
Efficient lignin depolymerization is unique to the wood decay basidiomycetes, collectively referred to as white rot fungi. Phanerochaete chrysosporium simultaneously degrades lignin and cellulose, whereas the closely related species, Ceriporiopsis subvermispora, also depolymerizes lignin but may do so with relatively little cellulose degradation. To investigate the basis for selective ligninolysis, we conducted comparative genome analysis of C. subvermispora and P. chrysosporium. Genes encoding manganese peroxidase numbered 13 and five in C. subvermispora and P. chrysosporium, respectively. In addition, the C. subvermispora genome contains at least seven genes predicted to encode laccases, whereas the P. chrysosporium genome contains none. We also observed expansion of the number of C. subvermispora desaturase-encoding genes putatively involved in lipid metabolism. Microarray-based transcriptome analysis showed substantial up-regulation of several desaturase and MnP genes in wood-containing medium. MS identified MnP proteins in C. subvermispora culture filtrates, but none in P. chrysosporium cultures. These results support the importance of MnP and a lignin degradation mechanism whereby cleavage of the dominant nonphenolic structures is mediated by lipid peroxidation products. Two C. subvermispora genes were predicted to encode peroxidases structurally similar to P. chrysosporium lignin peroxidase and, following heterologous expression in Escherichia coli, the enzymes were shown to oxidize high redox potential substrates, but not Mn(2+). Apart from oxidative lignin degradation, we also examined cellulolytic and hemicellulolytic systems in both fungi. In summary, the C. subvermispora genetic inventory and expression patterns exhibit increased oxidoreductase potential and diminished cellulolytic capability relative to P. chrysosporium.
Keywords: Basidiomycota; Genomics; Hydrolysis; Lignin; Molecular Sequence Data; Oxidation-Reduction; Phylogeny; Species Specificity

The Drosophila melanogaster Genetic Reference Panel. - Mackay, Trudy F C; Richards, Stephen; Stone, Eric A; Barbadilla, Antonio; Ayroles, Julien F; Zhu, Dianhui; Casillas, Sònia; Han, Yi; Magwire, Michael M; Cridland, Julie M; Richardson, Mark F; Anholt, Robert R H; et al. (Nature, 2012)
A major challenge of biology is understanding the relationship between molecular genetic variation and variation in quantitative traits, including fitness. This relationship determines our ability to predict phenotypes from genotypes and to understand how evolutionary forces shape variation within and between species. Previous efforts to dissect the genotype-phenotype map were based on incomplete genotypic information. Here, we describe the Drosophila melanogaster Genetic Reference Panel (DGRP), a community resource for analysis of population genomics and quantitative traits. The DGRP consists of fully sequenced inbred lines derived from a natural population. Population genomic analyses reveal reduced polymorphism in centromeric autosomal regions and the X chromosome, evidence for positive and negative selection, and rapid evolution of the X chromosome. Many variants in novel genes, most at low frequency, are associated with quantitative traits and explain a large fraction of the phenotypic variance. The DGRP facilitates genotype-phenotype mapping using the power of Drosophila genetics.
Keywords: Alleles; Animals; Centromere; Chromosomes, Insect; Drosophila melanogaster; Genome-Wide Association Study; Genomics; Genotype; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Starvation; Telomere; X Chromosome

Epistasis dominates the genetic architecture of Drosophila quantitative traits. - Huang, Wen; Richards, Stephen; Carbone, Mary Anna; Zhu, Dianhui; Anholt, Robert R H; Ayroles, Julien F; Duncan, Laura; Jordan, Katherine W; Lawrence, Faye; Magwire, Michael M; Warner, Crystal B; Blankenburg, Kerstin; et al. (Proc Natl Acad Sci U S A, 2012)
Epistasis-nonlinear genetic interactions between polymorphic loci-is the genetic basis of canalization and speciation, and epistatic interactions can be used to infer genetic networks affecting quantitative traits. However, the role that epistasis plays in the genetic architecture of quantitative traits is controversial. Here, we compared the genetic architecture of three Drosophila life history traits in the sequenced inbred lines of the Drosophila melanogaster Genetic Reference Panel (DGRP) and a large outbred, advanced intercross population derived from 40 DGRP lines (Flyland). We assessed allele frequency changes between pools of individuals at the extremes of the distribution for each trait in the Flyland population by deep DNA sequencing. The genetic architecture of all traits was highly polygenic in both analyses. Surprisingly, none of the SNPs associated with the traits in Flyland replicated in the DGRP and vice versa. However, the majority of these SNPs participated in at least one epistatic interaction in the DGRP. Despite apparent additive effects at largely distinct loci in the two populations, the epistatic interactions perturbed common, biologically plausible, and highly connected genetic networks. Our analysis underscores the importance of epistasis as a principal factor that determines variation for quantitative traits and provides a means to uncover genetic networks affecting these traits. Knowledge of epistatic networks will contribute to our understanding of the genetic basis of evolutionarily and clinically important traits and enhance predictive ability at an individualized level in medicine and agriculture.
Keywords: Animals; Drosophila melanogaster; Epistasis, Genetic; Genes, Insect; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Evaluation of 16S rDNA-based community profiling for human microbiome research. (PLoS One, 2012)
The Human Microbiome Project will establish a reference data set for analysis of the microbiome of healthy adults by surveying multiple body sites from 300 people and generating data from over 12,000 samples. To characterize these samples, the participating sequencing centers evaluated and adopted 16S rDNA community profiling protocols for ABI 3730 and 454 FLX Titanium sequencing. In the course of establishing protocols, we examined the performance and error characteristics of each technology, and the relationship of sequence error to the utility of 16S rDNA regions for classification- and OTU-based analysis of community structure. The data production protocols used for this work are those used by the participating centers to produce 16S rDNA sequence for the Human Microbiome Project. Thus, these results can be informative for interpreting the large body of clinical 16S rDNA data produced for this project.
Keywords: Bacteria; Bayes Theorem; Humans; Metagenome; RNA, Ribosomal, 16S

Exome capture reveals ZNF423 and CEP164 mutations, linking renal ciliopathies to DNA damage response signaling. - Chaki, Moumita; Airik, Rannar; Ghosh, Amiya K; Giles, Rachel H; Chen, Rui; Slaats, Gisela G; Wang, Hui; Hurd, Toby W; Zhou, Weibin; Cluckey, Andrew; Gee, Heon Yung; Ramaswami, Gokul; et al. (Cell, 2012)
Nephronophthisis-related ciliopathies (NPHP-RC) are degenerative recessive diseases that affect kidney, retina, and brain. Genetic defects in NPHP gene products that localize to cilia and centrosomes defined them as "ciliopathies." However, disease mechanisms remain poorly understood. Here, we identify by whole-exome resequencing, mutations of MRE11, ZNF423, and CEP164 as causing NPHP-RC. All three genes function within the DNA damage response (DDR) pathway. We demonstrate that, upon induced DNA damage, the NPHP-RC proteins ZNF423, CEP164, and NPHP10 colocalize to nuclear foci positive for TIP60, known to activate ATM at sites of DNA damage. We show that knockdown of CEP164 or ZNF423 causes sensitivity to DNA damaging agents and that cep164 knockdown in zebrafish results in dysregulated DDR and an NPHP-RC phenotype. Our findings link degenerative diseases of the kidney and retina, disorders of increasing prevalence, to mechanisms of DDR.
Keywords: Animals; Cilia; DNA Damage; DNA-Binding Proteins; Exome; Gene Knockdown Techniques; Genes, Recessive; Humans; Kidney Diseases, Cystic; Mice; Microtubule Proteins; MRE11 Homologue Protein; Proteins; Signal Transduction; Zebrafish

Gene therapy rescues cilia defects and restores olfactory function in a mammalian ciliopathy model. - McIntyre, Jeremy C; Davis, Erica E; Joiner, Ariell; Williams, Corey L; Tsai, I-Chun; Jenkins, Paul M; McEwen, Dyke P; Zhang, Lian; Escobado, John; Thomas, Sophie; Szymanska, Katarzyna; Johnson, Colin A; et al. (Nat Med, 2012)
Cilia are evolutionarily conserved microtubule-based organelles that are crucial for diverse biological functions, including motility, cell signaling and sensory perception. In humans, alterations in the formation and function of cilia manifest clinically as ciliopathies, a growing class of pleiotropic genetic disorders. Despite the substantial progress that has been made in identifying genes that cause ciliopathies, therapies for these disorders are not yet available to patients. Although mice with a hypomorphic mutation in the intraflagellar transport protein IFT88 (Ift88Tg737Rpw mice, also known as ORPK mice)5 have been well studied, the relevance of IFT88 mutations to human pathology is unknown. We show that a mutation in IFT88 causes a hitherto unknown human ciliopathy. In vivo complementation assays in zebrafish and mIMCD3 cells show the pathogenicity of this newly discovered allele. We further show that ORPK mice are functionally anosmic as a result of the loss of cilia on their olfactory sensory neurons (OSNs). Notably, adenoviral-mediated expression of IFT88 in mature, fully differentiated OSNs of ORPK mice is sufficient to restore ciliary structures and rescue olfactory function. These studies are the first to use in vivo therapeutic treatment to reestablish cilia in a mammalian ciliopathy. More broadly, our studies indicate that gene therapy is a viable option for cellular and functional rescue of the complex ciliary organelle in established differentiated cells.
Keywords: Adenoviridae; Animals; Cilia; Genetic Complementation Test; Genetic Diseases, Inborn; Genetic Therapy; Genetic Vectors; Humans; Mice; Microscopy, Fluorescence; Mutation; Olfactory Receptor Neurons; Smell; Tubulin; Tumor Suppressor Proteins; Zebrafish

Identical genomic organization of two hemichordate hox clusters. - Freeman, Robert; Ikuta, Tetsuro; Wu, Michael; Koyanagi, Ryo; Kawashima, Takeshi; Tagawa, Kunifumi; Humphreys, Tom; Fang, Guang-Chen; Fujiyama, Asao; Saiga, Hidetoshi; Lowe, Christopher; Worley, Kim; et al. (Curr Biol, 2012)
Genomic comparisons of chordates, hemichordates, and echinoderms can inform hypotheses for the evolution of these strikingly different phyla from the last common deuterostome ancestor. Because hox genes play pivotal developmental roles in bilaterian animals, we analyzed the Hox complexes of two hemichordate genomes. We find that Saccoglossus kowalevskii and Ptychodera flava both possess 12-gene clusters, with mir10 between hox4 and hox5, in 550 kb and 452 kb intervals, respectively. Genes hox1-hox9/10 of the clusters are in the same genomic order and transcriptional orientation as their orthologs in chordates, with hox1 at the 3' end of the cluster. At the 5' end, each cluster contains three posterior genes specific to Ambulacraria (the hemichordate-echinoderm clade), two forming an inverted terminal pair. In contrast, the echinoderm Strongylocentrotus purpuratus contains a 588 kb cluster of 11 orthologs of the hemichordate genes, ordered differently, plausibly reflecting rearrangements of an ancestral hemichordate-like ambulacrarian cluster. Hox clusters of vertebrates and the basal chordate amphioxus have similar organization to the hemichordate cluster, but with different posterior genes. These results provide genomic evidence for a well-ordered complex in the deuterostome ancestor for the hox1-hox9/10 region, with the number and kind of posterior genes still to be elucidated.
Keywords: Animals; Biological Evolution; Chordata, Nonvertebrate; Genes, Homeobox; Genome; Molecular Sequence Data; Multigene Family; Phylogeny; Transcription, Genetic

Integrated analyses of microRNAs demonstrate their widespread influence on gene expression in high-grade serous ovarian carcinoma. - Creighton, Chad J; Hernandez-Herrera, Anadulce; Jacobsen, Anders; Levine, Douglas A; Mankoo, Parminder; Schultz, Nikolaus; Du, Ying; Zhang, Yiqun; Larsson, Erik; Sheridan, Robert; Xiao, Weimin; Spellman, Paul T; et al. (PLoS One, 2012)
BACKGROUND: The Cancer Genome Atlas (TCGA) Network recently comprehensively catalogued the molecular aberrations in 487 high-grade serous ovarian cancers, with much remaining to be elucidated regarding the microRNAs (miRNAs). Here, using TCGA ovarian data, we surveyed the miRNAs, in the context of their predicted gene targets. METHODS AND RESULTS: Integration of miRNA and gene patterns yielded evidence that proximal pairs of miRNAs are processed from polycistronic primary transcripts, and that intronic miRNAs and their host gene mRNAs derive from common transcripts. Patterns of miRNA expression revealed multiple tumor subtypes and a set of 34 miRNAs predictive of overall patient survival. In a global analysis, miRNA:mRNA pairs anti-correlated in expression across tumors showed a higher frequency of in silico predicted target sites in the mRNA 3'-untranslated region (with less frequency observed for coding sequence and 5'-untranslated regions). The miR-29 family and predicted target genes were among the most strongly anti-correlated miRNA:mRNA pairs; over-expression of miR-29a in vitro repressed several anti-correlated genes (including DNMT3A and DNMT3B) and substantially decreased ovarian cancer cell viability. CONCLUSIONS: This study establishes miRNAs as having a widespread impact on gene expression programs in ovarian cancer, further strengthening our understanding of miRNA biology as it applies to human cancer. As with gene transcripts, miRNAs exhibit high diversity reflecting the genomic heterogeneity within a clinically homogeneous disease population. Putative miRNA:mRNA interactions, as identified using integrative analysis, can be validated. TCGA data are a valuable resource for the identification of novel tumor suppressive miRNAs in ovarian as well as other cancers.
Keywords: 3' Untranslated Regions; Breast; Cell Line, Tumor; DNA Copy Number Variations; Female; Gene Expression Regulation, Neoplastic; Humans; MicroRNAs; Neoplasms, Cystic, Mucinous, and Serous; Ovarian Neoplasms

An integrative variant analysis suite for whole exome next-generation sequencing data. - Challis, Danny; Yu, Jin; Evani, Uday S; Jackson, Andrew R; Paithankar, Sameer; Coarfa, Cristian; Milosavljevic, Aleksandar; Gibbs, Richard A; Yu, Fuli (BMC Bioinformatics, 2012)
BACKGROUND: Whole exome capture sequencing allows researchers to cost-effectively sequence the coding regions of the genome. Although the exome capture sequencing methods have become routine and well established, there is currently a lack of tools specialized for variant calling in this type of data. RESULTS: Using statistical models trained on validated whole-exome capture sequencing data, the Atlas2 Suite is an integrative variant analysis pipeline optimized for variant discovery on all three of the widely used next generation sequencing platforms (SOLiD, Illumina, and Roche 454). The suite employs logistic regression models in conjunction with user-adjustable cutoffs to accurately separate true SNPs and INDELs from sequencing and mapping errors with high sensitivity (96.7%). CONCLUSION: We have implemented the Atlas2 Suite and applied it to 92 whole exome samples from the 1000 Genomes Project. The Atlas2 Suite is available for download at http://sourceforge.net/projects/atlas2/. In addition to a command line version, the suite has been integrated into the Genboree Workbench, allowing biomedical scientists with minimal informatics expertise to remotely call, view, and further analyze variants through a simple web interface. The existing genomic databases displayed via the Genboree browser also streamline the process from variant discovery to functional genomics analysis, resulting in an off-the-shelf toolkit for the broader community.
Keywords: Exome; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Open Reading Frames; Polymorphism, Single Nucleotide; Software

MAPK target sites of eyes absent are not required for eye development or survival in Drosophila. - Jusiak, Barbara; Abulimiti, Abuduaini; Haelterman, Nele; Chen, Rui; Mardon, Graeme (PLoS One, 2012)
Eyes absent (Eya) is a highly conserved transcription cofactor and protein phosphatase that plays an essential role in eye development and survival in Drosophila. Ectopic eye induction assays using cDNA transgenes have suggested that mitogen activated protein kinase (MAPK) activates Eya by phosphorylating it on two consensus target sites, S402 and S407, and that this activation potentiates the ability of Eya to drive eye formation. However, this mechanism has never been tested in normal eye development. In the current study, we generated a series of genomic rescue transgenes to investigate how loss- and gain-of-function mutations at these two MAPK target sites within Eya affect Drosophila survival and normal eye formation: eya(+)GR, the wild-type control; eya(SA)GR, which lacks phosphorylation at the two target residues; and eya(SDE)GR, which contains phosphomimetic amino acids at the same two residues. Contrary to the previous studies in ectopic eye development, all eya genomic transgenes tested rescue both eye formation and survival equally effectively. We conclude that, in contrast to ectopic eye formation, MAPK-mediated phosphorylation of Eya on S402 and S407 does not play a role in normal development. This is the first study in Drosophila to evaluate the difference in outcomes between genomic rescue and ectopic cDNA-based overexpression of the same gene. These findings indicate similar genomic rescue strategies may prove useful for re-evaluating other long-standing Drosophila developmental models.
Keywords: Animals; Compound Eye, Arthropod; Drosophila; Drosophila Proteins; Eye Proteins; Gene Expression Regulation, Developmental; Mitogen-Activated Protein Kinases; Mutation; Phenotype; Phosphorylation; Signal Transduction

Mutations in KAT6B, encoding a histone acetyltransferase, cause Genitopatellar syndrome. - Campeau, Philippe M; Kim, Jaeseung C; Lu, James T; Schwartzentruber, Jeremy A; Abdul-Rahman, Omar A; Schlaubitz, Silke; Murdock, David M; Jiang, Ming-Ming; Lammer, Edward J; Enns, Gregory M; Rhead, William J; Rowland, Jon; et al. (Am J Hum Genet, 2012)
Genitopatellar syndrome (GPS) is a skeletal dysplasia with cerebral and genital anomalies for which the molecular basis has not yet been determined. By exome sequencing, we found de novo heterozygous truncating mutations in KAT6B (lysine acetyltransferase 6B, formerly known as MYST4 and MORF) in three subjects; then by Sanger sequencing of KAT6B, we found similar mutations in three additional subjects. The mutant transcripts do not undergo nonsense-mediated decay in cells from subjects with GPS. In addition, human pathological analyses and mouse expression studies point to systemic roles of KAT6B in controlling organismal growth and development. Myst4 (the mouse orthologous gene) is expressed in mouse tissues corresponding to those affected by GPS. Phenotypic differences and similarities between GPS, the Say-Barber-Biesecker variant of Ohdo syndrome (caused by different mutations of KAT6B), and Rubinstein-Taybi syndrome (caused by mutations in other histone acetyltransferases) are discussed. Together, the data support an epigenetic dysregulation of the limb, brain, and genital developmental programs.
Keywords: Abnormalities, Multiple; Animals; Blepharophimosis; Blepharoptosis; Bone Diseases, Developmental; Cerebellum; Epigenomics; Exome; Female; Heart Defects, Congenital; Heterozygote; Histone Acetyltransferases; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Musculoskeletal Abnormalities; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Sequence Analysis, DNA; Urogenital Abnormalities

Pancreatic cancer genomes reveal aberrations in axon guidance pathway genes. - Biankin, Andrew V; Waddell, Nicola; Kassahn, Karin S; Gingras, Marie-Claude; Muthuswamy, Lakshmi B; Johns, Amber L; Miller, David K; Wilson, Peter J; Patch, Ann-Marie; Wu, Jianmin; Chang, David K; Cowley, Mark J; et al. (Nature, 2012)
Pancreatic cancer is a highly lethal malignancy with few effective therapies. We performed exome sequencing and copy number analysis to define genomic aberrations in a prospectively accrued clinical cohort (n = 142) of early (stage I and II) sporadic pancreatic ductal adenocarcinoma. Detailed analysis of 99 informative tumours identified substantial heterogeneity with 2,016 non-silent mutations and 1,628 copy-number variations. We define 16 significantly mutated genes, reaffirming known mutations (KRAS, TP53, CDKN2A, SMAD4, MLL3, TGFBR2, ARID1A and SF3B1), and uncover novel mutated genes including additional genes involved in chromatin modification (EPC1 and ARID2), DNA damage repair (ATM) and other mechanisms (ZIM2, MAP2K4, NALCN, SLC16A4 and MAGEA6). Integrative analysis with in vitro functional data and animal models provided supportive evidence for potential roles for these genetic aberrations in carcinogenesis. Pathway-based analysis of recurrently mutated genes recapitulated clustering in core signalling pathways in pancreatic ductal adenocarcinoma, and identified new mutated genes in each pathway. We also identified frequent and diverse somatic aberrations in genes described traditionally as embryonic regulators of axon guidance, particularly SLIT/ROBO signalling, which was also evident in murine Sleeping Beauty transposon-mediated somatic mutagenesis models of pancreatic cancer, providing further supportive evidence for the potential involvement of axon guidance genes in pancreatic carcinogenesis.
Keywords: Animals; Axons; Carcinoma, Pancreatic Ductal; Gene Dosage; Gene Expression Regulation, Neoplastic; Genome; Humans; Kaplan-Meier Estimate; Mice; Mutation; Pancreatic Neoplasms; Proteins; Signal Transduction

Patterns and rates of exonic de novo mutations in autism spectrum disorders. - Neale, Benjamin M; Kou, Yan; Liu, Li; Ma'ayan, Avi; Samocha, Kaitlin E; Sabo, Aniko; Lin, Chiao-Feng; Stevens, Christine; Wang, Li-San; Makarov, Vladimir; Polak, Paz; Yoon, Seungtai; et al. (Nature, 2012)
Autism spectrum disorders (ASD) are believed to have genetic and environmental origins, yet in only a modest fraction of individuals can specific causes be identified. To identify further genetic risk factors, here we assess the role of de novo mutations in ASD by sequencing the exomes of ASD cases and their parents (n = 175 trios). Fewer than half of the cases (46.3%) carry a missense or nonsense de novo variant, and the overall rate of mutation is only modestly higher than the expected rate. In contrast, the proteins encoded by genes that harboured de novo missense or nonsense mutations showed a higher degree of connectivity among themselves and to previous ASD genes as indexed by protein-protein interaction screens. The small increase in the rate of de novo events, when taken together with the protein interaction results, are consistent with an important but limited role for de novo point mutations in ASD, similar to that documented for de novo copy number variants. Genetic models incorporating these data indicate that most of the observed de novo events are unconnected to ASD; those that do confer risk are distributed across many genes and are incompletely penetrant (that is, not necessarily sufficient for disease). Our results support polygenic models in which spontaneous coding mutations in any of a large number of genes increases risk by 5- to 20-fold. Despite the challenge posed by such models, results from de novo events and a large parallel case-control study provide strong evidence in favour of CHD8 and KATNAL2 as genuine autism risk factors.
Keywords: Autistic Disorder; Case-Control Studies; DNA-Binding Proteins; Exome; Exons; Family Health; Genetic Predisposition to Disease; Humans; Models, Genetic; Multifactorial Inheritance; Mutation; Phenotype; Poisson Distribution; Protein Interaction Maps; Transcription Factors

REGγ is associated with multiple oncogenic pathways in human cancers. - He, Jing; Cui, Long; Zeng, Yu; Wang, Guangqiang; Zhou, Ping; Yang, Yuanyuan; Ji, Lei; Zhao, Yanyan; Chen, Jiwu; Wang, Zhuo; Shi, Tieliu; Zhang, Pei; et al. (BMC Cancer, 2012)
BACKGROUND: Recent studies suggest a role of the proteasome activator, REGγ, in cancer progression. Since there are limited numbers of known REGγ targets, it is not known which cancers and pathways are associated with REGγ. METHODS: REGγ protein expressions in four different cancers were investigated by immunohistochemistry (IHC) analysis. Following NCBI Gene Expression Omnibus (GEO) database search, microarray platform validation, differential expressions of REGγ in corresponding cancers were statistically analyzed. Genes highly correlated with REGγ were defined based on Pearson's correlation coefficient. Functional links were estimated by Ingenuity Core analysis. Finally, validation was performed by RT-PCR analysis in established cancer cell lines and IHC in human colon cancer tissues RESULTS: Here, we demonstrate overexpression of REGγ in four different cancer types by micro-tissue array analysis. Using meta-analysis of publicly available microarray databases and biological studies, we verified elevated REGγ gene expression in the four types of cancers and identified genes significantly correlated with REGγ expression, including genes in p53, Myc pathways, and multiple other cancer-related pathways. The predicted correlations were largely consistent with quantitative RT-PCR analysis. CONCLUSIONS: This study provides us novel insights in REGγ gene expression profiles and its link to multiple cancer-related pathways in cancers. Our results indicate potentially important pathogenic roles of REGγ in multiple cancer types and implicate REGγ as a putative cancer marker.
Keywords: Antigens, Neoplasm; Autoantigens; Colonic Neoplasms; Disease Progression; Gene Expression Profiling; Humans; Immunohistochemistry; Liver Neoplasms; Lung Neoplasms; Microarray Analysis; Neoplasms; Proteasome Endopeptidase Complex; Thyroid Neoplasms; Tumor Cells, Cultured

A systematic survey of loss-of-function variants in human protein-coding genes. - MacArthur, Daniel G; Balasubramanian, Suganthi; Frankish, Adam; Huang, Ni; Morris, James; Walter, Klaudia; Jostins, Luke; Habegger, Lukas; Pickrell, Joseph K; Montgomery, Stephen B; Albers, Cornelis A; Zhang, Zhengdong D; et al. (Science, 2012)
Genome-sequencing studies indicate that all humans carry many genetic variants predicted to cause loss of function (LoF) of protein-coding genes, suggesting unexpected redundancy in the human genome. Here we apply stringent filters to 2951 putative LoF variants obtained from 185 human genomes to determine their true prevalence and properties. We estimate that human genomes typically contain ~100 genuine LoF variants with ~20 genes completely inactivated. We identify rare and likely deleterious LoF alleles, including 26 known and 21 predicted severe disease-causing variants, as well as common LoF variants in nonessential genes. We describe functional and evolutionary differences between LoF-tolerant and recessive disease genes and a method for using these differences to prioritize candidate genes found in clinical sequencing studies.
Keywords: Disease; Gene Expression; Gene Frequency; Genetic Variation; Genome, Human; Humans; Phenotype; Polymorphism, Single Nucleotide; Proteins; Selection, Genetic

Copy number variation detection in whole-genome sequencing data using the Bayesian information criterion. - Xi, Ruibin; Hadjipanayis, Angela G; Luquette, Lovelace J; Kim, Tae-Min; Lee, Eunjung; Zhang, Jianhua; Johnson, Mark D; Muzny, Donna M; Wheeler, David A; Gibbs, Richard A; Kucherlapati, Raju; Park, Peter J (Proc Natl Acad Sci U S A, 2011)
DNA copy number variations (CNVs) play an important role in the pathogenesis and progression of cancer and confer susceptibility to a variety of human disorders. Array comparative genomic hybridization has been used widely to identify CNVs genome wide, but the next-generation sequencing technology provides an opportunity to characterize CNVs genome wide with unprecedented resolution. In this study, we developed an algorithm to detect CNVs from whole-genome sequencing data and applied it to a newly sequenced glioblastoma genome with a matched control. This read-depth algorithm, called BIC-seq, can accurately and efficiently identify CNVs via minimizing the Bayesian information criterion. Using BIC-seq, we identified hundreds of CNVs as small as 40 bp in the cancer genome sequenced at 10× coverage, whereas we could only detect large CNVs (> 15 kb) in the array comparative genomic hybridization profiles for the same genome. Eighty percent (14/16) of the small variants tested (110 bp to 14 kb) were experimentally validated by quantitative PCR, demonstrating high sensitivity and true positive rate of the algorithm. We also extended the algorithm to detect recurrent CNVs in multiple samples as well as deriving error bars for breakpoints using a Gibbs sampling approach. We propose this statistical approach as a principled yet practical and efficient method to estimate CNVs in whole-genome sequencing data.
Keywords: Algorithms; Bayes Theorem; Brain Neoplasms; Comparative Genomic Hybridization; Computer Simulation; DNA Copy Number Variations; Female; Gene Dosage; Genome; Genome, Human; Glioblastoma; Humans; Models, Genetic; Models, Statistical; Sequence Analysis, DNA

dbNSFP: a lightweight database of human nonsynonymous SNPs and their functional predictions. - Liu, Xiaoming; Jian, Xueqiu; Eric Boerwinkle (Hum Mutat, 2011)
With the advance of sequencing technologies, whole exome sequencing has increasingly been used to identify mutations that cause human diseases, especially rare Mendelian diseases. Among the analysis steps, functional prediction (of being deleterious) plays an important role in filtering or prioritizing nonsynonymous SNP (NS) for further analysis. Unfortunately, different prediction algorithms use different information and each has its own strength and weakness. It has been suggested that investigators should use predictions from multiple algorithms instead of relying on a single one. However, querying predictions from different databases/Web-servers for different algorithms is both tedious and time consuming, especially when dealing with a huge number of NSs identified by exome sequencing. To facilitate the process, we developed dbNSFP (database for nonsynonymous SNPs' functional predictions). It compiles prediction scores from four new and popular algorithms (SIFT, Polyphen2, LRT, and MutationTaster), along with a conservation score (PhyloP) and other related information, for every potential NS in the human genome (a total of 75,931,005). It is the first integrated database of functional predictions from multiple algorithms for the comprehensive collection of human NSs. dbNSFP is freely available for download at http://sites.google.com/site/jpopgen/dbNSFP.
Keywords: Algorithms; Computational Biology; Databases, Nucleic Acid; Genetic Association Studies; Humans; Internet; Polymorphism, Single Nucleotide; Software

Exome sequencing of head and neck squamous cell carcinoma reveals inactivating mutations in NOTCH1. - Agrawal, Nishant; Frederick, Mitchell J; Pickering, Curtis R; Bettegowda, Chetan; Chang, Kyle; Li, Ryan J; Fakhry, Carole; Xie, Tong-Xin; Zhang, Jiexin; Wang, Jing; Zhang, Nianxiang; El-Naggar, Adel K; et al. (Science, 2011)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide. To explore the genetic origins of this cancer, we used whole-exome sequencing and gene copy number analyses to study 32 primary tumors. Tumors from patients with a history of tobacco use had more mutations than did tumors from patients who did not use tobacco, and tumors that were negative for human papillomavirus (HPV) had more mutations than did HPV-positive tumors. Six of the genes that were mutated in multiple tumors were assessed in up to 88 additional HNSCCs. In addition to previously described mutations in TP53, CDKN2A, PIK3CA, and HRAS, we identified mutations in FBXW7 and NOTCH1. Nearly 40% of the 28 mutations identified in NOTCH1 were predicted to truncate the gene product, suggesting that NOTCH1 may function as a tumor suppressor gene rather than an oncogene in this tumor type.
Keywords: Carcinoma; Carcinoma, Squamous Cell; Cell Cycle Proteins; Codon, Nonsense; Exons; F-Box Proteins; F-Box-WD Repeat-Containing Protein 7; Gene Dosage; Genes, p53; Genes, Tumor Suppressor; Head and Neck Neoplasms; Humans; INDEL Mutation; Mutation; Mutation, Missense; Neoplasms, Squamous Cell; Nicotiana; Oligonucleotide Array Sequence Analysis; Oncogenes; Papillomaviridae; Papillomavirus Infections; Receptor, Notch1; Sequence Analysis, DNA; Smoking; Squamous Cell Carcinoma of Head and Neck; Ubiquitin-Protein Ligases

Genetical genomics of Th1 and Th2 immune response in a baboon model of atherosclerosis risk factors. - Vinson, A; Curran, J E; Johnson, M P; Dyer, T D; Moses, E K; Blangero, J; Cox, L A; Rogers, J; Havill, L M; VandeBerg, J L; Mahaney, M C (Atherosclerosis, 2011)
OBJECTIVE: CD4(+) T-cells mediate inflammation in atherosclerosis, but additive genetic effects on associated pathways of Th1 and Th2 immune response have not been described. We sought to characterize heritability, pleiotropy, and QTL effects on the expression of genes implicated in Th1 and Th2 immune response in a baboon model of risk factors for atherosclerosis. METHODS: We employed a maximum likelihood-based variance decomposition approach to estimate additive genetic effects on transcript levels generated from a gene expression profile of lymphocytes in 499 pedigreed baboons maintained on a basal diet. Transcript levels for 57 genes implicated in Th1 and Th2 immune response were selected for analysis based on significant heritability in this profile. Multipoint whole genome scans were conducted on heritable transcript levels to localize QTLs influencing these measures. To evaluate pleiotropic effects on transcript levels, we estimated genetic and phenotypic correlations among transcript measures, and assessed their correspondence using a Mantel test. Network analysis using GeneGo's MetaCore™ software was conducted to characterize known interaction among coded proteins. RESULTS: Heritabilities for candidate gene transcript levels ranged from 0.092-0.786 (median h(2)=0.278, P=4.72×10(-4)). Linkage analyses yielded significant evidence (LOD≥2.73) for 14 eQTLs (LOD score range 2.76-14.87, genome-wide P=4.9×10(-2)-1.03×10(-14)). Estimates of genetic correlation supported shared additive genetic effects incorporating all 57 transcripts (null hypothesis of ρ(G)=0 rejected at FDR≤0.05 for 522 of 1596 estimates), and accounted for most of the observed phenotypic correlation among transcripts (Mantel test, r([ρP],)([ρG])=0.781, P<0.0001). Network analysis revealed direct interactions among 54 of the 57 coded proteins. CONCLUSIONS: We conclude that major genetic effects influence expression levels of multiple genes implicated in Th1 and Th2 immune response. Additionally, we find that expression levels of these candidate genes are characterized by extensive pleiotropy, consistent with known interaction among their coded proteins, many of which are independently associated with atherosclerosis.
Keywords: Animals; Atherosclerosis; Disease Models, Animal; Female; Gene Expression Profiling; Gene Regulatory Networks; Genetic Pleiotropy; Genetic Predisposition to Disease; Heredity; Inflammation; Male; Models, Genetic; Papio hamadryas; Phenotype; Quantitative Trait Loci; Risk Assessment; Risk Factors; Th1 Cells; Th2 Cells; Transcription, Genetic

Genome sequence of an Australian kangaroo, Macropus eugenii, provides insight into the evolution of mammalian reproduction and development. - Renfree, Marilyn B; Papenfuss, Anthony T; Deakin, Janine E; Lindsay, James; Heider, Thomas; Belov, Katherine; Rens, Willem; Waters, Paul D; Pharo, Elizabeth A; Shaw, Geoff; Wong, Emily S W; Lefèvre, Christophe M; et al. (Genome Biol, 2011)
BACKGROUND: We present the genome sequence of the tammar wallaby, Macropus eugenii, which is a member of the kangaroo family and the first representative of the iconic hopping mammals that symbolize Australia to be sequenced. The tammar has many unusual biological characteristics, including the longest period of embryonic diapause of any mammal, extremely synchronized seasonal breeding and prolonged and sophisticated lactation within a well-defined pouch. Like other marsupials, it gives birth to highly altricial young, and has a small number of very large chromosomes, making it a valuable model for genomics, reproduction and development. RESULTS: The genome has been sequenced to 2 × coverage using Sanger sequencing, enhanced with additional next generation sequencing and the integration of extensive physical and linkage maps to build the genome assembly. We also sequenced the tammar transcriptome across many tissues and developmental time points. Our analyses of these data shed light on mammalian reproduction, development and genome evolution: there is innovation in reproductive and lactational genes, rapid evolution of germ cell genes, and incomplete, locus-specific X inactivation. We also observe novel retrotransposons and a highly rearranged major histocompatibility complex, with many class I genes located outside the complex. Novel microRNAs in the tammar HOX clusters uncover new potential mammalian HOX regulatory elements. CONCLUSIONS: Analyses of these resources enhance our understanding of marsupial gene evolution, identify marsupial-specific conserved non-coding elements and critical genes across a range of biological systems, including reproduction, development and immunity, and provide new insight into marsupial and mammalian biology and genome evolution.
Keywords: Animals; Australia; Biological Evolution; Chromosome Mapping; Chromosomes, Mammalian; Female; Gene Expression Regulation; Genome; Genomic Imprinting; In Situ Hybridization, Fluorescence; Macropodidae; MicroRNAs; Molecular Sequence Data; Reproduction; Sequence Alignment; Sequence Analysis, DNA; Transcriptome

Genome-wide high-density SNP linkage search for glioma susceptibility loci: results from the Gliogene Consortium. - Shete, Sanjay; Lau, Ching C; Houlston, Richard S; Claus, Elizabeth B; Barnholtz-Sloan, Jill; Lai, Rose; Il'yasova, Dora; Schildkraut, Joellen; Sadetzki, Siegal; Johansen, Christoffer; Bernstein, Jonine L; Olson, Sara H; et al. (Cancer Res, 2011)
Gliomas, which generally have a poor prognosis, are the most common primary malignant brain tumors in adults. Recent genome-wide association studies have shown that inherited susceptibility plays a role in the development of glioma. Although first-degree relatives of patients exhibit a two-fold increased risk of glioma, the search for susceptibility loci in familial forms of the disease has been challenging because the disease is relatively rare, fatal, and heterogeneous, making it difficult to collect sufficient biosamples from families for statistical power. To address this challenge, the Genetic Epidemiology of Glioma International Consortium (Gliogene) was formed to collect DNA samples from families with two or more cases of histologically confirmed glioma. In this study, we present results obtained from 46 U.S. families in which multipoint linkage analyses were undertaken using nonparametric (model-free) methods. After removal of high linkage disequilibrium single-nucleotide polymorphism, we obtained a maximum nonparametric linkage score (NPL) of 3.39 (P = 0.0005) at 17q12-21.32 and the Z-score of 4.20 (P = 0.000007). To replicate our findings, we genotyped 29 independent U.S. families and obtained a maximum NPL score of 1.26 (P = 0.008) and the Z-score of 1.47 (P = 0.035). Accounting for the genetic heterogeneity using the ordered subset analysis approach, the combined analyses of 75 families resulted in a maximum NPL score of 3.81 (P = 0.00001). The genomic regions we have implicated in this study may offer novel insights into glioma susceptibility, focusing future work to identify genes that cause familial glioma.
Keywords: Adolescent; Adult; Aged; Brain Neoplasms; Child; Chromosome Mapping; Family Health; Female; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Glioma; Humans; Linkage Disequilibrium; Lod Score; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; United States; Young Adult

A high-resolution map of human evolutionary constraint using 29 mammals. - Lindblad-Toh, Kerstin; Garber, Manuel; Zuk, Or; Lin, Michael F; Parker, Brian J; Washietl, Stefan; Kheradpour, Pouya; Ernst, Jason; Jordan, Gregory; Mauceli, Evan; Ward, Lucas D; Lowe, Craig B; et al. (Nature, 2011)
The comparison of related genomes has emerged as a powerful lens for genome interpretation. Here we report the sequencing and comparative analysis of 29 eutherian genomes. We confirm that at least 5.5% of the human genome has undergone purifying selection, and locate constrained elements covering ∼4.2% of the genome. We use evolutionary signatures and comparisons with experimental data sets to suggest candidate functions for ∼60% of constrained bases. These elements reveal a small number of new coding exons, candidate stop codon readthrough events and over 10,000 regions of overlapping synonymous constraint within protein-coding exons. We find 220 candidate RNA structural families, and nearly a million elements overlapping potential promoter, enhancer and insulator regions. We report specific amino acid residues that have undergone positive selection, 280,000 non-coding elements exapted from mobile elements and more than 1,000 primate- and human-accelerated elements. Overlap with disease-associated variants indicates that our findings will be relevant for studies of human biology, health and disease.
Keywords: Animals; Disease; Evolution, Molecular; Exons; Genome; Genome, Human; Genomics; Health; Humans; Mammals; Molecular Sequence Annotation; Phylogeny; RNA; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

Kinda baboons (Papio kindae) and grayfoot chacma baboons (P. ursinus griseipes) hybridize in the Kafue river valley, Zambia. - Jolly, C J; Burrell, A S; Phillips-Conroy, J E; Bergey, C; Rogers, J (Am J Primatol, 2011)
The ranges of small kinda (Papio kindae) and much larger grayfooted chacma (P. ursinus griseipes) baboons adjoin in the Kafue National Park, Zambia. In a visual survey of baboons at 48 sites in the Kafue River drainage we found that, contrary to previous reports, groups at the species interface near the town of Ngoma are phenotypically diverse and presumably formed by multigenerational hybridization. Mitochondrial and/or Y-chromosome genetic markers from fecal samples (N=164) collected at 29 sites support this conclusion. Groups with phenotypic signs of a history of hybridization also had taxon-specific mitochondria and Y-haplotypes from both parental species. Although the distribution of mitochondrial haplotypes largely mirrored that of external phenotypes, a significant proportion of male specimens from grayfoot as well as hybrid groups carried kinda Y-chromosomes, and kinda Y-chromosomes were involved in all observed cases of mitochondrial/Y-chromosome discordance. These observations are consistent with, though they do not prove, a population history in which the range of chacmas and the hybrid zone have advanced at the expense of the kinda range. They also suggest that, unexpectedly, kinda male×chacma female matings are much more common than the reciprocal cross in the ancestry of hybrids. We suggest that distinctive male kinda behavior and the "juvenile" appearance of kinda baboons of both sexes, perhaps combined with obstetric difficulties of a small kinda female carrying the large offspring of a chacma male, may account for this bias.
Keywords: Animals; Animals, Wild; DNA, Mitochondrial; Female; Genes, Y-Linked; Genetic Markers; Genetic Variation; Haplotypes; Hybridization, Genetic; Male; Papio; Papio ursinus; Phenotype; Sexual Behavior, Animal; Zambia

Minimum information about a marker gene sequence (MIMARKS) and minimum information about any (x) sequence (MIxS) specifications. - Yilmaz, Pelin; Kottmann, Renzo; Field, Dawn; Knight, Rob; Cole, James R; Amaral-Zettler, Linda; Gilbert, Jack A; Karsch-Mizrachi, Ilene; Johnston, Anjanette; Cochrane, Guy; Vaughan, Robert; Hunter, Christopher; et al. (Nat Biotechnol, 2011)
Here we present a standard developed by the Genomic Standards Consortium (GSC) for reporting marker gene sequences--the minimum information about a marker gene sequence (MIMARKS). We also introduce a system for describing the environment from which a biological sample originates. The 'environmental packages' apply to any genome sequence of known origin and can be used in combination with MIMARKS and other GSC checklists. Finally, to establish a unified standard for describing sequence data and to provide a single point of entry for the scientific community to access and learn about GSC checklists, we present the minimum information about any (x) sequence (MIxS). Adoption of MIxS will enhance our ability to analyze natural genetic diversity documented by massive DNA sequencing efforts from myriad ecosystems in our ever-changing biosphere.
Keywords: Biomarkers; Checklist; Databases, Genetic; Environment; Genes, rRNA; Genetic Variation; Humans; Information Storage and Retrieval; Internet; Metagenomics; Programming Languages; Sequence Analysis, DNA; Software

Recurrent chromosome 16p13.1 duplications are a risk factor for aortic dissections. - Kuang, Shao-Qing; Guo, Dong-chuan; Prakash, Siddharth K; McDonald, Merry-Lynn N; Johnson, Ralph J; Wang, Min; Regalado, Ellen S; Russell, Ludivine; Cao, Jiu-Mei; Kwartler, Callie; Fraivillig, Kurt; Coselli, Joseph S; et al. (PLoS Genet, 2011)
Chromosomal deletions or reciprocal duplications of the 16p13.1 region have been implicated in a variety of neuropsychiatric disorders such as autism, schizophrenia, epilepsies, and attention-deficit hyperactivity disorder (ADHD). In this study, we investigated the association of recurrent genomic copy number variants (CNVs) with thoracic aortic aneurysms and dissections (TAAD). By using SNP arrays to screen and comparative genomic hybridization microarrays to validate, we identified 16p13.1 duplications in 8 out of 765 patients of European descent with adult-onset TAAD compared with 4 of 4,569 controls matched for ethnicity (P = 5.0 × 10⁻⁵, OR = 12.2). The findings were replicated in an independent cohort of 467 patients of European descent with TAAD (P = 0.005, OR = 14.7). Patients with 16p13.1 duplications were more likely to harbor a second rare CNV (P = 0.012) and to present with aortic dissections (P = 0.010) than patients without duplications. Duplications of 16p13.1 were identified in 2 of 130 patients with familial TAAD, but the duplications did not segregate with TAAD in the families. MYH11, a gene known to predispose to TAAD, lies in the duplicated region of 16p13.1, and increased MYH11 expression was found in aortic tissues from TAAD patients with 16p13.1 duplications compared with control aortas. These data suggest chromosome 16p13.1 duplications confer a risk for TAAD in addition to the established risk for neuropsychiatric disorders. It also indicates that recurrent CNVs may predispose to disorders involving more than one organ system, an observation critical to the understanding of the role of recurrent CNVs in human disease and a finding that may be common to other recurrent CNVs involving multiple genes.
Keywords: Adult; Aged; Aorta; Aortic Aneurysm, Thoracic; Aortic Dissection; Case-Control Studies; Chromosome Duplication; Chromosomes, Human, Pair 16; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Myosin Heavy Chains; Pedigree; Phenotype; Risk Factors

Targeted enrichment beyond the consensus coding DNA sequence exome reveals exons with higher variant densities. - Bainbridge, Matthew N; Wang, Min; Wu, Yuanqing; Newsham, Irene; Muzny, Donna M; Jefferies, John L; Albert, Thomas J; Burgess, Daniel L; Gibbs, Richard A (Genome Biol, 2011)
BACKGROUND: Enrichment of loci by DNA hybridization-capture, followed by high-throughput sequencing, is an important tool in modern genetics. Currently, the most common targets for enrichment are the protein coding exons represented by the consensus coding DNA sequence (CCDS). The CCDS, however, excludes many actual or computationally predicted coding exons present in other databases, such as RefSeq and Vega, and non-coding functional elements such as untranslated and regulatory regions. The number of variants per base pair (variant density) and our ability to interrogate regions outside of the CCDS regions is consequently less well understood. RESULTS: We examine capture sequence data from outside of the CCDS regions and find that extremes of GC content that are present in different subregions of the genome can reduce the local capture sequence coverage to less than 50% relative to the CCDS. This effect is due to biases inherent in both the Illumina and SOLiD sequencing platforms that are exacerbated by the capture process. Interestingly, for two subregion types, microRNA and predicted exons, the capture process yields higher than expected coverage when compared to whole genome sequencing. Lastly, we examine the variation present in non-CCDS regions and find that predicted exons, as well as exonic regions specific to RefSeq and Vega, show much higher variant densities than the CCDS. CONCLUSIONS: We show that regions outside of the CCDS perform less efficiently in capture sequence experiments. Further, we show that the variant density in computationally predicted exons is more than 2.5-times higher than that observed in the CCDS.
Keywords: Alleles; Computational Biology; Consensus Sequence; Exome; Exons; Gene Frequency; Genome, Human; Humans; Introns; Mutation Rate; Open Reading Frames; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

TTC21B contributes both causal and modifying alleles across the ciliopathy spectrum. - Davis, Erica E; Zhang, Qi; Liu, Qin; Diplas, Bill H; Davey, Lisa M; Hartley, Jane; Stoetzel, Corinne; Szymanska, Katarzyna; Ramaswami, Gokul; Logan, Clare V; Muzny, Donna M; Young, Alice C; et al. (Nat Genet, 2011)
Ciliary dysfunction leads to a broad range of overlapping phenotypes, collectively termed ciliopathies. This grouping is underscored by genetic overlap, where causal genes can also contribute modifier alleles to clinically distinct disorders. Here we show that mutations in TTC21B, which encodes the retrograde intraflagellar transport protein IFT139, cause both isolated nephronophthisis and syndromic Jeune asphyxiating thoracic dystrophy. Moreover, although resequencing of TTC21B in a large, clinically diverse ciliopathy cohort and matched controls showed a similar frequency of rare changes, in vivo and in vitro evaluations showed a significant enrichment of pathogenic alleles in cases (P < 0.003), suggesting that TTC21B contributes pathogenic alleles to ∼5% of ciliopathy cases. Our data illustrate how genetic lesions can be both causally associated with diverse ciliopathies and interact in trans with other disease-causing genes and highlight how saturated resequencing followed by functional analysis of all variants informs the genetic architecture of inherited disorders.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Ciliary Motility Disorders; Genetic Variation; Humans; Mice; Mutation; Pedigree; Photoreceptor Cells; Zebrafish

Calpain-10 is a component of the obesity-related quantitative trait locus Adip1. - Cheverud, James M; Fawcett, Gloria L; Jarvis, Joseph P; Norgard, Elizabeth A; Pavlicev, Mihaela; Pletscher, L Susan; Polonsky, Kenneth S; Ye, Honggang; Bell, Graeme I; Semenkovich, Clay F (J Lipid Res, 2010)
We previously mapped Adip1, an obesity quantitative trait locus (QTL), to the central portion of murine chromosome 1 containing the calpain-10 (Capn10) gene. Human studies have associated calpain-10 (CAPN10) variants with type 2 diabetes and various metabolic traits. We performed a quantitative hybrid complementation test (QHCT) to determine whether differences attributed to Adip1 are the result of variant Capn10 alleles in LG/J and SM/J mice. We crossed LG/J and SM/J to wild-type (C57BL/6J) and Capn10 knockout (Capn10(-/-)) mice to form four F(1) hybrid groups: LG/J by wild-type, LG/J by Capn10(-/-), SM/J by wild-type, and SM/J by Capn10(-/-). We performed a two-way ANOVA with the experimental strain, tester strain, and their interaction as the factors. Significant interaction indicates a quantitative failure to complement. We found failure to complement for fat, organ, and body weights, and leptin, female free fatty acid, and triglyceride levels. Capn10(-/-) resulted in heavier weights and higher serum levels in LG/J crosses but not in SM/J crosses. For glucose tolerance and insulin response tests, the Capn10(-/-) allele resulted in lower glucose levels in crosses with SM/J but had no effect in the LG/J crosses. Differences between the LG/J and SM/J Capn10 alleles are the likely source of some of the QTL effects mapped to Adip1 in the LG/J-by-SM/J cross. Capn10 plays an important role in regulating obesity and diabetes in mice.
Keywords: Alleles; Animals; Calpain; Female; Gene Knockout Techniques; Genetic Complementation Test; Genetic Variation; Hybridization, Genetic; Male; Mice; Obesity; Quantitative Trait Loci

A catalog of reference genomes from the human microbiome. - Nelson, Karen E; Weinstock, George M; Highlander, Sarah K; Worley, Kim C; Creasy, Heather Huot; Wortman, Jennifer Russo; Rusch, Douglas B; Mitreva, Makedonka; Sodergren, Erica; Chinwalla, Asif T; Feldgarden, Michael; Gevers, Dirk; et al. (Science, 2010)
The human microbiome refers to the community of microorganisms, including prokaryotes, viruses, and microbial eukaryotes, that populate the human body. The National Institutes of Health launched an initiative that focuses on describing the diversity of microbial species that are associated with health and disease. The first phase of this initiative includes the sequencing of hundreds of microbial reference genomes, coupled to metagenomic sequencing from multiple body sites. Here we present results from an initial reference genome sequencing of 178 microbial genomes. From 547,968 predicted polypeptides that correspond to the gene complement of these strains, previously unidentified ("novel") polypeptides that had both unmasked sequence length greater than 100 amino acids and no BLASTP match to any nonreference entry in the nonredundant subset were defined. This analysis resulted in a set of 30,867 polypeptides, of which 29,987 (approximately 97%) were unique. In addition, this set of microbial genomes allows for approximately 40% of random sequences from the microbiome of the gastrointestinal tract to be associated with organisms based on the match criteria used. Insights into pan-genome analysis suggest that we are still far from saturating microbial species genetic data sets. In addition, the associated metrics and standards used by our group for quality assurance are presented.
Keywords: Bacteria; Bacterial Proteins; Biodiversity; Computational Biology; Databases, Genetic; Gastrointestinal Tract; Genes, Bacterial; Genetic Variation; Genome, Archaeal; Genome, Bacterial; Humans; Metagenome; Metagenomics; Mouth; Peptides; Phylogeny; Respiratory System; Sequence Analysis, DNA; Skin; Urogenital System

Deep resequencing reveals excess rare recent variants consistent with explosive population growth. - Coventry, Alex; Bull-Otterson, Lara M; Liu, Xiaoming; Clark, Andrew G; Maxwell, Taylor J; Crosby, Jacy; Hixson, James E; Rea, Thomas J; Donna M Muzny; Lewis, Lora R; David A Wheeler; Aniko Sabo; et al. (Nat Commun, 2010)
Accurately determining the distribution of rare variants is an important goal of human genetics, but resequencing of a sample large enough for this purpose has been unfeasible until now. Here, we applied Sanger sequencing of genomic PCR amplicons to resequence the diabetes-associated genes KCNJ11 and HHEX in 13,715 people (10,422 European Americans and 3,293 African Americans) and validated amplicons potentially harbouring rare variants using 454 pyrosequencing. We observed far more variation (expected variant-site count ∼578) than would have been predicted on the basis of earlier surveys, which could only capture the distribution of common variants. By comparison with earlier estimates based on common variants, our model shows a clear genetic signal of accelerating population growth, suggesting that humanity harbours a myriad of rare, deleterious variants, and that disease risk and the burden of disease in contemporary populations may be heavily influenced by the distribution of rare variants.

Functional and evolutionary insights from the genomes of three parasitoid Nasonia species. - Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; et al. (Science, 2010)
We report here genome sequences and comparative analyses of three closely related parasitoid wasps: Nasonia vitripennis, N. giraulti, and N. longicornis. Parasitoids are important regulators of arthropod populations, including major agricultural pests and disease vectors, and Nasonia is an emerging genetic model, particularly for evolutionary and developmental genetics. Key findings include the identification of a functional DNA methylation tool kit; hymenopteran-specific genes including diverse venoms; lateral gene transfers among Pox viruses, Wolbachia, and Nasonia; and the rapid evolution of genes involved in nuclear-mitochondrial interactions that are implicated in speciation. Newly developed genome resources advance Nasonia for genetic research, accelerate mapping and cloning of quantitative trait loci, and will ultimately provide tools and knowledge for further increasing the utility of parasitoids as pest insect-control agents.
Keywords: Animals; Arthropods; Biological Evolution; DNA Methylation; DNA Transposable Elements; Female; Gene Transfer, Horizontal; Genes, Insect; Genetic Speciation; Genetic Variation; Genome, Insect; Host-Parasite Interactions; Insect Proteins; Insect Viruses; Insecta; Male; Molecular Sequence Data; Quantitative Trait Loci; Recombination, Genetic; Sequence Analysis, DNA; Wasp Venoms; Wasps; Wolbachia

Genetic diversity in India and the inference of Eurasian population expansion. - Xing, Jinchuan; Watkins, W Scott; Hu, Ya; Huff, Chad D; Sabo, Aniko; Muzny, Donna M; Bamshad, Michael J; Gibbs, Richard A; Jorde, Lynn B; Yu, Fuli (Genome Biol, 2010)
BACKGROUND: Genetic studies of populations from the Indian subcontinent are of great interest because of India's large population size, complex demographic history, and unique social structure. Despite recent large-scale efforts in discovering human genetic variation, India's vast reservoir of genetic diversity remains largely unexplored. RESULTS: To analyze an unbiased sample of genetic diversity in India and to investigate human migration history in Eurasia, we resequenced one 100-kb ENCODE region in 92 samples collected from three castes and one tribal group from the state of Andhra Pradesh in south India. Analyses of the four Indian populations, along with eight HapMap populations (692 samples), showed that 30% of all SNPs in the south Indian populations are not seen in HapMap populations. Several Indian populations, such as the Yadava, Mala/Madiga, and Irula, have nucleotide diversity levels as high as those of HapMap African populations. Using unbiased allele-frequency spectra, we investigated the expansion of human populations into Eurasia. The divergence time estimates among the major population groups suggest that Eurasian populations in this study diverged from Africans during the same time frame (approximately 90 to 110 thousand years ago). The divergence among different Eurasian populations occurred more than 40,000 years after their divergence with Africans. CONCLUSIONS: Our results show that Indian populations harbor large amounts of genetic variation that have not been surveyed adequately by public SNP discovery efforts. Our data also support a delayed expansion hypothesis in which an ancestral Eurasian founding population remained isolated long after the out-of-Africa diaspora, before expanding throughout Eurasia.
Keywords: DNA, Mitochondrial; Ethnicity; Gene Frequency; Genetic Variation; Genetics, Population; Geography; Humans; India; Polymorphism, Single Nucleotide; Population Density; Population Dynamics; Sequence Analysis, DNA

Integrating common and rare genetic variation in diverse human populations. - Altshuler, David M; Gibbs, Richard A; Peltonen, Leena; Altshuler, David M; Gibbs, Richard A; Peltonen, Leena; Dermitzakis, Emmanouil; Schaffner, Stephen F; Yu, Fuli; Peltonen, Leena; Dermitzakis, Emmanouil; Bonnen, Penelope E; et al. (Nature, 2010)
Despite great progress in identifying genetic variants that influence human disease, most inherited risk remains unexplained. A more complete understanding requires genome-wide studies that fully examine less common alleles in populations with a wide range of ancestry. To inform the design and interpretation of such studies, we genotyped 1.6 million common single nucleotide polymorphisms (SNPs) in 1,184 reference individuals from 11 global populations, and sequenced ten 100-kilobase regions in 692 of these individuals. This integrated data set of common and rare alleles, called 'HapMap 3', includes both SNPs and copy number polymorphisms (CNPs). We characterized population-specific differences among low-frequency variants, measured the improvement in imputation accuracy afforded by the larger reference panel, especially in imputing SNPs with a minor allele frequency of <or=5%, and demonstrated the feasibility of imputing newly discovered CNPs and SNPs. This expanded public resource of genome variants in global populations supports deeper interrogation of genomic variation and its role in human disease, and serves as a step towards a high-resolution map of the landscape of human genetic variation.
Keywords: DNA Copy Number Variations; Genome, Human; Human Genome Project; Humans; Polymorphism, Single Nucleotide; Population Groups

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; White People

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin; White People

Whole exome capture in solution with 3 Gbp of data. - Bainbridge, Matthew N; Wang, Min; Burgess, Daniel L; Kovar, Christie; Rodesch, Matthew J; D'Ascenzo, Mark; Kitzman, Jacob; Wu, Yuan-Qing; Newsham, Irene; Richmond, Todd A; Jeddeloh, Jeffrey A; Muzny, Donna; et al. (Genome Biol, 2010)
We have developed a solution-based method for targeted DNA capture-sequencing that is directed to the complete human exome. Using this approach allows the discovery of greater than 95% of all expected heterozygous singe base variants, requires as little as 3 Gbp of raw sequence data and constitutes an effective tool for identifying rare coding alleles in large scale genomic studies.
Keywords: Base Pairing; Databases, Nucleic Acid; Exons; Gene Library; Haplotypes; Humans; Polymorphism, Single Nucleotide; Reproducibility of Results; Sequence Alignment; Sequence Analysis, DNA; Solutions

Whole-genome sequencing in a patient with Charcot-Marie-Tooth neuropathy. - Lupski, James R; Reid, Jeffrey G; Gonzaga-Jauregui, Claudia; Rio Deiros, David; Chen, David C Y; Nazareth, Lynne; Bainbridge, Matthew; Dinh, Huyen; Jing, Chyn; Wheeler, David A; McGuire, Amy L; Zhang, Feng; et al. (N Engl J Med, 2010)
BACKGROUND: Whole-genome sequencing may revolutionize medical diagnostics through rapid identification of alleles that cause disease. However, even in cases with simple patterns of inheritance and unambiguous diagnoses, the relationship between disease phenotypes and their corresponding genetic changes can be complicated. Comprehensive diagnostic assays must therefore identify all possible DNA changes in each haplotype and determine which are responsible for the underlying disorder. The high number of rare, heterogeneous mutations present in all humans and the paucity of known functional variants in more than 90% of annotated genes make this challenge particularly difficult. Thus, the identification of the molecular basis of a genetic disease by means of whole-genome sequencing has remained elusive. We therefore aimed to assess the usefulness of human whole-genome sequencing for genetic diagnosis in a patient with Charcot-Marie-Tooth disease. METHODS: We identified a family with a recessive form of Charcot-Marie-Tooth disease for which the genetic basis had not been identified. We sequenced the whole genome of the proband, identified all potential functional variants in genes likely to be related to the disease, and genotyped these variants in the affected family members. RESULTS: We identified and validated compound, heterozygous, causative alleles in SH3TC2 (the SH3 domain and tetratricopeptide repeats 2 gene), involving two mutations, in the proband and in family members affected by Charcot-Marie-Tooth disease. Separate subclinical phenotypes segregated independently with each of the two mutations; heterozygous mutations confer susceptibility to neuropathy, including the carpal tunnel syndrome. CONCLUSIONS: As shown in this study of a family with Charcot-Marie-Tooth disease, whole-genome sequencing can identify clinically relevant variants and provide diagnostic information to inform the care of patients.
Keywords: Adult; Aged; Aged, 80 and over; Charcot-Marie-Tooth Disease; Codon, Nonsense; Female; Genes, Recessive; Genetic Association Studies; Genome, Human; Genotype; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

The 8q24 cancer risk variant rs6983267 shows long-range interaction with MYC in colorectal cancer. - Pomerantz, Mark M; Ahmadiyeh, Nasim; Jia, Li; Herman, Paula; Verzi, Michael P; Doddapaneni, Harshavardhan; Beckwith, Christine A; Chan, Jennifer A; Hills, Adam; Davis, Matt; Yao, Keluo; Kehoe, Sarah M; et al. (Nat Genet, 2009)
An inherited variant on chromosome 8q24, rs6983267, is significantly associated with cancer pathogenesis. We present evidence that the region harboring this variant is a transcriptional enhancer, that the alleles of rs6983267 differentially bind transcription factor 7-like 2 (TCF7L2) and that the risk region physically interacts with the MYC proto-oncogene. These data provide strong support for a biological mechanism underlying this non-protein-coding risk variant.
Keywords: Alleles; Cell Line, Tumor; Chromosomes, Human, Pair 8; Colorectal Neoplasms; Enhancer Elements, Genetic; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Protein Binding; Proto-Oncogene Mas; Proto-Oncogene Proteins c-myc; TCF Transcription Factors; Transcription Factor 7-Like 2 Protein

Bos taurus genome assembly. - Liu, Yue; Qin, Xiang; Song, Xing-Zhi Henry; Jiang, Huaiyang; Shen, Yufeng; Durbin, K James; Lien, Sigbjørn; Kent, Matthew Peter; Sodeland, Marte; Ren, Yanru; Zhang, Lan; Sodergren, Erica; et al. (BMC Genomics, 2009)
BACKGROUND: We present here the assembly of the bovine genome. The assembly method combines the BAC plus WGS local assembly used for the rat and sea urchin with the whole genome shotgun (WGS) only assembly used for many other animal genomes including the rhesus macaque. RESULTS: The assembly process consisted of multiple phases: First, BACs were assembled with BAC generated sequence, then subsequently in combination with the individual overlapping WGS reads. Different assembly parameters were tested to separately optimize the performance for each BAC assembly of the BAC and WGS reads. In parallel, a second assembly was produced using only the WGS sequences and a global whole genome assembly method. The two assemblies were combined to create a more complete genome representation that retained the high quality BAC-based local assembly information, but with gaps between BACs filled in with the WGS-only assembly. Finally, the entire assembly was placed on chromosomes using the available map information.Over 90% of the assembly is now placed on chromosomes. The estimated genome size is 2.87 Gb which represents a high degree of completeness, with 95% of the available EST sequences found in assembled contigs. The quality of the assembly was evaluated by comparison to 73 finished BACs, where the draft assembly covers between 92.5 and 100% (average 98.5%) of the finished BACs. The assembly contigs and scaffolds align linearly to the finished BACs, suggesting that misassemblies are rare. Genotyping and genetic mapping of 17,482 SNPs revealed that more than 99.2% were correctly positioned within the Btau_4.0 assembly, confirming the accuracy of the assembly. CONCLUSION: The biological analysis of this bovine genome assembly is being published, and the sequence data is available to support future bovine research.
Keywords: Animals; Cattle; Chromosome Mapping; Chromosomes, Artificial, Bacterial; Genetic Markers; Genome; Genomics; Sequence Analysis, DNA

A common allele in RPGRIP1L is a modifier of retinal degeneration in ciliopathies. - Khanna, Hemant; Davis, Erica E; Murga-Zamalloa, Carlos A; Estrada-Cuzcano, Alejandro; Lopez, Irma; den Hollander, Anneke I; Zonneveld, Marijke N; Othman, Mohammad I; Waseem, Naushin; Chakarova, Christina F; Maubaret, Cecilia; Diaz-Font, Anna; et al. (Nat Genet, 2009)
Despite rapid advances in the identification of genes involved in disease, the predictive power of the genotype remains limited, in part owing to poorly understood effects of second-site modifiers. Here we demonstrate that a polymorphic coding variant of RPGRIP1L (retinitis pigmentosa GTPase regulator-interacting protein-1 like), a ciliary gene mutated in Meckel-Gruber (MKS) and Joubert (JBTS) syndromes, is associated with the development of retinal degeneration in individuals with ciliopathies caused by mutations in other genes. As part of our resequencing efforts of the ciliary proteome, we identified several putative loss-of-function RPGRIP1L mutations, including one common variant, A229T. Multiple genetic lines of evidence showed this allele to be associated with photoreceptor loss in ciliopathies. Moreover, we show that RPGRIP1L interacts biochemically with RPGR, loss of which causes retinal degeneration, and that the Thr229-encoded protein significantly compromises this interaction. Our data represent an example of modification of a discrete phenotype of syndromic disease and highlight the importance of a multifaceted approach for the discovery of modifier alleles of intermediate frequency and effect.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Ciliary Body; Europe; Genetic Variation; GTP Phosphohydrolases; Humans; Mutation; Polymorphism, Single Nucleotide; Retinal Degeneration; Retinitis Pigmentosa; RNA, Messenger; Uveitis; Zebrafish

The completion of the Mammalian Gene Collection (MGC). - Temple, Gary; Gerhard, Daniela S; Rasooly, Rebekah; Feingold, Elise A; Good, Peter J; Robinson, Cristen; Mandich, Allison; Derge, Jeffrey G; Lewis, Jeanne; Shoaf, Debonny; Collins, Francis S; Jang, Wonhee; et al. (Genome Res, 2009)
Since its start, the Mammalian Gene Collection (MGC) has sought to provide at least one full-protein-coding sequence cDNA clone for every human and mouse gene with a RefSeq transcript, and at least 6200 rat genes. The MGC cloning effort initially relied on random expressed sequence tag screening of cDNA libraries. Here, we summarize our recent progress using directed RT-PCR cloning and DNA synthesis. The MGC now contains clones with the entire protein-coding sequence for 92% of human and 89% of mouse genes with curated RefSeq (NM-accession) transcripts, and for 97% of human and 96% of mouse genes with curated RefSeq transcripts that have one or more PubMed publications, in addition to clones for more than 6300 rat genes. These high-quality MGC clones and their sequences are accessible without restriction to researchers worldwide.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA; DNA, Complementary; Gene Library; Genes; Humans; Mammals; Mice; National Institutes of Health (U.S.); Rats; Reverse Transcriptase Polymerase Chain Reaction; United States

Copy number variation of CCL3-like genes affects rate of progression to simian-AIDS in Rhesus Macaques (Macaca mulatta). - Degenhardt, Jeremiah D; de Candia, Paola; Chabot, Adrien; Schwartz, Stuart; Henderson, Les; Ling, Binhua; Hunter, Meredith; Jiang, Zhaoshi; Palermo, Robert E; Katze, Michael; Eichler, Evan E; Ventura, Mario; et al. (PLoS Genet, 2009)
Variation in genes underlying host immunity can lead to marked differences in susceptibility to HIV infection among humans. Despite heavy reliance on non-human primates as models for HIV/AIDS, little is known about which host factors are shared and which are unique to a given primate lineage. Here, we investigate whether copy number variation (CNV) at CCL3-like genes (CCL3L), a key genetic host factor for HIV/AIDS susceptibility and cell-mediated immune response in humans, is also a determinant of time until onset of simian-AIDS in rhesus macaques. Using a retrospective study of 57 rhesus macaques experimentally infected with SIVmac, we find that CCL3L CNV explains approximately 18% of the variance in time to simian-AIDS (p<0.001) with lower CCL3L copy number associating with more rapid disease course. We also find that CCL3L copy number varies significantly (p<10(-6)) among rhesus subpopulations, with Indian-origin macaques having, on average, half as many CCL3L gene copies as Chinese-origin macaques. Lastly, we confirm that CCL3L shows variable copy number in humans and chimpanzees and report on CCL3L CNV within and among three additional primate species. On the basis of our findings we suggest that (1) the difference in population level copy number may explain previously reported observations of longer post-infection survivorship of Chinese-origin rhesus macaques, (2) stratification by CCL3L copy number in rhesus SIV vaccine trials will increase power and reduce noise due to non-vaccine-related differences in survival, and (3) CCL3L CNV is an ancestral component of the primate immune response and, therefore, copy number variation has not been driven by HIV or SIV per se.
Keywords: Animals; Calibration; Chemokine CCL3; Disease Progression; DNA Primers; Gene Dosage; Genetics, Population; Immune System; Likelihood Functions; Macaca mulatta; Microsatellite Repeats; Models, Statistical; Proportional Hazards Models; Reverse Transcriptase Polymerase Chain Reaction; Simian Acquired Immunodeficiency Syndrome

Fine mapping of chromosome 6q23-25 region in familial lung cancer families reveals RGS17 as a likely candidate gene. - You, Ming; Wang, Daolong; Liu, Pengyuan; Vikis, Haris; James, Michael; Lu, Yan; Wang, Yian; Wang, Min; Chen, Qiong; Jia, Dongmei; Liu, Yan; Wen, Weidong; et al. (Clin Cancer Res, 2009)
PURPOSE: We have previously mapped a major susceptibility locus influencing familial lung cancer risk to chromosome 6q23-25. However, the causal gene at this locus remains undetermined. In this study, we further refined this locus to identify a single candidate gene, by fine mapping using microsatellite markers and association studies using high-density single nucleotide polymorphisms (SNP). EXPERIMENTAL DESIGN: Six multigenerational families with five or more affected members were chosen for fine-mapping the 6q linkage region using microsatellite markers. For association mapping, we genotyped 24 6q-linked cases and 72 unrelated noncancer controls from the Genetic Epidemiology of Lung Cancer Consortium resources using the Affymetrix 500K chipset. Significant associations were validated in two independent familial lung cancer populations: 226 familial lung cases and 313 controls from the Genetic Epidemiology of Lung Cancer Consortium, and 154 familial cases and 325 controls from Mayo Clinic. Each familial case was chosen from one high-risk lung cancer family that has three or more affected members. RESULTS: A region-wide scan across 6q23-25 found significant association between lung cancer susceptibility and three single nucleotide polymorphisms in the first intron of the RGS17 gene. This association was further confirmed in two independent familial lung cancer populations. By quantitative real-time PCR analysis of matched tumor and normal human tissues, we found that RGS17 transcript accumulation is highly and consistently increased in sporadic lung cancers. Human lung tumor cell proliferation and tumorigenesis in nude mice are inhibited upon knockdown of RGS17 levels. CONCLUSION: RGS17 is a major candidate for the familial lung cancer susceptibility locus on chromosome 6q23-25.
Keywords: Aged; Animals; Cell Line, Tumor; Chromosome Mapping; Chromosomes, Human, Pair 6; Female; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lung; Lung Neoplasms; Male; Mice; Mice, Nude; Microsatellite Repeats; Middle Aged; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; RGS Proteins; RNA, Small Interfering; Transplantation, Heterologous

The genome sequence of taurine cattle: a window to ruminant biology and evolution. - Elsik, Christine G; Tellam, Ross L; Worley, Kim C; Gibbs, Richard A; Muzny, Donna M; Weinstock, George M; Adelson, David L; Eichler, Evan E; Elnitski, Laura; Guigó, Roderic; Hamernik, Debora L; Kappes, Steve M; et al. (Science, 2009)
To understand the biology and evolution of ruminants, the cattle genome was sequenced to about sevenfold coverage. The cattle genome contains a minimum of 22,000 genes, with a core set of 14,345 orthologs shared among seven mammalian species of which 1217 are absent or undetected in noneutherian (marsupial or monotreme) genomes. Cattle-specific evolutionary breakpoint regions in chromosomes have a higher density of segmental duplications, enrichment of repetitive elements, and species-specific variations in genes associated with lactation and immune responsiveness. Genes involved in metabolism are generally highly conserved, although five metabolic genes are deleted or extensively diverged from their human orthologs. The cattle genome sequence thus provides a resource for understanding mammalian evolution and accelerating livestock genetic improvement for milk and meat production.
Keywords: Alternative Splicing; Animals; Animals, Domestic; Biological Evolution; Cattle; Evolution, Molecular; Female; Genetic Variation; Genome; Humans; Male; MicroRNAs; Molecular Sequence Data; Proteins; Sequence Analysis, DNA; Species Specificity; Synteny

Genome, transcriptome, and secretome analysis of wood decay fungus Postia placenta supports unique mechanisms of lignocellulose conversion. - Martinez, Diego; Challacombe, Jean; Morgenstern, Ingo; Hibbett, David; Schmoll, Monika; Kubicek, Christian P; Ferreira, Patricia; Ruiz-Duenas, Francisco J; Martinez, Angel T; Kersten, Phil; Hammel, Kenneth E; Vanden Wymelenberg, Amber; et al. (Proc Natl Acad Sci U S A, 2009)
Brown-rot fungi such as Postia placenta are common inhabitants of forest ecosystems and are also largely responsible for the destructive decay of wooden structures. Rapid depolymerization of cellulose is a distinguishing feature of brown-rot, but the biochemical mechanisms and underlying genetics are poorly understood. Systematic examination of the P. placenta genome, transcriptome, and secretome revealed unique extracellular enzyme systems, including an unusual repertoire of extracellular glycoside hydrolases. Genes encoding exocellobiohydrolases and cellulose-binding domains, typical of cellulolytic microbes, are absent in this efficient cellulose-degrading fungus. When P. placenta was grown in medium containing cellulose as sole carbon source, transcripts corresponding to many hemicellulases and to a single putative beta-1-4 endoglucanase were expressed at high levels relative to glucose-grown cultures. These transcript profiles were confirmed by direct identification of peptides by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Also up-regulated during growth on cellulose medium were putative iron reductases, quinone reductase, and structurally divergent oxidases potentially involved in extracellular generation of Fe(II) and H(2)O(2). These observations are consistent with a biodegradative role for Fenton chemistry in which Fe(II) and H(2)O(2) react to form hydroxyl radicals, highly reactive oxidants capable of depolymerizing cellulose. The P. placenta genome resources provide unparalleled opportunities for investigating such unusual mechanisms of cellulose conversion. More broadly, the genome offers insight into the diversification of lignocellulose degrading mechanisms in fungi. Comparisons with the closely related white-rot fungus Phanerochaete chrysosporium support an evolutionary shift from white-rot to brown-rot during which the capacity for efficient depolymerization of lignin was lost.
Keywords: Base Sequence; Biological Evolution; Cellulases; Enzymes; Gene Expression Profiling; Genome, Fungal; Glycoside Hydrolases; Lignin; Metabolic Networks and Pathways; Molecular Sequence Data; Oxidoreductases; Polyporales; Wood

Genome-wide survey of SNP variation uncovers the genetic structure of cattle breeds. - Gibbs, Richard A; Taylor, Jeremy F; Van Tassell, Curtis P; Barendse, William; Eversole, Kellye A; Gill, Clare A; Green, Ronnie D; Hamernik, Debora L; Kappes, Steven M; Lien, Sigbjørn; Matukumalli, Lakshmi K; McEwan, John C; et al. (Science, 2009)
The imprints of domestication and breed development on the genomes of livestock likely differ from those of companion animals. A deep draft sequence assembly of shotgun reads from a single Hereford female and comparative sequences sampled from six additional breeds were used to develop probes to interrogate 37,470 single-nucleotide polymorphisms (SNPs) in 497 cattle from 19 geographically and biologically diverse breeds. These data show that cattle have undergone a rapid recent decrease in effective population size from a very large ancestral population, possibly due to bottlenecks associated with domestication, selection, and breed formation. Domestication and artificial selection appear to have left detectable signatures of selection within the cattle genome, yet the current levels of diversity within breeds are at least as great as exists within humans.
Keywords: Animals; Breeding; Cattle; Female; Gene Frequency; Genetic Variation; Genome; Male; Molecular Sequence Data; Mutation; Polymorphism, Single Nucleotide; Population Density

Low frequency of MLL3 mutations in colorectal carcinoma. - Vakoc, Christopher R; Wen, Yu-Ye; Gibbs, Richard A; Johnstone, Cameron N; Rustgi, Anil K; Blobel, Gerd A (Cancer Genet Cytogenet, 2009)
Keywords: Carcinoma; Case-Control Studies; Colorectal Neoplasms; DNA-Binding Proteins; Gene Frequency; Genetic Testing; Humans; Mutation; Polymorphism, Single Nucleotide

Microarray analysis of somatostatin receptor 5-regulated gene expression profiles in murine pancreas. - Patel, Sanjeet G; Zhou, Guisheng; Liu, Shi-He; Li, Min; Jeong, Jae-Wook; DeMayo, Francesco J; Marie-Claude Gingras; Richard A Gibbs; Fisher, William E; Brunicardi, F Charles (World J Surg, 2009)
BACKGROUND: We previously demonstrated that somatostatin receptor type 5 (SSTR5) gene ablation results in alterations in insulin secretion and glucose metabolism, accompanied by morphologic alterations in the islets of Langerhans. The underlying mechanism(s) by which SSTR5 exerts its cellular functions remain(s) unknown. We hypothesized that SSTR5 mediates the inhibitory effect of somatostatin (SST) on insulin secretion and islet proliferation by regulating a specific set of pancreatic genes. METHODS: To identify SSTR5-regulated pancreatic genes, gene expression microarray analysis was performed on the whole pancreas of 1- and 3-month-old wild-type (WT) and SSTR5 knockout (SSTR5-/-) male mice. Real-time RT-PCR and immunofluorescence were performed to validate selected differentially expressed genes. RESULTS: A set of 143 probes were identified to be differentially expressed in the pancreas of 1-month-old SSTR5-/- mice, 72 of which were downregulated and 71 upregulated. At 3 months of age, SSTR5 gene ablation resulted in downregulation of a set of 30 probes and upregulation of a set of 37 probes. Among these differentially expressed genes, there were 15 and 5 genes that were upregulated and downregulated, respectively, in mice at both 1 and 3 months of age. Three genes, PAP/INGAP, ANG, and TDE1, were selected to be validated by real-time RT-PCR and immunofluorescence. CONCLUSIONS: A specific set of genes linked to a wide range of cellular functions such as islet proliferation, apoptosis, angiogenesis, and tumorigenesis were either upregulated or downregulated in SSTR5-deficient male mice compared with their expression in wild-type mice. Therefore, these genes are potential SSTR5-regulated genes during normal pancreatic development and functional maintenance.
Keywords: Animals; Apoptosis; Cell Proliferation; Down-Regulation; Fluorescent Antibody Technique; Gene Expression Profiling; Islets of Langerhans; Male; Mice; Mice, Knockout; Neoplasm Proteins; Neovascularization, Pathologic; Oligonucleotide Array Sequence Analysis; Pancreas; Pancreatitis-Associated Proteins; Proteins; Receptors, Cell Surface; Receptors, Somatostatin; Reverse Transcriptase Polymerase Chain Reaction; Ribonuclease, Pancreatic; Up-Regulation

Mutations in smooth muscle alpha-actin (ACTA2) cause coronary artery disease, stroke, and Moyamoya disease, along with thoracic aortic disease. - Guo, Dong-chuan; Papke, Christina L; Tran-Fadulu, Van; Regalado, Ellen S; Avidan, Nili; Johnson, Ralph Jay; Kim, Dong H; Pannu, Hariyadarshi; Willing, Marcia C; Sparks, Elizabeth; Pyeritz, Reed E; Singh, Michael N; et al. (Am J Hum Genet, 2009)
The vascular smooth muscle cell (SMC)-specific isoform of alpha-actin (ACTA2) is a major component of the contractile apparatus in SMCs located throughout the arterial system. Heterozygous ACTA2 mutations cause familial thoracic aortic aneurysms and dissections (TAAD), but only half of mutation carriers have aortic disease. Linkage analysis and association studies of individuals in 20 families with ACTA2 mutations indicate that mutation carriers can have a diversity of vascular diseases, including premature onset of coronary artery disease (CAD) and premature ischemic strokes (including Moyamoya disease [MMD]), as well as previously defined TAAD. Sequencing of DNA from patients with nonfamilial TAAD and from premature-onset CAD patients independently identified ACTA2 mutations in these patients and premature onset strokes in family members with ACTA2 mutations. Vascular pathology and analysis of explanted SMCs and myofibroblasts from patients harboring ACTA2 suggested that increased proliferation of SMCs contributed to occlusive diseases. These results indicate that heterozygous ACTA2 mutations predispose patients to a variety of diffuse and diverse vascular diseases, including TAAD, premature CAD, ischemic strokes, and MMD. These data demonstrate that diffuse vascular diseases resulting from either occluded or enlarged arteries can be caused by mutations in a single gene and have direct implications for clinical management and research on familial vascular diseases.
Keywords: Actins; Adolescent; Adult; Aortic Aneurysm, Thoracic; Aortic Dissection; Cell Proliferation; Cells, Cultured; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Models, Molecular; Moyamoya Disease; Mutation; Myocytes, Smooth Muscle; Protein Isoforms; Stroke; Young Adult

Prepublication data sharing. - Birney, Ewan; Hudson, Thomas J; Green, Eric D; Gunter, Chris; Eddy, Sean; Rogers, Jane; Harris, Jennifer R; Ehrlich, S Dusko; Apweiler, Rolf; Austin, Christopher P; Berglund, Lisa; Bobrow, Martin; et al. (Nature, 2009)
Rapid release of prepublication data has served the field of genomics well. Attendees at a workshop in Toronto recommend extending the practice to other biological data sets.
Keywords: Access to Information; Cooperative Behavior; Guidelines as Topic; Human Genome Project; Humans; Ontario; Publishing; Research; Research Personnel

Replication of long-bone length QTL in the F9-F10 LG,SM advanced intercross. - Norgard, Elizabeth A; Jarvis, Joseph P; Roseman, Charles C; Maxwell, Taylor J; Kenney-Hunt, Jane P; Samocha, Kaitlin E; Pletscher, L Susan; Wang, Bing; Fawcett, Gloria L; Leatherwood, Christopher J; Wolf, Jason B; Cheverud, James M (Mamm Genome, 2009)
Quantitative trait locus (QTL) mapping techniques are frequently used to identify genomic regions associated with variation in phenotypes of interest. However, the F(2) intercross and congenic strain populations usually employed have limited genetic resolution resulting in relatively large confidence intervals that greatly inhibit functional confirmation of statistical results. Here we use the increased resolution of the combined F(9) and F(10) generations (n = 1455) of the LG,SM advanced intercross to fine-map previously identified QTL associated with the lengths of the humerus, ulna, femur, and tibia. We detected 81 QTL affecting long-bone lengths. Of these, 49 were previously identified in the combined F(2)-F(3) population of this intercross, while 32 represent novel contributors to trait variance. Pleiotropy analysis suggests that most QTL affect three to four long bones or serially homologous limb segments. We also identified 72 epistatic interactions involving 38 QTL and 88 novel regions. This analysis shows that using later generations of an advanced intercross greatly facilitates fine-mapping of confidence intervals, resolving three F(2)-F(3) QTL into multiple linked loci and narrowing confidence intervals of other loci, as well as allowing identification of additional QTL. Further characterization of the biological bases of these QTL will help provide a better understanding of the genetics of small variations in long-bone length.
Keywords: Animals; Bone and Bones; Crosses, Genetic; DNA Replication; Female; Hybridization, Genetic; Male; Mice; Organ Size; Quantitative Trait Loci

Resources for genetic management and genomics research on non-human primates at the National Primate Research Centers (NPRCs). - Kanthaswamy, S; Capitanio, J P; Dubay, C J; Ferguson, B; Folks, T; Ha, J C; Hotchkiss, C E; Johnson, Z P; Katze, M G; Kean, L S; Kubisch, H Michael; Lank, S; et al. (J Med Primatol, 2009)
The National Primate Research Centers (NPRCs) established Working Groups (WGs) for developing resources and mechanisms to facilitate collaborations among non-human primate (NHP) researchers. Here we report the progress of the Genome Banking and the Genetics and Genomics WGs in developing resources to advance the exchange, analysis and comparison of NHP genetic and genomic data across the NPRCs. The Genome Banking WG has established a National NHP DNA bank comprising 1250 DNA samples from unrelated animals and family trios from the 10 NHP species housed within the NPRC system. The Genetics and Genomics WG is developing SNP arrays that will provide a uniform, highly informative, efficient and low-cost method for rhesus and long-tailed macaque genotyping across the eight NPRCs. This WG is also establishing a Biomedical Informatics Research Network-based portal for shared bioinformatics resources including vital statistics, genotype and population data and information on the National NHP DNA bank.
Keywords: Animals; Genomics; National Institutes of Health (U.S.); Primates; United States

Genetic architecture of adiposity and organ weight using combined generation QTL analysis. - Fawcett, Gloria L; Roseman, Charles C; Jarvis, Joseph P; Wang, Bing; Wolf, Jason B; Cheverud, James M (Obesity (Silver Spring), 2008)
We present here a detailed study of the genetic contributions to adult body size and adiposity in the LG,SM advanced intercross line (AIL), an obesity model. This study represents a first step in fine-mapping obesity quantitative trait loci (QTLs) in an AIL. QTLs for adiposity in this model were previously isolated to chromosomes 1, 6, 7, 8, 9, 12, 13, and 18. This study focuses on heritable contributions and the genetic architecture of fatpad and organ weights. We analyzed both the F(2) and F(3) generations of the LG,SM AIL population single-nucleotide polymorphism (SNP) genotyped with a marker density of approximately 4 cM. We replicate 88% of the previously identified obesity QTLs and identify 13 new obesity QTLs. Nearly half of the single-trait QTLs were sex-specific. Several broad QTL regions were resolved into multiple, narrower peaks. The 113 single-trait QTLs for organs and body weight clustered into 27 pleiotropic loci. A large number of epistatic interactions are described which begin to elucidate potential interacting molecular networks. We present a relatively rapid means to obtain fine-mapping details from AILs using dense marker maps and consecutive generations. Analysis of the complex genetic architecture underlying fatpad and organ weights in this model may eventually help to elucidate not only heritable contributions to obesity but also common gene sets for obesity and its comorbidities.
Keywords: Adipose Tissue; Adiposity; Animals; Disease Models, Animal; Epistasis, Genetic; Female; Kidney; Liver; Male; Mice; Mice, Inbred Strains; Myocardium; Obesity; Organ Size; Quantitative Trait Loci; Sex Characteristics; Spleen

The genome of the model beetle and pest Tribolium castaneum. - Stephen Richards; Richard A Gibbs; Weinstock, George M; Brown, Susan J; Denell, Robin; Beeman, Richard W; Richard A Gibbs; Beeman, Richard W; Brown, Susan J; Bucher, Gregor; Friedrich, Markus; Grimmelikhuijzen, Cornelis J P; et al. (Nature, 2008)
Tribolium castaneum is a member of the most species-rich eukaryotic order, a powerful model organism for the study of generalized insect development, and an important pest of stored agricultural products. We describe its genome sequence here. This omnivorous beetle has evolved the ability to interact with a diverse chemical environment, as shown by large expansions in odorant and gustatory receptors, as well as P450 and other detoxification enzymes. Development in Tribolium is more representative of other insects than is Drosophila, a fact reflected in gene content and function. For example, Tribolium has retained more ancestral genes involved in cell-cell communication than Drosophila, some being expressed in the growth zone crucial for axial elongation in short-germ development. Systemic RNA interference in T. castaneum functions differently from that in Caenorhabditis elegans, but nevertheless offers similar power for the elucidation of gene function and identification of targets for selective insect control.
Keywords: Animals; Base Composition; Body Patterning; Cytochrome P-450 Enzyme System; DNA Transposable Elements; Genes, Insect; Genome, Insect; Growth and Development; Humans; Insecticides; Neurotransmitter Agents; Oogenesis; Phylogeny; Proteome; Receptors, G-Protein-Coupled; Receptors, Odorant; Repetitive Sequences, Nucleic Acid; RNA Interference; Taste; Telomere; Tribolium; Vision, Ocular

Large scale variation in Enterococcus faecalis illustrated by the genome analysis of strain OG1RF. - Bourgogne, Agathe; Garsin, Danielle A; Qin, Xiang; Singh, Kavindra V; Sillanpaa, Jouko; Yerrapragada, Shailaja; Ding, Yan; Dugan-Rocha, Shannon; Buhay, Christian; Shen, Hua; Chen, Guan; Williams, Gabrielle; et al. (Genome Biol, 2008)
BACKGROUND: Enterococcus faecalis has emerged as a major hospital pathogen. To explore its diversity, we sequenced E. faecalis strain OG1RF, which is commonly used for molecular manipulation and virulence studies. RESULTS: The 2,739,625 base pair chromosome of OG1RF was found to contain approximately 232 kilobases unique to this strain compared to V583, the only publicly available sequenced strain. Almost no mobile genetic elements were found in OG1RF. The 64 areas of divergence were classified into three categories. First, OG1RF carries 39 unique regions, including 2 CRISPR loci and a new WxL locus. Second, we found nine replacements where a sequence specific to V583 was substituted by a sequence specific to OG1RF. For example, the iol operon of OG1RF replaces a possible prophage and the vanB transposon in V583. Finally, we found 16 regions that were present in V583 but missing from OG1RF, including the proposed pathogenicity island, several probable prophages, and the cpsCDEFGHIJK capsular polysaccharide operon. OG1RF was more rapidly but less frequently lethal than V583 in the mouse peritonitis model and considerably outcompeted V583 in a murine model of urinary tract infections. CONCLUSION: E. faecalis OG1RF carries a number of unique loci compared to V583, but the almost complete lack of mobile genetic elements demonstrates that this is not a defining feature of the species. Additionally, OG1RF's effects in experimental models suggest that mediators of virulence may be diverse between different E. faecalis strains and that virulence is not dependent on the presence of mobile genetic elements.
Keywords: Animals; Anti-Bacterial Agents; Bacterial Proteins; Biofilms; DNA, Bacterial; Drug Resistance, Bacterial; Enterococcus faecalis; Fusidic Acid; Genetic Variation; Genome, Bacterial; Genomics; Interspersed Repetitive Sequences; Membrane Proteins; Mice; Operon; Repetitive Sequences, Nucleic Acid; Rifampin; Sequence Homology, Nucleic Acid

Pleiotropic patterns of quantitative trait loci for 70 murine skeletal traits. - Kenney-Hunt, Jane P; Wang, Bing; Norgard, Elizabeth A; Fawcett, Gloria; Falk, Doug; Pletscher, L Susan; Jarvis, Joseph P; Roseman, Charles; Wolf, Jason; Cheverud, James M (Genetics, 2008)
Quantitative trait locus (QTL) studies of a skeletal trait or a few related skeletal components are becoming commonplace, but as yet there has been no investigation of pleiotropic patterns throughout the skeleton. We present a comprehensive survey of pleiotropic patterns affecting mouse skeletal morphology in an intercross of LG/J and SM/J inbred strains (N = 1040), using QTL analysis on 70 skeletal traits. We identify 798 single-trait QTL, coalescing to 105 loci that affect on average 7-8 traits each. The number of traits affected per locus ranges from only 1 trait to 30 traits. Individual traits average 11 QTL each, ranging from 4 to 20. Skeletal traits are affected by many, small-effect loci. Significant additive genotypic values average 0.23 standard deviation (SD) units. Fifty percent of loci show codominance with heterozygotes having intermediate phenotypic values. When dominance does occur, the LG/J allele tends to be dominant to the SM/J allele (30% vs. 8%). Over- and underdominance are relatively rare (12%). Approximately one-fifth of QTL are sex specific, including many for pelvic traits. Evaluating the pleiotropic relationships of skeletal traits is important in understanding the role of genetic variation in the growth and development of the skeleton.
Keywords: Animals; Bone and Bones; Chromosomes, Mammalian; Mice; Quantitative Trait Loci; Quantitative Trait, Heritable

Progress and prospects in rat genetics: a community view. - Aitman, Timothy J; Critser, John K; Cuppen, Edwin; Dominiczak, Anna; Fernandez-Suarez, Xose M; Flint, Jonathan; Gauguier, Dominique; Geurts, Aron M; Gould, Michael; Harris, Peter C; Holmdahl, Rikard; Hübner, Norbert; et al. (Nat Genet, 2008)
The rat is an important system for modeling human disease. Four years ago, the rich 150-year history of rat research was transformed by the sequencing of the rat genome, ushering in an era of exceptional opportunity for identifying genes and pathways underlying disease phenotypes. Genome-wide association studies in human populations have recently provided a direct approach for finding robust genetic associations in common diseases, but identifying the precise genes and their mechanisms of action remains problematic. In the context of significant progress in rat genomic resources over the past decade, we outline achievements in rat gene discovery to date, show how these findings have been translated to human disease, and document an increasing pace of discovery of new disease genes, pathways and mechanisms. Finally, we present a set of principles that justify continuing and strengthening genetic studies in the rat model, and further development of genomic infrastructure for rat research.
Keywords: Animals; Animals, Genetically Modified; Chromosome Mapping; Disease Models, Animal; Gene Targeting; Genetic Diseases, Inborn; Genome; Genomics; Humans; Rats

Somatic mutations affect key pathways in lung adenocarcinoma. - Ding, Li; Getz, Gad; Wheeler, David A; Mardis, Elaine R; McLellan, Michael D; Cibulskis, Kristian; Sougnez, Carrie; Greulich, Heidi; Muzny, Donna M; Morgan, Margaret B; Fulton, Lucinda; Fulton, Robert S; et al. (Nature, 2008)
Determining the genetic basis of cancer requires comprehensive analyses of large collections of histopathologically well-classified primary tumours. Here we report the results of a collaborative study to discover somatic mutations in 188 human lung adenocarcinomas. DNA sequencing of 623 genes with known or potential relationships to cancer revealed more than 1,000 somatic mutations across the samples. Our analysis identified 26 genes that are mutated at significantly high frequencies and thus are probably involved in carcinogenesis. The frequently mutated genes include tyrosine kinases, among them the EGFR homologue ERBB4; multiple ephrin receptor genes, notably EPHA3; vascular endothelial growth factor receptor KDR; and NTRK genes. These data provide evidence of somatic mutations in primary lung adenocarcinoma for several tumour suppressor genes involved in other cancers--including NF1, APC, RB1 and ATM--and for sequence changes in PTPRD as well as the frequently deleted gene LRP1B. The observed mutational profiles correlate with clinical features, smoking status and DNA repair defects. These results are reinforced by data integration including single nucleotide polymorphism array and gene expression array. Our findings shed further light on several important signalling pathways involved in lung adenocarcinoma, and suggest new molecular targets for treatment.
Keywords: Adenocarcinoma, Bronchiolo-Alveolar; Female; Gene Dosage; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Lung Neoplasms; Male; Mutation; Proto-Oncogenes

Understanding the development of human bladder cancer by using a whole-organ genomic mapping strategy. - Majewski, Tadeusz; Lee, Sangkyou; Jeong, Joon; Yoon, Dong-Sup; Kram, Andrzej; Kim, Mi-Sook; Tuziak, Tomasz; Bondaruk, Jolanta; Lee, Sooyong; Park, Weon-Seo; Tang, Kuang S; Chung, Woonbok; et al. (Lab Invest, 2008)
The search for the genomic sequences involved in human cancers can be greatly facilitated by maps of genomic imbalances identifying the involved chromosomal regions, particularly those that participate in the development of occult preneoplastic conditions that progress to clinically aggressive invasive cancer. The integration of such regions with human genome sequence variation may provide valuable clues about their overall structure and gene content. By extension, such knowledge may help us understand the underlying genetic components involved in the initiation and progression of these cancers. We describe the development of a genome-wide map of human bladder cancer that tracks its progression from in situ precursor conditions to invasive disease. Testing for allelic losses using a genome-wide panel of 787 microsatellite markers was performed on multiple DNA samples, extracted from the entire mucosal surface of the bladder and corresponding to normal urothelium, in situ preneoplastic lesions, and invasive carcinoma. Using this approach, we matched the clonal allelic losses in distinct chromosomal regions to specific phases of bladder neoplasia and produced a detailed genetic map of bladder cancer development. These analyses revealed three major waves of genetic changes associated with growth advantages of successive clones and reflecting a stepwise conversion of normal urothelial cells into cancer cells. The genetic changes map to six regions at 3q22-q24, 5q22-q31, 9q21-q22, 10q26, 13q14, and 17p13, which may represent critical hits driving the development of bladder cancer. Finally, we performed high-resolution mapping using single nucleotide polymorphism markers within one region on chromosome 13q14, containing the model tumor suppressor gene RB1, and defined a minimal deleted region associated with clonal expansion of in situ neoplasia. These analyses provided new insights on the involvement of several non-coding sequences mapping to the region and identified novel target genes, termed forerunner (FR) genes, involved in early phases of cancer development.
Keywords: Aged; Carcinoma, Transitional Cell; Chromosome Mapping; Chromosomes, Human, Pair 13; Humans; Male; Microsatellite Repeats; Middle Aged; Polymorphism, Single Nucleotide; Retinoblastoma Protein; Urinary Bladder; Urinary Bladder Neoplasms; Urothelium

What everybody should know about the rat genome and its online resources. - Twigger, Simon N; Pruitt, Kim D; Fernandez-Suarez, Xose M; Karolchik, Donna; Worley, Kim C; Maglott, Donna R; Brown, Garth; Weinstock, George; Gibbs, Richard A; Kent, Jim; Birney, Ewan; Jacob, Howard J (Nat Genet, 2008)
It has been four years since the original publication of the draft sequence of the rat genome. Five groups are now working together to assemble, annotate and release an updated version of the rat genome. As the prevailing model for physiology, complex disease and pharmacological studies, there is an acute need for the rat's genomic resources to keep pace with the rat's prominence in the laboratory. In this commentary, we describe the current status of the rat genome sequence and the plans for its impending 'upgrade'. We then cover the key online resources providing access to the rat genome, including the new SNP views at Ensembl, the RefSeq and Genes databases at the US National Center for Biotechnology Information, Genome Browser at the University of California Santa Cruz and the disease portals for cardiovascular disease and obesity at the Rat Genome Database.
Keywords: Animals; Computational Biology; Databases, Genetic; Disease Models, Animal; Genetic Diseases, Inborn; Genetic Variation; Genome; Genomics; Haplotypes; Humans; Internet; Polymorphism, Single Nucleotide; Rats; Rats, Mutant Strains; Sequence Analysis, DNA

Analyses of deep mammalian sequence alignments and constraint predictions for 1% of the human genome. - Margulies, Elliott H; Cooper, Gregory M; Asimenos, George; Thomas, Daryl J; Dewey, Colin N; Siepel, Adam; Birney, Ewan; Keefe, Damian; Schwartz, Ariel S; Hou, Minmei; Taylor, James; Nikolaev, Sergey; et al. (Genome Res, 2007)
A key component of the ongoing ENCODE project involves rigorous comparative sequence analyses for the initially targeted 1% of the human genome. Here, we present orthologous sequence generation, alignment, and evolutionary constraint analyses of 23 mammalian species for all ENCODE targets. Alignments were generated using four different methods; comparisons of these methods reveal large-scale consistency but substantial differences in terms of small genomic rearrangements, sensitivity (sequence coverage), and specificity (alignment accuracy). We describe the quantitative and qualitative trade-offs concomitant with alignment method choice and the levels of technical error that need to be accounted for in applications that require multisequence alignments. Using the generated alignments, we identified constrained regions using three different methods. While the different constraint-detecting methods are in general agreement, there are important discrepancies relating to both the underlying alignments and the specific algorithms. However, by integrating the results across the alignments and constraint-detecting methods, we produced constraint annotations that were found to be robust based on multiple independent measures. Analyses of these annotations illustrate that most classes of experimentally annotated functional elements are enriched for constrained sequences; however, large portions of each class (with the exception of protein-coding sequences) do not overlap constrained regions. The latter elements might not be under primary sequence constraint, might not be constrained across all mammals, or might have expendable molecular functions. Conversely, 40% of the constrained sequences do not overlap any of the functional elements that have been experimentally identified. Together, these findings demonstrate and quantify how many genomic functional elements await basic molecular characterization.
Keywords: Animals; Evolution, Molecular; Genome, Human; Human Genome Project; Humans; Mammals; Open Reading Frames; Phylogeny; Sequence Alignment

Characterizing the cancer genome in lung adenocarcinoma. - Weir, Barbara A; Woo, Michele S; Getz, Gad; Perner, Sven; Ding, Li; Beroukhim, Rameen; Lin, William M; Province, Michael A; Kraja, Aldi; Johnson, Laura A; Shah, Kinjal; Sato, Mitsuo; et al. (Nature, 2007)
Somatic alterations in cellular DNA underlie almost all human cancers. The prospect of targeted therapies and the development of high-resolution, genome-wide approaches are now spurring systematic efforts to characterize cancer genomes. Here we report a large-scale project to characterize copy-number alterations in primary lung adenocarcinomas. By analysis of a large collection of tumours (n = 371) using dense single nucleotide polymorphism arrays, we identify a total of 57 significantly recurrent events. We find that 26 of 39 autosomal chromosome arms show consistent large-scale copy-number gain or loss, of which only a handful have been linked to a specific gene. We also identify 31 recurrent focal events, including 24 amplifications and 7 homozygous deletions. Only six of these focal events are currently associated with known mutations in lung carcinomas. The most common event, amplification of chromosome 14q13.3, is found in approximately 12% of samples. On the basis of genomic and functional analyses, we identify NKX2-1 (NK2 homeobox 1, also called TITF1), which lies in the minimal 14q13.3 amplification interval and encodes a lineage-specific transcription factor, as a novel candidate proto-oncogene involved in a significant fraction of lung adenocarcinomas. More generally, our results indicate that many of the genes that are involved in lung adenocarcinoma remain to be discovered.
Keywords: Adenocarcinoma; Cell Line, Tumor; Chromosome Deletion; Chromosomes, Human, Pair 14; Gene Amplification; Genome, Human; Genomics; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Loss of Heterozygosity; Lung Neoplasms; Neoplasms; Nuclear Proteins; Polymorphism, Single Nucleotide; Proto-Oncogene Mas; RNA Interference; Thyroid Nuclear Factor 1; Transcription Factors

EGFR-T790M is a rare lung cancer susceptibility allele with enhanced kinase activity. - Vikis, Haris; Sato, Mitsuo; James, Michael; Wang, Daolong; Wang, Yian; Wang, Min; Jia, Dongmei; Liu, Yan; Bailey-Wilson, Joan E; Amos, Christopher I; Pinney, Susan M; Petersen, Gloria M; et al. (Cancer Res, 2007)
The use of tyrosine kinase inhibitors (TKI) has yielded great success in treatment of lung adenocarcinomas. However, patients who develop resistance to TKI treatment often acquire a somatic resistance mutation (T790M) located in the catalytic cleft of the epidermal growth factor receptor (EGFR) enzyme. Recently, a report describing EGFR-T790M as a germ-line mutation suggested that this mutation may be associated with inherited susceptibility to lung cancer. Contrary to previous reports, our analysis indicates that the T790M mutation confers increased Y992 and Y1068 phosphorylation levels. In a human bronchial epithelial cell line, overexpression of EGFR-T790M displayed a growth advantage over wild-type (WT) EGFR. We also screened 237 lung cancer family probands, in addition to 45 bronchoalveolar tumors, and found that none of them contained the EGFR-T790M mutation. Our observations show that EGFR-T790M provides a proliferative advantage with respect to WT EGFR and suggest that the enhanced kinase activity of this mutant is the basis for rare cases of inherited susceptibility to lung cancer.
Keywords: Alleles; Animals; Chlorocebus aethiops; COS Cells; DNA, Neoplasm; ErbB Receptors; Genes, erbB-1; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Lung Neoplasms; Pedigree; Phosphorylation

Evolutionary and biomedical insights from the rhesus macaque genome. - Richard A Gibbs; Jeffrey Rogers; Katze, Michael G; Bumgarner, Roger; Weinstock, George M; Mardis, Elaine R; Remington, Karin A; Strausberg, Robert L; Venter, J Craig; Wilson, Richard K; Batzer, Mark A; Bustamante, Carlos D; et al. (Science, 2007)
The rhesus macaque (Macaca mulatta) is an abundant primate species that diverged from the ancestors of Homo sapiens about 25 million years ago. Because they are genetically and physiologically similar to humans, rhesus monkeys are the most widely used nonhuman primate in basic and applied biomedical research. We determined the genome sequence of an Indian-origin Macaca mulatta female and compared the data with chimpanzees and humans to reveal the structure of ancestral primate genomes and to identify evidence for positive selection and lineage-specific expansions and contractions of gene families. A comparison of sequences from individual animals was used to investigate their underlying genetic diversity. The complete description of the macaque genome blueprint enhances the utility of this animal model for biomedical research and improves our understanding of the basic biology of the species.
Keywords: Animals; Biomedical Research; Evolution, Molecular; Female; Gene Duplication; Gene Rearrangement; Genetic Diseases, Inborn; Genetic Variation; Genome; Humans; Macaca mulatta; Male; Multigene Family; Mutation; Pan troglodytes; Sequence Analysis, DNA; Species Specificity

Family-based association study of matrix metalloproteinase-3 and -9 haplotypes with susceptibility to ischemic white matter injury. - Fornage, Myriam; Mosley, Thomas H; Jack, Clifford R; de Andrade, Mariza; Kardia, Sharon L R; Eric Boerwinkle; Turner, Stephen T (Hum Genet, 2007)
Susceptibility to ischemic damage to the subcortical white matter of the brain has a strong genetic basis. Dysregulation of matrix metalloproteinases (MMPs) contributes to loss of cerebrovascular integrity and white matter injury. We investigated whether sequence variation in the genes encoding MMP3 and MMP9 is associated with variation in leukoaraiosis volume, determined by magnetic resonance imaging, in non-Hispanic whites and African-Americans using family-based association tests. Seven hundred and fifty-six white and 671 African-American individuals from sibships ascertained through two or more siblings with hypertension were genotyped for 7 and 8 haplotype-tagging polymorphisms in the MMP3 and MMP9 genes, respectively. MMP3 sequence variation was significantly associated with variation in leukoaraiosis volume in Whites. Two common haplotypes with opposing relationships to leukoaraiosis volume were identified. MMP9 sequence variation was also significantly associated with variation in leukoaraiosis volume in both African-Americans and Whites. Different haplotypes contributed to these associations in the two racial groups. These findings add to the growing body of evidence from animal models and human clinical studies suggesting a role of MMPs in ischemic white matter injury. They provide the basis for further investigation of the role of these genes in susceptibility and/or progression to clinical disease.
Keywords: Aged; Base Sequence; Black or African American; Brain Ischemia; Family Health; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Leukoaraiosis; Linkage Disequilibrium; Male; Matrix Metalloproteinase 3; Matrix Metalloproteinase 9; Middle Aged; Polymorphism, Single Nucleotide; Siblings; White People

Forerunner genes contiguous to RB1 contribute to the development of in situ neoplasia. - Lee, Sangkyou; Jeong, Joon; Majewski, Tadeusz; Scherer, Steven E; Kim, Mi-Sook; Tuziak, Tomasz; Tang, Kuang S; Baggerly, Keith; Grossman, Herbert Barton; Zhou, Jain-Hua; Shen, Lanlan; Bondaruk, Jolanta; et al. (Proc Natl Acad Sci U S A, 2007)
We used human bladder cancer as a model system and the whole-organ histologic and genetic mapping strategy to identify clonal genetic hits associated with growth advantage, tracking the evolution of bladder cancer from intraurothelial precursor lesions. Six putative chromosomal regions critical for clonal expansion of intraurothelial neoplasia and development of bladder cancer were identified by using this approach. Focusing on one of the regions, which includes the model tumor suppressor RB1, we performed allelotyping of single-nucleotide polymorphic sites and identified a 1.34-Mb segment around RB1 characterized by a loss of polymorphism associated with the initial expansion of in situ neoplasia. This segment contains several positional candidate genes referred to by us as forerunner genes that may contribute to such expansion. We subsequently concentrated our efforts on the two neighbor genes flanking RB1, namely ITM2B and CHC1L, as well as P2RY5, which is located inside RB1. Here, we report that ITM2B and P2RY5 modulated cell survival and were silenced by methylation or point mutations, respectively, and thus by functional loss may contribute to the growth advantage of neoplasia. We also show that homozygous inactivation of P2RY5 was antecedent to the loss of RB1 during tumor development, and that nucleotide substitutions in P2RY5 represent a cancer predisposing factor.
Keywords: Base Sequence; Gene Expression Regulation, Neoplastic; Humans; Loss of Heterozygosity; Models, Molecular; Polymorphism, Genetic; Protein Structure, Tertiary; Receptors, Purinergic P2; Retinoblastoma Protein; Urinary Bladder Neoplasms

Genome sequence of Fusobacterium nucleatum subspecies polymorphum - a genetically tractable fusobacterium. - Karpathy, Sandor E; Qin, Xiang; Gioia, Jason; Jiang, Huaiyang; Liu, Yamei; Petrosino, Joseph F; Yerrapragada, Shailaja; Fox, George E; Haake, Susan Kinder; Weinstock, George M; Highlander, Sarah K (PLoS One, 2007)
Fusobacterium nucleatum is a prominent member of the oral microbiota and is a common cause of human infection. F. nucleatum includes five subspecies: polymorphum, nucleatum, vincentii, fusiforme, and animalis. F. nucleatum subsp. polymorphum ATCC 10953 has been well characterized phenotypically and, in contrast to previously sequenced strains, is amenable to gene transfer. We sequenced and annotated the 2,429,698 bp genome of F. nucleatum subsp. polymorphum ATCC 10953. Plasmid pFN3 from the strain was also sequenced and analyzed. When compared to the other two available fusobacterial genomes (F. nucleatum subsp. nucleatum, and F. nucleatum subsp. vincentii) 627 open reading frames unique to F. nucleatum subsp. polymorphum ATCC 10953 were identified. A large percentage of these mapped within one of 28 regions or islands containing five or more genes. Seventeen percent of the clustered proteins that demonstrated similarity were most similar to proteins from the clostridia, with others being most similar to proteins from other gram-positive organisms such as Bacillus and Streptococcus. A ten kilobase region homologous to the Salmonella typhimurium propanediol utilization locus was identified, as was a prophage and integrated conjugal plasmid. The genome contains five composite ribozyme/transposons, similar to the CdISt IStrons described in Clostridium difficile. IStrons are not present in the other fusobacterial genomes. These findings indicate that F. nucleatum subsp. polymorphum is proficient at horizontal gene transfer and that exchange with the Firmicutes, particularly the Clostridia, is common.
Keywords: Amino Acids; Base Sequence; Clostridium; DNA, Bacterial; Evolution, Molecular; Fusobacterium nucleatum; Gene Transfer Techniques; Genome, Bacterial; Humans; Infections; Introns; Multigene Family; Open Reading Frames; Peptides; Plasmids; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid

Genome-wide detection and characterization of positive selection in human populations. - Sabeti, Pardis C; Varilly, Patrick; Fry, Ben; Lohmueller, Jason; Hostetter, Elizabeth; Cotsapas, Chris; Xie, Xiaohui; Byrne, Elizabeth H; McCarroll, Steven A; Gaudet, Rachelle; Schaffner, Stephen F; Lander, Eric S; et al. (Nature, 2007)
With the advent of dense maps of human genetic variation, it is now possible to detect positive natural selection across the human genome. Here we report an analysis of over 3 million polymorphisms from the International HapMap Project Phase 2 (HapMap2). We used 'long-range haplotype' methods, which were developed to identify alleles segregating in a population that have undergone recent selection, and we also developed new methods that are based on cross-population comparisons to discover alleles that have swept to near-fixation within a population. The analysis reveals more than 300 strong candidate regions. Focusing on the strongest 22 regions, we develop a heuristic for scrutinizing these regions to identify candidate targets of selection. In a complementary analysis, we identify 26 non-synonymous, coding, single nucleotide polymorphisms showing regional evidence of positive selection. Examination of these candidates highlights three cases in which two genes in a common biological process have apparently undergone positive selection in the same population:LARGE and DMD, both related to infection by the Lassa virus, in West Africa;SLC24A5 and SLC45A2, both involved in skin pigmentation, in Europe; and EDAR and EDA2R, both involved in development of hair follicles, in Asia.
Keywords: Antiporters; Edar Receptor; Gene Frequency; Genetics, Population; Genome, Human; Geography; Haplotypes; Humans; Models, Molecular; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Selection, Genetic

Identification and analysis of functional elements in 1% of the human genome by the ENCODE pilot project. - Birney, Ewan; Stamatoyannopoulos, John A; Dutta, Anindya; Guigó, Roderic; Gingeras, Thomas R; Margulies, Elliott H; Weng, Zhiping; Snyder, Michael; Dermitzakis, Emmanouil T; Thurman, Robert E; Kuehn, Michael S; Taylor, Christopher M; et al. (Nature, 2007)
We report the generation and analysis of functional data from multiple, diverse experiments performed on a targeted 1% of the human genome as part of the pilot phase of the ENCODE Project. These data have been further integrated and augmented by a number of evolutionary and computational analyses. Together, our results advance the collective knowledge about human genome function in several major areas. First, our studies provide convincing evidence that the genome is pervasively transcribed, such that the majority of its bases can be found in primary transcripts, including non-protein-coding transcripts, and those that extensively overlap one another. Second, systematic examination of transcriptional regulation has yielded new understanding about transcription start sites, including their relationship to specific regulatory sequences and features of chromatin accessibility and histone modification. Third, a more sophisticated view of chromatin structure has emerged, including its inter-relationship with DNA replication and transcriptional regulation. Finally, integration of these new sources of information, in particular with respect to mammalian evolution based on inter- and intra-species sequence comparisons, has yielded new mechanistic and evolutionary insights concerning the functional landscape of the human genome. Together, these studies are defining a path for pursuit of a more comprehensive characterization of human genome function.
Keywords: Chromatin; Chromatin Immunoprecipitation; Conserved Sequence; DNA Replication; Evolution, Molecular; Exons; Genetic Variation; Genome, Human; Genomics; Heterozygote; Histones; Humans; Pilot Projects; Protein Binding; Regulatory Sequences, Nucleic Acid; RNA, Messenger; RNA, Untranslated; Transcription Factors; Transcription Initiation Site; Transcription, Genetic

Identification of a novel tumor suppressor gene p34 on human chromosome 6q25.1. - Wang, Min; Vikis, Haris G; Wang, Yian; Jia, Dongmei; Wang, Daolong; Bierut, Laura J; Bailey-Wilson, Joan E; Amos, Christopher I; Pinney, Susan M; Petersen, Gloria M; de Andrade, Mariza; Yang, Ping; et al. (Cancer Res, 2007)
In this study, we observed loss of heterozygosity (LOH) in human chromosomal fragment 6q25.1 in sporadic lung cancer patients. LOH was observed in 65% of the 26 lung tumors examined and was narrowed down to a 2.2-Mb region. Single-nucleotide polymorphism (SNP) analysis of genes located within this region identified a candidate gene, termed p34. This gene, also designated as ZC3H12D, C6orf95, FLJ46041, or dJ281H8.1, carries an A/G nonsynonymous SNP at codon 106, which alters the amino acid from lysine to arginine. Nearly 73% of heterozygous lung cancer tissues with LOH and the A/G SNP also exhibited loss of the A allele. In vitro clonogenic and in vivo nude mouse studies showed that overexpression of the A allele exerts tumor suppressor function compared with the G allele. p34 is located within a recently mapped human lung cancer susceptibility locus, and association of the p34 A/G SNP was tested among these families. No significant association between the less frequent G allele and lung cancer susceptibility was found. Our results suggest that p34 may be a novel tumor suppressor gene involved in sporadic lung cancer but it seems not to be the candidate familial lung cancer susceptibility gene linked to chromosomal region 6q23-25.
Keywords: Alleles; Animals; Base Sequence; Chromosomes, Human, Pair 6; Codon; Female; Genes, Tumor Suppressor; Genetic Predisposition to Disease; Humans; Loss of Heterozygosity; Lung Neoplasms; Mice; Mice, Nude; Molecular Sequence Data; Polymorphism, Single Nucleotide

Paradoxical DNA repair and peroxide resistance gene conservation in Bacillus pumilus SAFR-032. - Gioia, Jason; Yerrapragada, Shailaja; Qin, Xiang; Jiang, Huaiyang; Igboeli, Okezie C; Muzny, Donna; Dugan-Rocha, Shannon; Ding, Yan; Hawes, Alicia; Liu, Wen; Perez, Lesette; Kovar, Christie; et al. (PLoS One, 2007)
BACKGROUND: Bacillus spores are notoriously resistant to unfavorable conditions such as UV radiation, gamma-radiation, H2O2, desiccation, chemical disinfection, or starvation. Bacillus pumilus SAFR-032 survives standard decontamination procedures of the Jet Propulsion Lab spacecraft assembly facility, and both spores and vegetative cells of this strain exhibit elevated resistance to UV radiation and H2O2 compared to other Bacillus species. PRINCIPAL FINDINGS: The genome of B. pumilus SAFR-032 was sequenced and annotated. Lists of genes relevant to DNA repair and the oxidative stress response were generated and compared to B. subtilis and B. licheniformis. Differences in conservation of genes, gene order, and protein sequences are highlighted because they potentially explain the extreme resistance phenotype of B. pumilus. The B. pumilus genome includes genes not found in B. subtilis or B. licheniformis and conserved genes with sequence divergence, but paradoxically lacks several genes that function in UV or H2O2 resistance in other Bacillus species. SIGNIFICANCE: This study identifies several candidate genes for further research into UV and H2O2 resistance. These findings will help explain the resistance of B. pumilus and are applicable to understanding sterilization survival strategies of microbes.
Keywords: Bacillus; DNA Repair; Drug Resistance, Bacterial; Gamma Rays; Genes, Bacterial; Genome, Bacterial; Hydrogen Peroxide; Oxidative Stress; Sequence Analysis, DNA; Spores, Bacterial; Ultraviolet Rays

A second generation human haplotype map of over 3.1 million SNPs. - Frazer, Kelly A; Ballinger, Dennis G; Cox, David R; Hinds, David A; Stuve, Laura L; Gibbs, Richard A; Belmont, John W; Boudreau, Andrew; Hardenbol, Paul; Leal, Suzanne M; Pasternak, Shiran; Wheeler, David A; et al. (Nature, 2007)
We describe the Phase II HapMap, which characterizes over 3.1 million human single nucleotide polymorphisms (SNPs) genotyped in 270 individuals from four geographically diverse populations and includes 25-35% of common SNP variation in the populations surveyed. The map is estimated to capture untyped common variation with an average maximum r2 of between 0.9 and 0.96 depending on population. We demonstrate that the current generation of commercial genome-wide genotyping products captures common Phase II SNPs with an average maximum r2 of up to 0.8 in African and up to 0.95 in non-African populations, and that potential gains in power in association studies can be obtained through imputation. These data also reveal novel aspects of the structure of linkage disequilibrium. We show that 10-30% of pairs of individuals within a population share at least one region of extended genetic identity arising from recent ancestry and that up to 1% of all common variants are untaggable, primarily because they lie within recombination hotspots. We show that recombination rates vary systematically around genes and between genes of different function. Finally, we demonstrate increased differentiation at non-synonymous, compared to synonymous, SNPs, resulting from systematic differences in the strength or efficacy of natural selection between populations.
Keywords: Female; Haplotypes; Homozygote; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Racial Groups; Recombination, Genetic; Selection, Genetic

Sequence variation in the soluble epoxide hydrolase gene and subclinical coronary atherosclerosis: interaction with cigarette smoking. - Wei, Qi; Doris, Peter A; Pollizotto, Martin V; Eric Boerwinkle; Jacobs, David R; Siscovick, David S; Fornage, Myriam (Atherosclerosis, 2007)
Soluble epoxide hydrolase (EPHX2) catalyses the degradation of the vasoactive and anti-inflammatory epoxyeicosatrienoic acids and may play a role in the pathophysiology of atherosclerosis. 1337 African-Americans and 1645 Whites from the CARDIA study were genotyped for 22 and 15 EPHX2 single nucleotide polymorphisms (SNPs), respectively, to examine the associations of common EPHX2 haplotypes and genotypes with presence of coronary artery calcified plaque (CAC). The potential influence of cigarette smoking, which increases EPHX2 gene expression, on these associations was also assessed. In African-Americans, a common haplotype uniquely tagged by the R287Q polymorphism was associated with significantly greater risk for CAC (OR=1.7; 95% CI=1.04-3.0). In Whites, a common haplotype uniquely tagged by a polymorphism in Intron 11 of the gene was associated with significantly greater risk for CAC (OR=1.3; 95% CI=1.02-1.6). These haplotype-tagging polymorphisms also showed significant associations with CAC in individual SNP analyses, and these relationships were significantly modified by smoking. This detailed investigation of the association of EPHX2 genetic variation with CAC supports EPHX2's emerging role as a risk factor for atherosclerosis, whose effects are influenced by smoking.
Keywords: Adolescent; Adult; Black or African American; Coronary Artery Disease; Epoxide Hydrolases; Female; Gene Frequency; Haplotypes; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking; Solubility; White People

Subtle genetic changes enhance virulence of methicillin resistant and sensitive Staphylococcus aureus. - Highlander, Sarah K; Hultén, Kristina G; Qin, Xiang; Jiang, Huaiyang; Yerrapragada, Shailaja; Mason, Edward O; Shang, Yue; Williams, Tiffany M; Fortunov, Régine M; Liu, Yamei; Igboeli, Okezie; Petrosino, Joseph; et al. (BMC Microbiol, 2007)
BACKGROUND: Community acquired (CA) methicillin-resistant Staphylococcus aureus (MRSA) increasingly causes disease worldwide. USA300 has emerged as the predominant clone causing superficial and invasive infections in children and adults in the USA. Epidemiological studies suggest that USA300 is more virulent than other CA-MRSA. The genetic determinants that render virulence and dominance to USA300 remain unclear. RESULTS: We sequenced the genomes of two pediatric USA300 isolates: one CA-MRSA and one CA-methicillin susceptible (MSSA), isolated at Texas Children's Hospital in Houston. DNA sequencing was performed by Sanger dideoxy whole genome shotgun (WGS) and 454 Life Sciences pyrosequencing strategies. The sequence of the USA300 MRSA strain was rigorously annotated. In USA300-MRSA 2658 chromosomal open reading frames were predicted and 3.1 and 27 kilobase (kb) plasmids were identified. USA300-MSSA contained a 20 kb plasmid with some homology to the 27 kb plasmid found in USA300-MRSA. Two regions found in US300-MRSA were absent in USA300-MSSA. One of these carried the arginine deiminase operon that appears to have been acquired from S. epidermidis. The USA300 sequence was aligned with other sequenced S. aureus genomes and regions unique to USA300 MRSA were identified. CONCLUSION: USA300-MRSA is highly similar to other MRSA strains based on whole genome alignments and gene content, indicating that the differences in pathogenesis are due to subtle changes rather than to large-scale acquisition of virulence factor genes. The USA300 Houston isolate differs from another sequenced USA300 strain isolate, derived from a patient in San Francisco, in plasmid content and a number of sequence polymorphisms. Such differences will provide new insights into the evolution of pathogens.
Keywords: Adolescent; Anti-Bacterial Agents; Base Sequence; Genomic Islands; Humans; Hydrolases; Methicillin Resistance; Molecular Epidemiology; Molecular Sequence Data; Open Reading Frames; Plasmids; Polymorphism, Genetic; Staphylococcal Infections; Staphylococcus aureus; United States

Chromosome rearrangement and diversification of Francisella tularensis revealed by the type B (OSU18) genome sequence. - Petrosino, Joseph F; Xiang, Qin; Karpathy, Sandor E; Jiang, Huaiyang; Yerrapragada, Shailaja; Liu, Yamei; Gioia, Jason; Hemphill, Lisa; Gonzalez, Arely; Raghavan, T M; Uzman, Akif; Fox, George E; et al. (J Bacteriol, 2006)
The gamma-proteobacterium Francisella tularensis is one of the most infectious human pathogens, and the highly virulent organism F. tularensis subsp. tularensis (type A) and less virulent organism F. tularensis subsp. holarctica (type B) are most commonly associated with significant disease in humans and animals. Here we report the complete genome sequence and annotation for a low-passage type B strain (OSU18) isolated from a dead beaver found near Red Rock, Okla., in 1978. A comparison of the F. tularensis subsp. holarctica sequence with that of F. tularensis subsp. tularensis strain Schu4 (P. Larsson et al., Nat. Genet. 37:153-159, 2005) highlighted genetic differences that may underlie different pathogenicity phenotypes and the evolutionary relationship between type A and type B strains. Despite extensive DNA sequence identity, the most significant difference between type A and type B isolates is the striking amount of genomic rearrangement that exists between the strains. All but two rearrangements can be attributed to homologous recombination occurring between two prominent insertion elements, ISFtu1 and ISFtu2. Numerous pseudogenes have been found in the genomes and are likely contributors to the difference in virulence between the strains. In contrast, no rearrangements have been observed between the OSU18 genome and the genome of the type B live vaccine strain (LVS), and only 448 polymorphisms have been found within non-transposase-coding sequences whose homologs are intact in OSU18. Nonconservative differences between the two strains likely include the LVS attenuating mutation(s).
Keywords: Chromosomes, Bacterial; DNA Transposable Elements; DNA, Bacterial; Evolution, Molecular; Francisella tularensis; Gene Rearrangement; Genome, Bacterial; Molecular Sequence Data; Polymorphism, Genetic; Pseudogenes; Recombination, Genetic; Sequence Analysis, DNA; Sequence Homology; Virulence

Community annotation: procedures, protocols, and supporting tools. - Elsik, Christine G; Worley, Kim C; Zhang, Lan; Milshina, Natalia V; Jiang, Huaiyang; Reese, Justin T; Childs, Kevin L; Venkatraman, Anand; Dickens, C Michael; Weinstock, George M; Richard A Gibbs (Genome Res, 2006)
Investigators at the Baylor College of Medicine Human Genome Sequencing Center (BCM-HGSC) and BeeBase organized a community-wide effort to manually annotate the honey bee (Apis mellifera) genome. Although various strategies for manual annotation have been used in the past, the value of dispersed community annotation has not yet been demonstrated. Here we make a case for the merit of dispersed community annotation. We present annotation procedures, standard protocols, and tools used for sequence analysis, data submission, and data management. We also report lessons learned from this dispersed community annotation effort for a metazoan genome.
Keywords: Animals; Bees; Databases, Genetic; Genome, Human; Genomics; Humans; Models, Genetic; Molecular Sequence Data; Sequence Analysis

Designing new microsatellite markers for linkage and population genetic analyses in rhesus macaques and other nonhuman primates. - Raveendran, Muthuswamy; R. Alan Harris; Milosavljevic, Aleksandar; Johnson, Zach; Shelledy, Wendy; Cameron, Judy; Jeffrey Rogers (Genomics, 2006)
Identification of polymorphic microsatellite loci in nonhuman primates is useful for various biomedical and evolutionary studies of these species. Prior methods for identifying microsatellites in nonhuman primates are inefficient. We describe a new strategy for marker development that uses the available whole genome sequence for rhesus macaques. Fifty-four novel rhesus-derived microsatellites were genotyped in large pedigrees of rhesus monkeys. Linkage analysis was used to place 51 of these loci into the existing rhesus linkage map. In addition, we find that microsatellites identified this way are polymorphic in other Old World monkeys such as baboons. This approach to marker development is more efficient than previous methods and produces polymorphisms with known locations in the rhesus genome assembly. Finally, we propose a nomenclature system that can be used for rhesus-derived microsatellites genotyped in any species or for novel loci derived from the genome sequence of any nonhuman primate.
Keywords: Animals; Chromosome Mapping; Genetic Markers; Genetic Techniques; Genetics, Population; Humans; Macaca mulatta; Microsatellite Repeats; Papio hamadryas; Pedigree; Polymorphism, Genetic

The DNA sequence, annotation and analysis of human chromosome 3. - Donna M Muzny; Steven E Scherer; Kaul, Rajinder; Wang, Jing; Yu, Jun; Sudbrak, Ralf; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; et al. (Nature, 2006)
After the completion of a draft human genome sequence, the International Human Genome Sequencing Consortium has proceeded to finish and annotate each of the 24 chromosomes comprising the human genome. Here we describe the sequencing and analysis of human chromosome 3, one of the largest human chromosomes. Chromosome 3 comprises just four contigs, one of which currently represents the longest unbroken stretch of finished DNA sequence known so far. The chromosome is remarkable in having the lowest rate of segmental duplication in the genome. It also includes a chemokine receptor gene cluster as well as numerous loci involved in multiple human cancers such as the gene encoding FHIT, which contains the most common constitutive fragile site in the genome, FRA3B. Using genomic sequence from chimpanzee and rhesus macaque, we were able to characterize the breakpoints defining a large pericentric inversion that occurred some time after the split of Homininae from Ponginae, and propose an evolutionary history of the inversion.
Keywords: Animals; Base Sequence; Chromosome Breakage; Chromosome Inversion; Chromosomes, Human, Pair 3; Contig Mapping; CpG Islands; DNA, Complementary; Evolution, Molecular; Expressed Sequence Tags; Human Genome Project; Humans; Macaca mulatta; Molecular Sequence Data; Pan troglodytes; Sequence Analysis, DNA; Synteny

Evaluating potential for whole-genome studies in Kosrae, an isolated population in Micronesia. - Bonnen, Penelope E; Pe'er, Itsik; Plenge, Robert M; Salit, Jackie; Lowe, Jennifer K; Shapero, Michael H; Lifton, Richard P; Breslow, Jan L; Daly, Mark J; Reich, David E; Jones, Keith W; Stoffel, Markus; et al. (Nat Genet, 2006)
Whole-genome association studies are predicted to be especially powerful in isolated populations owing to increased linkage disequilibrium (LD) and decreased allelic diversity, but this possibility has not been empirically tested. We compared genome-wide data on 113,240 SNPs typed on 30 trios from the Pacific island of Kosrae to the same markers typed in the 270 samples from the International HapMap Project. The extent of LD is longer and haplotype diversity is lower in Kosrae than in the HapMap populations. More than 98% of Kosraen haplotypes are present in HapMap populations, indicating that HapMap will be useful for genetic studies on Kosrae. The long-range LD around common alleles and limited diversity result in improved efficiency in genetic studies in this population and augments the power to detect association of 'hidden SNPs'.
Keywords: Alleles; Gene Frequency; Genetic Predisposition to Disease; Genetics, Medical; Genome, Human; Haplotypes; Humans; Linkage Disequilibrium; Micronesia; Polymorphism, Single Nucleotide

Evidence for alternative candidate genes near RB1 involved in clonal expansion of in situ urothelial neoplasia. - Kim, Mi-Sook; Jeong, Joon; Majewski, Tadeusz; Kram, Andrzej; Yoon, Dong-Sup; Zhang, Ruo-Dan; Li, Jun-Zhi; Ptaszynski, Konrad; Kuang, Tang C; Zhou, Jain-Hua; Sathyanarayana, Ubaradka G; Tuziak, Tomasz; et al. (Lab Invest, 2006)
In this paper, we present whole-organ histologic and genetic mapping studies using hypervariable DNA markers on chromosome 13 and then integrate the recombination- and single-nucleotide polymorphic sites (SNPs)-based deletion maps with the annotated genome sequence. Using bladders resected from patients with invasive urothelial carcinoma, we studied allelic patterns of 40 microsatellite markers mapping to all regions of chromosome 13 and 79 SNPs located within the 13q14 region containing the RB1 gene. A whole-organ histologic and genetic mapping strategy was used to identify the evolution of allelic losses on chromosome 13 during the progression of bladder neoplasia. Markers mapping to chromosomal regions involved in clonal expansion of preneoplastic intraurothelial lesions were subsequently tested in 25 tumors and 21 voided urine samples of patients with bladder cancer. Four clusters of allelic losses mapping to distinct regions of chromosome 13 were identified. Markers mapping to the 13q14 region that is flanked by D13S263 and D13S276, which contains the RB1 gene, showed allelic losses associated with early clonal expansion of intraurothelial neoplasia. Such losses could be identified in approximately 32% bladder tumor tissue samples and 38% of voided urines from patients with bladder cancer. The integration of distribution patterns of clonal allelic losses revealed by the microsatellite markers with those obtained by genotyping of SNPs disclosed that the loss within an approximately 4-Mb segment centered around RB1 may represent an incipient event in bladder neoplasia. However, the inactivation of RB1 occurred later and was associated with the onset of severe dysplasia/carcinoma in situ. Our studies provide evidence for the presence of critical alternative candidate genes mapping to the 13q14 region that are involved in clonal expansion of neoplasia within the bladder antecedent to the inactivation of the RB1 gene.
Keywords: Aged; Aged, 80 and over; Alleles; Chromosome Mapping; Chromosomes, Human, Pair 13; DNA Methylation; Humans; Immunohistochemistry; Middle Aged; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Recombination, Genetic; Retinoblastoma Protein; Urinary Bladder Neoplasms

The finished DNA sequence of human chromosome 12. - Scherer, Steven E; Donna M Muzny; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; Gunaratne, Preethi; R. Alan Harris; Hawes, Alicia C; Hernandez, Judith; et al. (Nature, 2006)
Human chromosome 12 contains more than 1,400 coding genes and 487 loci that have been directly implicated in human disease. The q arm of chromosome 12 contains one of the largest blocks of linkage disequilibrium found in the human genome. Here we present the finished sequence of human chromosome 12, which has been finished to high quality and spans approximately 132 megabases, representing approximately 4.5% of the human genome. Alignment of the human chromosome 12 sequence across vertebrates reveals the origin of individual segments in chicken, and a unique history of rearrangement through rodent and primate lineages. The rate of base substitutions in recent evolutionary history shows an overall slowing in hominids compared with primates and rodents.
Keywords: Animals; Base Composition; Chromosomes, Human, Pair 12; CpG Islands; Evolution, Molecular; Expressed Sequence Tags; Genes; Humans; Linkage Disequilibrium; Microsatellite Repeats; Molecular Sequence Data; Mutagenesis, Insertional; Pan troglodytes; Sequence Analysis, DNA; Sequence Deletion; Short Interspersed Nucleotide Elements; Synteny

The genome of the sea urchin Strongylocentrotus purpuratus. - Sodergren, Erica; Weinstock, George M; Davidson, Eric H; Cameron, R Andrew; Gibbs, Richard A; Angerer, Robert C; Angerer, Lynne M; Arnone, Maria Ina; Burgess, David R; Burke, Robert D; Coffman, James A; Dean, Michael; et al. (Science, 2006)
We report the sequence and analysis of the 814-megabase genome of the sea urchin Strongylocentrotus purpuratus, a model for developmental and systems biology. The sequencing strategy combined whole-genome shotgun and bacterial artificial chromosome (BAC) sequences. This use of BAC clones, aided by a pooling strategy, overcame difficulties associated with high heterozygosity of the genome. The genome encodes about 23,300 genes, including many previously thought to be vertebrate innovations or known only outside the deuterostomes. This echinoderm genome provides an evolutionary outgroup for the chordates and yields insights into the evolution of deuterostomes.
Keywords: Animals; Calcification, Physiologic; Cell Adhesion Molecules; Complement Activation; Computational Biology; Embryonic Development; Evolution, Molecular; Gene Expression Regulation, Developmental; Genes; Genome; Immunity, Innate; Immunologic Factors; Male; Nervous System Physiological Phenomena; Proteins; Sequence Analysis, DNA; Signal Transduction; Strongylocentrotus purpuratus; Transcription Factors

The genome sequence of Mannheimia haemolytica A1: insights into virulence, natural competence, and Pasteurellaceae phylogeny. - Gioia, Jason; Qin, Xiang; Jiang, Huaiyang; Clinkenbeard, Kenneth; Lo, Reggie; Liu, Yamei; Fox, George E; Yerrapragada, Shailaja; McLeod, Michael P; McNeill, Thomas Z; Hemphill, Lisa; Sodergren, Erica; et al. (J Bacteriol, 2006)
The draft genome sequence of Mannheimia haemolytica A1, the causative agent of bovine respiratory disease complex (BRDC), is presented. Strain ATCC BAA-410, isolated from the lung of a calf with BRDC, was the DNA source. The annotated genome includes 2,839 coding sequences, 1,966 of which were assigned a function and 436 of which are unique to M. haemolytica. Through genome annotation many features of interest were identified, including bacteriophages and genes related to virulence, natural competence, and transcriptional regulation. In addition to previously described virulence factors, M. haemolytica encodes adhesins, including the filamentous hemagglutinin FhaB and two trimeric autotransporter adhesins. Two dual-function immunoglobulin-protease/adhesins are also present, as is a third immunoglobulin protease. Genes related to iron acquisition and drug resistance were identified and are likely important for survival in the host and virulence. Analysis of the genome indicates that M. haemolytica is naturally competent, as genes for natural competence and DNA uptake signal sequences (USS) are present. Comparison of competence loci and USS in other species in the family Pasteurellaceae indicates that M. haemolytica, Actinobacillus pleuropneumoniae, and Haemophilus ducreyi form a lineage distinct from other Pasteurellaceae. This observation was supported by a phylogenetic analysis using sequences of predicted housekeeping genes.
Keywords: Actinobacillus pleuropneumoniae; Adhesins, Bacterial; DNA, Bacterial; Gene Expression Regulation, Bacterial; Genome, Bacterial; Haemophilus ducreyi; Mannheimia haemolytica; Phylogeny; Prophages; Sequence Analysis, DNA; Transcription, Genetic; Transformation, Bacterial; Virulence

Recurrent duplication-driven transposition of DNA during hominoid evolution. - Johnson, Matthew E; Cheng, Ze; Morrison, V Anne; Scherer, Steven; Ventura, Mario; Gibbs, Richard A; Green, Eric D; Eichler, Evan E (Proc Natl Acad Sci U S A, 2006)
The underlying mechanism by which the interspersed pattern of human segmental duplications has evolved is unknown. Based on a comparative analysis of primate genomes, we show that a particular segmental duplication (LCR16a) has been the source locus for the formation of the majority of intrachromosomal duplications blocks on human chromosome 16. We provide evidence that this particular segment has been active independently in each great ape and human lineage at different points during evolution. Euchromatic sequence that flanks sites of LCR16a integration are frequently lineage-specific duplications. This process has mobilized duplication blocks (15-200 kb in size) to new genomic locations in each species. Breakpoint analysis of lineage-specific insertions suggests coordinated deletion of repeat-rich DNA at the target site, in some cases deleting genes in that species. Our data support a model of duplication where the probability that a segment of DNA becomes duplicated is determined by its proximity to core duplicons, such as LCR16a.
Keywords: Animals; Base Sequence; Biological Evolution; Chromosomes, Human, Pair 16; DNA; DNA Transposable Elements; Evolution, Molecular; Gene Duplication; Hominidae; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

Color-blind fluorescence detection for four-color DNA sequencing. - Lewis, Ernest K; Haaland, Wade C; Nguyen, Freddy; Heller, Daniel A; Allen, Matthew J; MacGregor, Robert R; Berger, C Scott; Willingham, Britain; Burns, Lori A; Scott, Graham B I; Kittrell, Carter; Johnson, Bruce R; et al. (Proc Natl Acad Sci U S A, 2005)
We present an approach called pulsed multiline excitation (PME) for measurements of multicomponent, fluorescence species and demonstrate its application in capillary electrophoresis for DNA sequencing. To fully demonstrate the advantages of PME, a fluorescent dye set has been developed whose absorption maxima span virtually the entire visible spectrum. Unlike emission wavelength-dependent approaches for identifying fluorescent species, the removal of the spectral component in PME confers a number of advantages including higher and normalized signals from all dyes present in the assay, the elimination of spectral cross-talk between dyes, and higher signal collection efficiency. Base-calling is unambiguously determined once dye mobility corrections are made. These advantages translate into significantly enhanced signal quality as illustrated in the primary DNA sequencing data and provide a means for achieving accurate base-calling at lower reagent concentrations.
Keywords: Base Sequence; Color; Fluorescence; Fluorescent Dyes; Reproducibility of Results; Sensitivity and Specificity; Sequence Analysis, DNA

Deletion of FMR1 in Purkinje cells enhances parallel fiber LTD, enlarges spines, and attenuates cerebellar eyelid conditioning in Fragile X syndrome. - Koekkoek, S K E; Yamaguchi, K; Milojkovic, B A; Dortland, B R; Ruigrok, T J H; Maex, R; De Graaf, W; Smit, A E; VanderWerf, F; Bakker, C E; Willemsen, R; Ikeda, T; et al. (Neuron, 2005)
Absence of functional FMRP causes Fragile X syndrome. Abnormalities in synaptic processes in the cerebral cortex and hippocampus contribute to cognitive deficits in Fragile X patients. So far, the potential roles of cerebellar deficits have not been investigated. Here, we demonstrate that both global and Purkinje cell-specific knockouts of Fmr1 show deficits in classical delay eye-blink conditioning in that the percentage of conditioned responses as well as their peak amplitude and peak velocity are reduced. Purkinje cells of these mice show elongated spines and enhanced LTD induction at the parallel fiber synapses that innervate these spines. Moreover, Fragile X patients display the same cerebellar deficits in eye-blink conditioning as the mutant mice. These data indicate that a lack of FMRP leads to cerebellar deficits at both the cellular and behavioral levels and raise the possibility that cerebellar dysfunctions can contribute to motor learning deficits in Fragile X patients.
Keywords: Animals; Cerebellum; Conditioning, Eyelid; Dendrites; Fragile X Mental Retardation Protein; Fragile X Syndrome; Gene Deletion; Humans; Long-Term Synaptic Depression; Male; Mice; Mice, Knockout; Mice, Mutant Strains; Models, Neurological; Nerve Fibers; Nerve Tissue Proteins; Purkinje Cells; Reflex, Startle; RNA-Binding Proteins

The DNA sequence of the human X chromosome. - Ross, Mark T; Grafham, Darren V; Coffey, Alison J; Scherer, Steven; McLay, Kirsten; Muzny, Donna; Platzer, Matthias; Howell, Gareth R; Burrows, Christine; Bird, Christine P; Frankish, Adam; Lovell, Frances L; et al. (Nature, 2005)
The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that is consistent with their proposed role as way stations in the process of X-chromosome inactivation. We found 1,098 genes in the sequence, of which 99 encode proteins expressed in testis and in various tumour types. A disproportionately high number of mendelian diseases are documented for the X chromosome. Of this number, 168 have been explained by mutations in 113 X-linked genes, which in many cases were characterized with the aid of the DNA sequence.
Keywords: Animals; Antigens, Neoplasm; Centromere; Chromosomes, Human, X; Chromosomes, Human, Y; Contig Mapping; Crossing Over, Genetic; Dosage Compensation, Genetic; Evolution, Molecular; Female; Genetic Linkage; Genetics, Medical; Genomics; Humans; Male; Polymorphism, Single Nucleotide; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Testis

G309D and W437OPA PINK1 mutations in Caucasian Parkinson's disease patients. - Deng, H; Le, W D; Zhang, X; Pan, T H; Jankovic, J (Acta Neurol Scand, 2005)
OBJECTIVE: To determine whether the G309D and W437OPA mutations in PINK1 gene are present in American Caucasian population of patients with Parkinson's disease (PD). METHODS: We searched for the G309D and W437OPA mutation by sequencing the regions of interest in the PINK1 gene in 237 unrelated Caucasian patients. RESULTS: None of the 237 samples showed the G309D or W437OPA mutations. CONCLUSIONS: The G309D and W437OPA mutations in PINK1 gene probably do not represent common causes of familial or sporadic PD in a Caucasian population.
Keywords: Adult; Amino Acid Substitution; DNA Mutational Analysis; Female; Genetic Testing; Genome, Human; Humans; Male; Middle Aged; Mutation; Parkinson Disease; Protein Kinases; United States; White People

Generation and annotation of the DNA sequences of human chromosomes 2 and 4. - Hillier, LaDeana W; Graves, Tina A; Fulton, Robert S; Fulton, Lucinda A; Pepin, Kymberlie H; Minx, Patrick; Wagner-McPherson, Caryn; Layman, Dan; Wylie, Kristine; Sekhon, Mandeep; Becker, Michael C; Fewell, Ginger A; et al. (Nature, 2005)
Human chromosome 2 is unique to the human lineage in being the product of a head-to-head fusion of two intermediate-sized ancestral chromosomes. Chromosome 4 has received attention primarily related to the search for the Huntington's disease gene, but also for genes associated with Wolf-Hirschhorn syndrome, polycystic kidney disease and a form of muscular dystrophy. Here we present approximately 237 million base pairs of sequence for chromosome 2, and 186 million base pairs for chromosome 4, representing more than 99.6% of their euchromatic sequences. Our initial analyses have identified 1,346 protein-coding genes and 1,239 pseudogenes on chromosome 2, and 796 protein-coding genes and 778 pseudogenes on chromosome 4. Extensive analyses confirm the underlying construction of the sequence, and expand our understanding of the structure and evolution of mammalian chromosomes, including gene deserts, segmental duplications and highly variant regions.
Keywords: Animals; Base Composition; Base Sequence; Centromere; Chromosomes, Human, Pair 2; Chromosomes, Human, Pair 4; Conserved Sequence; CpG Islands; Euchromatin; Expressed Sequence Tags; Gene Duplication; Genetic Variation; Genomics; Humans; Molecular Sequence Data; Physical Chromosome Mapping; Polymorphism, Genetic; Primates; Proteins; Pseudogenes; Recombination, Genetic; RNA, Messenger; RNA, Untranslated; Sequence Analysis, DNA

The genome of the social amoeba Dictyostelium discoideum. - Eichinger, L; Pachebat, J A; Glöckner, G; Rajandream, M-A; Sucgang, R; Berriman, M; Song, J; Olsen, R; Szafranski, K; Xu, Q; Tunggal, B; Kummerfeld, S; et al. (Nature, 2005)
The social amoebae are exceptional in their ability to alternate between unicellular and multicellular forms. Here we describe the genome of the best-studied member of this group, Dictyostelium discoideum. The gene-dense chromosomes of this organism encode approximately 12,500 predicted proteins, a high proportion of which have long, repetitive amino acid tracts. There are many genes for polyketide synthases and ABC transporters, suggesting an extensive secondary metabolism for producing and exporting small molecules. The genome is rich in complex repeats, one class of which is clustered and may serve as centromeres. Partial copies of the extrachromosomal ribosomal DNA (rDNA) element are found at the ends of each chromosome, suggesting a novel telomere structure and the use of a common mechanism to maintain both the rDNA and chromosomal termini. A proteome-based phylogeny shows that the amoebozoa diverged from the animal-fungal lineage after the plant-animal split, but Dictyostelium seems to have retained more of the diversity of the ancestral genome than have plants, animals or fungi.
Keywords: Animals; ATP-Binding Cassette Transporters; Base Composition; Cell Adhesion; Cell Movement; Centromere; Conserved Sequence; Dictyostelium; DNA Transposable Elements; DNA, Ribosomal; Eukaryotic Cells; Gene Duplication; Gene Transfer, Horizontal; Genome; Genomics; Humans; Molecular Sequence Data; Phylogeny; Proteome; Protozoan Proteins; Repetitive Sequences, Nucleic Acid; RNA, Transfer; Sequence Analysis, DNA; Signal Transduction; Social Behavior; Telomere

Highly multiplexed molecular inversion probe genotyping: over 10,000 targeted SNPs genotyped in a single tube assay. - Hardenbol, Paul; Yu, Fuli; Belmont, John; Mackenzie, Jennifer; Bruckner, Carsten; Brundage, Tiffany; Boudreau, Andrew; Chow, Steve; Eberle, Jim; Erbilgin, Ayca; Falkowski, Mat; Fitzgerald, Ron; et al. (Genome Res, 2005)
Large-scale genetic studies are highly dependent on efficient and scalable multiplex SNP assays. In this study, we report the development of Molecular Inversion Probe technology with four-color, single array detection, applied to large-scale genotyping of up to 12,000 SNPs per reaction. While generating 38,429 SNP assays using this technology in a population of 30 trios from the Centre d'Etude Polymorphisme Humain family panel as part of the International HapMap project, we established SNP conversion rates of approximately 90% with concordance rates >99.6% and completeness levels >98% for assays multiplexed up to 12,000plex levels. Furthermore, these individual metrics can be "traded off" and, by sacrificing a small fraction of the conversion rate, the accuracy can be increased to very high levels. No loss of performance is seen when scaling from 6,000plex to 12,000plex assays, strongly validating the ability of the technology to suppress cross-reactivity at high multiplex levels. The results of this study demonstrate the suitability of this technology for comprehensive association studies that use targeted SNPs in indirect linkage disequilibrium studies or that directly screen for causative mutations.
Keywords: Chromosome Inversion; Cluster Analysis; DNA Probes; Gene Expression Profiling; Genome, Human; Genotype; Humans; Molecular Probe Techniques; Molecular Probes; Polymorphism, Single Nucleotide; Research Design

Lineage-specific expansions of retroviral insertions within the genomes of African great apes but not humans and orangutans. - Yohn, Chris T; Jiang, Zhaoshi; McGrath, Sean D; Hayden, Karen E; Khaitovich, Philipp; Johnson, Matthew E; Eichler, Marla Y; McPherson, John D; Zhao, Shaying; Pääbo, Svante; Eichler, Evan E (PLoS Biol, 2005)
Retroviral infections of the germline have the potential to episodically alter gene function and genome structure during the course of evolution. Horizontal transmissions between species have been proposed, but little evidence exists for such events in the human/great ape lineage of evolution. Based on analysis of finished BAC chimpanzee genome sequence, we characterize a retroviral element (Pan troglodytes endogenous retrovirus 1 [PTERV1]) that has become integrated in the germline of African great ape and Old World monkey species but is absent from humans and Asian ape genomes. We unambiguously map 287 retroviral integration sites and determine that approximately 95.8% of the insertions occur at non-orthologous regions between closely related species. Phylogenetic analysis of the endogenous retrovirus reveals that the gorilla and chimpanzee elements share a monophyletic origin with a subset of the Old World monkey retroviral elements, but that the average sequence divergence exceeds neutral expectation for a strictly nuclear inherited DNA molecule. Within the chimpanzee, there is a significant integration bias against genes, with only 14 of these insertions mapping within intronic regions. Six out of ten of these genes, for which there are expression data, show significant differences in transcript expression between human and chimpanzee. Our data are consistent with a retroviral infection that bombarded the genomes of chimpanzees and gorillas independently and concurrently, 3-4 million years ago. We speculate on the potential impact of such recent events on the evolution of humans and great apes.
Keywords: Animals; Chromosome Mapping; Endogenous Retroviruses; Gorilla gorilla; Hominidae; Humans; Introns; Molecular Sequence Data; Pan troglodytes; Pongo pygmaeus; Protein Biosynthesis; Retroelements; Species Specificity; Transcription, Genetic

Pooled genomic indexing of rhesus macaque. - Milosavljevic, Aleksandar; Harris, Ronald A; Sodergren, Erica J; Jackson, Andrew R; Kalafus, Ken J; Hodgson, Anne; Cree, Andrew; Dai, Weilie; Csuros, Miklos; Zhu, Baoli; De Jong, Pieter J; Weinstock, George M; et al. (Genome Res, 2005)
Pooled genomic indexing (PGI) is a method for mapping collections of bacterial artificial chromosome (BAC) clones between species by using a combination of clone pooling and DNA sequencing. PGI has been used to map a total of 3858 BAC clones covering approximately 24% of the rhesus macaque (Macaca mulatta) genome onto 4178 homologous loci in the human genome. A number of intrachromosomal rearrangements were detected by mapping multiple segments within the individual rhesus BACs onto multiple disjoined loci in the human genome. Transversal pooling designs involving shuffled BAC arrays were employed for robust mapping even with modest DNA sequence read coverage. A further innovation, short-tag pooled genomic indexing (ST-PGI), was also introduced to further improve the economy of mapping by sequencing multiple, short, mapable tags within a single sequencing reaction.
Keywords: Animals; Chromosome Aberrations; Chromosomes, Artificial, Bacterial; Contig Mapping; DNA; Genetic Markers; Genome; Genome, Human; Humans; Macaca mulatta; Sequence Alignment; Sequence Analysis, DNA

Biochemical and genetic interaction between the fragile X mental retardation protein and the microRNA pathway. - Jin, Peng; Zarnescu, Daniela C; Ceman, Stephanie; Nakamoto, Mika; Mowrey, Julie; Jongens, Thomas A; Nelson, David L; Moses, Kevin; Warren, Stephen T (Nat Neurosci, 2004)
Fragile X syndrome is caused by a loss of expression of the fragile X mental retardation protein (FMRP). FMRP is a selective RNA-binding protein which forms a messenger ribonucleoprotein (mRNP) complex that associates with polyribosomes. Recently, mRNA ligands associated with FMRP have been identified. However, the mechanism by which FMRP regulates the translation of its mRNA ligands remains unclear. MicroRNAs are small noncoding RNAs involved in translational control. Here we show that in vivo mammalian FMRP interacts with microRNAs and the components of the microRNA pathways including Dicer and the mammalian ortholog of Argonaute 1 (AGO1). Using two different Drosophila melanogaster models, we show that AGO1 is critical for FMRP function in neural development and synaptogenesis. Our results suggest that FMRP may regulate neuronal translation via microRNAs and links microRNAs with human disease.
Keywords: Animals; Argonaute Proteins; Blotting, Western; Disease Models, Animal; Drosophila melanogaster; Drosophila Proteins; Eye; Fragile X Syndrome; HeLa Cells; Humans; Immunohistochemistry; Male; MicroRNAs; Microscopy, Electron, Scanning; Nerve Tissue Proteins; Neuromuscular Junction; Neuronal Plasticity; Precipitin Tests; Ribonuclease III; RNA-Induced Silencing Complex

Complete genome sequence of Rickettsia typhi and comparison with sequences of other rickettsiae. - McLeod, Michael P; Qin, Xiang; Karpathy, Sandor E; Gioia, Jason; Highlander, Sarah K; Fox, George E; McNeill, Thomas Z; Jiang, Huaiyang; Muzny, Donna; Jacob, Leni S; Hawes, Alicia C; Sodergren, Erica; et al. (J Bacteriol, 2004)
Rickettsia typhi, the causative agent of murine typhus, is an obligate intracellular bacterium with a life cycle involving both vertebrate and invertebrate hosts. Here we present the complete genome sequence of R. typhi (1,111,496 bp) and compare it to the two published rickettsial genome sequences: R. prowazekii and R. conorii. We identified 877 genes in R. typhi encoding 3 rRNAs, 33 tRNAs, 3 noncoding RNAs, and 838 proteins, 3 of which are frameshifts. In addition, we discovered more than 40 pseudogenes, including the entire cytochrome c oxidase system. The three rickettsial genomes share 775 genes: 23 are found only in R. prowazekii and R. typhi, 15 are found only in R. conorii and R. typhi, and 24 are unique to R. typhi. Although most of the genes are colinear, there is a 35-kb inversion in gene order, which is close to the replication terminus, in R. typhi, compared to R. prowazekii and R. conorii. In addition, we found a 124-kb R. typhi-specific inversion, starting 19 kb from the origin of replication, compared to R. prowazekii and R. conorii. Inversions in this region are also seen in the unpublished genome sequences of R. sibirica and R. rickettsii, indicating that this region is a hot spot for rearrangements. Genome comparisons also revealed a 12-kb insertion in the R. prowazekii genome, relative to R. typhi and R. conorii, which appears to have occurred after the typhus (R. prowazekii and R. typhi) and spotted fever (R. conorii) groups diverged. The three-way comparison allowed further in silico analysis of the SpoT split genes, leading us to propose that the stringent response system is still functional in these rickettsiae.
Keywords: Chromosome Inversion; DNA, Bacterial; Electron Transport Complex IV; Frameshifting, Ribosomal; Gene Expression Regulation, Bacterial; Gene Rearrangement; Genes, Bacterial; Genes, rRNA; Genome, Bacterial; Genomics; Molecular Sequence Data; Pseudogenes; Rickettsia; Rickettsia conorii; Rickettsia typhi; RNA, Transfer; RNA, Untranslated; Sequence Analysis, DNA; Sequence Homology; Synteny

EAnnot: a genome annotation tool using experimental evidence. - Ding, Li; Sabo, Aniko; Berkowicz, Nicolas; Meyer, Rekha R; Shotland, Yoram; Johnson, Mark R; Pepin, Kymberlie H; Wilson, Richard K; Spieth, John (Genome Res, 2004)
The sequence of any genome becomes most useful for biological experimentation when a complete and accurate gene set is available. Gene prediction programs offer an efficient way to generate an automated gene set. Manual annotation, when performed by experienced annotators, is more accurate and complete than automated annotation. However, it is a laborious and expensive process, and by its nature, introduces a degree of variability not found with automated annotation. EAnnot (Electronic Annotation) is a program originally developed for manually annotating the human genome. It combines the latest bioinformatics tools to extract and analyze a wide range of publicly available data in order to achieve fast and reliable automatic gene prediction and annotation. EAnnot builds gene models based on mRNA, EST, and protein alignments to genomic sequence, attaches supporting evidence to the corresponding genes, identifies pseudogenes, and locates poly(A) sites and signals. Here, we compare manual annotation of human chromosome 6 with annotation performed by EAnnot in order to assess the latter's accuracy. EAnnot can readily be applied to manual annotation of other eukaryotic genomes and can be used to rapidly obtain an automated gene set.
Keywords: Algorithms; Base Sequence; Chromosomes, Human, Pair 6; Computational Biology; Genome; Genomics; Humans; Models, Genetic; Sensitivity and Specificity; Sequence Alignment

Genome sequence of the Brown Norway rat yields insights into mammalian evolution. - Gibbs, Richard A; Weinstock, George M; Metzker, Michael L; Muzny, Donna M; Sodergren, Erica J; Scherer, Steven; Scott, Graham; Steffen, David; Worley, Kim C; Burch, Paula E; Okwuonu, Geoffrey; Hines, Sandra; et al. (Nature, 2004)
The laboratory rat (Rattus norvegicus) is an indispensable tool in experimental medicine and drug development, having made inestimable contributions to human health. We report here the genome sequence of the Brown Norway (BN) rat strain. The sequence represents a high-quality 'draft' covering over 90% of the genome. The BN rat sequence is the third complete mammalian genome to be deciphered, and three-way comparisons with the human and mouse genomes resolve details of mammalian evolution. This first comprehensive analysis includes genes and proteins and their relation to human disease, repeated sequences, comparative genome-wide studies of mammalian orthologous chromosomal regions and rearrangement breakpoints, reconstruction of ancestral karyotypes and the events leading to existing species, rates of variation, and lineage-specific and lineage-independent evolutionary events such as expansion of gene families, orthology relations and protein evolution.
Keywords: Animals; Base Composition; Centromere; Chromosomes, Mammalian; CpG Islands; DNA Transposable Elements; DNA, Mitochondrial; Evolution, Molecular; Gene Duplication; Genome; Genomics; Humans; Introns; Male; Mice; Models, Molecular; Mutagenesis; Polymorphism, Single Nucleotide; Rats; Rats, Inbred BN; Regulatory Sequences, Nucleic Acid; Retroelements; RNA Splice Sites; RNA, Untranslated; Sequence Analysis, DNA; Telomere

Genomic segmental polymorphisms in inbred mouse strains. - Li, Jiangzhen; Jiang, Tao; Mao, Jian-Hua; Balmain, Allan; Peterson, Leif; Harris, Charles; Rao, Pulivarthi H; Havlak, Paul; Richard A Gibbs; Cai, Wei-Wen (Nat Genet, 2004)
By analyzing genomic copy-number differences using high-resolution mouse whole-genome BAC arrays, we uncover substantial differences in regional DNA content between inbred strains of mice. The identification of these apparently common segmental polymorphisms suggests that these differences can contribute to genetic variability and pathologic susceptibility.
Keywords: Animals; Base Sequence; Chromosomes, Artificial, Bacterial; Gene Dosage; In Situ Hybridization, Fluorescence; Mice; Mice, Inbred Strains; Polymorphism, Genetic

Integrated and sequence-ordered BAC- and YAC-based physical maps for the rat genome. - Krzywinski, Martin; Wallis, John; Gösele, Claudia; Bosdet, Ian; Chiu, Readman; Graves, Tina; Hummel, Oliver; Layman, Dan; Mathewson, Carrie; Wye, Natasja; Zhu, Baoli; Albracht, Derek; et al. (Genome Res, 2004)
As part of the effort to sequence the genome of Rattus norvegicus, we constructed a physical map comprised of fingerprinted bacterial artificial chromosome (BAC) clones from the CHORI-230 BAC library. These BAC clones provide approximately 13-fold redundant coverage of the genome and have been assembled into 376 fingerprint contigs. A yeast artificial chromosome (YAC) map was also constructed and aligned with the BAC map via fingerprinted BAC and P1 artificial chromosome clones (PACs) sharing interspersed repetitive sequence markers with the YAC-based physical map. We have annotated 95% of the fingerprint map clones in contigs with coordinates on the version 3.1 rat genome sequence assembly, using BAC-end sequences and in silico mapping methods. These coordinates have allowed anchoring 358 of the 376 fingerprint map contigs onto the sequence assembly. Of these, 324 contigs are anchored to rat genome sequences localized to chromosomes, and 34 contigs are anchored to unlocalized portions of the rat sequence assembly. The remaining 18 contigs, containing 54 clones, still require placement. The fingerprint map is a high-resolution integrative data resource that provides genome-ordered associations among BAC, YAC, and PAC clones and the assembled sequence of the rat genome.
Keywords: Animals; Automation; Chromosomes; Chromosomes, Artificial, Bacterial; Chromosomes, Artificial, Yeast; Cloning, Molecular; Computational Biology; Contig Mapping; DNA Fingerprinting; Genetic Markers; Genome; Physical Chromosome Mapping; Polymerase Chain Reaction; Rats; Sequence Analysis, DNA

Pash: efficient genome-scale sequence anchoring by Positional Hashing. - Kalafus, Ken J; Jackson, Andrew R; Milosavljevic, Aleksandar (Genome Res, 2004)
Pash is a computer program for efficient, parallel, all-against-all comparison of very long DNA sequences. Pash implements Positional Hashing, a novel parallelizable method for sequence comparison based on k-mer representation of sequences. The Positional Hashing method breaks the comparison problem in a unique way that avoids the quadratic penalty encountered with other sensitive methods and confers inherent low-level parallelism. Furthermore, Positional Hashing allows one to readily and predictably trade between sensitivity and speed. In a simulated comparison task, anchoring computationally mutated reads onto a genome, the sensitivity of Pash was equal to or greater than that of BLAST and BLAT, with Pash outperforming these programs as the reads became shorter and less similar to the genome. Using modest computing resources, we employed Pash for two large-scale sequence comparison tasks: comparison of three mammalian genomes, and anchoring millions of chimpanzee whole-genome shotgun sequencing reads onto the human genome. The results of these comparisons by Pash agree with those computed by other methods that use more than an order of magnitude more computing resources. These results confirm the sensitivity of Positional Hashing.
Keywords: Animals; Chromosome Mapping; Cluster Analysis; Computational Biology; DNA; Genome; Genome, Human; Humans; Mice; Pan troglodytes; Rats; Sensitivity and Specificity; Software

Polymorphism of the soluble epoxide hydrolase is associated with coronary artery calcification in African-American subjects: The Coronary Artery Risk Development in Young Adults (CARDIA) study. - Fornage, Myriam; Eric Boerwinkle; Doris, Peter A; Jacobs, David; Liu, Kiang; Wong, Nathan D (Circulation, 2004)
BACKGROUND: Modulation of endogenous epoxide levels by soluble epoxide hydrolase (sEH) in the endothelium represents an important mechanism in the regulation of cardiovascular function. We examined the relationship between a common, functional polymorphism of the human sEH gene and coronary artery calcification (CAC) in young, largely asymptomatic African-American and non-Hispanic white subjects. METHODS AND RESULTS: Multiple logistic regression and Tobit regression models were used to assess the relationship between the sEH Arg287Gln polymorphism and presence and quantity of CAC. Models adjusting for race (except in race-specific analyses), age, sex, smoking, body mass index, systolic blood pressure, LDL cholesterol, and HDL cholesterol were estimated. Allele and genotype frequency distributions were not significantly different between the 2 ethnic groups (P=0.22; P=0.17, respectively). The Arg287Gln polymorphism of the sEH gene was a significant predictor of CAC status in African-American participants, either alone or after adjusting for other risk factors. African-American subjects with at least 1 copy of the Gln287 allele had a 2-fold greater risk of having CAC compared with those not carrying this allele (95% CI, 1.1 to 2.9; P=0.02). There was no relationship between Arg287Gln polymorphism and the probability of having CAC in white participants (OR, 0.8; 95% CI, 0.5 to 1.3; P=0.49). Inferences from multivariable Tobit regression were similar to those obtained in the logistic regression models, indicating that the Arg287Gln polymorphism was a significant independent predictor of both presence and quantity of CAC in African-American but not white subjects. CONCLUSIONS: These data suggest an intriguing and possibly novel role for sEH in the pathogenesis of atherosclerosis, which deserves additional investigation.
Keywords: Adolescent; Adult; Black or African American; Calcinosis; Coronary Artery Disease; Coronary Vessels; Epoxide Hydrolases; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Male; Polymorphism, Genetic; Risk Factors

The status, quality, and expansion of the NIH full-length cDNA project: the Mammalian Gene Collection (MGC). - Gerhard, Daniela S; Wagner, Lukas; Feingold, Elise A; Shenmen, Carolyn M; Grouse, Lynette H; Schuler, Greg; Klein, Steven L; Old, Susan; Rasooly, Rebekah; Good, Peter; Guyer, Mark; Peck, Allison M; et al. (Genome Res, 2004)
The National Institutes of Health's Mammalian Gene Collection (MGC) project was designed to generate and sequence a publicly accessible cDNA resource containing a complete open reading frame (ORF) for every human and mouse gene. The project initially used a random strategy to select clones from a large number of cDNA libraries from diverse tissues. Candidate clones were chosen based on 5'-EST sequences, and then fully sequenced to high accuracy and analyzed by algorithms developed for this project. Currently, more than 11,000 human and 10,000 mouse genes are represented in MGC by at least one clone with a full ORF. The random selection approach is now reaching a saturation point, and a transition to protocols targeted at the missing transcripts is now required to complete the mouse and human collections. Comparison of the sequence of the MGC clones to reference genome sequences reveals that most cDNA clones are of very high sequence quality, although it is likely that some cDNAs may carry missense variants as a consequence of experimental artifact, such as PCR, cloning, or reverse transcriptase errors. Recently, a rat cDNA component was added to the project, and ongoing frog (Xenopus) and zebrafish (Danio) cDNA projects were expanded to take advantage of the high-throughput MGC pipeline.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA Primers; DNA, Complementary; Gene Library; Humans; Mice; National Institutes of Health (U.S.); Open Reading Frames; Rats; United States; Xenopus laevis; Zebrafish

Differentially expressed nucleolar TGF-beta1 target (DENTT) in mouse development. - Ozbun, Laurent L; Martínez, Alfredo; Angdisen, Jerry; Umphress, Sarah; Kang, Yang; Wang, Min; You, Ming; Jakowlew, Sonia B (Dev Dyn, 2003)
Differentially expressed nucleolar TGF-beta1 target (DENTT) is a recently identified gene whose mRNA is differentially affected by TGF-beta1 in TGF-beta1-responsive human lung cancer cells and who is a new member of the TSPY/TSPY-like/SET/NAP-1 (TTSN) protein superfamily. Here, we report that mouse DENTT mRNA contains a 2031-bp open reading frame that encodes a predicted polypeptide of 677-amino acids with a relative molecular mass of 77,671 Da. The mouse and human DENTT sequences show 77% and 78% homology at the nucleotide and amino acid level, respectively. Mouse DENTT is predicted to be a nuclear protein with two nuclear localization signals (NLS), two coiled-coil regions, and a domain that shows significant identity to a region that defines the TTSN superfamily. Green fluorescent protein (GFP)-tagged full-length mouse DENTT transfected into COS-7 cells showed localization predominantly in the nucleolus. Reverse transcription-polymerase chain reaction amplification, Northern hybridization, and Western blot analyses showed expression of mouse DENTT mRNA and protein throughout mouse embryogenesis. Immunohistochemical staining analysis showed that DENTT is expressed in multiple tissues in a defined spatiotemporal pattern during mouse embryogenesis. The heart and primitive brain were the first organs of the embryo that showed immunoreactivity for the DENTT antibody by day 8 of development (E8). In the developing mouse brain, the choroid plexus was intensely stained for DENTT in all stages of development. The spinal cord and dorsal root ganglia were also positive for DENTT staining beginning in the 11-day-old embryo (E11), where homogeneous immunostaining was observed throughout the developing neurons. By day 16 of development (E16), only a small subset of the neuronal population in the spinal cord and dorsal root ganglia was positively stained for DENTT. DENTT immunoreactivity increased steadily with maturation as the differentiation of cartilage and osteoblasts proceeded and reached a maximum in the growth plate during endochondral ossification. DENTT expression was also detected in multiple rodent cell types in vitro, including mouse F9 embryonal carcinoma (EC) cells. Addition of retinoic acid or sodium butyrate to F9 EC cells showed a rapid decrease in expression of DENTT protein occurring by 1 hr that continued to decrease to almost undetectable levels after 24 hr. Cotransfection of full-length mouse DENTT expression plasmid with 3TPLux or COL7A1Luc Luciferase reporter plasmids into F9 EC cells significantly increased the level of 3TPLux reporter transcription while decreasing the level of COL7A1Luc reporter transcription, suggesting that DENTT may play multiple roles in modulating transcriptional responses. These findings suggest new roles for the TTSN superfamily during embryogenesis and differentiation.
Keywords: 3T3 Cells; Animals; Base Sequence; Blotting, Northern; Blotting, Western; Bone and Bones; Cardiovascular System; Cell Cycle Proteins; Cell Differentiation; Cell Nucleolus; Chorion; Digestive System; DNA-Binding Proteins; Female; Gene Expression Regulation, Developmental; Genes, Reporter; Heart; Humans; Immunohistochemistry; Male; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Nervous System; Nuclear Proteins; Placenta; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sequence Homology, Amino Acid; Transcriptional Activation; Transforming Growth Factor beta; Transforming Growth Factor beta1

The DNA sequence and analysis of human chromosome 14. - Heilig, Roland; Eckenberg, Ralph; Petit, Jean-Louis; Fonknechten, Núria; Da Silva, Corinne; Cattolico, Laurence; Levy, Michaël; Barbe, Valérie; de Berardinis, Véronique; Ureta-Vidal, Abel; Pelletier, Eric; Vico, Virginie; et al. (Nature, 2003)
Chromosome 14 is one of five acrocentric chromosomes in the human genome. These chromosomes are characterized by a heterochromatic short arm that contains essentially ribosomal RNA genes, and a euchromatic long arm in which most, if not all, of the protein-coding genes are located. The finished sequence of human chromosome 14 comprises 87,410,661 base pairs, representing 100% of its euchromatic portion, in a single continuous segment covering the entire long arm with no gaps. Two loci of crucial importance for the immune system, as well as more than 60 disease genes, have been localized so far on chromosome 14. We identified 1,050 genes and gene fragments, and 393 pseudogenes. On the basis of comparisons with other vertebrate genomes, we estimate that more than 96% of the chromosome 14 genes have been annotated. From an analysis of the CpG island occurrences, we estimate that 70% of these annotated genes are complete at their 5' end.
Keywords: 5' Untranslated Regions; Animals; Base Composition; Chromosomes, Artificial; Chromosomes, Human, Pair 14; CpG Islands; DNA, Mitochondrial; DNA, Ribosomal; Genes; Genomics; Humans; Immunity; Mice; Microsatellite Repeats; Molecular Sequence Data; Open Reading Frames; Physical Chromosome Mapping; Pseudogenes; Reproducibility of Results; Sequence Analysis, DNA; Synteny

The DNA sequence of human chromosome 7. - Hillier, LaDeana W; Fulton, Robert S; Fulton, Lucinda A; Graves, Tina A; Pepin, Kymberlie H; Wagner-McPherson, Caryn; Layman, Dan; Maas, Jason; Jaeger, Sara; Walker, Rebecca; Wylie, Kristine; Sekhon, Mandeep; et al. (Nature, 2003)
Human chromosome 7 has historically received prominent attention in the human genetics community, primarily related to the search for the cystic fibrosis gene and the frequent cytogenetic changes associated with various forms of cancer. Here we present more than 153 million base pairs representing 99.4% of the euchromatic sequence of chromosome 7, the first metacentric chromosome completed so far. The sequence has excellent concordance with previously established physical and genetic maps, and it exhibits an unusual amount of segmentally duplicated sequence (8.2%), with marked differences between the two arms. Our initial analyses have identified 1,150 protein-coding genes, 605 of which have been confirmed by complementary DNA sequences, and an additional 941 pseudogenes. Of genes confirmed by transcript sequences, some are polymorphic for mutations that disrupt the reading frame.
Keywords: Animals; Base Sequence; Chromosomes, Human, Pair 7; Gene Duplication; Humans; Mice; Molecular Sequence Data; Physical Chromosome Mapping; Proteins; Pseudogenes; RNA, Untranslated; Sequence Analysis, DNA; Species Specificity; Williams Syndrome

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part I. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document focuses on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Acute Disease; Arteriosclerosis; Consensus; Coronary Disease; Death, Sudden, Cardiac; Disease Progression; Humans; Models, Cardiovascular; Risk Assessment; Syndrome; Terminology as Topic

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part II. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document will focus on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Animals; Biomarkers; Coronary Artery Disease; Death, Sudden, Cardiac; Disease Susceptibility; Female; Humans; Male; Mass Screening; Myocardial Infarction; Myocardium; Risk Assessment; Severity of Illness Index; Swine; Thrombophilia

Haplotype structure, LD blocks, and uneven recombination within the LRP5 gene. - Twells, Rebecca C J; Mein, Charles A; Phillips, Michael S; Hess, J Fred; Veijola, Riitta; Gilbey, Matthew; Bright, Matthew; Metzker, Michael; Lie, Benedicte A; Kingsnorth, Amanda; Gregory, Edward; Nakagawa, Yusuke; et al. (Genome Res, 2003)
Patterns of linkage disequilibrium (LD) in the human genome are beginning to be characterized, with a paucity of haplotype diversity in "LD blocks," interspersed by apparent "hot spots" of recombination. Previously, we cloned and physically characterized the low-density lipoprotein-receptor-related protein 5 (LRP5) gene. Here, we have extensively analysed both LRP5 and its flanking three genes, spanning 269 kb, for single nucleotide polymorphisms (SNPs), and we present a comprehensive SNP map comprising 95 polymorphisms. Analysis revealed high levels of recombination across LRP5, including a hot-spot region from intron 1 to intron 7 of LRP5, where there are 109 recombinants/Mb (4882 meioses), in contrast to flanking regions of 14.6 recombinants/Mb. This region of high recombination could be delineated into three to four hot spots, one within a 601-bp interval. For LRP5, three haplotype blocks were identified, flanked by the hot spots. Each LD block comprised over 80% common haplotypes, concurring with a previous study of 14 genes that showed that common haplotypes account for at least 80% of all haplotypes. The identification of hot spots in between these LD blocks provides additional evidence that LD blocks are separated by areas of higher recombination.
Keywords: 3' Flanking Region; 5' Flanking Region; Alleles; Chromosome Mapping; Chromosomes, Human, Pair 11; Diabetes Mellitus, Type 1; Gene Frequency; Genetic Markers; Genetics, Population; Genotype; Haplotypes; Humans; Introns; LDL-Receptor Related Proteins; Linkage Disequilibrium; Low Density Lipoprotein Receptor-Related Protein-5; Microsatellite Repeats; Nuclear Family; Polymorphism, Single Nucleotide; Receptors, LDL; Recombination, Genetic

Interaction between soluble thrombomodulin and intercellular adhesion molecule-1 in predicting risk of coronary heart disease. - Wu, Kenneth K; Aleksic, Nena; Ballantyne, Christie M; Ahn, Chul; Juneja, Harinder; Eric Boerwinkle (Circulation, 2003)
BACKGROUND: Results from previous ARIC (Atherosclerosis Risk In Communities) analyses indicate that soluble intercellular adhesive molecule-1 (sICAM) and soluble thrombomodulin (sTM) levels are associated with risk of coronary heart disease (CHD) in an opposite direction. A high sICAM level increases the risk of CHD, whereas a high level of sTM has a lower risk of CHD. It was unclear whether there was an interaction between sTM and sICAM. METHODS AND RESULTS: Using a nested case-cohort design, we measured sTM and sICAM in 317 incident CHD cases and 726 non-cases from the ARIC participants. Consistent with our previous reports, sICAM values in the upper versus the lower tertile increased the risk of CHD event by approximately 2-fold (95% confidence interval [CI], 1.46 to 2.87) whereas sTM values in the lower versus the upper tertile increased CHD risk by approximately 4-fold (95% CI, 2.80 to 5.74). Interaction between these 2 parameters was determined by weighted Cox proportional hazard regression. A significant interaction (P=0.038) was noted. Combinatorial analysis shows a significant increase in CHD risk ratio (RR) (4.66, 95% CI, 1.89 to 11.46) of the lower sTM/upper sICAM group versus the upper sTM/lower sICAM group. Individuals whose sTM values were in the upper tertile had a RR below 1, even when sICAM were in the upper tertile. The RR of lower tertile sTM was increased by sICAM in a tertile-dependent manner. CONCLUSIONS: Weighted Cox proportional hazard analysis shows a significant interaction between sTM and sICAM in predicting risk of CHD event. Combinatorial analysis reveals that an upper tertile sICAM had a significant increase in the risk of a CHD event only when sTM was in the lower tertile.
Keywords: Case-Control Studies; Coronary Disease; Female; Humans; Intercellular Adhesion Molecule-1; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Thrombomodulin

Internet Contig Explorer (iCE)--a tool for visualizing clone fingerprint maps. - Fjell, Christopher D; Bosdet, Ian; Schein, Jacqueline E; Jones, Steven J M; Marra, Marco A (Genome Res, 2003)
Fingerprinted clone physical maps have proven useful in various applications, supporting both whole-genome and region-specific DNA sequencing as well as gene cloning studies. Fingerprint maps have been generated for several genomes, including those of human, mouse, rat, the nematodes Caenorhabditis elegans and Caenorhabditis briggsae, Arabidopsis thaliana and rice. Fingerprint maps of other genomes, including those of fungi, bacteria, poplar, and the cow, are being generated. The increasing use of fingerprint maps in genomic research has spawned a need in the research community for intuitive computer tools that facilitate viewing of the maps and the underlying fingerprint data. In this report we describe a new Java-based application called iCE (Internet Contig Explorer) that has been designed to provide views of fingerprint maps and associated data. Users can search for and display individual clones, contigs, clone fingerprints, clone insert sizes and markers. Users can also load into the software lists of particular clones of interest and view their fingerprints. iCE is being used at our Genome Centre to offer up to the research community views of the mouse, rat, bovine, C. briggsae, and several fungal genome bacterial artificial chromosome (BAC) fingerprint maps we have either completed or are currently constructing. We are also using iCE as part of the Rat Genome Sequencing Project to manage our provision of rat BAC clones for sequencing at the Human Genome Sequencing Center at the Baylor College of Medicine.
Keywords: Animals; Arabidopsis; Caenorhabditis; Caenorhabditis elegans; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; DNA, Helminth; DNA, Plant; Humans; Internet; Mice; Oryza; Rats; Software

Rigid, conjugated, fluoresceinated thymidine triphosphates: syntheses and polymerase mediated incorporation into DNA analogues. - Thoresen, Lars H; Jiao, Guan-Sheng; Haaland, Wade C; Metzker, Michael L; Burgess, Kevin (Chemistry, 2003)
Syntheses of a unique set of energy transfer dye labeled nucleoside triphosphates, compounds 1-3, are described. Attempts to prepare these compounds were only successful if the triphosphorylation reaction was performed before coupling the dye to the nucleobase, and not the other way around. Compounds were prepared as both the 2'-deoxy (a) and 2',3'-dideoxy- (b) forms. They feature progressively longer rigid conjugated linkers connecting the nucleobase and the hydroxyxanthone moiety. UV spectra of the parent nucleosides 12-14 show that as the length of the linker increases so does the absorption of the donor in the 320-330 nm region, but with relatively little red-shift of the maxima. Fluorescence spectra of the same compounds show that radiation in the 320-330 nm region results in predominant emission from the fluorescein. When the linker is irradiated at 320 nm, the only significant emission observed corresponds to the hydroxyxanthone part of the molecules at 520 nm; this corresponds to an effective Stokes' shift of 200 nm. As the absorption at 320-330 nm by the linker increases with length, so does the intensity of the fluorescein emission. A gel assay was used to gauge relative incorporation efficiencies of compounds 1-3, dTTP, ddTTP, and 6-TAMRA-ddTTP. Throughout, the thermostable polymerase TaqFS was used, as it is the one most widely applied in high throughput DNA sequencing. This assay showed that only compounds 3 were incorporated efficiently; these have the longest linkers. Of these, the 2'-deoxy nucleoside 3 a was incorporated and did not prevent the polymerase from extending the chain further. The 2',3'-dideoxy nucleoside 3 b was incorporated only about 430 times less efficiently than ddTTP under the same conditions, and caused chain termination. The implications of these studies on modified sequencing protocols are discussed.
Keywords: DNA; Fluoresceins; Spectrometry, Fluorescence; Spectrophotometry, Ultraviolet; Substrate Specificity; Taq Polymerase; Thymine Nucleotides

Software for automated analysis of DNA fingerprinting gels. - Fuhrmann, Daniel R; Krzywinski, Martin I; Chiu, Readman; Saeedi, Parvaneh; Schein, Jacqueline E; Bosdet, Ian E; Chinwalla, Asif; Hillier, LaDeana W; Waterston, Robert H; McPherson, John D; Jones, Steven J M; Marra, Marco A (Genome Res, 2003)
Here we describe software tools for the automated detection of DNA restriction fragments resolved on agarose fingerprinting gels. We present a mathematical model for the location and shape of the restriction fragments as a function of fragment size, with model parameters determined empirically from "marker" lanes containing molecular size standards. Automated identification of restriction fragments involves several steps, including: image preprocessing, to put the data in a form consistent with a linear model; marker lane analysis, for determination of the model parameters; and data lane analysis, a procedure for detecting restriction fragment multiplets while simultaneously determining the amplitude curve that describes restriction fragment amplitude as a function of mobility. In validation experiments conducted on fingerprinted and sequenced Bacterial Artificial Chromosome (BAC) clones, sensitivity and specificity of restriction fragment identification exceeded 96% on restriction fragments ranging in size from 600 base pairs (bp) to 30,000 bp. The integrated suite of software tools, written in MATLAB and collectively called BandLeader, is in use at the BC Cancer Agency Genome Sciences Centre (GSC) and the Washington University Genome Sequencing Center, and has been provided to the Wellcome Trust Sanger Institute and the Whitehead Institute. Employed in a production mode at the GSC, BandLeader has been used to perform automated restriction fragment identification for more than 850,000 BAC clones for mouse, rat, bovine, and poplar fingerprint mapping projects.
Keywords: Animals; Cattle; Chromosomes, Artificial, Bacterial; DNA; DNA Fingerprinting; Gels; Mice; Models, Chemical; Rats; Sepharose; Software

Beta 2 adrenergic receptor 5' haplotypes influence promoter activity. - Johnatty, Sharon E; Abdellatif, Maha; Shimmin, Lawrence; Clark, Richard B; Boerwinkle, Eric (Br J Pharmacol, 2002)
1. Transcriptional control of the human beta(2) adrenergic receptor gene (ADRB2) predominantly resides within a 549 base pair region immediately 5' to the start of translation. Within this region, four naturally occurring polymorphisms, -468 C-->G, -367 T-->C, -47 T-->C, and -20 T-->C, have been identified. 2. To determine the individual site and haplotype effects of these polymorphisms, we generated 16 luciferase-based mutant constructs which were transiently transfected into HEK293 cells, and measured ADRB2 promoter-driven luciferase activity. 3. Two of the 16 mutant constructs, GCCT (-468G, -367C, -47C, -20T) and CTCT, showed a highly significant 3 fold decrease in luciferase induction relative to the reference CTTT. These haplotype effects could not be accounted for by the separate and additive effects of each site. 4. These findings indicate that promoter polymorphisms interact to significantly alter beta(2) adrenergic receptor expression, and should be examined further for their association with disease-related phenotypes.
Keywords: Cell Line; Haplotypes; Humans; Luciferases; Mutation; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Adrenergic, beta-2; Statistics, Nonparametric; Transfection

Factor XIIIA Val34Leu polymorphism does not predict risk of coronary heart disease: The Atherosclerosis Risk in Communities (ARIC) Study. - Aleksic, Nena; Ahn, Chul; Wang, Yao-Wei; Juneja, Harinder; Folsom, Aaron R; Eric Boerwinkle; Wu, Kenneth K (Arterioscler Thromb Vasc Biol, 2002)
Factor XIII catalyzes the cross-linking of fibrin. Cross-sectional studies have suggested that a common polymorphism site at residue 34 of the A subunit of factor XIII (FXIIIA) with a substitution of Leu for Val (FXIIIA Val34Leu) was associated with reduced coronary heart disease (CHD). This association has not been examined in prospective studies. Healthy subjects (n=15 792) were recruited from 4 US communities into the Atherosclerosis Risk in Communities (ARIC) study from 1987 to 1989. They were followed, and incident CHD events were identified and verified. For the present study, we included 423 patients with CHD as cases and 479 noncases. FXIIIA Val34Leu polymorphism was determined by the single-strand conformational polymorphism method. There were no significant differences in the genotype frequencies between cases and noncases. The genotypes showed little association with known CHD risk factors. A weighted proportional hazards regression analysis adjusting for other risk factors confirmed no association of the genotypes with risk of CHD. This prospective study did not provide evidence of a reduced CHD risk for the FXIIIA 34Leu allele.
Keywords: Case-Control Studies; Coronary Artery Disease; Factor XIIIa; Female; Gene Frequency; Genotype; Humans; Incidence; Male; Maryland; Middle Aged; Minnesota; Mississippi; North Carolina; Polymorphism, Single-Stranded Conformational; Risk Factors

Generation and initial analysis of more than 15,000 full-length human and mouse cDNA sequences. - Strausberg, Robert L; Feingold, Elise A; Grouse, Lynette H; Derge, Jeffery G; Klausner, Richard D; Collins, Francis S; Wagner, Lukas; Shenmen, Carolyn M; Schuler, Gregory D; Altschul, Stephen F; Zeeberg, Barry; Buetow, Kenneth H; et al. (Proc Natl Acad Sci U S A, 2002)
The National Institutes of Health Mammalian Gene Collection (MGC) Program is a multiinstitutional effort to identify and sequence a cDNA clone containing a complete ORF for each human and mouse gene. ESTs were generated from libraries enriched for full-length cDNAs and analyzed to identify candidate full-ORF clones, which then were sequenced to high accuracy. The MGC has currently sequenced and verified the full ORF for a nonredundant set of >9,000 human and >6,000 mouse genes. Candidate full-ORF clones for an additional 7,800 human and 3,500 mouse genes also have been identified. All MGC sequences and clones are available without restriction through public databases and clone distribution networks (see http:mgc.nci.nih.gov).
Keywords: Algorithms; Animals; DNA, Complementary; Gene Library; Humans; Mice; Open Reading Frames; Sequence Analysis, DNA

Initial sequencing and comparative analysis of the mouse genome. - Waterston, Robert H; Lindblad-Toh, Kerstin; Birney, Ewan; Rogers, Jane; Abril, Josep F; Agarwal, Pankaj; Agarwala, Richa; Ainscough, Rachel; Alexandersson, Marina; An, Peter; Antonarakis, Stylianos E; Attwood, John; et al. (Nature, 2002)
The sequence of the mouse genome is a key informational tool for understanding the contents of the human genome and a key experimental tool for biomedical research. Here, we report the results of an international collaboration to produce a high-quality draft sequence of the mouse genome. We also present an initial comparative analysis of the mouse and human genomes, describing some of the insights that can be gleaned from the two sequences. We discuss topics including the analysis of the evolutionary forces shaping the size, structure and sequence of the genomes; the conservation of large-scale synteny across most of the genomes; the much lower extent of sequence orthology covering less than half of the genomes; the proportions of the genomes under selection; the number of protein-coding genes; the expansion of gene families related to reproduction and immunity; the evolution of proteins; and the identification of intraspecies polymorphism.
Keywords: Animals; Base Composition; Chromosomes, Mammalian; Conserved Sequence; CpG Islands; Evolution, Molecular; Gene Expression Regulation; Genes; Genetic Variation; Genome; Genome, Human; Genomics; Humans; Mice; Mice, Knockout; Mice, Transgenic; Models, Animal; Multigene Family; Mutagenesis; Neoplasms; Physical Chromosome Mapping; Proteome; Pseudogenes; Quantitative Trait Loci; Repetitive Sequences, Nucleic Acid; RNA, Untranslated; Selection, Genetic; Sequence Analysis, DNA; Sex Chromosomes; Species Specificity; Synteny

Genetic mapping and DNA sequence-based analysis of deleted regions on chromosome 16 involved in progression of bladder cancer from occult preneoplastic conditions to invasive disease. - Yoon, D S; Li, L; Zhang, R D; Kram, A; Ro, J Y; Johnston, D; Grossman, H B; Scherer, S; Czerniak, B (Oncogene, 2001)
Histologic and genetic mapping with 30 hypervariable markers mapped to chromosome 16 were performed on 234 DNA samples of five cystectomy specimens from patients with invasive bladder cancer. Allelic losses of individual markers were related to microscopically identified precursor conditions in the entire bladder mucosa and invasive cancer. Their significance for the development and progression of neoplasia from in situ preneoplastic conditions to invasive disease was analysed by the nearest neighbor algorithm and binomial maximum likelihood analysis. Using this approach we identified five distinct regions of allelic losses defined by their flanking markers and predicted size as follows. p13.3(D16S418-D16S406, 1.2 cM), p13.1(D16S748-D16S287, 12.9 cM), q12 1(D16S409-D16S514, 24.0 cM), q22.1 (D16S496-D16S515, 5.4 cM), and q24 (D16S507-D16S511, 5.9 cM and D16S402-D16S413, 17.4 cM). The regions mapping to p13.1 and q24 were involved in early intraurothelial phases of bladder neoplasia such as mild to moderate dysplasia. On the other hand the deleted region mapping to p13.3 was involved in progression of severe dysplasia/carcinoma in situ to invasive bladder cancer. Testing of markers that exhibited statistically significant LOH in relation to progression of neoplasia from precursor conditions to invasive cancer on 28 tumors and voided urine samples from 25 patients with bladder cancer revealed that q12.1 showed LOH in 46.4% of tumor and 32.0% of voided urine samples. The LOH of a single marker D16S541 could be detected in approximately 28% of tumors and 20% of voided urine samples of patients with bladder cancer. These data imply that the deleted region centered around marker D16S541 spanning approximately 10 cM and flanked by D16S409 and D16S415 contains a novel putative tumor suppressor gene or genes playing an important role in the development of human bladder cancer. To facilitate more precise positional mapping and identification of pathogenetically relevant genes, we analysed of human genome contig and sequence databases spanning the deleted regions. Multiple known candidate genes and several smaller gene-rich areas mapping to the target regions of chromosome 16 were identified.
Keywords: Aged; Chromosome Mapping; Chromosomes, Human, Pair 16; Disease Progression; DNA, Neoplasm; Genes, Tumor Suppressor; Genetic Markers; Humans; Loss of Heterozygosity; Male; Middle Aged; Neoplasm Invasiveness; Precancerous Conditions; Sequence Deletion; Tissue Distribution; Urinary Bladder Neoplasms; Urine

Initial sequencing and analysis of the human genome. - Lander, E S; Linton, L M; Birren, B; Nusbaum, C; Zody, M C; Baldwin, J; Devon, K; Dewar, K; Doyle, M; FitzHugh, W; Funke, R; Gage, D; et al. (Nature, 2001)
The human genome holds an extraordinary trove of information about human development, physiology, medicine and evolution. Here we report the results of an international collaboration to produce and make freely available a draft sequence of the human genome. We also present an initial analysis of the data, describing some of the insights that can be gleaned from the sequence.
Keywords: Animals; Chromosome Mapping; Conserved Sequence; CpG Islands; Databases, Factual; DNA Transposable Elements; Drug Industry; Evolution, Molecular; Forecasting; GC Rich Sequence; Gene Duplication; Genes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Human Genome Project; Humans; Mutation; Private Sector; Proteins; Proteome; Public Sector; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Species Specificity

Mapping and genome sequence analysis of chromosome 5 regions involved in bladder cancer progression. - Kram, A; Li, L; Zhang, R D; Yoon, D S; Ro, J Y; Johnston, D; Grossman, H B; Scherer, S; Czerniak, B (Lab Invest, 2001)
We studied the evolution of allelic losses on chromosome 5 by whole-organ histologic and genetic mapping in 234 mucosal DNA samples of 5 cystectomy specimens with invasive bladder cancer and preneoplastic changes in adjacent urothelium. The frequency of alterations in individual loci was verified on 32 tumors and 29 voided urine samples from patients with bladder cancer. Finally, deleted regions on chromosome 5 were integrated with the human genome contigs and sequence-based databases. Deleted regions on chromosome 5 involved in intraurothelial phases of bladder neoplasia defined by their nearest flanking markers and predicted size were identified as follows: q13.3-q22 (D5S424-D5S656; 38.8 centimorgan [cM]); q22-q31.1 (D5S656-D5S808; 19.2 cM), q31.1-q32 (D5S816-SPARC; 11.5 cM), and q34 (GABRA1-D5S415; 6.4 cM). The two most frequently deleted neighbor markers (D5S2055 and D5S818) mapping to q22-q31.1 defined a 9 cM region, which may contain genes that play an important role in early phases of urinary bladder carcinogenesis. Human genome database analysis provided an accurate map of deleted regions with positions of 138 known genes and revealed several smaller gene-rich areas representing putative targets for further mapping. The strategic approach presented here, which combines whole-organ histologic and genetic mapping with analysis of the rapidly emerging human genome sequence database, facilitates identification of genes potentially involved in early phases of bladder carcinogenesis.
Keywords: Aged; Alleles; Chromosome Mapping; Chromosomes, Human, Pair 5; Expressed Sequence Tags; Genome; Humans; Loss of Heterozygosity; Male; Middle Aged; Urinary Bladder Neoplasms

A physical map of the human genome. - McPherson, J D; Marra, M; Hillier, L; Waterston, R H; Chinwalla, A; Wallis, J; Sekhon, M; Wylie, K; Mardis, E R; Wilson, R K; Fulton, R; Kucaba, T A; et al. (Nature, 2001)
The human genome is by far the largest genome to be sequenced, and its size and complexity present many challenges for sequence assembly. The International Human Genome Sequencing Consortium constructed a map of the whole genome to enable the selection of clones for sequencing and for the accurate assembly of the genome sequence. Here we report the construction of the whole-genome bacterial artificial chromosome (BAC) map and its integration with previous landmark maps and information from mapping efforts focused on specific chromosomal regions. We also describe the integration of sequence data with the map.
Keywords: Chromosomes, Artificial, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Gene Duplication; Genome, Human; Humans; In Situ Hybridization, Fluorescence; Repetitive Sequences, Nucleic Acid

The genome sequence of Drosophila melanogaster. - Adams, M D; Celniker, S E; Holt, R A; Evans, C A; Gocayne, J D; Amanatides, P G; Steven E Scherer; Li, P W; Hoskins, R A; Galle, R F; George, R A; Lewis, S E; et al. (Science, 2000)
The fly Drosophila melanogaster is one of the most intensively studied organisms in biology and serves as a model system for the investigation of many developmental and cellular processes common to higher eukaryotes, including humans. We have determined the nucleotide sequence of nearly all of the approximately 120-megabase euchromatic portion of the Drosophila genome using a whole-genome shotgun sequencing strategy supported by extensive clone-based sequence and a high-quality bacterial artificial chromosome physical map. Efforts are under way to close the remaining gaps; however, the sequence is of sufficient accuracy and contiguity to be declared substantially complete and to support an initial analysis of genome structure and preliminary gene annotation and interpretation. The genome encodes approximately 13,600 genes, somewhat fewer than the smaller Caenorhabditis elegans genome, but with comparable functional diversity.
Keywords: Animals; Biological Transport; Chromatin; Cloning, Molecular; Computational Biology; Contig Mapping; Cytochrome P-450 Enzyme System; DNA Repair; DNA Replication; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genome; Heterochromatin; Insect Proteins; Nuclear Proteins; Protein Biosynthesis; Sequence Analysis, DNA; Transcription, Genetic

Sequence and organization of pXO1, the large Bacillus anthracis plasmid harboring the anthrax toxin genes. - Okinaka, R T; Cloud, K; Hampton, O; Hoffmaster, A R; Hill, K K; Keim, P; Koehler, T M; Lamke, G; Kumano, S; Mahillon, J; Manter, D; Martinez, Y; et al. (J Bacteriol, 1999)
The Bacillus anthracis Sterne plasmid pXO1 was sequenced by random, "shotgun" cloning. A circular sequence of 181,654 bp was generated. One hundred forty-three open reading frames (ORFs) were predicted using GeneMark and GeneMark.hmm, comprising only 61% (110,817 bp) of the pXO1 DNA sequence. The overall guanine-plus-cytosine content of the plasmid is 32.5%. The most recognizable feature of the plasmid is a "pathogenicity island," defined by a 44.8-kb region that is bordered by inverted IS1627 elements at each end. This region contains the three toxin genes (cya, lef, and pagA), regulatory elements controlling the toxin genes, three germination response genes, and 19 additional ORFs. Nearly 70% of the ORFs on pXO1 do not have significant similarity to sequences available in open databases. Absent from the pXO1 sequence are homologs to genes that are typically required to drive theta replication and to maintain stability of large plasmids in Bacillus spp. Among the ORFs with a high degree of similarity to known sequences are a collection of putative transposases, resolvases, and integrases, suggesting an evolution involving lateral movement of DNA among species. Among the remaining ORFs, there are three sequences that may encode enzymes responsible for the synthesis of a polysaccharide capsule usually associated with serotype-specific virulent streptococci.
Keywords: Antigens, Bacterial; Bacillus anthracis; Bacterial Toxins; DNA, Bacterial; Genes, Bacterial; Molecular Sequence Data; Open Reading Frames; Plasmids; Recombination, Genetic; Replication Origin; Restriction Mapping; Sequence Analysis, DNA; Sequence Homology

Sequence, assembly and analysis of pX01 and pX02. - Okinaka, R; Cloud, K; Hampton, O; Hoffmaster, A; Hill, K; Keim, P; Koehler, T; Lamke, G; Kumano, S; Manter, D; Martinez, Y; Ricke, D; et al. (J Appl Microbiol, 1999)
Bacillus anthracis plasmids pX01 and pX02, harboured by the Sterne and Pasteur strains, respectively, have been sequenced by random 'shotgun' cloning and high throughout sequence analysis. These sequences have been assembled (Sequencher) to generate a circulate pX01 plasmid containing 181 656 bp and a single linear (gapped) pX02 contig containing at least 93.479 bp. Initial annotation suggests that the two plasmids combined contain at least 200 potential open reading frames (ORFs) with < 40% having significant similarity to sequences registered in open databases. Collectively, only 118 566 bp of the pX01 DNA (65%) represent predicted coding regions. This value is similar to published gene densities for other plasmids and is indicative of the larger intergenic spaces in plasmids vs those found in the chromosomes of the parental microbes (85-93% gene density). A 70 kbp region including the toxin genes (cya, lef and pag) is distinct from the remainder of the pX01 sequence: (1) it has a lower gene density (58 vs 70%) than the remaining 111 kbp; (2) it contains all but one of the co-regulated transcriptional fusions identified by transposon mutagenesis (Hoffmaster & Koehler 1997) and (3) it contains a significantly higher proportion of positive BLAST scores (62 vs 20%) for putative ORFs. These data suggest different origins for the two regions of pX01.
Keywords: Bacillus anthracis; Genes, Bacterial; Open Reading Frames; Plasmids; Sequence Analysis

Three common CFTR mutations should be included in a neonatal screening programme for cystic fibrosis in Sweden. - Schaedel, C; Hjelte, L; de Monestrol, I; Johannesson, M; Kollberg, H; Kornfält, R; Holmberg, L (Clin Genet, 1999)
Children with cystic fibrosis (CF) diagnosed by neonatal screening have a better nutritional development and other advantages compared with those in a nonscreened group. The two-tier immunoreactive trypsinogen (IRT)/DNA screening protocol has been found superior to the single-tier IRT approach, improving the positive predictive value and thus reducing the false-positive rate. However, variations of the DNA test are required for different populations. In this study we examined CFTR (cystic fibrosis transmembrane conductance regulator) mutations in 331 CF patients attending the centres in Stockholm, Lund and Uppsala, comprising about 75% of the CF population in Sweden. The frequency of deltaF508 among CF alleles was 68.3%. There were two other mutations, 394delTT and 3659delC, found to be fairly frequent, amounting to 8.5 and 7.9%, respectively. Other mutations were comparatively rare. A simple and effective method of analysing the three mutations from Guthrie cards has been developed. Assuming Hardy-Weinberg equilibrium, 90% of our CF patients will be expected to carry at least one deltaF508 allele and 97.6% to carry at least one deltaF508, 394delTT or 3659delC copy. Including the latter two in a screening programme would thus substantially reduce the risk of a false-negative outcome.
Keywords: Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Gene Frequency; Homozygote; Humans; Infant, Newborn; Mutation; Neonatal Screening; Polymorphism, Single-Stranded Conformational; Sweden

Test of the potential of a dATP surrogate for sequencing via MALDI-MS. - Jacutin, S; Zhang, A J; Russell, D H; Gibbs, R A; Burgess, K (Nucleic Acids Res, 1997)
1-(2'-Deoxy-beta-d-ribofuranosyl)-3-nitropyrrole phosphate was incorporated into a DNA decamer and analyzed via matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS). The extent and composition of the various fragment peaks were compared with those in the MALDI-MS spectrum of dT4AT5. The nitropyrrole-containing oligomer proved to be more robust. Two different DNA template assays were then used to attempt to identify DNA replicating enzymes that would incorporate the corresponding triphosphate, i.e. 1-(2'-deoxy-beta-d-ribofuranosyl)-3-nitropyrrole triphosphate (dXTP). It was shown that dXTP was not incorporated by some enzymes and it inhibited others. However, DNA polymerase I Klenow fragment and avian myeloblastosis virus reverse transcriptase incorporated dXTP in place of dATP and then replicated the template overhang in the usual way. The potential of dXTP as a surrogate for dATP in DNA sequencing with MALDI-MS analysis is discussed.
Keywords: Deoxyadenine Nucleotides; DNA Polymerase I; DNA-Directed DNA Polymerase; Mass Spectrometry; Nucleotides; Pyrroles; Retroviridae; RNA-Directed DNA Polymerase; Sequence Analysis, DNA; Substrate Specificity; Taq Polymerase; Templates, Genetic

Duplication of a gene-rich cluster between 16p11.1 and Xq28: a novel pericentromeric-directed mechanism for paralogous genome evolution. - Eichler, E E; Lu, F; Shen, Y; Antonacci, R; Jurecic, V; Doggett, N A; Moyzis, R K; Baldini, A; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1996)
We have identified a 26.5 kb gene-rich duplication shared by human Xq28 and 16p11.1. Complete comparative sequence analysis of cosmids from both loci has revealed identical Xq28 and 16p11.1 genomic structures for both the human creatine transporter gene (SLC6A8) and five exons of the CDM gene (DXS1357E). Overall nucleotide similarity within the duplication was found to be 94.6%, suggesting that this interchromosomal duplication occurred within recent evolutionary time (7-10 mya). Based on comparisons between genomic and cDNA sequence, both the Xq28 creatine transporter and DXS1357E genes are transcriptionally active. Predicted translation of exons and RT-PCR analysis reveal that chromosome 16 paralogs likely represent pseudogenes. Comparative fluorescent in situ hybridization (FISH) analyses of chromosomes from various primates indicate that this gene-rich segment has undergone several duplications. In gorilla and chimpanzee, multiple pericentromeric localizations on a variety of chromosomes were found using probes from the duplicated region. In other species, such as the orangutan and gibbon, FISH signals were only identified at the distal end of the X chromosome, suggesting that the Xq28 locus represents the ancestral copy. Sequencing of the 16p 11.1/Xq28 duplication breakpoints has revealed the presence of repetitive immunoglobulin-like CAGGG pentamer sequences at or near the paralogy boundaries. The mobilization and dispersal of this gene-rich 27 kb element to the pericentromeric regions of primate chromosomes defines an unprecedented form of recent genome evolution and a novel mechanism for the generation of genetic diversity among closely related species.
Keywords: Animals; Base Sequence; Carrier Proteins; Centromere; Chromosome Mapping; Chromosomes, Human, Pair 16; Cosmids; Creatine; Evolution, Molecular; Exons; Hominidae; Humans; Hylobates; Membrane Proteins; Membrane Transport Proteins; Models, Genetic; Molecular Sequence Data; Multigene Family; Proteins; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; X Chromosome

Genomic organization of the mouse double minute 2 gene. - Jones, S N; Ansari-Lari, M A; Hancock, A R; Jones, W J; Richard A Gibbs; Donehower, L A; Bradley, A (Gene, 1996)
Transfection of the mouse double minute 2 (Mdm2) oncogene has been found to induce immortalization of primary cells and to transform cultured cells. Amplification and/or overexpression of human MDM2 has been documented in a large percentage of human cancers. Mouse and human Mdm2 cDNA have been cloned from transformed cells and the cDNA sequence of both genes have been reported previously. In this report, we present the gene structure of mouse Mdm2. Comparison of the coding sequences of the Mdm2 gene with the previously reported cDNA sequence and with Mdm2 sequences obtained from an Mdm2-bearing cosmid clone capable of inducing transformation revealed that the reported cDNA sequence was in error, and that Mdm2-induced transformation of cells does not require an activating mutation in Mdm2. Ligation-anchor PCR analysis of transcripts produced from the P1 and P2 promoters indicates that transcription initiates at sites upstream of those reported previously for both promoters.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Genome; Mice; Molecular Sequence Data; Nuclear Proteins; Promoter Regions, Genetic; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-mdm2; Proto-Oncogenes; Transcription, Genetic

Improved ligation-anchored PCR strategy for identification of 5' ends of transcripts. - Ansari-Lari, M A; Jones, S N; Timms, K M; Richard A Gibbs (Biotechniques, 1996)
Keywords: Alternative Splicing; Animals; Bacteriophage T4; Biotin; DNA Primers; DNA, Complementary; Exons; Humans; Mice; Nuclear Proteins; Polymerase Chain Reaction; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-mdm2; RNA Ligase (ATP); RNA, Messenger; Thiolester Hydrolases; Ubiquitin Thiolesterase

Infection of a yellow baboon with simian immunodeficiency virus from African green monkeys: evidence for cross-species transmission in the wild. - Jin, M J; Rogers, J; Phillips-Conroy, J E; Allan, J S; Desrosiers, R C; Shaw, G M; Sharp, P M; Hahn, B H (J Virol, 1994)
Many African primates are known to be naturally infected with simian immunodeficiency viruses (SIVs), but only a fraction of these viruses has been molecularly characterized. One primate species for which only serological evidence of SIV infection has been reported is the yellow baboon (Papio hamadryas cynocephalus). Two wild-living baboons with strong SIVAGM seroreactivity were previously identified in a Tanzanian national park where baboons and African green monkeys shared the same habitat (T. Kodama, D. P. Silva, M. D. Daniel, J. E. Phillips-Conroy, C. J. Jolly, J. Rogers, and R. C. Desrosiers, AIDS Res. Hum. Retroviruses 5:337-343, 1989). To determine the genetic identity of the viruses infecting these animals, we used PCR to examine SIV sequences directly in uncultured leukocyte DNA. Targeting two different, nonoverlapping genomic regions, we amplified and sequenced a 673-bp gag gene fragment and a 908-bp env gene fragment from one of the two baboons. Phylo-genetic analyses revealed that this baboon was infected with an SIVAGM strain of the vervet subtype. These results provide the first direct evidence for simian-to-simian cross-species transmission of SIV in the wild.
Keywords: Amino Acid Sequence; Animals; Animals, Wild; Base Sequence; Chlorocebus aethiops; DNA Primers; DNA, Viral; Female; Genes, env; Genes, gag; Genome, Viral; HIV Envelope Protein gp120; Infectious Disease Transmission, Vertical; Leukocytes; Membrane Glycoproteins; Molecular Sequence Data; Papio; Phylogeny; Polymerase Chain Reaction; Retroviridae Proteins; Sequence Homology, Amino Acid; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Viral Envelope Proteins

Termination of DNA synthesis by novel 3'-modified-deoxyribonucleoside 5'-triphosphates. - Metzker, M L; Raghavachari, R; Stephen Richards; Jacutin, S E; Civitello, A; Burgess, K; Richard A Gibbs (Nucleic Acids Res, 1994)
Eight 3'-modified-dNTPs were synthesized and tested in two different DNA template assays for incorporation activity. From this enzymatic screen, two 3'-O-methyl-dNTPs were shown to terminate DNA syntheses mediated by a number of polymerases and may be used as alternative terminators in Sanger sequencing. 3'-O-(2-Nitrobenzyl)-dATP is a UV sensitive nucleotide and was shown to be incorporated by several thermostable DNA polymerases. Base specific termination and efficient photolytic removal of the 3'-protecting group was demonstrated. Following deprotection, DNA synthesis was reinitiated by the incorporation of natural nucleotides into DNA. The identification of this labile terminator and the demonstration of a one cycle stop-start DNA synthesis are initial steps in the development of a novel sequencing strategy.
Keywords: Base Sequence; Chromatography, High Pressure Liquid; Deoxyribonucleotides; DNA; DNA-Directed DNA Polymerase; Molecular Sequence Data; Molecular Structure; Templates, Genetic

Identification of a 2 base pair nonsense mutation causing a cryptic splice site in a DMD patient. - Winnard, A V; Jia-Hsu, Y; Richard A Gibbs; Mendell, J R; Burghes, A H (Hum Mol Genet, 1992)
Keywords: Amino Acid Sequence; Base Sequence; DNA; Female; Humans; Molecular Sequence Data; Muscular Dystrophies; Mutation; Polymerase Chain Reaction; RNA Splicing; RNA, Messenger

Transient alterations in the expression of protease and extracellular matrix genes during metastatic lung colonization by H-ras-transformed 10T1/2 fibroblasts. - Marie-Claude Gingras; Jarolim, L; Finch, J; Bowden, G T; Wright, J A; Greenberg, A H (Cancer Res, 1990)
It has been proposed that tumor progression is a selective process and that only a minority of tumor cells survive this selection because they possess the phenotypic traits necessary for metastasis and organ colonization. Both proteases and extracellular matrix proteins have been implicated in invasion and metastasis formation. To examine the nature of the selection process, we transformed 10T1/2 fibroblasts with T24 H-ras and the neoR gene and selected a clonal line expressing the mutant ras gene. After i.v. injection of this line into syngeneic C3H/HeN mice, tumor cells were recovered from lungs by enzymatic treatment and selective outgrowth in G418. Less than one of 10(3) cells survived in the lung 30 min after inoculation, and these exhibited a unique phenotype. This was characterized by a propensity to lodge in the lung on reinjection; markedly enhanced mRNA levels of procollagen alpha 2(I), procollagen alpha 1(III), and fibronectin; and decreased levels of laminin, major excreted protein (procathepsin L), transin, and H-ras. Between 1 and 9 days after tumor injection, the phenotype of the cells surviving in the lung changed dramatically and exhibited a pattern of gene expression with increased protease and low matrix protein mRNA levels. This coincided with a 26-fold increase in the ability to colonize lungs on i.v. injection. Both the phenotype characterized by its propensity to arrest in the lung and that showing enhanced metastatic ability were unstable on prolonged in vitro culture. We hypothesize that two selection events have occurred. The first is for lung arrest and implantation of variants of the injected tumor with high matrix protein and low protease levels. A second selection then occurs for tumor cells that carry a favorable phenotype for invasion and proliferation which is associated with low matrix protein and high protease gene expression. These two phenotypes are represented within a clonal population of recently transformed tumor cells.
Keywords: Animals; Cell Line; Cell Transformation, Neoplastic; Endopeptidases; Extracellular Matrix; Fibrosarcoma; Gene Expression Regulation, Neoplastic; Genes, ras; Lung Neoplasms; Mice; Neoplasm Metastasis; Phenotype; Time Factors; Transfection

Natural killer cell regulation of implantation and early lung growth of H-ras-transformed 10T1/2 fibroblasts in mice. - Greenberg, A H; Egan, S E; Jarolim, L; Marie-Claude Gingras; Wright, J A (Cancer Res, 1987)
We examined the relative role of the natural killer (NK) cell and H-ras gene in controlling metastasis formation using a novel assay for quantitating viable tumor cells entering and surviving in the lung for up to 13 days following i.v. tumor inoculation. This assay utilized the resistance to G418 sulfate conferred by transfection of the neoR gene into 10T1/2 fibroblasts along with activated H-ras. We had previously shown that the metastatic efficiency of T-24-H-ras-transformed 10T1/2 fibroblasts correlated with H-ras expression at the RNA level. In this paper we show that the NK cell could recognize H-ras-transformed fibroblasts in vivo and control experimental metastasis formation using NK-suppressed and -activated syngeneic C3H recipients. Evaluation of NK sensitivity in vitro of individual lines did not predict metastatic ability. However, NK susceptibility in vitro did inversely correlate with the ability of tumor cells to arrest and survive in the lung for the first 48 h after i.v. inoculation. Although the level of H-ras RNA correlated with the ultimate metastatic potential, it did not correlate with the initial rate of tumor cell pulmonary retention or clearing. Over the next 10 to 12 days, however, we detected a preferential survival and outgrowth of high H-ras-expressing variants, which correlated well with the ultimate metastatic ability but not NK susceptibility. These observations argue that the NK cell has its major effect early in the course of the disease, while subsequent tumor growth occurs preferentially in high H-ras-expressing cell lines.
Keywords: Animals; Fibroblasts; Killer Cells, Natural; Lung Neoplasms; Mice; Mice, Inbred C3H; Neoplasm Metastasis; Oncogenes; Transfection